[2,2]Paracyclophane-Based π-Conjugated Molecular Wires Reveal Molecular-Junction Behavior - Molina-Ontoria, Agustin; Wielopolski, Mateusz; Gebhardt, Julian; Gouloumis, Andreas; Clark, Timothy; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2011)
The electronic coupling as well as the attenuation factor ( extgreekb), which depends primarily on the nature of the molecular bridge and is used as a benchmark to test the molecular wire behavior, have been determined in a systematic study carried out on a series of ZnP/C60 conjugates connected through a [2,2′]paracyclophane-oligophenylenevinylene (pCp-oPPV). The convergent synthesis involves a series of Horner-Emmons olefination reactions or double palladium-catalized Heck-type reactions. ZnP-pCp-C60 conjugates were finally obtained by the 1,3-dipolar cycloaddition reaction of the in situ-generated azomethyne ylide containing the ZnP-pCp moiety to the [60]fullerene using Prato conditions. Experimental (UV-vis, fluorescence, transient absorption spectroscopy, and solution electrochemistry) and theoretical studies revealed that the pCps act as molecular junctions. If hole transfer is assumed to be the dominant charge transfer (CT) mechanism, CT is facilitated in one direction (from C60 to ZnP via pCp) but disfavored in the other direction (from ZnP to C60 via pCp).
EAM Import::2019-03-13

25th Anniversary article: 25 years of fullerene research in electron transfer chemistry - Kirner, Sabrina; Sekita, Michael; Guldi, Dirk Michael (Advanced Materials, 2014)
The past 25 years have served as a test bed for exploring the chemistry and physics, in general, and the electron transfer chemistry, in particular, of low-dimensional carbon. Nevertheless, the new realm started with the advent of fullerenes, followed in chronological order by carbon nanotubes, and, more recently, by graphene. The major thrust of this Review article is to historically recap the versatility of fullerenes regarding the design, the synthesis, and the tests as an electroactive building block in photosynthetic reaction mimics, photovoltaics, and catalysis. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

[2]Catenanes decorated with porphyrin and [60]fullerene groups: Design, convergent synthesis, and photoinduced processes - Megiatto, Jackson D.; Schuster, David I.; Abwandner, Silke; De Miguel Rojas, Gustavo; Guldi, Dirk Michael (Journal of the American Chemical Society, 2010)
A new class of [2]catenanes containing zinc(II)-porphyrin (ZnP) and/or [60]fullerene (C) as appended groups has been prepared. A complete description of the convergent synthetic approach based on Cu(I) template methodology and "click" 1, 3-dipolar cycloaddition chemistry is described. This new electron donor-acceptor catenane family has been subjected to extensive spectroscopic, computational, electro-chemical and photophysical studies. H NMR spectroscopy and computational analysis have revealed that the ZnP-C-[2]catenane adopts an extended conformation with the chromophores as far as possible from each other. A detailed photophysical investigation has revealed that upon irradiation the ZnP singlet excited state initially transfers energy to the (phenanthroline)-Cu(I) complex core, producing a metal-to-ligand charge transfer (MLCT) excited state, which in tum transfers an electron to the C group, generating the ZnP-[Cu(phen)]-C charge-separated state. A further charge shift from the [Cu(phen) ] complex to the ZnP subunit, competitive with decay to the ground state, leads to the isoenergetic long distance ZnP -[Cu(phen)-C charge-separated radical pair state, which slowly decays back to the ground state on the microsecond time scale. The slow rate of back-electron transfer indicates that in this interlocked system, as in previously studied covalently linked ZnP-C hybrid materials, this process occurs in the Marcus-inverted region. © 2010 American Chemical Society.

A carbon-carbon hybrid - immobilizing carbon nanodots onto carbon nanotubes - Strauß, Volker; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael (Chemical Science, 2015)
The thrust of this work is to integrate small and uniformly sized carbon nanodots (CNDs) with single-walled carbon nanotubes (SWCNT) of different diameters as electron donors and electron acceptors, respectively, and to test their synergetic interactions in terms of optoelectronic devices. CNDs (denoted pCNDs, where p indicates pressure) were prepared by pressure-controlled microwave decomposition of citric acid and urea. pCNDs were immobilized on single-walled carbon nanotubes by wrapping the latter with poly(4-vinylbenzyl trimethylamine) (PVBTA), which features positively charged ammonium groups in the backbone. Negatively charged surface groups on the CNDs lead to attractive electrostatic interactions. Ground state interactions between the CNDs and SWCNTs were confirmed by a full-fledged photophysical investigation based on steady-state and time-resolved techniques. As a complement, charge injection into the SWCNTs upon photoexcitation was investigated by ultra-short time-resolved spectroscopy.

Accessing Photoredox Transformations with an Iron(III) Photosensitizer and Green Light - Aydogan, Akin; Bangle, Rachel E.; Cadranel, Alejandro; Turlington, Michael D.; Conroy, Daniel T.; Cauët, Emilie; Singleton, Michael L.; Meyer, Gerald J.; Sampaio, Renato N.; Elias, Benjamin; Troian-Gautier, Ludovic (Journal of the American Chemical Society, 2021)
Efficient excited-state electron transfer between an iron(III) photosensitizer and organic electron donors was realized with green light irradiation. This advance was enabled by the use of the previously reported iron photosensitizer, [Fe(phtmeimb)2]+ (phtmeimb = phenyl[tris(3-methyl-imidazolin-2-ylidene)]borate, that exhibited long-lived and luminescent ligand-to-metal charge-transfer (LMCT) excited states. A benchmark dehalogenation reaction was investigated with yields that exceed 90% and an enhanced stability relative to the prototypical photosensitizer [Ru(bpy)3]2+. The initial catalytic step is electron transfer from an amine to the photoexcited iron sensitizer, which is shown to occur with a large cage-escape yield. For LMCT excited states, this reductive electron transfer is vectorial and may be a general advantage of Fe(III) photosensitizers. In-depth time-resolved spectroscopic methods, including transient absorption characterization from the ultraviolet to the infrared regions, provided a quantitative description of the catalytic mechanism with associated rate constants and yields.
CRIS-Team Scopus Importer:2021-10-08

A charge-transfer challenge: Combining fullerenes and metalloporphyrins in aqueous environments - Krokos, Evangelos; Spänig, Fabian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2012)
A series of truly water-soluble C60/porphyrin electron donor-acceptor conjugates has been synthesized to serve as powerful mimics of photosynthetic reaction centers. To this end, the overall water-solubility of the conjugates was achieved by adding hydrophilic dendrimers of different generations to the porphyrin moiety. An important variable is the metal center of the porphyrin; we examined zinc(II), copper(II), cobalt(II), nickel(II), iron- (III), and manganese (III). The first insights into electronic communication between the electron donors and the electron acceptors came from electrochemical assays, which clearly indicate that the redox processes centered either on C60 or the porphyrins are mutually affected. Absorption measurements, however, revealed that the electronic communication in terms of, for example, charge-transfer features, remains spectroscopically invisible. The polar environment that water provides is likely to be a cause of the lack of detection. Despite this, transient absorption measurements confirm that intramolecular charge separation processes in the excited state lead to rapid deactivation of the excited states and, in turn, afford the formation of radical ion pair states in all of the investigated cases. Most importantly, the lifetimes of the radical ion pairs were found to depend strongly on several aspects. The nature of the coordinated metal center and the type of dendrimer have a profound impact on the lifetime. It has been revealed that the nature/electronic configuration of the metal centers is decisive in powering a charge recombination that either reinstates the ground state or any given multiplet excited state. Conversely, the equilibrium of two opposing forces in the dendrimers, that is, the interactions between their hydrophilic regions and the solvent and the electronic communication between their hydrophobic regions and the porphyrin and/or fullerene, is the key to tuning the lifetimes. © 2012 Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.

Achieving High Fill Factor via Increasing Interfacial Disorder to Inhibit Bimolecular Recombination for Efficient Organic Solar Cells - He, Dan; Xie, Linwei; Bai, Yahui; Zhang, Huotian; Liu, Liping; Kong, Jingyao; Chai, Yongqiang; Li, Xiaojun; Wang, Mengni; Zhang, Yajie; Zhang, Jianqi; Li, Yongfang; et al. (Angewandte Chemie International Edition, 2025)
The inferior fill factor (FF) is one of main reasons impeding further improvement of power conversion efficiencies (PCEs) in organic solar cells (OSCs). But no theoretical framework for high FFs has been established yet. Herein, an efficient strategy is developed to enhance FFs via introducing a small molecule, CNDT, into active layer to increase electron donor/acceptor interface disorder, raise energy barrier for charge back transfer, and thus reduce bimolecular recombination rate constant (krec). CNDTs tend to distribute over donor/acceptor interfaces and disturb molecular stacking of Y6 to deliver more disordered donor/acceptor interfaces but higher crystal quality in the D18:Y6+ blend film, compared to D18:Y6. Altogether, in the D18:Y6+ blend film, a higher energy of charge transfer state magnifies energy barrier for charge recombination to decrease charge recombination rate/ratio and reduce krec, inhibiting bimolecular recombination in devices. Therefore, FFs of OSCs are improved from 75.78% (D18:Y6) to 81.13% (D18:Y6+), yielding a higher PCE of 19.45%. Moreover, D18:L8-BO+ based OSCs feature FFs over 83%, a record for OSCs so far. PCE increases subsequently to 19.80%. It demonstrates that increasing interface disorder without sacrificing crystal quality enhances energy barrier of charge recombination and inhibits bimolecular recombination to efficiently improve FFs for higher PCEs.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Charge carrier recombination; Donor/acceptor interfaces; Fill factors; Organic solar cells

Acriflavine-Functionalized Silica@Manganese Ferrite Nanostructures for Synergistic Radiation and Hypoxia Therapies - Eckenberger, Elisabeth; Raczka, Theodor; Neuhuber, Winfried; Distel, Luitpold; Klein, Stefanie (ACS Applied Bio Materials, 2023)
Mesoporous and nonmesoporous SiO2@MnFe2O4 nanostructures were loaded with the hypoxia-inducible factor-1 inhibitor acriflavine for combined radiation and hypoxia therapies. The X-ray irradiation of the drug-loaded nanostructures not only triggered the release of the acriflavine inside the cells but also initiated an energy transfer from the nanostructures to surface-adsorbed oxygen to generate singlet oxygen. While the drug-loaded mesoporous nanostructures showed an initial drug release before the irradiation, the drug was primarily released upon X-ray radiation in the case of the nonmesoporous nanostructures. However, the drug loading capacity was less efficient for the nonmesoporous nanostructures. Both drug-loaded nanostructures proved to be very efficient in irradiated MCF-7 multicellular tumor spheroids. The damage of these nanostructures toward the nontumorigenic MCF-10A multicellular spheroids was very limited because of the small number of nanostructures that entered the MCF-10A spheroids, while similar concentrations of acriflavine without nanostructures were toxic for the MCF-10A spheroids.
CRIS-Team Scopus Importer:2023-09-29
Keywords: drug delivery; hypoxia; magnetic mesoporous silica@MnFe2O4 nanoparticles; magnetic silica@MnFe2O4 nanoparticle acriflavine; multicellular tumor spheroids; radiation therapy

Activating multistep charge-transfer processes in fullerene- subphthalocyanine-ferrocene molecular hybrids as a function of π-π Orbital overlap - Gonzalez-Rodriguez, David; Carbonell, Esther; De Miguel Rojas, Gustavo; Atienza Castellanos, Carmen Maria; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
We have synthesized two different fullerene-subphthalocyanine-ferrocene conjugates. The molecules were designed so that the ferrocene unit is linked at the subphthalocyanine axial position through a phenoxy spacer while the C is rigidly held close to the concave face of the macrocycle via a 3-fold C -symmetrical anchoring. The Bingel trisaddition reaction leading to the final products proceeded with very high regioselectivities and full diastereoselectivity. The only difference between both systems is the length of the triple tether employed, which finely regulates the regioselectivity of the trisaddition reaction and the distance between the subphthalocyanine and the C complementary π-π surfaces. Thus, when the tether is connected to the subphthalocyanine through a direct C-C bond, a short π-π distance of 3.25-3.30 Å was calculated. In contrast, when it is connected through a slightly longer C-O-C bond, the distance increases to 3.5-3.6 Å. This π-π distance has a strong influence on the ground-state electronic interactions between the subphthalocyanine and the C , as determined from electronic absorption and cyclic voltammetry measurements. In addition, fluorescence and time-resolved transient absorption experiments demonstrated that different mechanisms operate in the two systems after photoexcitation. Despite the similar HOMO-LUMO gaps, only when the two complementary π-π surfaces of the subphthalocyanine and the C are held at a close distance, therefore showing a high degree of orbital overlap, is a multistep electron transfer process triggered, ultimately leading to the long-lived, spatially separated C radical anion and ferrocenium radical cation pair. A full account of the synthesis, characterization, and studies of the ground- and excited-state electronic interactions occurring in these conjugates, as well as in their reference C -subphthalocyanine and subphthalocyanine- ferrocene dyads, is presented in this article. © 2010 American Chemical Society.

A digital twin to overcome long-time challenges in photovoltaics - Lüer, Larry; Peters, Ian Marius; Smith, Ana-Suncana; Dorschky, Eva; Eskofier, Björn; Liers-Bergmann, Frauke; Franke, Jörg; Sjarov, Martin; Brossog, Matthias; Guldi, Dirk Michael; Maier, Andreas; Brabec, Christoph (Joule, 2024)
The recent successes of emerging photovoltaics (PVs) are largely driven by innovations in material science. However, closing the gap to commercialization still requires significant progress to match contradicting requirements, such as performance, longevity, and recyclability. In this perspective, we envision the layout of a digital twin for PV materials able to provide the necessary acceleration of innovation. The layout combines machine learning approaches, as performed in materials acceleration platforms (MAPs), with physical models and digital twin concepts used in engineering. This layout will allow the use of high-throughput (HT) experimentation in MAPs to improve the parametrization of quantum chemical and solid-state models. In turn, the improved and generalized models can be used to obtain the crucial structural parameters. HT experimentation will thus yield a detailed understanding of generally valid structure-property relationships. We discuss the current state of the enabling technologies, namely fast scale-bridging surrogate models and large-scale optimization under uncertainty, and identify promising approaches for further development.<br
Keywords: digital twin; emerging photovoltaics; artificial intelligence; multi-scale simulations; optimization; high-throughput methods; materials acceleration platforms

Adsorption of cobalt (II) octaethyIporphyrin and 2H-octaethylporphyrin on Ag(111): New insight into the surface coordinative bond - Bai, Yun; Buchner, Florian; Kellner, Ina; Schmid, Martin; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (New Journal of Physics, 2009)
The adsorption of cobalt (II) octaethylporphyrin (CoOEP) and 2H-octaethylporphyrin (2HOEP) on Ag(111) was investigated with scanning tunneling microscopy (STM) and photoelectron spectroscopy (XPS/UPS), in order to achieve a detailed mechanistic understanding of the surface chemical bond of coordinated metal ions. Previous studies of related systems, especially cobalt (II) tetraphenylporphyrin (CoTPP) on Ag(111), have revealed adsorptioninduced changes of the oxidation state of the Co ion and the appearance of a new valence state. These effects were attributed to a covalent interaction of the Co ion with the silver substrate. However, recent studies show that the porphyrin ligand of adsorbed CoTPP undergoes a pronounced saddle-shape distortion, which could alter the electronic structure and thus provide an alternative explanation for the new valence state previously attributed to the formation of a surface coordinative bond. With the octaethylporphyrins investigated here, which were found to adsorb in a flat, undistorted conformation on Ag(111), the effects of geometric distortion can be separated from those of the electronic interaction with the substrate. The CoOEP monolayer gives rise to an adsorption-induced shift of the Co 2p signal (-1.9 eV relative to the multilayer), a new valence state at 0.6 eV below the Fermi energy, and a work-function shift of -0.84eV (2HOEP: -0.44eV) relative to the clean surface. Comparison with data for the distorted CoTPP confirms the existence of a covalent ion-surface interaction that is insensitive to the conformation of the ligand. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.

A Facile One-Pot Synthesis of Water-Soluble, Patchy Fe3O4-Au Nanoparticles for Application in Radiation Therapy - Klein, Stefanie; Hubner, Jakob; Menter, Christina; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Applied Sciences, 2019)
A facile one-pot synthesis route for the preparation of water-soluble, biocompatible patchy Fe3O4-Au nanoparticles (Fe3O4-Au pNPs) was developed. Biocompatibility was attained through surface functionalization with 1-methyl-3-(dodecylphosphonic acid) imidazolium bromide. The morphology, composition, crystal structure and magnetic properties of the Fe3O4-Au pNPs were investigated by conducting experiments with transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction and superconducting quantum interference device, respectively. Internalization of the Fe3O4-Au pNPs by MCF-7 cells occurred via endocytosis. The performance of the Fe3O4-Au pNPs as X-ray radiosensitizer in tumor cells was compared with that of gold nanocluster and Fe3O4 NPs. For this reason, MCF-7, A549 and MCF-10A cells were loaded with the respective kind of nanoparticles and treated with X-rays at doses of 1, 2 or 3 Gy. The nanoparticle-induced changes of the concentration of the reactive oxygen species (ROS) were detected using specific assays, and the cell survival under X-ray exposure was assessed employing the clonogenic assay. In comparison with the gold nanocluster and Fe3O4 NPs, the Fe3O4-Au pNPs exhibited the highest catalytic capacity for ROS generation in MCF-7 and A549 cells, whereas in the X-ray-induced ROS formation in healthy MCF-10A cells was hardly enhanced by the Fe3O4 NPs and Fe3O4-Au pNPs. Moreover, the excellent performance of Fe3O4-Au pNPs as X-ray radiosensitizers was verified by the quickly decaying radiation dose survival curve of the nanoparticle-loaded MCF-7 and A549 cells and corroborated by the small values of the associated dose-modifying factors.
CRIS-Team WoS Importer:2020-02-21

A Family of Superhelicenes: Easily Tunable, Chiral Nanographenes by Merging Helicity with Planar pi Systems - Reger, David; Haines, Philipp; Amsharov, Konstantin; Schmidt, Julia A.; Ullrich, Tobias; Bönisch, Simon; Hampel, Frank; Görling, Andreas; Nelson, Jenny; Jelfs, Kim E.; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2021)
We designed a straightforward synthetic route towards a full-fledged family of pi-extended helicenes: superhelicenes. They have two hexa-peri-hexabenzocoronenes (HBCs) in common that are connected via a central five-membered ring. By means of structurally altering this 5-membered ring, we realized a versatile library of molecular building blocks. Not only the superhelicene structure, but also their features are tuned with ease. In-depth physico-chemical characterizations served as a proof of concept thereof. The superhelicene enantiomers were separated, their circular dichroism was measured in preliminary studies and concluded with an enantiomeric assignment. Our work was rounded-off by crystal structure analyses. Mixed stacks of M- and P-isomers led to twisted molecular wires. Using such stacks, charge-carrier mobilities were calculated, giving reason to expect outstanding hole transporting properties.
CRIS-Team WoS Importer:2021-07-23

A Fluorescence-Detected Coordination-Induced Spin State Switch - Kurz, Hannah; Schoetz, Konstantin; Papadopoulos, Ilias; Heinemann, Frank Wilhelm; Maid, Harald; Guldi, Dirk Michael; Koehler, Anna; Hoerner, Gerald; Weber, Birgit (Journal of the American Chemical Society, 2021)
The response of the spin state to in situ variation of the coordination number (CISSS) is a promising and viable approach to smart sensor materials, yet it suffers to date from insensitive detection. Herein, we present the synthetic access to a family of planar nickel(II) complexes, whose CISSS is sensitively followed by means of fluorescence detection. For this purpose, nickel(II) complexes with four phenazine-based Schiff base-like ligands were synthesized and characterized through solution-phase spectroscopy (NMR and UV-vis), solid-state structure analysis (single-crystal XRD), and extended theoretical modeling. All of them reveal CISSS in solution through axial ligating a range of N- and O-donors. CISSS correlates nicely with the basicity of the axial ligand and the substitution-dependent acidity of the nickel(II) coordination site. Remarkably, three out of the four nickel(II) complexes are fluorescent in noncoordinating solvents but are fluorescence-silent in the presence of axial ligands such as pyridine. As these complexes are rare examples of fluorescent nickel(II) complexes, the photophysical properties with a coordination number of 4 were studied in detail, including temperature-dependent lifetime and quantum yield determinations. Most importantly, fluorescence quenching upon adding axial ligands allows a "black or white", i.e. digital, sensoring of spin state alternation. Our studies of fluorescence-detected CISSS (FD-CISSS) revealed that absorption-based CISSS and FD-CISSS are super proportional with respect to the pyridine concentration: FD-CISSS features a higher sensitivity. Overall, our findings indicate a favored ligation of these nickel(II) complexes in the excited state in comparison to the ground state.
CRIS-Team WoS Importer:2021-03-26

A fluorescent molecular rotor showing vapochromism, aggregation-induced emission, and environmental sensing in living cells - König, Matthias; Storti, Barbara; Bizzarri, Ranieri; Guldi, Dirk Michael; Brancato, Giuseppe; Bottari, Giovanni (Journal of Materials Chemistry C, 2016)
Among the plethora of recently proposed molecular sensors, those belonging to the class of fluorescent molecular rotors (FMRs) have attracted much attention owing to their peculiar photophysical properties that enable an unprecedented sensitivity towards environmental microviscosity. The usual FMR synthetic design prescribes chromophores characterized by an intramolecular rotation between two well-defined excited states, a locally excited state and a twisted internal charge transfer (TICT) state, where the sensing capabilities arise from a dual competition of the corresponding radiative/non-radiative decay processes. However, we have recently demonstrated a different modus operandi of a new subclass of solvatochromic FMRs, which exploit a solvent-independent, barrier-free intramolecular rotation of the excited dye. The rotational dynamics is modulated by local viscosity and, in turn, manifested through a variable spectral signal. In order to translate the same rotational mechanism in a versatile sensor of polarity and viscosity, we designed and thoroughly characterized a novel FMR, namely 4-(triphenylamino)-phthalonitrile (TPAP). Remarkably, in addition to a high sensitivity versus solvent polarity and viscosity, TPAP is also able to form stable fluorescent nanoparticles characterized by aggregation-induced emission, via a simple sonochemical treatment. Such peculiar features are tested in different applications aiming at illustrating its capability to report on solvatochromic and vapochromic effects, as well as to provide detailed intracellular information through bioimaging studies.
CRIS-Team Scopus Importer:2023-03-07

A Fully Conjugated TTF-π-TCAQ System: Synthesis, Structure, and Electronic Properties - Santos, Jose; Illescas, Beatriz M.; Martin, Nazario; Adrio, Javier; Carretero, Juan C.; Viruela, Rafael; Orti, Enrique; Spänig, Fabian; Guldi, Dirk Michael (Chemistry - A European Journal, 2011)
The synthesis of the first fully conjugated tetrathiafulvalene–tetracyano-p-quinodimethane ((TTF)–TCNQ)-type system has been carried out by means of a Julia–Kocienski olefination reaction. In particular, a tetracyanoanthraquinodimethane (TCAQ) formyl derivative and two new sulfonylmethyl-exTTFs (exTTF=2-[9-(1,3-dithiol-2-ylidene)anthracen-10(9H)-ylidene]-1,3-dithiole)—prepared as new building blocks—were linked. A variety of experimental conditions reveal that the use of sodium hexamethyldisilazane (NaHMDS) as base in THF afforded the E olefins with excellent stereoselectivity. Theoretical calculations at the B3LYP/6-31G** level point to highly distorted exTTF and TCAQ that form an almost planar stilbene unit between them. Although calculations predicted appreciable electronic communication between the donor and the acceptor, cyclic voltammetric studies did not substantiate this effect. It was only in photophysical assays that the electronic communication emerged in the form of a charge-transfer (CT) absorption and emission. Once photoexcited (i.e., the locally excited state or excited charge-transfer state), an ultrafast, subpicosecond charge separation leads to a radical ion pair state in which the spectroscopic features of the radical cation of exTTF as well as the radical anion of TCAQ are discernable. The radical ion pair is metastable and undergoes a fast ((1.0±0.2)ps) charge recombination to reconstitute the electronic ground state. Such ultrafast charge separation and recombination processes come as a consequence of the very short vinyl linkage between the two electroactive units.
EAM Import::2019-03-13

A Functional Hexaphenylbenzene Library Comprising of One, Three, and Six Peripheral Rylene-Diimide Substituents - Dusold, Carolin; Platzer, Benedikt; Haines, Philipp; Reger, David; Jux, Norbert; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Synthesis and characterization of a series of rylene-diimide substituted hexaphenylbenzenes (HPBs) is presented. The direct connection of the rylene-diimide units to the HPBs via the imide-N-position without any linkers as well as the use of naphthalene-diimides (NDIs) next to perylene-diimides (PDIs) is unprecedented. While mono-substituted products were obtained by imidization reactions with amino-HPB and the respective rylene-monoimides, key step for the formation of tri- and hexa-substituted HPBs is the Co-catalysed cyclotrimerization. Particular emphasis for physic-chemical characterization was on to the number of NDIs/PDIs per HPB and the overall substitution patterns. Lastly, Scholl oxidation conditions were applied to all HPB systems to generate the corresponding hexa-peri-hexabenzocoronenes (HBCs). Importantly, the efficiency of the transformation strongly depends on the number of NDIs/PDIs. While three rylene-diimide units already hinder the Scholl reaction, the successful synthesis of mono-substituted HBCs is possible.
CRIS-Team WoS Importer:2021-01-15

A Geometrically Well-Defined and Systematically Tunable Experimental Model to Transition from Planar to Mesoporous Perovskite Solar Cells - Döhler, Dirk; Büttner, Pascal; Scheler, Florian; Thiel, Dominik; Puscher, Bianka; Bochmann, Sebastian; Mitrovic, Julian; Boix, Pablo P.; Guldi, Dirk Michael; Minguez-Bacho, Ignacio; Bachmann, Julien (ACS Applied Energy Materials, 2022)
A series of perovskite solar cells with systematically varying surface area of the interface between n-type electron conducting layer (TiO2) and perovskite are prepared by using an ordered array of straight, cylindrical nanopores generated by anodizing an aluminum layer evaporated onto a transparent conducting electrode. A series of samples with pore length varied from 100 to 500 nm are compared to each other and complemented by a classical planar cell and a mesoporous counterpart. All samples are characterized in terms of morphology, chemistry, optical properties, and performance. All samples absorb light to the same degree, and the increased interface area does not generate enhanced recombination. However, the short circuit current density increases monotonically with the specific surface area, indicating improved charge extraction efficiency. The importance of the slow interfacial rearrangement of ions associated with planar perovskite cells is shown to decrease in a systematic manner as the interfacial surface area increases. The results demonstrate that planar and mesoporous cells obey to the same physical principles and differ from each other quantitatively, not qualitatively. Additionally, the study shows that a significantly lower TiO2 surface area compared to mesoporous TiO(2 )is needed for an equal charge extraction.
CRIS-Team WoS Importer:2022-10-14

Aggregation of a Crown Ether Decorated Zinc-Phthalocyanine by Collision-Induced Desolvation of Electrospray Droplets. - Kellner, Ina; Hahn, Uwe; Dürr, Maximilian; Torres, Tomas; Ivanovic-Burmazovic, Ivana; Drewello, Thomas (Journal of Physical Chemistry A, 2015)
The aggregation of phthalocyanines is well-known in solution but has never before been studied in the gas phase. We investigated the tetra-[18]crown-6 ether functionalized zinc-phthalocyanine (ZnPcTetCr, M) with electrospray ionization mass spectrometry (ESI-MS) in the absence of coordinating metal cations. Apart from the molecular ion M(+•), singly and multiply charged aggregates Mn(z(+•)) were observed, bound together by electrostatic interactions, without alkali metal cations inside the crown ethers. Collision-induced dissociation (CID) experiments indicate that these clusters consist of stacked neutral M and radical cations M(+•). After the oxidation of individual molecules at the electrospray needle, the aggregation occurs during desolvation of the charged droplets created in the source. Complete evaporation of the solvent and detection of the aggregates was found to require an additional acceleration of the droplets in the transfer region of the instrument, the resulting collisions with neutral gas assisting the desolvation process.

Aggregation promotes charge separation in fullerene-indacenodithiophene dyad - Wang, Chong; Wu, Bo; Li, Yang; Zhou, Shen; Wu, Conghui; Dong, Tianyang; Jiang, Ying; Hua, Zihui; Song, Yupeng; Wen, Wei; Tian, Jianxin; Chai, Yongqiang; et al. (Nature Communications, 2024)
Fast photoinduced charge separation (CS) and long-lived charge-separated state (CSS) in small-molecules facilitate light-energy conversion, while simultaneous attainment of both remains challenging. Here we accomplish this through aggregation based on fullerene-indacenodithiophene dyads. Transient absorption spectroscopy reveals that, compared to solution, the CS time in aggregates is accelerated from 41.5 ps to 0.4 ps, and the CSS lifetime is prolonged from 311.4 ps to 40 μs, indicating that aggregation concomitantly promotes fast CS and long-lived CSS. Fast CS arises from the hot charge-transfer states dissociation, opening up additional resonant channels to free carriers (FCs); subsequently, charge recombination into intramolecular triplet CSS becomes favorable mediated by spin-uncorrelated FCs. Different from fullerene/indacenodithiophene blends, the unique CS mechanism in dyad aggregates reduces the long-lived CSS dependence on molecular order, resulting in a CSS lifetime 200 times longer than blends. This endows the dyad aggregates to exhibit both photoelectronic switch properties and superior photocatalytic capabilities.
CRIS-Team Scopus Importer:2024-07-19

A Hole Delocalization Strategy: Photoinduced Mixed-Valence MLCT States Featuring Extended Lifetimes - Aramburu-Troselj, Bruno M.; Oviedo, Paola S.; Pieslinger, German E.; Hodak, Jose H.; Baraldo, Luis M.; Guldi, Dirk Michael; Cadranel, Alejandro (Inorganic Chemistry, 2019)
Bimetallic trans-[RuII(tpm)(bpy)(μNC)RuII(L)4(CN)]2+, where bpy is 2,2′-bipyridine, tpm is tris(1-pyrazolyl)methane and L = 4-methoxypyridine (MeOpy) or pyridine (py), was examined using ultrafast vis-NIR transient absorption spectroscopy. Of great relevance are the longest-lived excited states in the form of strongly coupled photoinduced mixed-valence systems, which exhibit intense photoinduced absorptions in the NIR and are freely tunable by the judicious choice of the coordination spheres of the metallic ions. Using the latter strategy, we succeeded in tailoring the excited state lifetimes of bimetallic complexes and, in turn, achieving significantly longer values relative to related monometallic complexes. Notable is the success in extending the lifetimes, when considering the higher density of vibrational states, as they are expected to facilitate nonradiative ground-state recovery.
CRIS-Team Scopus Importer:2019-09-17

Aligning Single-Walled Carbon Nanotubes By Means Of Langmuir-Blodgett Film Deposition: Optical, Morphological, and Photo-electrochemical Studies - Giancane, Gabriele; Ruland, Andres; Sgobba, Vito; Manno, Daniela; Serra, Antonio; Farinola, Gianluca M.; Omar, Omar Hassan; Guldi, Dirk Michael; Valli, Ludovico (Advanced Functional Materials, 2010)
An alkoxy-substituted poly(phenylene thiophene) is used in order to suspend single-walled carbon nanotubes in an organic solvent. The suspension is spread on the air–water interface of a Langmuir trough and the floating film is characterized by means of Brewster angle microscopy and UV-visible reflection spectroscopy and the compression isotherm is recorded. The polymer/carbon-nanotube blend is transferred onto different substrates using the Langmuir–Blodgett technique. AFM measurements indicate the formation of globular structures for the samples transferred at low surface-pressure values and a tubular morphology for high-pressure-deposited samples. AFM analysis is repeated on a sample exposed to soft X-rays for about 5h and a highly organized structure of bundles of carbon nanotubes rises up. Samples with different numbers of layers are transferred onto ITO substrates by means of the Langmuir–Blodgett method and are tested as photocathodes in a photo-electrochemical cell. A Voc of 0.18 V, an Isc of 85.8 mA, FF of 40.0%, and η of (6.23×10−3)% are obtained.

Alkali-Metal-Templated Self-Assembly of Nickel(II) [12-MC-3] Metallacoronates Based on Bis(pyrazol-1-yl)acetato Ligands - Beyer, Andreas; von Gernler, Marc; Pflock, Stephan; Türkoglu, Gazi; Müller, Lisa; Zahl, Achim; Gieb, Klaus; Müller, Paul; Drewello, Thomas; Burzlaff, Nicolai (Chemistry - A European Journal, 2018)
Keywords: Metallacrowns; Nickel; Acetyl acetonate; Template synthesis; Tripodal ligands

Alkalinity Initiated Decomposition of Mediating Imidazolium Ions in High Current Density CO 2 Electrolysis - Neubauer, Sebastian S.; Schmid, Bernhard; Reller, Christian; Guldi, Dirk Michael; Schmid, Guenter (ChemElectroChem, 2017)
Aqueous ionic liquid electrolytes featuring the promising 1,3-dialkyl- and 1,2,3-trialkyl-imidazolium cations are reported in CO2 electrolysis up to 200 mAcm-2. A close-to-application flow cell setup equipped with silver gas diffusion electrode to overcome CO2 mass transport limitations was used. Faraday efficiencies for CO as high as 68% were achieved, while inhibiting the hydrogen evolution reaction. Particular attention is paid to the stability of the ionic liquids, which is determined by 1H NMR spectroscopic measurements. The root cause of decomposition is the formation of hydroxide ions through reduction reactions. A high local pH arises that depends on the current density. The water content is also found to play a key role. An overall mechanism is proposed from analysis of the decomposition products including methylamine, ethylamine, formate, acetate and N1-ethyl-N2-methylethane-1,2-diamine. Methylation of the susceptible C2 position of the imidazolium ring fails to stabilize the system under high conversion rate electrolysis conditions.
EAM Import::2019-03-13

All-Fullerene Electron Donor–Acceptor Conjugates - Izquierdo, Marta; Platzer, Benedikt; Stasyuk, Anton J.; Stasyuk, Olga A.; Voityuk, Alexander A.; Cuesta, Sergio; Solà, Miquel; Guldi, Dirk Michael; Martín, Nazario (Angewandte Chemie International Edition, 2019)
The synthesis and characterization of a covalent all-fullerene C 60 -Lu 3 N@I h -C 80 electron donor–acceptor conjugate has been realized by sequential 1,3-dipolar cycloaddition reactions of azomethine ylides on Lu 3 N@I h -C 80 and C 60 . To the best of our knowledge, this is the first time that two fullerenes behaving as both electron donor (Lu 3 N@I h -C 80 ) and acceptor (C 60 ) are forming an electroactive dumbbell. DFT calculations reveal up to 16 diastereomeric pairs, that is, 8 with syn and 8 with anti orientation, with the anti-RSSS isomer being the most stable. Spectroelectrochemical absorption and femtosecond transient absorption experiments support the notion that a C 60 ⋅− -Lu 3 N@I h -C 80 ⋅+ charge-separated state is formed. Spin conversion from the charge-separated singlet state C 60 ⋅− -Lu 3 N@I h -C 80 ⋅+ into the corresponding triplet state is facilitated by the heavy-atom effect stemming from the Lu 3 N-cluster, which, in turn, slows down the charge recombination by one order of magnitude.
CRIS-Team Scopus Importer:2019-05-24
Keywords: electroactive dyads; excited states; fullerenes; photoinduced electron transfer; stereoisomers⋅

Alteration of the Optoelectronic Properties of CuInS2 Quantum Dots via Colloidal Annealing - Dehm, Katharina; Zanetti, Alberto; Fett, Bastian; Mauritz, Vincent; Hamburger, Robert C.; Langford, Daniel; Guldi, Dirk Michael; Young, Elizabeth R.; Mandel, Karl; Crisp, Ryan (Crystal Growth and Design, 2024)
Colloidal semiconductor quantum dots (QDs) have tunable optoelectronic properties, thereby making them interesting materials for applications involving light-matter interactions. However, crystallographic and surface defects greatly impair their potential performance in devices. Herein, we present a straightforward approach to improve the quality of copper indium disulfide (CuInS2) QDs by adjusting the parameters of the colloidal synthesis. By the introduction of prolonged heating times after the nanocrystal growth has already gone to completion, defect states are partially removed. This “colloidal annealing” for varying time spans (from 5 up to 90 min) with longer annealing times correlating with a decreased ratio of emission from defect states compared to band edge emission, results in enhanced color purity. At shorter annealing times, the defects removed are mainly structural, indicated by the transition from mixed crystal phases to an almost phase-pure material. At longer annealing times, further improvements are linked to surface defect removal. Findings from transient absorption spectroscopy further confirm this trend by revealing a decrease in the intensity of a photoinduced absorption feature associated with sub-band gap states compared to the band edge bleach signal. These findings highlight the applicability of colloidal annealing as a straightforward strategy for direct material optimization during colloidal synthesis.<br

Altering singlet fission pathways in perylene-dimers; perylene-diimide versus perylene-monoimide - Papadopoulos, Ilias; Gutierrez-Moreno, David; Bo, Yifan; Casillas, Ruben; Greißel, Phillip; Clark, Timothy; Fernandez-Lazaro, Fernando; Guldi, Dirk Michael (Nanoscale, 2022)
We used a systematic approach to shed light on the inherent differences in perylenes, namely monoimides versus diimides, including coplanarity and dipole moment, and their impact on singlet fission (SF) by designing, synthesizing, and probing a full fledged series of phenylene- and naphthalene-linked dimers. Next to changing the functionality of the perylene core, we probed the effect of the spacers and their varying degrees of rotational freedom, molecular electrostatic potentials, and intramolecular interactions on the SF-mechanism and -efficiencies. An arsenal of spectroscopic techniques revealed that for perylene-monoimides, a strong charge-transfer mixing with the singlet and triplet excited states restricts SF and yields low triplet quantum yields. This is accompanied by an up-conversion channel that includes geminate triplet-triplet recombination. Using perylene-diimides alters the SF-mechanism by populating a charge-separated-state intermediate, which either favors or shuts-down SF. Napthylene-spacers bring about higher triplet quantum yields and overall better SF-performance for all perylene-monoimides and perylene-diimides. The key to better SF-performance is rotational freedom because it facilitates the overall excited-state polarization and amplifies intramolecular interactions between chromophores.
CRIS-Team WoS Importer:2022-04-08

A metallofullerene electron donor that powers an efficient spin flip in a linear electron donor-acceptor conjugate - Rudolf, Marc; Feng, Lai; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Journal of the American Chemical Society, 2013)
The dream target of artificial photosynthesis is the realization of long-lived radical ion pair states that power catalytic centers and, consequently, the production of solar fuels. Notably, magnetic field effects, especially internal magnetic field effects, are rarely employed in this context. Here, we report on a linear LuN@I-C-PDI electron donor-acceptor conjugate, in which the presence of the LuN cluster exerts an appreciable electron nuclear hyperfine coupling on the charge transfer dynamics. As such, a fairly efficient radical ion pair intersystem crossing converts the initially formed singlet radical ion pair state, [(LuN@I-C)- PDI], to the corresponding triplet radical ion pair state, [(LuN@I-C)- PDI]. Most notably, the radical ion pair state lifetime of the latter is nearly 1000 times longer than that of the former. © 2013 American Chemical Society.

A molecular Ce2@ih-C80 switch-unprecedented oxidative pathway in photoinduced charge transfer reactivity - Guldi, Dirk Michael; Feng, Lai; Radhakrishnan, Shankara Gayathri; Nikawa, Hidefumi; Yamada, Michio; Mizorogi, Naomi; Tsuchiya, Takahiro; Akasaka, Takeshi; Nagase, Shigeru; Angeles Herranz, M.; Martin, Nazario (Journal of the American Chemical Society, 2010)
We report for the first time the versatile Ce@I -C building block toward synthesizing a novel electron donor-acceptor conjugate, Ce@I-C-ZnP (1). A systematic investigation of the charge transfer chemistry documents a reductive charge transfer (i.e., formation of (Ce@I-C )-(ZnP)) in nonpolar media (i.e., toluene/THF), while an oxidative charge transfer (i.e., formation of (Ce@I-C)-(ZnP) ) dominates in polar media (i.e., benzonitrile/DMF). Reduction of the [Ce] cluster, which is highly localized and collinearly arranged with respect to the quaternary bridge carbon, is sufficiently exothermic in all solvents. Notably weak is the electronic coupling between the [Ce] cluster and the electron-donating ZnP. The oxidation of C and the simultaneous reduction of ZnP, on the other hand, necessitate solvent stabilization. In such a case, the strongly exothermic (Ce@I-C) -(ZnP) radical ion pair state formation is compensated within the framework of a nonadiabatic charge transfer by a C /ZnP electronic matrix element, as the sum of good overlap and short distance, that exceeds that for [Ce] /ZnP. © 2010 American Chemical Society.

A Molecular Popeye: Li+@C60 and its Complexes with [n]Cycloparaphenylenes - Freiberger, Markus; Solymosi, Iris; Freiberger, Eva Marie; Hirsch, Andreas; Perez-Ojeda Rodriguez, Maria Eugenia; Drewello, Thomas (Nanoscale, 2023)
In this work, we compare for the first time the stability of [n]cycloparaphenylene ([n]CPP)-based host–guest complexes with Li+@C60 and C60 in the gas and the solution phase. Our gas-phase experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li+@C60. This increased interaction strength is also observed in solution. Isothermal titration calorimetry shows for the formation of [10]CPP⊃Li+@C60 a two orders of magnitude larger association constant than that for the C60 analog. Additionally, an increased binding entropy is observed. This study contributes to a better understanding of host–guest complexes between [n]CPPs and endohedral metallofullerenes at a molecular level, which is the prerequisite for future applications.

Amphiphilic anthanthrene trimers that exfoliate graphite and individualize single wall carbon nanotubes - Münich, Peter Wilhelm; Pfäffli, Matthias; Volland, Michel; Liu, Shi-Xia; Haener, Robert; Guldi, Dirk Michael (Nanoscale, 2020)
A phosphodiester-linked dialkynyl substituted anthanthrene trimer (1) has been designed and synthesized. Its graphene ribbon like structure is expected to facilitate interactions with nanographene (NG) and single wall carbon nanotubes (SWCNT) to yield novel and stable carbon-based nanomaterials. Interactions with trimer 1 lead to exfoliation of NG and to the individualization of SWCNTs. Phosphate groups, in general, and their negative charges, in particular, render the resulting nanomaterials soluble in ethanol, which is ecologically favourable over DMF required for the processing of pristine NG or SWCNTs. The newly formed nanomaterials were probed by complementary spectroscopic and microscopic techniques. Of particular importance were transient absorption and fluorescence excitation measurements, which revealed an efficient energy transfer within the carbon-based nanomaterials.
CRIS-Team Scopus Importer:2020-01-14

Amphiphilic Zinc Porphyrin Single-Walled Carbon Nanotube Hybrids: Efficient Formation and Excited State Charge Transfer Studies - Menon, Arjun; Münich, Peter Wilhelm; Wagner, Pawel; Officer, David L.; Guldi, Dirk Michael (Small, 2021)
Herein, the microscopic and spectroscopic characterization of a novel non-covalent electron donor−acceptor system, in which three different metalloporphyrins (1, 2, and 3) play the dual role of light harvester and electron donor with SWCNTs as electron acceptor, is described. To this end, microscopy, that is, atomic force microscopy (AFM) and transmission electron microscopy (TEM) corroborate the formation of 1-SWCNT, 2-SWCNT, and 3-SWCNT. Spectroscopy by means of Raman, fluorescence, and transient absorption spectroscopy confirmed efficient charge-transfer interaction from photoexcited metalloporphyrins to SWCNTs in the ground and excited state of 1-SWCNT, 2-SWCNT, and 3-SWCNT. The complementary use of spectroelectrochemical and transient absorption measurements substantiates the formation of one-electron oxidized metalloporphyrins after photoexcitation. Multiwavelength global analysis provides insights into the charge-separation and recombination processes in 1-SWCNT, 2-SWCNT, and 3-SWCNT upon photoexcitation. Notably, both the charge-separation and recombination dynamics are fastest in 2-SWCNT. Importantly, the strongest interactions in the steady-state experiments are associated with the fastest excited state decay in the time-resolved measurements.
CRIS-Team Scopus Importer:2021-01-22
Keywords: carbon nanotubes; charge-transfer interactions; doping; non-covalent functionalization; porphyrins

A multicomponent molecular approach to artificial photosynthesis-the role of fullerenes and endohedral metallofullerenes - Rudolf, Marc; Kirner, Sabrina; Guldi, Dirk Michael (Chemical Society Reviews, 2016)
In this review article, we highlight recent advances in the field of solar energy conversion at a molecular level. We focus mainly on investigations regarding fullerenes as well as endohedral metallofullerenes in energy and/or electron donor-acceptor conjugates, hybrids, and arrays, but will also discuss several more advanced systems. Hereby, the mimicry of the fundamental processes occurring in natural photosynthesis, namely light harvesting (LH), energy transfer (EnT), reductive/oxidative electron transfer (ET), and catalysis (CAT), which serve as a blue print for the rational design of artificial photosynthetic systems, stand at the focalpoint. Importantly, the key processes in photosynthesis, that is, LH, EnT, ET, and CAT, define the structure of this review with the only further differentiation in terms of covalent and non-covalent systems. Fullerenes as well as endohedral metallofullerenes are chosen by virtue of their small reorganization energies in electron transfer processes, on the one hand, and their exceptional redox behaviour, on the other hand.
CRIS-Team Scopus Importer:2023-03-07

An electrochemical and photophysical study of a covalently linked inorganic-organic dyad - Kahnt, Axel; Heiniger, Leo-Philipp; Liu, Shi-Xia; Tu, Xiaoyan; Zheng, Zhiping; Hauser, Andreas; Decurtins, Silvio; Guldi, Dirk Michael (ChemPhysChem, 2010)
A molecular donor-acceptor dyad comprising a hexarhenium cluster core, [Re(m-Se)], and a fullerene moiety which are covalently linked through a pyridine ligand was synthesized and fully characterized. The electrochemical and photophysical properties are reported. The detailed study includes cyclic voltammetry, steady-state absorption and fluorescence spectroscopy, radiation chemistry and transient absorption spectroscopy. A light-induced electron transfer between the inorganic cluster moiety and the fullerene can be excluded. However, a light-induced energy transfer from the rhenium cluster to the fullerene is proposed © Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

An endohedral metallofullerene as a pure electron donor: Intramolecular electron transfer in donor-acceptor conjugates of La2@C80 and 11,11,12,12-tetracyano-9,10-anthra- p -quinodimethane (TCAQ) - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
An endohedral metallofullerene, La@C, is covalently linked to the strong electron acceptor 11,11,12,12-tetracyano-9,10- anthra-p-quinodimethane (TCAQ) by means of the Prato reaction, affording two different [5,6]-metallofulleropyrrolidines, namely 1a and 2a. 1a and 2a were isolated and fully characterized by means of MALDI-TOF mass, UV-vis-NIR absorption, and NMR spectroscopies. In addition, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) corroborated the unique redox character of 2a, that is, the presence of the electron-donating La@C and the electron-accepting TCAQ. Although a weak electronic coupling dictates the interactions between La@C and TCAQ in the ground state, time-resolved transient absorption experiments reveal that in the excited state (i.e., π-π* centered at La@C) the unprecedented formation of the (La@C) -(TCAQ) radical ion pair state evolves in nonpolar and polar media with a quantum efficiency of 33%. © 2012 American Chemical Society.

A new approach for the photosynthetic antenna-reaction center complex with a model organized around an s-triazine linker - Kuhri, Susanne; Charalambidis, Georgios; Angaridis, Panagiotis A.; Lazarides, Theodore; Pagona, Georgia; Tagmatarchis, Nikos; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Chemistry - A European Journal, 2014)
Two new artificial mimics of the photosynthetic antenna-reaction center complex have been designed and synthesized (BDP-HP-C and BDP-ZnP-C). The resulting electron-donor/acceptor conjugates contain a porphyrin (either in its free-base form (HP) or as Zn-metalated complex (ZnP)), a boron dipyrrin (BDP), and a fulleropyrrolidine possessing, as substituent of the pyrrolidine nitrogen, an ethylene glycol chain terminating in an amino group C-X-NH (X=spacer). In both cases, the three different components were connected by s-triazine through stepwise substitution reactions of cyanuric chloride. In addition to the facile synthesis, the star-type arrangement of the three photo- and redox-active components around the central s-triazine unit permits direct interaction between one another, in contrast to reported examples in which the three components are arranged in a linear fashion. The energy- and electron-transfer properties of the resulting electron-donor/acceptor conjugates were investigated by using UV/Vis absorption and emission spectroscopy, cyclic voltammetry, and femtosecond transient absorption spectroscopy. Comparison of the absorption spectra and cyclic voltammograms of BDP-HP-C and BDP-ZnP-C with those of BDP-HP, BDP-ZnP and BDP-C, which were used as references, showed that the spectroscopic and electrochemical properties of the individual constituents are basically retained, although some appreciable shifts in terms of absorption indicate some interactions in the ground state. Fluorescence lifetime measurements and transient absorption experiments helped to elucidate the antenna function of BDP, which upon selective excitation undergoes a rapid and efficient energy transfer from BDP to HP or ZnP. This is then followed by an electron transfer to C, yielding the formation of the singlet charge-separated states, namely BDP-HP-C and BDP-ZnP-C. As such, the sequence of energy transfer and electron transfer in the present models mimics the events of natural photosynthesis. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

A new exTTF-crown ether platform to associate fullerenes: Cooperative n-π and π-π Effects - Grimm, Bruno; Santos, Jose; Illescas, Beatriz M.; Munoz, Antonio; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2010)
A new and readily available exTTF-bis(crown ether), 1, efficiently recognizes C as well as C by means of cooperative π-π and n-π interactions. The geometrical (concave-convex) and electronic (donor-acceptor) complementarity accounts on one hand for remarkable binding strengths, with association constants reaching 10 M in benzonitrile, and on the other hand for lifetimes of the photogenerated radical ion pair state on the order of 45 ps. © 2010 American Chemical Society.

An exciting twenty-year journey exploring porphyrinoid-based photo- and electro-active systems - Bottari, Giovanni; de la Torre, Gema; Guldi, Dirk Michael; Torres, Tomás (Coordination Chemistry Reviews, 2021)
This review highlights the combined effort of the Torres and Guldi groups in the preparation and study of porphyrinoid-based photo- and electro-active systems. The perfect synergy between the deep knowledge on the chemistry of porphyrinoids and advanced carbon allotropes possessed by the Spanish team, and the profound expertise in the advanced photophysical characterization and photon- and charge-management held by the German group represents the real asset of this transnational collaboration. Along the last twenty years, the two groups have developed a plethora of electron donor–acceptor architectures based mainly on phthalocyanines and subphthalocyanines, but also porphyrins and other porphyrinoids, connected, either covalently or through supramolecular interactions, to several electroactive units such as advanced carbon allotropes, that is, fullerenes, carbon nanotubes, and graphene, among others. Important guidelines relating the structural and electronic features of such photo- and electro-active species with physical aspects such as the dynamics of charge separation, charge transport, charge shift, and charge recombination processes have been obtained. This knowledge has resulted crucial for the implementation of many of these systems into applied research fields such as optoelectronics, solar energy conversion, and biomedicine.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Advanced carbon allotropes; Electron donor–acceptor systems; Energy conversion; Phthalocyanines; Subphthalocyanines

An improved synthesis of 4-cyano-1,10-phenanthroline, 4,7-dicyano-1,10- phenanthroline and their bis(4,4′-di-tert-butyl-2,2′-bipyridine) ruthenium(II) complexes - Staehle, Robert; Menzel, Roberto; Peuntinger, Katrin; Pilz, T. David; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Beckert, Rainer; Rau, Sven (Polyhedron, 2014)
This report describes a new palladium catalyzed synthesis of 4-cyano-1,10-phenanthroline (nphen, 1), 4,7-dicyano-1,10-phenanthroline (dnphen, 2) and their corresponding ruthenium complexes. The two cationic complexes, [(tbbpy)Ru(nphen)] 3 and [(tbbpy)Ru(dnphen) ] 4 (tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine), were synthesized using an improved microwave procedure. All compounds were fully characterized, including the solid-state molecular structures of the complexes. The influence of 1 and 2 on the metal-to-ligand charge transfer (MLCT) transitions were studied and compared to the ruthenium(II) polypyridyl complexes containing the related 4,4′-dicyano-2,2′-bipyridine (dnbpy) and the non-functionalized 1,10-phenanthroline (phen) ligand. © 2014 Elsevier Ltd. All rights reserved.

A non-covalent strategy to prepare electron donor-acceptor rotaxanes - Scarel, Francesco; Ehli, Christian; Guldi, Dirk Michael; Mateo-Alonso, Aurelio (Chemical Communications, 2013)
A straightforward non-covalent synthetic strategy for producing donor-acceptor rotaxanes is reported. Femtosecond absorption spectroscopy illustrates that the use of this strategy gives rise to supramolecular chromophores with different electron transfer behavior. © 2013 The Royal Society of Chemistry.

A Novel Electron Donor-Acceptor Carbazole-Zn(II)Phthalocyanine – Perfluorinated Subphthalocyanine Conjugate: Synthesis, Characterization, and Photoinduced Electron-Transfer - Platzer, Benedikt; Ghazal, Basma; Marinas, Victor; Labella, Jorge; Victoria Martinez-Diaz, M.; Maksheed, Saad; Guldi, Dirk Michael; Torres, Tomas (Chemphotochem, 2022)
Porphyrinoids are considered perfect candidates for the preparation of model electron donor-acceptor (D-A) systems as they enable fast and efficient photoinduced electron transfer. Herein, we report on the synthesis and photophysical characterization of a ZnPc−SubPc conjugate covalently connected through a short-range alkyne spacer. We designed and prepared the conjugate, which comprise, on the one hand, a perfluorinated SubPc with strong electron acceptor character and, on the other, a Pc peripherally functionalized with carbazoles with strong electron donor character. Photoinduced electron transfer events are in-depth analyzed by several techniques, including steady-state absorption, time-resolved emission and transient absorption measurements on different time scales. Our studies confirm a full charge separation occurring from a photoexcited charge transfer state.
CRIS-Team Scopus Importer:2022-11-25
Keywords: electron transfer; near infrared; organic photovoltaics; phthalocyanines; subphthalocyanines

A novel empirical method for quickly estimating the charge-transfer state of fullerene-donor derivatives - Liu, Liping (Physical Chemistry Chemical Physics, 2019)

Anthracene-Fused Oligo-BODIPYs: A New Class of π-Extended NIR-Absorbing Materials - Labella, Jorge; Durán-Sampedro, Gonzalo; Krishna, Swathi; Martínez-Díaz, M. Victoria; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie International Edition, 2022)
Large π-conjugated systems are key in the area of molecular materials. Herein, we prepare via AuI-catalyzed cyclization a series of fully π-conjugated anthracene-fused oligo-BODIPYs. Their structural and optoelectronic properties were studied by several techniques, ranging from X-ray, UV/Vis, and cyclic voltammetry to transient absorption spectroscopy. As a complement, their electronic structures were explored by means of Density Functional Theory (DFT) calculations. Depending on the size and shape of the π-conjugated skeleton, unique features—such as face-to-face supramolecular organization, NIR absorption and fluorescence as well as strong electron accepting character—were noted. All in all, the aforementioned features render them valuable for technological applications.
CRIS-Team Scopus Importer:2022-12-23
Keywords: BODIPY; Conjugation; Dyes/Pigments; NIR; π-Systems

Anticancer Effect of an Electronically Coupled Oligoferrocene - Zeh, Gina; Haines, Philipp; Miehlich, Matthias; Kienz, Torben; Neidlinger, Andreas; Friedrich, Ralf P.; Alexiou, Christoph; Hampel, Frank; Guldi, Dirk Michael; Meyer, Karsten; Schatz, Jürgen; Heinze, Katja; et al. (Organometallics, 2020)
The mode of anticancer activity of simple ferrocenes often relies on their intracellular oxidation with the formation of cytotoxic ferrocenium species. The former compounds should be considered as prodrugs and derived from them ferroceniums as drugs. The drugs are 17e- organometallic species. Therefore, they are chemically unstable and decompose with formation of free cyclopentadienyl ligands (which are further transformed to more stable species) and iron ions. The short lifetime of ferrocenium drugs limits the anticancer effect of ferrocene prodrugs. In this paper we prepared a series of acylated aminoferrocene monomers, dimers, and higher oligonuclear complexes FcN (where N = 1-4). Drugs [FcN]+ derived from FcN (N > 1) are more stable than monomeric [Fc]+, provided that the ferrocene units are electronically coupled. Correspondingly, we expected that FcN species will be more potent anticancer agents in comparison to the related monomers. These assumptions were confirmed for dimer 10. We observed that this prodrug has sufficient solubility in aqueous solution (100 μM) and favorable lipophilicity (log P = 2.2 ± 0.2). Ferrocene units in 10 are efficiently electronically coupled via a -C(═O)NH- linker according to cyclic voltammetry, differential pulse voltammetry, and spectroelectrochemistry. We observed that 10 is the most efficient catalyst of the production of reactive oxygen species (ROS) and the most active anticancer agent in comparison to control monomers and their mixtures.
CRIS-Team Scopus Importer:2020-09-14

Antimony sulfide as a light absorber in highly ordered, coaxial nanocylindrical arrays: preparation and integration into a photovoltaic device - Wu, Yanlin; Assaud, Loic; Kryschi, Carola; Capon, Boris; Detavernier, Christophe; Santinacci, Lionel; Bachmann, Julien (Journal of Materials Chemistry A, 2015)
We demonstrate the preparation of functional 'extremely thin absorber' solar cells consisting of massively parallel arrays of nanocylindrical, coaxial n-TiO2/i-Sb2S3/p-CuSCN junctions. Anodic alumina is used as an inert template that provides ordered pores of 80 nm diameter and 1-50 mu m length. Atomic layer deposition (ALD) then coats pores of up to 20 mm with thin layers of the electron conductor and the intrinsic light absorber. The crystallization of the initially amorphous Sb2S3 upon annealing is strongly promoted by an underlying crystalline TiO2 layer. After the remaining pore volume is filled with the hole conductor by solution evaporation, the resulting coaxial p-i-n junctions display stable diode and photodiode electrical characteristics. A recombination timescale of 40 ms is extracted from impedance spectroscopy in open circuit conditions, whereas transient absorption spectroscopy indicates that holes are extracted from Sb2S3 with a lifetime of 1 ns.

A panchromatic supramolecular fullerene-based donor-acceptor assembly derived from a peripherally substituted bodipy-zinc phthalocyanine dyad - Rio, Yannick; Seitz, Wolfgang; Gouloumis, Andreas; Vazquez, Purificacion; Sessler, Jonathan L.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2010)
A panchromatic 4,4-difluoro4-bora-3a,4a-diaza-s-indacene -zinc phthalocyanine conjugate (BodipyZnPc) 1 was synthesized starting from phthalocyanine aldehyde 4, via dipyrromethane 3 and dipyrromethene 2. Conjugate 1 represents the first example in which a Bodipy unit is tethered to the peripheral position of a phthalocyanine core. Electrochemical and optical measurements provided evidence for strong electronic interactions between the Bodipy and ZnPc constituents in the ground state of 1. When conjugate 1 is subjected to photoexcitation in the spectral region corresponding to the Bodipy absorption, the strong fluorescence characteristic of the latter subunit is effectively quenched (i.e., ≥97%). Excitation spectral analysis confirmed that the photoexcited Bodipy and the tethered ZnPc subunits interact and that intraconjugate singlet energy transfer occurs with an efficiency of ca. 25 %. Treatment of conjugate 1 with N-pyridylfulleropyrrolidine (8), an electron-acceptor system containing a nitrogen ligand, gives rise to the novel electron donor-acceptor hybrid l↔8 through ligation to the ZnPc center. Irradiation of the resulting supramolecular ensemble within the visible range leads to a charge-separated Bodipy-ZnPc-C radical-ion-pair state, through a sequence of excited-state and charge transfers, characterized by a remarkably long lifetime of 39.9 ns in toluene. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.

A paradigmatic change: Linking fullerenes to electron acceptors - Feng, Lai; Rudolf, Marc; Wolfrum, Silke; Troeger, Anna; Slanina, Zdenek; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Ameri, Tayebeh; Brabec, Christoph; Guldi, Dirk Michael (Journal of the American Chemical Society, 2012)
The potential of Lu N@C and its analogues as electron acceptors in the areas of photovoltaics and artificial photosynthesis is tremendous. To this date, their electron-donating properties have never been explored, despite the facile oxidations that they reveal when compared to those of C . Herein, we report on the synthesis and physicochemical studies of a covalently linked Lu N@C -perylenebisimide (PDI) conjugate, in which PDI acts as the light harvester and the electron acceptor. Most important is the unambiguous evidence-in terms of spectroscopy and kinetics-that corroborates a photoinduced electron transfer evolving from the ground state of Lu N@C to the singlet excited state of PDI. In stark contrast, the photoreactivity of a C -PDI conjugate is exclusively governed by a cascade of energy-transfer processes. Also, the electron-donating property of the Lu N@C moiety was confirmed through constructing and testing a bilayer heterojunction solar cell device with a PDI and Lu N@C derivative as electron acceptor and electron donor, respectively. In particular, a positive photovoltage of 0.46 V and a negative short circuit current density of 0.38 mA are observed with PDI/Ca as anode and ITO/Lu N@C as cathode. Although the devices were not optimized, the sign of the V and the flow direction of J clearly underline the unique oxidative role of Lu N@C within electron donor-acceptor conjugates toward the construction of novel optoelectronic devices. © 2012 American Chemical Society.

A photochemical on-off switch for tuning the equilibrium mixture of H 2 nuclear spin isomers as a function of temperature - Frunzi, Michael; Jockusch, Steffen; Chen, Judy Y. -C.; Krick Calderon, Rafael; Lei, Xuegong; Murata, Yasujiro; Komatsu, Koichi; Guldi, Dirk Michael; Lawler, Ronald G.; Turro, Nicholas J. (Journal of the American Chemical Society, 2011)
The photochemical interconversion of the two allotropes of the hydrogen molecule [para-H (pH) and ortho-H (oH )] incarcerated inside the fullerene C (pH @C and oH@C, respectively) is reported. Photoexcitation of H@C generates a fullerene triplet state that serves as a spin catalyst for pH/oH conversion. This method provides a means of changing the pH/oH ratio inside C by simply irradiating H @C at different temperatures, since the equilibrium ratio is temperature-dependent and the electronic triplet state of the fullerene produced by absorption of the photon serves as an "on-off" spin catalyst. However, under comparable conditions, no photolytic pH /oH interconversion was observed for H @C, which was rationalized by the significantly shorter triplet lifetime of H@C relative to H @C. © 2011 American Chemical Society.

A photoinduced mixed valence photoswitch - Cotic, Agustina; Cerfontaine, Simon; Slep, Leonardo D.; Elias, Benjamin; Troian-Gautier, Ludovic; Cadranel, Alejandro (Physical Chemistry Chemical Physics, 2022)
The ground state and photoinduced mixed valence states (GSMV and PIMV, respectively) of a dinuclear (Dp(4+)) ruthenium(ii) complex bearing 2,2 '-bipyridine ancillary ligands and a 2,2 ':4 ',4 '':2 '',2 '''-quaterpyridine (Lp) bridging ligand were investigated using femtosecond and nanosecond transient absorption spectroscopy, electrochemistry and density functional theory. It was shown that the electronic coupling between the transiently light-generated Ru(ii) and Ru(iii) centers is H-DA similar to 450 cm(-1) in the PIMV state, whereas the electrochemically generated GSMV state showed H-DA similar to 0 cm(-1), despite virtually identical Ru-Ru distances. This stemmed from the changes in dihedral angles between the two bpy moieties of Lp, estimated at 30 degrees and 4 degrees for the GSMV and PIMV states, respectively, consistent with a through-bond rather than a through-space mechanism. Electronic coupling can be turned on by using visible light excitation, making Dp(4+) a competitive candidate for photoswitching applications. A novel strategy to design photoinduced charge transfer molecular switches is proposed.
CRIS-Team WoS Importer:2022-06-24

APTES-Terminated ultrasmall and iron-doped silicon nanoparticles as X-Ray dose enhancer for radiation therapy - Klein, Stefanie; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2018)
Silicon nanoparticles with sizes between were synthesized through wet-chemistry procedures using diverse phase transfer reagents. On the other hand, the preparation of iron-doped silicon nanoparticles was carried out using the precursor Na4Si4 containing 5% Fe. Biocompatibility of all silicon nanoparticle samples was achieved by surface-stabilizing with (3-aminopropyl)triethoxysilane. These surface structures provided positive surface charges which facilitated electrostatic binding to the negatively charged biological membranes. The mode of interaction with membranes, being either incorporation or just attachment, was found to depend on the nanoparticle size. The smallest silicon nanoparticles (ca. 1.5 nm) were embedded in the mitochondrial membrane in MCF-7 cells. When interacting with X-rays these silicon nanoparticles were observed to enhance the superoxide formation upon depolarizing the mitochondrial membrane. X-ray irradiation of MCF-7 cells loaded with the larger silicon nanoparticles was shown to increase the intracellular singlet oxygen generation. The doping of the silicon nanoparticles with iron led to additional production of hydroxyl radicals via the Fenton reaction.
EVALuna2:35202

A push-pull unsymmetrical subphthalocyanine dimer - Zango, German; Zirzlmeier, Johannes; Claessens, Christian G.; Clark, Timothy; Victoria Martinez-Diaz, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2015)
Unsymmetrical subphthalocyanine fused dimers have been prepared from appropriate ortho-dinitrile SubPc precursors. In particular, either electron-donating or electron-accepting substituents have been introduced on each SubPc constituent unit, resulting in unprecedented push-pull pi-extended curved aromatic macrocycles. From fluorescence experiments in solvents of different polarity we conclude a dual fluorescence, namely a delocalized singlet excited state (1.73 eV) and a polarized charge transfer state (<1.7 eV). Pump probe experiments corroborate the dual nature of the fluorescence. On one hand, the delocalized singlet excited state gives rise to a several nanosecond lasting intersystem crossing yielding the corresponding triplet excited state. On the other hand, the polarized charge transfer state deactivates within a few picosesonds. Visualization of the charge transfer state was accomplished by means of molecular modeling with a slight polarization of the HOMO towards the electron donor and of the LUMO towards the electron acceptor.

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Area-Selective Growth of HfS(2)Thin Films via Atomic Layer Deposition at Low Temperature - Cao, Yuanyuan; Wähler, Tobias; Park, Hyoungwon; Will, Johannes; Prihoda, Annemarie; Moses Badlyan, Narine; Fromm, Lukas; Yokosawa, Tadahiro; Wang, Bingzhe; Guldi, Dirk Michael; Görling, Andreas; Maultzsch, Janina; et al. (Advanced Materials Interfaces, 2020)
The transition-metal dichalcogenide HfS(2)is a promising alternative semiconductor with adequate band gap and high carrier mobility. However, a controllable growth of continuous HfS(2)films with selectivity for specific surfaces at a low temperature on a large scale has not been demonstrated yet. Herein, HfS(2)films are grown at 100 degrees C by atomic layer deposition (ALD) based on the precursors tetrakis(dimethylamido)hafnium and H2S. In situ vibrational spectroscopy allows for the definition of the temperature range over which (Me2N)(4)Hf chemisorbs as one monolayer. In that range, sequential exposures of the solid surface with (Me2N)(4)Hf and H2S result in self-limiting reactions that yield alternating surface termination with dimethylamide and thiol. Repeating the cycle grows smooth, continuous, stoichiometric films of thicknesses adjustable from angstroms to >100 nm, as demonstrated by spectroscopic ellipsometry, XRR, AFM, UV-vis and Raman spectroscopy, XPS, and TEM. The well-defined surface chemistry enables one to deposit HfS(2)selectively using, for example, patterns generated in molecular self-assembled monolayers. This novel ALD reaction combines several attractive features necessary for integrating HfS(2)into devices.
CRIS-Team Scopus Importer:2020-10-23
Keywords: 2D materials; atomic layer deposition; dichalcogenides; hafnium disulfide; thin films

Aromatic Nanosandwich Obtained by σ-Dimerization of a Nanographenoid π-Radical - Moshniaha, Liliia; Żyła-Karwowska, Marika; Chmielewski, Piotr J.; Lis, Tadeusz; Cybińska, Joanna; Gońka, Elżbieta; Oschwald, Johannes; Drewello, Thomas; Rivero, Samara Medina; Casado, Juan; Stȩpień, Marcin (Journal of the American Chemical Society, 2020)
A 139-π-electron nanographenoid radical was obtained by expanding the periphery of a naphthalimide-azacoronene hybrid with a methine bridge. The radical was isolated in the form of its σ-dimer, which was shown to possess a conformationally restricted two-layer structure both in the solid state and in solution. The dimer is cleaved into its parent radicals when exposed to ultraviolet or visible radiation in toluene solutions but is resistant to thermally induced dissociation. Under inert conditions, the radicals recombine quantitatively into the σ-dimer with observable kinetics, but they are oxidized into a ketone derivative in the presence of atmospheric oxygen. Combined structural, spectroscopic, and theoretical evidence shows that the σ-dimer contains a weak C(sp3)-C(sp3) bond, but is stabilized against thermal dissociation by a very strong dispersive interaction between the overlapping πsurfaces.
CRIS-Team Scopus Importer:2020-03-10

A Small Dye Puzzle: π-Conjugation of Perylenes with External Aromatic Compounds via Imidazo-Quinoxaline Bridges - Dobeneck, Michaela; Kaur, Ramandeep; Platzer, Benedikt; Guldi, Dirk Michael; Hirsch, Andreas (Chemphotochem, 2021)
The synthesis and characterization of a library of unprecedented π-extended perylenes is reported. For this purpose, a successful step-by-step connection of three puzzle pieces, namely a perylene, an imidazole-quinoxaline bridge and an o-quinone was developed. Our synthetic route allows for facile access to linearly π-extended perylenes in a highly chemoselective manner. The absorption and fluorescence properties are solvent dependent and are bathochromically shifted relative to unbridged perylene references. Overall, the fluorescence quantum yields are high with values ranging from 46 % to 11 %. To complete the physico-chemical characterization, differential pulse and cyclic voltammograms were recorded showing two reductions and two oxidations for each of the linearly π-extended perylenes.
CRIS-Team Scopus Importer:2020-12-11
Keywords: conjugation; dye and pigments; heterodimers; perylene

Assembling a phthalocyanine and perylenediimide donor-acceptor hybrid through a platinum(II) diacetylide linker - Jimenez, Angel J.; Sekita, Michael; Caballero, Esmeralda; Luisa Marcos, M.; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2013)
In a novel electron-donor-acceptor conjugate, phthalocyanine (Pc) and perylenediimide (PDI) are connected through a trans-platinum(II) diacetylide linker to yield Pc-Pt-PDI1. In the ground state, the presence of Pt disrupts the electronic communication between the two electroactive components, as revealed by UV/Vis spectroscopy and electrochemical studies. The photophysical behavior of 1 is compared with that of the corresponding Pc-PDI electron-donor-acceptor conjugate2 in terms of charge separation and charge recombination. The insertion of Pt between Pc and PDI impacts the results in a longer-lived Pc/PDI radical ion-pair state. In addition, the intermediately formed Pc triplet excited state is formed with higher quantum yields in 1 than in 2. Linked up: The photophysical behavior of a phthalocyanine (Pc)-perylenediimide (PDI) Pc-Pt-PDI donor-acceptor hybrid (see figure), in which a platinum diacetylide linker disrupts electronic communication between the two electroactive components, is compared with that of the corresponding conjugated Pc-PDI array in terms of photoinduced generation of a long-lived charge-separation state. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Assembling Mesoscale-Structured Organic Interfaces in Perovskite Photovoltaics - Hou, Yi; Xie, Chen; Radmilovic, Vuk V.; Puscher, Bianka; Wu, Mingjian; Heumüller, Thomas; Karl, André; Li, Ning; Tang, Xiaofeng; Meng, Wei; Chen, Shi; Osvet, Andres; et al. (Advanced Materials, 2019)
Mesoscale-structured materials offer broad opportunities in extremely diverse applications owing to their high surface areas, tunable surface energy, and large pore volume. These benefits may improve the performance of materials in terms of carrier density, charge transport, and stability. Although metal oxides–based mesoscale-structured materials, such as TiO2, predominantly hold the record efficiency in perovskite solar cells, high temperatures (above 400 °C) and limited materials choices still challenge the community. A novel route to fabricate organic-based mesoscale-structured interfaces (OMI) for perovskite solar cells using a low-temperature and green solvent–based process is presented here. The efficient infiltration of organic porous structures based on crystalline nanoparticles allows engineering efficient “n-i-p” and “p-i-n” perovskite solar cells with enhanced thermal stability, good performance, and excellent lateral homogeneity. The results show that this method is universal for multiple organic electronic materials, which opens the door to transform a wide variety of organic-based semiconductors into scalable n- or p-type porous interfaces for diverse advanced applications.<br

Assembling phthalocyanine dimers through a platinum(II) acetylide linker - Jimenez, Angel J.; Luisa Marcos, M.; Hausmann, Anita; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Phthalocyanine (Pc) dimers connected through trans-platinum(II) diacetylide linkers have been prepared by reaction of the corresponding ethynylphthalocyanines with trans-bis(triethylphosphine)platinum(II) chloride. Special emphasis was placed on the analysis of the ground- and excited-state features of these compounds in relation to butadiyne-bridged Pc dimers and the corresponding monomers. Both Zn -containing Pc dimers exhibit long-lived triplet excited states. The insertion of σ-bonded trans-platinum(II) diacetylide spacers decoupled the two Pc groups and led to an appreciable acceleration (by a factor of up to 10) of the radiative and nonradiative decay rate of the singlet and triplet excited states. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Assessing the Photoinduced Electron-Donating Behavior of Carbon Nanodots in Nanoconjugates - Ferrer-Ruiz, Andres; Scharl, Tobias; Rodriguez-Perez, Laura; Cadranel, Alejandro; Angeles Herranz, M.; Martin, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
Carbon nanodots (CNDs) undergo electron transfer in different scenarios. Previous studies have mainly focused on the electron-accepting features of CNDs in covalently linked donor-acceptor nanoconjugates. In view of this, we decided to carry out in this study the formation of covalently linked nanoconjugates that feature electron-donating pressure synthesized carbon nanodots (pCNDs) and electron-accepting 11,11,12,12-tetracyano-9,10-anthra-p-quinodimethane (TCAQ): pCND-TCAQ The stability of the one-electron reduced form of TCAQ renders it the acceptor of choice. Detailed structural and electrochemical investigations allowed the characterization of pCND-TCAQ Furthermore, investigations regarding intramolecular interactions, by means of steady-state and pump-probe transient absorption spectroscopies, allowed detection and characterization of three excited state species, in general, and the pCND(center dot+)-TCAQ(center dot-) charge-separated state, in particular.
CRIS-Team WoS Importer:2021-02-05

Assigning Electronic States in Carbon Nanodots - Strauß, Volker; Kahnt, Axel; Zolnhofer, Eva; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas; Peukert, Wolfgang; Etschel, Sebastian; Halik, Marcus; Guldi, Dirk Michael (Advanced Functional Materials, 2016)
Luminescent carbon nanodots exhibit enormous potential to be used as functional building blocks in energy conversion devices. Their intrinsic heterogeneity, however, hinders a thorough characterization and subsequently their applicability. In this work, the spectroscopic and electrochemical properties of prototype carbon nanodots were thoroughly studied in solution. Spectro-electrochemical experiments revealed information on the spectral features of several oxidized and reduced species of our carbon nanodots. Therefore, these experiments were complemented with pulse radiolysis where the spectral signature of the one-electron oxidized and reduced forms were identified. Both, electrochemically and radiolytically reduced and oxidized products show high reactivity in solution which correlates with an open-shell character, detected by paramagnetic resonance spectroscopy. The herein presented studies help to understand the complex nature of carbon nanodots and serve to overcome difficulties in device fabrication.

A study of acridine and acridinium-substituted bis(terpyridine)zinc(ii) and ruthenium(ii) complexes as photosensitizers for O2 ( 1Δg) generation - Eberhard, Jens; Peuntinger, Katrin; Rath, Susann; Neumann, Beate; Stammler, Hans-Georg; Guldi, Dirk Michael; Mattay, Jochen (Photochemical & Photobiological Sciences, 2014)
The homoleptic zinc(ii) and ruthenium(ii) metal complexes of bis(tridentate) 9-acridine and 10-methyl-9-acridinium-substituted terpyridines were tested for their suitability as triplet photosensitizers (PS) using the photooxidation of 1,5-dihydroxynaphthalene (DHN) to Juglone as a model reaction. Singlet oxygen (OΔ) generation is superior or comparable to Ru(bpy) for the acridine complexes, whereas the acridinium complexes are ineffective. The molecular structure of the bis(9-(5-([2,2′:6′,2′′-terpyridin]- 4′-yl)thien-2-yl)-10-methylacridinium)zinc(ii) complex ([Zn(MeATT) ][PF]) is determined by X-ray structure analysis, whereas for other complexes DFT calculations were performed for structural parameters to obtain insights into their electronic properties. This journal is © The Royal Society of Chemistry and Owner Societies.

A Supramolecular [10]CPP Junction Enables Efficient Electron Transfer in Modular Porphyrin–[10]CPP⊃Fullerene Complexes - Xu, Youzhi; Wang, Bingzhe; Kaur, Ramandeep; Minameyer, Martin; Bothe, Michael; Drewello, Thomas; Guldi, Dirk Michael; Von Delius, Max (Angewandte Chemie International Edition, 2018)
Efficient photoinduced electron transfer was observed across a [10]cycloparaphenylene ([10]CPP) moiety that serves as a rigid non-covalent bridge between a zinc porphyrin and a range of fullerenes. The preparation of iodo-[10]CPP is the key to the synthesis of a porphyrin–[10]CPP conjugate, which binds C60, C70, (C60)2, and other fullerenes (KA>105 m−1). Fluorescence and pump–probe spectroscopy revealed intramolecular energy transfer between CPP and porphyrin and also efficient charge separation between porphyrin and fullerenes, affording up to 0.5 μs lifetime charge-separated states. The advantage of this approach towards electron donor–acceptor dyads is evident in the case of dumbbell-shaped (C60)2, which gave intricate charge-transfer behavior in 1:1 and 2:1 complexes. These results suggest that [10]CPP and its cross-coupled derivatives could act as supramolecular mediators of charge transport in organic electronic devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electron transfer; fullerenes; host–guest systems; strained molecules; time-resolved spectroscopy

A Tetraethynyl[5]cumulene - Marshall, Jonathan L.; Arslan, Funda; Januszewski, Johanna; Ferguson, Michael J.; Tykwinski, Rik R. (Helvetica Chimica Acta, 2019)
The first example of a new class of carbon-rich molecules is introduced, namely, a derivative of tetraethynyl[5]cumulene (TE5C). The use of sterically demanding pendent groups is the decisive structural feature to provide a stable product. Whereas triisopropylsilyl groups are seemingly not sufficiently large to afford an isolable cumulene product, switching to the larger tris(3,5-di-tert-butylphenyl)methyl (supertrityl') groups gives a crystalline, stable compound ([5]TE). The structural and electronic properties of [5]TE are examined in comparison to its closest known molecular relatives, tetraaryl[5]cumulenes.
CRIS-Team WoS Importer:2019-04-09

A three-level luminescent response in a pyrene/ferrocene rotaxane - Mateo-Alonso, Aurelio; Ehli, Christian; Guldi, Dirk Michael; Prato, Maurizio (Organic Letters, 2013)
A solvent switchable rotaxane equipped with a pyrene stopper and with two ferrocenyl units on the macrocycle is reported, in which three different states, two nondegenerate and one degenerate, can be obtained in different solvents at room temperature. This is accompanied by high contrast changes in fluorescence intensity of the pyrene stopper by the presence of the ferrocenyl moieties on the macrocycle, which quench the emission of pyrene more efficiently with proximity. © 2012 American Chemical Society.

A Universal Design Strategy Based on NiPS3 Nanosheets towards Efficient Photothermal Conversion and Solar Desalination - Wang, Honglei; Bo, Yifan; Klingenhof, Malte; Peng, Jiali; Wang, Dong; Wu, Bing; Pezoldt, Jörg; Cheng, Pengfei; Knauer, Andrea; Hua, Weibo; Wang, Hongguang; van Aken, Peter A.; et al. (Advanced Functional Materials, 2023)
2D nanomaterials are proposed as promising photothermal materials for interfacial photothermal water evaporation. However, low evaporation efficiency, the use of hazardous hydrofluoric solution, and poor stability severely limit their practical applications. Here, a mixed solvent exfoliation surface deposition (MSESD) strategy for the preparation of NiPS3 nanosheets and NiPS3/polyvinyl alcohol (PVA) converter is successfully developed. The converter is obtained by drop-casting the NiPS3/PVA nanosheets onto a sponge. The PVA is mainly deposited on the edge of NiPS3 nanosheets, which not only improves the stability of NiPS3 nanosheets, but also adheres to the sponge to prepare a 3D photothermal converter, which shows an evaporation rate of 1.48 kg m−2 h−1 and the average photothermal conversion efficiency (PTCE) of 93.5% under a light intensity of 1 kW m−2. The photothermal conversion mechanism reveals that the energy of absorbed photons in NiPS3 nanosheets can be effectively converted into heat through non-radiative photon transitions as well as multiple optical interactions. To the best of the knowledge, this is the first report on the application of 2D metal-phosphorus-chalcogen (MPChx) for solar desalination, which provides new insights and guidance for the development of high-performance 2D photothermal materials.
CRIS-Team Scopus Importer:2023-11-17
Keywords: 2D materials; desalination; NiPS; photothermal conversions; surface depositions

A voyage into the synthesis and photophysics of homo- and heterobinuclear ensembles of phthalocyanines and porphyrins - De La Torre, Gema; Bottari, Giovanni; Sekita, Michael; Hausmann, Anita; Guldi, Dirk Michael; Torres, Tomas (Chemical Society Reviews, 2013)
The remarkable properties of both phthalocyanines and porphyrins as individual building blocks have motivated the synthesis and study of homo- and heterobinuclear conjugates as light-harvesting systems. These planar chromophores share important electronic features such as high molar absorption coefficients, rich redox chemistry and interesting photoinduced energy and/or electron transfer abilities. In addition, some of these properties can be tuned by the introduction of different peripheral substituents and metal centres. In this review, we present relevant synthetic strategies for the preparation of covalent and supramolecular, homo- and heterobinuclear systems based on phthalocyanine and porphyrin chromophores, leading to a variety of architectures. In such systems, the degree of electronic interaction between the components is highly dependent on the electronic features of the two macrocycles, their linkage, and the molecular topology of the ensemble. In addition, incorporation of electroactive units into these binuclear systems has been pursued, affording multicomponent, donor-acceptor conjugates. In-depth photophysical characterization of the ground- and excited-state features of many of these homo- and heterobinuclear phthalocyanine and/or porphyrin ensembles has also been presented. Particular attention has been paid to understand the fundamental dynamics of the energy transfer and charge separation processes of these systems. This review intends to offer a general overview of the preparation of this class of compounds and the study of their photophysical properties which clearly show their potentiality as model compounds of light-harvesting complexes. © 2013 The Royal Society of Chemistry.

A water-soluble, bay-functionalized perylenediimide derivative - correlating aggregation and excited state dynamics - Dirian, Konstantin; Bauroth, Stefan; Roth, Alexandra Marina; Syrgiannis, Zois; Rigodanza, F.; Burian, Max; Amenitsch, H.; Sharapa, Dmitry; Prato, M.; Clark, Timothy; Guldi, Dirk Michael (Nanoscale, 2018)
The aggregation and the photophysics of a water soluble perylenediimide (PDI) derivative that features two bromine substituents in the bay positions has been probed. Non-fluorescent aggregates were found to be present at concentrations of 1.0 x 10(-5) M. In situ small-angle X-ray scattering (SAXS) measurements and complementary molecular modeling showed the presence of PDI aggregates. In their singlet excited states, the PDI aggregates are characterized by distinct transient fingerprints and rapid deactivation, as revealed by pump-probe experiments on the femto-, pico-, nano-, and microsecond timescales. The product of this deactivation is a PDI triplet excited state. The efficiency of the triplet formation depends on the concentration, and hence on the degree of aggregation. Notably, for PDI concentrations in the range of the critical micelle concentration, the efficiency of intersystem crossing is close to zero. In short, we have demonstrated, for the first time, aggregation-induced formation of triplet excited states for PDI derivatives.

Azulenocyanines immobilized on graphene; On the way to panchromatic absorption and efficient DSSC blocking layers - Volland, Michel; Lennert, Annkatrin; Roth, Alexandra Marina; Ince, Mine; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2019)
Herein, a novel electron donor-acceptor hybrid consisting of a NIR absorbing azulenocyanine as an electron donor and few-layer graphene as an electron acceptor was prepared. The extended aromatic core of azulenocyanine (1) assists in the exfoliation of graphite and allows the formation of a very high-quality few-layer graphene azulenocyanine hybrid system (2). The formation of a stable azulenocyanine/graphene hybrid was verified by means of an arsenal of spectroscopic and microscopic techniques. Notable is the fact that the absorption spectrum recorded for 1 and likewise that for 2 covers large portions of the solar spectrum, that is, from the UV through the visible to the NIR region. In light of the latter, we incorporated 1 as well as 2 as a photosensitizer in dye sensitized solar cells (DSSCs) and probed their light harvesting. Besides an increase in the photovoltaic conversion efficiency we focused on the stability of DSSCs by preventing charge recombination between FTO and the liquid electrolyte. We used 2 as a blocking layer and in comparison with a TiCl4 pretreated blocking layer a superior conversion efficiency was realized.
CRIS-Team Scopus Importer:2019-06-21

A π-stacked porphyrin-fullerene electron donor-acceptor conjugate that features a surprising frozen geometry - Ciammaichella, Alina; Dral, Pavlo; Clark, Timothy; Tagliatesta, Pietro; Sekita, Michael; Guldi, Dirk Michael (Chemistry - A European Journal, 2012)
A "frozen" electron donor-acceptor array that bears porphyrin and fullerene units covalently linked through the ortho position of a phenyl ring and the nitrogen of a pyrrolidine ring, respectively, is reported. Electrochemical and photophysical features suggest that the chosen linkage supports both through-space and through-bond interactions. In particular, it has been found that the porphyrin singlet excited state decays within a few picoseconds by means of a photoinduced electron transfer to give the rapid formation of a long-lived charge-separated state. Density functional theory (DFT) calculations show HOMO and LUMO to be localized on the electron-donating porphyrin and the electron-accepting fullerene moiety, respectively, at this level of theory. More specifically, semiempirical molecular orbital (MO) configuration interaction (CI) and unrestricted natural orbital (UNO)-CI methods shed light on the nature of the charge-transfer states and emphasize the importance of the close proximity of donor and acceptor for effective electron transfer. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Balancing binding strength and charge transfer lifetime in supramolecular associates of fullerenes - Grimm, Bruno; Isla, Helena; Perez, Emilio M.; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2011)
A macrocyclic exTTF host for fullerenes offers control over the electronic coupling between an electron donor and an acceptor, and stabilizes the charge separated state lifetimes into the range of 500 ps. © 2011 The Royal Society of Chemistry.

Battlement-shaped 1D coordination polymer based on a bis(N-methylimidazole- 2-yl)butadiyne ligand - Waidmann, Thomas; Fritsch, Nico; Tucher, Johannes; Rudolf, Marc; Glaser, Felix; Guldi, Dirk Michael; Burzlaff, Nicolai (Crystengcomm, 2013)
Bis(N-methylimidazole-2-yl)butadiyne (bmib) has been prepared starting from N-methylimidazole following two different pathways. Bmib fluoresces and is capable of forming 1D coordination polymers by clamping together metal units. The molecular structure of a zinc coordination polymer based on bmib and zinc acetate resembles a battlement of a fortress. © 2013 The Royal Society of Chemistry.

Beneficial effects of liquid crystalline phases in solid-state dye-sensitized solar cells - Costa, Ruben Dario; Werner, Fabian; Wang, Xinjiao; Grönninger, Philipp; Feihl, Sebastian; Kohler, Florian; Wasserscheid, Peter; Hibler, Susanne; Beranek, Radim; Meyer, Karsten; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. In particular, a good balance between dye regeneration and hole transport is only realized in the liquid crystalline phase. Devices that employ a single component ionic liquid based electrolyte show a remarkably stable efficiency during 1000 h under outdoor operation temperature conditions and 1 sun illumination. Two novel double-alkyl functionalized imidazolium ionic liquid crystals have successfully been utilized to demonstrate the benefits of the liquid crystalline phase on the ssDSSC performance. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Benzoporphyrins: Selective Co-sensitization in Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Chemistry - A European Journal, 2016)
A novel class of dyes, namely benzoporphyrins, was synthesized and implemented into dye-sensitized solar cells. They feature complementary absorptions compared to N719, which renders them promising candidates for co-sensitization in DSSCs. Notably, metallated benzoporphyrins reveal a TiO2-nanoparticle attachment that is size and aggregation dependent. Therefore, unproductive energy-transfer events between the selectively attached dyes can be prevented. In light of the latter, an efficiency improvement of 39 % has been achieved upon selective adsorption of benzoporphyrins and N719 onto different layers of TiO2 photoelectrode.
EAM Import::2019-03-13

Beware of Doping: Ta2O5 Nanotube Photocatalyst Using CNTs as Hard Templates - Cherevan, Alexey; Gebhardt, Paul; Kunzmann, Andreas; Costa, Ruben D.; Eder, Dominik (ACS Applied Energy Materials, 2018)
Nanostructuring constitutes a promising strategy to increase efficiency and stability of contemporary photocatalysts. Here, we report on the synthesis of highly crystalline Ta2O5 nanotubes (NTs) by using carbon nanotubes (CNTs) as sacrificial hard templates and elucidate the role of residual Fe nanoparticles-often used as catalyst for the CNT growth-on their photocatalytic performance toward H-2 evolution. We show that, when using as grown CNTs, the resulting Ta2O5 NTs contained detectable amounts of Fe and possessed negligible photocatalytic activity. When CNTs were, however, purified from Fe by thermally annealing the CNTs at 2100 degrees C, the same synthetic procedure yielded pure Ta2O5 NTs that showed a 40-fold increase in activity compared to the Fe-containing counterpart. A complementary set of analytical techniques in a combination with additional model experiments indicate that the detrimental effect of the residual Fe on the photocatalytic activity originates from atomic doping and formation of a segregated FeOx phase within the Ta2O5 matrix that can both act as efficient electron traps. Our result highlights that the presence of residual catalyst needs to be taken into account when using CNTs as hard templates and generally illustrates a possible effect of unintentional dopants that are often not considered in preparing functional nanostructures.
CRIS-Team WoS Importer:2019-02-27

Bidirectional Electron Transfer Capability in Phthalocyanine-Sc3N@Ih-C80 Complexes - Trukhina, Olga; Rudolf, Marc; Bottari, Giovanni; Akasaka, Takeshi; Echegoyen, Luis; Torres, Tomas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2015)
To activate oxidative and/or reductive electron transfer reactions, N-pyridyl-substituted Sc3N@Ih-C80 (4) and C60 (3) fulleropyrrolidines have been prepared and axially coordinated to electron-rich (1) or electron-deficient (2) Zn(II)phthalocyanines (Zn(II)Pcs) through zinc-pyridyl, metal-ligand coordination affording a full-fledged family of electron donor-acceptor ensembles. An arsenal of photophysical assays as they were carried out with, for example, 1/4 and 2/4 show unambiguously that a Zn(II)Pc-to-Sc3N@Ih-C80 photoinduced electron transfer takes place in the former ensemble, whereas a Sc3N@Ih-C80-to-Zn(II)Pc electron transfer occurs in the latter ensemble. To the best of our knowledge, this is the first time that a fullerene-based molecular building block shows an electron transfer dichotomy, namely acting both as electron-acceptor or electron-donor, and its outcome is simply governed by the electronic nature of its counterpart. In light of the latter, the present work, which involves the use of Sc3N@Ih-C80, one of the most abundant and easy-to-purify endohedral metallofullerenes, is, on one hand, a paradigmatic change and, on the other hand, an important milestone en-route toward the construction of easy-to-prepare molecular materials featuring switchable electron transfer reactivity.
CRIS-Team Scopus Importer:2023-03-07

Bifunctional Au-Fe3O4 Nanoheterodimers Acting as X-ray Protector in Healthy Cells and as X-ray Enhancer in Tumor Cells - Klein, Stefanie; Smuda, Matthias; Harreiß, Christina; Menter, Christina; Distel, Luitpold; Kryschi, Carola (ACS Applied Materials and Interfaces, 2019)
Bifunctional Au-Fe3O4 nanoheterodimers were synthesized by thermally decomposing Fe(III)oleate on gold nanoparticles followed by functionalizing with tiron, 2,3-dihydroxybenzoic acid, or caffeic acid. These catechol derivatives are antioxidative and thus are predicted to function as superoxide scavengers. In particular, caffeic acid lost its antioxidant capacity, although it was covalently linked through its carboxyl moiety to the Fe3O4 surface. Tiron was shown to bind via its catechol group to the Au-Fe3O4 nanoheterodimers, and 2,3-dihydroxybenzoic was just physisorbed between the oleic acid surface structures. Caffeic-acid stabilized Au-Fe3O4 nanoheterodimers turned out to act as X-ray protector in healthy cells but as X-ray enhancing agents in cancer cells. Furthermore, these functionalized Au-Fe3O4 nanoheterodimers were found to inhibit the migratory capacity of the cancer cells.
CRIS-Team Scopus Importer:2019-11-05
Keywords: 2; 3-dihydroxybenzoic acid; Au-Fe; caffeic acid; cell migration; radioprotector; radiosensitizer; tiron

Bifurcation of excited state trajectories toward energy transfer or electron transfer directed by wave function symmetry - Oviedo, Paola S.; Baraldo, Luis M.; Cadranel, Alejandro (Proceedings of the National Academy of Sciences of the United States of America, 2021)
This work explores the concept that differential wave function overlap between excited states can be engineered within a molecular chromophore. The aim is to control excited state wave function symmetries, so that symmetry matches or mismatches result in differential orbital overlap and define low-energy trajectories or kinetic barriers within the excited state surface, that drive excited state population toward different reaction pathways. Two donor–acceptor assemblies were explored, where visible light absorption prepares excited states of different wave function symmetry. These states could be resolved using transient absorption spectroscopy, thanks to wave function symmetry-specific photoinduced optical transitions. One of these excited states undergoes energy transfer to the acceptor, while another undertakes a back-electron transfer to restate the ground state. This differential behavior is possible thanks to the presence of kinetic barriers that prevent excited state equilibration. This strategy can be exploited to avoid energy dissipation in energy conversion or photoredox catalytic schemes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Electron transfer; Energy transfer; Excited state electronic coupling; Mixed valence; Photoinduced; Wave function symmetry

Binary Indium-Zinc Oxide Photoanodes for Efficient Dye-Sensitized Solar Cells - Peukert, Wolfgang; Stanzel, Melanie; Kunzmann, Andreas; Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2016)
The benefits of incorporating binary metal-oxide electrodes en route toward efficient dye-sensitized solar cells (DSSCs) have recently emerged. The current work aims at realizing efficient indium-doped zinc oxide based DSSCs by means of enhancing charge transport processes and reducing recombination rates. Electrochemical impedance spectroscopic assays corroborate that low amounts of indium reduce charge transport resistances and increase electron recombination resistances. The latter are in concert with a remarkable enhancement of the charge collection efficiency from 33% to 83% for devices with ZnO and InZnO photoanodes, respectively. Going beyond 15 mol% of indium, an effective electron trapping increases the charge transport resistance and, in turn, dramatically reduces charge collection efficiency. Upon implementing InZnO into an electron cascade photoanode architecture featuring an InZnO bottom layer and a ZnO top layer, a device efficiency of 5.77% and a significantly high current density of 20.4 mA cm in binary ZnO DSSCs are achieved.
Keywords: binary oxides; charge collection efficiency; flame spray pyrolysis; indium-zinc oxide photoanodes; n-type DSSCs

Binding N_2_, N_2_H_2_, N_2_H_4_ and NH_3_ to Transition Metal Sulfur Sites: Modeling Potential Intermediates of Biological N_2_ Fixation - Sellmann, Dieter; Kisch, Horst; Hille, Andreas; Rösler, Annette; Heinemann, Frank Wilhelm; Moll, Matthias; Brehm, Georg; Reiher, Markus; Heß, Bernd Artur; Bauer, W. (Chemistry - A European Journal, 2003)
UnivIS-Import:2017-03-24:Pub.2003.forsch.sonder.sfb583.bindin

Bioinspired Hybrid White Light-Emitting Diodes - Weber, Michael; Niklaus, Lukas; Pröschel, Marlene; Brana Coto, Pedro; Sonnewald, Uwe; Costa Riquelme, Rubén Dario (Advanced Materials, 2015)
The first bioinspired hybrid white-light-emitting diodes (bio-HLEDs) featuring protein cascade coatings are presented. For easy fabrication a new strategy to stabilize proteins in rubber-like material was developed. The synergy between the excellent features of fluorescent proteins and the easily processed rubber produces bio-HLEDs with less than 10% loss in luminous efficiency over 100 hours.

Blending Through-Space and Through-Bond π-π-Coupling in [2,2']-Paracyclophane-oligophenylenevinylene Molecular Wires - Wielopolski, Mateusz; Molina-Ontoria, Agustin; Schubert, Christina; Margraf, Johannes; Krokos, Evangelos; Kirschner, Johannes; Gouloumis, Andreas; Clark, Timothy; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2013)
A series of ZnP-pCp-oPPV-C60 conjugates covalently connected through [2,2′]-paracyclophane-oligophenylenevinylene (pCp-oPPV) bridges containing one, two, and three [2,2′]-paracyclophanes (pCps) has been prepared in multistep synthetic procedures involving Horner–Wadsworth–Emmons olefination reactions and/or Heck type Pd-catalyzed reactions. Molecular modeling suggests that charge transfer is effectively mediated by the pCp-oPPVs through a predominant hole-transfer mechanism. Photophysical investigation supports molecular modeling and reveals two major trends. On one hand, C60 excitation of 1, 2, and 3 leads exclusively to charge transfer between pCp and C60 to afford a ZnP-(pCp-oPPV)•+-C60•– radical ion pair state without giving rise to a subsequent charge shift to yield the ZnP•+-pCp-oPPV-C60•– radical ion pair state. On the other hand, ZnP excitation of 1, 2, and 3 results in a rather slow charge transfer between ZnP and C60, after which the ZnP•+-pCp-oPPV-C60•– radical ion pair state evolves. In temperature-dependent ZnP fluorescence experiments, which were performed in the temperature range from 273 to 338 K, two domains are discernible: low and high temperature behaviors. In the low temperature range (i.e., below 30 °C) the rate constants do not change, suggesting that a superexchange mechanism is the modus operandi. In the high temperature range (i.e., >30 °C) the rate constants increase. Moreover, we find rather strong distance dependence for 1 and 2 and weak distance dependence for 2 and 3. A damping factor of 0.145 Å–1 is derived for the former pair and 0.012 Å–1 for the latter.
EAM Import::2019-03-13

Bowl-shape electron donors with absorptions in the visible range of the solar spectrum and their supramolecular assemblies with C 60 - Isla, Helena; Grimm, Bruno; Perez, Emilio M.; Rosario Torres, M.; Angeles Herranz, M.; Viruela, Rafael; Arago, Juan; Orti, Enrique; Guldi, Dirk Michael; Martin, Nazario (Chemical Science, 2012)
We describe the synthesis, electronic, optical and photophysical properties of a family of three electron-donor bowl-shaped organic molecules that absorb light in the whole range of the visible spectrum (up to 800 nm in one case), and associate C in solution with binding constants in the range of 10 -10 M as measured from both UV-vis and fluorescence titrations in several solvents. These molecules are π-extended derivatives of tetrathiafulvalene, based on a truxene core to which two or three units of dithiole are covalently attached. The inclusion of the bulky dithiole groups is responsible for their bowl-shape geometry, which allows them to associate with C , and their electron-donor character. The symmetric derivative 1, with three dithiole units, absorbs light in the 370-520 nm range. Exchanging one of the dithiole groups by an electron-withdrawing group, ketone (2) and dicyanomethylene (3), results in an intramolecular push-pull effect that extends the absorption to nearly 700 nm in the case of 2, and up to 800 nm in the case of 3. Transient absorption measurements, supported by spectroelectrochemical and radiolytical experiments, reveal that upon photoexcitation of the 1C associate the fully charge-separated state 1 C is generated, with lifetimes of hundreds of picoseconds. Molecular-level understanding of the electronic and supramolecular properties of 1-3 is provided by density functional theory calculations. © 2012 The Royal Society of Chemistry.

Bright luminescent lithium and magnesium carbene complexes - Pinter, Piermaria; Schüßlbauer, Christoph; Watt, Fabian A.; Dickmann, Nicole; Herbst-Irmer, Regine; Morgenstern, Bernd; Grünwald, Annette; Ullrich, Tobias; Zimmer, Michael; Hohloch, Stephan; Guldi, Dirk Michael; Munz, Dominik (Chemical Science, 2021)
We report on the convenient synthesis of a CNC pincer ligand composed of carbazole and two mesoionic carbenes, as well as the corresponding lithium- and magnesium complexes. Mono-deprotonation affords a rare "naked" amide anion. In contrast to the proligand and its mono-deprotonated form, tri-deprotonated s-block complexes show bright luminescence, and their photophysical properties were therefore investigated by absorption- and luminescence spectroscopy. They reveal a quantum yield of 16% in solution at ambient temperature. Detailed quantum-chemical calculations assist in rationalizing the emissive properties based on an Intra-Ligand-Charge-Transfer (ILCT) between the carbazolido- and mesoionic carbene ligands. (Earth-)alkali metals prevent the distortion of the ligand following excitation and, thus, by avoiding non-radiative deactivation support bright luminescence.
CRIS-Team WoS Importer:2021-05-07

Bulbous gold-carbon nanodot hybrid nanoclusters for cancer therapy - Hasenöhrl, Dominik; Saha, Avishek; Strauss, Volker; Wibmer, Leonie; Klein, Stefanie; Guldi, Dirk Michael; Hirsch, Andreas (Journal of Materials Chemistry B, 2017)

Bypassing the Single Junction Limit with Advanced Photovoltaic Architectures - Lüer, Larry; Peters, Ian Marius; Le Corre, Vincent Marc; Forberich, Karen; Guldi, Dirk Michael; Brabec, Christoph (Advanced Materials, 2023)
Multijunction devices and photon up- and down-conversion are prominent concepts aimed at increasing photovoltaic efficiencies beyond the single junction limit. Integrating these concepts into advanced architectures may address long-standing issues such as processing complexity, microstructure control, and resilience against spectral changes of the incoming radiation. However, so far, no models have been established to predict the performance of such integrated architectures. Here, a simulation environment based on Bayesian optimization is presented, that can predict and virtually optimize the electrical performance of multi-junction architectures, both vertical and lateral, in combination with up- and down-conversion materials. Microstructure effects on performance are explicitly considered using machine-learned predictive models from high throughput experimentation on simpler architectures. Two architectures that would surpass the single junction limit of photovoltaic energy conversion at reasonable complexity are identified: a vertical “staggered half octave system,” where selective absorption allows the use of 6 different bandgaps, and the lateral “overlapping rainbow system” where selective irradiation allows the use of a narrowband energy acceptor with reduced voltage losses, according to the energy gap law. Both architectures would be highly resilient against spectral changes, in contrast with two terminal multi-junction architectures which are limited by Kirchhoff's law.<br

Caffeic Acid, Quercetin and 5-Fluorocytidine-Functionalized Au-Fe3O4 Nanoheterodimers for X-ray-Triggered Drug Delivery in Breast Tumor Spheroids - Klein, Stefanie; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Nanomaterials, 2021)
Au-Fe3O4 nanoheterodimers (NHD) were functionalized with the natural and synthetic anticancer drugs caffeic acid (CA), quercetin (Q) and 5-fluorocytidine (5FC). Their X-radiation dose-enhancing potential and chemotherapeutic efficacy for bimodal cancer therapy were investigated by designing multicellular tumor spheroids (MCTS) to in vitro avascular tumor models. MCTS were grown from the breast cancer cell lines MCF-7, MDA-MB-231, and MCF-10A. The MCF-7, MDA-MB-231 and MCF-10A MCTS were incubated with NHD-CA, NHD-Q, or NHD-5FC and then exposed to fractionated X-radiation comprising either a single 10 Gy dose, 2 daily single 5 Gy doses or 5 daily single 2 Gy doses. The NHD-CA, NHD-Q, and NHD-5FC affected the growth of X-ray irradiated and non-irradiated MCTS in a different manner. The impact of the NHDs on the glycolytic metabolism due to oxygen deprivation inside MCTS was assessed by measuring lactate secretion and glucose uptake by the MCTS. The NHD-CA and NHD-Q were found to act as X-radiation dose agents in MCF-7 MCTS and MDA-MB-231 MCTS and served as radioprotector in MCF-10A MCTS. X-ray triggered release of CA and Q inhibited lactate secretion and thereupon disturbed glycolytic reprogramming, whereas 5FC exerted their cytotoxic effects on both, healthy and tumor cells, after their release into the cytosol.
CRIS-Team WoS Importer:2021-06-11

Calculating the fragmentation process in quadrupole ion traps - Neugebauer, Thomas; Drewello, Thomas (International Journal of Mass Spectrometry, 2022)
The present theoretical study calculates the consequences of an ion dissociating in a quadrupole field, describing both 3D and linear ion traps. The dissociation induces a change in q-stability parameter, resulting in fragment ions abruptly changing their trajectories. This includes a change in oscillation amplitude and mean-square velocity, i.e., effective collisional temperature. While the first one can lead to ions being lost to the electrodes, the latter one can be used to determine how likely fragment ions are to be further excited. During the collisional focusing process, ions can endure internal heating, just like during the injection process. The difference here is that fragment ions start this process with already elevated internal energies. The process is calculated by making use of the well-known phase-space ellipses. It is shown that fragment ions of lower m/z in average decrease their oscillation amplitude and are thus better trapped. Only very light ions close to the LMCO have a high chance of being lost. However, lighter fragment ions in average start with higher mean-square velocities than the precursor was assumed to need to have to induce dissociation, suggesting further collisional heating. Despite the harsh collisional environment m/z ratios close to the LMCO in average have to endure, a small percentage of these ions drastically decrease their oscillation amplitude, not requiring any collisional focusing. Fragment ions of higher m/z in average increase their oscillation amplitudes, however, their low velocities make further internal heating unlikely. The used calculations have been uploaded to Github: https://github.com/NeugebauerT/ion-trap.
CRIS-Team Scopus Importer:2022-08-05

Carbazole-substituted dialkoxybenzodithiophene dyes for efficient light harvesting and the effect of alkoxy tail length - Wagner, Klaudia; Wagner, Pawel; Hasani, Fargol; Barnsley, Jonathan E.; Gordon, Keith C.; Lennert, Annkatrin; Guldi, Dirk Michael; Officer, David L. (Dyes and Pigments, 2020)
A set of new donor-π-acceptor organic PM dyes, bearing carbazole as electron donor and cyanoacrylic acid as electron acceptor, has been synthesized and fully characterized with particular focus on application in dye-sensitized solar cells (DSSCs). Importantly, a change in ‘linker’ structure resulted in the electron re-distribution in the oxidized dye, in general, and the localization of the ‘electron hole’, in particular, when compared with the MK2 benchmark. In addition, modifying the PM dyes with different lengths of alkoxy chains, that is, 1, 4, and 8 carbons, strongly influences the access of the oxidized cobalt ions to the surface affecting recombination, which had an appreciable effect on dye-sensitized solar cell performances. While the performance of the PM dyes was 15–20% lower than MK2, they are considerably easier and less expensive to synthesize, offering excellent potential for future DSSC applications.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Aggregation; Donor-pi-acceptor; Dye-sensitized solar cell; Electron hole; Metal-free organic dyes

Carbene based photochemical molecular assemblies for solar driven hydrogen generation. - Peuntinger, Katrin; Pilz, T. David; Staehle, Robert; Schaub, Markus; Kaufhold, Simon; Petermann, Lydia; Wunderlin, Markus; Goerls, Helmar; Heinemann, Frank Wilhelm; Li, Jing; Drewello, Thomas; Vos, Johannes G.; et al. (Dalton Transactions, 2014)
Novel photocatalysts based on ruthenium complexes with NHC (N-heterocyclic carbene)-type bridging ligands have been prepared and structurally and photophysically characterised. The identity of the NHC-unit of the bridging ligand was established unambiguously by means of X-ray structural analysis of a heterodinuclear ruthenium-silver complex. The photophysical data indicate ultrafast intersystem crossing into an emissive and a non-emissive triplet excited state after excitation of the ruthenium centre. Exceptionally high luminescence quantum yields of up to 39% and long lifetimes of up to 2 μs are some of the triplet excited state characteristics. Preliminary studies into the visible light driven photocatalytic hydrogen formation show no induction phase and constant turnover frequencies that are independent on the concentration of the photocatalyst. In conclusion this supports the notion of a stable assembly under photocatalytic conditions.

Carbon Dots Enabling Parts-Per-Billion Sensitive and Ultraselective Photoluminescence Lifetime-Based Sensing of Inorganic Mercury - Zdražil, Lukáš; Panáček, David; Šedajová, Veronika; Baďura, Zdeněk; Langer, Michal; Medveď, Miroslav; Paloncýová, Markéta; Scheibe, Magdalena; Kalytchuk, Sergii; Zoppellaro, Giorgio; Kment, Štěpán; Cadranel, Alejandro; et al. (Advanced Optical Materials, 2023)
One of the UN Sustainable Development Goals is to ensure universal access to clean drinking water. Among the various types of water contaminants, mercury (Hg) is considered to be one of the most dangerous ones. It is mostly its immense toxicity and vast environmental impact that stand out. To tackle the issue of monitoring water quality, a nanosensor based on carbon dots (CDs) is developed, whose surface is functionalized with carboxylic groups. CDs show Hg2+ concentration-dependent photoluminescence (PL) lifetimes along with an ultrahigh sensitivity and selectivity. The selectivity of PL quenching by Hg2+ is rationalized by performing light-induced electron paramagnetic resonance (LEPR) spectroscopy showing significant perturbation of the CD photoexcited state upon Hg2+ binding. The experimental findings are supported by time-dependent density functional theory (TD-DFT) calculations. These unveiled the emergence of a low-lying charge transfer state involving a vacant 6s orbital of Hg2+ stabilized by relativistic effects.
CRIS-Team Scopus Importer:2023-07-21
Keywords: carbon dots; colloidal nanomaterials; mercury sensing; time-resolved photoluminescence

Carbon Nanodots for All-in-One Photocatalytic Hydrogen Generation - Jana, Bikash; Reva, Yana; Scharl, Tobias; Strauss, Volker; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of the American Chemical Society, 2021)
Carbon nanodots (CNDs) were photochemically altered to produce dihydrogen under light irradiation. Within the complex structure of CNDs, photo-oxidation takes place at citrazinic acid molecular fluorophore sites. Important is the fact that the resulting CND materials have a dual function. On one hand, they absorb light, and on the other hand, they photo- and electrocatalytically produce dihydrogen from water and seawater, without any external photosensitizer or cocatalyst. Record HER activities of 15.15 and 19.70 mmol(H2) g(catalyst)-1 h-1 were obtained after 1 h of 75 mW/cm2 Xe lamp illumination, from water and seawater, respectively. This impressive performance outweighs the remaining structural uncertainties. A full-fledged physicochemical investigation based on an arsenal of steady-state and time-resolved spectroscopic characterizations together with microscopy enabled a comprehensive look into the reaction mechanism. For an efficient dihydrogen formation, a precatalytic activation by means of reduction with a sacrificial electron donor is imperative.
CRIS-Team Scopus Importer:2021-12-24

Carbon Nanodots for Charge-Transfer Processes - Margraf, Johannes T.; Strauss, Volker; Clark, Timothy; Guldi, Dirk Michael; Cadranel, Alejandro (Accounts of Chemical Research, 2019)
ConspectusIn recent years, carbon nanodots (CNDs) have emerged as an environmentally friendly, biocompatible, and inexpensive class of material, whose features sparked interest for a wide range of applications. Most notable is their photoactivity, as exemplified by their strong luminescence. Consequently, CNDs are currently being investigated as active components in photocatalysis, sensing, and optoelectronics. Charge-transfer interactions are common to all these areas. It is therefore essential to be able to fine-tune both the electronic structure of CNDs and the electronic communication in CND-based functional materials.The complex, but not completely deciphered, structure of CNDs necessitates, however, a multifaceted strategy to investigate their fundamental electronic structure and to establish structure-property relationships. Such investigations require a combination of spectroscopic methods, such as ultrafast transient absorption and fluorescence up-conversion techniques, electrochemistry, and modeling of CNDs, both in the absence and presence of other photoactive materials. Only a sound understanding of the dynamics of charge transfer, charge shift, charge transport, etc., with and without light makes much-needed improvements in, for example, photocatalytic processes, in which CNDs are used as either photosensitizers or catalytic centers, possible.This Account addresses the structural, photophysical, and electrochemical properties of CNDs, in general, and the charge-transfer chemistry of CNDs, in particular. Pressure-synthesized CNDs (pCNDs), for which citric acid and urea are used as inexpensive and biobased precursor materials, lie at the center of attention. A simple microwave-assisted thermolytic reaction, performed in sealed vessels, yields pCNDs with a fairly homogeneous size distribution of ∼1-2 nm. The narrow and excitation-independent photoluminescence of pCNDs contrasts with that seen in CNDs synthesized by other techniques, making pCNDs optimal for in-depth physicochemical analyses. The atomistic and electronic structures of CNDs were also analyzed by quantum chemical modeling approaches that led to a range of possible structures, ranging from heavily functionalized, graphene-like structures to disordered amorphous particles containing small sp 2 domains.Both the electron-accepting and -donating performances of CNDs make the charge-transfer chemistry of CNDs rather versatile. Both covalent and noncovalent synthetic approaches have been explored, resulting in architectures of various sizes. CNDs, for example, have been combined with molecular materials ranging from electron-donating porphyrins and extended tetrathiafulvalenes to electron-accepting perylendiimides, or nanocarbon materials such as polymer-wrapped single-walled carbon nanotubes. In every case, charge-separated states formed as part of the reaction cascades initiated by photoexcitation. Charge-transfer assemblies including CNDs have also played a role in technological applications: for example, a proof-of-concept dye-sensitized solar cell was designed and tested, in which CNDs were adsorbed on the surface of mesoporous anatase TiO 2 . The wide range of reported electron-donor-acceptor systems documents the versatility of CNDs as molecular building blocks, whose electronic properties are tunable for the needs of emerging technologies.
CRIS-Team Scopus Importer:2019-05-02

Carbon Nanodots: Supramolecular Electron Donor-Acceptor Hybrids Featuring Perylenediimides - Strauß, Volker; Margraf, Johannes; Dirian, Konstantin; Syrgiannis, Zois; Prato, Maurizio; Wessendorf, Cordula; Hirsch, Andreas; Clark, Timothy; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2015)
We describe the formation of charge-transfer complexes that feature electron-donating carbon nanodots (CND) and electron-accepting perylenediimides (PDI). The functionalities of PDIs have been selected to complement those of CNDs in terms of electrostatic and -stacking interactions based on oppositely charged ionic head groups and extended -systems, respectively. Importantly, the contributions from electrostatic interactions were confirmed in reference experiments, in which stronger interactions were found for PDIs that feature positively rather than negatively charged head groups. The electronic interactions between the components in the ground and excited state were characterized in complementary absorption and fluorescence titration assays that suggest charge-transfer interactions in both states with binding constants on the order of 8x10(4)M(-1) (25Lg(-1)). Selective excitation of the two components in ultrafast pump probe experiments gave a 210ps lived charge-separated state.
Keywords: carbon nanodots; charge transfer; donor-acceptor compounds; perylenediimides; transient absorption

Carbon Nanodots: Toward a Comprehensive Understanding of Their Photoluminescence - Strauß, Volker; Margraf, Johannes; Dolle, Christian; Butz, Benjamin; Nacken, Thomas; Walter, Johannes; Bauer, Walter; Peukert, Wolfgang; Spiecker, Erdmann; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
We report the characterization of carbon nanodots (CNDs) synthesized under mild and controlled conditions, that is, in a microwave reactor. The CNDs thus synthesized exhibit homogeneous and narrowly dispersed optical properties. They are thus well suited as a testbed for studies of the photophysics of carbon-based nanoscopic emitters. In addition to steady-state investigations, time-correlated single-photon counting, fluorescence up-conversion, and transient pump probe absorption spectroscopy were used to elucidate the excited-state dynamics. Moreover, quenching the CND-based emission with electron donors or acceptors helped shed light on the nature of individual states. Density functional theory and semiempirical configuration-interaction calculations on model systems helped understand the fundamental structure-property relationships for this novel type of material.

Carbon Nanohorn-based electrolyte for Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Casillas Pacheco, Ruben; Kohler, Florian; Wasserscheid, Peter; Prato, Maurizio; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
For the first time, carbon nanohorns were implemented into solid-state electrolytes for highly efficient solid-state and quasi-solid-state DSSCs. They feature an effective catalytic behavior towards the reduction of I3- and enhance the I3- diffusivity into the electrolyte. In a final device, solar cells with 7.84% efficiency at room temperature were achieved. As a matter of fact, this is the highest reported efficiency for nanocarbon-based electrolytes up to date.

Carbon Nanohorns as Integrative Materials for Efficient Dye-Sensitized Solar Cells - Costa Riquelme, Rubén Dario; Feihl, Sebastian; Kahnt, Axel; Gambhir, Sanjeev; Officer, David L.; Wallace, Gordon G.; Lucio, Mara Isabel; Herrero, Mara Antonia; Vzquez, Ester; Syrgiannis, Zois; Prato, Maurizio; Guldi, Dirk Michael (Advanced Materials, 2013)
Different nanocarbons, that is, single-wall carbon nanotubes, graphene, single-wall carbon nanohorns (SWCNHs), and their respective oxidized analogs have been used to fabricate novel doped TiO2 electrodes for DSSCs. Our results indicate that all of the nanocarbons significantly enhance the device characteristics when compared to standard TiO2 electrodes. Overall, our most outstanding finding is that SWCNH derivatives are also a plausible material for developing highly-efficient DSSCs.

Carbon nanomaterials as integrative components in dye-sensitized solar cells - Costa, Ruben Dario; Guldi, Dirk Michael (Nanocarbon-Inorganic Hybrids: Next Generation Composites for Sustainable Energy Applications, 2014)
One of the major challenges that humanity faces is the development of renewable energy resources to secure our current lifestyle. In fact, linking problems such as pollution and globalwarming to the use of fossil fuels as an energy source is eye opening [1-3]. In this context, different renewable energy sources such as windmill-powered plants, hydropower, biomass production, geothermal power, and solar energy are currently under scrutiny. Among the aforementioned, solar energy bears one of the greatest potentials for securing the current energy supply. This notion is based on the amount of energy that reaches the earth’s surface at zero costs and at continuous supply. Notably, one hour of solar irradiation covers more than theworld’s current energy demand for a complete year. As such, photovoltaic devices/solar cells are considered as a superior means of energy harvesting [2, 4, 5].
CRIS-Team Scopus Importer:2023-03-07

Carbon nanostructures for energy - Martín, Nazario; Guldi, Dirk Michael; Hirsch, Andreas (Energy and Environmental Science, 2011)

Carbon nanostructures for solar energy conversion schemes - Guldi, Dirk Michael; Sgobba, Vito (Chemical Communications, 2011)
Developing environmentally friendly, renewable energy is one of the challenges to society in the 21st century. One of the renewable energy technologies is solar energy conversion - a technology that directly converts daylight into electricity. This highlight surveys recent breakthroughs in the field of implementing carbon nanostructures - fullerenes (0D), carbon nanotubes (1D), carbon nanohorns, and graphene (2D) - into solar energy conversion schemes, that is, bulk heterojunction and dye-sensitized solar cells. © The Royal Society of Chemistry 2011.

Carbon nanostructures - Introducing the latest web themed issue - Martin, Nazario; Guldi, Dirk Michael; Echegoyen, Luis (Chemical Communications, 2011)

Carbon nanotubes dispersed in aqueous solution by ruthenium(II) polypyridyl complexes - Huang, Kewei; Saha, Avishek; Dirian, Konstantin; Jiang, Chengmin; Chu, Pin-Lei E.; Tour, James M.; Guldi, Dirk Michael; Marti, Angel A. (Nanoscale, 2016)
Cationic ruthenium(ii) polypyridyl complexes with appended pyrene groups have been synthesized and used to disperse single-walled carbon nanotubes (SWCNT) in aqueous solutions. To this end, planar pyrene groups enable association by means of π-stacking onto carbon nanotubes and, in turn, the attachment of the cationic ruthenium complexes. Importantly, the ionic nature of the ruthenium complexes allows the formation of stable dispersions featuring individualized SWCNTs in water as confirmed in a number of spectroscopic and microscopic assays. In addition, steady-state photoluminescence spectroscopy was used to probe the excited state interactions between the ruthenium complexes and SWCNTs. These studies show that the photoluminescence of both, that is, of the ruthenium complexes and of SWCNTs, are quenched when they interact with each other. Pump-probe transient absorption experiments were performed to shed light onto the nature of the photoluminescence quenching, showing carbon nanotube-based bands with picosecond lifetimes, but no new bands which could be unambigously assigned to photoinduced charge transfer process. Thus, from the spectroscopic data, we conclude that quenching of the photoluminescence of the ruthenium complexes is due to energy transfer to proximal SWCNTs.
CRIS-Team Scopus Importer:2023-03-07

Cascades of energy and electron transfer in a panchromatic absorber - Joseph, Jan; Bauroth, Stefan; Charisiadis, Asterios; Charalambidis, Georgios; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Nanoscale, 2022)
The investigation of molecular model systems is fundamental towards a deeper understanding of key photochemical steps in natural photosynthesis. Herein, we report an entirely non-covalent triad consisting of boron dipyrromethene (BDP), porphyrin (ZnP), and fullerene (C60). Non-covalent binding motifs such as an amidinium-carboxylate salt bridge as well as axial pyridyl-metal coordination offer substantial electronic coupling and establish efficient pathways for photoactivated energy and electron transfer processes along a well-tuned gradient. Experimental findings from steady-state and time-resolved spectroscopic assays, as well as (spectro-)electrochemical measurements corroborate the formation of BDP|ZnP|C60 in solution, on one hand, and significant communication in the excited states, on the other hand. BDP acts as an energy harvesting antenna towards ZnP, which eventually undergoes charge separation with C60 by electron transfer from ZnP to C60. Notably, full spectral deconvolution of the transient species was achieved, supporting the successful self-assembly as well as giving a clear view onto the occurring photophysical processes and their spectral footprints upon photoexcitation.
CRIS-Team Scopus Importer:2022-07-08

Catalyzing Singlet Fission by Transition Metals: Second versus Third Row Effects - Hou, Yuxuan; Papadopoulos, Ilias; Bo, Yifan; Wollny, Anna-Sophie; Ferguson, Michael J.; Mai, Lukas; Tykwinski, Rik R.; Guldi, Dirk Michael (Precision Chemistry, 2023)
The synthesis and characterization of platinum(II) and palladium(II) complexes bearing two (dimers Pt(Lpc)2Cl2 and Pd(Lpc)2Cl2), one (monomers Pt(Lpc)(Lref)Cl2 and Pd(Lpc)(Lref)-Cl2), or no (reference compounds Pt(Lref)2Cl2 and Pd(Lref)2Cl2) pentacene-based pyridyl ligands are presented. Photophysical properties of the dimers are probed by means of steady-state and time-resolved transient absorption measurements in comparison to the monomer and model compounds. Our results document that despite enhanced spin-orbit coupling from the presence of heavy atoms, intramolecular singlet fission (iSF) is not challenged by intersystem crossing. iSF thus yields correlated triplet pairs and even uncorrelated triplet excited states upon decoherence. Importantly, significant separation of the two pentacenyl groups facilitates decoupling of the two chromophores. Furthermore, the mechanism of iSF is altered depending on the respective metal center, that is, Pt(II) versus Pd(II). The dimer based on Pt(II), Pt(Lpc)2Cl2, exhibits a direct pathway for the iSF and forms a correlated triplet pair with singlet-quintet spin-mixing within 10 ns in variable solvents. On the other hand, the dimer based on Pd(II), Pd(Lpc)2Cl2, leads to charge transfer mixing during the population of the correlated triplet pair that is dependent on solvent polarity. Moreover, Pd(Lpc)2Cl2 gives rise to a stable equilibrium between singlet and quintet correlated triplet pairs with lifetimes of up to 170 ns. Inherent differences in the size and polarizability, when contrasting platinum(II) with palladium(II), are the most likely rationale for the underlying trends.
CRIS-Team Scopus Importer:2024-12-16
Keywords: electronic coupling; metal complexes; pentacene dimers; singlet fission; ultrafast spectroscopy

Catching metallic nitride endohedral fullerenes in organic and aqueous media - Strauß, Volker; Radhakrishnan, Shankara Gayathri; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2016)
Two bis-tetraphenylporphyrin tweezers-like conjugates bearing different linkers have been characterized by means of electrochemical and photophysical methods. The thrust of this work was the complexation of these bis-porphyrins with C60 and metallic nitride endohedral fullerenes (MNEF) like Sc3N@C80 in organic and in aqueus media - studied by a combination of steady-state and time-resolved spectroscopies. In the context of charge separation evidence for the formation of the 1a(•+)-Sc3N@C80 (•-) and 1c(•+)-Sc3N@C80(•-) charge separated states in organic and aqueous media, respectively, came from transient absorption spectroscopy. Multi-wavelength analyses afforded charge separated state lifetimes of around 400 ps.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charge-transfer; metallic nitride endohedral fullerenes; porphyrin; time-resolved spectroscopy; tweezers

Celebrating 10 years of Nanoscale - Niederberger, Markus; Stellacci, Francesco; Bai, Chunli; Guldi, Dirk Michael (Nanoscale, 2019)
CRIS-Team Scopus Importer:2019-11-05

Chain propagation determines the chemo- And regioselectivity of alkyl radical additions to C-O: Vs. C-C double bonds - Paulisch, Tiffany O.; Strieth-Kalthoff, Felix; Henkel, Christian; Pitzer, Lena; Guldi, Dirk Michael; Glorius, Frank (Chemical Science, 2020)
Investigations into the selectivity of intermolecular alkyl radical additions to C-O- vs. C-C-double bonds in α,β-unsaturated carbonyl compounds are described. Therefore, a photoredox-initiated radical chain reaction is explored, where the activation of the carbonyl-group through an in situ generated Lewis acid-originating from the substrate-enables the formation of either C-O or the C-C-addition products. α,β-Unsaturated aldehydes form selectively 1,2-, while esters and ketones form the corresponding 1,4-addition products exclusively. Computational studies lead to reason that this chemo- and regioselectivity is determined by the consecutive step, i.e. an electron transfer, after reversible radical addition, which eventually propagates the radical chain.
CRIS-Team Scopus Importer:2020-02-04

Charge and energy transfer processes in ruthenium(II) phthalocyanine based electron donor-acceptor materials - Implications for solar cell performance - Spänig, Fabian; Lopez-Duarte, Ismael; Fischer, Markus K. R.; Victoria Martinez-Diaz, M.; Baeuerle, Peter; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
Six supramolecular electron donor-acceptor hybrids, based on a ruthenium(II) phthalocyanine [RuPc] coordinating different dendritic oligothiophene (DOT) ligands [Py-nT] (n = 3, 9, 21) in either one [RuPcCO(Py-nT)] or two [RuPc(Py-nT) ] axial positions, have been characterized by standard spectroscopic methods and their photophysical behavior has been established by using ultrafast and fast time-resolved techniques. Based on the spectrochemical and radiolytically generated [Py-nT] (i.e., one-electron reduction of [Py-nT]) and [RuPcCO(Py) or RuPc(Py) ] (i.e., one-electron oxidation of [RuPcCO(Py) or RuPc(Py) ]) features, the deactivation processes were assigned to a solvent independent energy transfer in RuPcCO(Py-3T) and RuPc(Py-3T) and a strongly solvent dependent charge transfer mechanism, which competes with the energy transfer and the intersystem crossing for RuPcCO(Py-9T), RuPc(Py-9T) , RuPcCO(Py-21T) and RuPc(Py-21T) . © 2011 The Royal Society of Chemistry.

Charge carrier dynamics in a ternary bulk heterojunction system consisting of P3HT, fullerene, and a low bandgap polymer - Koppe, Markus; Egelhaaf, Hans-Joachim; Clodic, Ewan; Morana, Mauro; Lueer, Larry; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
The photoresponse of P3HT:PC BM based organic solar cells can be enhanced by blending the bulk heterojunction with the low band gap polymer Si-PCPDTBT. Organic solar cells containing the resulting ternary blend as the photoactive layer deliver short circuit currents of up to 15.5 mA cm. Morphological studies show modest phase separation without the perturbation of the crystallinity of the P3HT:PC BM matrix, in accordance with the measured acceptable fill factors. Picosecond time-resolved pump-probe spectroscopy reveals that the sensitization of P3HT:PC BM with Si-PCPDTBT involves the transfer of photogenerated positive polarons from the low band gap polymer to P3HT within few hundreds of picoseconds. Intensity dependent experiments in combination with global fitting show that the charge transfer from Si-PCPDTBT to P3HT competes with non-geminate charge carrier recombination of the holes in the Si-PCPDTBT phase with electrons in the PC BM phase, both processes being of diffusive nature. At excitation densities corresponding to steady state conditions under one sun, modelling predicts hole transfer efficiencies exceeding 90%, in accordance with IQE measurements. At higher pump intensities, bimolecular recombination suppresses the hole transfer process effectively. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Charge-Gating Dibenzothiophene-S,S-dioxide Bridges in Electron Donor-Bridge-Acceptor Conjugates - Yzambart, Gilles; Zieleniewska, Anna; Bauroth, Stefan; Clark, Timothy; Bryce, Martin R.; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2017)
The synthesis of a series of new electron donor bridge acceptor (D-B-A) conjugates (18-20) comprising electron-donating zinc(II) porphyrins (ZnPs) and electron-accepting fullerenes (C(60)s) connected through various co-oligonier bridges containing both dibenzothiophene-S,S-dioxide and fluorene units is reported. Detailed investigations using cyclic voltarnmetry, absorption, fluorescence, and femto/nanosecond transient absorption spectroscopy in.combination with quantum,chemical calculations have enabled us to develop a detailed mechanistic view of the charge-transfer processes that follow photoexcitation of ZnP, the bridge, or C-60. Variations in the dynamics of charge separation, charge recombination, and charge transfer gating are primarily consequences of the electronic properties of the co-oligomer bridges, including their electron affinity and the energy levels of the excited states. In particular, placing one dibenothiophene-S,S-dioxide building block at the center of the molecular bridge flanked by two fluorene building blocks, as in 20, favors hole rather than electron transfer between the remote electron donors and acceptors, as demonstrated by exciting C-60 rather than ZnP. In 18 and 19, in which one dibenzothiophene-S,S-dioxide and one throrene building block constitute the molecular bridge, photoexcitation of either ZnP or C-60 results in both hole and electron transfer. Dibenzothiophene-S,S-dioxide is thug shown to be an excellent building block for probing how subtle structural and electronic variations in the bridge affect unidirectional charge transport in D-B-A conjugates. The experimental results are supported by computational calculations.

Charge separation in a covalently-linked phthalocyanine-oligo(p- phenylenevinylene)-C60 system. Influence of the solvent polarity - Cid, Juan-Jose; Kahnt, Axel; Vazquez, Purificacion; Guldi, Dirk Michael; Torres, Tomas (Journal of Inorganic Biochemistry, 2012)
A photo- and redoxactive system ZnPc-oPPV-C 2, in which the photoexcited state electron donor - zinc phthalocyanine - and the ground state electron acceptor - C - are connected by a oligo(p- phenylenevinylene) (oPPV) spacer, has been synthesized in a multi-step synthesis by means of two consecutive Wadsworth-Horner-Emmons and a dipolar 1,3-cycloaddition reactions as key steps. The simpler system ZnPc-C 1 has also been prepared as a reference model for photophysical studies. In this regards, the photophysical investigations by means of fluorescence, flash photolysis, and transient-absorption spectroscopy have manifested a clear dependence between charge transfer kinetics and spatial arrangement. In both systems, intramolecular charge separation evolves from the photoexcited ZnPc and yields the ZnPc /C radical ion pairs. Interestingly, the ZnPc /C radical ion pair lifetimes and quantum yields are strongly impacted by the solvent polarity and the distance. To this end, maximum radical ion pair lifetimes of 2900 and 5530 ps were found in anisol for 1 and 2, respectively. © 2011 Elsevier Inc. All rights reserved.

Charge transfer events in semiconducting single-wall carbon nanotubes - Oelsner, Christian; Antonia Herrero, M.; Ehli, Christian; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Electron-donating ferrocene units have been attached to SWNTs, with different degrees of functionalization. By means of a complementary series of novel spectroscopic techniques (i.e., steady-state and time-resolved), we have documented that mutual interactions between semiconducting SWNT and the covalently attached electron donor (i.e., ferrocene) lead, in the event of photoexcitation, to the formation of radical ion pairs. In the accordingly formed radical ion pairs, oxidation of ferrocene and reduction of SWNT were confirmed by spectroelectrochemistry. It is, however, shown that only a few semiconducting SWNTs [i.e., (9,4), (8,6), (8,7), and (9,7)] are susceptible to photoinduced electron transfer processes. These results are of relevant importance for the development of SWNT-based photovoltaics. © 2011 American Chemical Society.

Charge-transfer in a π-stacked fullerene porphyrin dyad: Evidence for back electron transfer in the 'Marcus-inverted' region - Guldi, Dirk Michael; Luo, Chuping; Prato, Maurizio; Dietel, Elke; Hirsch, Andreas (Chemical Communications, 2000)
The 'Marcus-inverted' region for BET in a π-π stacked fullerene- porphyrin dyad was determined based on (i) the photoactivation of an intramolecular ET in a variety of solvents and (ii) the formation of a highly energetic charge-separated state.

Charge transfer in graphene quantum dots coupled with tetrathiafulvalenes - Scharl, Tobias; Ferrer-Ruiz, Andres; Saura-Sanmartin, Adrian; Rodriguez-Perez, Laura; Angeles Herranz, M.; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2019)
Water-soluble fluorescent graphene quantum dots have been successfully prepared through a top-down approach, that is, starting with graphite, and covalently functionalizing it with π-extended tetrathiafulvalene. Charge transfer investigations reveal noticeably slower charge recombination when compared with exTTF nanoconjugates featuring carbon nanodots, for which a larger presence of trap states is observed.
CRIS-Team Scopus Importer:2019-06-07

Charge transfer in sapphyrin-fullerene hybrids employing dendritic ensembles - Grimm, Bruno; Karnas, Elizabeth; Brettreich, Michael; Ohta, Kiminori; Hirsch, Andreas; Guldi, Dirk Michael; Torres, Tomas; Sessler, Jonathan L. (Journal of Physical Chemistry B, 2010)
A new approach to creating noncovalent charge transfer ensembles is described. It is based on two components that are linked through anion-receptor interactions. The first component is sapphyrin, a pentapyrrolic expanded porphyrin, which is capable of carboxylate anion recognition and more importantly can act as a photodonor when irradiated in the presence of a suitable electron acceptor. The second component is the electron acceptor and consists of one of two different C fullerene cores functionalized with multiple carboxylate anion groups arranged in a dendritic fashion. Depending on the specific choice of the fullerene carboxylate anion dendrimer employed in ensemble construction, 1:1 or 1:2 complexes are formed when the C cores are titrated with sapphyrin. The resulting noncovalent arrays undergo sapphyrin-to-fullerene electron transfer when irradiated with 387 nm light. This gives rise to charge separated states with lifetimes of ca. 470 and 600 ps in the case of the 1:1 and 1:2 sapphyrin-fullerene ensembles, respectively. © 2010 American Chemical Society.

Charge transfer interactions in self-assembled single walled carbon nanotubes/Dawson-Wells polyoxometalate hybrids - Bosch-Navarro, Concha; Matt, Benjamin; Izzet, Guillaume; Romero-Nieto, Carlos; Dirian, Konstantin; Raya, Andres; Molina, Sergio I.; Proust, Anna; Guldi, Dirk Michael; Marti-Gastaldo, Carlos; Coronado, Eugenio (Chemical Science, 2014)
We demonstrate the success in self-assembling pyrene-modified Dawson-Wells-type polyoxometalates (POMs) with single walled carbon nanotubes (SWCNTs) by means of π-π interactions. In this context, the immobilization of POMs onto SWCNTs is corroborated by aberration-corrected high-resolution electron microscopy, thermogravimetric analysis, and Raman spectroscopy. From steady-state and time-resolved photophysical techniques we derived evidence for mutual interactions between SWCNTs and POMs in the excited states. The latter are the inception to a charge transfer from the SWCNTs to the POMs. Our results corroborate the suitability of POM-SWCNTs assemblies for photoactive molecular devices. This journal is
CRIS-Team Scopus Importer:2023-03-07

Charge Transport through Molecules: Organic Nanocables for Molecular Electronics - Wielopolski, Mateusz; Guldi, Dirk Michael; Clark, Timothy; Martín, Nazario (Wiley-VCH Verlag GmbH & Co. KGaA, 2011)

Chemical functionalization and characterization of graphene-based materials - Bottari, Giovanni; Angeles Herranz, Ma; Wibmer, Leonie; Volland, Michel; Rodriguez-Perez, Laura; Guldi, Dirk Michael; Hirsch, Andreas; Martin, Nazario; D'Souza, Francis; Torres, Tomas (Chemical Society Reviews, 2017)
Graphene-based materials (GBMs), with graphene, their most known member, at the head, constitute a large family of materials which has aroused the interest of scientists working in different research fields such as chemistry, physics, or materials science, to mention a few, arguably as no other material before. In this review, we offer a general overview on the most relevant synthetic approaches for the covalent and non-covalent functionalization and characterization of GBMs. Moreover, some representative examples of the incorporation into GBMs of electroactive units such as porphyrins, phthalocyanines, or ferrocene, among others, affording electron donor-acceptor (D-A) hybrids are presented. For the latter systems, the photophysical characterization of their ground- and excited-state features has also been included, paying particular attention to elucidate the fundamental dynamics of the energy transfer and charge separation processes of these hybrids. For some of the presented architectures, their application in solar energy conversion schemes and energy production has been also discussed. Graphene-based materials (GBMs), with graphene, their most known member, at the head, constitute a large family of materials which has aroused the interest of scientists working in different research fields such as chemistry, physics, or materials science, to mention a few, arguably as no other material before. In this review, we offer a general overview on the most relevant synthetic approaches for the covalent and non-covalent functionalization and characterization of GBMs. Moreover, some representative examples of the incorporation into GBMs of electroactive units such as porphyrins, phthalocyanines, or ferrocene, among others, affording electron donor-acceptor (D-A) hybrids are presented. For the latter systems, the photophysical characterization of their ground- and excited-state features has also been included, paying particular attention to elucidate the fundamental dynamics of the energy transfer and charge separation processes of these hybrids. For some of the presented architectures, their application in solar energy conversion schemes and energy production has been also discussed.

Chemistry at the rim: Differentiation of isomeric open-cage fullerenes by MALDI-LIFT and ESI-MS/MS - Nye, Leanne C.; Hitzenberger, Jakob; Roubelakis, Manolis M.; Orfanopoulos, Michael; Drewello, Thomas (International Journal of Mass Spectrometry, 2019)
Isomeric open-cage fullerenes ( OCFs) are studied by MALDI-LIFT. The two types of isomers feature different connectivities of the heteroatoms at the rim of the orifice to the fullerene cage. The molecular ions (radical cations, M+.) are generated by electron transfer MALDI, using DCTB as the matrix. The resulting LIFT spectra are indistinguishable. The alternative use of pencil lead is found inferior as a matrix but proves an exceptionally facile method of creating sodium and potassium adducts. The fragmentation of these metallated OCFs reveals different fragmentation pathways allowing the differentiation of the OCF isomers. This is evidently caused by the different interactions of the metal cation with the heteroatoms at the rim of the orifice. Additionally, the influence of the functionalization and isomer structure on the sodium ion affinity (SIA) is analysed by the kinetic method investigating the dissociations of sodium-bound hetero-dimers in electrospray ionization/ collision-induced dissociation (ESI-CID) experiments. (C) 2018 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Cholesteryl oleate-appended phthalocyanines as potential photosensitizers in the treatment of leishmaniasis - Sanchez Contreras, Laura E.; Zirzlmeier, Johannes; Kirner, Sabrina; Setaro, Francesca; Martinez, Fernando; Lozada, Stefany; Escobar, Patricia; Hahn, Uwe; Guldi, Dirk Michael; Torres, Tomas (Journal of Porphyrins and Phthalocyanines, 2015)
Two phthalocyanines (Pcs) with either a zinc or a ruthenium metal at the center of the macrocycle have been functionalized by a cholesteryl oleate moiety. The potential photosensitizers (PSs) for the treatment of cutaneous leishmaniasis have been studied on their photophysical properties and their ability to generate singlet oxygen. These experiments corroborate that solvent mixtures containing variable ratios of THF and water impact the excited state deactivation. The compounds were used preloaded into LDL particles and their phototoxic activity was evaluated in a preliminary way.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cholesterol; leishmaniasis; phthalocyanines; singlet oxygen; steroids

Choosing the right nanoparticle size-designing novel ZnO electrode architectures for efficient dye-sensitized solar cells - Pfau, Markus; Kunzmann, Andreas; Segets, Doris; Peukert, Wolfgang; Wallace, Gordon G.; Officer, David L.; Clark, Timothy; Costa, Ruben Dario; Guldi, Dirk Michael (Journal of Materials Chemistry A, 2017)
A novel concept for constructing optimized ZnO-based photoanodes as integrative components of dye-sensitized solar cells (DSSCs) is realized by deploying differently sized nanoparticles, ranging from 2 to 10 nm, together with commercially available 20 nm nanoparticles. The 2 nm nanoparticles were used to construct an efficient buffer layer for transparent electrodes based on 10 nm nanoparticles, resulting in a relative increase of device efficiency from 1.8 to 3.0% for devices without and with a buffer layer, respectively. A mixture of 10 and 20 nm nanoparticles was optimized to maximize the diffuse reflection and to minimize the charge transport resistance in a light-scattering layer. This optimization resulted in a homogenous layer of more than 15 mm that provided a device efficiency of 3.3%. The buffer layer, transparent electrode, and light-scattering electrode, were then combined to give an overall efficiency of around 5%. Thus, this work demonstrates that varying the electrode architecture with nanoparticles of different diameters is a powerful strategy for improving the overall efficiency of ZnO-based DSSCs.

Chromoendoscopy in magnetically guided capsule endoscopy - Mewes, Philip; Foertsch, Stefan; Juloski, Aleksandar Lj; Angelopoulou, Elli; Gölder, Stefan; Guldi, Dirk Michael; Hornegger, Joachim; Messmann, Helmut (Biomedical Engineering Online, 2013)
Background: Diagnosis of intestinal metaplasia and dysplasia via conventional endoscopy is characterized by low interobserver agreement and poor correlation with histopathologic findings. Chromoendoscopy significantly enhances the visibility of mucosa irregularities, like metaplasia and dysplasia mucosa. Magnetically guided capsule endoscopy (MGCE) offers an alternative technology for upper GI examination. We expect the difficulties of diagnosis of neoplasm in conventional endoscopy to transfer to MGCE. Thus, we aim to chart a path for the application of chromoendoscopy on MGCE via an ex-vivo animal study.Methods: We propose a modified preparation protocol which adds a staining step to the existing MGCE preparation protocol. An optimal staining concentration is quantitatively determined for different stain types and pathologies. To that end 190 pig stomach tissue samples with and without lesion imitations were stained with different dye concentrations. Quantitative visual criteria are introduced to measure the quality of the staining with respect to mucosa and lesion visibility. Thusly determined optimal concentrations are tested in an ex-vivo pig stomach experiment under magnetic guidance of an endoscopic capsule with the modified protocol.Results: We found that the proposed protocol modification does not impact the visibility in the stomach or steerability of the endoscopy capsule. An average optimal staining concentration for the proposed protocol was found at 0.4% for Methylene blue and Indigo carmine. The lesion visibility is improved using the previously obtained optimal dye concentration.Conclusions: We conclude that chromoendoscopy may be applied in MGCE and improves mucosa and lesion visibility. Systematic evaluation provides important information on appropriate staining concentration. However, further animal and human in-vivo studies are necessary. © 2013 Mewes et al.; licensee BioMed Central Ltd.

Chromophore Multiplication To Enable Exciton Delocalization and Triplet Diffusion Following Singlet Fission in Tetrameric Pentacene - Hetzer, Constantin; Basel, Bettina; Kopp, Sebastian M.; Hampel, Frank; White, Fraser J.; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Angewandte Chemie International Edition, 2019)
A tetrameric pentacene, PT, has been used to explore the effects of exciton delocalization on singlet fission (SF). For the first time, triplet decorrelation through intramolecular triplet diffusion was observed following SF. Transient absorption spectroscopy was used to examine different decorrelation mechanisms (triplet diffusion versus structural changes) for PT and its dimeric equivalent PD on the basis of the rate and activation barrier of the decorrelation step. Charge-separation experiments using tetracyano-p-quinodimethane (TCNQ) to quench triplet excitons formed through SF demonstrate that enhanced intersystem crossing, that is, spin catalysis, is a widely underestimated obstacle to quantitative harvesting of the SF products. The importance of spatial separation of the decorrelated triplet states is emphasized, and independent proof that the decorrelated triplet pair state consists of two (T-1) states per molecule is provided.
CRIS-Team WoS Importer:2019-10-04

Chromoselective Synthesis of Sulfonyl Chlorides and Sulfonamides with Potassium Poly(heptazine imide) Photocatalyst - Markushyna, Yevheniia; Schüßlbauer, Christoph; Ullrich, Tobias; Guldi, Dirk Michael; Antonietti, Markus; Savateev, Aleksandr (Angewandte Chemie International Edition, 2021)
Among external stimuli used to promote a chemical reaction, photocatalysis possesses a unique one-light. Photons are traceless reagents that provide an exclusive opportunity to alter chemoselectivity of the photocatalytic reaction varying the color of incident light. This strategy may be implemented by using a sensitizer capable to activate a specific reaction pathway depending on the excitation light. Herein, we use potassium poly(heptazine imide) (K-PHI), a type of carbon nitride, to generate selectively three different products from S-arylthioacetates simply varying the excitation light and otherwise identical conditions. Namely, arylchlorides are produced under UV/purple, sulfonyl chlorides with blue/white, and diaryldisulfides at green to red light. A combination of the negatively charged polyanion, highly positive potential of the valence band, presence of intraband states, ability to sensitize singlet oxygen, and multi-electron transfer is shown to enable this chromoselective conversion of thioacetates.
CRIS-Team WoS Importer:2021-08-20

Cobaloxime Complex Salts: Synthesis, Patterning on Carbon Nanomembranes and Heterogeneous Hydrogen Evolution Studies - Oswald, Eva; Gaus, Anna Laurine; Kund, Julian; Küllmer, Maria; Romer, Jan; Weizenegger, Simon; Ullrich, Tobias; Mengele, Alexander K.; Petermann, Lydia; Leiter, Robert; Unwin, Patrick R.; Kaiser, Ute; et al. (Chemistry - A European Journal, 2021)
Cobaloximes are promising, earth-abundant catalysts for the light-driven hydrogen evolution reaction (HER). Typically, these cobalt(III) complexes are prepared in situ or employed in their neutral form, for example, [Co(dmgH)2(py)Cl], even though related complex salts have been reported previously and could, in principle, offer improved catalytic activity as well as more efficient immobilization on solid support. Herein, we report an interdisciplinary investigation into complex salts [Co(dmgH)2(py)2]+[Co(dmgBPh2)2Cl2]−, (Formula presented.) and [Co(dmgH)2(py)2]+BArF−. We describe their strategic syntheses from the commercially available complex [Co(dmgH)2(py)Cl] and demonstrate that these double and single complex salts are potent catalysts for the light-driven HER. We also show that scanning electrochemical cell microscopy can be used to deposit arrays of catalysts [Co(dmgH)2(py)2]+[Co(dmgBPh2)2Cl2]−, (Formula presented.) and [Co(dmgH)2(py)Cl] on supported and free-standing amino-terminated ∼1-nm-thick carbon nanomembranes (CNMs). Photocatalytic H2 evolution at such arrays was quantified with Pd microsensors by scanning electrochemical microscopy, thus providing a new approach for catalytic evaluation and opening up novel routes for the creation and analysis of “designer catalyst arrays”, nanoprinted in a desired pattern on a solid support.
CRIS-Team Scopus Importer:2021-11-26
Keywords: catalyst nanoarrays; cobaloximes; in situ amperometric H; photocatalysis; SECCM

Coexistence of MLCT Excited States of Different Symmetry upon Photoexcitation of a Single Molecular Species - Oviedo, Paola S.; Pieslinger, German E.; Baraldo, Luis M.; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2019)
Photoexcitation of [Ru(tpy)(bpy)(mu-CN)Ru-(py)(4)Cl](2+) ([RuRu](2+)) at 387 nm results in the population of two (MLCT)-M-3 excited states of different symmetry that coexist on the nanosecond scale. Common to both states is an excited electron in a tpy-based orbital. Their configuration differs in the position of the hole. In one excited state, (3)MLCTz, the hole sits in an orbital parallel to the intermetallic axis allowing for a strong metal-metal electronic interaction. As a result, (3)MLCTz is highly delocalized over both metal centers and shows an intense photoinduced intervalence charge transfer (PIIVCT) NIR signature. In the other excited state, (3)MLCTxy, the hole is localized in an orbital perpendicular to the intermetallic axis and hence, significant intermetallic coupling is absent. This state shows no PIIVCT in the NIR and its spectrum is very similar to the one observed [Ru(tpy)(bpy)(CN)](+) reference. Both (MLCT)-M-3 excited states have nanosecond lifetimes. The intervening energy barrier for a hole reconfiguration between the two different (MLCT)-M-3 excited states offers the opportunity to exploit wave functions of different symmetry before either the interconversion between them or the decay to the ground state is operative.
CRIS-Team WoS Importer:2019-03-06

Collecting up to 115% of Singlet-Fission Products by Single-Walled Carbon Nanotubes - Menon, Arjun; Papadopoulos, Ilias; Harreiß, Christina; Mora-Fuentes, Juan P.; Cortizo-Lacalle, Diego; Mateo-Alonso, Aurelio; Spiecker, Erdmann; Guldi, Dirk Michael (Acs Nano, 2020)
In this contribution, we focused on integrating a phenylene-bridged dibenzodiazahexacene dimer (o-DAD), which is singlet fission (SF) active, onto single-walled carbon nanotubes (SWCNTs) as a low-energy sink for energetically low lying excited states that stem from SF. Spectroscopic and microscopic assays assisted in documenting that SWCNT/o-DAD feature high stability in THF as a result of electronic interactions between the individual constituents. For example, statistical Raman analysis underlined n-doping of SWCNTs in the presence of o-DAD. Fluorescence spectroscopy prompted an energy transfer between the individual constituents, a conclusion that was exclusively derived from the quenching of the o-DAD-centered fluorescence. Excitation spectroscopy with a focus on the SWCNT fluorescence confirmed independently this conclusion by showing o-DAD-centered features. Our work was rounded off by time-resolved transient absorption measurements with SWCNT/o-DAD, in which evidence was gathered for the sequential o-DAD-centered SF with an efficiency of 112% followed by a unidirectional energy transfer from o-DAD to SWCNT and a rapid deactivation. The energy transfer efficiency from SF products such as (S1S0)CT and 1(T1T1) exceeded the 100% threshold with values of 115%, which is conventionally found in energy transfer scheme
Keywords: carbon nanotubes; pyrene-fused azaacenes; singlet fission; energy transfer; doping

Combining Electron-Accepting Phthalocyanines and Nanorod-like CuO Electrodes for p-Type Dye-Sensitized Solar Cells - Langmar, Oliver; Ganivet, Carolina R.; Lennert, Annkatrin; Costa, Ruben Dario; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2015)
A route is reported for the synthesis of two electron-accepting phthalocyanines featuring linkers with different lengths as sensitizers for p-type dye-sensitized solar cells (DSSCs). Importantly, our devices based on novel nanorod-like CuO photocathodes showed high efficiencies of up to 0.191 %: the highest value reported to date for CuO-based DSSCs.
EAM Import::2019-03-13

Combining Zinc Phthalocyanines, Oligo(p-Phenylenevinylenes), and Fullerenes to Impact Reorganization Energies and Attenuation Factors - Krug, Marcel; Stangel, Christina; Zieleniewska, Anna; Clark, Timothy; Torres, Tomas; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (ChemPhysChem, 2019)
A study on electron transfer in three electron donoracceptor complexes is reported. These architectures consist of a zinc phthalocyanine (ZnPc) as the excitedstate electron donor and a fullerene (C-60) as the groundstate electron acceptor. These complexes are brought together by axial coordination at ZnPc. The key variable in our design is the length of the molecular spacer, namely, oligopphenylenevinylenes. The lack of appreciable groundstate interactions is in accordance with strong excitedstate interactions, as inferred from the quenching of ZnPc centered fluorescence and the presence of a shortlived fluorescence component. Fullfledged femtosecond and nanosecond transient absorption spectroscopy assays corroborated that the ZnPc C-+(60) chargeseparated state formation comes at the expense of excitedstate interactions following ZnPc photoexcitation. At a first glance, the ZnPc C-+(60) charge separated state lifetime increased from 0.4 to 86.6 ns as the electron donoracceptor separation increased from 8.8 to 29.1 angstrom. A closer look at the kinetics revealed that the changes in chargeseparated state lifetime are tied to a decrease in the electronic coupling element from 132 to 1.2 cm(1), an increase in the reorganization energy of charge transfer from 0.43 to 0.63 eV, and a large attenuation factor of 0.27 angstrom(1).
CRIS-Team WoS Importer:2019-11-08

Communication via electron and energy transfer between zinc oxide nanoparticles and organic adsorbates - Gnichwitz, Jan-Frederik; Hirsch, Andreas; Guldi, Dirk Michael; Peukert, Wolfgang; Werner, Fabian; Marczak, Renata (Journal of Physical Chemistry C, 2009)
Stable ZnO nanoparticles suitable for further surface functionalization were synthesized in the liquid phase from homogeneous ethanolic solutions of the precursors lithium hydroxide and zinc acetate. It was found that the growth of the particles was governed by temperature as well as the presence of the reaction byproduct lithium acetate during the aging process. In particular, the reaction could be almost completely arrested by removal of this byproduct. The washing consisted of repeated precipitation of the ZnO particles by addition of alkanes such as heptane, removal of the supernatant, and redispersion in ethanol. Furthermore, the surface of the colloidal ZnO nanoparticles was successfully modified by catechol-anchoring group containing dye molecules, i.e., 5-(N-(3,4-dihydroxyphenethyl)-2-phenoxyacetamide)-10,15,20-(p-tert- butyltriphenyl)porphyrinatozinc (DOPAZ) and 5-(3,4-dihydroxy-N-phenylbenzamide)- 10,15,20-tris(4-tert-butylphenyl)porphyrinatozinc (CAMIZ), for the study of photochemical properties. Thermogravimetric analysis proved the stability of the catechol anchor groups. Steady-state absorption spectroscopy as well as steady-state and time-resolved emission studies confirmed the electronic communication between the ZnO nanoparticles in their excited state and both of the porphyrins. More than 96% emission quenching of ZnO can be achieved by addition of the porphyrins, proving that the visible emission of the ZnO is caused by surface states, since only the surface of the particles was altered by the grafting experiments. Moreover, with increasing porphyrin concentrations the lifetimes changed from 46.0 to 15.3 ns. The shortened lifetimes prompt a new deactivation pathway, namely, through the electronic coupling of the porphyrins to the ZnO nanoparticle. Assuming that the decrease in lifetime is entirely due to electron transfer to the porphyrins, a rate constant of 0.35 × 10 s could be determined for this process. When testing the excited state of the porphyrin in comparative assays between ZnO and Al O , we conclude a similar electron transfer deactivation. © 2009 American Chemical Society.
Keywords: Nanoparticle; electron; functionalization

Complexation and electronic communication between corannulene-based buckybowls and a curved truxene-TTF donor - Gallego, Maria; Calbo, Joaquin; Krick Calderon, Rafael; Pla, Paula; Hsieh, Ya-Chu; Perez, Emilio M.; Wu, Yao-Ting; Orti, Enrique; Guldi, Dirk Michael; Martin, Nazario (Chemistry - A European Journal, 2017)
The association behavior of an electron-donating, bowl-shaped, truxene-based tetrathiafulvalene (truxTTF) with two corannulene-based fullerene fragments, C32H12 and C38H14, is investigated in several solvents. Formation of 1:1 complexes is followed by absorption titrations and complemented by density functional theory (DFT) calculations. The binding constants are in the range logKa=2.9–3.5. DFT calculations reveal that the most stable arrangement is the conformation in which the 1,3-dithiole ring of truxTTF is placed inside the concave cavity of the corannulene derivative. This arrangement is confirmed experimentally by NMR measurements, and implies that a combination of π–π and CH–π interactions is the driving force for association. Timedependent DFT calculations reproduce the experimental UV/ Vis titrations and provide a detailed understanding of the spectral changes observed. Femtosecond transient absorption studies reveal the processes occurring after photoexcitation of either C32H12 or C38H14 and their supramolecular associates with truxTTF. In the case of truxTTF·C38H14, photoexcitation yields the charge-separated state truxTTFC+·C38H14·-with a lifetime of approximately 160 ps.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Association constants; Buckybowls; Donor–acceptor systems; Photoinduced charge transfer; Supramolecular chemistry

Complexation and Versatile Reactivity of a Highly Lewis Acidic Cationic Mg Complex with Alkynes and Phosphines - Pahl, Jürgen; Stennett, Thomas; Volland, Michel; Guldi, Dirk Michael; Harder, Sjoerd (Chemistry - A European Journal, 2019)
[(BDI)Mg+][B(C6F5)(4)(-)] (1; BDI=CH[C(CH3)NDipp](2); Dipp=2,6-diisopropylphenyl) was prepared by reaction of (BDI)MgnPr with [Ph3C+][B(C6F5)(4)(-)]. Addition of 3-hexyne gave [(BDI)Mg+(EtCCEt)][B(C6F5)(4)(-)]. Single-crystal X-ray analysis, NMR investigations, Raman spectra, and DFT calculations indicate a significant Mg-alkyne interaction. Addition of the terminal alkynes PhCCH or Me3SiCCH led to alkyne deprotonation by the BDI ligand to give [(BDI-H)Mg+(CCPh)](2)2[B(C6F5)(4)(-)] (2, 70%) and [(BDI-H)Mg+(CCSiMe3)](2)2[B(C6F5)(4)(-)] (3, 63%). Addition of internal alkynes PhCCPh or PhCCMe led to [4+2] cycloadditions with the BDI ligand to give Mg+C(Ph)=C(Ph)C[C(Me)=NDipp](2)(2) 2[B(C6F5)(4)(-)] (4, 53%) and Mg+C(Ph)=C(Me)C[C(Me)=NDipp](2)(2)2[B(C6F5)(4)(-)] (5, 73%), in which the Mg center is N,N,C-chelated. The (BDI)Mg+ cation can be viewed as an intramolecular frustrated Lewis pair (FLP) with a Lewis acidic site (Mg) and a Lewis (or BrOnsted) basic site (BDI). Reaction of [(BDI)Mg+][B(C6F5)(4)(-)] (1) with a range of phosphines varying in bulk and donor strength generated [(BDI)Mg+PPh3][B(C6F5)(4)(-)] (6), [(BDI)Mg+PCy3][B(C6F5)(4)(-)] (7), and [(BDI)Mg+ PtBu3][B(C6F5)(4)(-)] (8). The bulkier phosphine PMes(3) (Mes=mesityl) did not show any interaction. Combinations of [(BDI)Mg+][B(C6F5)(4)(-)] and phosphines did not result in addition to the triple bond in 3-hexyne, but during the screening process it was discovered that the cationic magnesium complex catalyzes the hydrophosphination of PhCCH with HPPh2, for which an FLP-type mechanism is tentatively proposed.
CRIS-Team WoS Importer:2019-03-01

Concave-Convex π-π Template Approach Enables the Synthesis of [10]Cycloparaphenylene-Fullerene [2]Rotaxanes - Xu, Youzhi; Kaur, Ramandeep; Wang, Bingzhe; Minameyer, Martin; Gsänger, Sebastian; Meyer, Bernd; Drewello, Thomas; Guldi, Dirk Michael; Von Delius, Max (Journal of the American Chemical Society, 2018)
The cycloparaphenylenes (CPPs) are a class of strained macrocycles that until 2008 were considered beyond the reach of organic synthesis. With its cyclic array of ten para-substituted phenylene rings, [10]CPP possesses a concave π-system that is perfectly preorganized for the strong supramolecular association of convex fullerenes such as C60. Although mechanically interlocked CPP architectures have been observed in the gas phase, the rational synthesis of bulk quantities has not been achieved yet, which is likely due to the fact that conventional template strategies are not amenable to CPP rings that lack heteroatoms. Here, we report the synthesis of two [2]rotaxanes in which a [10]CPP ring binds to a central fullerene bis-adduct and is prevented from dethreading by the presence of two bulky fullerene hexakis-adduct stoppers. The final step in the rotaxane synthesis is surprisingly efficient (up to ca. 40% yield) and regioselective because the fullerene acts as an efficient convex template, while [10]CPP acts as a supramolecular directing group, steering the reaction at the central fullerene exclusively toward two trans regioisomers. Comprehensive physicochemical studies confirmed the interlocked structure, shed light on the dynamic nature of the CPP-fullerene interaction, and revealed intriguing consequences of the mechanical bond on charge transfer processes. In light of recent advances in the synthesis of nanohoops and nanobelts, our concave-convex π-π templating strategy may be broadly useful and enable applications in molecular electronics or complex molecular machinery.
CRIS-Team Scopus Importer:2022-04-14

Concave versus planar geometries for the hierarchical organization of mesoscopic 3D helical fibers - Luis Lopez, Juan; Atienza, Carmen; Insuasty, Alberto; Lopez-Andarias, Javier; Romero, Carlos; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2012)
Chromophore-peptide systems: A study on a series of pentapeptides covalently connected to planar π systems (1 a and 1 b) or to a curved π system (1 c) showed the influence of the concave shape on the efficient chiral transmission at nano- and mesoscales. Control over the hierarchical growth by H bonding, π-π, and solvophobic interactions made possible the efficient generation of electroactive 3D helical fibers (see picture). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Conformational control of photoinduced charge separation within phenothiazine-pyrene dyads - Kurzawa, Jana; Acar, Nursel; Schneider, Siegfried; Daub, Jörg; Clark, Timothy; et al. (Journal of Physical Chemistry A, 2002)
Electron donor-acceptor systems, in which phenothiazine is tethered to pyrene by means of a phenyl bridge, exhibit a dual emission in moderately and very polar solvents. Employing steady-state and time-resolved fluorescence spectroscopy, we were able to provide evidence that the "blue" and "red" emission bands originate from different conformers. The ground-state geometry of the majority species is identical to that found in the crystalline state (the quasi-equatorial conformer). This conformation executes a fast electron-transfer process accompanied by significant structural relaxation. Consequently, its fluorescence exhibits a large solvatochromic shift typical for charge-transfer states. The photophysical properties of the minority species (the quasi-axial conformer) vary significantly with the substitution pattern of the bridging phenyl ring. In part, this difference is related to the orientational factor, K, governing the rate of energy transfer between the pyrene and phenothiazine moieties. In the para-substituted derivative, fluorescence emission from both the excited phenylpyrene and the phenylphenothiazine subsystem can be observed. In the meta-substituted derivative, fluorescence originates mainly from the primarily absorbing phenylpyrene subsystem. In nonpolar solvent (cyclohexane), the nature of the fluorescing state differs for the para- and meta-substituted compounds. Whereas in the former, the fluorescence originates from the locally excited phenothiazine, it is governed by emission from a structurally modified CT state in the latter derivative. Semiempirical (AM1/CI) molecular orbital calculations with a continuum solvent treatment have been used to investigate the different states involved and provide explanations for the observed results. The calculations reveal the existence of an intermediately populated CT state in which the negative charge is partly localized in the bridge as well as in the pyrene acceptor.

Conformational Landscapes and Energetics of Carbon Nanohoops and their Ring-in-Ring Complexes - Geue, Niklas; Freiberger, Markus; Frühwald, Stefan; Görling, Andreas; Drewello, Thomas; Barran, Perdita E. (Journal of Physical Chemistry Letters, 2024)
Carbon nanohoops are promising precursors for the synthesis of nanotubes, whose structural dynamics are not well understood. Here, we investigate the conformational landscape and energetics of cycloparaphenylenes (CPPs), a methylene-bridged CPP and a carbon nanobelt. These nanohoops can form host-guest complexes with other rings, and understanding their structure is crucial for predicting their properties and identifying potential applications. We used a combination of ion mobility, tandem mass spectrometry, and density functional theory to characterize the nanohoops and their ring-in-ring complexes, following the energetics and conformations of their disassembly from intact complexes to fragment ions. Our results show structural integrity of the nanohoops and host-guest complexes. They also reveal interesting trends in size, packing density, stability, and structure between [6]CPP, the methylene-bridged CPP, and the carbon nanobelt as guests in ring-in-ring complexes. Taken together, our work illustrates how mass spectrometry data can help to unravel the rules that govern the formation of carbon nanohoop assemblies.
CRIS-Team Scopus Importer:2024-07-05

Controlling additive behavior to reveal an alternative morphology formation mechanism in polymer: Fullerene bulk-heterojunctions - Güldal, Nusret Sena; Berlinghof, Marvin; Kassar, Thaer; Du, Xiaoyan; Jiao, Xuechen; Meyer, Markus; Ameri, Tayebeh; Osvet, Andres; Li, Ning; Destri, Giovanni Li; Fink, Rainer; Ade, Harald; et al. (Journal of Materials Chemistry A, 2016)
One of the most employed morphology optimization methods to design better performing organic photovoltaic devices is ink formulation engineering with additives. In this work, by employing a suboptimal host solvent mixture and 1,8-diiodooctane (DIO) as a very optimal solvent for both components in poly-thieno[3,2b]thiophene-diketopyrrolopyrrole-co-thiophene (DPP-TT-T)-based bulk-heterojunctions (BHJ), an alternative, previously unknown mechanism of additive behavior on BHJ microstructure formation is presented. In situ characterization methods involving grazing incidence X-ray diffraction, white-light reflectometry, laser light scattering and photoluminescence during film drying reveal that the microstructure formation under the influence of DIO is led towards thermodynamic equilibrium during host solvent drying, and the kinetics of morphology formation (i.e. polymer crystallization, fullerene aggregation...) are controlled dominantly by the additive during its evaporation. Ex situ X-ray-based characterization methods, such as scanning transmission X-ray microspectroscopy (STXM) and resonant soft X-ray scattering (R-SoXS), additionally reveal that the microstructure of dried films favors smaller domain sizes with purer domains, smaller fullerene aggregates, bimodal polymer crystallization relative to the substrate and more face-on molecular orientation relative to the donor/acceptor interface, which at the end lead to better performing devices with power conversion efficiencies ranging from 1.25% to 4.68%.
Keywords: Engineering controlled terms: Additives; Fullerenes; Heterojunctions; Interfaces (materials); Light scattering; Microstructure; Molecular orientation; Morphology; Polymers; Solvents; Thiophene; X ray diffraction; X ray scattering Bulk heterojunction (BHJ); Characterization methods; Donor/acceptor interface; Grazing incidence X-ray diffraction; In-situ characterization; Microstructure formation; Organic photovoltaic devices; Power conversion efficiencies Engineering main heading: Polymer films

Controlling and Fine-Tuning Charge-Transfer Emission in 2,6-Dicyanoaniline Multichromophores Prepared through Domino Reactions: Entry to a Potentially New Class of OLEDs - Plass, Fabian; Bönisch, Simon; Held, Felix; Ullrich, Tobias; Fischer, Florian; Guryev, Anton; Görling, Andreas; Kahnt, Axel; Tsogoeva, Svetlana (Journal of Organic Chemistry, 2021)
Substituted 2,6-dicyanoanilines are versatile electron donor-acceptor compounds, which have recently received considerable attention, since they exhibit strong fluorescence and may have utility in the synthesis of fluorescent materials, non-natural photosynthetic systems, and materials with nonlinear optical properties. The majority of known synthetic procedures are, however, "stop-and-go"reaction processes involving time-consuming and waste-producing isolation and purification of product intermediates. Here, we present the synthesis of substituted 2,6-dicyanoanilines via atom-economical and eco-friendly one-pot processes, involving metal-free domino reactions, and their subsequent photochemical and photophysical measurements and theoretical calculations. These studies exhibit the existence of an easily tunable radical ion pair-based charge-transfer (CT) emission in the synthesized 2,6-dicyanoaniline-based electron donor-acceptor systems. The charge-transfer processes were explored by photochemical and radiation chemical measurements, in particular, based on femtosecond laser photolysis transient absorption spectroscopy and time-resolved emission spectroscopy, accompanied by pulse radiolysis and complemented by quantum chemical investigations employing time-dependent density-functional theory. This chromophore class exhibits a broad-wavelength-range fine-tunable charge recombination emission with high photoluminescence quantum yields up to 0.98. Together with its rather simple and cost-effective synthesis (using easily available starting materials) and customizable properties, it renders this class of compounds feasible candidates as potential dyes for future optoelectronic devices like organic light-emitting diodes (OLEDs).
CRIS-Team Scopus Importer:2021-05-14

Controlling Electronic Events Through Rational Structural Design in Subphthalocyanine-Corrole Dyads: Synthesis, Characterization, and Photophysical Properties - Marinas, Victor; Platzer, Benedikt; Labella, Jorge; Caroleo, Fabrizio; Nardis, Sara; Paolesse, Roberto; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2022)
Porphyrinoids are considered perfect candidates for their incorporation into electron donor-acceptor (D-A) arrays due to their remarkable optoelectronic properties and low reorganization energies. For the first time, a series of subphthalocyanine (SubPc) and corrole (Cor) were covalently connected through a short-range linkage. SubPc axial substitution strategies were employed, which allowed the synthesis of the target molecules in decent yields. In this context, a qualitative synthetic approach was performed to reverse the expected direction of the different electronic events. Consequently, in-depth absorption, fluorescence, and electrochemical assays enabled the study of electronic and photophysical properties. Charge separation was observed in cases of electron-donating Cors, whereas a quantitative energy transfer from the Cor to the SubPc was detected in the case of electron accepting Cors.
CRIS-Team WoS Importer:2022-09-09

Controlling Interchromophore Coupling in Diamantane-Linked Pentacene Dimers To Create a “Binary” Pair - Greißel, Phillip; Schroeder, Zachary W.; Thiel, Dominik; Ferguson, Michael J.; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Journal of the American Chemical Society, 2024)
Two isomeric pentacene dimers, each linked by a diamantane spacer, have been synthesized. These dimers are designed to provide experimental evidence to support quantum mechanical calculations, which predict the substitution pattern on the carbon-rich diethynyldiamantane spacer to be decisive in controlling the interpentacene coupling. Intramolecular singlet fission (i-SF) serves as a probe for the existence and strength of the electronic coupling between the two pentacenes, with transient absorption spectroscopy as the method of choice to characterize i-SF. 4,9-Substitution of diamantane provides a pentacene dimer (4,9-dimer) in which the two chromophores are completely decoupled and that, following photoexcitation, deactivates to the ground state analogous to a monomeric pentacene chromophore. Conversely, 1,6-substitution provides a pentacene dimer (1,6-dimer) that exhibits sufficiently strong coupling to drive i-SF, resulting in correlated triplet M(T1T1) yields close to unity and free triplet (T1 + T1) yields of ca. 50%. Thus, the diamantane spacer effectively switches “on” or “off” the coupling between the chromophores, based on the substitution pattern. The binary control of diamantane contrasts other known molecular spacers designed only to modulate the coupling strength between two pentacenes.
CRIS-Team Scopus Importer:2024-04-19

Controlling Interfacial Charge Transfer and Fill Factors in CuO-based Tandem Dye-Sensitized Solar Cells - Langmar, Oliver; Fazio, Ettore; Schol, Peter; De La Torre, Gema; Costa, Ruben Dario; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2019)
We designed and synthesized a series of novel electron-accepting zinc(II)phthalocyanines (ZnPc) and probed them in p-type dye sensitized solar cells (p-DSSCs) by using CuO as photocathodes. By realizing the right balance between interfacial charge separation and charge recombination, optimized fill factors (FFs) of 0.43 were obtained. With a control over fill factors in p-DSSCs in hand we turned our attemtion to i-DSSCs, in which we combined for the first time CuO-based p-DSSCs with TiO2 -based n-DSSCs using ZnPc and N719. In the resulting t-DSSCs, the V-OC of 0.86 V is the sum of those found in p- and n-DSSCs, while the FF remains around 0.63. It is only the smaller J(SC)s in t-DSSCs that limits the efficiency to 0.69%.
CRIS-Team WoS Importer:2019-04-12

Controlling Intramolecular Förster Resonance Energy Transfer and Singlet Fission in a Subporphyrazine–Pentacene Conjugate by Solvent Polarity - Guzman, David; Papadopoulos, Ilias; Lavarda, Giulia; Rami, Parisa R.; Tykwinski, Rik R.; Rodriguez-Morgade, M. Salome; Guldi, Dirk Michael; Torres, Tomas (Angewandte Chemie International Edition, 2020)
Due its complementary absorptions in the range of 450 and 600 nm, an energy-donating hexaaryl-subporphyrazine has been linked to a pentacene dimer, which acts primarily as an energy acceptor and secondarily as a singlet fission enabler. In the corresponding conjugate, efficient intramolecular Förster resonance energy transfer (i-FRET) is the modus operandi to transfer energy from the subporphyrazine to the pentacene dimer. Upon energy transfer, the pentacene dimer undergoes intramolecular singlet fission (i-SF), that is, converting the singlet excited state, via an intermediate state, into a pair of correlated triplet excited states. Solvatochromic fluorescence of the subporphyrazine is a key feature of this system and features a red-shift as large as 20 nm in polar media. Solvent is thus used to modulate spectral overlap between the fluorescence of subporphyrazine and absorption of the pentacene dimer, which controls the Förster rate constant, on one hand, and the triplet quantum yield, on the other hand. The optimum spectral overlap is realized in xylene, leading to Förster rate constant of 3.52×1011 s−1 and a triplet quantum yield of 171 % ±10 %. In short, the solvent polarity dependence, which is a unique feature of subporphyrazines, is decisive in terms of adjusting spectral overlap, ensuring a sizable Förster rate constant, and maximizing triplet quantum yields. Uniquely, this optimization can be achieved without a need for synthetic modification of the subporphyrazine donor.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Förster resonance energy transfer; intramolecular singlet fission; subporphyrazine

Controlling Solar Hydrogen Production by Organizing Porphyrins - Nikolaou, Vasilis; Charalambidis, Georgios; Ladomenou, Kalliopi; Nikoloudakis, Emmanouil; Drivas, Charalambos; Vamvasakis, Ioannis; Panagiotakis, Stylianos; Landrou, Georgios; Agapaki, Eleni; Stangel, Christina; Henkel, Christian; Joseph, Jan; et al. (Chemsuschem, 2020)
In this study, a highly efficient photocatalytic H2 production system is developed by employing porphyrins as photocatalysts. Palladium and platinum tetracarboxyporphyrins (PdTCP and PtTCP) are adsorbed or coadsorbed onto TiO2 nanoparticles (NPs), which act as the electron transport medium and as a scaffold that promotes the self-organization of the porphyrinoids. The self-organization of PdTCP and PtTCP, forming H- and J-aggregates, respectively, is the key element for H2 evolution, as in the absence of TiO2 NPs no catalytic activity is detected. Notably, J-aggregated PtTCPs are more efficient for H2 production than H-aggregated PdTCPs. In this approach, a single porphyrin, which self-organizes onto TiO2 NPs, acts as the light harvester and simultaneously as the catalyst, whereas TiO2 serves as the electron transport medium. Importantly, the concurrent adsorption of PdTCP and PtTCP onto TiO2 NPs results in the most efficient catalytic system, giving a turnover number of 22,733 and 30.2 mmol(H2) g(cat)−1.
CRIS-Team Scopus Importer:2020-12-25
Keywords: hydrogen evolution; nanoparticles; photocatalysis; porphyrinoids; self-assembly

Controlling the Charge Transfer Mechanism and Efficiency by Means of Different C70 Regioisomeric Adducts - Plass, Fabian; Lukyanov, Daniil A.; Konev, Alexander S.; Kahnt, Axel; Amsharov, Konstantin; Khlebnikov, Alexander F.; Guldi, Dirk Michael (Small Structures, 2020)
Here, differences stemming from two newly synthesized electron donor–acceptor conjugates, α- or β-regioisomeric adducts featuring orthogonal arrangements of an electron-donating free-base porphyrin (H2P) and electron-accepting C70, are reported. Key to a full-fledged investigation in terms of both experiments and theory is the use of a rigid linker to separate the electron acceptor and donor. Both conjugates are experimentally investigated by means of femtosecond/nanosecond transient absorption measurements, which is further supported by radiation chemical studies based on pulse radiolysis. Significant regioisomeric differences are seen in the charge recombination kinetics, in general, which are as large as 1.4-fold, and in the relative distributions of the charge recombination pathways, in particular, which reach nearly 1.5-fold. Clearly, α-regioisomers of C70 adducts are much better suited for the construction of future energy conversion systems than β-regioisomers; a fact that relates to the superior electron delocalization within the carbon caps of C70 made out of “corannulenoid” fragments relative to the equator region of fullerenes featuring extended “phenanthrenoid” rings.<br
Keywords: fullerenes; molecular electron donor–acceptors; photoinduced electron transfers; regioisomers; synthetic methods

Controlling the Chromaticity of Small-Molecule Light-Emitting Electrochemical Cells Based on TIPS-Pentacene - Weber, Michael; Adam, Matthias; Tykwinski, Rik; Costa, Ruben Dario (Advanced Functional Materials, 2015)
This work demonstrates a novel proof-of-concept to implement pentacene derivatives as emitters for the third generation of light-emitting electrochemical cells based on small-molecules (SM-LECs). Here, a straightforward procedure is shown to control the chromaticity of pentacene-based lighting devices by means of a photoinduced cycloaddition process of the 6,13-bis(triisopropylsilylethynyl) (TIPS)-pentacene that leads to the formation of anthracene-core dimeric species featuring a high-energy emission. Without using the procedure, SM-LECs featuring deep-red emission with Commission Internationale d'Eclairage (CIE) coordinates of x = 0.69/y = 0.31 and irradiance of 0.4 extgreekmW cm-2 are achieved. After a careful optimization of the cycloaddition process, warm white devices with CIE coordinates of x = 0.36/y = 0.38 and luminances of 10 cd m-2 are realized. Here, the mechanism of the device is explained as a host–guest system, in which the dimeric species acts as the high-energy band gap host and the low-energy bandgap TIPS-pentacene is the guest. To the best of the knowledge, this work shows the first warm white SM-LECs. Since this work is based on the archetypal TIPS-pentacene and the photoinduced cycloaddition process is well-knownfor any pentacenes, this proof-of-concept could open a new way to use these compounds for developing white lighting sources.
EAM Import::2019-03-13

Controlling the crystalline three-dimensional order in bulk materials by single-wall carbon nanotubes - Lopez-Andarias, Javier; Luis Lopez, Juan; Atienza, Carmen; Brunetti, Fulvio G.; Romero-Nieto, Carlos; Guldi, Dirk Michael; Martin, Nazario (Nature Communications, 2014)
The construction of ordered single-wall carbon nanotube soft-materials at the nanoscale is currently an important challenge in science. Here we use single-wall carbon nanotubes as a tool to gain control over the crystalline ordering of three-dimensional bulk materials composed of suitably functionalized molecular building blocks. We prepare p-type nanofibres from tripeptide and pentapeptide-containing small molecules, which are covalently connected to both carboxylic and electron-donating 9,10-di(1,3-dithiol-2-ylidene)-9,10- dihydroanthracene termini. Adding small amounts of single-wall carbon nanotubes to the so-prepared p-nanofibres together with the externally controlled self assembly by charge screening by means of Ca2+ results in new and stable single-wall carbon nanotube-based supramolecular gels featuring remarkably long-range internal order. © 2014 Macmillan Publishers Limited.
CRIS-Team Scopus Importer:2023-03-07

Controlling the transformation of primary into quaternary structures: Towards hierarchically built-up twisted fibers - Luis Lopez, Juan; Atienza, Carmen; Seitz, Wolfgang; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2010)
From the ground up: In the hierarchical organization of cyanurate 1 and π-extended tetrathiafulvalene (π-exTTF) 2 an example of the controlled one-, two, and three-dimensional assembly of nonplanar building blocks on different scales highly ordered lamellar crystalline packing based on π-π interactions between π-exTTF units ensured the unidirectional growth of twisted nanofibers as the quaternary structure. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Control over charge transfer through molecular wires by temperature and chemical structure modifications - Wielopolski, Mateusz; De Miguel Rojas, Gustavo; Van Der Pol, Cornelia; Brinkhaus, Linda; Katsukis, Georgios; Bryce, Martin; Clark, Timothy; Guldi, Dirk Michael (Acs Nano, 2010)
A series of electron donor-acceptor arrays containing π-conjugated oligofluorenes (oFL) of variable length between a zinc porphyrin (ZnP) as electron donor and fullerene (C ) as electron acceptor have been prepared by following a convergent synthesis. The electronic interactions between the electroactive species were determined by cyclic voltammetry, UV-visible, fluorescence, and femto/nanosecond transient absorption spectroscopy. Our studies clearly confirm that, although the C units are connected to the ZnP donor through π-conjugated oFL frameworks, no significant electronic interactions prevail in the ground state. Theoretical calculations predict that a long-range electron transfer occurs primarily due to a maximized π-conjugated pathway from the donor to the acceptor. Photoexcitation of ZnP-oFL -C results in transient absorption maxima at 715 and 1010 nm, which are unambiguously attributed to the photolytically generated radical ion pair state, [ZnP - oFL -C ], with lifetimes in the microsecond time regime. Temperature-dependent photophysical experiments have shown that the charge-transfer mechanism is controllable by temperature. Both charge separation and charge recombination processes give rise to a molecular wire behavior of the oFL moiety with an attenuation factor (β) of 0.097 Å . The correlation β to the connection pattern between the ZnP donor and the oFL linker revealed that even small alterations of the linker π-electron system break the homogeneous π-conjugation pattern, leading to higher values of β. © 2010 American Chemical Society.

Control over Tuning Fullerene Microcrystals by Means of Engineering Charge-Transfer Interactions - Wang, Bingzhe; Qu, Yongtao; Piao, Guangzhe; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2019)
Multifunctional fullerene microcrystals have been prepared by the involvement of water in the liquid-liquid interfacial precipitation. The resulting microcrystals were characterized microscopically and spectroscopically. The role of water in engineering charge-transfer interactions between fullerenes and electron-donating solvents has been corroborated through thermogravimetric and transient absorption spectroscopy analyses.
CRIS-Team Scopus Importer:2019-05-21
Keywords: charge transfer; crystal; fullerene; morphology

Convergent synthesis and photoinduced processes in multi-chromophoric rotaxanes - Megiatto, Jackson D.; Li, Ke; Schuster, David I.; Palkar, Amit; Herranz, M. Angeles; Echegoyen, Luis; Abwandner, Silke; De Miguel Rojas, Gustavo; Guldi, Dirk Michael (Journal of Physical Chemistry B, 2010)
A series of [2]rotaxane materials, in which [60]fullerene is linked to a macrocycle and ferrocene (Fc) moieties are placed at the termini of a thread, both of which possess a central Cu(I)-1,10-phenanthroline [Cu(phen) ] complex, were synthesized by self-assembly using Sauvage metal template methodology. Two types of threads were constructed, one with terminal ester linkages, and a second with terminal 1,2,3-triazole linkages derived from Cu(I)-catalyzed "click" 1,3-cycloaddition reactions. Model compounds lacking the fullerene moiety were prepared in an analogous manner. The ability of the interlocked Fc-[Cu(phen)2]+-Cgo hybrids to undergo electron transfer upon photoexcitation in benzonitrile, dichloromethane, and oritho-dichlorobenzene was investigated by means of time-resolved fluorescence and transient absorption spectroscopy, using excitation wavelengths directed at the fullerene and [Cu(phen) ] subunits. The energies of the electronic excited states and charge separated (CS) states that might be formed upon photoexcitation were determined from spectroscopic and electrochemical data. These studies showed that MLCT excited states of the copper complex in the fullerenerotaxanes were quenched by electron transfer to the fullerene in benzonitrile, resulting in charge separated states with oxidized copper and reduced fullerene moieties, (Fc) -[Cu(phen)2] -C . Even though electron transfer from Fc to the oxidized copper complex is predicted to be exergonic by 0.16 to 0.20 eV, no unequivocal evidence in support of such a process was obtained. The conclusion that Fc plays no role in the photoinduced processes in our systems rests on the lack of enhancement of the lifetime of the charge separated state, as measured by decay of C at ∼1000 nm, since one-electron oxidized Fc is very difficult to detect spectroscopically in the 500-800 nm spectral region. © 2010 American Chemical Society.

Cooperativity and tunable excited state deactivation: Modular self-assembly of depsipeptide dendrons on a Hamilton receptor modified porphyrin platform - Gnichwitz, Jan-Frederik; Wielopolski, Mateusz; Hartnagel, Kristine; Hartnagel, Uwe; Guldi, Dirk Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2008)
A series of novel supramolecular architectures were built around a tin tetraphenyl porphyrin platform 6 - functionalized by a 2-fold 1-ethyl-3-3-(3-dimethylaminopropyl)carbodiimide (EDC) promoted condensation reaction - and chiral depsipeptide dendrons of different generations 1-4. Here, implementation of a Hamilton receptor provided the necessary means to keep the constituents together via strong hydrogen bonding. Characterization of all architectures has been performed, including 4 which is the fourth generation, on the basis of NMR and photophysical methods. In particular, several titration experiments were conducted suggesting positive cooperativity, an assessment that is based on association constants that tend to be higher for the second binding step than for the first step. Importantly, molecular modeling calculations reveal a significant deaggregation of the intermolecular network of 6 during the course of the first binding step. As a consequence, an improved accessibility of the second Hamilton receptor unit in 6 emerges and, in turn, facilitates the higher association constants. The features of the equilibrium, that is, the dynamic exchange of depsipeptide dendrons 1-4 with fullerene 5, was tested in photophysical reference experiments. These steady-state and time-resolved measurements showed the tunable excited-state deactivations of these complexes upon photoexcitation. © 2008 American Chemical Society.

Coordinating Electron Transport Chains to an Electron Donor - Villegas, Carmen; Wolf, Maximilian; Joly, Damien; Luis Delgado, Juan; Guldi, Dirk Michael; Martin, Nazario (Organic Letters, 2015)
Two electron transport chains (2 and 3) featuring two fullerenes with different electron acceptor strengths have been synthesized, characterized, and coordinated to a light harvesting/electron donating zinc porphyrin. Electrochemical assays corroborate the redox gradients along the designed electron transport chains, and complementary absorption and fluorescence titrations prove the assembly of ZnP-2 and ZnP-3 hybrids.
CRIS-Team Scopus Importer:2023-03-07

Coordination of iron atoms by tetraphenylporphyrin monolayers and multilayers on Ag(111) and formation of iron-tetraphenylporphyrin - Buchner, Florian; Flechtner, Ken; Bai, Yun; Zillner, Elisabeth; Kellner, Ina; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (Journal of Physical Chemistry C, 2008)
The in situ metalation of monolayers and multilayers of 2H-tetraphenylporphyrin (2HTPP) with Fe atoms on Ag(111) was studied with scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS). This surface-confined coordination reaction results in the formation of adsorbed iron(II)-tetraphenylporphyrin (FeTPP). It is demonstrated that metalation of 2HTPP is achieved either by depositing iron atoms onto a monolayer of 2HTPP at room temperature or, alternatively, by depositing 2HTPP onto a Ag(111) surface with predeposited iron. The latter route requires elevated temperatures, indicating that this reaction includes at least one step with an activation barrier. In addition, it is demonstrated that vapor deposited Fe atoms also react with multilayers of the porphyrin at room temperature under the formation of FeTPP. © 2008 American Chemical Society.

Coordinative interactions between porphyrins and C60, La@C 82, and La2@C80 - Tsuchiya, Takahiro; Rudolf, Marc; Wolfrum, Silke; Radhakrishnan, Shankara Gayathri; Aoyama, Ryo; Yokosawa, Yuya; Oshima, Azusa; Akasaka, Takeshi; Nagase, Shigeru; Guldi, Dirk Michael (Chemistry - A European Journal, 2013)
For the first time, a C derivative (1) and two different lanthanum metallofullerene derivatives, La@CPy (2) and La @CPy (3), that feature a pyridyl group as a coordination site for transition-metal ions have been synthesized and integrated as electron acceptors into coordinative electron-donor/electron-acceptor hybrids. Zinc tetraphenylporphyrin (ZnP) served as an excited-state electron donor in this respect. Our investigations, by means of steady-state and time-resolved photophysical techniques found that electron transfer governs the excited-state deactivation in all of these systems, namely 1/ZnP, 2/ZnP, and 3/ZnP, whereas, in the ground state, notable electronic interactions are lacking. Variation of the electron-accepting fullerene or metallofullerene moieties provides the incentive for fine-tuning the binding constants, the charge-separation kinetics, and the charge-recombination kinetics. To this end, the binding constants, which ranged from log K=3.94-4.38, are dominated by axial coordination, with minor contributions from the orbital overlap of the curved and planar π systems. The charge-separation and charge-recombination kinetics, which are in the order of 10 and 10 s, relate to the reduction potential of the fullerene and metallofullerenes, respectively. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Covalent and noncovalent phthalocyanine - Carbon nanostructure systems: Synthesis, photoinduced electron transfer, and application to molecular photovoltaics - Bottari, Giovanni; De La Torre, Gema; Guldi, Dirk Michael; Torres, Tomas (Chemical Reviews, 2010)
The tunable absorption features of phthalocyanine (Pcs) and related compounds such as subphthalocyanines (SubPcs) render them ideal antenna systems that harvest light over a broad range of the solar spectrum. The different synthetic strategies that have been pursued so far for the preparation of D-A Pc and SubPc-carbon nanostructure systems, having the donor and the acceptor units connected either covalently or by using supramolecular interactions were studied. A thorough analysis on the photophysical properties of dyads in solution was also carried out, confirming the occurrence of PET events. Transmission electron microscopy (TEM) studies revealed that the amphiphilic Pc-C60 dyad salt, when dispersed in water, is able to form perfectly ordered 1-D nanotubules, due to a combination of solvophobic and π-π stacking interactions. One of the most outstanding applications of these materials is their incorporation in photovoltaic devices in which generation of electrical current from solar energy takes place.

Covalently linked heterofullerene-porphyrin conjugates; new model systems for long-lived intramolecular charge separation - Hauke, Frank; Atalick, Stefan; Guldi, Dirk Michael; Hirsch, Andreas; Hauke, Frank (Tetrahedron, 2006)
Attaching tetraphenyl porphyrins, with peripheral acetyl or malonate groups, to CN leads to the first covalently linked heterofullerene-porphyrin conjugates that exhibit long-lived intramolecular charge separation. © 2005 Elsevier Ltd. All rights reserved.

Covalently linked porphyrin-La@C 82 hybrids: Structural elucidation and investigation of intramolecular interactions - Feng, Lai; Slanina, Zdenek; Sato, Satoru; Yoza, Kenji; Tsuchiya, Takahiro; Mizorogi, Naomi; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2011)
π-π talks: Three isomeric porphyrin-La@C hybrids were synthesized and structurally characterized for the first time (see picture: La blue sphere, N dark blue, O red). The two chromophores, which have a large π surface, evidently exhibit electronic interactions in the ground state and communicate with each other in the photoexcited state. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Creating and testing carbon interfaces - Integrating oligomeric phthalocyanines onto single walled carbon nanotubes - Strauß, Volker; Gallego, Almudena; De La Torre, Gema; Chamberlain, Thomas W.; Khlobystov, Andrei N.; Torres, Tomas; Guldi, Dirk Michael (Faraday Discussions, 2014)
Two oligomers, that is, para-phenylenevinylene with either pendant Pd(II)Pc or Zn(II)Pc units, have been synthesized and their interactions with SWCNTs and peapods - C60@SWCNT - have been probed by complementary spectroscopy and microscopy. Spectroscopy assisted mainly in shedding light onto electronic interactions in the ground and excited state, while microscopy enabled insights into the degree of individualizing SWCNTs/C60@SWCNTs and their stabilization.
CRIS-Team Scopus Importer:2023-03-07

Cruciforms' polarized emission confirms disjoint molecular orbitals and excited states - Gard, Matthew N.; Zucchero, Anthony J.; Kuzmanich, Gregory; Oelsner, Christian; Guldi, Dirk Michael; Dreuw, Andreas; Bunz, Uwe H. F.; Garcia-Garibay, Miguel A. (Organic Letters, 2012)
Steady-state and time-resolved polarized spectroscopy studies reveal that electronic excitation to the third excited state of 1,4-distyryl-2,5- bis(arylethynyl)benzene cruciforms results in fluorescence emission that is shifted an angle of ca. 60°. This result is consistent with quantum chemical calculations of the lowest electronic excited states and their transition dipole moments. The shift originates from the disjointed nature of the occupied molecular orbitals being localized on the different branches of the cruciforms. © 2012 American Chemical Society.

Cyano-Functionalized Graphitic Carbon Nitride with Adsorption and Photoreduction Isosite Achieving Efficient Uranium Extraction from Seawater - Liu, Liping (Advanced Functional Materials, 2024)

Cyclopentadienylruthenium π complexes of subphthalocyanines: A "drop-pin" approach to modifying the electronic features of aromatic macrocycles - Caballero, Esmeralda; Fernandez-Ariza, Javier; Lynch, Vincent M.; Nieto, Carlos Romero; Salome Rodriguez-Morgade, M.; Sessler, Jonathan L.; Guldi, Dirk Michael; Torres, Tomas (Angewandte Chemie International Edition, 2012)
Facing facts: Coordination of Cp*Ru (Cp*=CMe ) to the concave and convex π surfaces of subphthalocyanines constitutes a new approach to the functionalization of subazaporphyrins. While the convex face shows higher reactivity, coordination to the concave side produces a stronger diatropic influence on the Cp* ligand and a greater perturbation of the macrocyclic π-electronic features. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Cyclopenta[hi]aceanthrylene Decorated with Multiple and Long Alkoxy Chains: Physicochemical Properties and Single-Walled Carbon Nanotubes' Exfoliation Capability - Schierl, Christoph; Pardo, Virtudes; Bottari, Giovanni; Guldi, Dirk Michael; Torres, Tomas (ECS Journal of Solid State Science and Technology, 2020)
A rod-like cyclopenta[hi]aceanthrylene (CPA) derivative bearing three dodecyloxy chains at each of its two terminal positions was prepared. Spectroscopic (i.e., steady-state absorption and fluorescence) and electrochemical studies carried out with this polycyclic aromatic hydrocarbon (PAH) derivative showed an intense absorption through the entire UV-vis spectral range, weak fluorescence, small HOMO-LUMO gap, and excellent electron accepting capability. Transient absorption spectroscopy (TAS) revealed the formation of singlet and triplet excited states; the latter was, however, only observed in the presence of a triplet sensitizer. The exfoliation capability of this lipophilic CPA towards single-walled carbon nanotubes (SWCNTs) in THF was also investigated. On one hand, transmission electron microscopy (TEM) pointed to an efficient debundling of SWCNTs by the CPA derivative by means of non-covalent interactions. On the other hand, important differences in the ground and excited state features of the uncomplexed and SWCNT-complexed CPA were revealed by Raman and TAS.
CRIS-Team Scopus Importer:2020-07-10

Dark State of the Thiele Hydrocarbon: Efficient Solvatochromic Emission from a Nonpolar Centrosymmetric Singlet Diradicaloid - Punzi, Angela; Dai, Yasi; Dibenedetto, Carlo N.; Mesto, Ernesto; Schingaro, Emanuela; Ullrich, Tobias; Striccoli, Marinella; Guldi, Dirk Michael; Negri, Fabrizia; Farinola, Gianluca M.; Blasi, Davide (Journal of the American Chemical Society, 2023)
In this work, a comprehensive investigation of the photoinduced processes and mechanisms linked to the luminescence of a novel nonperchlorinated Thiele hydrocarbon (TTH) is presented. Despite the comparable diradical character of TTH (y0 = 0.32-0.44) and the unsubstituted Thiele hydrocarbon (TH) (y0 = 0.30), the polyhalogenated species is inert and photostable, showing an intense deep-red/near-infrared (NIR) fluorescence (photoluminescence quantum yield (PLQY) = 0.84 in toluene) even at room temperature and in the solid state (PLQY = 0.19). TTH displays a large Stokes shift (307 nm in benzonitrile) and solvatochromic behavior, which is unusual for a centrosymmetric, nonpolar, and low-conjugated species. These outstanding emission features are interpreted through quantum-chemical calculations, indicating that its fluorescence arises from the low-lying dark doubly excited zwitterionic state, typically found at low excitation energies in diradicaloids, acquiring dipole moment and intensity by state mixing via twisting around the strongly elongated exocyclic CC bonds of the excited p-quinodimethane (pQDM) core, with a mechanism similar to sudden polarization occurring in olefins. Such a mechanism is derived from ns and fs transient absorption measurements.
CRIS-Team Scopus Importer:2023-09-29

Davydov splitting and singlet fission in excitonically coupled pentacene dimers - Basel, Bettina; Hetzer, Constantin; Zirzlmeier, Johannes; Thiel, Dominik; Guldi, Rebecca; Hampel, Frank; Kahnt, Axel; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Chemical Science, 2019)
Singlet fission (SF) allows two charges to be generated from the absorption of a single photon and is, therefore, potentially transformative toward improving solar energy conversion. Key to the present study of SF is the design of pentacene dimers featuring a xanthene linker that strictly places two pentacene chromophores in a rigid arrangement and, in turn, enforces efficient, intramolecular pi-overlap that mimics interactions typically found in condensed state (e.g., solids, films, etc.). Inter-chromophore communication ensures Davydov splitting, which plays an unprecedented role toward achieving SF in pentacene dimers. Transient absorption measurements document that intramolecular SF evolves upon excitation into the lower Davydov bands to form a correlated triplet pair at cryogenic temperature. At room temperature, the two spin-correlated triplets, one per pentacene moiety within the dimers, are electronically coupled to an excimer state. The presented results are transferable to a broad range of acene morphologies including aggregates, crystals, and films.
CRIS-Team WoS Importer:2019-04-12

Decatungstate-Photocatalyzed Addition of Lactones to [60]Fullerene - Malliaros, Nikitas G.; Kellner, Ina; Drewello, Thomas; Orfanopoulos, Michael (Journal of Organic Chemistry, 2021)
A new, one step functionalization of C60 with lactones has been developed. This photochemical approach utilizes a variety of lactonyl radicals deriving from lactones through a hydrogen atom abstraction process mediated by tetrabutylammonium decatungstate [(n-Bu4N)4W10O32]. This reaction provides access to a previously unknown class of materials, namely 1-lactonyl-2-hydro[60]fullerenes. A mechanism for this new reaction has been proposed based mainly on the structure of reaction products and deuterium-incorporated experiments.
CRIS-Team Scopus Importer:2021-08-06

Deciphering the Energy Transfer Mechanism Across Metal Halide Perovskite-Phthalocyanine Interfaces - Cortés-Villena, Alejandro; Cadranel, Alejandro; Azizi, Kobra; Torres, Tomás; Guldi, Dirk Michael; Pérez-Prieto, Julia; Galian, Raquel E. (Advanced Science, 2025)
Energy transfer processes in nanohybrids are at the focal point of conceptualizing, designing, and realizing novel energy-harvesting systems featuring nanocrystals that absorb photons and transfer their energy unidirectionally to surface-immobilized functional dyes. Importantly, the functionality of these dyes defines the ultimate application. Herein, CsPbBr3 perovskite nanocrystals (NCs) are interfaced with zinc phthalocyanine (ZnPc) dyes featuring carboxylic acid. The functionality is the photosensitization of singlet oxygen. The CsPbBr3@ZnPc nanohybrid is to the best of our knowledge the first example, in which an unusual Dexter-type singlet energy transfer between metal halide perovskite nanocrystals and phthalocyanine dyes enables singlet oxygen generation as a proof-of-concept application. A detailed temporal picture of the singlet energy transfer mechanism is made possible by combining key time-resolved spectroscopic techniques, that are, femtosecond, nanosecond, and microsecond transient absorption spectroscopy as well as time-correlated single photon counting, and target analyses. In fact, three excitonic components in the NCs govern a concerted Dexter-type energy transfer. The work illustrates the potential of CsPbBr3@ZnPc as a singlet photosensitizer of ZnPc to produce singlet oxygen (1O2) almost quantitatively while photoexciting CsPbBr3.
CRIS-Team Scopus Importer:2025-01-31
Keywords: perovskite nanocrystals; perovskite-phthalocyanine nanohybrids; singlet energy transfers; time-resolved photoluminescence; transient absorption spectroscopy

Decorating graphene nanosheets with electron accepting pyridyl-phthalocyanines - Wibmer, Leonie; Lourenco, Leandro M. O.; Roth, Alexandra Marina; Katsukis, Georgios; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Tome, Joao P. C.; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2015)
We describe herein the preparation of novel exfoliated graphene-phthalocyanine nanohybrids, and the investigation of their photophysical properties. Pyridyl-phthalocyanines (Pcs) 1-3 are presented as novel electron accepting building blocks of variable strengths with great potential for the exfoliation of graphite via their immobilization onto the basal plane of graphene in dimethylformamide (DMF) affording single layered and turbostratic graphene based G1-G3. G1-G3 were fully characterized (AFM, TEM, Raman, steady-state and pump probe transient absorption spectroscopy) and were studied in terms of electron donor-acceptor interactions in the ground and excited states. In this context, electron transfer upon photoexcitation from graphene to the electron accepting Pcs with dynamics, for example, in G2 of <1 and 330 ± 50 ps for charge separation and charge recombination, respectively, was corroborated in a series of steady-state and time-resolved spectroscopy experiments. This journal is
CRIS-Team Scopus Importer:2023-03-07

Decorating polyelectrolyte wrapped SWNTs with CdTe quantum dots for solar energy conversion - Leubner, Susanne; Katsukis, Georgios; Guldi, Dirk Michael (Faraday Discussions, 2012)
We report herein on the development of a synthetic route towards SWNT/polyelectrolyte/QD nanohybrids. On one hand, negatively charged thioglycolic acid capped CdTe QDs were prepared via an aqueous solution based synthesis. On the other hand, SWNTs were coated with a positively charged polyelectrolyte. By virtue of electrostatic interactions between QDs and SWNTs, SWNT/polyelectrolyte/QD nanohybrids were realized, whose formation was corroborated by thorough spectroscopic and microscopic investigations. Of particular relevance are changes of the QD related emission - quantum yields and lifetimes - upon their integration into the nanohybrids. The latter is indicative for electronic communication between both the photo- and redoxactive constituents, namely QDs and SWNTs, whose nature is electron transfer. © 2012 The Royal Society of Chemistry.

Deep-Saddle-Shaped Nanographene Induced by Four Heptagons: Efficient Synthesis and Properties - Borrisov, Boris; Beneventi, Giovanni Mariano; Fu, Yubin; Qiu, Zhen Lin; Komber, Hartmut; Deng, Qing Song; Greißel, Phillip; Cadranel, Alejandro; Guldi, Dirk Michael; Ma, Ji; Feng, Xinliang (Journal of the American Chemical Society, 2024)
The construction of multiple heptagonal rings in nanographene is the key step for obtaining exotic carbon nanostructures with a negative curvature and intriguing properties. Herein, a novel saddle-shaped nanographene (1) with four embedded heptagons is synthesized via a highly efficient one-shot Scholl reaction from a predesigned oligophenylene precursor. Notably, a quadruple [6]helicene intermediate was also obtained and isolated by controlling the Scholl reaction conditions. Interestingly, the single crystal structures of 1 display a saddle geometry induced by the four embedded heptagons, resulting in a deep curvature with a width of 16.5 Å and a depth of 8.0 Å. Theoretical calculations at the molecular level suggest a weak antiaromatic character of the heptagons in 1. Remarkably, compound 1 exhibits dual fluorescence from S1 and S2. The deep-saddle-shaped geometry in 1 defines host-guest interactions with fullerenes, which were explored in titration experiments and by theoretical methods. The resulting 1@C60 are stable and are subject to an electron transfer from photoexcited 1 to C60. Our current study underscores the influence of heptagon rings on the photophysical, self-assembly, and electron-donating properties of NGs.
CRIS-Team Scopus Importer:2024-10-18

Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111) - Bachmann, Philipp; Steinhauer, Johann; Späth, Florian; Düll, Fabian; Bauer, Udo; Eschenbacher, Roman; Hemauer, Felix; Scheuermeyer, Marlene; Bösmann, Andreas; Büttner, Miriam; Neiß, Christian; Görling, Andreas; et al. (Journal of Chemical Physics, 2019)
Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viability as the LOHC system. In the photoemission experiments, for all Hx-2-methylindoles, we find deprotonation at the NH bond starting between 240 and 300 K, resulting in a 2-methylindolide species. Simultaneously or before this reaction step, the dehydrogenation of 2-methyloctahydroindole via 2-methylindoline and 2-methylindole intermediates is observed. For 2-methyloctahydroindole, we also find π-allyl intermediates above 230 K. Starting at ∼390 K, decomposition of the remaining 2-methylindolide species takes place under the conditions of our surface science experiments. DFT calculations give insight into the relative energies of the various species, reaction intermediates, and their isomers both in the gas phase and on the Pt(111) surface.
CRIS-Team Scopus Importer:2019-10-22

Dendrimer-Dye Assemblies as Templates for the Formation of Gold Nanostructures - Düring, Jasmin; Alex, Wiebke; Zika, Alexander; Branscheid, Robert; Spiecker, Erdmann; Gröhn, Franziska (Macromolecules, 2017)
Dendrimer–dye assemblies are used as novel supramolecular nanoreactors for the formation of various gold nanostructures. The organic–inorganic hybrid systems are investigated with dynamic light scattering, UV–vis spectroscopy, and transmission electron microscopy (TEM) as well as cryo-TEM and high-resolution TEM (HRTEM). We show that the shape of the hybrid assemblies is determined by the choice and the ratio of the building blocks. Shape and size of the gold nanoparticles within the assemblies are controlled by the reducing agent. The accessible range of gold morphologies extends from small and spherical, over ellipsoidal, faceted, and large to highly anisotropic. The approach may open the way to new hybrid systems with applications in catalysis or in the biomedical field.

Dendritic metalloporphyrin-fullerene conjugates: Changing the microenvironment around redox-active centers and its impact on charge-transfer reactions - Krokos, Evangelos; Spänig, Fabian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2012)
Photophysical investigations on a series of (2,4,6)-tris-substituted metalloporphyrin-fullerene conjugates revealed the effects of an electron-rich microenvironment surrounding the electron-donating porphyrin as a function of the metal center. On one hand, for all conjugates-water-soluble and non-water-soluble-ultrafast charge separation was observed upon photoexcitation. On the other hand, when examining the charge recombination dynamics for the non-water-soluble conjugates it becomes obvious that the (2,4,6)-tris- substitution stabilizes the radical-ion-pair state relative to the mono-substitution in the ortho-, meta-, and para-position. The more efficient protection of the electron-donating porphyrin from solvation is thought to be the major cause for this impact. Nevertheless, the situation is slightly different for the water-soluble conjugates. At first glance, the radical-ion-pair state lifetimes are, also in the case of the (2,4,6)-tris-substitution, longer than for the mono-substituted ortho-, meta- and para-conjugates. Upon closer inspection, they fail, however, to exhibit any metal dependence. Competing with the protection from solvation of the dendrons, dipole-charge interactions impact the stabilization in the polar aqueous environment and, in turn, become the dominant force governing the electron-transfer dynamics. Caged porphyrins: Photophysical and photochemical characterization of a series of porphyrin-fullerene conjugates have been performed. The conjugates are intended to act as mimics of the photosynthetic center and emphasis was placed on the dependence of microenvironmental effects on electron-transfer dynamics (see figure). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dendritic porphyrin-fullerene conjugates: Efficient light-harvesting and charge-transfer events - Schlundt, Sebastian; Kuzmanich, Gregory; De Miguel Rojas, Gustavo; Kovács, Christian; Garcia-Garibay, Miguel A.; Guldi, Dirk Michael; Hirsch, Andreas; et al. (Chemistry - A European Journal, 2009)
A novel dendritic C-HP(ZnP) (P = porphyrin) conjugate gives rise to the successful mimicry of the primary events in photosynthesis, that is, light harvesting, unidirectional energy transfer, charge transfer, and charge-shift reactions. Owing, however, to the flexibility of the linkers that connect the Q, HP, and ZnP units, the outcome depends strongly on the rigidity/viscosity of the environment. In an agar matrix or Triton X-100, timeresolved transient absorption spectroscopic analysis and fluorescence-lifetime measurements confirm the following sequence. Initially, light harvesting is seen by the peripheral C-H P-*(ZnP) conjugate. Once photoexcited, a unidirectional energy transfer funnels the singlet excited-state energy to HP to form C-*(HP)-(ZnP), which powers an intramolecular charge transfer that oxidizes the photoexcited HP and reduces the adjacent C species. In the correspondingly formed (C)'(HP) -(ZnP) conjugate, an intramolecular charge-shift reaction generates (C)-HP-(ZnP) , in which the radical cation resides on one of the three ZnP moieties, and for which lifetimes of up to 460 ns are found. On the other hand, investigations in organic media (i.e., toluene, THF, and benzonitrile) reveal a short cut, that is, the peripheral ZnP unit reacts directly with C to form (C)H P-(ZnP) . Substantial configurational rearrangements-placing ZnP and C in proximity to each other-are, however, necessary to ensure the required through space interactions (i.e., close approach). Consequently, the lifetime of (C)'"-H P(ZnP) is as short as 100 ps in benzonitrile. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA,.

Dendronized fullerene-porphyrin conjugates in ortho, meta, and para positions: A charge-transfer assay - Krokos, Evangelos; Schubert, Christina; Spaenig, Fabian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry-An Asian Journal, 2012)
The physicochemical characterization, that is, ground and excited state, of a new series of dendronized porphyrin/fullerene electron donor-acceptor conjugates in nonaqueous and aqueous environments is reported. In contrast to previous work, we detail the charge-separation and charge-recombination dynamics in zinc and copper metalloporphyrins as a function of first- and second-generation dendrons as well as a function of ortho, meta, and para substitution. Both have an appreciable impact on the microenvironments of the redox-active constituents, namely the porphyrins and the fullerenes. As a matter of fact, the resulting charge-transfer dynamics were considerably impacted by the interplay between the associated forces that reach from dendron-induced shielding to dipole-charge interactions. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Dendronizing and metalating trans-2 C60 tetraaryl porphyrins - A versatile approach toward water-soluble donor-acceptor conjugates - Ruppert, Michaela; Spänig, Fabian; Wielopolski, Mateusz; Jäger, Christof; Bauer, Walter; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2010)
We have realized for the first time a series of truly water-soluble and tightly coupled porphyrin/C electron-donor-acceptor conjugates in which the charge separation and charge recombination dynamics are controlled by modifying the nature of the dendrimer and/or the choice of the central metal atom. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA. Weinheim.

Designing carbon dots for enhanced photo-catalysis: Challenges and opportunities - Zdrazil, Lukas; Cadranel, Alejandro; Medved‘, Miroslav; Otyepka, Michal; Zbořil, Radek; Guldi, Dirk Michael (Chem, 2024)
Carbon dots (CDs) are a fascinating class of nanomaterials with a straightforward design by means of an organic chemistry toolbox and an unsurmountable potential in the field of artificial photosynthesis. The vast structural diversity of CDs and the complex photo-physics thereof impose, however, significant challenges on their full utilization. Gathering a profound understanding of the structure-activity relationship and precise identification of the photo-catalytically active sites within CDs is crucial. This review summarizes the current understanding of photo-catalytically active CD-based systems. First, we analyze the structural complexity of CDs in the context of hydrogen photo-production, addressing the different roles of CDs in photo-catalytic hydrogen evolution as photosensitizers, co-catalysts, and catalysts. Second, we present the most important aspects to be considered for the design of CDs-based photo-catalysts, focusing on the fine-tuning of optical properties and charge management and discussing the timescales of events in the photo-excited state. Both experimental and theoretical methods relevant to studying structurally complex CDs are outlined. Finally, we share our thoughts on the future opportunities in CD-based photo-catalysis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: carbon dots; functional materials; hydrogen production; photo-catalysis; SDG7: Affordable and clean energy; structure-property relationship

Designing Cascades of Electron Transfer Processes in Multicomponent Graphene Conjugates - Limosani, Francesca; Kaur, Ramandeep; Cataldo, Antonino; Bellucci, Stefano; Micciulla, Federico; Zanoni, Robertino; Lembo, Angelo; Wang, Bingzhe; Pizzoferrato, Roberto; Guldi, Dirk Michael; Tagliatesta, Pietro (Angewandte Chemie International Edition, 2020)
A novel family of nanocarbon-based materials was designed, synthesized, and probed within the context of charge-transfer cascades. We integrated electron-donating ferrocenes with light-harvesting/electron-donating (metallo)porphyrins and electron-accepting graphene nanoplates (GNP) into multicomponent conjugates. To control the rate of charge flow between the individual building blocks, we bridged them via oligo-p-phenyleneethynylenes of variable lengths by β-linkages and the Prato–Maggini reaction. With steady-state absorption, fluorescence, Raman, and XPS measurements we realized the basic physico-chemical characterization of the photo- and redox-active components and the multicomponent conjugates. Going beyond this, we performed transient absorption measurements and corroborated by single wavelength and target analyses that the selective (metallo)porphyrin photoexcitation triggers a cascade of charge transfer events, that is, charge separation, charge shift, and charge recombination, to enable the directed charge flow. The net result is a few nanosecond-lived charge-separated state featuring a GNP-delocalized electron and a one-electron oxidized ferrocenium.
CRIS-Team Scopus Importer:2020-10-23
Keywords: graphene nanoplates; zinc-tetraphenylporphyrin

Designing Squaraines to Control Charge Injection and Recombination Processes in NiO-based Dye-Sensitized Solar Cells - Langmar, Oliver; Saccone, Davide; Amat, Anna; Fantacci, Simona; Viscardi, Guido; Barolo, Claudia; Costa, Ruben Dario; Guldi, Dirk Michael (ChemSusChem, 2017)
Herein, the synthesis of a new family of squaraines (SQs) and their application in p-type dye-sensitized solar cells (DSSCs) is presented. In particular, two sets of SQs were designed featuring either two or four anchoring carboxylic groups combined with either oxygen or dicyanovinyl central groups. The SQs were characterized by using a joint theoretical, photophysical, and electrochemical approach. Importantly, the presence of different central groups forces a frozen cis (dicyanovinyl group) or a trans (oxygen group) SQ conformation. Based on the latter, the current work enables a direct comparison between cis and trans isomers as well as the impact of a different number of anchors. Considering their electron-accepting and light-harvesting character, they were tested in NiO-based DSSCs. Photocurrent-voltage, incident photon-to-current conversion efficiency (IPCE), and electrochemical impedance spectroscopy measurements were performed. By virtue of their different symmetry, stereochemistry, and number of carboxylic groups, altered adsorption behavior onto NiO electrodes as well as diverse charge injection and charge recombination dynamics were noted under operation conditions. SQs with four linkers in a frozen cis isomerism show the best charge collection properties among the investigated SQs, providing a valuable guideline for the molecular design of future SQs for p-type DSSCs. In addition, we assembled tandem DSSCs featuring SQ/NiO photocathodes and N719/TiO2 photoanodes. The IPCE of the resulting tandem DSSCs implies light harvesting throughout most of the visible part of the solar spectrum owing to the complementary absorption features of SQ and N719.
EAM Import::2019-03-13

Designing Ultrastrong Materials for Space Applications - Kotov, N. A.; Mamedov, A. A.; Prato, Maurizio; Guldi, Dirk Michael; Wicksted, J.; Hirsch, Andreas (UV/Optical/IR Space Telescopes: Innovative Technologies and Concepts, 2004)
Designing of ultrastrong materials that have relatively low weight to be used in space applications is discussed. Single wall carbon nanotubes (SWNT) are suitable for such application because of their exceptional mechanical properties. However, severe structural inhomogeneity result in the premature failure of hybrid SWNT/polymer materials. It has been found that a sequential layering of chemically-modified nanotubes and polyelectrolytes can greatly reduce the phase segregation and render SWNT composites highly homogeneous.

Design, synthesis and photoinduced processes in molecular interlocked photosynthetic [60]fullerene systems - Megiatto, Jackson D.; Guldi, Dirk Michael; Schuster, David I. (Chemical Society Reviews, 2020)
In natural photosynthesis, the protein backbone directs and positions primary and secondary electron donor and acceptor moieties in the reaction center to control the yield and kinetics of the sequential electron transfer reactions that transform light energy into chemical potential. Organization of the active cofactors is mainly driven by noncovalent interactions between the protein scaffold and the chromophores. Based on the natural system blueprint, several research efforts have investigated π-π stacking, ionic interactions as well as formation of hydrogen and coordinative bonds as noncovalent organizing principles for the assembly of electron donors and acceptors in artificial reaction centers. Introduction of supramolecular concepts into the organization of electron donor-acceptor in artificial photosynthetic models raises the possibility of applying template-directed synthesis techniques to assemble interlocked systems in which the photo-redox components are mechanically rather than covalently linked. Rotaxanes and catenanes are the leading examples of interlocked molecules, whose recent developments in synthetic chemistry have allowed their efficient preparation. Introduction of mechanical bonds into electron donor-acceptor systems allows the study of the interlocked components' submolecular motions and conformational changes, which are triggered by external stimuli, on the thermodynamic and kinetic parameters of photoinduced processes in artificial reaction centers. This Tutorial discusses our efforts in the synthesis and photophysical investigation of rotaxanes and catenanes decorated with peripheral electron donors and [60]fullerene as the acceptor. The assembly of our rotaxanes and catenanes is based on the classic 1,10-phenanthroline-copper(i) metal template strategy in conjunction with the virtues of the Cu(i)-catalyzed-1,3-dipolar cycloaddition of azides and alkynes (the CuAAC or "click" reaction) as the protocol for the final macrocyclization or stoppering reactions of the entwined precursors. Time-resolved emission and transient absorption experiments revealed that upon excitation, our multichromophoric rotaxanes and catenanes undergo a cascade of sequential energy and electron transfer reactions that ultimately yield charge separated states with lifetimes as long as 61 microseconds, thereby mimicking the functions of the natural systems. The importance of the Cu(i) ion (used to assemble the interlocked molecules) as an electronic relay in the photoinduced processes is also highlighted. The results of this research demonstrate the importance of the distinct molecular conformations adopted by rotaxanes and catenanes in the electron transfer dynamics and illustrate the versatility of interlocked molecules as scaffolds for the organization of donor-acceptor moieties in the design of artificial photosynthetic reaction centers.
CRIS-Team Scopus Importer:2020-01-31

Detailed investigations of ZnO photoelectrodes preparation for dye sensitized solar cells - Marczak, Renata; Werner, Fabian; Ahmad, Rameez; Lobaz, Volodymyr; Guldi, Dirk Michael; Peukert, Wolfgang (Langmuir, 2011)
Wurtzite ZnO hexagonal nanopyramids were successfully synthesized in the liquid phase from homogeneous methanolic solutions of zinc acetate and tetramethylammonium hydroxide at an excess of zinc ions. The formation and properties of the nanocrystals were examined as a function of synthesis conditions. No significant influence of the [Zn ]/[OH ] ratio was noticed on the final particle size, in spite of increased amounts of OH ions, which tend to accelerate the particle nucleation and growth. Nevertheless, the reactant concentration ratio influences the surface properties of the ZnO nanocrystals. Mesoporous ZnO films were prepared by doctor blading ethanolic pastes containing ZnO nanoparticles and ethyl cellulose onto FTO conductive glass substrate followed by calcination. Additionally, the influence of a plasticizer (triacetin)-used during the paste preparation-on the film quality was investigated. A higher content of ZnO nanoparticles and plasticizer in the pastes improved the film quality. Four different temperatures (i.e., 400, 425, 450, and 475 °C) were used for the film calcination and their influence on the structural properties of the films was characterized. In principle, increasing the calcination temperature goes hand in hand with an increase of particle size, as well as the pore diameter and reduction of the surface area. Suitable mesoporous films were employed as photoanodes in dye sensitized solar cells (DSSCs). In order to assess the effect of the varied parameters on complete DSSC devices-using cis-diisothiocyanato-bis(2,2′- bipyridyl-4,4′-dicarboxylato) ruthenium(II)bis(tetrabutylammonium (N719) as a sensitizer-incident photon to current efficiency (IPCE) and current voltage measurements were carried out. The IPCE measurements confirmed photoinduced electron injection from the dye, reaching IPCE values up to 76%. Furthermore, current-voltage characteristics of complete cells emphasized the importance of the proper preparation methods and temperatures. These features are important assets for the preparation of nanocrystalline ZnO based photoelectrodes and for improving the DSSC performance. © 2011 American Chemical Society.

Determination of the two-dimensional distributions of gold nanorods by multiwavelength analytical ultracentrifugation - Wawra, Simon; Pflug, Lukas; Thajudeen, Thaseem; Kryschi, Carola; Stingl, Michael; Peukert, Wolfgang (Nature Communications, 2018)
Properties of nanoparticles are influenced by various parameters like size, shape or composition. Comprehensive high throughput characterization techniques are urgently needed to improve synthesis, scale up to production and make way for new applications of multidimensional particulate systems. In this study, we present a method for measuring two-dimensional size distributions of plasmonic nanorods in a single experiment. Analytical ultracentrifuge equipped with a multiwavelength extinction detector is used to record the optical and sedimentation properties of gold nanorods simultaneously. A combination of sedimentation and extinction properties, both depending on diameter and length of the dispersed nanorods, is used to measure two-dimensional distributions of gold nanorod samples. The length, diameter, aspect ratio, volume, surface and cross-sectional distributions can be readily obtained from these results. As the technique can be extended to other non-spherical plasmonic particles and can be used for determining relative amounts of particles of different shapes it provides complete and quantitative insights into particulate systems.
EAM Import::2019-03-13

Determining the Attenuation Factor in Molecular Wires Featuring Covalent and Noncovalent Tectons - Vela, Sonia; Bauroth, Stefan; Atienza, Carmen; Molina-Ontoria, Agustin; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2016)
Hybrid covalent/supramolecular porphyrin–fullerene structures were synthesized as highly efficient molecular wires with a remarkably low attenuation factor (β=0.07±0.01 Å−1). Hydrogen-bonding interactions and p-phenylene oligomers of different lengths are responsible for efficient electron transfer in the molecular wires.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electron transfer; fullerenes; hydrogen bonds; molecular wires; porphyrinoids

Diastereoselective formation of homochiral flexible perylene bisimide cyclophanes and their hybrids with fullerenes - Solymosi, Iris; Krishna, Swathi; Nuin, Edurne; Maid, Harald; Scholz, Barbara; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Hirsch, Andreas (Chemical Science, 2021)
Cyclophanes of different ring sizes featuring perylene-3,4:9,10-tetracarboxylic acid bisimide (PBI) linked by flexible malonates were designed, synthesized, and investigated with respect to their structural, chemical and photo-physical properties. It is predominantly the number of PBIs and their geometric arrangement, which influence dramatically their properties. For example, two-PBI containing cyclophanes reveal physico-chemical characteristics that are governed by strong co-facial π–π interactions. This is in stark contrast to cyclophanes with either three or four PBIs. Key to co-facial π–π stackings are the flexible malonate linkers, which, in turn, set up the ways and means for diastereoselectivity of the homochiral PBIs at low temperatures, on one hand. In terms of selectivity, diastereomeric (M,M)/(P,P) : (M,P)/(P,M) pairs with a ratio of approximately 10 : 1 are discernible in the 1H NMR spectra in C2D2Cl4 and a complete diastereomeric excess is found in CD2Cl2. On the other hand, symmetry-breaking charge transfer as well as charge separation at room temperature are corroborated in steady-state and time-resolved photo-physical investigations. Less favourable are co-facial π–π stackings in the three-PBI containing cyclophanes. For statistical reasons, the diastereoisomers (M,M,M)/(P,P,P) and (M,M,P)/(P,P,M) occur here in a ratio of 1 : 3. In this case, symmetry-breaking charge transfer as well as charge separation are both slowed down. The work was rounded-off by integrating next to the PBIs, for the first time, hydrophobic or hydrophilic fullerenes into the resulting cyclophanes. Our novel fullerene–PBI cyclophanes reveal unprecedented diastereoselective formation of homochiral (M,M)/(P,P) pairs exceeding the traditional host–guest approach. Hybridization with fullerenes allows us to modulate the resulting solubility, stacking, cavity and chirality, which is of tremendous interest in the fiel
CRIS-Team WoS Importer:2021-10-29

Direct Covalent Coupling of Porphyrins to Graphene - Dasler, Daniela; Schäfer, Ricarda; Minameyer, Martin; Hitzenberger, Jakob; Hauke, Frank; Drewello, Thomas; Hirsch, Andreas (Journal of the American Chemical Society, 2017)

Direct exfoliation of graphite with a porphyrin - Creating functionalizable nanographene hybrids - Malig, Jenny; Stephenson, Adam W. I.; Wagner, Pawel; Wallace, Gordon G.; Officer, David L.; Guldi, Dirk Michael (Chemical Communications, 2012)
Exfoliation of graphite was achieved using a free-base porphyrin 1 resulting in an efficient fabrication of single-layer nanographene (NG)-1 hybrid platelets that can be further functionalized with other nanomaterials. The novel nanographene-porphyrin hybrids reveal efficient charge transfer in the excited state. © 2012 The Royal Society of Chemistry.

Direct metalation of a phthalocyanine monolayer on Ag(111) with coadsorbed iron atoms - Bai, Yun; Buchner, Florian; Wendahl, Matthew T.; Kellner, Ina; Bayer, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus; Gottfried, Michael (Journal of Physical Chemistry C, 2008)
An ordered monolayer of phthalocyanine on a silver(111) surface reacts with the stoichiometric amount of coadsorbed Fe atoms to form iron(II)- phthalocyanine. This surface-confined redox reaction was studied with X-ray photoelectron spectroscopy (XPS) and scanning tunneling microscopy (STM). The formation of iron-(II)-phthalocyanine was confirmed by comparison with the directly deposited complex. No side reactions such as the coordination of Fe atoms on the peripheral nitrogen atoms of the phthalocyanine molecules were observed. © 2008 American Chemical Society.

Discovery of Unforeseen Energy-Transfer-Based Transformations Using a Combined Screening Approach - Strieth-Kalthoff, Felix; Henkel, Christian; Teders, Michael; Kahnt, Axel; Knolle, Wolfgang; Gomez-Suarez, Adrian; Dirian, Konstantin; Alex, Wiebke; Bergander, Klaus; Daniliuc, Constantin G.; Abel, Bernd; Guldi, Dirk Michael; et al. (Chem, 2019)
The discovery of novel (catalytic) transformations and mechanisms is commonly based on rational design. However, many discoveries have resulted directly from experimental serendipity. Building on this, we report a two-dimensional screening protocol, combining "mechanism-based" and "reaction-based" screening and its application to the field of visible light photocatalysis. To this end, two energy-transfer-based cycloaddition reactions could be realized: a notably endergonic energy transfer process allows for the dearomative cycloaddition of benzothiophenes and related heterocycles. Moreover, by sensitization of enone moieties, a [2+2]-cycloaddition to alkynes and an unexpected cycloaddition-rearrangement cascade were discovered. Advanced spectro-scopic techniques (in particular transient absorption spectroscopy and pulse radiolysis) were utilized to investigate the underlying photophysical processes and gain insight into reaction kinetics. Combining these results with further mechanistic analysis can eventually turn out to be helpful upon knowledge-driven development of improved systems. Such screening approaches can thus provide complementary access toward novel and more efficient catalytic protocols.
CRIS-Team WoS Importer:2019-08-27

Dispersing Perylene Diimide/SWCNT Hybrids: Structural Insights at the Molecular Level and Fabricating Advanced Materials - Tsarfati, Yael; Strauß, Volker; Kuhri, Susanne; Krieg, Elisha; Weissman, Haim; Shimoni, Eyal; Baram, Jonathan; Guldi, Dirk Michael; Rybtchinski, Boris (Journal of the American Chemical Society, 2015)
The unique properties of carbon nanotubes (CNT) are advantageous for emerging applications. Yet, the CNT insolubility hampers their potential. Approaches based on covalent and noncovalent methodologies have been tested to realize stable dispersions of CNTs. Noncovalent approaches are of particular interest as they preserve the CNTs structures and properties. We report on hybrids, in which perylene diimide (PDI) amphiphiles are noncovalently immobilized onto single wall carbon nanotubes (SWCNT). The resulting hybrids were dispersed and exfoliated both in water and organic solvents in the presence of two different PDI derivatives, PP2b and PP3a. The dispersions were investigated using cryogenic transmission electron microscopy (cryo-TEM), providing unique structural insights into the exfoliation. A helical arrangement of PP2b assemblies on SWCNTs dominates in aqueous dispersions, while a single layer of PP2b and PP3a was found on SWCNTs in organic dispersions. The dispersions were probed by steady-state and time-resolved spectroscopies, revealing appreciable charge redistribution in the ground state, and an efficient electron transfer from SWCNTs to PDIs in the excited state. We also fabricated hybrid materials from the PP2b/SWCNT dispersions. A supramolecular membrane was prepared from aqueous dispersions and used for size-selective separation of gold nanoparticles. Hybrid buckypaper films were prepared from the organic dispersions. In the latter, high conductivity results from enhanced electronic communication and favorable morphology within the hybrid material. Our findings shed light onto SWCNT/dispersant molecular interactions, and introduce a versatile approach toward universal solution processing of SWCNT-based materials.
CRIS-Team Scopus Importer:2023-03-07

Dispersing silicon nanoparticles with a stirred media mill and subsequent functionalization with phenyl acetylene - Reindl, Armin; Cimpean, Carla Ramona; Bauer, Walter; Peukert, Wolfgang; Kryschi, Carola; Comanici, Radu; Ebbers, André (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
Silicon particles were dispersed in 1-butanol using a stirred media mill. Morphology, size and bulk structure of untreated, ground and styrenyl-functionalized silicon nanoparticles (SiNP) were examined using high-resolution transmission electron microscopy (HRTEM), dynamic light scattering (DLS) and X-ray diffraction (XRD). The amorphous oxide shell of the SiNP was removed by hydrofluoric acid (HF) etching. The resulting hydride (H)-terminated SiNP surfaces were functionalized with styrene via hydrosilylation of phenyl acetylene. Evidences for the styrenyl termination of the SiNP through Sisingle bondC bonds were obtained from diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), solid-state C nuclear magnetic resonance (NMR) and HRTEM. © 2007 Elsevier B.V. All rights reserved.
Keywords: Silicon nanoparticles; Stirred media mill; Hydrosilylation; Nuclear magnetic resonance

Dispersion and characterization of arc discharge single-walled carbon nanotubes-towards conducting transparent films - Rösner, Benedikt; Guldi, Dirk Michael; Chen, J.; Minett, A. I.; Fink, Rainer (Nanoscale, 2014)
This study addresses a combination of a well-developed and mild dispersion method and high-quality arc discharge single-walled carbon nanotubes (SWCNTs) as starting materials. Thus, we advance in fabrication of transparent, conducting films with extraordinary low material loss during SWCNT processing. The starting material was characterized by means of thermogravimetric analysis, high-resolution transmission electron microscopy and Raman spectroscopy. The quality of the starting material and produced dispersions was evaluated by ultraviolet and visible light absorption spectroscopy and Raman spectroscopy. A transparent conductive film was fabricated by drop-casting, whereas films were obtained with electrical to optical conductivity ratios (σ/ σ) as high as 2.2, combined with a loss of nanotube material during processing well below 20 wt%. High pressure carbon monoxide conversion (HiPCO) SWCNTs, which are very well described in the literature, were used for comparison. This journal is © the Partner Organisations 2014.

Distorted fused porphyrin-phthalocyanine conjugates: Synthesis and photophysics of supramolecular assembled systems with a pyridylfullerene - Pereira, Ana M. V. M.; Soares, Ana R. M.; Hausmann, Anita; Neves, Maria G. P. M. S.; Tome, Augusto C.; Silva, Artur M. S.; Cavaleiro, Jose A. S.; Guldi, Dirk Michael; Torres, Tomas (Physical Chemistry Chemical Physics, 2011)
In the current work, we report on the synthesis and photophysical features of supramolecular hybrid systems that are based on newly fused porphyrin-phthalocyanine (P-Pc) conjugates and a pyridylfullerene. The ZnP-ZnPc conjugate was synthesized in three steps starting with a Diels-Alder reaction between β-vinylporphyrin and fumaronitrile. The resulting mixture of isomeric adducts was then dehydrogenated to yield the corresponding benzo[b]porphyrin-2,2-dicarbonitrile. In the final step, cyclotetramerization with 4-tert-butylphthalonitrile, in the presence of zinc acetate, afforded the bis-metalated conjugate. Selective demetallation of ZnP led to the HP-ZnPc conjugate. For both conjugates steric hindrance is the inception to a bent configuration, which does, however, not preclude enlargement of the π-conjugated system, that is, the porphyrins and the phthalocyanines. The two conjugates coordinate N-(4-pyridyl)fullero[c] pyrrolidine giving rise to the corresponding supramolecular porphyrin- phthalocyanine-fullerene systems. Photophysical measurements corroborate a sequential deactivation in the excited state, namely an initial intramolecular energy transfer from ZnP or HP to ZnPc followed by an intramolecular charge transfer to yield ZnP-(ZnPc)-(C) and HP-(ZnPc)-(C), respectively. © the Owner Societies 2011.

Dithiafulvenyl-Extended N-Heterotriangulenes and Their Interaction with C60: Cooperative Fluorescence - Gliemann, Bettina; Strauß, Volker; Hitzenberger, Jakob; Dral, Pavlo O.; Hampel, Frank; Gisselbrecht, Jean-Paul; Drewello, Thomas; Thiel, Walter; Guldi, Dirk Michael; Kivala, Milan (Chemistry - A European Journal, 2017)
We describe the synthesis as well as the electronic and photophysical characterization of novel N-heterotriangulene derivatives decorated with methoxycarbonyl- and methyl-sulfanyl-substituted dithiafulvenyl moieties. The association of these electron-rich compounds with fullerene C60 as electron acceptor was investigated by means of photophysical, voltammetric, and mass spectrometric methods and rationalized by DFT calculations. Importantly, light-induced interactions between the dithiafulvene-substituted N-heterotriangulene bearing methoxycarbonyl substituents with C60 leads to cooperative fluorescence. Quantitative Job plot analyses by means of fluorescence spectroscopy and voltammetry confirm a 1:1 association with binding constants in the order of 104 m-1. Supportive results for the supramolecular assembly of both N-heterotriangulenes with C60 were obtained by ESI mass spectrometric investigations in the gas phase.
EAM Import::2019-03-13

Donor-acceptor conjugates of lanthanum endohedral metallofullerene and π-extended tetrathiafulvalene - Takano, Yuta; Angeles Herranz, M.; Martin, Nazario; Radhakrishnan, Shankara Gayathri; Guldi, Dirk Michael; Tsuchiya, Takahiro; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2010)
Stable donor-acceptor conjugates (2, 3) involving an endohedral metallofullerene, La @I -C , and π-extended tetrathiafulvalene (exTTF) have been synthesized by highly regioselective 1,3-dipolar cycloadditions of exTTF-containing azomethine ylides to the endofullerene, yielding exclusively [5,6] metallofulleropyrrolidines with C symmetry in high yields (68-77%). The cyclic voltammograms (CVs) of the conjugates reveal the redox active character of the system due to the presence of both donor and acceptor groups, that is, exTTF and La @I -C , respectively. Furthermore, the electrochemically reversible character of the endofullerene confirms the presence of the [5,6] adduct. Despite the relatively close proximity between the exTTF and the endohedral metallofullerene (EMF), only a weak electronic interaction was observed in the ground state, as evidenced by absorption spectroscopy and CV measurements of 2 and 3. On the other hand, in the excited state the fast formation of a radical ion-pair state (i.e., 6.0 × 10 s ), that is, the reduction of the electron accepting La @C and the oxidation of exTTF, evolves with lifetimes as long as several ns (3.0 × 10 s ) in toluene. Transient absorption spectroscopy experiments confirmed these observations. © 2010 American Chemical Society.

Do the intramolecular π interactions improve the stability of ionic, pyridine-carbene-based iridium(III) complexes? - Casillas, Ruben; et al. (Journal of Physical Chemistry C, 2013)

Driving the quadricyclane-to-norbornadiene isomerization by charge separation with perylenediimide as electron acceptor - Zika, Wiebke; Leng, Andreas; Weiß, René; Pinter, Simone; Schüßlbauer, Christoph; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Chemical Science, 2023)
Through comprehensive photo-assays, this study investigates the reaction coordinate governing the interconversion between quadricyclane (QC) and norbornadiene (NBD) upon photo-irradiation up to a wavelength of 550 nm. To harness this spectroscopic range for energy release, we link the NBD-core with a highly electron-accepting perylenediimide (PDI) with broad absorption, achieving strong electronic coupling between them. We detail the successful synthesis and present extensive DFT calculations to determine the amount of stored energy. By means of transient absorption spectroscopy, an oxidative electron transfer is observed during the QC-to-NBD isomerization following the initial PDI photoexcitation. This charge-separated state is key to triggering the back-isomerization with visible light excitation.
CRIS-Team Scopus Importer:2023-10-20

Dual Function of Naphthalenediimide Supramolecular Photocatalyst with Giant Internal Electric Field for Efficient Hydrogen and Oxygen Evolution - Liu, Liping (Small, 2024)

Dynamic Covalent Formation of Concave Disulfide Macrocycles Mechanically Interlocked with Single-Walled Carbon Nanotubes - Balakrishna, Bugga; Menon, Arjun; Cao, Kecheng; Gsänger, Sebastian; Beil, Sebastian B.; Villalva, Julia; Shyshov, Oleksandr; Martin, Oliver; Hirsch, Andreas; Meyer, Bernd; Kaiser, Ute; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2020)
The formation of discrete macrocycles wrapped around single-walled carbon nanotubes (SWCNTs) has recently emerged as an appealing strategy to functionalize these carbon nanomaterials and modify their properties. Here, we demonstrate that the reversible disulfide exchange reaction, which proceeds under mild conditions, can install relatively large amounts of mechanically interlocked disulfide macrocycles on the one-dimensional nanotubes. Size-selective functionalization of a mixture of SWCNTs of different diameters were observed, presumably arising from error correction and the presence of relatively rigid, curved π-systems in the key building blocks. A combination of UV/Vis/NIR, Raman, photoluminescence excitation, and transient absorption spectroscopy indicated that the small (6,4)-SWCNTs were predominantly functionalized by the small macrocycles 12, whereas the larger (6,5)-SWCNTs were an ideal match for the larger macrocycles 22. This size selectivity, which was rationalized computationally, could prove useful for the purification of nanotube mixtures, since the disulfide macrocycles can be removed quantitatively under mild reductive conditions.
CRIS-Team Scopus Importer:2020-09-04
Keywords: curved π-systems; disulfide exchange; mechanically interlocked architectures; single-walled carbon nanotubes; supramolecular chemistry

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Dynamic Kinetic Sensitization of beta-Dicarbonyl Compounds-Access to Medium-Sized Rings by De Mayo-Type Ring Expansion - Paulisch, Tiffany O.; Mai, Lukas; Strieth-Kalthoff, Felix; James, Michael J.; Henkel, Christian; Guldi, Dirk Michael; Glorius, Frank (Angewandte Chemie International Edition, 2021)
Herein, we present a photocatalyzed two-carbon ring expansion of beta-dicarbonyl compounds with unactivated olefins that provides facile access to medium-sized rings. Selective sensitization of the substoichiometric enol tautomer enables reactivity of substrates incompatible with the classical De Mayo reaction conditions. Key to success is the identification of the metal-based sensitizer fac-[Ir(CF3-pmb)(3)], which can be excited using common near-visible LEDs, and possesses a high triplet excited state energy of 73.3 kcal mol(-1). This exactly falls in the range between the triplet energies of the enol and keto tautomer, thereby enabling a dynamic kinetic sensitization. Demonstrating the applicability of fac-[Ir(CF3-pmb)(3)] as a photocatalyst in organic synthesis for the first time, we describe a two-step photocycloaddition-ring-opening cascade with beta-ketoesters, -diketones, and -ketoamides. The mechanism has been corroborated by time-resolved spectroscopy, as well as further experimental and computational studies.
CRIS-Team WoS Importer:2021-12-31

Dysregulation of the B lymphocyte compartment in patients with chronic graft-versus-host disease - Habenicht, Katharina Marie; Bootz, Anna; Schneider, Alexandra; Schäfer, Simon; Hoffmann, P.; Winkler, Julia; Wolff, D.; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Easy and versatile coating approach for long-living white hybrid light-emitting diodes - Niklaus, Lukas; Dakhil, Haider; Kostrzewa, Monika Maria; Brana Coto, Pedro; Sonnewald, Uwe; Wierschem, Andreas; Costa Riquelme, Rubén Dario (Materials Horizons, 2016)
Herein, we provide a new easy-to-do protocol for preparing luminescent rubber-like materials based on a wide palette of compounds, such as small-molecules, quantum dots, polymers, and coordination complexes. The combination of this new protocol with that for preparing similar rubbers based on fluorescent proteins states the universal character of our approach. This is further assessed by using comprehensive spectroscopic and rheological investigations. Furthermore, the novel luminescent rubbers are applied as downconverting packing systems to develop white hybrid light-emitting diodes (WHLEDs), which are heralded as a solid alternative to achieve energy-saving, solid-state, and white-emitting sources in the coming future. As such, the current work also provides a clear prospect of this emerging lighting technology by means of a direct comparison among WHLEDs fabricated with all the above-mentioned down-converting systems. Here, the use of rubbers based on coordination complexes outperforms the others in terms of both luminous efficiency and colour quality with an unprecedented stability superior to 1000 h under continuous operation conditions. This represents an order of magnitude enhancement compared to the state-of-the-art WHLEDs, while keeping luminous efficiencies of around 100 lm W-1.

Effective Ligand Passivation of Cu2O Nanoparticles through Solid-State Treatment with Mercaptopropionic Acid - Azimi, Seyed Hamed; Kuhri, Susanne; Osvet, Andres; Matt, Gebhard; Khanzada, Laraib Sarfraz; Lemmer, Mario; Luechinger, Norman A.; Larsson, Mats I.; Zeira, Eitan; Guldi, Dirk Michael; Brabec, Christoph (Journal of the American Chemical Society, 2014)
In colloidal nanoparticle (NPs) devices, trap state densities at their surface exert a profound impact on the rate of charge carrier recombination and, consequently, on the deterioration of the device performance. Here, we report on the successful application of a ligand exchange strategy to effectively passivate the surface of cuprite (Cu2O) NPs. Cu2O NPs were prepared by means of a novel synthetic route based on flame spray pyrolysis. FTIR, XRD, XPS, and HRTEM measurements corroborate the formation of cubic cuprite Cu2O nanocrystals, excluding the possible presence of undesired CuO or Cu phases. Most importantly, steady-state emission and transient absorption assays document that surface passivation results in substantial changes in the intensity of emissive excitonic states-centered at copper and oxygen vacancies-and in the lifetime of excitons near the band edge. To shed light onto ultrafast processes in Cu2O nanocrystals additional pump probe experiments on the femtosecond and nanosecond time scales were carried out. Two discernible species were observed: on one hand, an ultrafast component ( ps) that relates to the excitons; on the other hand, a long-lived component ( μs) that originates from the defects/trap states.
Keywords: Engineering controlled terms: Nanocrystals; Spray pyrolysis Charge carrier recombination; Colloidal nanoparticles; Ligand passivation; Mercaptopropionic acid; Pump-probe experiments; Steady-state emissions; Surface passivation; Transient absorption Engineering main heading: Excitons EMTREE drug terms: 3 mercaptopropionic acid; copper; copper nanoparticle; nanocrystal; oxygen EMTREE medical terms: article; assay; infrared spectroscopy; pyrolysis; solid; steady state; surface property; transient absorption assay; transmission electron microscopy; X ray photoelectron spectroscopy

Effect of Chelate Ring Size in Iron(II) Isothiocyanato Complexes with Tetradentate Tripyridyl-alkylamine Ligands on Spin Crossover Properties - Leibold, Michael; Kisslinger, Sandra; Heinemann, Frank Wilhelm; Hampel, Frank; Ichiyanagi, Yuko; Klein, Michael; Homenya, Patrick; Renz, Franz; Toftlund, Hans; Brehm, Georg; Schneider, Siegfried; Reiher, Markus; et al. (Zeitschrift für Anorganische und Allgemeine Chemie, 2016)
Iron(II) complexes of the type [Fe(L)(NCS)(2)] with tetradentate ligands L are well known to show spin crossover properties. However, this behavior is quite sensitive in regard to small changes of the ligand system. Starting from the thoroughly investigated complex [Fe(tmpa)(NCS)(2)] [tmpa = tris(2-pyridylmethyl)amine, also abbreviated as tpa in the literature] we modified the ligand by increasing systematically the chelate ring sizes from 5 to 6 thus obtaining complexes [Fe(pmea)(NCS)(2)], [Fe(pmap)(NCS)(2)], and [Fe(tepa)(NCS)(2)] [pmea = N,N-bis[(2-pyridyl)methyl]-2-(2-pyridyl)ethylamine, pmap = N,N-bis[2-(2-pyridyl)ethyl]-(2-pyridyl)methylamine, and tepa = tris[2-(2-pyridyl)ethyl]amine]. All complexes were structurally characterized and spin crossover properties were investigated using Mo ss bauer spectroscopy, magnetic measurements, and IR/Raman analyses. The results demonstrated that only the iron complexes with tmpa and pmea showed spin crossover properties, whereas the complexes with the ligands pmap and tepa only formed high spin complexes. Furthermore, DFT calculations supported these findings demonstrating again the strong influence of ligand environment. Herein the effect of increasing the chelate ring sizes in iron(II) isothiocyanato complexes with tetradentate tripyridyl-alkylamine ligands is clearly demonstrated.
Keywords: Tetradentate pyridyl ligands; Spin crossover; LIESST effect; Mossbauer; Iron

Effect of cytosine and adenine on graphene oxide for the sensing of dopamine: Electrochemical and theoretical studies - Zhao, Yulin; Kumar, Mohan; Freiberger, Markus; Kudur Jayaprakash, Gururaj; Wang, Miao; Reddy, Sathish; Yang, Chenxin; Zhao, Wei (Microchemical Journal, 2024)
In this work, the electrochemical interaction between dopamine and cytosine/adenine on the graphene oxide (GO) is elucidated by quantum chemical simulation methods. Initially, GO, cytosine-functionalized GO (CGO), and adenine-functionalized GO (AGO) were prepared, and then utilized for the carbon paste electrode (CPE) modification. The as-prepared CGO-modified CPE (CGCPE) and AGO-modified CPE (AGCPE) were applied for the electrochemical sensing of dopamine (DA), and the obtained consequences illustrate the improved sensitivity of modified CPEs (MCPEs) compared to bare CPE (BCPE). Here, applied theoretical concepts based on analytical Fukui functions and frontier molecular orbitals (FMO) for cytosine and adenine functional groups in order to find active sites, and explained with evidence for the detection of DA by enhancing sensitivity. Moreover, the AGCPE has been shown higher electrochemical response compared to CGCPE for the detection of DA, and this result also agreed with theoretically from Global electron transfer results. The MCPEs were also utilized to examine the different electrochemical parameters and determine the DA concentration in the nanomolar range. The detection limit for CGCPE and AGCPE was found to be 9 nm and 7 nm, respectively.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Adenine; Cytosine; Dopamine; Frontier molecular orbitals; Graphene oxide

Effect of PCBM on the photodegradation kinetics of polymers for organic photovoltaics - Distler, Andreas; Kutka, Peter; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Guldi, Dirk Michael; Di Nuzzo, Daniele; Meskers, Stefan C. J.; Janssen, Rene A. J. (Chemistry of Materials, 2012)
The photo-oxidation behavior of three different polymers-namely, poly(3-hexylthiophene) (P3HT), poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2, 1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), and poly[2,6-(4,4-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-alt- 4,7-(2,1,3-benzothiadiazole)] (Si-PCPDTBT)-is investigated in neat polymer films and in blends with [6,6]-phenyl-C-butyric acid methyl ester (PCBM) for different polymer:PCBM ratios. PCBM is shown to have both stabilizing and destabilizing effects, the extent of which is dependent on the type of polymer with which it is blended. Screening of the polymer from incident light by PCBM turns out to play an only minor role in the stabilization of P3HT. Quenching of the polymer excited states is also not a significant stabilization mechanism, as demonstrated by the comparison of the reduction of photo-oxidation rates to the extent of photoluminescence quenching by PCBM and 2,7-dinitrofluorenone (DNF). Photoinduced absorption spectroscopy reveals that the enhanced degradation of C-PCPDTBT in blend films with PCBM correlates with the population of the polymer triplet state via the polymer:PCBM charge-transfer state. © 2012 American Chemical Society.

Effect of the triazole ring in zinc porphyrin-fullerene dyads on the charge transfer processes in NiO-based devices - Nikolaou, Vasilis; Plass, Fabian; Planchat, Aurelien; Charisiadis, Asterios; Charalambidis, Georgios; Angaridis, Panagiotis A.; Kahnt, Axel; Odobel, Fabrice; Coutsolelos, Athanassios G. (Physical Chemistry Chemical Physics, 2018)
Herein, the synthesis of three covalently linked donor-acceptor zinc porphyrin-fullerene (ZnP-C-60) dyads (C(60)trZnPCOOH, C(60)trZnPtrCOOH and C60ZnPCOOH) is described, and their application as sensitizers in NiO-based dye-sensitized solar cells (DSCs) is discussed. To the best of our knowledge, this is the first example where covalently linked ZnP-C-60 dyads have been used as chromophores in NiO-based DSCs. In an effort to examine whether the distance of the chromophore from the electron acceptor entity and/or the NiO surface affects the performance of the cells, a triazole ring was introduced as a spacer between ZnP and the two peripheral units C-60 and -COOH. The triazole ring was inserted between ZnP and C-60 in dyad C(60)trZnPCOOH, whereas both the anchoring group and C-60 were connected to ZnP through triazole spacers in C(60)trZnPtrCOOH, and dyad C60ZnPCOOH did not contain any triazole linker. Photophysical investigation performed by ultrafast transient absorption spectroscopy in solution and on the NiO surface demonstrated that all the porphyrin-fullerene dyads exhibited long-lived charge-separated states due to electron shifts from the reduced porphyrin core to C-60. The transient experiments performed in solution showed that the presence of triazole ring influenced the photophysical properties of the dyads C(60)trZnPCOOH and C(60)trZnPtrCOOH and in particular, increased the lifetime of the charge-separated states compared to that of the C60ZnPCOOH dyad. On the other hand, the corresponding studies on the NiO surface proved that the triazole spacer has a rather moderate impact on the charge separation (NiO-ZnP center dot+-C-60(center dot-)) and charge recombination (NiO-(3)*ZnP-C-60) rate constants. All three dyads exhibited enhanced performance in terms of photovoltaic measurements with more than threefold increase compared to the reference compound PhtrZnPCOOH in which the C-60 acceptor is absent. Two different electrolytes were examined (I-3(-)/I- and Co-III/II) and in most cases, the presence of the triazole ring enhanced their photovoltaic performance. The best performing dyad in I-3(-)/I- was C(60)trZnPCOOH (PCE = 0.076%); in Co-III/II, the best performing dyad was C(60)trZnPtrCOOH (PCE = 0.074%).
Created from Fastlane, WoS look-up

Efficient Access to 5-Bromo- and 5,6-Dibromophenanthroline Ligands - Stumper, Anne; Pilz, Thomas David; Schaub, Markus; Goerls, Helmar; Sorsche, Dieter; Peuntinger, Katrin; Guldi, Dirk Michael; Rau, Sven (European Journal of Inorganic Chemistry, 2017)
Bromo-functionalized precursor molecules are essential for generating desired target compounds through cross-coupling reactions. Herein we show an improved synthetic route, feasible at low temperatures and affording high yields, to the ligands 5-bromo-1,10-phenanthroline (1) and 5,6-dibromo-1,10-phenanthroline (2). The corresponding ruthenium complexes, containing various equivalents of ligand 2, are easily accessible in high yields, including the analogue of tris-homoleptic [Ru(bpy)3]2+ (bpy = 2,2′-bipyridine), [Ru(2)3]2+. X-ray diffraction analyses have provided detailed information on the structures of the ligands and their corresponding metal complexes. An investigation of the electrochemical properties has provided detailed information on the 3MLCT state localized on 2. We show the conversion of heteroleptic ruthenium complexes of these ligands in Suzuki cross-coupling reactions whereas the ligands did not undergo reaction under the same conditions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bromine; Cross-coupling; N ligands; Ruthenium; Synthesis design

Efficient and Stable Solid-State Dye-Sensitized Solar Cells by the Combination of Phosphonium Organic Ionic Plastic Crystals with Silica - Lennert, Annkatrin; Wagner, Klaudia; Yunis, Ruhamah; Pringle, Jennifer M.; Guldi, Dirk Michael; Officer, David L. (ACS Applied Materials and Interfaces, 2018)
Remarkably efficient quasi-solid-state dye-sensitized solar cells (DSSCs) have been fabricated using organic ionic plastic crystal electrolytes based on a small triethyl(methyl)phosphonium [P1222] cation and two types of sulfonamide anions, bis(fluorosulfonyl)amide (FSA) and bis(trifluoromethanesulfonyl)amide (TFSA), in combination with varying amounts of silica (SiO2). Solar cell efficiencies of up to 7.4% were obtained, which is comparable to our benchmark efficiencies of liquid (acetonitrile) electrolyte-based devices. Such a high efficiency for DSSCs using quasi-solid-state electrolytes is attributed to improved ionic conductivity, enhanced redox couple transport, improved interfacial interaction between the electrolyte and the electrode as well as decreased resistance at both electrode interfaces. Notably, the devices with the silica-containing electrolytes displayed excellent stability after 5 months of storage, with the most stable devices, formed with either plastic crystal electrolyte containing 2% silica, showing no decrease in efficiency.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; phosphonium OIPC; plastic crystals; silica composites; solid-state electrolyte; stability

Efficient charge-transfer from diketopyrrolopyrroles to single-walled carbon nanotubes - Papadopoulos, Ilias; Menon, Arjun; Plass, Fabian; Molina, Desire; Harreiß, Christina; Kahnt, Axel; Spiecker, Erdmann; Sastre-Santos, Angela; Guldi, Dirk Michael (Nanoscale, 2021)
In this contribution, the excited state charge-transfer interactions between single-walled carbon nanotubes (SWCNTs) and a variety of phenyl, 4-bromophenyl, and thiophene substituted diketopyrrolopyrroles (DPPs), is described. Atomic force microscopy (AFM) and aberration corrected high resolution transmission electron microscopy (AC-HRTEM) corroborated the successful formation of DPP/SWCNTs. Steady-state absorption, fluorescence, and Raman spectroscopies all gave insights into the impact on their ground and excited states as well as on the nature of their electronic communication/interaction. Of great value was time-resolved transient absorption spectroscopy on the femto- and nanosecond time-scales; it assisted in deciphering the charge-transfer mechanism from the DPPs to the SWCNT and in analyzing the dynamics thereof with transfer efficiencies of up to 81%. Important confirmation for the one-electron oxidized DPPs came from pulse radiolysis assays with focus on establishing their spectral fingerprints. Our full-fledged work demonstrates that the successful preparation of stable DPP/SWCNTs represents an important step towards establishing them as a viable alternative to porphyrin-based systems in emerging applications such as solar energy conversion.
CRIS-Team WoS Importer:2021-07-16

Efficient Energy-Conversion Materials for the Future: Understanding and Tailoring Charge-Transfer Processes in Carbon Nanostructures - Strauß, Volker; Roth, Alexandra Marina; Sekita, Michael; Guldi, Dirk Michael (Chem, 2016)
In this review, we survey the role of carbon-based nanomaterials in energy-conversion schemes. In particular, we highlight charge-transfer processes on the molecular scale in sp2 carbon in zero dimensions (fullerenes), sp2 carbon in one dimension (carbon nanotubes), sp2 carbon in two dimensions (graphene), and sp2/sp3 carbon in zero and two dimensions (defectuous carbon nanostructures). As such, we conclude that the versatility of carbon-based nanomaterials in terms of structural and electronic properties renders them broadly applicable electroactive components for future energy devices.
CRIS-Team Scopus Importer:2023-03-07
Keywords: artificial photosynthesis; carbon nanodots; carbon nanostructures; carbon nanotubes; charge transfer; fullerenes; graphene; light harvesting

Efficient light harvesting anionic heptamethine cyanine-[60] and [70]fullerene hybrids - Villegas, Carmen; Krokos, Evangelos; Bouit, Pierre-Antoine; Delgado, Juan Luis; Guldi, Dirk Michael; Martin, Nazario (Energy and Environmental Science, 2011)
New anionic fullerene-heptamethine conjugates absorbing as far as 900 nm have been synthesized and fully characterized by physicochemical means. In terms of electron transfer, we have succeeded in realizing the rarely occurring scenario of a charge transfer commencing with a higher excited state. Kinetic studies reveal that charge separation and charge recombination dynamics occur in the normal and inverted Marcus region, respectively. © 2011 The Royal Society of Chemistry.

Efficient Low Driving Force Charge Separation in an Electron Deficient Zn-Porphyrin-Fullerene Donor-Acceptor Conjugate - Wolf, Maximilian; Costa, Joana I. T.; Minameyer, Martin; Drewello, Thomas; Tome, Augusto C.; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2019)
Here, we present a novel conjugate based on a weakly electron-donating Zn(H)-meso-tetrakis(pentafluorophenyl)porphyrin linked to a strongly electron-accepting C-60. From spectroscopic and electrochemical investigations a 1.9 eV high charge-separated state is derived. Transient absorption spectroscopy measurements analyzed by global target analysis confirmed the successful charge separation with a quantum yield of 72% despite an overall small driving force of only 0.2 eV. The charge separated state lifetime is in the nanosecond range. Considering that 90% of the singlet excited state energy is transiently stored in the charge-separated state, we conclude a charge separation energy efficiency of 65%.
CRIS-Team WoS Importer:2019-12-13

Efficient Photocatalytic Hydrogen and Oxygen Evolution by Side-Group Engineered Benzodiimidazole Oligomers with Strong Built-in Electric Fields and Short-Range Crystallinity - Liu, Liping (Angewandte Chemie International Edition, 2022)

Efficient synthetic access to cationic dendrons and their application for ZnO nanoparticles surface functionalization: New building blocks for dye-sensitized solar cells - Gnichwitz, Jan-Frederik; Marczak, Renata; Werner, Fabian; Lang, Nina; Jux, Norbert; Guldi, Dirk Michael; Peukert, Wolfgang; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A new concept for the efficient synthesis of cationic dendrons, 4-tert-butyl-1-(3-(3,4-dihydroxybenzamido)benzyl)pyridinium bromide (17), 1,1′-(5-(3,4-dihydroxybenzamido)-1,3-phenylene)bis(methylene) bis(4-tert-butylpyridinium) bromide (18), N1,N7-bis(3-(4-tert-butyl-pyridium- methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenyl-amino) -3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (19), and N1,N7-bis(3,5-bis(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3, 5-bis(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3, 4-dihydroxybenzamido)heptanediamide hexabromide (20), and their facile binding to zinc oxide (ZnO) nanostructures is introduced. Dendrons containing highly reactive benzylic bromides reacted readily with 4-tert-butyl-pyridine and resulted in cationic dendrons. Furthermore, these permanently positively charged dendrons were equipped with a catechol anchor group. This enabled ZnO surface functionalization by simple immersion. The adsorption of 17, 18, 19, and 20 on the colloidal nanoparticles was monitored by Langmuir isotherms. The highest obtained experimental loadings correspond to 99.5%, 98.6%, 99.1%, and 42.5% of the particle surface for 17, 18, 19, and 20, respectively. These results indicate insufficient adsorption of the largest molecule 20 leading to reduced colloidal stability of the nanoparticles, while an enhanced stability after grafting with 17, 18, and 19 was observed. Mesoporous films suitable for the use as electrodes in dye-sensitized solar cells (DSSCs) were prepared. Subsequently, the films were functionalized with 18, 19, or 20 and sensitized with zinc-5,15-bis-[2′,6′-bis-2″,2″-bis-(carboxy)- ethyl-methyl-4′-tert-butyl-pheny]-10,20-bis-(4′-tert-butylphenyl) porphyrin-octasodium-salt. UV-vis absorption spectra confirmed that 18, 19, and 20 are suitable for the stable electrostatic attachment of the dye. Current-voltage characteristics of complete cells demonstrated that increasing positive functionalization of the ZnO surface leads to decreased open circuit voltages (V ). All V values were around 0.4 V with a maximum for the 18 functionalized ZnO film of 0.45 V. The maximum cell efficiency obtained (0.31%) is rather high, considering the narrow spectral absorption of the dye and the rather thin ZnO films used. Finally, incident photon to current efficiency (IPCE) measurements confirmed photoinduced electron injection from the dye. These features are important assets for applications in particle technology and even facilitated advanced devices like a supramolecular DSSC complete with a subsequent layer of negatively charged porphyrins. © 2010 American Chemical Society.

Efficient utilization of higher-lying excited states to trigger charge-transfer events - Bouit, Pierre-Antoine; Spänig, Fabian; Kuzmanich, Gregory; Krokos, Evangelos; Oelsner, Christian; Garcia-Garibay, Miguel A.; Delgado, Juan Luis; Martin, Nazario; Guldi, Dirk Michael (Chemistry - A European Journal, 2010)
Several new fullerene-heptamethine conjugates, which absorb as far as into the infrared spectrum as 800 nm, have been synthesized and fully characterized by physicochemical means. In terms of optical and electrochemical characteristics, appreciable electronic coupling between both electroactive species is deduced. The latter also reflect the excited-state features. To this end, time-resolved, transient absorption measurements revealed that photoexcitation is followed by a sequence of charge-transfer events which evolve from higher singlet excited states (i.e., S-fast charge transfer) and the lowest singlet excited state of the heptamethine cyanine (i.e., S - slow charge transfer), as the electron donor, to either a covalently linked C or C as the electron acceptor. Finally, charge transfer from photoexcited C/ C completes the charge-transfer sequence. The slow internal conversion within the light-harvesting heptamethine cyanine and the strong electronic coupling between the individual constituents are particularly beneficial to this process. © 2010 Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim.

Electroactive carbon nanoforms: A comparative study via sequential arylation and click chemistry reactions - Mateos-Gil, Jaime; Rodriguez-Perez, Laura; Moreno-Oliva, Maria; Katsukis, Georgios; Romero-Nieto, Carlos; Angeles Herranz, Ma; Guldi, Dirk Michael; Martin, Nazario (Nanoscale, 2015)
The reactivity of several carbon nanoforms (CNFs), single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs) and graphene, has been investigated through a combination of arylation and click chemistry CuI-mediated azide-alkyne cycloaddition (CuAAC) reactions. The approach is based on the incorporation of electroactive π-extended tetrathiafulvalene (exTTF) units into the triazole linkers to modulate the electronic properties of the obtained conjugates. The introduction of strain, by bending the planar graphene sheet into a 3D carbon framework, is responsible for the singular reactivity observed in carbon nanotubes. The formed nanoconjugates were fully characterized by analytical, spectroscopic, and microscopic techniques (TGA, FTIR, Raman, UV-Vis-NIR, cyclic voltammetry, TEM and XPS). In the case of SWCNT conjugates, where the functionalization degree is higher, a series of steady-state and time resolved spectroscopy experiments revealed a photoinduced electron transfer from the exTTF unit to the electron-accepting SWCNT.
CRIS-Team Scopus Importer:2023-03-07

Electrochemical polymerization and characterization of polypyrrole on Mg-Al alloy (AZ91D) - Turhan, Can Metehan; Weiser, Martin; Killian, Manuela; Leitner, Bernhard; Virtanen, Sannakaisa (Synthetic Metals, 2011)

Electroluminescence: From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins (Adv. Funct. Mater. 37/2016) - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Martí, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel Georg; Costa, Ruben Dario (Advanced Functional Materials, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Electron-accepting phthalocyanine-pyrene conjugates: Towards liquid phase exfoliation of graphite and photoactive nanohybrid formation with graphene - Roth, Alexandra Marina; Ragoussi, Maria-Eleni; Wibmer, Leonie; Katsukis, Georgios; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2014)
Herein, we describe the synthesis of a zinc(ii) alkylsulfonylphthalocyanine-pyrene conjugate, its assembly with highly exfoliated graphite, and the investigation of the photophysical properties of the resulting nanohybrid. The presence of the pyrene unit in the conjugate is decisive in terms of non-covalently immobilizing the electron accepting phthalocyanines onto the basal plane of highly exfoliated graphite. As a matter of fact, strong interactions dominate the electronic properties of the nanohybrid in both the ground and excited states. For example, femtosecond pump probe experiments assist in corroborating an ultrafast charge separation, that is, the generation of the one-electron reduced radical anion of the phthalocyanine and one-electron oxidized graphene after irradiation at 387 nm, followed by slow charge recombination. © 2014 the Partner Organisations.
CRIS-Team Scopus Importer:2023-03-07

Electron accepting porphycenes on graphene - Costa, Ruben Dario; Malig, Jenny; Brenner, Wolfgang; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2013)
The versatility of nanographene (NG) as an electron donor is demonstrated when integrated together with an electron accepting porphycene into a novel electron NG hybrid. This feature is further exploited in dye-sensitized solar cells (DSSCs), in which photoanodes (ZnO) reveal a cascade of electron flow as modus operandi. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electron-donating behavior of few-layer graphene in covalent ensembles with electron-accepting phthalocyanines - Ragoussi, Maria-Eleni; Katsukis, Georgios; Roth, Alexandra Marina; Malig, Jenny; De La Torre, Gema; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2014)
We describe herein the first example of highly exfoliated graphene covalently linked to electron accepting phthalocyanines. The functionalization of the nanocarbon surface with alkylsulfonyl phthalocyanines was attained by means of a "click" chemistry protocol. The new ensemble was fully characterized (thermogravimetric analysis, atomic force microscopy, transmission electron microscopy and Raman, as well as ground-state absorption) and was studied in terms of electron donor-acceptor interactions in the ground and in the excited state. In particular, a series of steady-state and time-resolved spectroscopy experiments demonstrated photoinduced electron transfer from the graphene to the electron-accepting phthalocyanines. This is the first example of an electron donor-acceptor nanoconjugate, that is, few-layer graphene/phthalocyanine, pinpointing the uncommon electron donating character of graphene. © 2014 American Chemical Society.

Electron donor-acceptor interactions in regioselectively synthesized exTTF2-C70(CF3)10 dyads - Takano, Yuta; Angeles Herranz, M.; Martin, Nazario; De Miguel Rojas, Gustavo; Guldi, Dirk Michael; Kareev, Ivan E.; Strauss, Steven H.; Boltalina, Olga V.; Tsuchiya, Takahiro; Akasaka, Takeshi (Chemistry - A European Journal, 2010)
The decakis(trifluoromethyl)fullerene C-CO(CF ) in which the CF groups are arranged on a para-meta-para ribbon of C(CF) edge-sharing hexagons, and which has now been prepared in quantities of hundreds of milligrams, was reacted under standard Bingel-Hirsch conditions with a bis-π-extended tetrathiafulvalene (exTTF) malonate derivative to afford a single cxTTF-C(CF) regioisomer in 80% yield based on consumed starting material. The highly soluble hybrid was thoroughly characterized by using ID H, C, and F NMR, 2D NMR, and UV/Vis spectroscopy; matrix-assisted laser desorption ionization (MALDI) mass spectrometry; and electrochemistry. The cyclic voltammogram of the exTTFC(CF) dyad revealed an irreversible second reduction process, which is indicative of a typical retro-Bingel reaction; whereas the usual phenomenon of exTTF inverted potentials (E>E), resulting in a single, two-electron oxidation process, was also observed. Steady-state and time-resolved photolytic techniques demonstrated that the C-C(CF)singlet excited state is subject to a rapid electron-transfer quenching. The resulting charge-separated states were identified by transient absorption spectroscopy, and radical pair lifetimes of the order of 300 ps in toluene were determined. The exTTFC(CF), dyad represents the first example of exploitation of the highly soluble trifluoromethylated fullerenes for the construction of systems able to mimic the photosynthetic process, and is therefore of interest in the search for new materials for photovoltaic applications. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA,.

Electron-enriched supramolecular PDI-SiO2 promoting PDS activation for enhanced photocatalytic advanced oxidation - Liu, Liping (Applied Catalysis B-Environmental, 2024)

Electronically Tuned Asymmetric meso-Substituted Porphyrins for p-Type Solar Cells - Grzegorzek, Norbert; Zieleniewska, Anna; Schür, Annika; Maichle-Mössmer, Cäcilia; Killian, Manuela; Guldi, Dirk Michael; Chernick, Erin T. (ChemPlusChem, 2019)
A series of electronically tuned asymmetric porphyrins have been synthesized for use in p-type solar cells. The porphyrin derivatives were strategically designed with electron-withdrawing capability and an electronic dipole gradient to aid in electron-harvesting capacity from a nickel oxide cathode. Specifically, the porphyrins were substituted at the meso position with different arrangements of the electron-withdrawing pentafluorobenzene moiety, electron-donating/coordinating 4-pyridyl ligand, and an electron withdrawing/synthetically modifiable 4-cyanophenyl unit. Two distinct free-base porphyrins were synthesized, one of which was further metallated with nickel(II). The porphyrins were fully characterized and their electronic properties explored experimentally by electrochemistry, and both steady state and time-resolved spectroscopy. Finally, the porphyrins were incorporated into a p-type solar cell device utilizing NiO as the cathode, and demonstrating a preliminary maximum performance of η(%)=0.082 and IPCE MAX (%)=26.0 without co-sensitization.
CRIS-Team Scopus Importer:2019-05-28
Keywords: dye-sensitized solar cells; light harvesting; nickel; photosensitizers; porphyrinoids

Electronic Communication across Porphyrin Hexabenzocoronene Isomers - Martin, Max; Lungerich, Dominik; Haines, Philipp; Hampel, Frank; Jux, Norbert (Angewandte Chemie International Edition, 2019)
Single-molecule electronic components (SMECs) are envisioned as next-generation building blocks in quantum circuit systems. However, challenges such as the reproducibility of the electrode attachment to the individual molecules hamper their fundamental investigation. For our purpose, we introduced quasi optoelectronic electrodes (QOEs) that allow for rapid investigations of the properties and suitability of compounds for molecular electronic devices. In particular, we probed hexa-peri-hexabenzocoronene (HBC) as a model system for D6h-symmetrical nanographenes, with porphyrins as QOEs attached to the periphery. We prepared selectively bis-porphyrin-functionalized HBCs with ortho-, meta- and para-substitution and studied their communication properties, in correlation to the geometrical alignment and size of the system, by electrochemistry and optical spectroscopy. Further insights into structure–property relationships were gained by DFT calculations and X-ray diffraction analysis.
CRIS-Team Scopus Importer:2019-06-04
Keywords: exchange interactions; hydrocarbons; molecular electronics; porphyrinoids; UV/Vis spectroscopy

Electronic Energy Transduction from Ru(py)4 - Cadranel, Alejandro; Oviedo, Paola S.; Albores, Pablo; Baraldo, Luis M.; Guldi, Dirk Michael; Hodak, Jose H. (Inorganic Chemistry)
Despite the large body of work on Ru(bpy)2 sensitizer fragments, the same attention has not been devoted to their Ru(py)4 analogues. In this context, we explored the donor-acceptor trans-[Ru(L)4(μ-NC)Cr(CN)52]4-, where L = pyridine, 4-methoxypyridine, 4-dimethylaminopyridine. We report on the synthesis and the crystal structure as well as the electrochemical, spectroscopical, and photophysical properties of these trimetallic complexes, including transient absorption measurements. We observed emission from chromium-centered d-d states upon illuminating into either MLCT or MM′CT absorptions of Ru(L)4 or Ru-Cr, respectively. The underlying energy transfer is as fast as 600 fs with quantum efficiencies ranging from 10% to 100%. These results document that Ru(py)4 sensitizer fragments are as efficient as Ru(bpy)2 in short-range energy transfer scenarios.
CRIS-Team Scopus Importer:2022-04-14

Electron transfer in a supramolecular associate of a fullerene fragment - Krick Calderon, Rafael; Gallego, Maria; Calbo, Joaquin; Arago, Juan; Calderon, Rafael M. Krick; Liquido, Fernando H.; Iwamoto, Takahiro; Greene, Allison K.; Jackson, Edward A.; Perez, Emilio M.; Orti, Enrique; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2014)
Herein, we investigate the association of a fullerene fragment, hemifullerene CH, with an electron-donating bowl-shaped tetrathiafulvalene derivative (truxTTF). UV/Vis titrations and DFT calculations support formation of the supramolecular complex, for which an association constant of log K=3.6±0.3 in CHCl at room temperature is calculated. Remarkably, electron transfer from truxTTF to CH to form the fully charge-separated species takes place upon irradiation of the associate with light, constituting the first example in which a fullerene fragment mimics the electron-accepting behavior of fullerenes within a supramolecular complex. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Electron transfer through rigid organic molecular wires enhanced by electronic and electron–vibration coupling - Sukegawa, Junpei; Schubert, Christina; Zhu, Xiaozhang; Tsuji, Hayato; Guldi, Dirk Michael; Nakamura, Eiichi (Nature Chemistry, 2014)
Electron transfer (ET) is a fundamental process in a wide range of biological systems, photovoltaics and molecular electronics. Therefore to understand the relationship between molecular structure and ET properties is of prime importance. For this purpose, photoinduced ET has been studied extensively using donor–bridge–acceptor molecules, in which π-conjugated molecular wires are employed as bridges. Here, we demonstrate that carbon-bridged oligo-p-phenylenevinylene (COPV), which is both rigid and flat, shows an 840-fold increase in the ET rate compared with the equivalent flexible molecular bridges. A 120-fold rate enhancement is explained in terms of enhanced electronic coupling between the electron donor and the electron acceptor because of effective conjugation through the COPVs. The remainder of the rate enhancement is explained by inelastic electron tunnelling through COPV caused by electron–vibration coupling, unprecedented for organic molecular wires in solution at room temperature. This type of nonlinear effect demonstrates the versatility and potential practical utility of COPVs in molecular device applications.

Electron vs energy transfer in arrays featuring two Bodipy chromophores axially bound to a Sn(IV) porphyrin via a phenolate or benzoate bridge - Lazarides, Theodore; Kuhri, Susanne; Charalambidis, Georgios; Panda, Manas K.; Guldi, Dirk Michael; Coutsolelos, Athanassios G. (Inorganic Chemistry, 2012)
In this report we describe the synthesis of multichromophore arrays consisting of two Bodipy units axially bound to a Sn(IV) porphyrin center either via a phenolate (3) or via a carboxylate (6) functionality. Absorption spectra and electrochemical studies show that the Bodipy and porphyrin chromophores interact weakly in the ground state. However, steady-state emission and excitation spectra at room temperature reveal that fluorescence from both the Bodipy and the porphyrin of 3 are strongly quenched suggesting that, in the excited state, energy and/or electron transfer might occur. Indeed, as transient absorption experiments show, selective excitation of Bodipy in 3 results in a rapid decay (τ ≈ 2 ps) of the Bodipy-based singlet excited state and a concomitant rise of a charge-separated state evolving from the porphyrin-based singlet excited state. In contrast, room-temperature emission studies on 6 show strong quenching of the Bodipy-based fluorescence leading to sensitized emission from the porphyrin moiety due to a transduction of the singlet excited state energy from Bodipy to the porphyrin. Emission experiments at 77 K in frozen toluene reveal that the room-temperature electron transfer pathway observed in 3 is suppressed. Instead, Bodipy excitation in 3 and 6 results in population of the first singlet excited state of the porphyrin chromophore. Subsequently, intersystem crossing leads to the porphyrin-based triplet excited state. © 2012 American Chemical Society.

Electrostatically arranged cytochrome c-fullerene photoelectrodes - Zilbermann, Israel; Lin, Andrew; Hatzimarinaki, Maria; Hirsch, Andreas; Guldi, Dirk Michael (Chemical Communications, 2004)
We have developed a molecular-level switch - a C/cytochrome c modified ITO electrode - that reversibly transmits and processes solar energy.

Electrostatic assemblies of fullerene-porphyrin hybrids: Toward long-lived charge separation - Balbinot, Domenico; Atalick, Stefan; Guldi, Dirk Michael; Hatzimarinaki, Maria; Hirsch, Andreas; Jux, Norbert (Journal of Physical Chemistry B, 2003)
The Coulomb complex formation of a dendritic fullerene oligocarboxylate (1) and an octapyridinium zinc porphyrin salt (ZnP) was investigated. A Job plot obtained by monitoring the Soret absorption of ZnP upon addition of 1 in a phosphate buffer (pH 7.2, ionic strength = 0.012) indicated the formation of a 1:1 complex, ZnP/1, for which an association constant of (3.5 ± 1.0) × 10 M was determined. Parallel fluorescence titration experiments revealed that the ZnP emission is strongly quenched in the ZnP/1 complex. In particular, the noted decrease of fluorescence intensity in ZnP with variation of 1 and evidence for a new short-lived emissive component suggest a static quenching event inside a ZnP/1 complex. From the fluorescence titration, a value of (1.1 ± 0.1) × 10 M for the association constant of the ZnP/1 complex at pH 7.2 was derived. The association constant decreased, however, when the ionic strength of the solution was raised. Electron-transfer quenching was confirmed by transient absorption spectroscopy, which showed the fingerprint absorptions of the ZnP radical cation and the 1 radical anion and a lifetime of 1.1 μs for the charge-separated state. Molecular dynamic simulations offer insight into the supramolecular structure of the fullerene-porphyrin hybrid, ZnP/1.

Electrostatic complexation and photoinduced electron transfer between Zn-Cytochrome c and polyanionic fullerene dendrimers - Braun, Martin; Atalick, Stefan; Guldi, Dirk Michael; Lanig, Harald; Brettreich, Michael; Burghardt, Stephan; Hatzimarinaki, Maria; Ravanelli, Elena; Prato, Maurizio; van Eldik, Rudi; Hirsch, Andreas (Chemistry - A European Journal, 2003)
Two dendritic fullerene (DF) monoadducts, 2 and 3, which can carry up to 9 and 18 negative charges, respectively, were examined with respect to electrostatic complexation with Cytochrome c (Cytc). To facilitate comprehensive photophysical investigations, the zinc analogue of Cytc (ZnCytc) was prepared according to a novel, modified procedure. The association of ZnCytc and DF, and consequential photo-induced electron transfer within ZnCytc-DF from the photoexcited protein to the fullerene, was proven by fluorescence spectroscopy and transient absorption spectroscopy. These findings were also supported by circular dichroism as well as by extensive molecular dynamics (MD) simulations.

Electrostatic layer-by-layer construction and characterization of photoelectrochemical solar cells based on water soluble polythiophenes and carbon nanotubes - Sgobba, Vito; Troeger, Anna; Cagnoli, Rita; Mateo-Alonso, Aurelio; Prato, Maurizio; Parenti, Francesca; Mucci, Adele; Schenetti, Luisa; Guldi, Dirk Michael (Journal of Materials Chemistry, 2009)
Positively and negatively charged functionalized polythiophenes and single walled carbon nanotubes were sequentially adsorbed on indium tin oxide electrodes by electrostatic and van der Waals interactions using the layer-by-layer deposition method. The resulting donor/acceptor photoelectrodes were tested as photoelectrochemical cells. Upon illumination, monochromatic incident photoconversion efficiencies of 8.2 and 4.3% were determined for eight stacks of single walled carbon nanotubes with ammonium and sulfonate polythiophene derivatives, respectively. © The Royal Society of Chemistry 2009.

Elucidating the electronic properties of single-wall carbon nanohorns - Zieleniewska, Anna; Lodermeyer, Fabian; Prato, Maurizio; Rumbles, Garry; Guldi, Dirk Michael; Blackburn, Jeffrey L. (Journal of Materials Chemistry C, 2022)
Single-walled carbon nanohorns are an allotrope of carbon with promising properties for a variety of applications. Despite their promise, the majority carrier type (i.e. electrons or holes) that defines the electronic properties of this novel semiconductor is poorly understood and so far only indirect measurements have been employed to arrive at contradictory results. Here, we directly determine the majority carrier type in single-wall carbon nanohorns for the first time by means of thermopower measurements. Using this direct method, we show that SWCNH films exhibit a positive Seebeck coefficient indicating that SWCNHs behave as p-type semiconductors. This result is further corroborated by intentionally tuning the hole or electron concentrations of SWCNH layers via redox doping with molecular electron acceptors and donors, respectively. These results provide a framework for both measuring and chemically tuning the majority carrier type in this emerging nanocarbon semiconductor.
CRIS-Team WoS Importer:2022-04-15

Elucidating the Excited-State Properties of CuInS2 Nanocrystals upon Phase Transformation: Quasi-Quantum Dots Versus Bulk Behavior - Azimi, Seyed Hamed; Kuhri, Susanne; Stahl, Melissa S.; Hou, Yi; Guldi, Dirk Michael; Brabec, Christoph (Advanced Electronic Materials, 2015)
New insights into the complex relation between the thermal phase transformation and the excited state properties of chalcopyrite CuInS nanocrystals (CIS NCs) are presented. An in situ solution processing method via depositing molecular precursors is applied, offering advantages in terms of simplicity, low-temperature processability, and control over crystallite size, and optical properties. At low annealing temperatures, strong carrier quantum confinement and small crystallite sizes are realized for CIS NC films. CIS crystal growth is found to set in at higher annealing temperatures inducing a complete transformation from quasi-quantum-dot (QD) via bulk-like to bulk behavior. The transition of a near-infrared localized surface plasmon resonance (LSPR) towards a bulk-like plasmon resonance documents the crystal growth and further acts as a valuable probe to relate crystallite size with copper-deficient stoichiometries. In addition, time-resolved photophysical investigations help to shed light on the dynamics and mechanisms of exciton and charge carrier generation of CIS NC films as a function of annealing temperature. The in situ-prepared CIS NC films are further passivated by a thin CdS layer, leading to the formation of long-lived excitons and an effective CIS ground-state depletion.
Keywords: chalcopyrite; CuInS2 nanocrystals; exciton generation; localized surface plasmon resonance; transient absorption spectroscopy

Encapsulation of hydrophobic drugs in shell-by- shell coated nanoparticles for radio—and chemotherapy—an in Vitro study - Klein, Stefanie; Luchs, Tobias; Leng, Andreas; Distel, Luitpold; Neuhuber, Winfried; Hirsch, Andreas (Bioengineering, 2020)
Our research objective was to develop novel drug delivery vehicles consisting of TiO2 and Al2O3 nanoparticles encapsulated by a bilayer shell that allows the reversible embedment of hydrophobic drugs. The first shell is formed by covalent binding of hydrophobic phosphonic acid at the metal oxide surface. The second shell composed of amphiphilic sodium dodecylbenzenesulfonate emerges by self-aggregation driven by hydrophobic interactions between the dodecylbenzene moiety and the hydrophobic first shell. The resulting double layer provides hydrophobic pockets suited for the intake of hydrophobic drugs. The nanoparticles were loaded with the anticancer drugs quercetin and 7-amino-4-methylcoumarin. Irradiation with X-rays was observed to release the potential anticancer drugs into the cytoplasm. In Michigan Cancer Foundation (MCF)-10 A cells, quercetin and 7-amino-4-methylcoumarin acted as antioxidants by protecting the non-tumorigenic cells from harmful radiation effects. In contrast, these agents increased the reactive oxygen species (ROS) formation in cancerous MCF-7 cells. Quercetin and 7-amino-4-methylcoumarin were shown to induce apoptosis via the mitochondrial pathway in cancer cells by determining an increase in TUNEL-positive cells and a decrease in mitochondrial membrane potential after irradiation. After X-ray irradiation, the survival fraction of MCF-7 cells with drug-loaded nanoparticles considerably decreased, which demonstrates the excellent performance of the double-layer stabilized nanoparticles as drug delivery vehicles.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Al; Chemotherapy; Drug delivery; Quercetin; Radiotherapy; Shell-by-shell nanoparticles; TiO

Endohedral fullerenes for organic photovoltaic devices - Ross, Russel B.; Cardona, Claudia M.; Guldi, Dirk Michael; Sankaranarayanan, Shankara Gayathri; Reese, Matthew O.; Kopidakis, Nikos; Peet, Jeff; Walker, Bright; Bazan, Guillermo C.; Van Keuren, Edward; Holloway, Brian C.; Drees, Martin (Nature Materials, 2009)
So far, one of the fundamental limitations of organic photovoltaic (OPV) device power conversion efficiencies (PCEs) has been the low voltage output caused by a molecular orbital mismatch between the donor polymer and acceptor molecules. Here, we present a means of addressing the low voltage output by introducing novel trimetallic nitride endohedral fullerenes (TNEFs) as acceptor materials for use in photovoltaic devices. TNEFs were discovered in 1999 by Stevenson et al.; for the first time derivatives of the TNEF acceptor, Lu 3 N@C 80, are synthesized and integrated into OPV devices. The reduced energy offset of the molecular orbitals of Lu 3 N@C 80 to the donor, poly(3-hexyl)thiophene (P3HT), reduces energy losses in the charge transfer process and increases the open circuit voltage (Voc) to 260 mV above reference devices made with [6,6]-phenyl-C 61 -butyric methyl ester (C 60 -PCBM) acceptor. PCEs >4% have been observed using P3HT as the donor material. This work clears a path towards higher PCEs in OPV devices by demonstrating that high-yield charge separation can occur with OPV systems that have a reduced donor/acceptor lowest unoccupied molecular orbital energy offset.

Endohedral metallofullerenes-filled fullerene derivatives towards multifunctional reaction center mimics - Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Feng, Lai; Tsuchiya, Takahiro; Akasaka, Takeshi; Echegoyen, Luis (Chemistry - A European Journal, 2012)
In recent years, endohedral metallofullerenes have attracted tremendous interest not only in physics and chemistry, but also in interdisciplinary areas, such as materials and biological sciences. In this concept article we highlight recent results on different endohedral metallofullerenes based on lanthanides and their derivatives. The chemical and excited state reactivities of endohedral metallofullerenes are discussed for various endohedral clusters. Most important is the part that covers spectroscopic and kinetic assays of reductive and oxidative charge transfer evolving from photoexcited electron donors and electron acceptors, respectively, in a variety of electron donor-acceptor conjugates. Towards this end, we refer to the applications of endohedral metallofullerenes in photovoltaic devices that feature greater efficiency than devices fabricated with empty fullerenes. Herein, we focus mainly on results obtained in the groups of Akasaka, Echegoyen, and Guldi. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Enhanced binding strengths of acyclic porphyrin hosts with endohedral metallofullerenes - Grimm, Bruno; Schornbaum, Julia; Cardona, Claudia M.; Van Paauwe, John D.; Boyd, Peter D. W.; Guldi, Dirk Michael (Chemical Science, 2011)
The complementary use of spectroscopy and electrochemistry shed light onto the supramolecular interactions of calixarene scaffold bearing bisporphyrins 1 and 2 as hosts with a series of fullerenes -C , Sc N@C , and Lu N@C - as guest molecules. Importantly, the present work shows a noticeable variation in binding strength when C or endohedral fullerene guests are included into the bisporphyrins hosts. These sizeable differences could be clarified by computational models of the host-guest complexes, on the one hand, and a systematic investigation of the electron transfer chemistry, on the other hand. Detailed studies document an oxidative charge transfer (i.e., electron transfer from the bisporphyrin to the fullerene) for the C inclusion complexes, while a reductive charge transfer (i.e., electron transfer from the fullerene to porphyrin) is operative in the endohedral metallofullerene host-guest complexes. © The Royal Society of Chemistry 2011.

Enhanced internal electric field of CdS/NU-M Z-scheme heterojunction for efficient photocatalytic hydrogen evolution - Liu, Liping (Chemical Engineering Journal, 2024)

Enhanced In Vitro Biocompatibility and Water Dispersibility of Magnetite and Cobalt Ferrite Nanoparticles Employed as ROS Formation Enhancer in Radiation Cancer Therapy - Klein, Stefanie; Kizaloglu, Melek; Portilla Berlanga, Luis; Park, Hyoungwon; Rejek, Tobias; Hümmer, Julian; Meyer, Karsten; Hock, Rainer; Distel, Luitpold; Halik, Marcus; Kryschi, Carola (Small, 2018)

Enhanced performance of dye-sensitized solar cells based on TiO2 nanotube membranes using an optimized annealing profile - Mohammadpour, F.; Moradi, M.; Lee, Kiyoung; Cha, Gi; So, Seulgi; Kahnt, Axel; Guldi, Dirk Michael; Altomare, Marco; Schmuki, Patrik (Chemical Communications, 2015)
We use free-standing TiO2 nanotube membranes that are transferred onto FTO slides in front-side illuminated dye-sensitized solar cells (DSSCs). We investigate the key parameters for solar cell arrangement of self-ordered anodic TiO2 nanotube layers on the FTO substrate, namely the influence of the annealing procedure on the DSSC light conversion efficiency. The results show that using an optimal temperature annealing profile can significantly enhance the DSSC efficiency (in our case extgreekh = 9.8%), as it leads to a markedly lower density of trapping states in the tube oxide, and thus to strongly improved electron transport properties.
EAM Import::2019-03-14

Enhancing Built-in Electric Fields for Efficient Photocatalytic Hydrogen Evolution by Encapsulating C60 Fullerene into Zirconium-Based Metal-Organic Frameworks - Liu, Liping; Meng, Haibing; Chai, Yongqiang; Chen, Xianjie; Xu, Jingyi; Liu, Xiaolong; Liu, Weixu; Guldi, Dirk Michael; Zhu, Yongfa (Angewandte Chemie International Edition, 2023)
High-efficiency photocatalysts based on metal-organic frameworks (MOFs) are often limited by poor charge separation and slow charge-transfer kinetics. Herein, a novel MOF photocatalyst is successfully constructed by encapsulating C60 into a nano-sized zirconium-based MOF, NU-901. By virtue of host-guest interactions and uneven charge distribution, a substantial electrostatic potential difference is set-up in C60@NU-901. The direct consequence is a robust built-in electric field, which tends to be 10.7 times higher in C60@NU-901 than that found in NU-901. In the catalyst, photogenerated charge carriers are efficiently separated and transported to the surface. For example, photocatalytic hydrogen evolution reaches 22.3 mmol g−1 h−1 for C60@NU-901, which is among the highest values for MOFs. Our concept of enhancing charge separation by harnessing host-guest interactions constitutes a promising strategy to design photocatalysts for efficient solar-to-chemical energy conversion.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Charge Transfer; Host-Guest Systems; Metal-Organic Frameworks; Photocatalytic Hydrogen Evolution; Robust Internal Electric Field

Enhancing Carrier Transport via σ-Linkage Length Modulation in D-σ-A Semiconductors for Photocatalytic Oxidation - Liu, Liping (Angewandte Chemie International Edition, 2023)

Enhancing internal electric field of 3D porous chitosan-PDI polymer with donor-acceptor structure for efficient photocatalytic advanced oxidation - Liu, Liping (Applied Catalysis B-Environmental, 2024)

Enhancing molecular recognition in electron donor-acceptor hybrids via cooperativity - Krick Calderon, Rafael; Valero, Julian; Grimm, Bruno; De Mendoza, Javier; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
Herein, we report the synthesis of guanidinium bis-porphyrin tweezers 1 and fullerene carboxylate 3, their assembly into a novel supramolecular 1@3 electron donor-acceptor hybrid, and its characterization. In solution, the binding constant affording 1@3 is exceptionally high. 1@3, which features a highly confined topography, builds up from a combination of guanidinium- carboxylate hydrogen bonding and π-π stacking/charge-transfer motifs. The latter is governed by interactions between the electron-donating porphyrin and the electron-accepting fullerene. Importantly, positive cooperativity between the applied binding motifs is corroborated by a number of experimental techniques, such as NMR, absorption, fluorescence, etc. In addition, transient absorption experiments shed light onto electron-transfer processes taking place in the ground state and upon photoexcitation. In fact, porphyrin excitation powers an electron transfer to the fullerene yielding charge separated state lifetimes in the nanosecond regime. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-07

Enhancing photocurrent efficiencies by resonance energy transfer in CdTe quantum dot multilayers: Towards rainbow solar cells - Ruland Palaia, Andres; Schulz-Drost, Christian; Sgobba, Vito; Guldi, Dirk Michael (Advanced Materials, 2011)
The impact of Förster resonant energy transfer (FRET) in CdTe quantum dot (QD) based photoelectrochemical cells is investigated. By deposition of different CdTe QD sizes onto indium on oxide electrodes, FRET across the photoactive film could be obtained, resulting in a 25% enhancement of the photon-to-current efficiency when compared to reference systems that lack FRET. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Enhancing Planar Inverted Perovskite Solar Cells with Innovative Dumbbell-Shaped HTMs: A Study of Hexabenzocoronene and Pyrene-BODIPY-Triarylamine Derivatives - Rocha-Ortiz, Juan S.; Wu, Jianchang; Wenzel, Jonas; Bornschlegl, Andreas; Perea, Jose Dario; Leon, Salvador; Barabash, Anastasia; Wollny, Anna-Sophie; Guldi, Dirk Michael; Zhang, Jiyun; Insuasty, Alberto; Lüer, Larry; et al. (Advanced Functional Materials, 2023)
Keywords: hexabenzocoronene; donor–acceptor; BODIPY; π-conjugation; perovskite solar cells; hole-transport materials

En route towards panchromatic light harvesting: Photophysical and electrochemical properties of Bodipy-porphyrazine conjugates - Kuhri, Susanne; Engelhardt, V.; Faust, Rüdiger; Guldi, Dirk Michael (Chemical Science, 2014)
The concept of panchromatic light harvesting, that is, broad absorption cross sections throughout most of the visible range and excited state funnelling, has been realized in a novel set of porphyrazines. On one hand, zinc, copper, or magnesium ions were complexed by porphyrazines to tune their ground and excited state features. On the other hand, up to eight Bodipys were covalently attached to the periphery of the porphyrazines to enhance the ground state absorption. The corresponding star-shaped conjugates were probed by advanced photophysical measurements, that is, time-resolved fluorescence and femtosecond transient absorption spectroscopy. From the latter we derive spectroscopic and kinetic evidence in support of a fast and unidirectional energy transfer from the photoexcited Bodipy at the periphery to the porphyrazine at the core. In addition, the impact of the different metal centers is demonstrated. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-07

Epitaxial Growth of PbSe Quantum Dots on MoS2 Nanosheets and their Near-Infrared Photoresponse - Schornbaum, Julia; Winter, Benjamin; Schießl, Stefan; Gannott, Florentina; Katsukis, Georgios; Guldi, Dirk Michael; Spiecker, Erdmann; Zaumseil, Jana (Advanced Functional Materials, 2014)
A facile one-pot synthesis of hybrid materials consisting of PbSe quantum dots (QDs) that grow epitaxially on MoS2 nanoflakes resulting in three equivalent orientation variants of the PbSe QDs with respect to the MoS2 lattice is demonstrated. The epitaxial growth and cross-sectional high-resolution transmission electron microscopy (HRTEM) investigations verify a direct and linker-free contact between the quantum dots and the transition metal dichalcogenide (TMD) nanoflakes, while maintaining surface passivation of the PbSe with oleic acid ligands on the outside. Solution-processed photodetectors based on PbSe-MoS2 hybrids exhibit stable photoconduction when illuminated with near-IR light (wavelength > 1200 nm) without any laborious ligand-exchange steps. Flexible devices fabricated on polyethylene terephthalate (PET) substrates show excellent stability upon repeated bending. These hybrid materials are air-stable and solution-processable at low temperatures and thus promising for low-cost flexible near-IR photodetectors.

Erratum: A voyage into the synthesis and photophysics of homo- and heterobinuclear ensembles of phthalocyanines and porphyrins (Chemical Society Reviews (2013) 42 (8049-8105) DOI:10.1039/C3CS60140D) - De La Torre, Gema; Bottari, Giovanni; Sekita, Michael; Hausmann, Anita; Guldi, Dirk Michael; Torres, Tomás (Chemical Society Reviews, 2013)

Erratum: Porphyrin-phthalocyanine/pyridylfullerene supramolecular assemblies (Chemistry - A European Journal (2012) 18 DOI: 10.1002/chem. 201103776) - Pereira, Ana M V M; Hausmann, Anita; Soares, Ana R M; Tomé, João P C; Trukhina, Olga; Urbani, Maxence; Neves, Maria G P M S; Cavaleiro, José A S; Guldi, Dirk Michael; Torres, Tomás (Chemistry - A European Journal, 2013)

Es werde Licht ... Absorptionsspektroskopie für die Schule - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2012)

Evidence for Charge-Transfer Mediation in the Primary Events of Singlet Fission in a Weakly Coupled Pentacene Dimer - Basel, Bettina; Zirzlmeier, Johannes; Hetzer, Constantin; Seelam, Rajagopala Reddy; Phelan, Brian T.; Krzyaniak, Matthew D.; Volland, Michel; Brana Coto, Pedro; Young, Ryan M.; Clark, Timothy; Thoss, Michael; Tykwinski, Rik; et al. (Chem, 2018)
Singlet fission (SF) is a process that converts one singlet excited state into two triplet states. The mechanism of SF is still not well understood. Here, we report on the use of a combination of transient absorption and electron paramagnetic resonance spectroscopies in conjunction with theoretical calculations to probe SF in a pentacene dimer linked by a non-conjugated, 1,4-diethynylbicyclo[2.2.2]octane spacer. Next to observing the key intermediates in solution-based SF, including the formation and decay of a quintet state that precedes formation of the pentacene triplet excitons, we demonstrate that the coupling is sufficiently weak that SF is essentially inoperative in non-polar media. Transitioning to a polar medium, however, amplifies the coupling strength such that SF becomes operative and supports long triplet lifetimes. Our results offer strong evidence for a charge-transfer mediation and, in turn, provide a solid framework for decoding the complete mechanism of SF in systems beyond pentacene.

Evidence of pronounced electronic coupling in a directly bonded fullerene-ferrocene dyad - Hauke, Frank; Hirsch, Andreas; Liu, Sheng-Gao; Echegoyen, Luis; Swartz, Angela; Luo, Chuping; Guldi, Dirk Michael (ChemPhysChem, 2002)
A new donor-acceptor dyad (7) involving a ferrocene moiety as donor and an azafullerene as acceptor has been synthesized by treating bisazafullerenyl (1) with ferrocenium hexafluorophosphate. This compound represents the first example of a fullerene-based dyad where two electroactive groups are connected by only a single σ-bond. The cyclic voltammetry of 7, in comparison to the corresponding reference systems, clearly reveals strong electronic coupling between the ferrocene and the azafullerene moiety in the ground state. For example, the Fc-based, reversible, one electron oxidation wave is significantly positively shifted by 183 mV with respect to that of the parent ferrocene. This indicates the existence of intramolecular charge transfer (ICT) from the donating Fc to the accepting azafullerenyl group. Photophysical studies on 7 were carried out by means of emission and transient absorption spectroscopy. An instantaneous deactivation of the fullerene singlet excited-state results in the formation of the chargeseparated (CN)-(Fc) radical pair. From the charge-transfer dynamics with a lower limit of ≥ 5 × 10 s, we infer strong electronic coupling (V) between the azafullerene and the ferrocene moiety of the order of 60 cm in benzonitrile.

Evolution of a ‘privileged’ P-alkene ligand: added planar chirality beats BINOL axial chirality in catalytic asymmetric C-C bond formation - Leinauer, Luisa; Parla, Giorgio; Messelberger, Julian; Herrera, Alberto Cesar; Heinemann, Frank Wilhelm; Langer, Jens; Chuchelkin, Ilya; Grasruck, Alexander; Frieß, Sibylle; Chelouan, Ahmed; Gavrilov, Konstantin; Dorta, Romano (Chemical Communications, 2023)
Alkene planar chirality is introduced in the ‘privileged’ P-alkene phosphoramidite ligand 1. The resulting diastereomeric ligands (pR,R)-5 and (pS,R)-5 form optically pure complexes of Rh(i) and Pd(ii), which catalyze conjugate additions of boron C-nucleophiles to enones and allylic alkylations, respectively. In the Rh-catalyzed reaction, the planar chirality of the alkene exerts absolute enantiocontrol over the potent BINOL auxiliary.
CRIS-Team Scopus Importer:2023-12-15

Excited state kinetics in crystalline solids: Self-quenching in nanocrystals of 4,4′-disubstituted benzophenone triplets occurs by a reductive quenching mechanism - Kuzmanich, Gregory; Simoncelli, Sabrina; Gard, Matthew N.; Spänig, Fabian; Henderson, Bryana L.; Guldi, Dirk Michael; Garcia-Garibay, Miguel A. (Journal of the American Chemical Society, 2011)
We report an efficient triplet state self-quenching mechanism in crystals of eight benzophenones, which included the parent structure (1), six 4,4′-disubstituted compounds with NH (2), NMe (3), OH (4), OMe (5), COOH (6), and COOMe (7), and benzophenone-3,3′,4, 4′-tetracarboxylic dianhydride (8). Self-quenching effects were determined by measuring their triplet-triplet lifetimes and spectra using femtosecond and nanosecond transient absorption measurements with nanocrystalline suspensions. When possible, triplet lifetimes were confirmed by measuring the phosphorescence lifetimes and with the help of diffusion-limited quenching with iodide ions. We were surprised to discover that the triplet lifetimes of substituted benzophenones in crystals vary over 9 orders of magnitude from ca. 62 ps to 1 ms. In contrast to nanocrystalline suspensions, the lifetimes in solution only vary over 3 orders of magnitude (1-1000 μs). Analysis of the rate constants of quenching show that the more electron-rich benzophenones are the most efficiently deactivated such that there is an excellent correlation, ρ = -2.85, between the triplet quenching rate constants and the Hammet θ values for the 4,4′ substituents. Several crystal structures indicate the existence of near-neighbor arrangements that deviate from the proposed ideal for "n-type" quenching, suggesting that charge transfer quenching is mediated by a relatively loose arrangement. © 2011 American Chemical Society.

Excited state properties of anodic TiO2 nanotubes - Kahnt, Axel; Oelsner, Christian; Werner, Fabian; Guldi, Dirk Michael; Albu, Sergiu; Kirchgeorg, Robin; Lee, Kiyoung; Schmuki, Patrik (Applied Physics Letters, 2013)
Charge carriers, that is, holes as well as trapped and "free" electrons were investigated by means of time resolved spectroscopy in anodic TiO nanotubes that were heat treated at different temperatures. The lifetimes of the charge carrier were compared with those generated in reference layers of Solaronix Ti-Nanoxide D and Degussa P25 nanoparticles. Remarkably long lived "free" electrons were only noted in the TiO nanotubes. These findings have significance in view of any photoelectrochemical applications of TiO nanotubes. © 2013 2013 Author(s).

Excited-state relaxation dynamics of 3-vinylthiophene-terminated silicon quantum dots - Groenewegen, Vincent; Kuntermann, Volker; Haarer, Dietrich; Kunz, Michael; Kryschi, Carola (Journal of Physical Chemistry C, 2010)
In theory, silicon quantum dots (SiQDs) emit enhanced photoluminescence with a size-tunable spectrum in the visible range. In practice, surface states originating from oxide defect structures or organic ligands are strongly involved in exciton relaxation dynamics because the amplitudes of hole and electron wave functions are nonzero at the SiQD surface. In this study, SiQDs with well-defined surface properties were obtained through a wet-chemistry procedure providing SiQDs with adjustable sizes and oxide-free, 3-vinylthiophene-terminated surfaces. The 3-vinylthiophene-terminated SiQDs have a crystalline spherical 2 nm core and were observed to exhibit blue photoluminescence (∼460 nm) with a quantum yield and lifetime of ca. 23% and 1.3 ns, respectively. The interplay between electronically excited molecular states and conduction band states was examined upon direct monitoring of photoexcited carrier dynamics with femtosecond transient absorption spectroscopy. The 3-vinylthiophene ligands were found to act as surface-bound antennae that mediate ultrafast electron transfer or excitation energy transfer across the SiQD interface. © 2010 American Chemical Society.

Exciton Dynamics in J- And H-Aggregates of a Tricarbocyanine Near-Infrared Dye - Dimitriev, Oleg P.; Zirzlmeier, Johannes; Menon, Arjun; Slominskii, Yuri; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2021)
Intermolecular interactions in J- and H-aggregates of π-conjugated molecules provide fascinating incentives for excitonic pathways. Investigation regarding exciton dynamics in aggregates of tricarbocyanine near-infrared dyes by transient absorption spectroscopy revealed unusual intermolecular communications not only within different aggregates but also between different aggregates. To this end, aggregation was accompanied by a short-lived excitonic component, that is, on the picosecond time scale, due to additional relaxation channels and a long-lived component, that is, on the nanosecond to microsecond time scales. All of the aforementioned are in sharp contrast to what was found for the monomer. For the monomer, monoexponential exciton dynamics of about 0.5 ns was registered. Overall, the long-lived component in aggregates accounts for 1-5% of all excitons. In J-aggregates, it involves the formation of charge transfer/polaron states. In mixtures of J- and H-aggregates, contributions from the long-lived component further increased. We conclude that interactions between J- and H-aggregates open additional channels for exciton relaxation. One of them is a photoinduced charge transfer from, for example, the bright state in J-aggregates to the dark exciton states in H-aggregates, from where electrons are transferred into the continuum of states.
CRIS-Team Scopus Importer:2021-06-04

Excitons and Trions in One-Photon- and Two-Photon-Excited MoS2: A Study in Dispersions - Wibmer, Leonie; Lages, Sebastian; Unruh, Tobias; Guldi, Dirk Michael (Advanced Materials, 2018)
Herein, various dispersions of MoS2 obtained by means of liquid phase exfoliation are spectroscopically, (spectro-) electrochemically, and microscopically characterized. At the core of these studies are transient absorption assays. Importantly, small-angle X-ray scattering measurements are employed to corroborate the exfoliated character of the MoS2 flakes in dispersion, on the one hand, and to correlate the results with TEM, AFM, and Raman characterization in the solid state, on the other. It is, then, demonstrated that transient absorption spectroscopy responds sensitively not only to changes in the sample preparation but also to instrumental and environmental parameters. It is documented that the spectroscopic features and their underlying lifetimes are tuneable on the femto-, pico-, and nanosecond scales by changing, for example, the centrifugation speed, the pump fluence, or the temperature. In other words, transient absorption spectroscopy provides an in situ method to quantitatively characterize liquid dispersions of MoS2 without facing the problems of reaggregated samples due to their drying for microscopic assays. The most far reaching results stem from resonantly and nonresonantly changing the pump fluence to characterize either single- or multiple-excited-state species such as excitons, trions, and bi-/multiexcitons and to follow their formation and deactivation pattern.
Keywords: 2D materials; MoS2; pump-probe spectroscopy; small-angle X-ray scattering (SAXS)

Exfoliation of Graphene by Dendritic Water-Soluble Zinc Phthalocyanine Amphiphiles in Polar Media - Methfessel, Christian; Volland, Michel; Brunner, Kristin; Wibmer, Leonie; Hahn, Uwe; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Two zinc phthalocyanines (ZnPcs) have been equipped with Newkome-type dendritic branches of increasing size and number of terminal carboxylate functional groups. The negatively charged carboxylates render these polyelectrolytes soluble in polar media such as methanol or buffered water. Sonication of the ZnPcs with graphene allowed for pronounced non-covalent binding of the ZnPc moieties on the graphene surface. These hybrid systems were fully characterized via UV/Vis, AFM, TEM, Raman and transient absorption spectroscopy, yielding insights into the electron donating nature of the novel phthalocyanine structures.
Keywords: dendrimers; donor-acceptor system; energy transfer; exfoliation; graphene

Expanding the Chemical Space of Tetracyanobuta-1,3-diene (TCBD) through a Cyano-Diels-Alder Reaction: Synthesis, Structure, and Physicochemical Properties of an Anthryl-fused-TCBD Derivative - Mateo, Luis M.; Sagresti, Luca; Luo, Yusen; Guldi, Dirk Michael; Torres, Tomas; Brancato, Giuseppe; Bottari, Giovanni (Chemistry - A European Journal, 2021)
Tetracyanobuta-1,3-diene (TCBD) is a powerful and versatile electron-acceptor moiety widely used for the preparation of electroactive conjugates. While many reports addressing its electron-accepting capability have appeared in the literature, significantly scarcer are those dealing with its chemical modification, a relevant topic which allows to broaden the chemical space of this interesting functional unit. Here, we report on the first example of a high-yielding cyano-Diels-Alder (CDA) reaction between TCBD, that is, where a nitrile group acts as a dienophile, and an anthryl moiety, that is, acting as a diene. The resulting anthryl-fused-TCBD derivative, which structure was unambiguously identified by X-ray diffraction, shows high thermal stability, remarkable electron-accepting capability, and interesting electronic ground- and excited-state features, as characterized by a thorough theoretical, electrochemical, and photophysical investigation. Moreover, a detailed kinetic analysis of the intramolecular CDA reaction transforming the anthryl-TCBD-based reactant into the anthryl-fused-TCBD product was carried out at different temperatures.
CRIS-Team Scopus Importer:2021-10-22
Keywords: anthryl-fused derivative; cyano-Diels-Alder reaction; electron acceptor; photophysics; tetracyanobuta-1; 3-diene

Experimental and Theoretical Structure Elucidation of the [2 : 1] Complex Ion of Carbo[n]helicene with n=6, 7 and 8 and Ag+ - Oschwald, Johannes; Reger, David; Frühwald, Stefan; Warmbrunn, Vera; Görling, Andreas; Jux, Norbert; Drewello, Thomas (ChemPhysChem, 2023)
Gas-phase complexes of [n]helicenes with n=6, 7 and 8 and the silver(I) cation are generated utilizing electrospray ionization mass spectrometry (ESI-MS). Besides the well-established [1 : 1] helicene/Ag+-complex in which the helicene provides a tweezer-like surrounding for the Ag+, there is also a [2 : 1] complex formed. Density functional theory (DFT) calculations in conjunction with energy-resolved collision-induced dissociation (ER-CID) experiments reveal that the second helicene attaches via π-π stacking to the first helicene, which is part of the pre-formed [1 : 1] tweezer complex with Ag+. For polycyclic aromatic hydrocarbons (PAHs) of planar structure, the [2 : 1] complex with silver(I) is typically structured as an Ag+-bound dimer in which the Ag+ would bind to both PAHs as the central metal ion (PAH–Ag+–PAH). For helicenes, the Ag+-bound dimer is of similar thermochemical stability as the π-π stacked dimer, however, it is kinetically inaccessible. Coronene (Cor) is investigated in comparison to the helicenes as an essentially planar PAH. In analogy to the π-π stacked dimer of the helicenes, the Cor−Ag+−Cor−Cor complex is also observed. Competition experiments using [n]helicene mixtures reveal that the tweezer complexes of Ag+ are preferably formed with the larger helicenes, with n=6 being entirely ignored as the host for Ag+ in the presence of n=7 or 8.
CRIS-Team Scopus Importer:2023-09-15
Keywords: carbo[n]helicenes; density functional calculations; Energy-resolved CID; tweezer; [2 : 1] helicene/silver(I) complex ion

Exploring pi-extended subporphyrinoids as electron transporting materials in perovskite solar cells - Momblona, Cristina; Labella, Jorge; Gomez-Gomez, Marta; Guzman, David; Culik, Pavel; Kanda, Hiroyuki; Martinez-Diaz, M. Victoria; Guldi, Dirk Michael; Nazeeruddin, Mohammad Khaja; Torres, Tomas (Journal of Porphyrins and Phthalocyanines, 2022)
Due to their strong acceptor properties and enhanced charge transport capabilities, non-fullerene electron acceptors based on pi-extended derivatives - subnaphthalocyanines (SubNc) or subphtalocyanine dimers (SubPc(2)) - have been employed in organic photovoltaics in the past as an alternative to the expensive fullerene. However, these promising pi-extended derivatives have not been explored in perovskite solar cell technology. In this work, we implement a vacuum-deposited very thin film of SubNc or SubPc(2) as electron transport layers in perovskite solar cells. In particular, we demonstrate the excellent electron extraction properties of the thin films in contact with perovskite layer. The fabricated perovskite solar cells exhibit enhanced device performances with reduced hysteresis index and improved device stability. Our results validate the use of n-extended subporphyrinoids as promising candidates for perovskite optoelectronics with enhanced stability properties, being essential for further conunercialization of the perovskite technology.
CRIS-Team WoS Importer:2022-10-21

Exploring Tetrathiafulvalene–Carbon Nanodot Conjugates in Charge Transfer Reactions - Ferrer-Ruiz, Andres; Scharl, Tobias; Haines, Philipp; Rodriguez-Perez, Laura; Cadranel, Alejandro; Herranz, M. Angeles; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2018)
Carbon nanodots (CNDs) were synthesized using low-cost and biocompatible starting materials such as citric acid/urea, under microwave irradiation, and constant pressure conditions. The obtained pressure-synthesized CNDs (pCNDs) were covalently modified with photo- and electroactive π-extended tetrathiafulvalene (exTTF) by means of a two-step esterification reaction, affording pCND-exTTF. The electronic interactions between the pCNDs and exTTF were investigated in the ground and excited states. Ultrafast pump–probe experiments assisted in corroborating that charge separation governs the deactivation of photoexcited pCND-exTTF. These size-regular structures, as revealed by AFM, are stable electron donor–acceptor conjugates of interest for a better understanding of basic processes such as artificial photosynthesis, catalysis, and photovoltaics, involving readily available fluorescent nanodots.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon nanodots; charge transfer; donor–acceptor systems; excited state dynamics; tetrathiafulvalene

Exploring the Association of Electron-Donating Corroles with Phthalocyanines as Electron Acceptors - Platzer, Benedikt; Berna, Beatrice Berionni; Bischetti, Martina; Cicero, Daniel O.; Paolesse, Roberto; Nardis, Sara; Torres, Tomas; Guldi, Dirk Michael (Chemistry - A European Journal, 2022)
Electron-donating corroles (Cor) were integrated with electron-accepting phthalocyanines (Pc) to afford two different non-covalent Cor ⋅ Pc systems. At the forefront was the coordination between a 10-meso-pyridine Cor and a ZnPc. The complexation was corroborated in a combination of NMR, absorption, and fluorescence assays, and revealed association with binding constants as high as 106 m−1. Steady-state and time-resolved spectroscopies evidenced that regardless of exciting Cor or Pc, the charge-separated state evolved efficiently in both cases, followed by a slow charge-recombination to reinstate the ground state. The introduction of non-covalent linkages between Cor and Pc induces sizeable differences in the context of light harvesting and transfer of charges when compared with covalently linked Cor-Pc conjugates.
CRIS-Team Scopus Importer:2022-03-11
Keywords: electron transfer; organic photovoltaics; porphyrinoids; supramolecular chemistry

Exploring the Threshold between Fullerenes and Nanotubes: Characterizing Isomerically Pure, Empty-Caged, and Tubular Fullerenes D5h-C90 and D5d-C100 - Schüßlbauer, Christoph; Krug, Marcel; Ullrich, Tobias; Franklin, Hannah M.; Stevenson, Steven; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
We report the fully fledged photophysical characterization of isomerically pure, empty-caged, tubular fullerenes D5h-C90 and D5d-C100 and compare their key properties. In particular, the focus was on cage sizes between 60 and 150 carbon atoms with D3, D3d/h, and D5d/h symmetry. The optical band gap of D5d-C100 is 1.65 eV, which is larger than 1.37 eV of D5h-C90. In stark contrast to the nonluminescent D5h-C90, D5d-C100 luminesces at room temperature. Transient absorption spectroscopy shows that photoexcited D5d-C100 is subject to a slow intersystem crossing that generates a triplet excited state. In contrast, a fast, nonradiative internal conversion governs the deactivation of D5h-C90: In this case, exploring the corresponding triplet excited state required triplet-triplet sensitization experiments with anthracene. Density functional theory calculations revealed the electronic structure of the fullertubes, and calculations are consistent with our experimental findings. The calculated band gap systematically decreases with the number of carbon atoms within the D3 and D3d/h series. In contrast, an oscillating behavior is noted within the series of D5d/h fullertubes. Finally, photoexcited D5d-C100 was found to undergo hole transfer with electron-donating triethylamines readily but not electron transfer with electron-accepting methyl viologens.
CRIS-Team Scopus Importer:2022-07-01

Facile access to potent antiviral quinazoline heterocycles with fluorescence properties via merging metal-free domino reactions - Held, Felix; Guryev, Anton; Fröhlich, Tony; Hampel, Frank; Kahnt, Axel; Hutterer, Corina; Steingruber, Mirjam; Bahsi, Hanife; Von Bojnicic-Kninski, Clemens; Mattes, Daniela S.; Foertsch, Tobias C.; Nesterov-Mueller, Alexander; et al. (Nature Communications, 2017)
Most of the known approved drugs comprise functionalized heterocyclic compounds as subunits. Among them, non-fluorescent quinazolines with four different substitution patterns are found in a variety of clinically used pharmaceuticals, while 4,5,7,8-substituted quinazolines and those displaying their own specific fluorescence, favourable for cellular uptake visualization, have not been described so far. Here we report the development of a one-pot synthetic strategy to access these 4,5,7,8-substituted quinazolines, which are fluorescent and feature strong antiviral properties (EC50down to 0.6±0.1 μM) against human cytomegalovirus (HCMV). Merging multistep domino processes in one-pot under fully metal-free conditions leads to sustainable, maximum efficient and high-yielding organic synthesis. Furthermore, generation of artesunic acid-quinazoline hybrids and their application against HCMV (EC50down to 0.1±0.0 μM) is demonstrated. Fluorescence of new antiviral hybrids and quinazolines has potential applications in molecular imaging in drug development and mechanistic studies, avoiding requirement of linkage to external fluorescent markers.
EVALuna2:33762

Facile and quick preparation of carbon nanohorn-based counter electrodes for efficient dye-sensitized solar cells - Lodermeyer, Fabian; Prato, Maurizio; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
For the first time, Pt-free counter electrodes based on carbon nanohorns for highly efficient dye-sensitized solar cells were assembled by a facile and fast drop cast technique. These novel electrodes feature an effective catalytic behavior towards the reduction of I3- and, as such, afford even higher short-circuit current densities compared to Pt-based references. In a final device, solar cells with 7.7% efficiency were achieved.
EAM Import::2019-03-14

Facile decoration of functionalized single-wall carbon nanotubes with phthalocyanines via "click chemistry" - Campidelli, Stephane; Ballesteros, Beatriz; Filoramo, Arianna; Diaz Diaz, David; De La Torre, Gema; Torres, Tomas; Rahman, Aminur; Ehli, Christian; Kießling, Daniel; Werner, Fabian; Sgobba, Vito; Guldi, Dirk Michael; et al. (Journal of the American Chemical Society, 2008)
We describe the functionalization of single-wall carbon nanotubes (SWNTs) with 4-(2-trimethylsilyl)ethynylaniline and the subsequent attachment of a zinc-phthalocyanine (ZnPc) derivative using the reliable Huisgen 1,3-dipolar cycloaddition. The motivation of this study was the preparation of a nanotube-based platform which allows the facile fabrication of more complex functional nanometer-scale structures, such as a SWNT-ZnPc hybrid. The nanotube derivatives described here were fully characterized by a combination of analytical techniques such as Raman, absorption and emission spectroscopy, atomic force and scanning electron microscopy (AFM and SEM), and thermogravimetric analysis (TGA). The SWNT-ZnPc nanoconjugate was also investigated with a series of steady-state and time-resolved spectroscopy experiments, and a photoinduced communication between the two photoactive components (i.e., SWNT and ZnPc) was identified. Such beneficial features lead to monochromatic internal photoconversion efficiencies of 17.3% when the SWNT-ZnPc hybrid material was tested as photoactive material in an ITO photoanode. © 2008 American Chemical Society.

Facile one‑pot synthesis of water‑soluble fcc FePt3 alloy nanostructures - Kizaloğlu Akbulut, Melek; Harreiß, Christina; Löffler, Mario; Mayrhofer, Karl J.J.; Schöbitz, Michael; Bachmann, Julien; Spiecker, Erdmann; Hock, Rainer; Kryschi, Carola (SN Applied Sciences, 2020)
Proccessible FePt3 alloy nanoparticles with sizes smaller than 50 nm open the avenue to novel magnetic sensor, catalytic and biomedical applications. Our research objective was to establish a highly scalable synthesis technique for production of single-crystalline FePt3 alloy nanoparticles. We have elaborated a one-pot thermal decomposition technique for the synthesis of superparamagnetic FePt3 nanoparticles (FePt3 NPs) with mean sizes of 10 nm. Subsequent tiron coating provided water solubility of the FePt3 NPs and further processibility as bidental ligands enable binding to catalyst surfaces, smart substrates or biosensors. The chemical composition, structure, morphology, magnetic, optical and crystallographic properties of the FePt3 NPs were examined using high resolution transmission electron microscopy, high angle annular dark field-scanning transmission electron microscopy, scanning transmission electron microscopy-energy-dispersive X-ray spectroscopy mapping, Fourier transform infrared-attenuated total reflection, X-ray powder diffraction, X-ray photoelectron spectroscopy, vibrating sample magnetometry and UV–Vis absorption spectroscopy.<br
Keywords: Iron-platinum alloy; FePt3 nanoparticles; XPS; XRD analysis; Thermal decomposition route

Femtosecond spectroscopic study of carminic acid-DNA interactions - Gabel, Loredana-Bianca; Kryschi, Carola; Rusu, Catalin Florin; et al. (Chemical Physics, 2006)
Photo-excited carminic acid and carminic acid-DNA complexes in a buffer solution at pH 7 have been examined using a variety of spectroscopy techniques, that are in particular, the femtosecond resolved fluorescence upconversion and transient absorption spectroscopy. The observation of dual fluorescence emission, one peaks at 470 nm and the other at 570 nm, indicates to an excited-state (S) intramolecular proton transfer (ESIPT). A detailed analysis of the transient absorption measurements of an aqueous carminic-acid solution at pH 7 yielded four lifetimes for the excited-state (S): 8, 15, 33 and 46 ps. On the other hand, only two lifetimes, 34 and 47 ps, were observed by fluorescence upconversion spectroscopy because of the detection limitation to the long wavelength edge of the carminic-acid spectrum. The four S lifetimes were ascribed to the coexistence of respectively two tautomer (normal and tautomer) forms of carminic acid, in the non-dissociated state (CAH) and in the deprotonated state (CA). The fluorescence upconversion measurements of carminic acid-DNA complexes exhibited a prolongation of the fluorescence lifetimes. This effect was accepted as evidence for the formation of intercalation complexes between the carminic acid and the DNA. The intercalative binding of the carminic acid to DNA was confirmed by the fluorescence titration experiments resulting to a binding constant of 2 × 10 M that is typical for anthracycline-DNA complexes. © 2006 Elsevier B.V. All rights reserved.

Femtosecond transient absorption spectroscopy of silanized silicon quantum dots - Kuntermann, Volker; Cimpean, Carla Ramona; Brehm, Georg; Sauer, Guido; Kryschi, Carola; Wiggers, Hartmut (Physical Review B, 2008)
Excitonic properties of colloidal silicon quantum dots (Si qdots) with mean sizes of 4 nm were examined using stationary and time-resolved optical spectroscopy. Chemically stable silicon oxide shells were prepared by controlled surface oxidation and silanization of HF-etched Si qdots. The ultrafast relaxation dynamics of photogenerated excitons in Si qdot colloids were studied on the picosecond time scale from 0.3 ps to 2.3 ns using femtosecond-resolved transient absorption spectroscopy. The time evolution of the transient absorption spectra of the Si qdots excited with a 150 fs pump pulse at 390 nm was observed to consist of decays of various absorption transitions of photoexcited electrons in the conduction band which overlap with both the photoluminescence and the photobleaching of the valence band population density. Gaussian deconvolution of the spectroscopic data allowed for disentangling various carrier relaxation processes involving electron-phonon and phonon-phonon scatterings or arising from surface-state trapping. The initial energy and momentum relaxation of hot carriers was observed to take place via scattering by optical phonons within 0.6 ps. Exciton capturing by surface states forming shallow traps in the amorphous Si Ox shell was found to occur with a time constant of 4 ps, whereas deeper traps presumably localized in the Si-Si Ox interface gave rise to exciton trapping processes with time constants of 110 and 180 ps. Electron transfer from initially populated, higher-lying surface states to the conduction band of Si qdots (>2 nm) was observed to take place within 400 or 700 fs. © 2008 The American Physical Society.
Keywords: absorption; quantum; dots; spectroscopy

Fine-tuning the assemblies of carbon nanodots and porphyrins - Scharl, Tobias; Cadranel, Alejandro; Haines, Philipp; Strauß, Volker; Bernhardt, Sarah; Vela, Sonia; Atienza, Carmen; Gröhn, Franziska; Martin, Nazario; Guldi, Dirk Michael (Chemical Communications, 2018)
We present charge-transfer assemblies of electron accepting, pressure-synthesized carbon nanodots (pCNDs) and an electron donating porphyrin. Amidine derivatization of the porphyrin allows for hydrogen bonding interactions with the carboxyl groups on the surface of pCNDs, which drive the formation of the assembly. Upon photoexcitation, this electron donor-acceptor supramolecular construct features ultrafast charge separation, and subsequent charge recombination in 27 ps.
CRIS-Team Scopus Importer:2022-04-14

First comparative emission assay of single-wall carbon nanotubes - Solutions and dispersions - Guldi, Dirk Michael; Holzinger, Michael; Hirsch, Andreas; Georgakilas, Vasilios; Prato, Maurizio (Chemical Communications, 2003)
A variety of single-wall carbon nanotube samples were tested in steady-state and time-resolved emission experiments, where it was found that chemical functionalization and different degrees of oxidation affect the emission behavior.

Formation of gas-phase metal fluorides in reactions of fluorinated fullerenes at activated metal surfaces - Streletskiy, Alexey V.; Kellner, Ina; Nye, Leanne C.; Drewello, Thomas; Hvelplund, Preben; Boltalina, Olga V. (Journal of Fluorine Chemistry, 2017)
A comparative investigation into the chemical reactions of a series of fluorinated fullerenes (C60F18, C60F36 and C60F48) with a variety of activated metal surfaces is reported. New ways of generating intense beams of metal fluoride anions are demonstrated: either in reactions of fluorinated fullerene vapours with hot W and Mo metal surfaces in a plasma ion source or by laser desorption/ionisation (LDI) of solid fluorinated fullerenes from various metal substrates (Al, Fe, Cu, Pt, W). In both cases, the resulting metal fluorides and their anions are formed in the highest oxidation state, yielding molybdenum and tungsten hexafluoride anions (plasma ion source), aluminium and iron tetrafluoride anions, and copper trifluoride anions (LDI). No reactions were observed with Pt and W in LDI. The reactivity of the metals towards fluorination correlates with their positions in the metal activity series. Relative yields of bare metal cations are dictated by their ionisation energy. The yield of metal fluoride anions is strongly dependent on the fluorine content of the fluorofullerenes.
Created from Fastlane, Scopus look-up
Keywords: Fluorinated fullerenes; Fluorination; Laser desorption; Mass spectrometry; Metal fluorides; Negative ions

Formation of highly charged quasi-molecular ions of a polycationic [60]fullerene hexakis-adduct and their fragmentation behavior in the gas phase - Li, Jing; Nye, Leanne C.; Wasserthal, Lennard; Vinh, Chau; Kirschbaum, Rolf; Ivanovic-Burmazovic, Ivana; Hirsch, Andreas; Drewello, Thomas (European Journal of Organic Chemistry, 2015)
A novel polycationic [60]fullerene hexakis-adduct has been synthesized and investigated by electrospray ionization and tandem mass spectrometry. The polycationic ligand system comprises 12 pre-formed positive charges, compensated in the neutral molecule by bromide anions. Stable quasi-molecular cations were obtained through the release of the anionic counter ions covering a charge-state envelope from 3+ to 12+. Collision-induced dissociation experiments revealed three fragmentation pathways. A dominant neutral loss channel leads to daughter ions of the same charge state as the highly charged precursor ion and singly charged daughter ions can be expelled from the polycations through two distinct dissociation channels involving both the neutral and the charge-carrying part of their ligands.
Keywords: Electrospray ionization; Fullerenes; Mass spectrometry; Polycations

Formation of singly bonded fullerene dimers in electrospray mass spectrometry - Kellner, Ina; von Gernler, Marc; Tzirakis, Manolis D.; Orfanopoulos, Michael; Drewello, Thomas (Journal of Physical Chemistry C, 2014)
Created from Fastlane, Scopus look-up

Förster Resonance Energy Transfer Sensitized Singlet Fission in BODIPY-Pentacene Dimer Conjugates - Wollny, Anna-Sophie; Lavarda, Giulia; Papadopoulos, Ilias; López-Duarte, Ismael; Gotfredsen, Henrik; Hou, Yuxuan; Tykwinski, Rik R.; Torres, Tomás; Guldi, Dirk Michael (Advanced Optical Materials, 2023)
In the present work, the energy donor 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) is used for the first time in combination with a pentacene dimer (Pnc2) to provide the conjugate BODIPYPnc2 that features absorption throughout a large part of the solar spectrum. Upon photoexcitation, the singlet excited state energy of BODIPY is transferred to the pentacene dimer via intramolecular Förster resonance energy transfer (FRET). Subsequently, the pentacene dimer undergoes intramolecular singlet fission. In this process, a singlet correlated triplet pair is generated from the first singlet excited state via coupling to an intermediate state. The results show that solvent polarity has an influence on the system, with the largest FRET rate (i.e., 7.46 × 1011 s−1) being obtained in the most polar solvent (namely, benzonitrile) along with the largest triplet quantum yield (i.e., 207 ± 20%).
CRIS-Team Scopus Importer:2023-10-13
Keywords: BODIPY; down conversion; energy transfer; pentacene; photoenergy conversion; singlet fission; time-resolved spectroscopy

Four-Step Domino Reaction Enables Fully Controlled Non-Statistical Synthesis of Hexaarylbenzene with Six Different Aryl Groups** - Grau, Benedikt; Dill, Maximilian; Hampel, Frank; Kahnt, Axel; Jux, Norbert; Tsogoeva, Svetlana (Angewandte Chemie International Edition, 2021)
Hexaarylbenzene (HAB) derivatives are versatile aromatic systems playing a significant role as chromophores, liquid crystalline materials, molecular receptors, molecular-scale devices, organic light-emitting diodes and candidates for organic electronics. Statistical synthesis of simple symmetrical HABs is known via cyclotrimerization or Diels-Alder reactions. By contrast, the synthesis of more complex, asymmetrical systems, and without involvement of statistical steps, remains an unsolved problem. Here we present a generally applicable synthetic strategy to access asymmetrical HAB via an atom-economical and high-yielding metal-free four-step domino reaction using nitrostyrenes and alpha,alpha-dicyanoolefins as easily available starting materials. Resulting domino product-functionalized triarylbenzene (TAB)-can be used as a key starting compound to furnish asymmetrically substituted hexaarylbenzenes in high overall yield and without involvement of statistical steps. This straightforward domino process represents a distinct approach to create diverse and still unexplored HAB scaffolds, containing six different aromatic rings around central benzene core.
CRIS-Team WoS Importer:2021-09-03

From White to Red: Electric-Field Dependent Chromaticity of Light-Emitting Electrochemical Cells based on Archetypal Porphyrins - Weber, Michael; Wittmann, Judith; Burger, Alexandra; Malcioglu, Osman; Segarra-Marti, Javier; Hirsch, Andreas; Coto, Pedro B.; Bockstedte, Michel; Costa, Ruben D. (Advanced Functional Materials, 2016)
The differences in the electroluminescence (EL) of red-emitting free-base (H2TPP) and Zn-metalated (ZnTPP) archetypal porphyrins are rationalized in light-emitting electrochemical cells by means of an electric-field dependent effect, leading to whitish and reddish devices, respectively. Although H2TPP shows superior electrochemical and photophysical features compared to ZnTPP, devices prepared with ZnTPP surprisingly stand out with a deep-red EL similar to its photoluminescence (PL), while H2TPP devices feature unexpected whitish EL. Standard arguments such as degradation, device architecture, device mechanism, and changes in the nature of the emitting excited states are discarded. Based on electrochemical impedance spectroscopy and first-principles electronic structure methods, we provide evidence that the EL originates from two H2TPP regioisomers, in which the inner ring H atoms are placed in collinear and vicinal configurations. The combination of their optical features provides an explanation for both the high- and low-energy EL features. Here, the emitting excited state nature is ascribed to the Q bands, since the Soret excited states remain high in energy. This contrasts to what is traditionally postulated in reports focused on H2TPP lighting devices. Hence, this work provides a new explanation for the nature of the high-energy EL band of H2TPP that might inspire future works focused on white-emitting molecular-based devices.
Keywords: collinear and vicinal regioisomers; electric-field dependent chromaticity; light-emitting electrochemical cells; tetraphenyl porphyrin; thin-film white-emitting sources

Frontispiece: Regio-, Stereo-, and Atropselective Synthesis of C60Fullerene Bisadducts by Supramolecular-Directed Functionalization - Bottari, Giovanni; Trukhina, Olga; Kahnt, Axel; Frunzi, Michael; Murata, Yasujiro; Rodríguez-Fortea, Antonio; Poblet, Josep M.; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie International Edition, 2016)
CRIS-Team Scopus Importer:2023-03-07
Keywords: atropisomerism; cycloaddition; fullerenes; phthalocyanines; supramolecular chemistry

Fullerenes (C60) versus heteroazafullerenes (C59N); a photophysical comparison of their monoadducts and hexaadducts - Guldi, Dirk Michael; Hirsch, Andreas; Hauke, Frank (Research on Chemical Intermediates, 2002)
The singlet and triplet excited state properties of a series of fullerene derivatives (C) are compared to those of the corresponding heteroazafullerenes derivatives (CN) by employing a variety of steady-state and time-resolved photophysical assays. The most far-reaching results infer that the CN (2, 5) analogous of C (1, 4) are characterized by shorter singlet lifetimes (1.01/0.57 ns versus 1.80/1.75 ns) and weaker fluorescence quantum yields (1.6 × 10/2.1 × 10 versus 6.0 × 10/1.09 × 10). This general conclusion applies for the monoadduct series (1, 2) and also for the highly functionalized hexaadducts (4, 5). Similarly, higher singlet energies (1.89 eV (4) versus 1.79 eV (1)) come together with higher fluorescence quantum yields for the hexaadducts than for the monoadducts.

Fullerenes-how 25 years of charge transfer chemistry have shaped our understanding of (interfacial) interactions - Zieleniewska, Anna; Lodermeyer, Fabian; Roth, A.; Guldi, Dirk Michael (Chemical Society Reviews, 2018)
In this review article, we highlight over 25 years of fullerene research in charge transfer chemistry. The major thrust of this work is to illustrate interfacial interactions between fullerenes and porphyrins in electron donor-acceptor conjugates as well as self-assembled associates and co-crystallites all the way to organic photovoltaics. Hereby, the analysis of the fundamental proceses, namely, energy transfer, charge shift, charge separation as well as charge recombination stand at the forefront. Our examples, illustrate on how fine-tuning the structure leads to substantial alteration of interfacial interactions.
CRIS-Team Scopus Importer:2022-04-14

Fullerene Van der Waals Oligomers as Electron Traps - Shubina, Tatyana; Sharapa, Dmitry; Schubert, Christina; Zahn, Dirk; Halik, Marcus; Keller, Paul A.; Pyne, Stephen G.; Jennepalli, Sreenu; Guldi, Dirk Michael; Clark, Timothy (Journal of the American Chemical Society, 2014)
Density functional theory calculations indicate that van der Waals fullerene dimers and larger oligomers can form interstitial electron traps in which the electrons are even more strongly bound than in isolated fullerene radical anions. The fullerenes behave like "super atoms", and the interstitial electron traps represent one-electron intermolecular σ-bonds. Spectroelectrochemical measurements on a bis-fullerene-substituted peptide provide experimental support. The proposed deep electron traps are relevant for all organic electronics applications in which non-covalently linked fullerenes in van der Waals contact with one another serve as n-type semiconductors.

Functionalized fullerenes: Synthesis and functions - Guldi, Dirk Michael; Martin, N. (Comprehensive Nanoscience and Nanotechnology, 2019)
This chapter presents details on the chemistry of fullerenes, namely intramolecular nucleophilic addition reactions (Bingel-Hirsch reaction), 1,3-dipolar cycloadditions of azomethyne ylides (Prato reaction), and Diels-Alder cycloaddition reactions of ortho-quinodimethanes, and highlights aspects that relate to key topics in the so-called ‘organic molecular electronics’ field, namely molecular machines, molecular charge transfer systems, and molecular wires. A common feature to all these molecular systems is the presence of an electron donor covalently linked to an electron accepting fullerene through an organic bridge.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Extended TTF; Fullerenes; Molecular charge transfer; Molecular machines; Molecular wires; Porphyrins; Synthesis

Functional nanomaterials: Applications in medicine and life sciences - Klein, Stefanie; Kryschi, Maximilian; Kryschi, Carola (De Gruyter, 2024)
Nanoparticles (NPs) offer an innovative platform for targeted cancer diagnosis and therapy. Advanced synthesis and surface functionalization strategies facilitate reversible binding and triggered release of drugs. NPs are also excellent contrast agents for clinical imaging techniques. This book discusses current and future applications of functional nanoparticles in oncology, as well as strategies for tailoring novel multifunctional nanomaterials. Describes the various types of biocompatible nanomaterials with potential for use in nanomedicine. Explores all fields of application for nanoparticles in cancer diagnosis and treatment, from tumor targeting and imaging to radiotherapy.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bioinorganic chemistry; Biomedical engineering; Metallic nanoparticles; Molecular nanoscience; Nanomedicine; Nanoparticles; Therapeutic nano-carriers

Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

Gas-Phase Transformation of Fluorinated Benzoporphyrins to Porphyrin-Embedded Conical Nanocarbons - Lungerich, Dominik; Hitzenberger, Jakob; Ruppel, Michael; Döpper, Tibor; Witt, Matthias; Ivanovic-Burmazovic, Ivana; Görling, Andreas; Jux, Norbert; Drewello, Thomas (Chemistry - A European Journal, 2020)
Geodesic nitrogen-containing graphene fragments are interesting candidates for various material applications, but the available synthetic protocols, which need to overcome intrinsic strain energy during the formation of the bowl-shaped skeletons, are often incompatible with heteroatom-embedded structures. Through this mass spectrometry-based gas-phase study, we show by means of collision-induced dissociation experiments and supported by density functional theory calculations, the first evidence for the formation of a porphyrin-embedded conical nanocarbon. The influences of metalation and functionalization of the used tetrabenzoporphyrins have been investigated, which revealed different cyclization efficiencies, different ionization possibilities, and a variation of the dissociation pathway. Our results suggest a stepwise process for HF elimination from the fjord region, which supports a selective pathway towards bent nitrogen-containing graphene fragments.
CRIS-Team Scopus Importer:2020-09-11
Keywords: annulenes; collision-induced dissociation; C−F activation; mass spectrometry; polycyclic aromatic hydrocarbons; porphyrinoids

Gating charge recombination rates through dynamic bridges in tetrathiafulvalene-fullerene architectures - Castellanos, Sonia; Vieira, Andre A.; Illescas, Beatriz M.; Sacchetti, Valentina; Schubert, Christina; Moreno, Javier; Guldi, Dirk Michael; Hecht, Stefan; Martin, Nazario (Angewandte Chemie International Edition, 2013)
An open and shut case: The competition between charge separation and recombination in artificial photosynthetic systems can be controlled by using photochromic dynamic bridge. The photoinduced opening and closing of the bridge mediates the electronic coupling between donor (D) and acceptor (A). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Generation and detection of [C59N]+ by laser desorption/ionisation high-field Fourier transform ion cyclotron resonance mass spectrometry - Feng, X.; Clipston, Nigel; Brown, T.; Cooper, H.; Reuther, Uwe; Hirsch, Andreas; Derrick, P. J.; Drewello, Thomas (Rapid Communications in Mass Spectrometry, 2000)
Important parameters to consider when developing a liquid chromatography/mass spectrometry (LC/MS) method are buffer type and concentration, and column geometry. In the work presented here the choice of buffer for the analysis of basic compounds using a polar embedded phase (HyPURITY(TM) ADVANCE) is illustrated for the analysis of tricyclic antidepressants. Method transfer from a 4.6 mm i.d. column to a 2.1 mm i.d. column is demonstrated for the analysis of triazines and anabolic steroids and their metabolites, with no change in selectivity and with added speed of analysis. Analysis of eight β-blockers is achieved in 65 seconds by using a short 30 x 4.6 mm C18 column. (C) 2000 John Wiley and Sons, Ltd.

Geometric influence on intramolecular photoinduced electron transfer in platinum(II) acetylide-linked donor-acceptor assemblies - Molina-Ontoria, Agustin; Rivera-Nazario, Danisha M.; Tigreros, Alexis; Ortiz, Alejandro; Nunez, Jose E.; Insuasty, Braulio; Lüders, Daniela; Wolfrum, Silke; Guldi, Dirk Michael; Echegoyen, Luis (Chemistry - A European Journal, 2014)
A new donor-acceptor system, in which the electron donor triphenylamine (TPA) and the electron acceptor C60 are bridged through a cis- or trans-platinum(II) acetylide spacer have been prepared. Ground-state studies were conducted using electrochemistry and UV/Vis spectroscopy. Fluorescence studies suggested that charge transfer is the deactivation mechanism for the singlet excited state, and this was verified by transient absorption spectroscopy. Selective photoexcitation of 1 and 2 at 387 nm leads to a fast charge transfer between the TPA and C60, which gives rise to a radical ion-pair state (TPA.+-Pt-C60.-). Our results suggest that charge transfer is favored for the cis configuration while the presence of the trans configuration in the PtII diacetylide results in a longer-lived charge separated states. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electron transfer; excited states; fullerenes; platinum(II) acetylide; triphenylamine

Glycophthalocyanines as photosensitizers for triggering mitotic catastrophe and apoptosis in cancer cells - Soares, Ana R. M.; Neves, Maria G. P. M. S.; Tome, Augusto C.; Carmen Iglesias-De La Cruz, M.; Zamarron, Alicia; Carrasco, Elisa; Gonzalez, Salvador; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael; Juarranz, Angeles (Chemical Research in Toxicology, 2012)
Photodynamic therapy (PDT) is a treatment modality for different forms of cancer based on the combination of light, molecular oxygen, and a photosensitizer (PS) compound. When activated by light, the PS generates reactive oxygen species leading to tumor destruction. Phthalocyanines are compounds that have already shown to be efficient PSs for PDT. Several examples of carbohydrate substituted phthalocyanines have been reported, assuming that the presence of carbohydrate moieties could improve their tumor selectivity. This work describes the photoeffects of symmetric and asymmetric phthalocyanines with D-galactose (socalled GPh1, GPh2, and GPh3) on HeLa carcinoma cells and their involvement in cell death. Photophysical properties and in vitro photodynamic activities for the compounds considered revealed that the asymmetric glycophthalocyanine GPh3 is very efficient and selective, producing higher photocytotoxicity on cancer cells than in nonmalignat HaCaT. The cell toxiticy after PDT treatment was dependent upon light exposure level and GPh3 concentration. GPh3 causes cell cycle arrest at the metaphase stage leading to multiple spindle poles, mitotic catastrophe, followed by apoptosis in cancer cells. These effects were partially negated by the pancaspase inhibitor Z-VAD-FMK. Together, these results indicate that GPh3 is an excellent candidate drug for PDT, able to induce selective tumor cell death. (Chemical Equation Presented). © 2012 American Chemical Society.

Grafting porphyrins (face-to-edge/orthogonal versus face-to-face/parallel) to ZnO en route toward dye-sensitized solar cells - Werner, Fabian; Gnichwitz, Jan-Frederik; Marczak, Renata; Palomares, Emilio; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Journal of Physical Chemistry B, 2010)
Novel types of binding motives have been investigated within the context of sensitizing ZnO-based dyesensitized solar cells with metalloporphyrins. In particular, a complementary class of metalloporphyrin has been synthesized to probe the impact of a face-to-edge/orthogonal versus face-to-face/parallel orientation of the metalloporphyrin with respect to ZnO and has been compared to TiO-based dye-sensitized solar cells. Our studies provide a deep and detailed understanding of the individual electron-transfer processes at the ZnO/metalloporphyrin interface, that is, electron injection, recombination, and dye regeneration, by means of steady-state and time-resolved techniques. Interestingly, we found that for our novel ZnO/metalloporphyrin systems, the injection efficiencies are close to unity, despite their long, nonconjugated anchoring group length. © 2010 American Chemical Society.

Graphene - Another new kid on the (carbon) block - Guldi, Dirk Michael (Electrochemical Society Interface, 2011)

Graphene Oxide: A One- versus Two-Component Material - Naumov, Anton; Grote, Fabian; Overgaard, Marc; Roth, Alexandra Marina; Halbig, Christian Eberhard; Norgaard, Kasper; Guldi, Dirk Michael; Eigler, Siegfried (Journal of the American Chemical Society, 2016)
The structure of graphene oxide (GO) is a matter of discussion. While established GO models are based on functional groups attached to the carbon framework, another frequently used model claims that GO consists of two components, a slightly oxidized graphene core and highly oxidized molecular species, oxidative debris (OD), adsorbed on it. Those adsorbents are claimed to be the origin for optical properties of GO. Here, we examine this model by preparing GO with a low degree of functionalization, combining it with OD and studying the optical properties of both components and their combination in an artificial two-component system. The analyses of absorption and emission spectra as well as lifetime measurements reveal that properties of the combined system are distinctly different from those of GO. That confirms structural models of GO as a separate oxygenated hexagonal carbon framework with optical properties governed by its internal structure rather than the presence of OD. Understanding the structure of GO allows further reliable interpretation of its optical and electronic properties and enables controlled processing of GO.
CRIS-Team Scopus Importer:2023-03-07

Graphene Oxide-BODIPY Conjugates as Highly Fluorescent Materials - Reina, Giacomo; Beneventi, Giovanni Mariano; Kaur, Ramandeep; Biagiotti, Giacomo; Cadranel, Alejandro; Ménard-Moyon, Cécilia; Nishina, Yuta; Richichi, Barbara; Guldi, Dirk Michael; Bianco, Alberto (Chemistry - A European Journal, 2023)
Covalent functionalization of graphene oxide (GO) with boron dipyrromethenes (BODIPYs) was achieved through a facile synthesis, affording two different GO-BODIPY conjugates where the main difference lies in the nature of the spacer and the type of bonds between the two components. The use of a long but flexible spacer afforded strong electronic GO-BODIPY interactions in the ground state. This drastically altered the light absorption of the BODIPY structure and impeded its selective excitation. In contrast, the utilisation of a short, but rigid spacer based on boronic esters resulted in a perpendicular geometry of the phenyl boronic acid BODIPY (PBA-BODIPY) with respect to the GO plane, which enables only minor electronic GO-BODIPY interactions in the ground state. In this case, selective excitation of PBA-BODIPY was easily achieved, allowing to investigate the excited state interactions. A quantitative ultrafast energy transfer from PBA-BODIPY to GO was observed. Furthermore, due to the reversible dynamic nature of the covalent GO-PBA-BODIPY linkage, some PBA-BODIPY is free in solution and, hence, not quenched from GO. This resulted in a weak, but detectable fluorescence from the PBA-BODIPY that will allow to exploit GO-PBA-BODIPY for slow release and imaging purposes.
CRIS-Team Scopus Importer:2023-05-19
Keywords: carbon nanomaterials; chemical functionalization; imaging; photoluminescent properties; transient absorption spectroscopy

Ground and excited state electronic interactions in push-pull-chromophore- [60]fullerene conjugates - Yamada, Michio; Tancini, Francesca; Sekita, Michael; Guldi, Dirk Michael; Boudon, Corinne; Gisselbrecht, Jean-Paul; Alberti, Mariza N.; Schweizer, W. Bernd; Diederich, Francois (Fullerenes Nanotubes and Carbon Nanostructures, 2014)
A variety of push-pull-chromophore-[60]fullerene conjugates connected with different spacers was successfully synthesized by applying "click chemistry" to the corresponding acetylene-appended fullerene precursors. Direct connection of the fullerene cages to push-pull motifs gives rise to ground state electronic interactions, which were characterized by electrochemical studies. On the other hand, when the two moieties were linked through pyrrolidine rings, no interactions occurred between the C units and the push-pull motifs in the ground states. Instead, an electron transfer proceeded upon light exitation, giving the charge-separated states, which was corroborated by time-resolved transient absorption measurements. © 2014 Taylor and Francis Group, LLC.

Ground State versus Excited State: Discrepancy in Electronic Communication in a Series of meso–meso Two-Atom-Bridged Diporphyrins - Zieleniewska, Anna; Harper, Shannon R.; Arnold, Dennis P.; Guldi, Dirk Michael (Chemistry - A European Journal, 2018)
The focal point of this work is the photophysical characterization of three meso–meso two-atom-bridged diporphyrins. Detailed investigations by means of cyclic voltammetry, absorption, fluorescence, and femto-/nanosecond transient absorption spectroscopy revealed the discrepancy in electronic communication in a series of meso–meso two-atom-bridged porphyrins in the ground state and in the excited state. In the ground state, the azo bridge facilitates the strongest electronic communication between the two porphyrins. In the excited state, however, the ethene bridge induces the strongest coupling, followed by the imine and azo bridges.
CRIS-Team Scopus Importer:2022-04-14
Keywords: diporphyrins; electronic communication; electronic spectra; photochemistry; porphyrinoids

Happy Photometry-Tips and Tricks against the Pitfalls when using a School Photometer - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2020)
With the help of photometry, a large number of scientific projects can be performed at school. In this context, it is recommended to follow a series of experimental parameters. The following article is a help for identification of possible disruptive factors and troubleshooting.
CRIS-Team WoS Importer:2020-08-07

Harnessing multiple generated excitons from intermolecular singlet fission of perylene–monoimides in a p-type dye-sensitized solar cell - Papadopoulos, Ilias; Schol, Peter; Garcés-Garcés, Jose; Sastre-Santos, Ángela; Fernández-Lázaro, Fernando; Guldi, Dirk Michael (Solar Energy, 2023)
A perylene-monoimide (PMI) monomer is functionalized with a benzoic acid to support immobilization on copper oxide (CuO) / nickel oxide (NiO) p-type semiconductors in order to construct p-type dye-sensitized solar cells (DSSCs). All devices are fully characterized by means of J-V, electrochemical impedance, and incident photon-to-current conversion efficiency (IPCE) measurements. Their optimization in terms of PMI uptake, iodine / Li+ addition and layer thickness lead to efficiencies as high as 0.07 %. For PMIs, the favorable relationship between their respective singlet and triplet excited state energies of 2.36 and 1.12 eV enable thermodynamically driven singlet fission (SF). The strong inter–PMI interactions on the semiconductor surface allow for an efficient and fast intermolecular SF. The formed correlated triplet pair ((T1)(T1)) is corroborated by means of time-resolved transient absorption spectroscopy (TAS) and partakes in an interfacially charge injection into the CuO / NiO semiconductors within the p-type DSSCs.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Intermolecular singlet fission; P-type dye sensitized solar cells; Perylene-monoimides; Time-resolved spectroscopy

Helically and Linearly Fused Rylenediimide-Hexabenzocoronenes - Dusold, Carolin; Haines, Philipp; Platzer, Benedikt; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Perylene- as well as naphthalenediimides were fused to hexabenzocoronenes (HBCs) at their imide position to realize highly π-extended donor–acceptor (D–A)-hybrids. Successful isomer separation in the first step was decisive to guarantee a straightforward synthetic sequence. Hexaphenylbenzenes as precursors were accessed via Diels–Alder reactions and reacted in a Scholl oxidation to yield the respective HBC derivatives. The fully conjugated benzimidazole linker, which separates the electron donating HBC from the electron accepting rylenediimide, enabled the formation of either a linear or a helical configuration. Largely different chemical, physical, and optoelectrical characteristics were noted for the two configurations. What stood out was their aggregation and their excited state deactivation depending on the solvent polarity. Results from global analysis of the femtosecond transient absorption data corroborated the formation of a charge-transfer (CT) state that is stabilized in the helically fused configuration relative to the linear analogue. However, a comparison with spectroelectrochemical experiments failed to disclose evidence for a charge-separated (CS) state.
CRIS-Team Scopus Importer:2021-03-19
Keywords: charge transfer; helicene; hexabenzocoronene HBC; rylenediimide; transient absorption

Helically Chiral Mixed-Valence Systems Comprising N-Heterotriangulenes: Stabilization of the Cationic Species by π-Expansion - Borstelmann, Jan; Zank, Simon; Krug, Marcel; Berger, Georg; Fröhlich, Nina; Glotz, Gabriel; Gnannt, Frederik; Schneider, Lars; Rominger, Frank; Deschler, Felix; Clark, Timothy; Gescheidt, Georg; et al. (Angewandte Chemie International Edition, 2025)
We report the efficient stabilization of nitrogen-centered radical cations in a dimeric N-heterotriangulene bridged by a rigid π-conjugated [5]helicene backbone (NTH). The rigid scaffold exhibits helical chirality, allowing the enantiomers to be separated and their chiroptical properties studied, including circular dichroism (CD) and circularly polarized luminescence (CPL). Successive oxidation towards the radical cation NTH⋅+ and dication NTH2+ reveals strong electronic communication between the two nitrogen-centers, as demonstrated by X-ray crystallography, electrochemistry, UV/Vis/nIR spectroscopy and electron paramagnetic resonance (EPR) spectroscopy. CD measurements of the enantiomerically pure cations reveal strong Cotton effects in the nIR region extending up to 2000 nm. Density functional theory confirms the observed enhanced electronic communication, classifying NTH⋅+ as a Robin-Day Class III mixed-valence charge-transfer (MV–CT) system. NTH2+ exhibits a quinoidal structure with partial diradical character and open-shell singlet ground state, as shown by variable temperature EPR measurements. Time-resolved transient absorption spectroscopy shows the photo-induced generation of NTH⋅+ in the presence of a suitable electron acceptor.
CRIS-Team Scopus Importer:2025-03-07
Keywords: helicenes; mixed valence systems; N-heterotriangulenes; oxidation; radical cations

Hierarchically nanostructured MnCo2O4 as active catalysts for the synthesis of N-benzylideneaniline from benzyl alcohol and aniline - Liu, Liping (Green Chemistry, 2017)

Hierarchical organization of perylene bisimides and polyoxometalates for photo-assisted water oxidation - Bonchio, Marcella; Syrgiannis, Zois; Burian, Max; Marino, Nadia; Pizzolato, Erica; Dirian, Konstantin; Rigodanza, Francesco; Volpato, Giulia Alice; La Ganga, Giuseppina; Demitri, Nicola; Berardi, Serena; Amenitsch, Heinz; et al. (Nature Chemistry, 2019)
The oxygen in Earth’s atmosphere is there primarily because of water oxidation performed by photosynthetic organisms using solar light and one specialized protein complex, photosystem II (PSII). High-resolution imaging of the PSII ‘core’ complex shows the ideal co-localization of multi-chromophore light-harvesting antennas with the functional reaction centre. Man-made systems are still far from replicating the complexity of PSII, as the majority of PSII mimetics have been limited to photocatalytic dyads based on a 1:1 ratio of a light absorber, generally a Ru–polypyridine complex, with a water oxidation catalyst. Here we report the self-assembly of multi-perylene-bisimide chromophores (PBI) shaped to function by interaction with a polyoxometalate water-oxidation catalyst (Ru4POM). The resulting [PBI]5Ru4POM complex shows a robust amphiphilic structure and dynamic aggregation into large two-dimensional paracrystalline domains, a redshifted light-harvesting efficiency of >40% and favourable exciton accumulation, with a peak quantum efficiency using ‘green’ photons (λ > 500 nm). The modularity of the building blocks and the simplicity of the non-covalent chemistry offer opportunities for innovation in artificial photosynthesis.
CRIS-Team Scopus Importer:2021-04-20

High efficiency and stability small molecule solar cells developed by bulk microstructure fine-tuning - Min, Jie; Jiao, Xuechen; Sgobba, Vito; Kan, Bin; Heumüller, Thomas; Rechberger, Stefanie; Spiecker, Erdmann; Guldi, Dirk Michael; Wan, Xiangjian; Chen, Yongsheng; Ade, Harald; Brabec, Christoph (Nano Energy, 2016)
Morphological control over the bulk heterojunction (BHJ) microstructure of a high-efficiency small molecule photovoltaic system composed of a quinquethiophene based molecule (DRCN5T) as electron donor and [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM) as electron acceptor is demonstrated using three different post-processing strategies, including thermal annealing (TA), solvent vapor annealing (SVA), and two-step annealing (TA-SVA) treatments. We systematically analyze the processing condition-microstructure-device property relationships, explore the corresponding morphology evolution and their effects on carrier transport and recombination dynamics in BI-Js as well as understand the nature of phase-separation process resulting in light-induced degradation mechanisms. Within the investigated results, the causative relations between annealing sequence, photovoltaic parameters, morphology evolution and charge carrier dynamics are for the first time delineated. In addition, the observed trade-offs in device efficiency and stability with respect to the well-defined morphologies are highlighted. The in-depth picture of the bulk microstructure formation and its kinetic evolution as a function of the specific post-processing approaches is a valuable asset for the design of new photovoltaic materials and thin film nanoscale architectures that are more efficient and better aid future commercialization efforts. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Blend microstructure; Morphological control; Annealing sequence; Phase-separation; Charge carrier dynamics; Degradation mechanisms

Highly efficient photocatalytic hydrogen production via porphyrin-fullerene supramolecular photocatalyst with donor-acceptor structure - Liu, Liping (Chemical Engineering Journal, 2022)

Highly Stable Lasing from Solution-Epitaxially Grown Formamidinium-Lead-Bromide Micro-Resonators - Afify, Hany A.; Sytnyk, Mykhailo; Rehm, Viktor; Barabash, Anastasia; Mashkov, Oleksandr; Osvet, Andres; Volobuev, Valentine V.; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Götz, Klaus; Unruh, Tobias; et al. (Advanced Optical Materials, 2022)
High-quality epitaxial growth of oriented microcrystallites on a semiconductor substrate is demonstrated here for formamidinium lead bromide perovskite, by drop casting of precursor solutions in air. The microcrystallites exhibit green photoluminescence at room temperature, as well as lasing with low thresholds. Lasing is observed even though the substrate is fully opaque at the lasing wavelengths, and even though it has a higher refractive index as the perovskite active material. Moreover, the lasing is stable for more than 109 excitation pulses, which is more than what is previously achieved for devices kept in the air. Such highly stable lasing under pulsed excitation represents an important step towards continuous mode operation or even electrical excitation in future perovskite-based devices.
CRIS-Team Scopus Importer:2022-04-14
Keywords: halide perovskites; lasing; microresonators; solution epitaxy

Highly Strained, Radially π-Conjugated Porphyrinylene Nanohoops - Xu, Youzhi; Gsänger, Sebastian; Minameyer, Martin; Imaz, Inhar; Maspoch, Daniel; Shyshov, Oleksandr; Schwer, Fabian; Ribas, Xavi; Drewello, Thomas; Meyer, Bernd; Von Delius, Max (Journal of the American Chemical Society, 2019)
Small π-conjugated nanohoops are difficult to prepare, but offer an excellent platform for studying the interplay between strain and optoelectronic properties, and, increasingly, these shape-persistent macrocycles find uses in host-guest chemistry and self-assembly. We report the synthesis of a new family of radially π-conjugated porphyrinylene/phenylene nanohoops. The strain energy in the smallest nanohoop [2]CPT is approximately 54 kcal mol-1, which results in a narrowed HOMO-LUMO gap and a red shift in the visible part of the absorption spectrum. Because of its high degree of preorganization and a diameter of ca. 13 Å, [2]CPT was found to accommodate C60 with a binding affinity exceeding 108 M-1 despite the fullerene not fully entering the cavity of the host (X-ray crystallography). Moreover, the π-extended nanohoops [2]CPTN, [3]CPTN, and [3]CPTA (N for 1,4-naphthyl; A for 9,10-anthracenyl) have been prepared using the same strategy, and [2]CPTN has been shown to bind C70 5 times more strongly than [2]CPT. Our failed synthesis of [2]CPTA highlights a limitation of the experimental approach most commonly used to prepare strained nanohoops, because in this particular case the sum of aromatization energies no longer outweighs the buildup of ring strain in the final reaction step (DFT calculations). These results indicate that forcing ring strain onto organic semiconductors is a viable strategy to fundamentally influence both optoelectronic and supramolecular properties.
CRIS-Team Scopus Importer:2019-11-26

Homo and Hetero Molecular 3D Nanographenes Employing a Cyclooctatetraene Scaffold - Urieta-Mora, Javier; Krug, Marcel; Alex, Wiebke; Perles, Josefina; Fernández, Israel; Molina-Ontoria, Agustín; Guldi, Dirk Michael; Martín, Nazario (Journal of the American Chemical Society, 2020)
Two novel homo and hetero three-dimensional nanographenes, NG1 and NG2, featuring a cyclooctatetraene core are designed, synthesized, and characterized. A concise and efficient bottom-up methodology was employed during which 24 new carbon-carbon bonds were formed. By means of a Scholl reaction nanographenes with 53 fused rings are realized, which exhibited good solubility in common organic solvents. The resulting saddle-like structures of NG1 and NG2 are electron-rich and show good chemical and electrochemical stability. Their molecular structures are fully elucidated by single-crystal X-ray crystallography. From their crystal structure analysis is concluded that both nanographenes are chiral and crystallize as a racemic mixture. Our work was rounded-off by excited state investigations such as electron and energy transfer with electron-acceptors and -donors.
CRIS-Team Scopus Importer:2020-03-17

Homoleptic and Heteroleptic Copper Complexes as Redox Couples in Dye-Sensitized Solar Cells - Guldi, Dirk Michael; Lennert, Annkatrin (Chemphotochem, 2019)
To gather a comprehensive understanding of copper complexes as redox couples in dye-sensitized solar cells (DSSCs), a series of copper complexes were synthesized and thoroughly characterized. Characterization was undertaken using an arsenal of spectroscopic techniques, including steady-state spectroscopy, electrochemical and spectroelectrochemical assays, current-voltage measurements, electrochemical impedance spectroscopy (EIS), and transient absorption spectroscopy (TAS). Starting from a homoleptic copper complex featuring two bathocuproine ligands and replacing one of them by either another N- or a P-coordinating ligand, a clear relationship between ligand size, on one hand, and charge transport, recombination as well as effective regeneration of the sensitizer, on the other hand, was established. With this information in hand, the future targeted synthesis of copper complexes to achieve maximum device performance may be achieved.
CRIS-Team WoS Importer:2019-08-30

Host-guest complexation of [60]fullerenes and porphyrins enabled by "click chemistry" - Le Ho, Khanh-Hy; Hijazi, Ismail; Rivier, Lucie; Gautier, Christelle; Jousselme, Bruno; De Miguel Rojas, Gustavo; Nieto, Carlos Romero; Guldi, Dirk Michael; Heinrich, Benoit; Donnio, Bertrand; Campidelli, Stephane (Chemistry - A European Journal, 2013)
Herein the synthesis, characterization, and organization of a first-generation dendritic fulleropyrrolidine bearing two pending porphyrins are reported. Both the dendron and the fullerene derivatives were synthesized by Cu-catalyzed alkyne-azide cycloaddition (CuAAC). The electron-donor-acceptor conjugate possesses a shape that allows the formation of supramolecular complexes by encapsulation of C within the jaws of the two porphyrins of another molecule. The interactions between the two photoactive units (i.e., C and Zn-porphyrin) were confirmed by cyclic voltammetry as well as by steady-state and time-resolved spectroscopy. For example, a shift of about 85 mV was found for the first reduction of C in the electron-donor-acceptor conjugate compared with the parent molecules, which indicates that C is included in the jaws of the porphyrin. The fulleropyrrolidine compound exhibits a rich polymorphism, which was corroborated by AFM and SEM. In particular, it was found to form supramolecular fibrils when deposited on substrates. The morphology of the fibrils suggests that they are formed by several rows of fullerene-porphyrin complexes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Hot electron injection into semiconducting polymers in polymer based-perovskite solar cells and their fate - Jiménez-López, Jesús; Puscher, Bianka; Cambarau, Werther; Fink, Rainer; Palomares, Emilio; Guldi, Dirk Michael (Nanoscale, 2019)
Metal halide perovskites are known to possess upon photoexcitation long-lived hot carriers. By using femtosecond laser transient absorption spectroscopy, we probed in the current work interfacial charge transfer, that is, hot electrons and holes in methylammonium lead iodide perovskite. The focus was, on the one hand, on titanium dioxide as an electron transporting material and, on the other hand, on several organic semiconducting materials as hole transporting materials in perovskite solar cells. An unexpected carrier loss pathway for hot electrons was found in the form of injection into the low lying LUMOs of several organic semiconducting materials. Of great importance is the fact that the final photocurrents of perovskite solar cells scale with the suppression of this newly discovered loss pathway.
CRIS-Team Scopus Importer:2019-12-27

How To Make Nitroaromatic Compounds Glow: Next-Generation Large X-Shaped, Centrosymmetric Diketopyrrolopyrroles - Skonieczny, Kamil; Papadopoulos, Ilias; Thiel, Dominik; Gutkowski, Krzysztof; Haines, Philipp; McCosker, Patrick Michael; Laurent, Adele D.; Keller, Paul A.; Clark, Timothy; Jacquemin, Denis; Guldi, Dirk Michael; Gryko, Daniel T. (Angewandte Chemie International Edition, 2020)
Red-emissive pi-expanded diketopyrrolopyrroles (DPPs) with fluorescence reaching lambda=750 nm can be easily synthesized by a three-step strategy involving the preparation of diketopyrrolopyrrole followed by N-arylation and subsequent intramolecular palladium-catalyzed direct arylation. Comprehensive spectroscopic assays combined with first-principles calculations corroborated that both N-arylated and fused DPPs reach a locally excited (S-1) state after excitation, followed by internal conversion to states with solvent and structural relaxation, before eventually undergoing intersystem crossing. Only the structurally relaxed state is fluorescent, with lifetimes in the range of several nanoseconds and tens of picoseconds in nonpolar and polar solvents, respectively. The lifetimes correlate with the fluorescence quantum yields, which range from 6 % to 88 % in nonpolar solvents and from 0.4 % and 3.2 % in polar solvents. A very inefficient (T-1) population is responsible for fluorescence quantum yields as high as 88 % for the fully fused DPP in polar solvents.
CRIS-Team WoS Importer:2020-07-24

Hybrid Dye-Titania Nanoparticles for Superior Low-Temperature Dye-Sensitized Solar Cells - Kunzmann, Andreas; Valero, Silvia; Sepulveda, Angel E.; Rico-Santacruz, Marisa; Lalinde, Elena; Berenguer, Jesus R.; Garcia-Martinez, Javier; Guldi, Dirk Michael; Serrano, Elena; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2018)
In this work, a new strategy to design low-temperature (≤200 °C) sintered dye-sensitized solar cells (lt-DSSC) is reported to enhance charge collection efficiencies (ηcoll), photoconversion efficiencies (η), and stabilities under continuous operation conditions. Realization of lt-DSSC is enabled by the integration of hybrid nanoparticles based on TiO2-Ru(II) complex (TiO2_Ru_IS)—obtained by in situ bottom-up construction of Ru(II) N3 dye-sensitized titania—into the photoelectrode. Incentives for the use of TiO2_Ru_IS are i) dye stability due to its integration into the TiO2 anatase network and ii) enhanced charge collection yield due to its significant resistance toward electron recombination with electrolytes. It is demonstrated that devices with single-layer photoelectrodes featuring blends of P25 and TiO2_Ru_IS give rise to a 60% ηcoll relative to a 46% ηcoll for devices with P25-based photoelectrodes. Responsible for this trend is a better charge transport and a reduced electron recombination. When using a multilayered photoelectrode architecture with a top layer based only on TiO2_Ru_IS, devices with an even higher ηcoll (74%) featuring a η of around 8.75% and stabilities of 600 h are achieved. This represents the highest values reported for lt-DSSC to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: charge collection efficiency; dye-sensitized solar cells; hybrid dye-titania nanoparticles; low temperature sintering; multilayered electrodes

Hydrogen bonding mediated orthogonal and reversible self-assembly of porphyrin sensitizers onto TiO2 nanoparticles - Zeininger, Lukas; Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Communications, 2016)
We report on the orthogonal, highly directional and reversible self-assembly of porphyrins onto TiO2 nanoparticles by means of hydrogen bonding interactions. Unifying the stable covalent surface attachment of tailored, synthesized Hamilton receptors with the advantages of a non-covalent supramolecular immobilization of porphyrin cyanurates resulted in a redox- and photo-active nanohybrid. The latter was successfully implemented into a new type of supramolecular dye-sensitized solar cells.

Hydrogen storage on fullerenes: Hydrogenation of C59N using C60H36 as the source of hydrogen - Vasil’ev, Yu; Hirsch, Andreas; Taylor, Roger; Drewello, Thomas (Chemical Communications, 2004)
CH has been used as the source of hydrogen for the in situ hydrogenation of (CN), leading to C NH as the main reaction product identified by negative-ion mass spectrometry and providing evidence of the usage of C as a storage device for hydrogen.

Identification of peptides reflecting the storage of UHT milk by MALDI-TOF-MS peptide profiling. - Dalabasmaz, Sevim; Dittrich, Daniel; Kellner, Ina; Drewello, Thomas; Pischetsrieder, Monika (Journal of Proteomics, 2019)
Proteolysis during the storage of UHT milk is associated with major technological problems, particularly bitter off-flavors and age gelation limiting the shelf life of milk. In this study, untargeted peptide profiling by MALDITOF- MS identified peptides that were formed by proteolysis and reflected the storage of UHT milk. Analysis of nine different commercial UHT samples recorded peptide profiles during and at the end of their shelf life. Relative quantification and sequencing of the peptides revealed that the concentrations of 22 peptides increased significantly during the storage of UHT milk due to the activity of endogenous milk proteases and microbial proteases as well as other unidentified proteolytic mechanisms. Based on highly discriminative AUC values from receiver operator characteristic (ROC) curve analysis, we selected ten peptides as marker candidates. Among those, the peptide β-casein192–206 (m/z 1668.9) was the most suitable marker differentiating expired-UHT from regular-UHT samples with 100% accuracy. Additionally, β-casein191–206 (m/z 1782.0) showed 100% specificity and β-casein139–161 (m/z 2696.4) 100% sensitivity. Thus, β-casein192–206, either by itself or in combination with β-casein191–206 and β-casein139–161, presents a reliable marker to monitor the storage of UHT milk based on proteolytic mechanisms.
Keywords: Peptide profiling; milk proteases; storage; UHT milk; MALDI-TOF-MS

Immobilizing NIR absorbing azulenocyanines onto single wall carbon nanotubes - From charge transfer to photovoltaics - Ince, Mine; Bartelmeß, Jürgen; Kießling, Daniel; Dirian, Konstantin; Victoria Martinez-Diaz, M.; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2012)
In this fundamental study, the supramolecular interactions between SWNTs and either symmetrical Zn(ii) octa-tert-butylazulenocyanine 1 or a Zn(ii) azulenocyanine-phthalocyanine 2 bearing a pyrene unit have been evaluated. The synthetic protocol allowed for the preparation of unsymmetrical azulenocyanine-phthalocyanine molecules, which incorporate reactive hydroxyl functional groups useful for the preparation of more elaborate derivatives, that is, the pyrene containing derivative 2 by an esterification reaction. To shed light onto the mutual interactions between 1 or 2 and SWNT, stable suspensions of SWNT in a mixture of 25% THF and 75% DMF were titrated with variable amounts of 1 or 2. These assays indicate a successful immobilization of azulenocyanine derivatives 1 or 2 onto SWNTs to yield the supramolecular hybrids SWNT/1 and SWNT/2. In this light, the physico-chemical properties of 1 and 2 as well as those of SWNT/1 and SWNT/2 were investigated. From these we conclude strong interactions in the ground state, and a rapid charge separation in the excited state of SWNT/1 or SWNT/2. The accordingly formed radical ion pair states decay with lifetimes of 124 and 137 ps for SWNT/1 and SWNT/2, respectively. Finally, SWNT/1 and SWNT/2 were integrated into photoelectrochemical cells, revealing a response throughout the visible and near-infrared with a moderate IPCE maxima of 2.5%. © 2012 The Royal Society of Chemistry.

Immobilizing water-soluble dendritic electron donors and electron acceptors - Phthalocyanines and perylenediimides - Onto single wall carbon nanotubes - Hahn, Uwe; Engmann, Sarah; Oelsner, Christian; Ehli, Christian; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
The complementary use of spectroscopy and microscopy sheds light onto mutual interactions between semiconducting single wall carbon nanotubes (SWNT) and either a strong dendritic electron acceptor - perylenediimide - or a strong dendritic electron donor - phthalocyanine. Importantly, the stability of the perylenediimide/SWNT electron donor-acceptor hybrids decreases with increasing dendrimer generation. Two effects are thought to be responsible for this trend. With increasing dendrimer generation we enhance (i) the hydrophilicity and (ii) the bulkiness of the resulting perylenediimides. Both effects are synergetic and, in turn, lower the immobilization strength onto SWNT. Owing to the larger size of the phthalocyanines, phthalocyanine/SWNT electron donor-acceptor hybrids, on the other hand, did not reveal such a marked dependence on the dendrimer generation. Several spectroscopies confirmed that distinct ground- and excited-state interactions prevail and that kinetically and spectroscopically well-characterized radical ion pair states are formed within a few picoseconds. © 2010 American Chemical Society.

Implementation of a Hamiliton-receptor-based hydrogen-bonding motif toward a new electron donor-acceptor prototype: Electron versus energy transfer - Wessendorf, Florian; Gnichwitz, Jan-Frederik; Sarova, Ginka; Hager, Kristine; Hartnagel, Uwe; Guldi, Dirk Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2007)
A new modular concept for the self-assembly of electron donor-acceptor complexes is presented that ensures (i) fine-tuning the strength of the complexation, (ii) controlling the electronic coupling to impact electron and energy transfer processes, and (iii) high solubility of the corresponding hybrid architectures This task has been realized through developing a series of porphyrin-fullerene donor-acceptor systems held together by a Hamilton-receptor-based hydrogen-bonding motif. In this context, novel libraries of C monoadducts (1) containing cyanuric acid side chains and of tetraphenylporphyrin derivatives (2) involving the complementary Hamilton-receptor unit were synthesized. The association constants of the corresponding 1:1 complexes (1·2) connected by six hydrogen bonds were determined complementary by NMR and fluorescence assays. Their strength, which was found to be in the range between 3.7 × 10 and 7.9 × 10 M, depends on the nature of the spacers, namely, hexylene versus propylene chains. Finally transient absorption studies revealed photoinduced electron transfer from ZnP to C in the corresponding 1·2 complexes, which generate radical ion pair states that are persistent well beyond the ns time scale. In the case of the analogous SnP complexes, energy instead of electron transfer was observed. This is due to the shift of oxidation potential caused by presence of Sn in the oxidation state of +4. © 2007 American Chemical Society.

Implementation of redox gradients in hydrogen bonded complexes containing N,N-dimethylaniline, flavin and fullerene derivatives - Murakami, Motonobu; Ohkubo, Kei; Hasobe, Taku; Sgobba, Vito; Guldi, Dirk Michael; Wessendorf, Florian; Hirsch, Andreas; Fukuzumi, Shunichi (Journal of Materials Chemistry, 2010)
A variety of supramolecular complexes were formed by associating an electron donor-substituted flavin dyad (10-[4′-(N,N-dimethylamino)phenyl] isoalloxazine: DMA-Fl) and a family of fullerene derivatives that contain single and double hydrogen bond receptors (SRC and DRC). The stoichiometry of the corresponding complexes, that is, DMA-Fl and SRC or DRC, were examined by Job's plot analysis of the absorption changes linked to DMA-Fl at 470 nm. To this end, 1:1 and 1:2 complex stoichiometries were determined for DMA-Fl-SRC and (DMA-Fl) -DRC, respectively. Molecular aggregates in the form of remarkably stable clusters were formed by the fast injection method. Insights into these clusters came from transmission electron microscopy (TEM) measurements, which revealed network configurations for (DMA-Fl-SRC ) with diameters in the range between 200 and 500 nm, while uniform nanoparticles of about 40 nm diameter were discernible for [(DMA-Fl)-DRC]. The highly colored composite clusters were assembled onto an optically transparent electrode covered with nanostructured SnO films by the electrophoretic deposition technique. Important are the photocurrent action spectra providing maximum IPCE values that are twice as high for [(DMA-Fl)-DRC ] than for (DMA-Fl-SRC). To complement these studies the dynamics of electron transfer were investigated by femtosecond laser flash photolysis in the supramolecular clusters (i.e., (DMA-Fl-SRC) and [(DMA-Fl)-DRC ]). As a matter of fact, for the first time we were able to demonstrate the unidirectional electron transfer from the terminal electron donor (N,N-dimethylaniline) moiety to the terminal electron acceptor (fullerene) moiety. © The Royal Society of Chemistry 2010.

Implementation of Single-Walled Carbon Nanohorns into Solar Cell Schemes - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (Advanced Energy Materials, 2017)
Recent advances in dye-sensitized solar cells (DSSC), including the use of nanocarbons, resulted in breakthroughs relevant to both the academic and industrial sectors. Their relevance encompasses, on one hand, the development and integration of novel nanocarbon/dye hybrids for superior light-harvesting and improved charge injection properties and, on the other hand, the integration of nanocarbons into each part of DSSCs for enhancing the charge collection efficiency as well as the dye and electrolyte regeneration processes. In the context of the earlier, control over the electron injection and recombination rates is realized on the molecular level. In the context of the latter, i) the charge transport and charge collection efficiencies in the photoelectrode are increased, ii) the charge recombination processes are reduced, when used as a nanocarbon-based buffer layer, iii) the ion diffusion and catalytic effects into (quasi) solid-state electrolytes are improved, and iv) devices using Pt-free counter electrodes with similar device efficiencies are realized. Leading examples of nanocarbons are graphene, carbon black, multi-walled carbon nanotubes, and single-walled carbon nanotubes. In this review, the focus is on a novel carbon allotrope, namely single-walled carbon nanohorns (SWCNH), which is discussed in depth and in comparison with other nanocarbons.
EAM Import::2019-03-13

Improved Carrier Collection and Hot Electron Extraction across Perovskite, C60, and TiO2 Interfaces - Jiménez-López, Jesús; Puscher, Bianka; Guldi, Dirk Michael; Palomares, Emilio (Journal of the American Chemical Society, 2020)
The use of C60 as an interfacial layer between TiO2 and methylammonium lead iodide perovskite is probed to reduce the current-voltage hysteresis in perovskite solar cells (PSCs) and, in turn, to impact the interfacial carrier injection and recombination processes that limit solar cell efficiencies. Detailed kinetic analyses across different time scales, that is, from the femtoseconds to the seconds, reveal that the charge carrier lifetimes as well as the charge injection and charge recombination dynamics depend largely on the presence or absence of C60. In addition, we corroborate that C60 is applicable in hot carrier PSCs as it is capable of extracting hot carriers generated throughout the early time scales following photoexcitation.
CRIS-Team Scopus Importer:2020-02-04

Improved charge carrier dynamics in polymer/perovskite nanocrystal based hybrid ternary solar cells - Soltani, Rezvan; Puscher, Bianka; Katbab, Ali Asghar; Levchuk, Ievgen; Kazerouni, Negar; Gasparini, Nicola; Camaioni, Nadia; Osvet, Andres; Batentschuk, Miroslaw; Fink, Rainer; Guldi, Dirk Michael; Ameri, Tayebeh (Physical Chemistry Chemical Physics, 2018)
Here, brand new ternary hybrid solar cells comprising perovskite nanocrystals (NCs) with a complementary absorption profile of the organic host matrix are reported. In particular, NH2CHNH2PbI3 (FAPbI3) perovskite NCs are implemented in bulk heterojunction organic solar cells based on the pDPP5T-2 electron donating polymer and a [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) acceptor at various loading amounts and the fabricated hybrid photovoltaics are thoroughly studied by employing different optoelectrical characterization methods. Current-voltage measurements and photoinduced charge carrier extraction by linear increasing voltage (photo-CELIV) reveal improved charge generation and charge transport properties upon incorporation of perovskite NCs into the photo-active layer of the hybrid solar cell. The power conversion efficiency (PCE) of the hybrid solar cell comprising 5% perovskite NCs is 10% enhanced compared to the organic reference, mainly due to the enlarged light harvesting and increased short circuit current density (Jsc). However, results suggest that introducing a higher amount of perovskite content induces bimolecular and trap-assisted recombination in the ternary devices. We perform a comprehensive transient absorption study of the charge transfer/transport mechanisms by employing femto-second pump-probe transient absorption spectroscopy (fs-TAS). fs-TAS measurements demonstrate a slower charge carrier recombination rate due to the introduction of perovskite NCs into the photoactive layer. Results reveal that DPP injects electrons from the singlet excited state into the perovskite NCs, which causes the desired cascading charge carrier transfer. In ternary blends, a small amount of FAPbI3 NCs provides an additional pathway in favor of the charge-separated state via the NCs, which, despite accelerating the depopulation of DPP's singlet excited state slightly slows down the charge-separation process between DPP and PC61BM. Interestingly, the loss processes are slowed down; an effect that is more important and, hence, explains the improved solar cell efficiency. © 2018 the Owner Societie

Improving charge injection and charge transport in CuO-based p-type DSSCs-a quick and simple precipitation method for small CuO nanoparticles - Langmar, Oliver; Ganivet, Carolina R.; Schol, Peter; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael (Journal of Materials Chemistry C, 2018)
Herein, we introduce a co-precipitation synthesis of CuO, which produces small and uniform nanoparticles (∼12 nm) with a specific surface area of 97.3 m2 g-1. The resulting CuO nanoparticles are superior to the commercial ones, which have previously been used to prepare p-type DSSCs. In turn, we compared p-type DSSCs consisting of CuO-based photocathodes based on newly synthesized and commercial nanoparticles. Devices based on new CuO nanoparticles enable higher dye loadings, and, in turn, superior short-circuit current densities and efficiencies. To corroborate our findings, electrochemical impedance spectroscopy and intensity modulated photocurrent spectroscopy assays were conducted, revealing a better charge injection and faster charge transport for those photocathodes featuring the new CuO nanoparticles.
CRIS-Team Scopus Importer:2022-04-14

Improving Photocatalytic Hydrogen Generation via Polycitric Acid-based Carbon Nanodots - Guldi, Dirk Michael; Langford, Daniel; Reva, Yana; Bo, Yifan; Gubanov, Kirill; Wu, Mingjian; Günay-Gürer, Ayşe; Mai, Lukas A.; Crisp, Ryan; Engelmann, Iryna; Spiecker, Erdmann; Fink, Rainer; et al. (Angewandte Chemie International Edition, 2025)
Bottom-up syntheses of carbon nanodots (CND) using solvothermal treatment of citric acid are known to afford nanometer-sized, amorphous polycitric acid-based materials. The addition of suitable co-reactants in the form of in situ synthesized N-hetero-π-conjugated chromophores facilitates hereby the overall functionalization. Reports regarding the influence of CND on the properties of, for example, N-hetero-π-conjugated chromophores are scarce. Thus, our incentive was to design a CND model that features phenazine (P-CND) – a well-known N-hetero-π-conjugated chromophore – to investigate the influence of the CND matrix on its redox chemistry as well as photochemistry. The scope of our work was to go beyond investigating the electrochemical properties of the resulting P-CND by shedding light onto differences relative to nano-aggregates of phenazine (PNZNA), which served as reference. In particular, chemical as well as electrochemical reduction of PNZNA initiated a reaction cascade that affords the primary reduction intermediate, that is, the reduced and protonated (PNZ-H)⋅. In accordance with existing literature, the final product of a bimolecular disproportionation was 5,10-dihydrophenazine (PNZ-H2). Reducing P-CND also resulted in the formation of (PNZ-H)⋅. But, no evidence for a subsequent bimolecular disproportionation was gathered. Instead, (PNZ-H)⋅ as an integrative part of P-CND was found to be actively involved in a H2 generation reaction. A more than twofold increase in efficiency compared to PNZNA under identical conditions was the consequence.
CRIS-Team Scopus Importer:2025-02-28
Keywords: carbon nanodot; phenazine; pulse radiolysis; reduction; transient absorption

Improving photocurrent generation: Supramolecularly and covalently functionalized single-wall carbon nanotubes-polymer/porphyrin donor-acceptor nanohybrids - Rahman, Aminur; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Jux, Norbert; Tchoul, Maxim N.; Ford, Warren T.; Mateo-Alonso, Aurelio; Prato, Maurizio (Chemistry - A European Journal, 2008)
Novel nanohybrids based on covalently and noncovalently functionalized single-wall carbon nanotubes (SWNTs) have been prepared and assembled for the construction of photoactive electrodes. Polymer-grafted SWNTs were synthesized by free-radical polymerization of (vinylbenzyl)trimethylammonium chloride. Poly[(vinylbenzyl)trimethylammonium chloride] (PVBTA) was also noncovalently wrapped around SWNTs to form stable, positively charged SWNT/PVBTA suspensions in water. Versatile donor-acceptor nanohybrids were prepared by using the electrostatic/van der Waals interactions between covalent SWNT-PVBTA and/or noncovalent SWNT/PVBTA and porphyrins (HP and/or ZnP ). Several spectroscopic, microscopic, transient, and photoelectrochemical measurements were taken to characterize the resulting supramolecular complexes. Photoexcitation of the nanohybrids afforded long-lived radical ion pairs with lifetimes as long as 2.2 us. In the final part, photoactive electrodes were constructed by using a layer-by-layer technique on an indium tin oxide covered glass support. Photocurrent measurements gave remarkable internal photon-to-current efficiencies of 3.81 and 9.90% for the covalent ZnP-/SWNT-PVBTA and noncovalent ZnP /SWNT/PVBTA complex, respectively, when a potential of 0.5 V was applied. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Influence of electronic and molecular structure on the fragmentation dynamic of even-electron carbocationic triangulenes and helicenes in the gas phase - Hitzenberger, Jakob; Uhl, Agnes; Schatz, Jürgen; Drewello, Thomas (Journal of Mass Spectrometry, 2017)
Stable, long-lived organic cations are directly transferred by electrospray ionization (ESI) from solution into the gas phase where their collision-induced dissociations (CID) are studied by tandem mass spectrometry. Three related types of triphenyl carbenium ions are investigated, in which the meta positions are either substituted by methoxy groups or tertiary nitrogen bridges, including tetramethoxyphenylacridinium (TMPA+), dimethoxyquinacridinium (DMQA+), and triazatriangulenium (TATA+) cations. These ions are triangular in shape with increasing degrees of planarity. Fragmentation occurs at the periphery of the triangular molecule, involving the methoxy groups and the substituent of the nitrogen bridge. Each initial precursor cation is an even electron (EE) system and shows competing dissociations into both even (EE) and odd electron (OE) fragment ions. The latter reaction is a breach of the classic ‘even-electron rule’ in mass spectrometry. While the EE fragment dissociates similar to the precursor, the OE fragment ion shows a rich radical-induced fragmentation pattern. Two driving forces direct the fragmentation of the EE precursor ion toward OE fragment ions, including the release of stabilized radicals and the extension of the π-system by increasing planarization of the triangulene core.
Keywords: Triangulenium salt; mass spectrometry

Influence of Single Skimmer Versus Dual Funnel Transfer on the Appearance of ESI-Generated LiCl Cluster/ß-Cyclodextrin Inclusion Complexes - Kellner, Ina; Drewello, Thomas (Journal of the American Society For Mass Spectrometry, 2015)
Created from Fastlane, Scopus look-up
Keywords: Cluster; Cyclodextrin; Electrospray; LiCl; Oligosaccharide; Salt

Influence of the fullerene LUMO level on the stability of bulk heterojunction solar cells - Distler, A.; Cheon, K. -S.; Waller, D.; Guldi, Dirk Michael; Hauch, J.; Egelhaaf, H. -J. (Journal of Materials Chemistry C, 2021)
Poly(3-hexylthiophene) (P3HT) is combined with a series of C-60-based derivatives with LUMO energies varying between -3.53 and -3.83 eV, in order to study the influence of the fullerene LUMO level on the performance and stability of organic solar cells as well as the degradation of the photoactive materials. UV/vis measurements show that P3HT degrades more slowly in all investigated P3HT:fullerene blends compared to neat P3HT films when being irradiated in air. Accordingly, all fullerene derivatives stabilize P3HT against photo-oxidation, albeit to different extents, with the electron affinity of the fullerene determining the degree of stabilization. A fullerene LUMO level of -3.75 eV is found to cause maximum stabilization, while the degradation rate increases for higher and lower values. Remarkably, the higher the stabilization effect imposed by the fullerene the slower the fullerene degrades itself, which indicates a non-sacrificial mode of stabilization. Transient absorption spectroscopy measurements show similar kinetics of exciton quenching and charge generation for all P3HT:fullerene combinations indicating a similar morphology in all blend films. Inverted solar cells made from the different P3HT:fullerene blends exhibit a good correlation between fullerene LUMO level and open-circuit voltage. Upon illumination in air, the photovoltaic devices follow the same degradation trend as the isolated photoactive layers by showing the same dependence on the fullerene LUMO level. Finally, we discuss different mechanisms, by which fullerene acceptors are potentially able to stabilize (UV light screening, excited-state quenching, and radical scavenging) as well as destabilize (morphological effects, superoxide or singlet oxygen sensitization, and polymer triplet-state population) donor polymers.
CRIS-Team WoS Importer:2021-07-23

Influence of the heavy-atom effect on singlet fission: A study of platinum-bridged pentacene dimers - Basel, Bettina; Young, Ryan M.; Krzyaniak, Matthew D.; Papadopoulos, Ilias; Hetzer, Constantin; Gao, Yueze; La Porte, Nathan T.; Phelan, Brian T.; Clark, Timothy; Tykwinski, Rik R.; Wasielewski, Michael R.; Guldi, Dirk Michael (Chemical Science, 2019)
The process of singlet fission (SF) produces two triplet excited states (T1 + T1) from one singlet excited exciton (S1) and a molecule in its ground state (S0). It, thus, possesses the potential to boost the solar cell efficiency above the thermodynamic Shockley-Queisser limit of 33%. A key intermediate in the SF mechanism is the singlet correlated triplet pair state 1(T1T1). This state is of great relevance, as its formation is spin-allowed and, therefore, very fast and efficient. Three fundamentally different pathways to formation of 1(T1T1) have been documented so far. The factors that influence which mechanism is associated with which chromophore, however, remain largely unknown. In order to harvest both triplet excitons independently, a decorrelation of the correlated triplet pair state to two individual triplets is required. This second step of the SF process implies a change in the total spin quantum number. In the case of a dimer, this is usually only possible if the coupling between the two pentacenes is sufficiently weak. In this study, we present two platinum-bridged pentacene dimers in which the pentacenes are coupled strongly, so that spin-decorrelation yielding (T1 + T1) was initially expected to be outcompeted by triplet-triplet annihilation (TTA) to the ground state. Both platinum-bridged pentacene dimers undergo quantitative formation of the (T1T1) state on a picosecond timescale that is unaffected by the internal heavy-atom effect of the platinum. Instead of TTA of (T1T1) to the ground state, the internal heavy-atom effect allows for 1(T1T1)-3(T1T1) and 1(T1T1)-5(T1T1) mixing and, thus, triggers subsequent TTA to the (T1S0) state and minor formation of (T1 + T1). A combination of transient absorption and transient IR spectroscopy is applied to investigate the mechanism of the (T1T1) formation in both dimers. Using a combination of experiment and quantum chemical calculations, we are able to observe a transition from the CT-mediated to the direct SF mechanism and identify relevant factors that influence the mechanism that dominates SF in pentacene. Moreover, a combination of time-resolved optical and electron paramagnetic resonance spectroscopic data allows us to develop a kinetic model that describes the effect of enhanced spin-orbit couplings on the correlated triplet pair state.
CRIS-Team Scopus Importer:2019-12-31

Initiating Electron Transfer in Doubly Curved Nanographene Upon Supramolecular Complexation of C-60 - Zank, Simon; Fernandez-Garcia, Jesus M.; Stasyuk, Anton J.; Voityuk, Alexander A.; Krug, Marcel; Sola, Miquel; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2021)
The formation of supramolecular complexes between C-60 and a molecular nanographene endowed with both positive and negative curvatures is described. The presence of a corannulene moiety and the saddle shape of the molecular nanographene allows the formation of complexes with 1:1, 1:2, and 2:1 stoichiometries. The association constants for the three possible supramolecular complexes were determined by H-1 NMR titration. Furthermore, the stability of the three complexes was calculated by theoretical methods that also predict the photoinduced electron transfer from the curved nanographene to the electron acceptor C-60. Time-resolved transient absorption measurements on the ns-time scale showed that the addition of C-60 to NG-1 solutions and photo-exciting them at 460 nm leads to the solvent-dependent formation of new species, in particular the formation of the one-electron reduced form of C-60 in benzonitrile was observed.
CRIS-Team WoS Importer:2022-01-07

Innovative inorganic-organic nanohybrid materials: Coupling quantum dots to carbon nanotubes - Schulz-Drost, Christian; Sgobba, Vito; Gerhards, Christina; Leubner, Susanne; Krick Calderon, Rafael; Ruland Palaia, Andres; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2010)
Inorganic meets organic: Covalent bonds (peptide condensation) and noncovalent interactions (π-π stacking) have been employed en route toward versatile donor-acceptor inorganic- organic nanohybrids, QD-pyrene/SWNT. A charge-transfer event within the hybrid transforms the excitonic state of the quantum dot into a charge-transfer state that has a lifetime of several nanoseconds. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

In situ hydrogenation of C59N and resonant electron capture of C59NHx (x=0, 1 and 5) - Vasil’ev, Yu; Abzalimov, R.; Tuktarov, R.; Nasibullaev, Sh.; Hirsch, Andreas; Taylor, Roger; Drewello, Thomas (Chemical Physics Letters, 2002)
The hydrogenation of the aza[60]fullerene CN· has been studied in situ. The CN· monomer is formed by thermal evaporation and dissociation of the (CN) dimer and is hydrogenated in the heated inlet channel of a mass spectrometer, which is used subsequently for the product analysis. In addition to the expected formation of CNH, the abundant production of CNH is observed. Increasing the availability of hydrogen for the reduction enhances the formation of CNH, which is eventually obtained as the main product. The effective yield curves of the negative ions CNH, where x = 0, 1 and 5 are detailed and contrasted with the ion yields of CH, where x = 0, 2 and 6. It is found that increasing hydrogen attainment reduces the energy range in which long-lived molecular ions can result from electron capture. © 2002 Elsevier Science B.V. All rights reserved.

In Situ Switching of Photoinduced Electron Transfer Direction by Regulating the Redox State in Fullerene-Based Dyads - Liu, Liping (Journal of the American Chemical Society, 2020)

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Integrating metalloporphycenes into p-type NiO-based dye-sensitized solar cells - Feihl, Sebastian; Costa, Ruben D.; Brenner, Wolfgang; Margraf, Johannes; Casillas Pacheco, Ruben; Langmar, Oliver; Browa, Anne; Shubina, Tatyana; Jux, Norbert; Guldi, Dirk Michael; Clark, Timothy (Chemical Communications, 2014)
In the current work, we have explored a novel synthetic route towards metalated porphycenes and their use in p-type NiO-based dye-sensitized solar cells. Particular emphasis is placed on the influence that the relative positioning of the anchoring group exerts on the DSSC performance.

Integrating water-soluble graphene into porphyrin nanohybrids - Malig, Jenny; Nieto, Carlos Romero; Jux, Norbert; Guldi, Dirk Michael (Advanced Materials, 2012)
Exfoliation of graphite by a positively charged pyrene derivative was achieved in water and electronic communication by non-invasive electrostatic interaction with a negatively charged porphyrin was accomplished and proven photospectroscopically. The oppositely charged components were assembled through layer by layer deposition. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Intense Ground-State Charge-Transfer Interactions in Low-Bandgap, Panchromatic Phthalocyanine-Tetracyanobuta-1,3-diene Conjugates - Sekita, Michael; Ballesteros, Beatriz; Diederich, Francois; Guldi, Dirk Michael; Bottari, Giovanni; Torres, Tomas (Angewandte Chemie International Edition, 2016)
A cycloaddition-retroelectrocyclization reaction between tetracyanoethylene and two zinc phthalocyanines (ZnIIPcs) bearing one or four anilino-substituted alkynes has been used to install a strong, electron-accepting tetracyanobuta-1,3-diene (TCBD) between the electron-rich ZnIIPc and aniline moieties. A combination of photophysical, electrochemical, and spectroelectrochemical investigations with the ZnIIPc-TCBD-aniline conjugates, which present panchromatic absorptions in the visible region extending all the way to the near infrared, show that the formal replacement of the triple bond by TCBD has a dramatic effect on their ground- and excited-state features. In particular, the formation of extremely intense, ground-state charge-transfer interactions between ZnIIPc and the electron-accepting TCBD were observed, something unprecedented not only in Pc chemistry but also in TCBD-based porphyrinoid systems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charge transfer; donor-acceptor systems; photophysics; phthalocyanines; tetracyanobutadienes

Intense Photoinduced Intervalence Charge Transfer in High-Valent Iron Mixed Phenolate/Carbene Complexes - Cadranel, Alejandro; Gravogl, Lisa; Munz, Dominik; Meyer, Karsten (Chemistry - A European Journal, 2022)
We report high-valent iron complexes supported by N-heterocyclic carbene (NHC)-anchored, bis-phenolate pincer ligands that undergo ligand-to-metal charge transfer (LMCT) upon photoexcitation. The resulting excited states - with a lifetime in the picosecond range - feature a ligand-based, mixed-valence system and intense intervalence charge transfer bands in the near-infrared region. Upon oxidation of the complex, corresponding intervalence charge transfer absorptions are also observed in the ground state. We suggest that the spectroscopic hallmarks of such LMCT states provide useful tools to decipher excited-state decay mechanisms in high-valent NHC complexes. Our observations further indicate that NHC-anchored, bis-phenolate pincer ligands are not sufficiently strong donors to prevent the population of excited metal-centered states in high-valent iron complexes.
CRIS-Team WoS Importer:2022-06-24
Keywords: iron N-heterocyclic carbene complexes; iron phenolate complexes; LMCT excited state; photoinduced mixed valency; ultrafast spectros

Interfaces of ionic liquids and transition metal surfaces - Adsorption, growth, and thermal reactions of ultrathin [C 1C 1Im] [Tf 2N] films on metallic and oxidised Ni(111) surfaces - Cremer, Till; Wibmer, Leonie; Krick Calderon, Sandra; Deyko, Alexey; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2012)
Ultrathin films of the ionic liquid 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C C Im][Tf N]) were deposited on differently terminated Ni(111) single crystal surfaces. The initial wetting behaviour, the growth characteristics, the molecular arrangement at the interface, and thermal reactivity were investigated using angle-resolved X-ray photoelectron spectroscopy (ARXPS). On clean Ni(111), the initial growth occurs in a layer-by-layer mode. At submonolayer coverages up to at least 0.40 ML, a preferential arrangement of the IL ions in a bilayer structure, with the imidazolium cations in contact with the Ni surface atoms and the anions on top of the cation, is deduced. For higher coverages, a transition to a checkerboard-type arrangement occurs, which is most likely due to repulsive dipole-dipole interactions in the first layer. An overall preference for a checkerboard-type adsorption behaviour, i.e., anions and cations adsorbing next to each other, is found on the oxygen-precovered O(√3×√3)R30°Ni(111) surface. The thermal stability of adsorbed IL layers on Ni(111) and on a fully oxidised Ni(111) surface was studied by heating the layers to elevated temperatures. For clean Ni(111) reversible adsorption takes place. For the oxidised surface, however, only cation-related moieties desorb, starting at ∼450 K, while anion-related signals remain on the surface up to much higher temperatures. © 2012 the Owner Societies.

Interfacial charge transfer in functionalized multi-walled carbon nanotube@TiO2 nanofibres - Saha, Avishek; Moya, Alicia; Kahnt, Axel; Iglesias, Daniel; Marchesan, Silvia; Wannemacher, Reinhold; Prato, Maurizio; Vilatela, Juan J.; Guldi, Dirk Michael (Nanoscale, 2017)
A new insight into photoinduced charge transfer processes across carbon nanotube@TiO2 interfaces has been gained based on experimental details from transient absorption spectroscopy. We show that photoinduced, interfacial hole transfer to carboxylic acid-functionalized multiwalled carbon nanotubes (oxMWCNTs) from TiO2 results in hole-doped oxMWCNTs and reduced TiO2. The latter is inferred from femto- and nanosecond transient absorption spectroscopy performed with oxMWCNT@TiO2 dispersions and complemented with investigations using methyl viologen and N,N,N',N'-tetramethyl-p-phenylenediamine as an electron scavenger and a hole scavenger, respectively. The results of ultraviolet photoemission spectroscopy (UPS) of the compounds corroborate the findings, highlighting the strong coupling between oxMWCNTs and TiO2 in these hybrids.
EAM Import::2019-03-13

Interfacial coordination interactions studied on cobalt octaethylporphyrin and cobalt tetraphenylporphyrin monolayers on Au(111) - Bai, Yun; Sekita, Michael; Schmid, Martin; Bischof, Thomas; Steinrück, Hans-Peter; Gottfried, Michael (Physical Chemistry Chemical Physics, 2010)
Monolayers and multilayers of cobalt octaethylporphyrin (CoOEP), cobalt tetraphenylporphyrin (CoTPP) and the corresponding free-base porphyrins 2HOEP and 2HTPP on an Au(111) surface were investigated with X-ray and UV photoelectron spectroscopy (XPS and UPS). For CoTPP and CoOEP monolayers, the XP spectra show a characteristic splitting of the Co 2p signal, which suggests that only a fraction of the Co ions forms coordinative bonds to the Au(111) surface, while the others interact more weakly. This is a remarkable difference to previous results for CoOEP and CoTPP on Ag(111), where all Co ions in the monolayer were found to interact strongly and uniformly with the silver surface. Presumably, the lateral structural and electronic inhomogeneities of the reconstructed Au(111) surface are responsible for the more complex interaction behaviour on the gold surface. UP spectra of CoOEP and CoTPP monolayers show a new electronic state around 0.3 eV below the Fermi energy (E), i.e., at lower binding energy than in the case of Ag(111), where a strong signal appeared at 0.6 eV below E. In contrast, the free-base porphyrins 2HOEP and 2HTPP show no additional valence states in the monolayer, indicating that the Co ion plays a central role in the electronic interaction between the metal complexes and the substrate. These results have important implications for metal/organic interfaces in organic electronics or photovoltaic devices based on π-conjugated semiconducting metal complexes, because the character of the chemical bond at the interface determines important parameters such as charge injecting rates. © 2010 the Owner Societies.

Interfacial interactions of iron(II) tetrapyrrole complexes on Au(111) - Schmid, Martin; Zirzlmeier, Johannes; Steinrück, Hans-Peter; Gottfried, J. Michael (Journal of Physical Chemistry C, 2011)
The electronic structure of monolayers of iron(II) phthalocyanine (FePc), iron(II) octaethylporphyrin (FeOEP), and iron(II) tetraphenylporphyrin (FeTPP), adsorbed on Au(111), was examined with X-ray and UV photoelectron spectroscopy (XPS/UPS). Comparison of the Fe 2p signals of FePc multilayers and monolayers revealed an additional component in the monolayer signal with a binding energy characteristic of Fe(0). This component accounts for ∼20% of the integral Fe 2p intensity, in agreement with previous observations on cobalt porphyrins on Au(111). The partial modification of the Fe 2p states suggests a laterally inhomogeneous interaction of the adsorbed molecules with the metal surface and is possibly related to the complex, reconstructed Au(111) surface morphology. Similar results obtained for FeTPP and FeOEP monolayers indicate that this effect is independent from the structure of the peripheral substituents on the core porphin moiety. The UP spectra of FePc and FeTPP monolayers show further indications for a substrate-molecule interaction mediated by the central Fe atom. In addition, FePc, FeTPP, and 2HTPP monolayers lead to a complete depopulation of the Shockley surface state of the clean Au(111) surface. © 2011 American Chemical Society.

Interfacing nanocarbons with organic and inorganic semiconductors: From nanocrystals/quantum dots to extended tetrathiafulvalenes - Katsukis, Georgios; Nieto, Carlos Romero; Malig, Jenny; Ehli, Christian; Guldi, Dirk Michael (Langmuir, 2012)
There is no doubt that the outstanding optical and electronic properties that low-dimensional carbon-based nanomaterials exhibit call for their implementation into optoelectronic devices. However, to harvest the enormous potential of these nanocarbons it is essential to probe them in multifunctional electron donor-acceptor systems, placing particular attention on the interactions between electron donors/electron acceptors and nanocarbons. This feature article outlines challenges and recent breakthroughs in the area of interfacing organic and inorganic semiconductors with low-dimensional nanocarbons that range from fullerenes (0D) and carbon nanotubes (1D) to graphene (2D). In the context of organic semiconductors, we focus on aromatic macrocycles and extended tetrathiafulvalenes, and CdTe nanocrystals/quantum dots represent the inorganic semiconductors. Particular emphasis is placed on designing and probing solar energy conversion nanohybrids. © 2012 American Chemical Society.

Interfacing porphyrins and carbon nanotubes through mechanical links - De Juan-Fernandez, Leire; Münich, Peter Wilhelm; Puthiyedath, Arjun; Nieto-Ortega, Belen; Casado, Santiago; Ruiz-Gonzalez, Luisa; Perez, Emilio M.; Guldi, Dirk Michael (Chemical Science, 2018)
We describe the synthesis of rotaxane-type species composed of macrocyclic porphyrin rings mechanically interlocked with SWCNT threads. The formation of mechanically interlocked SWCNTs (MINTs) proceeds with chiral selectivity, and was confirmed by spectroscopic and analytical techniques and adequate control experiments, and corroborated by high-resolution electron microscopy. From a thorough characterization of the MINTs through UV-vis-NIR absorption, fluorescence, Raman, and transient absorption spectroscopy we analyse in detail the electronic interactions of the porphyrins and the SWCNTs in the ground and excited states.
CRIS-Team Scopus Importer:2022-04-14

Interfacing strong electron acceptors with single wall carbon nanotubes - Oelsner, Christian; Schmidt, Cordula; Hauke, Frank; Prato, Maurizio; Hirsch, Andreas; Guldi, Dirk Michael; Hauke, Frank (Journal of the American Chemical Society, 2011)
The complementary use of steady-state and time-resolved spectroscopy in combination with electrochemistry and microscopy are indicative of mutual interactions between semiconducting SWNTs and a water-soluble strong electron acceptor, i.e., perylenediimide. Significant is the stability and the strong electronic coupling of the perylenediimide/SWNT electron donor-acceptor hybrids. Several spectroscopic and spectroelectrochemical techniques, i.e., Raman, absorption, and fluorescence, confirmed that distinct ground- and excited-state interactions occur and that kinetically and spectroscopically well characterized radical ion pair states form within a few picoseconds. © 2011 American Chemical Society.

Interfacing tetrapyridyl-C-60 with porphyrin dimers via -conjugated bridges: artificial photosynthetic systems with ultrafast charge separation - Stangel, Christina; Plass, Fabian; Charisiadis, Asterios; Giannoudis, Emmanouil; Chararalambidis, Georgios; Karikis, Kostas; Rotas, Georgios; Zervaki, Galateia E.; Lathiotakis, Nektarios N.; Tagmatarchis, Nikos; Kahnt, Axel; Coutsolelos, Athanassios G. (Physical Chemistry Chemical Physics, 2018)
We report on the synthesis, characterization and photophysical properties of a donor-bridge-acceptor supramolecular hybrid system, consisting of a tetrapyridyl fullerene derivative (C-60-tpyr) as electron acceptor, with the four pyridyl groups as part of oligophenyleneethynylene/phenylenevinylene bridges, and zinc porphyrin dimers (ZnP)(2) as electron donor species. Based on the metal-to-ligand coordination between the zinc metal centers of (ZnP)(2) and the four pyridyl entities of C-60-tpyr, a strong binding constant (5 x 10(5) M-1) for the formation of C-60-tpyr[(ZnP)(2)](2) was evidenced. Insights into the electronic interactions between the photoactive (ZnP)(2) units and C-60-tpyr emanated from complementary physicochemical assays, which were further supported by theoretical calculations. Notably, the absorption and emission titration assays revealed strong interactions between the electron donor and acceptor species within C-60-tpyr[(ZnP)(2)](2), both in the ground and excited state. Moreover, femtosecond and nanosecond laser photolysis transient absorption measurements were performed and provided solid evidence for intramolecular electron transfer processes derived from the singlet excited state of (ZnP)(2) to C-60-tpyr. Comparison with systems in which either four monomeric zinc porphyrins (ZnP) were complexed with C-60-tpyr or a (ZnP)(2) was coordinated with a dipyridylfullerene revealed the beneficial role of C-60-tpyr in increasing the lifetime of charge-separation.
Created from Fastlane, WoS look-up

Interfullerene Electronic Interactions and Excited-State Dynamics in Fullerene Dumbbell Conjugates - Chai, Yongqiang; Liu, Liping; Xu, Yanjun; Liu, Xiaolong; Wang, Chong; Bo, Yifan; Zhang, Yuhe; Wang, Zhuan; Weng, Yuxiang; Guldi, Dirk Michael; Wu, Bo; Wang, Chunru (Journal of the American Chemical Society, 2023)
Several dumbbell conjugates featuring M3N@Ih-C80 (M = Sc, Y) and C60 were prepared to systematically investigate interfullerene electronic interactions and excited state dynamics. From electrochemical investigations, we concluded that the redox potentials of our M3N@Ih-C80 (M = Sc, Y) dumbbells depend largely on the interfullerene electronic interactions. Assisted by DFT calculation, the unique role of metal atoms was highlighted. Most importantly, ultrafast spectroscopy experiments revealed symmetry-breaking charge separation in Sc3N@C80-dumbbell to yield an unprecedented (Sc3N@C80)•+-(Sc3N@C80)•- charge separated state. This is, to the best of our knowledge, the first time that symmetry-breaking charge separation following photoexcitation is corroborated in a fullerene system. As such, our work shed light on the significance of interfullerene electronic interactions and their uniqueness for modulating excited state properties.
CRIS-Team Scopus Importer:2023-09-29

Intermolecular packing and charge transfer in metallofullerene/porphyrin cocrystals - Bao, Lipiao; Wang, Bingzhe; Yu, Pengyuan; Huang, Chenli; Pan, Changwang; Fang, Hongyun; Akasaka, Takeshi; Guldi, Dirk Michael; Lu, Xing (Chemical Communications, 2019)
Charge transfer in metallofullerene/porphyrin cocrystals is revealed for the first time. Originated from the different solvents for crystallization, distinct stacking manners are presented in the two types of cocrystals. It is demonstrated that intermolecular packing, next to the nature of the corresponding electron donors and acceptors, dominates the charge transfer processes.
CRIS-Team Scopus Importer:2019-06-04

Intermolecular Singlet Fission in Unsymmetrical Derivatives of Pentacene in Solution - Casillas Pacheco, Ruben; Adam, Matthias; Brana Coto, Pedro; Waterloo, Andreas; Zirzlmeier, Johannes; Reddy, Seelam Rajagopala; Hampel, Frank; Mcdonald, Robert; Tykwinski, Rik R.; Thoss, Michael; Guldi, Dirk Michael (Advanced Energy Materials, 2019)
Intermolecular singlet fission (SF) is an electronically coupled process between two chromophores, where distance dependences are decisive in terms of rates and yields. In the current work, a family of pentacene derivatives featuring different functional groups have been designed, synthesized, and probed with respect to intermolecular SF in the low, medium, and high concentration regimes rather than in the solid state. By means of advanced photophysical techniques, global analysis modeling, and ab initio calculations, a model for intermolecular SF is postulated. The model is based on an early key intermediate, which involves the diffusional encounter between one pentacene in its singlet excited-state with another one in its ground state and which features excimer characteristics. This is followed by a transformation into a coupled triplet excited-state. The role of the functional group appended to pentacene is analyzed with respect to steric shielding of the pentacene core as a means to prevent photophysical degradation, as well as control diffusional encounter and, subsequently, SF. The findings demonstrate the potential of new molecular materials for SF, especially in solution studies, as well as the challenges of implementing them in energy conversion schemes due to the appearance of photodegradation processes that compete with SF.
CRIS-Team WoS Importer:2019-02-21

Intramolecular Down- and Up-Conversion in Dimeric Tetracene Complexes Centered via Platinum(II) and Palladium(II) - Bo, Yifan; Hou, Yuxuan; Matabuena, Melchor; Tykwinski, Rik R.; Guldi, Dirk Michael (Advanced Functional Materials, 2025)
Two dimeric tetracene complexes, Pt(Ltc)2Cl2 and Pd(Ltc)2Cl2, have been synthesized by coordination of a pyridyl substituted acene- to a Pt(II) and Pd(II) metal center. The photophysical properties of the two dimers are characterized and compared with the free tetracene ligand Ltc, as well as the corresponding monomeric complexes (Pt(Ltc)(Lref)Cl2 and Pd(Ltc)(Lref)Cl2) to shed light on the processes of intramolecular up- and down-conversion, namely triplet-triplet annihilation and singlet fission, respectively. Both the free ligand Ltc and Pt(Ltc)(Lref)Cl2 show high fluorescence quantum yields, while emission is heavily reduced in the Pt(Ltc)2Cl2 and Pd(II) complexes. Dimer Pt(Ltc)2Cl2 exhibits efficient singlet fission within 1.6 ns to form a correlated triplet pair (T1T1), confirming that coupling is mediated through Pt(II) over remarkably long inter-chromophore distances. Subsequently, (T1T1) dissociates into free triplets (T1 + T1) with yields of ca. 50%. Moreover, due to the isoenergetic level of the singlet excited state and (T1T1) for tetracene dimers, some (T1T1) in Pt(Ltc)2Cl2 is observed to undergo intramolecular up-conversion and return to the singlet excited state, followed by upconverted fluorescence. On the other hand, photoexcitation of Pd(Ltc)2Cl2 gives a kinetic behavior that is similar to the monomer Pd(Ltc)(Lref)Cl2, namely no singlet fission but fast intersystem crossing within hundreds of picoseconds. It is noted that triplet formation in the Pd(II) monomer and dimer complexes is low, and that non-radiative decay of the singlet excitons to the ground state dominates in both cases. The singlet excited state of all metal–organic complexes exhibits subtle intrachromophore charge-transfer characteristics in polar solvents and kinetic schemes that are similar to that observed in apolar solvents.
CRIS-Team Scopus Importer:2025-05-30
Keywords: intramolecular down-conversion; intramolecular singlet fission; intramolecular up-conversion; Pt(II)/Pd(II) metal complex; tetracene dimers

Intramolecular Singlet Fission in Individual Graphene Nanoribbons─Competition with a Charge Transfer - Greißel, Phillip; Beneventi, Giovanni Mariano; Weiß, René; Wollny, Anna-Sophie; Dubey, Rajeev K.; Melle-Franco, Manuel; Clark, Timothy; Mateo-Alonso, Aurelio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Graphene nanoribbons (NRs) constitute a versatile platform for developing novel materials, where their structure governs their optical, electronic, and magnetic properties while also shaping their excited-state dynamics. Here, we investigate a set of three twisted N-doped molecular NRs of increasing length, obtained by linearly fusing perylene diimide to pyrene and pyrazino- or thiadiazolo-quinoxaline residues. By employing various temperature-dependent time-resolved spectroscopy techniques, we reveal how the flexible twisted NR geometry promotes the formation of a mixed electronic state with varying contributions from locally excited and charge-transfer (CT) states. The fate of this mixed state is highly sensitive to the molecular geometry, length, and solvent polarity. For the shortest NR, intersystem crossing dominates the deactivation pathway, efficiently generating triplets in low-polarity solvents. In contrast, for the extended NRs, intramolecular singlet fission (SF) takes place within a single nanoribbon. This is enabled by enhanced superexchange coupling due to a pronounced push-pull nature and the existence of multiple localized π-electron states caused by heteroatom doping, thereby circumventing the need for dimeric interactions typically associated with conventional SF systems. In higher-polarity environments, evidence of a (diabatic) CT state emerges. These findings underscore the intricate relationship between geometry, energy levels, and excited-state dynamics in twisted N-doped NRs.
CRIS-Team Scopus Importer:2025-04-01

Intramolecular Triplet Diffusion Facilitates Triplet Dissociation in a Pentacene Hexamer - Greißel, Phillip; Thiel, Dominik; Gotfredsen, Henrik; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Miskolzie, Mark; Torres, Tomás; Clark, Timothy; Brøndsted Nielsen, Mogens; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
Triplet dynamics in singlet fission depend strongly on the strength of the electronic coupling. Covalent systems in solution offer precise control over such couplings. Nonetheless, efficient free triplet generation remains elusive in most systems, as the intermediate triplet pair 1(T1T1) is prone to triplet-triplet annihilation due to its spatial confinement. In the solid state, entropically driven triplet diffusion assists in the spatial separation of triplets, resulting in higher yields of free triplets. Control over electronic coupling in the solid state is, however, challenging given its sensitivity to molecular packing. We have thus developed a hexameric system (HexPnc) to enable solid-state-like triplet diffusion at the molecular scale. This system is realized by covalently tethering three pentacene dimers to a central subphthalocyanine scaffold. Transient absorption spectroscopy, complemented by theoretical structural optimizations and steady-state spectroscopy, reveals that triplet diffusion is indeed facilitated due to intramolecular cluster formation. The yield of free triplets in HexPnc is increased by a factor of up to 14 compared to the corresponding dimeric reference (DiPnc). Thus, HexPnc establishes crucial design aspects for achieving efficient triplet dissociation in strongly coupled systems by providing avenues for diffusive separation of 1(T1T1), while, concomitantly, retaining strong interchromophore coupling which preserves rapid formation of 1(T1T1).
CRIS-Team Scopus Importer:2024-02-23
Keywords: Oligoacene; Photoenergy Conversion; Singlet Fission; Triplet Dissociation; Ultrafast Spectroscopy

Intramolecular versus intermolecular electronic interactions between [5,6]-open and [6,6]-closed C60 adducts with exTTF - Takano, Yuta; Schubert, Christina; Mizorogi, Naomi; Feng, Lai; Iwano, Azusa; Katayama, Mikimasa; Angeles Herranz, M.; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Chemical Science, 2013)
Intramolecular and intermolecular electronic interactions are important concepts for fabricating fullerene-based nanostructures such as bulk heterojunction (BHJ) solar cells and supramolecular assemblies. To ascertain differences of the molecular interactions depending on the electronic characteristics of the fullerene adducts, we have synthesized and investigated the [5,6]-open and [6,6]-closed adducts of C, which are covalently linked to π-extended tetrathiafulvalene (exTTF) by a flexible σ-bond chain. The two adducts were synthesized by means of cycloaddition reactions and were characterized using spectroscopic methods such as MALDI-TOF mass spectrometry and NMR spectroscopy. Electronic properties of the [5,6]-open and [6,6]-closed adducts were investigated in the ground and excited states using steady-state absorption spectroscopy, cyclic and differential pulse voltammetry (CV and DPV), fluorescence spectroscopy, and femtosecond time-resolved absorption spectroscopy. DFT calculations of the two adducts predict that the flexible bridge between C and exTTF enables a closer proximity than the interlayer distance of graphite (3.35 Å), which dictates considerable π-π interactions. In comparing the [5,6]- and [6,6]-adducts, it is noteworthy to mention that the [6,6]-adduct revealed longer lifetimes of the photochemically formed radical ion pair states than that of the [5,6]-adduct, which is in contrast to results of recent investigations related to the photodynamics of [5,6]- and [6,6]-adducts of C. Titration experiments using references, namely [5,6]- and [6,6]-PCBM, inferred that the [6,6]-adduct gives rise to stronger electronic interactions with exTTF than the [5,6]-adduct. Comprehensive understanding of the different molecular properties, which the [5,6]- and [6,6]-adducts exhibit, provides valuable information regarding the morphology and/or the electronic properties of C-based nanocomposites, such as C-based BHJ solar cells or supramolecular assemblies. © 2013 The Royal Society of Chemistry.

Intrinsic and Extrinsic Incorporation of Indium and Single-Walled Carbon Nanotubes for Improved ZnO-Based DSSCs - Schol, Peter; Zhang, Wen Shan; Scharl, Tobias; Kunzmann, Andreas; Peukert, Wolfgang; Schröder, Rasmus R.; Guldi, Dirk Michael (Advanced Energy Materials, 2022)
A common goal in renewable energy research is the production of semiconductor layers with matching additives to gain desirable effects and advantages. Important examples are adjustment of the band gap, enhancing the conductivity, tailoring roughness of the semiconductor, or reducing the recombination rate of charge carriers. In this work a twofold approach is demonstrated. First, the intrinsic incorporation of indium into zinc oxide tunes the band gap of the semiconductor layer of the DSSCs. Second, single-walled carbon nanotubes (SWCNT) as an extrinsic additive improves the charge transport capabilities. To better combine the SWCNTs with the semiconductor layer a protective ZnO shell is grown on the SWCNTs. A combination of current–voltage, incident photon to current efficiency, and electrochemical impedance spectroscopic assays corroborates the positive effects of both additives on the cell performance. The effective charge-carrier diffusion lengths are enhanced from 0.52 µm for pure ZnO to 5.12 µm for low SWCNT concentrations and 15 mol% of indium. This, as well as the increase in collection efficiency from 30.3% to 62.3% enables enhanced transport in these novel devices. A final device utilizing 0.1 wt% SWCNT@ZnO20nm and In15Zn85O yields a current density of 16.49 mA cm−2 and an efficiency of 4.46%.
CRIS-Team Scopus Importer:2022-03-11
Keywords: indium–zinc oxide photoanodes; n-type DSSCs; semiconductor doping; single-wall carbon nanotubes

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Inversion of donor-acceptor roles in photoinduced intervalence charge transfers - Aramburu-Trošelj, Bruno M.; Oviedo, Paola S.; Ramírez-Wierzbicki, Ivana; Baraldo, Luis M.; Cadranel, Alejandro (Chemical Communications, 2019)
Upon MLCT photoexcitation, (tpy)Ru becomes the electron acceptor in the mixed valence (tpy-)RuIII-δ-NC-MII+δ moiety, reversing its role as the electron donor in the ground-state mixed valence analogue. Photoinduced mixed valence interactions can be tuned to obtain extended lifetimes and higher emission quantum yields, beneficial in supramolecular energy conversion schemes.
CRIS-Team Scopus Importer:2019-07-09

Investigating Electronic Communications in meso–meso Ethene-Bridged Unsymmetrical Diporphyrins - Zieleniewska, Anna; Guldi, Dirk Michael (Chemistry - A European Journal, 2019)
At the focal point of this work is the photophysical characterization of three meso–meso ethene-bridged diporphyrins featuring a diverse metallation pattern. Detailed investigations by means of cyclic voltammetry, absorption, fluorescence, and femto-/nanosecond transient absorption spectroscopy revealed the impact of open-shell nickel(II) on the electronic communication in ethene-bridged heterobimetallic diporphyrins.
CRIS-Team Scopus Importer:2019-07-09
Keywords: diporphyrins; electronic communication; photochemistry; porphyrin dimers; porphyrinoids

Investigation of carrier dynamics of QDs using kinetic model and ultrafast spectroscopy - Jana, Bikash; Ghosh, Srijon; Dutta, Avisek; Baranov, Alexander V.; Fedorov, Anatoly V.; Patra, Amitava (Optical Materials: X, 2022)
The study of carrier dynamics of QDs is extremely important for developing efficient light-harvesting systems. Here, we investigate size-dependent hole transfer from CdSe QDs to 4-aminothiophenol (4-ATPh) ligand using ultrafast spectroscopy. The photoluminescence (PL) quenching is found to be 99% and 77% for 4-ATPh ligand capped 2.9 nm and 4.3 nm QDs, respectively. We propose a stochastic model for analyzing time-resolved fluorescence decay curves of QDs to estimate the average number of ligands around QDs and it is found that the larger number of ligands are attached with smaller QDs. The analysis of TA spectroscopy data reveals that the kinetics of hole transfer from 2.9 nm QDs to ligand is faster than 4.3 nm CdSe QDs, depending on the offset between valence band (VB) of the CdSe QD and the HOMO of 4-ATPh ligands, and the average number of 4-ATPh ligands attached to each CdSe QD. The fundamental study of ligand-induced charge transfer processes in QDs is important for QD-based solar cell applications.
CRIS-Team Scopus Importer:2022-01-07

Investigation of Cycloparaphenylenes (CPPs) and their Noncovalent Ring-in-Ring and Fullerene-in-Ring Complexes by (Matrix-Assisted) Laser Desorption/Ionization and Density Functional Theory - Minameyer, Martin; Xu, Youzhi; Frühwald, Stefan; Görling, Andreas; von Delius, Max; Drewello, Thomas (Chemistry - A European Journal, 2020)
[n]Cycloparaphenylenes ([n]CPPs) with n=5, 8, 10 and 12 and their noncovalent ring-in-ring and [m]fullerene-in-ring complexes with m=60, 70 and 84 have been studied by direct and matrix-assisted laser desorption ionization ((MA)LDI) and density-functional theory (DFT). LDI is introduced as a straightforward approach for the sensitive analysis of CPPs, free from unwanted decomposition and without the need of a matrix. The ring-in-ring system of [[10]CPP⊃[5]CPP]+. was studied in positive-ion MALDI. Fragmentation and DFT indicate that the positive charge is exclusively located on the inner ring, while in [[10]CPP⊃C60]+. it is located solely on the outer nanohoop. Positive-ion MALDI is introduced as a new sensitive method for analysis of CPP⊃fullerene complexes, enabling the detection of novel complexes [[12]CPP⊃C60, 70 and 84]+. and [[10]CPP⊃C84]+.. Selective binding can be observed when mixing one fullerene with two CPPs or vice versa, reflecting ideal size requirements for efficient complex formation. Geometries, binding and fragmentation energies of CPP⊃fullerene complexes from DFT calculations explain the observed fragmentation behavior.
CRIS-Team Scopus Importer:2020-07-10
Keywords: cycloparaphenylene; density functional calculations; fullerene (MA)LDI mass spectrometry; gas-phase chemistry; supramolecular chemistry

Iodine-Pseudohalogen Ionic Liquid-Based Electrolytes for Quasi-Solid-State Dye-Sensitized Solar Cells - Lennert, Annkatrin; Sternberg, Michelle; Meyer, Karsten; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2017)
In the current work, novel symmetrically alkyl-substituted imidazolium-based ionic liquids have been synthesized featuring either iodide (I-) or selenocyanate (SeCN-) as counteranions. Physicochemical assays based on spectroscopy and electrochemistry techniques have been performed to identify the best ionic liquid for application as electrolytes in quasi-solid-state dye-sensitized solar cells (qssDSSC). The latter were mixed with additives such as 4-tert-butylpyridine (4tbpy) and guanidinium thiocyanate (GuSCN) to optimize electrode surface coverage, ionic diffusion, and dye regeneration. In addition, we demonstrate that electrolytes containing a mixture of I2 and (SeCN)2 enhance the open-circuit voltage of the final quasi-solid-state device by up to 70 mV. As such, iodine-pseudohalogen electrolytes reveal in qssDSSCs a good balance between dye regeneration and hole transport and, in turn, enhance the overall solar energy conversion efficiency by 70% with respect to reference qssDSSCs with iodine-based electrolytes. Finally, devices with the iodine-pseudohalogen electrolyte show a 1000 h stable efficiency of 7-8% under outdoor temperature operation conditions and 1 sun illumination.
EAM Import::2019-03-13

Ion formation pathways of crown ether-fullerene conjugates in the gas phase - Kellner, Ina; Nye, Leanne C.; von Gernler, Marc; Li, Jing; Tzirakis, Manolis D.; Orfanopoulos, Michael; Drewello, Thomas (Physical Chemistry Chemical Physics, 2014)
The ion formation of crown ether-[60]fullerene conjugates of the type (crown - H)-C60-H with crown = 12cr4, 15cr5 and 18cr6 has been studied with matrix-assisted laser desorption/ionisation (MALDI) and electrospray ionisation mass spectrometry (ESI MS). In total five different ways of ion formation are presented, including metalation (MALDI, ESI), protonation and oxidation (both in MALDI) in the positive-ion mode and deprotonation (MALDI, ESI) and reduction (MALDI) in the negative-ion mode. In line with thermochemistry, the deprotonation and electron transfer processes involve the C60 moiety as the charge-carrying entity, while protonation and metalation occur at the crown ether. Particular emphasis has been placed on the study of metal cation attachment in MALDI varying the crown ether size in the conjugate and using different alkali metal chlorides in the target preparation. Dissociation reactions of the metalated conjugates are influenced by the interaction strength of the metal cation to the crown ether fullerene conjugate. The data confirm an increase in bond strength with smaller metal cations, supporting the notion of charge density-driven interactions. © the Partner Organisations 2014.
Created from Fastlane, Scopus look-up

Iron cytochrome C nanohybrids - Supramolecular electron transfer to an electron accepting fullerene - Guldi, Dirk Michael; Zilbermann, Israel; Hatzimarinaki, Maria; Hirsch, Andreas (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2006)
For the first time, intracomplex electron transfer reactions were tested in cytochrome c based nanohybrids (i.e., Fe(II)CytC and Fe(III)CytC), to which polyanionic C derivatives were electrostatically associated. Successful radical ion pair formation, namely, oxidized FeCytC and reduced C, was detected when divalent Fe(II)CytC is used. The so formed Fe(III)CytC · C lives for 2.4 ± 0.5 μs. © by Oldenbourg Wissenschaftsverlag.

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Jetzt wird es bunt ... Fotometrische Experimente mit Materialien aus dem Federmäppchen - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2014)

Langmuir-schaefer films for aligned carbon nanotubes functionalized with a conjugate polymer and photoelectrochemical response enhancement - Sgobba, Vito; Giancane, Gabriele; Cannoletta, Donato; Operamolla, Alessandra; Omar, Omar Hassan; Farinola, Gianluca M.; Guldi, Dirk Michael; Valli, Ludovico (ACS Applied Materials and Interfaces, 2014)
Single-walled carbon nanotubes (SWCNTs) were suspended in 1,2-dichloroethane by noncovalent functionalization with a low-band-gap conjugated polymer 1 alternating dialkoxyphenylene-bisthiophene units with benzo[c][2,1,3]thiadiazole monomeric units. The suspended 1/SWCNT blend was transferred onto different solid substrates by the Langmuir-Schaefer deposition method, resulting in films with a high percentage of aligned nanotubes. Photoelectrochemical characterization of 1/SWCNT thin films on indium-tin oxide showed the benefits of SWCNT alignment for photoconversion efficiency. © 2013 American Chemical Society.

Lanthanide(III) Bis(phthalocyaninato)-[60]Fullerene dyads: Synthesis, characterization, and photophysical properties - Ballesteros, Beatriz; De La Torre, Gema; Shearer, Axel; Hausmann, Anita; Angeles Herranz, M.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2010)
A novel series of doubledecker lanthanide(III) bis(phthalocyaninato)-C dyads [Ln(Pc)(Pc')]-C (M = Sm, Eu, Lu; Pc = phthalocyanine) (1a-c) have been synthesized from unsymmetrically functionalized heteroleptic sandwich complexes [Ln(Pc)(Pc')] (Ln = Sm, Eu, Lu) 3a-c and fulleropyrrolidine carboxylic acid 2. The sandwich complexes 3a-c were obtained by means of a stepwise procedure from unsymmetrically substituted free-base phthalocyanine 5, which was first transformed into the monophthalocyaninato intermediate [Ln(acac) (Pc)] and further reacted with 1,2-dicyanobenzene in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). H NMR spectra of the bis(phthalocyaninato) complexes 3a-c and dyads 1a-c were obtained by adding hydrazine hydrate to solutions of the complexes in [D]DMF, a treatment that converts the free radical double-deckers into the protonated species, that is, [Ln(Pc)(Pc')H] and [Ln(Pc)(Pc')H]- C. The electronic absorption spectra of 3a-c and 1a-c in THF exhibit typical transitions of free-radical sandwich complexes. In the case of dyads 1a-c, the spectra display the absorption bands of both constituents, but no evidence of ground-state interactions could be appreciated. When the UV/Vis spectra of 3a-c and 1a-c were recorded in DMF, typical features of the reduced forms were observed. Cyclic voltammetry studies for 3a-c and 1a-c were performed in THF The electrochemical behavior of dyads 1a-c is almost the exact sum of the behavior of the components, namely the double-decker [Ln(Pc) (Pc')] and the C fullerene, thus confirming the lack of groundstate interactions between the electroactive units. Photophysical studies on dyads 1a-c indicate that only after irradiation at 387 nm, which excites both C and [Ln(Pc)(Pc')] components, a photoinduced electron transfer from the [Ln(Pc)(Pc')] to C occurs. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA.

Laser Desorption Mass Spectrometry of End Group-Protected Linear Polyynes: Evidence of Laser-Induced Cross-Linking - Kirschbaum, Rolf; Prenzel, Dominik; Frankenberger, Stephanie; Tykwinski, Rik; Drewello, Thomas (Journal of Physical Chemistry C, 2015)
End group-protected linear polyynes of composition Tr*-(C C)(n)-Tr* (with Tr* representing the super trityl group and n = 2, 4, 6, 8, 10) and tBu-(C C)(6)-tBu (with tBu being the tertiary butyl group) have been studied by laser desorption ionization (LDI) time-of-flight (ToF) mass spectrometry. tBu-terminated polyyne molecules show considerably higher stability during laser activation than Tr*-end-capped polyyne molecules. A key feature is the abundant formation of oligomeric species upon laser activation. Tandem mass spectrometry reveals strong bonding within the oligomers which indicates cross-linking of the former polyynes within the oligomers. The process is more abundantly occurring and less energy demanding than the laser-induced coalescence of C-60. Cross-linking is more efficient with the smaller end group (tBu), and larger oligomers are formed when the chain length of the polyyne increases, both a result of enhanced interaction of the triple bonds in neighboring chains. The presence of the matrix molecules in matrix-assisted (MA)LDI hinders the polyyne interaction, and oligomer formation is markedly reduced.

Laser-induced formation, fragmentation, coalescence, and delayed ionization of the C 59N heterofullerene - Clipston, Nigel; Brown, T.; Vasil’ev, Yu; Barrow, Mark P.; Herzschuh, Rainer; Reuther, Uwe; Hirsch, Andreas; Drewello, Thomas (Journal of Physical Chemistry A, 2000)
The formation of the nitrogen heterofullerene, C N, following the ablation of a variety of fullerene derivatives, all of which possess organic ligands bound to the carbon cage through a nitrogen atom, has been investigated utilizing laser desorption/ionization mass spectrometry. Investigating the formation of cationic and anionic C N , this approach is found to be a new and very efficient way to implement the initially exohedral nitrogen atom into the carbon cage. The laser-induced heterofullerene formation is discussed in terms of the structure and the charge state dependency of the target material. In further experiments, the coalescence reactivity, leading toward the formation of larger clusters has been examined following laser ablation of thin films of the (CsgNJa dimer. Coalescence leads to two major reaction products, consisting of larger C N clusters which retain the nitrogen atom networked into a larger carbon cage and pure C (n = even) carbon clusters. The C N cluster formation is accompanied by abundant metastable transitions caused by the loss of CN and the resulting implications for the coalescence mechanism are discussed. Finally, evidence is presented for the delayed electron emission of C N·. The observation of delayed ionization of heterofullerenes is unprecedented, revealing a similar resistance toward fragmentation as in the case of their all-carbon fullerene analogues. © 2000 American Chemical Society.

Laterally π-Extensed Nitrogen-Doped Molecular Nanographenes – From Anti-Kasha Emission to Ping-Pong Energy Transfer Events - Beneventi, Giovanni Mariano; Schöll, Kilian; Platzer, Benedikt; Krug, Marcel; Mai, Lukas; Negri, Fabrizia; Cadranel, Alejandro; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2024)
Nanographenes, which feature at least one dimension smaller than 100 nm, are drawing interdisciplinary attention. Understanding the interplay between structure and properties is, however, still in its infancy. Molecular nanographenes are much better suited to fill this knowledge gap than graphene quantum dots or nanoribbons. Their bottom-up synthesis allows atomic precision and, thereby, assists in handling structure and connecting it with properties. Herein, the effects of nitrogen-doping and lateral π-extension in molecular nanographenes and in their coordination complexes with ruthenium porphyrins are investigated. The presence of just nitrogen resulted in an increase of the fluorescence quantum yield, without, however, affecting the energy levels. Lateral π-extension of the nanographenes, instead, resulted in a modulation of the excited states energy, which leads to a thermally-activated dual fluorescence with quantum yields as high as 61%. In the corresponding coordination complexes, lateral π-extension resulted in a ping-pong energy transfer cascade, that is, from the nanographene to the metalloporphyrin and back to the nanographene. The results help to directly rationalize properties observed in both graphene quantum dots and nanoribbons. Moreover, they prove that molecular nanographenes are appealing components for solar energy conversion schemes, where the modulation of inter-component energy transfer is of utmost importance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: anti-Kasha emission; coordination complexes; energy transfer; metalloporphyrin; molecular nanographenes

Layer-by-Layer Assemblies of Catechol-Functionalized TiO2 Nanoparticles and Porphyrins through Electrostatic Interactions - Burger, Alexandra; Costa, Ruben Dario; Lobaz, Volodymyr; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
In the current work, we present the successful functionalization and stabilization of P-25 TiO2 nanoparticles by means of N1,N7-bis(3-(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (1). The design of the latter is aimed at nanoparticle functionalization and stabilization with organic building blocks. On one hand, 1 features a catechol anchor to enable its covalent grafting onto the TiO2 surface, and on the other hand, positively charged pyridine groups at its periphery to prevent TiO2 agglomeration through electrostatic repulsion. The success of functionalization and stabilization was corroborated by thermogravimetric analysis, dynamic light-scattering, and zeta potential measurements. As a complement to this, the formation of layer-by-layer assemblies, which are governed by electrostatic interactions, by alternate deposition of functionalized TiO2 nanoparticles and two negatively charged porphyrin derivatives, that is, 5,10,15,20-(phenoxyacetic acid)-porphyrin (2) and 5,10,15,20-(4-(2-ethoxycarbonyl)-4-(2-phenoxyacetamido)heptanedioic acid)-porphyrin (3), is documented. To this end, the layer-by-layer deposition is monitored by UV/Vis spectroscopy, scanning electron microscopy, ellipsometry, and profilometry techniques. The resulting assemblies are utilized for the construction and testing of novel solar cells. From stable and repeatable photocurrents generated during several ön-offc̈ycles of illumination, we derive monochromatic incident photo-to-current conversion efficiencies of around 3 \

Ligand field states dominate excited state decay in trans-[Ru(py)4Cl2] MLCT chromophores - Cotic, Agustina; Ramírez-Wierzbicki, Ivana; Pieslinger, German E.; Aramburu-Trošelj, Bruno M.; Cadranel, Alejandro (Inorganica Chimica Acta, 2021)
In this contribution, the ultrafast excited state dynamics of a family of trans-[Ru(L)4Cl2] metal to ligand charge transfer chromophores, where L = pyridine, 4-tert-butylpyridine, 4-methoxypyridine and 4,4′-bipyridine, are studied using a combination of femtosecond transient absorption spectroscopy and (TD)DFT theoretical methods. Ligand field states were directly observed and found to dominate the excited state decay cascade, leading to ligand photosubstitution. The internal conversion process that feeds ligand field states, indirectly after light absorption, occurs prior to thermal relaxation in <2 ps for L = pyridine, 4-tert-butylpyridine and 4-methoxypyridine, suggesting a downhill process. This is consistent with DFT calculations, that indicate the lowest triplet is a ligand field state. The exception is for L = 4,4′-bpy, where a slower internal conversion of 34 ps points to a thermally relaxed population undergoing an uphill process with a small energy barrier. Matching this notion, DFT yields a metal to ligand charge transfer character for the lowest triplet of this compound.
CRIS-Team Scopus Importer:2021-02-12

Light-Emitting Electrochemical Cells Based on Hybrid Lead Halide Perovskite Nanoparticles - Aygueler, Meltem F.; Weber, Michael; Puscher, Bianka; Medina, Dana D.; Docampo, Pablo; Costa, Ruben Dario (Journal of Physical Chemistry C, 2015)
Methylammonium lead bromide (MAPbBr3) perovskite nanoparticles (NPs) have been recently proposed as a new material for light-emitting diodes, as well as a new paradigm to elucidate the operational mechanism in perovskite solar cells. Here, we have expanded the synthesis concept to fabricate NPs based on formamidinium lead bromide (FAPbBr3). Importantly, we have demonstrated that the photophysical features of this novel material can be easily tuned by exchanging the organic cation, achieving lower radiative bimolecular recombination rate for FAPbBr3 NPs. Additionally, we report for the first time light-emitting electrochemical cells (LECs) based on perovskite NPs by an easily up-scalable spray-coating technique. Stable luminance of 1–2 cd/m2 at low driving currents was achieved for both types of materials. Overall, this work opens a new avenue of research into the field of organic–inorganic metal halide nanoparticles bearing different alkyl ammonium groups and their application in the developing field of thin-film lighting devices.
EAM Import::2019-03-12

Light harvesting enhancement upon incorporating alloy structured CdSeXTe1−X quantum dots in DPP:PC61BM bulk heterojunction solar cells - Soltani, Rezvan; Katbab, Ali Asghar; Schaumberger, Kerstin; Gasparini, Nicola; Brabec, Christoph; Rechberger, Stefanie; Spiecker, Erdmann; Alabau, Antoni Gimeno; Ruland, Andres; Saha, Avishek; Guldi, Dirk Michael; Sgobba, Vito; et al. (Journal of Materials Chemistry C, 2017)
Hybrid solar cells based on the pDPP5T-2 electron donating polymer, [6,6]-phenyl-C-butyric acid methyl ester (PCBM) and cadmium selenide telluride (CdSeTe) quantum dots (QDs) are fabricated and their photovoltaic performance and optoelectronic properties are investigated as a function of QD loading. The power conversion efficiency (PCE) of hybrid solar cells is improved up to 5.11% for the device containing 4 wt% of QDs which is mainly due to the enhancement in short circuit current density (J) resulting from increased light harvesting. A full-fledged study is performed on the microstructure, charge transfer/transport and recombination mechanisms of our ternary hybrid solar cells by employing various advanced techniques. The transmission electron microscopy (TEM) results reveal the non-agglomerated and uniform distribution of the CdSeTe QDs within the pDPP5T-2:PCBM host matrix at low QD concentrations. Transient absorption spectroscopy (TAS) showed a slower charge carrier recombination rate due to the introduction of QDs into the photoactive layer. It can be attributed to the more efficient exciton dissociation in ternary systems. These findings are consistent with the photovoltaic properties of the device.
Keywords: Engineering controlled terms: Absorption spectroscopy; Butyric acid; Cadmium compounds; Cadmium telluride; Charge transfer; Heterojunctions; High resolution transmission electron microscopy; Nanocrystals; Polymer solar cells; Semiconductor quantum dots; Solar power generation; Transmission electron microscopy Bulk heterojunction solar cells; Charge carrier recombination; Light harvesting enhancement; Optoelectronic properties; Photovoltaic performance; Power conversion efficiencies; Recombination mechanisms; Transient absorption spectroscopies Engineering main heading: Solar cells

Light-harvesting porphyrazines to enable intramolecular singlet fission - Medina, Diana Paola; Papadopoulos, Ilias; Lavarda, Giulia; Gotfredsen, Henrik; Rami, Parisa R.; Tykwinski, Rik R.; Rodríguez-Morgade, M. Salomé; Guldi, Dirk Michael; Torres, Tomás (Nanoscale, 2019)
A porphyrazine featuring complementary absorption to a pentacene dimer was chosen to fill the absorption gap of the latter in the range of 450 to 600 nm to realize panchromatic absorption through the visible region out to ca. 700 nm. Of even greater relevance is the quantitative intramolecular Förster resonance energy transfer (i-FRET) to funnel energy to the pentacene moieties, where efficient intramolecular singlet fission (i-SF) converts the singlet excited state into the corresponding triplet excited states. Remarkably, the triplet quantum yield either via direct excitation or via indirect i-FRET is up to 200% ± 20% in polar solvents.
CRIS-Team Scopus Importer:2019-12-10

Light-harvesting with panchromatically absorbing BODIPY-porphyrazine conjugates to power electron transfer in supramolecular donor-acceptor ensembles - Engelhardt, Verena; Kuhri, Susanne; Fleischhauer, Jan; Garcia-Iglesias, Miguel; Gonzalez-Rodriguez, David; Bottari, Giovanni; Torres, Tomas; Guldi, Dirk Michael; Faust, Ruediger (Chemical Science, 2013)

Light triggers molecular shuttling in rotaxanes: control over proximity and charge recombination - Wolf, Maximilian; Ogawa, Ayumu; Bechtold, Mareike; Vonesch, Maxime; Wytko, Jennifer A.; Oohora, Koji; Campidelli, Stephane; Hayashi, Takashi; Guldi, Dirk Michael; Weiss, Jean (Chemical Science, 2019)
We present the synthesis of novel rotaxanes based on mechanically interlocked porphyrins and fullerene and their advanced investigations by means of photophysical measurements. To this end, a fullerene-capped dumbbell-type axle containing a central triazole was threaded through strapped (metallo) porphyrins-either a free-base or a zinc porphyrin. Femtosecond-resolved transient absorption measurements revealed charge-separation between the porphyrin and fullerene upon light excitation. Solvent polarity and solvent coordination effects induced molecular motion of the rotaxanes upon charge separation and enabled, for the first time, subtle control over the charge recombination by enabling and controlling the directionality of shuttling.
CRIS-Team WoS Importer:2019-04-12

Linking photo- and redoxactive phthalocyanines covalently to graphene - Ragoussi, Maria-Eleni; Malig, Jenny; Katsukis, Georgios; Butz, Benjamin; Spiecker, Erdmann; De La Torre, Gema; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2012)
"Green" graphene: For the first time, the covalent attachment of a light-harvesting and electron-donating phthalocyanine to the basal plane of few-layer graphene is reported (see picture). Physicochemical characterizations reveal an ultrafast charge separation from the photoexcited phthalocyanine to few-layer graphene followed by a slower charge recombination. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Loading pentapod deca(organo)[60]fullerenes with electron donors: From photophysics to photoelectrochemical bilayers - Matsuo, Yutaka; Ichiki, Takahiko; Radhakrishnan, Shankara Gayathri; Guldi, Dirk Michael; Nakamura, Eiichi (Journal of the American Chemical Society, 2010)
A pentapod deca(aryl)[60]fullerene, C (C H CO H) (C H Fc) Me (4; Fc = ferrocenyl), bearing five carboxylic acid and five ferrocenyl groups was synthesized through top and bottom functionalization of [60]fullerene by means of copper-mediated penta-addition reactions. For electrochemical measurements (i.e., E = 0.08 V, five-electron oxidation of the ferrocenyl groups; E = -1.89 and -2.28 V for the fullerene part vs Fc/Fc ), we used an ester-protected compound, C (C H CO Et) (C H Fc) Me (2), and 4 was probed by performing femtosecond flash photolysis experiments in a variety of organic solvents. Importantly, the formation of a radical ion pair state was corroborated with lifetimes of up to 333 ps in toluene. In complementary studies, penta(carboxylic acid)-penta(ferrocenyl) compound 4 was deposited on indium-tin oxide (ITO) electrodes with a surface coverage (i.e., 0.14 nmol/cm ) that corresponded to a unique bilayer structure. Decisive for the bilayer motif is the presence of five ferrocenyl groups, which are assembled with a merry-go-round-shaped arrangement on the [60]fullerene. The novel 4/ITO photoelectrode gave rise to a cathodic photocurrent with a 12% quantum yield in the presence of methyl viologen, whereas an anodic photocurrent was generated in the presence of ascorbic acid for a C (C H CO H) (C H ) Me (5)/ITO photoelectrode. Photophysical investigations revealed that the difference in photocurrent, that is, cathodic versus anodic photocurrents, is related to the nature of the excited state feature in 4 (i.e., charge separated state) and 5 (i.e., triplet excited state). The unique molecular architecture of 4, in combination with its remarkable donor-acceptor properties, validates the use of the pentapod deca(aryl)[60]fullerene in photoelectrochemically active molecular devices. © 2010 American Chemical Society.

Long-Lived Charge Carrier Photogeneration in a Cooperative Supramolecular Double-Cable Polymer - Joseph, Jan; Berrocal, José Augusto; Casellas, Nicolás M.; Guldi, Dirk Michael; Torres, Tomás; García-Iglesias, Miguel (Journal of the American Chemical Society, 2024)
A newly designed C3-symmetric disc-shaped chromophore, BTT(NDI)3, features electron accepting naphthalene diimides linked to an electron donor BTT core. BTT(NDI)3 self-assembles in apolar solvents into highly ordered, chiral supramolecular fibers through π-π and 3-fold hydrogen-bonding interactions. This leads to a cooperative formation of plane-to-plane stacking of BTTs and J-aggregation of the outer NDIs. Such a structure ensures high charge mobility. Only photoexcitation of BTT in the BTT(NDI)3 polymers triggers a unidirectional electron transfer from BTT to NDI and results in (BTT•+-NDI•-) lifetimes that are by up to 3 orders of magnitude longer compared to (NDI•+-NDI•-) that is formed upon NDI photoexcitation. A multiphasic decay implies ambipolar pathways for charge carriers, that is, electron and hole delocalization along the respective BTT and NDI stacks. Our supramolecular approach offers potential for developing functional supramolecular polymers with continuous pathways for electrons and holes and, in turn, minimizing charge recombination losses in organic photovoltaic devices.
CRIS-Team Scopus Importer:2024-11-01

Long-Living Holes in Grey Anatase TiO2 Enable Noble-Metal-Free and Sacrificial-Agent-Free Water Splitting - Liu, Ning; Mohajernia, Shiva; Nguyen, Nhat Truong; Hejazi, Seyedsina; Plass, Fabian; Kahnt, Axel; Yokosawa, Tadahiro; Osvet, Andres; Spiecker, Erdmann; Guldi, Dirk Michael; Schmuki, Patrik (Chemsuschem, 2020)
Titanium dioxide has been the benchmark semiconductor in photocatalysis for more than 40 years. Full water splitting, that is, decomposing water into H2 and O2 in stoichiometric amounts and with an acceptable activity, still remains a challenge, even when TiO2-based photocatalysts are used in combination with noble-metal co-catalysts. The bottleneck of anatase-type TiO2 remains the water oxidation, that is, the hole transfer reaction from pristine anatase to the aqueous environment. In this work, we report that “grey” (defect engineered) anatase can provide a drastically enhanced lifetime of photogenerated holes, which, in turn, enables an efficient oxidation reaction of water to peroxide via a two-electron pathway. As a result, a Ni@grey anatase TiO2 catalyst can be constructed with an impressive performance in terms of photocatalytic splitting of neutral water into H2 and a stoichiometric amount of H2O2 without the need of any noble metals or sacrificial agents. The finding of long hole lifetimes in grey anatase opens up a wide spectrum of further photocatalytic applications of this material.
CRIS-Team Scopus Importer:2020-08-21
Keywords: long-living holes; noble-metal-free; sacrificial-agent-free; titanium dioxide; water splitting

Low-Dimensional Carbon Allotropes: Ground- and Excited-State Charge Transfer with NIR-Absorbing Heptamethine Cyanine - Roth, Alexandra Marina; Schierl, Christoph; Ferrer-Ruiz, Andres; Minameyer, Martin; Rodriguez-Perez, Laura; Villegas, Carmen; Angeles Herranz, Ma; Martin, Nazario; Guldi, Dirk Michael (Chem, 2017)
At the focal point of our studies are mutual interactions between an anionic heptamethine cyanine and individualized single-walled carbon nanotubes (SWCNTs) or exfoliated nanographene (NG). Here, we report the distinct near-infrared absorption of the heptamethine cyanine, which assists in visualizing the electronic interactions in the ground state with ease and precision. In statistical Raman assays, we conclude from downshifted 2D- and G-modes for SWCNTs, as well as upshifted 2D- and downshifted G-modes for NG, that these electronic interactions result in stable n-doping of SWCNTs and NG. Key to this shift of charge density is the electron-donating character of the heptamethine cyanine. In the excited state, a complete but metastable transfer of charges is accompanied by a radical-ion-pair state that lives for several nanoseconds. Such a time domain has not yet been realized, for example, in NG to date.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carbon nanotubes; cyanines; electron transfer; graphene; n-doping; NIR-light harvester; organic electronics; Raman spectroscopy; transient absorption spectroscopy

Low dimensional nanocarbons-chemistry and energy/electron transfer reactions - Dirian, Konstantin; Angeles Herranz, M.; Katsukis, Georgios; Malig, Jenny; Rodriguez-Perez, Laura; Romero, Carlos; Strauß, Volker; Martin, Nazario; Guldi, Dirk Michael (Chemical Science, 2013)
This Minireview sheds light onto the electronic communication between, on one hand, low dimensional nanocarbons-single and multiwalled 1D carbon nanotubes and 2D graphene-and, on the other hand, a variety of electroactive species en-route to novel electron donor-acceptor conjugates and hybrids in relation to their covalent and non-covalent chemistry, respectively. A common denominator to any of the highlighted conjugates/hybrids is charge transport across different scales, that is, from individual molecular conjugates/hybrids to morphologically controlled devices. This journal is © 2013 The Royal Society of Chemistry.

Low-spin to low-spin valence tautomeric transition in cobalt bis-dioxolenes - Mörtel, Max; Goodner, Stephen; Oschwald, Johannes; Scheurer, Andreas; Drewello, Thomas; Khusniyarov, Marat (Dalton Transactions, 2024)
Cobalt dioxolenes are a well-known class of switchable coordination compounds showing intramolecular electron transfer, which is always accompanied by a spin state change at the cobalt center. Here, we present the first example of thermally switchable cobalt bis-dioxolenes where intramolecular electron transfer seems to take place, but the spin state change is suppressed. This leads to the detection of thermal transition between a common ls-CoIII(SQ˙−)(Cat2−) and an extremely rare ls-CoII(SQ˙−)2 electronic state (hs - high-spin, ls - low-spin, SQ˙− - benzosemiquinonate(1−) radical and Cat2− - catecholate(2−)). Parallel to the present work, a similar work but on cobalt mono-dioxolenes has just appeared (Chem. Eur. J., 2023, 29, e202300091), suggesting thermal transition between ls-CoIII(Cat2−) and ls-CoII(SQ˙−) electronic states.
CRIS-Team Scopus Importer:2024-02-16

Magnesium Tetra(phenylethynyl)porphyrin: Stepwise Synthetic Route, Crystal Structures, and Longer Singlet Excited-State Lifetime than Zinc Congener - Nakagawa, Takafumi; Wang, Huan; Zieleniewska, Anna; Okada, Hiroshi; Aoyagi, Shinobu; Guldi, Dirk Michael; Matsuo, Yutaka (Chemistry - An Asian Journal, 2018)
Magnesium tetra(arylethynyl)porphyrins (aryl=Ph or 4-CF3C6H4) were synthesized via 5,15-di(triisopropylsilylethynyl)-10,20-di(arylethynyl)porphyrin to ensure good solubility and high synthetic yields. Magnesium tetra(phenylethynyl)porphyrin was subjected to structural analyses and physico-chemical characterization. Single-crystal X-ray analysis revealed porous crystal structures featuring solvent molecules in their pores. From femtosecond transient absorption measurements we concluded that the singlet excited-state lifetime of magnesium tetra(phenylethynyl)porphyrin is with 7.4 ns substantially longer than that of its zinc congener with 2.8 ns; this is attributed to the lower atomic weight of magnesium compared with zinc.
CRIS-Team Scopus Importer:2022-04-14
Keywords: coordination; magnesium; photochemistry; porphyrinoids; X-ray diffraction

Manipulating single-wall carbon nanotubes by chemical doping and charge transfer with perylene dyes - Ehli, Christian; Oelsner, Christian; Guldi, Dirk Michael; Mateo-Alonso, Aurelio; Prato, Maurizio; Schmidt, Cordula; Backes, Claudia; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Nature Chemistry, 2009)
Single-wall carbon nanotubes (SWNTs) are emerging as materials with much potential in several disciplines, in particular in electronics and photovoltaics. The combination of SWNTs with electron donors or acceptors generates active materials, which can produce electrical energy when irradiated. However, SWNTs are very elusive species when characterization of their metastable states is required. This problem mainly arises because of the polydispersive nature of SWNT samples and the inevitable presence of SWNTs in bundles of different sizes. Here, we report the complete and thorough characterization of an SWNT radical ion-pair state induced by complexation with a perylene dye, which combines excellent electron-accepting and-conducting features with a five-fused ring-system. At the same time, the perylene dye enables the dispersion of SWNTs by means of- interactions, which gives individual SWNTs in solution. This work clears a path towards electronic and optoelectronic devices in which regulated electrical transport properties are important. © 2009 Macmillan Publishers Limited. All rights reserved.

Mediating Reductive Charge Shift Reactions in Electron Transport Chains - Wolf, Maximilian; Villegas, Carmen; Trukhina, Olga; Delgado, Juan Luis; Torres, Tomas; Martin, Nazario; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2017)
We report the synthesis of a full-fledged family of covalent electron donor-acceptor(1)-acceptor(2) conjugates and their charge-transfer characterization by means of advanced photophysical assays. By virtue of variable excited state energies and electron donor strengths, either Zn(II)Porphyrins or Zn(II)Phthalocyanines were linked to different electron-transport chains featuring pairs of electron accepting fullerenes, that is, C-60 and C-70. In this way, a fine-tuned redox gradient is established to power a unidirectional, long-range charge transport from the excited-state electron donor via a transient C-60(center dot-) toward C-70(center dot-). This strategy helps minimize energy losses in the reductive, short-range charge shift from C-60 to C-70. At the forefront of our investigations are excited-state dynamics deduced from femtosecond transient absorption spectroscopic measurements and subsequent computational deconvolution of the transient absorption spectra. These provide evidence for cascades of short-range charge-transfer processes, including reductive charge shift reactions between the two electron-accepting fullerenes, and for kinetics that are influenced by the nature and length of the respective spacer. Of key importance is the postulate of a mediating state in the charge-shift reaction at weak electronic couplings. Our results point to an intimate relationship between triplet-triplet energy transfer and charge transfer.

Merging Carbon Nanostructures with Porphyrins - Menon, Arjun; Kaur, Ramandeep; Guldi, Dirk Michael (Springer Nature, 2022)
In this contribution, we highlight the most important work in the field of photon and charge management, focusing on electron donor-acceptor conjugates and/or systems built around porphyrins, on the one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates/systems are managed by the porphyrins, while the 0D, 1D, and 2D nanocarbons serve as the electro-active component, which allow the charges to be managed. Going beyond the highlighted examples with the characterization of photon and charge management, we emphasize photovoltaics and photocatalysis to convert and store energy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Charge management; Nanocarbons; Photon management; Porphyrins; Solar energy conversion

Metallic-like stoichiometric copper sulfide nanocrystals: Phase- and shape-selective synthesis, near-infrared surface plasmon resonance properties, and their modeling - Xie, Yi; Carbone, Luigi; Nobile, Concetta; Grillo, Vincenzo; D'Agostino, Stefania; Della Sala, Fabio; Giannini, Cinzia; Altamura, Davide; Oelsner, Christian; Kryschi, Carola; Cozzoli, P. Davide (Acs Nano, 2013)
In the realm of semiconductor nanomaterials, a crystal lattice heavily doped with cation/anion vacancies or ionized atomic impurities is considered to be a general prerequisite to accommodating excess free carriers that can support localized surface plasmon resonance (LSPR). Here, we demonstrate a surfactant-assisted nonaqueous route to anisotropic copper sulfide nanocrystals, selectively trapped in the covellite phase, which can exhibit intense, size-tunable LSPR at near-infrared wavelengths despite their stoichiometric, undoped structure. Experimental extinction spectra are satisfactorily reproduced by theoretical calculations performed by the discrete dipole approximation method within the framework of the Drude-Sommerfeld model. The LSPR response of the nanocrystals and its geometry dependence are interpreted as arising from the inherent metallic-like character of covellite, allowed by a significant density of lattice-constitutional valence-band free holes. As a consequence of the unique electronic properties of the nanocrystals and of their monodispersity, coherent excitation of symmetric radial breathing modes is observed for the first time in transient absorption experiments at LSPR wavelengths. © 2013 American Chemical Society.

Metal thiolate complexes binding molecular nitrogen under mild conditions: [my-N_2_Ru(P^1^Pr_3_)(N_2_Me_2_S_2_) - Sellmann, Dieter; Hille, Andreas; Heinemann, Frank Wilhelm; Moll, Matthias; Rösler, Annette; Sutter, Jörg; Brehm, Georg; Reiher, Markus; Heß, Bernd Artur; Schneider, Siegfried (Inorganica Chimica Acta)
UnivIS-Import:2017-03-24:Pub.2003.forsch.sonder.sfb583.metalt

Mixed Organic Ligand Shells: Controlling the Nanoparticle Surface Morphology toward Tuning the Optoelectronic Properties - Henkel, Christian; Wittmann, Judith; Träg, Johannes; Will, Johannes; Stiegler, Lisa; Strohriegl, Peter; Hirsch, Andreas; Unruh, Tobias; Zahn, Dirk; Halik, Marcus; Guldi, Dirk Michael (Small, 2020)
Precise control over the ratio of perylene bisimide (PBI) monomers and aggregates, immobilized on alumina nanoparticle (NP) surfaces, is demonstrated. Towards this goal, phosphonic acid functionalized PBI derivatives (PA-PBI) are shown to self-assemble into stoichiometrically mixed monolayers featuring aliphatic, glycolic, or fluorinated phosphonic acid ligands, serving as imbedding matrix (PA-M) to afford core-shell NPs. Different but, nevertheless, defined PBI monomer/aggregate composition is achieved by either the variation in the PA-PBI to PA-M ratios, or the utilization of different PA-Ms. Various steady-state as well as time-resolved spectroscopy techniques are applied to probe the core-shell NPs with respect to changes in their optical properties upon variations in the shell composition. To this end, the ratio between monomer and excimer-like emission assists in deriving information on the self-assembled monolayer composition, local ordering, and corresponding aggregate content. With the help of X-ray reflectivity measurements, accompanied by molecular dynamics simulations, the built-up of the particle shells, in general, and the PBI aggregation behavior, in particular, are explored in depth.
CRIS-Team WoS Importer:2019-12-10

Modification of the growth of iron on Ag(111) by predeposited organic monolayers - Buchner, Florian; Kellner, Ina; Steinrück, Hans-Peter; Marbach, Hubertus (Zeitschrift für Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2009)
We study the modification of the growth behaviour of iron on Ag(l11) by preadsorbed monolayers of 2H-phthalocyanine (2HPc) and 2H-tetraphenylporphyrin (2HTPP) by scanning tunneling microscopy, upon Fe deposition in ultra-high vacuum at room temperature. The growth of iron on clean Ag(111) follows the scheme expected from reports of similar systems: For low coverages (up to-0.3 ML) an almost exclusive agglomeration of iron clusters at step edges occurs, which continue to grow in a dendritic fashion at higher coverages. Upon deposition onto Ag(l11) precovered with monolayers of 2HTPP and 2HPc, at coverages up to 0.037 ML no growth of Fe islands but complete metalation, i.e., incorporation of the Fe atoms in the macrocyle of the preadsorbed molecules is found. For higher amounts of deposited Fe (0.037 < 0 < 0.30 ML), the formation of Fe islands is observed, which occurs differently for 2HPC and 2HTPP. While on 2HTPP two-dimensional islands are formed presumably underneath a FeTPP monolayer, for 2HPc the Fe growth is dominated by the formation of small 3D clusters within a FePc monolayer. At 0 = 2.0 ML, both systems exhibit small three dimensional Fe islands. These results are discussed considering different aspects like the molecular conformation of FeTPP and FePc on Ag(111) and the diffusional properties of Fe on the clean and modified substrate. © by Oldenbourg Wissenschaftsverlag.

Modifying the Semiconductor/Electrolyte Interface in CuO p-Type Dye-Sensitized Solar Cells: Optimization of Iodide/Triiodide-Based Electrolytes - Langmar, Oliver; Ganivet, Carolina R.; Scharl, Tobias; De La Torre, Gema; Torres, Tomas; Costa, Ruben Dario; Guldi, Dirk Michael (ACS Applied Energy Materials, 2018)
Studies related to novel electrolyte concepts for p-type dye-sensitized solar cells (p-DSSCs) set focus on developing alternatives to the iodide/triiodide (I-/I-3(-)) redox couples, while attempts to improve the performance of the latter are scarce. In this study, we report on the first complete optimization of an I-/I-3(-)-based electrolyte for p-DSSCs employing CuO-based photocathodes. Optimization of the electrolyte solvent, the effect of ionic liquids, and the concentration-dependent properties of various electrolyte additives were at the focal point. Electrochemical impedance spectroscopy and intensity-modulated photovoltage and photocurrent spectroscopies complemented basic electrochemical and device characterization, leading to a sound understanding of charge injection, charge recombination, and charge transport. To this end, optimization of the aforementioned parameters enabled 2-fold device efficiencies of 0.156% compared to 0.078% for nonoptimized devices.
CRIS-Team WoS Importer:2019-03-01

Modulating Charge-Transfer Interactions in Topologically Different Porphyrin-C60 Dyads - Guldi, Dirk Michael; Hirsch, Andreas; Scheloske, Michael; Dietel, Elke; Troisi, Alessandro; Zerbetto, Francesco; Prato, Maurizio (Chemistry - A European Journal, 2003)
Control over the interchromophore separation, their angular relationship, and the spatial overlap of their electronic clouds in several ZnP-C dyads (ZnP=zinc porphyrin) is used to modulate the rates of intramolecular electron transfer. For the first time, a detailed analysis of the charge transfer absorption and emission spectra, time-dependent spectroscopic measurements, and molecular dynamics simulations prove quantitatively that the same two moieties can produce widely different electron-transfer regimes. This investigation also shows that the combination of ZnP and C consistently produces charge recombination in the inverted Marcus region, with reorganization energies that are remarkably low, regardless of the solvent polarity. The time constants of electron transfer range from the μs to the ps regime, the electronic couplings from a few tens to several hundreds of cm, and the reorganization energies remain below 0.54 eV and can be as low as 0.16 eV.

Modulating the dynamics of Forster resonance energy transfer and singlet fission by variable molecular spacers - Zirzlmeier, Johannes; Lavarda, Giulia; Gotfredsen, Henrik; Papadopoulos, Ilias; Chen, Lan; Clark, Timothy; Tykwinski, Rik R.; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2020)
In contrast to previous work, the synergy between panchromatic absorption and molecular singlet fission (SF) is exploited to optimize solar energy conversion through evaluation of the distance dependence of intramolecular Forster Resonance Energy Transfer (i-FRET) in a series of subphthalocyanines (SubPcs) linked to pentacene dimers (Pnc(2)s). To provide control over i-FRET, the molecular spacer rather than the energy donating SubPc is tailored in the corresponding SubPc-Pnc(2) conjugates in terms of length (i.e., the number of aryl units) and flexibility (i.e., presence or absence of a CH2 group). AM1-CIS calculations support the experiments, which underline the importance of the molecular spacer to impact not only the i-FRET dynamics, but also the dynamics of intramolecular singlet fission (i-SF). For example, an additional phenyl group slows down both i-FRET and i-SF by a factor of similar to 3.8 and similar to 1.6, respectively, by a quinone-like conjugation pattern that affords a pentacene acceptor orbital that is fairly delocalized over both pentacenes and the bridging phenyl.
CRIS-Team WoS Importer:2020-12-11

Molecular Acenes for Light Capture, Conversion, and Storage - Greißel, Phillip; Wollny, Anna-Sophie; Bo, Yifan; Thiel, Dominik; Weiß, René; Guldi, Dirk Michael (Accounts of Materials Research, 2024)
Conspectus Efficient photovoltaics (PV) require capturing and converting solar energy across a broad range of energy. Losses due to thermalization and sub-bandgap photons place, however, significant boundaries on the performance of solar cells. For conventional single-junction cells, the theoretical maximum power conversion efficiency is capped at 33%, a constraint known as the detailed balance limit. Realizing the full potential of PVs requires developing novel strategies to overcome this fundamental obstacle. This Account describes the photon-management capabilities of acenes and addresses these fundamental losses en-route toward enhancing PV performances. For high-energy photons that exceed the semiconductor’s bandgap energy, singlet fission (SF) is a down-conversion pathway to mitigate thermalization losses. SF is a process in organic materials, in which a singlet excited state is split into two independent triplet excited states, effectively doubling the number of charge carriers. Pentacenes stand out among acenes due to their exergonic nature of SF. Numerous molecular pentacene dimers have been synthesized to elucidate the relationship between structure and enhancing SF efficiency. A broader light-harvesting range of SF materials is realized by covalently attaching complementary absorbing energy donors to set up energy donor-acceptor conjugates. Förster resonance energy transfer (FRET) is operative in these energy donor-acceptor conjugates, effectively extending the absorption of SF materials, as the energy donor efficiently transfers its absorbed excitation energy to the energy acceptor. Our studies on various binding motifs show that FRET efficiency depends not only on parameters like the energy donor-acceptor distance and spectral overlap but also on subtle factors such as the alignment of transition dipoles, which significantly affect the energy transfer dynamics and efficiency. Turning to low-energy photons, triplet-triplet annihilation up-conversion (TTA-UC) provides a means of light up-conversion and, thereby, the reduction of sub-bandgap losses. In TTA-UC, a singlet excited state that is potent enough to generate charge carriers is formed by combining two triplet excitons. It is effectively the reverse process of SF. The higher triplet energy of tetracene and an endergonic SF renders them highly effective for TTA-UC. We focus on various tetracene-based systems that maximize TTA-UC efficiency. Besides TTA-UC, two-photon absorption (TPA) is yet another mechanism to leverage below-bandgap photons. It is a nonlinear optical (NLO) process, and acenes reveal NLO properties that are essential for extending light absorption into the near-infrared and still powering SF. We demonstrate in our proof-of-concept studies how TPA further broadens the application potential of acenes for PV systems. The strategies outlined in this Account illustrate that acenes are valuable for addressing mechanistic losses in conventional solar cells. In the final section, we examine light storage following SF by means of interfacial electron transfer. Efficient charge-injection powered by SF materials still requires more research before being implemented in large-scale PV designs. Overall, the advances discussed in this Account not only highlight the pivotal role of acenes as model systems to investigate photon down- and up-conversion processes but also paint a promising picture that more efficient solar energy conversion schemes exceeding the detailed-balance limit can be realized by implementing these materials.
CRIS-Team Scopus Importer:2025-02-04

Molecular design of strong single-wall carbon nanotube/polyelectrolyte multilayer composites - Mamedov, A. A.; Kotov, N. A.; Prato, Maurizio; Guldi, Dirk Michael; Wicksted, J.; Hirsch, Andreas (Nature Materials, 2002)
The mechanical failure of hybrid materials made from polymers and single-wall carbon nanotubes (SWNT) is primarily attributed to poor matrix-SWNT connectivity and severe phase segregation. Both problems can be successfully mitigated when the SWNT composite is made following the protocol of layer-by-layer assembly. This deposition technique prevents phase segregation of the polymer/SWNT binary system, and after subsequent crosslinking, the nanometre-scale uniform composite with SWNT loading as high as 50 wt% can be obtained. The free-standing SWNT/polyelectrolyte membranes delaminated from the substrate were found to be exceptionally strong with a tensile strength approaching that of hard ceramics. Because of the lightweight nature of SWNT composites, the prepared free-standing membranes can serve as components for a variety of long-lifetime devices.

Molecular insights and concepts to engineer singlet fission energy conversion devices - Casillas, Ruben; Papadopoulos, Ilias; Ullrich, Tobias; Thiel, Dominik; Kunzmann, Andreas; Guldi, Dirk Michael (Energy and Environmental Science, 2020)
In thisReview, we showcase the fundamental processes of intermolecular and intramolecular singlet fission (SF). Furthermore we prioritize the information, which is relevant for the implementation of SF and SF-materials into solar energy conversion devices. We do this, firstly, by referring to the complexity of SF, and discussing key aspects of it; secondly, by mentioning the instrumental efforts, which assisted in unraveling SF in benchmark molecular building blocks such as tetracene, pentacene, and their corresponding dimers/oligomers; thirdly, by presenting a collection of SF-materials, as well as available photophysical and electrochemical data for energy conversion research. Among others, these include perylene-diimides (PDIs), diketopyrrolopyrroles (DPPs), carotenoids, conjugated polymers, and diradicaloids. This Review is rounded off by discussing pioneering contributions of SF in solar energy conversion schemes and highlighting recent developments in the field. Overall, a set of guidelines is given for new directions in SF, that is, the use of new tools to discover new SF-materials (i.e.spectroscopy, computation, machine-learning) and deposition processes (i.e.thin-films, DSSCs, OPVs) to couple SF-materials with the appropriate semiconductors.
CRIS-Team WoS Importer:2020-10-02

Molecular Layer Deposition from Dissolved Precursors - Fichtner, Johannes; Wu, Yanlin; Hitzenberger, Jakob; Drewello, Thomas; Bachmann, Julien (ECS Journal of Solid State Science and Technology, 2017)
We present a procedure for growing thin films of an organic polyamid material based on a cyclic repetition of two consecutive, complementary, self-limiting surface reactions. The molecular compounds that react with the surface are dissolved in an organic solvent. This new method exemplifies how atomic layer deposition (ALD) and molecular layer deposition (MLD) can benefit from being transferred from the gas phase to the liquid phase, given that a broad variety of advantageous reagents are only available in dissolved form. (c) The Author(s) 2017. Published by ECS. All rights reserve

Molecular layer deposition from dissolved precursors - Fichtner, Johannes; Wu, Yanlin; Hitzenberger, Jakob; Drewello, Thomas; Bachmann, Julien (ECS Transactions, 2017)
We present a procedure for growing thin films of an organic polyamid material based on a cyclic repetition of two consecutive, complementary, self-limiting surface reactions. The molecular compounds that react with the surface are dissolved in an organic solvent. This new method exemplifies how atomic layer deposition (ALD) and molecular layer deposition (MLD) can benefit from being transferred from the gas phase to the liquid phase, given that a broad variety of advantageous reagents are only available in dissolved form.
CRIS-Team Scopus Importer:2022-04-14

Molecular satellite dishes: Attaching parabolic and planar arenes to heterofullerenes - Hauke, Frank; Atalick, Stefan; Guldi, Dirk Michael; Mack, James; Scott, Lawrence; Hirsch, Andreas; Hauke, Frank (Chemical Communications, 2004)
The electrophilic attack of CN on arenes such as pyrene, coronene and corannulene leads to the regioselective formation of fullerene conjugates, in which polycyclic aromatics are connected to the spherical heterofullerene by a single σ-bond.

Molecular Valence Tautomeric Metal Complexes for Chemosensing - Mörtel, Max; Oschwald, Johannes; Scheurer, Andreas; Drewello, Thomas; Khusniyarov, Marat (Inorganic Chemistry, 2021)
Switchable valence tautomeric metal complexes have been long suggested for applications as chemosensors. However, no such molecular sensors have been yet reported. Here, we present a concept for sensing and the first prototype molecular sensor based on valence tautomeric cobalt-dioxolenes. A valence tautomeric cobalt-dioxolene complex [ls-CoIII(SQ•)(Cat)(stypy)2] [hs-CoII(SQ•)2(stypy)2] 1 (ls = low spin, hs = high spin, Cat = 3,5-di-tert-butylcatecholate(2-), SQ = one-electron oxidized, benzosemiquinone(1-) form of Cat, stypy = trans-4-styrylpyridine) has been used as a molecular sensor. The lability of axial stypy ligands of 1 in solution allows us to exchange stypy ligands by dimethyl sulfoxide and simple pyridine analytes in a controllable way, which triggers colorimetric and magnetic responses.
CRIS-Team Scopus Importer:2021-09-10

Molecular wires - Guldi, Dirk Michael; Nishihara, Hiroshi; Venkataraman, Latha (Chemical Society Reviews, 2015)
CRIS-Team Scopus Importer:2023-03-07

Molecular wires - impact of π-conjugation and implementation of molecular bottlenecks - Schubert, Christina; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael (Chemical Society Reviews, 2015)
In this review we highlight recent progress in the field of photochemically and thermally induced electron transport through molecular bridges as integrative parts of electron donor-bridge-acceptor conjugates. The major emphasis is hereby on the design and the modular composition of the bridges. To this end, we will demonstrate that control over attenuation factors and reorganization energies, on one hand, as well as electronic and electron-vibration couplings, on the other hand, enables tuning electron transport over distances as short as 3.5 Å and as large as 50 Å by up to nine orders of magnitude. In terms of electron transport, the maximum extreme is given by carbon-bridged oligo-p-phenylenevinylenes of different lengths, while a zinc tetraphenylporphyrin free base tetraphenylporphyrin dyad constitutes the minimum extreme.
EAM Import::2019-03-12

Monitoring biological membrane-potential changes: A CI QM/MM study - Rusu, Catalin Florin; Lanig, Harald; Othersen, Olaf; Kryschi, Carola; Clark, Timothy (Journal of Physical Chemistry B, 2008)
In recent decades, new less-invasive, nonlinear optical methods have been proposed and optimized for monitoring fast physiological processes in biological cells. One of these methods allows the action potential (AP) in cardiomyocytes or neurons to be monitored by means of second-harmonic generation (SHG). We now present the first, to our knowledge, simulations of the dependency of the intensity of the second harmonic (/SHG) on variations of the transmembrane potential (TMP) in a cardiomyocyte during an action potential (AP). For this, an amphiphilic potential-sensitive styryl dye molecule with nonlinear optical properties was embedded in a dipalmitoylphosphatidylcholine (DPPC) bilayer, replacing one of the phospholipid molecules. External electrical fields with different strengths were applied across the membrane to simulate the AP of a heart-muscle cell. We used a combined classical/quantum mechanical approach to model the structure and the spectroscopic properties of the embedded chromophore. Two 10 ns molecular dynamics (MD) simulations provided input geometries for semiempirical molecular orbital (QM/MM) single-point configuration interaction (CI) calculations, which were used to calculate the wavelengths and oscillator strengths of electronic transitions in the di-8-ANEPPS dye molecule. The results were then used in a sum-over-states treatment to calculate the second-order hyperpolarizability. The square of the hyperpolarizability scales with the intensity of the second harmonic, which is used to monitor the action potentials of cardiomyocytes experimentally. Thus, we computed changes in the intensity of the second harmonic (ΔI ) as function of TMP changes. Our results agree well with experimental measurements. © 2008 American Chemical Society.

Mono- and bis(pyrrolo)tetrathiafulvalene derivatives tethered to C 60: Synthesis, photophysical studies, and self-assembled monolayers - Solano, Marta Vico; Della Pia, Eduardo Antonio; Jevric, Martyn; Schubert, Christina; Wang, Xintai; Van Der Pol, Cornelia; Kadziola, Anders; Norgaard, Kasper; Guldi, Dirk Michael; Nielsen, Mogens Brondsted; Jeppesen, Jan O. (Chemistry - A European Journal, 2014)
A series of mono- (MPTTF) and bis(pyrrolo)tetrathiafulvalene (BPTTF) derivatives tethered to one or two C60 moieties was synthesized and characterized. The synthetic strategy for these dumbbell-shaped compounds was based on a 1,3-dipolar cycloaddition reaction between aldehyde-functionalized MPTTF/BPTTF derivatives, two different tailor-made amino acids, and C 60. Electronic communication between the MPTTF/BPTTF units and the C60 moieties was studied by a variety of techniques including cyclic voltammetry and absorption spectroscopy. These solution-based studies indicated no observable electronic communication between the MPTTF/BPTTF units and the C60 moieties. In addition, femtosecond and nanosecond transient absorption spectroscopy revealed, rather surprisingly, that no charge transfer from the MPTTF/BPTTF units to the C60 moieties takes place on excitation of the fullerene moiety. Finally, it was shown that the MPTTF-C 60 and C60-BPTTF-C60 dyad and triad molecules formed self-assembled monolayers on a Au(111) surface by anchoring to C 60. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cycloaddition; donor-acceptor systems; fullerenes; monolayers; tetrathiafulvalenes

Mono- And Tripodal Porphyrins: Investigation on the Influence of the Number of Pyrene Anchors in Carbon Nanotube and Graphene Hybrids - Garrido, Marina; Volland, Michel; Münich, Peter Wilhelm; Rodríguez-Pérez, Laura; Calbo, Joaquín; Ortí, Enrique; Herranz, M. ángeles; Martín, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
A series of molecular precursors, containing one (1 and 3) or three (2 and 4) pyrene anchors, covalently linked to porphyrins (free base or Zn), were prepared and characterized. All of them enable their π-πstacking onto low-dimensional nanocarbons including single-walled carbon nanotubes (SWCNTs) and nanographene (NG), their individualization, and their characterization. Microscopic (TEM, AFM) and spectroscopic (steady-state UV-vis and fluorescence, spectroelectrochemistry, and transient absorption measurements) techniques were at the forefront of the characterizations and were complemented by Raman spectroscopy and theoretical calculations. Of great importance is the Raman analysis, which corroborated n-doping of the nanocarbons due to the interactions with 1-4 when probed in the solid state. In solution, the situation is, however, quite different. Efficient charge separation was only observed for the graphene-based system NG/3.
CRIS-Team Scopus Importer:2020-02-04

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Multicomponent redox gradients on photoactive electrode surfaces - Guldi, Dirk Michael; Zilbermann, Israel; Anderson, Greg; Lin, Andrew; Balbinot, Domenico; Jux, Norbert; Hatzimarinaki, Maria; Hirsch, Andreas; Prato, Maurizio (Chemical Communications, 2004)
Redox gradients have been used to tailor the arrangement of photoactive ITO-electrodes at the molecular level.

Multifunctional and Tunable Surfaces Based on Pyrene Functionalized Nanoparticles - Wittmann, Judith; Stiegler, Lisa; Henkel, Christian; Träg, Johannes; Götz, Klaus; Unruh, Tobias; Zahn, Dirk; Hirsch, Andreas; Guldi, Dirk Michael; Halik, Marcus (Advanced Materials Interfaces, 2019)
The tuning of the optical properties of pyrene, immobilized on alumina nanoparticle surfaces, is demonstrated. To this end, phosphonic acid functionalized pyrene derivatives are shown to self‐assemble into stoichiometrically mixed monolayers featuring hydrophilic, hydrophobic, or fluorophilic phosphonic acid ligands and to form defined core–shell hybrids depending on the molecular mixing ratio and the nature of the ligand monomer, excimer, or mutual emission of both evolved. The spectroscopic observations are explained by the respective mobility of the dye molecules with respect to their fixed, specific anchor points and the resulting probability to form excimers and are supported by molecular dynamic simulations, X‐ray reflectivity measurements, and temperature‐dependent steady‐state fluorescence assays. In terms of an additional tuning of the emission color change and/or the on‐off switching of the fluorescence, the formation of core–shell–shell system is carried out by applying amphiphiles. The general concept is fully transferable to demobilized films of nanoparticles, thereby enabling a switchable solid‐state surfac

Multilayer assembly for solar energy conversion - Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael (Fullerenes and Other Carbon-Rich Nanostructures, 2014)
Organizing molecular thin films of electro- and photoactive building blocks provides a versatile platform to the nanoscale control of assembled multilayers and paves the way for the design of functional electronic devices and/or efficient photoenergy conversion devices. Assembly methods, including the Langmuir–Blodgett and the layer-by-layer technique, offer elegant means to realize well-ordered multifunctional thin films on variable surfaces. In this chapter, the fundamental factors and driving forces that govern the adsorption processes of multilayered assemblies are highlighted and numerous intriguing contributions to the field of template-assisted assemblies are presented. Owing to the applicability of these concepts to carbon-based materials – fullerenes and carbon nanotubes – particular attention is paid to the integration of these exceptionally materials combined with light absorbing constituents into nanostructured thin films en route towards versatile electron donor–acceptor nanohybrids for photoconversion schemes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Carbon nanotubes; Fullerenes; Langmuir Blodgett; Langmuir Schaefer; Layer by layer; Self assembly; Solar cells

Multiresponsive polymer nanoparticles based on disulfide bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules, 2021)
A disulfide polymer that is triggerable by ultrasound, UV, and redox in aqueous solution and can self-assemble with ionic probe molecules into again multitriggerable assemblies is presented. It is created by oxidative coupling of a branched insoluble thiol to water-soluble ionic thiols. The synthesis via a nanoprecipitation technique results in charged macromolecule particles with adjustable sizes between a few tens and a few hundred nanometers stable in aqueous solution. Macromolecules of different compositions form with pentaerythritol tetrakis(3-mercaptopropionate) as insoluble cross-linkers yielding the polymer backbone, while mercaptopropionic acid, mercaptosuccinic acid, or aminoethane thiol in varying amounts is coupled to the backbone. Molecular and nanoscale switchability of the disulfide macromolecule with UV light, redox potential, and ultrasound is demonstrated. The anionic character of the polymer particles is exploited by electrostatic self-assembly with the tetra-cationic 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphyrin and its zinc-metalated derivative, yielding supramolecular composite structures as a model system for delivery. The new type of polymer particles in aqueous solution may pave an alternative way toward multiresponsive and functional materials with potential in medicine and material science.
CRIS-Team Scopus Importer:2021-04-09

Multistep energy and electron transfer processes in novel rotaxane donor-acceptor hybrids generating microsecond-lived charge separated states - Kirner, Sabrina; Henkel, Christian; Guldi, Dirk Michael; Megiatto, Jackson D.; Schuster, David I. (Chemical Science, 2015)
A new set of [Cu(phen)2]+ based rotaxanes, featuring [60]-fullerene as an electron acceptor and a variety of electron donating moieties, namely zinc porphyrin (ZnP), zinc phthalocyanine (ZnPc) and ferrocene (Fc), has been synthesized and fully characterized with respect to electrochemical and photophysical properties. The assembly of the rotaxanes has been achieved using a slight variation of our previously reported synthetic strategy that combines the Cu(i)-catalyzed azide-alkyne cycloaddition reaction (the "click" or CuAAC reaction) with Sauvage's metal-template protocol. To underline our results, complementary model rotaxanes and catenanes have been prepared using the same strategy and their electrochemistry and photo-induced processes have been investigated. Insights into excited state interactions have been afforded from steady state and time resolved emission spectroscopy as well as transient absorption spectroscopy. It has been found that photo-excitation of the present rotaxanes triggers a cascade of multi-step energy and electron transfer events that ultimately leads to remarkably long-lived charge separated states featuring one-electron reduced C60 radical anion (C60-) and either one-electron oxidized porphyrin (ZnP+) or one-electron oxidized ferrocene (Fc+) with lifetimes up to 61 microseconds. In addition, shorter-lived charge separated states involving one-electron oxidized copper complexes ([Cu(phen)2]2+ (τ < 100 ns)), one-electron oxidized zinc phthalocyanine (ZnPc+; τ = 380-560 ns), or ZnP+ (τ = 2.3-8.4 μs), and C60- have been identified as intermediates during the sequence. Detailed energy diagrams illustrate the sequence and rate constants of the photophysical events occurring with the mechanically-linked chromophores. This work pioneers the exploration of mechanically-linked systems as platforms to position three distinct chromophores, which are able to absorb light over a very wide range of the visible region, triggering a cascade of short-range energy and electron transfer processes to afford long-lived charge separated states.
CRIS-Team Scopus Importer:2023-03-07

Nanobiosensing with graphene and carbon quantum dots: Recent advances - Walther, Brandon K.; Dinu, Cerasela Zoica; Guldi, Dirk Michael; Sergeyev, Vladimir G.; Creager, Stephen E.; Cooke, John P.; Guiseppi-Elie, Anthony (Materials Today, 2020)
Graphene and carbon quantum dots (GQDs and CQDs) are relatively new nanomaterials that have demonstrated impact in multiple different fields thanks to their unique quantum properties and excellent biocompatibility. Biosensing, analyte detection and monitoring wherein a key feature is coupled molecular recognition and signal transduction, is one such field that is being greatly advanced by the use of GQDs and CQDs. In this review, recent progress on the development of biotransducers and biosensors enabled by the creative use of GQDs and CQDs is reviewed, with special emphasis on how these materials specifically interface with biomolecules to improve overall analyte detection. This review also introduces nano-enabled biotransducers and different biosensing configurations and strategies, as well as highlights key properties of GQDs and CQDs that are pertinent to functional biotransducer design. Following relevant introductory material, the literature is surveyed with emphasis on work performed over the last 5 years. General comments and suggestions to advance the direction and potential of the field are included throughout the review. The strategic purpose is to inspire and guide future investigations into biosensor design for quality and safety, as well as serve as a primer for developing GQD- and CQD-based biosensors.
CRIS-Team Scopus Importer:2020-05-22

Nanocarbon hybrids: The paradigm of nanoscale self-ordering/self-assembling by means of charge transfer/doping interactions - Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Journal of Physical Chemistry Letters, 2013)
The scope of this Perspective is to highlight the potential of nanoscale self-ordering/self-assembling nanocarbons - fullerenes, single-wall carbon nanotubes, and graphene - en route toward novel charge transfer hybrids that unify several functions such as light harvesting, charge separation, and, eventually, catalysis. All of the given examples are fully characterized by a broad range of spectroscopic as well as microscopic techniques and, as such, document the success in tuning the electronic structure of functional nanocarbons by means of charge transfer/doping interactions. © 2013 American Chemical Society.

Nanographene favors electronic interactions with an electron acceptor rather than an electron donor in a planar fused push-pull conjugate - Volland, Michel; Zhou, Ping; Wibmer, Leonie; Haener, Robert; Decurtins, Silvio; Liu, Shi-Xia; Guldi, Dirk Michael (Nanoscale, 2019)
A combination of a preexfoliated nanographene (NG) dispersion and fused electron donor-acceptor tetrathiafulvalene-perylenediimide (TTF-PDI) results in a noncovalent functionalization of NG. Such novel types of nanohybrids were characterized by complementary spectroscopic and microscopic techniques. The design strategy of the chromophoric and electroactive molecular conjugate renders a large and planar -extended system with a distinct localization of electron-rich and electron-poor parts at either end of the molecular conjugate. Within the in situ formed nanohybrid, the conjugate was found to couple electronically with NG preferentially through the electron accepting PDI rather than the electron donating TTF and to form the one-electron reduced form of PDI, which corresponds to p-doping of graphene.
CRIS-Team WoS Importer:2019-03-15

Nanohoops Favour Light-Induced Energy Transfer over Charge Separation in Porphyrin/[10]CPP/Fullerene Rotaxanes - Schwer, Fabian; Zank, Simon; Freiberger, Markus; Steudel, Fabian M.; Geue, Niklas; Ye, Lei; Barran, Perdita E.; Drewello, Thomas; Guldi, Dirk Michael; von Delius, Max (Angewandte Chemie International Edition, 2025)
[2]Rotaxanes offer unique opportunities for studying and modulating charge separation and energy transfer, because the mechanical bond allows the robust, yet spatially dynamic tethering of photoactive groups. In this work, we synthesized [2]rotaxane triads comprising a central (aza)[10]CPP⊃C60 bis-adduct complex and two zinc porphyrin stoppers to address how the movable nanohoop affects light-induced charge separation and energy transfer between the rotaxane subcomponents. We found that neither the parent nanohoop [10]CPP nor its electron-deficient analogue aza[10]CPP actively participate in charge separation. In contrast, the nanohoops completely prevented through-space charge separation. This result is likely due to supramolecular “shielding”, because charge separation was observed in the thread that acted as reference dyad. On the other hand, the suppression of electron transfer allowed the observation of energy transfer from the porphyrin triplet to the fullerene triplet state with a lifetime of ca. 25 μs. The presence of the interlocked nanohoops therefore leads to a dramatic switch between charge separation and energy transfer. We suggest that our results explain observations made by others in photovoltaic devices comprising nanohoops and may pave the way toward strategic uses of mechanically interlocked architectures in devices that feature (triplet) energy transfer.
CRIS-Team Scopus Importer:2025-01-31
Keywords: charge separation; energy transfer; nanohoops; rotaxanes; Supramolecular chemistry

Naphthalenebisimides as photofunctional surfactants for SWCNTs - towards water-soluble electron donor-acceptor hybrids - Dirian, Konstantin; Backes, Susanne; Backes, Claudia; Strauß, Volker; Rodler, Fabian; Hauke, Frank; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Science, 2015)
A water soluble naphthalenebisimide derivative (NBI) was synthesized and probed to individualize, suspend, and stabilize single wall carbon nanotubes (SWCNTs). Besides a comprehensive photophysical and electrochemical characterization of NBI, stable suspensions of SWCNTs were realized in buffered D2O. Overall, the dispersion efficiency of the NBI surfactant was determined by comparison with naphthalene based references. Successful individualization of SWCNTs was corroborated in several microscopic assays. In addition, emission spectroscopy points to the strong quenching of SWCNT centered band gap emission, when NBIs are immobilized onto SWCNTs. The origin of the quenching was found to be strong electronic communication, which leads to charge separation between NBIs and photoexcited SWCNTs, and, which yields reduced NBIs as well oxidized SWCNTs. Notably, electrochemical considerations revealed that the energy content of these charge separated states is one of the highest reported for SWCNT based electron donor-acceptor hybrids so far.

Natural and synthetic nanovectors for cancer therapy - Eftekhari, Aziz; Kryschi, Carola; Pamies, David; Gulec, Sukru; Ahmadian, Elham; Janas, Dawid; Davaran, Soodabeh; Khalilov, Rovshan (Nanotheranostics, 2023)
Nanomaterials have been extensively studied in cancer therapy as vectors that may improve drug delivery. Such vectors not only bring numerous advantages such as stability, biocompatibility, and cellular uptake but have also been shown to overcome some cancer-related resistances. Nanocarrier can deliver the drug more precisely to the specific organ while improving its pharmacokinetics, thereby avoiding secondary adverse effects on the not target tissue. Between these nanovectors, diverse material types can be discerned, such as liposomes, dendrimers, carbon nanostructures, nanoparticles, nanowires, etc., each of which offers different opportunities for cancer therapy. In this review, a broad spectrum of nanovectors is analyzed for application in multimodal cancer therapy and diagnostics in terms of mode of action and pharmacokinetics. Advantages and inconveniences of promising nanovectors, including gold nanostructures, SPIONs, semiconducting quantum dots, various nanostructures, phospholipid-based liposomes, dendrimers, polymeric micelles, extracellular and exome vesicles are summarized. The article is concluded with a future outlook on this promising field.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cancer; drug delivery; nanomaterials; Nanoparticles; nanovectors

Negative molecular ions of azafullerenes and their hydrogenated derivatives - Vasil’ev, Yu; Abzalimov, R.; Nasibullaev, Sh.; Tuktarov, R.; Hauke, Frank; Reuther, Uwe; Hirsch, Andreas; Drewello, Thomas (Physics of the Solid State, 2002)
The formation and decay of negative molecular ions of azafullerenes and their hydrogenated derivatives are investigated by mass spectrometry. The mechanisms of resonant electron capture and the lifetimes of negative molecular ions with respect to the electron autodetachment in azafullerene molecules are discussed, A comparative analysis of the data obtained for azafullerenes and hydrogenated fullerene derivatives is carried out. © 2002 MAIK "Nauka/Interperiodica".

New Insights into Ring-In-Ring Complexes of [n]Cycloparaphenylenes including the [12]Carbon Nanobelt - Freiberger, Markus; Frühwald, Stefan; Minameyer, Martin; Görling, Andreas; Drewello, Thomas (Journal of Physical Chemistry A, 2023)
The supramolecular chemistry of cycloparaphenylenes (CPPs) is characterized by the ability of the ring system to undergo both concave and convex π-π interactions. As a consequence, ring-in-ring complexes can be formed in which the CPP serves as the host as well as the guest molecule ([n + x]CPP⊃[n]CPP). In this work, host-guest ring-in-ring complexes of [n]CPPs (n = 5-12) are investigated by means of electrospray ionization-tandem mass spectrometry (ESI-MS2) and laser desorption ionization mass spectrometry (LDI-MS). Extending the experimentally known complexes with ring size differences of five and six phenyl units (x = 5 and 6), we observe complexes with ring size differences of three up to seven phenyl units (x = 3-7). Energy-resolved collision experiments reveal that the charge is mainly located at the inner ring and complexes with phenyl unit differences of five and six are the most stable. In complexes featuring the same size difference, the complex stabilities slightly increase with an increasing size of the involved [n]CPPs. Utilizing the π-extended [12]carbon nanobelt ([12]CNB) as the guest also revealed an increase in complex stability. This study paves the way for a deeper understanding of the host-guest chemistry of CPPs.
CRIS-Team Scopus Importer:2023-12-08

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12

Nickel oxide nanostructured electrodes towards perylenediimide-based dye-sensitized solar cells - Feihl, Sebastian; Costa Riquelme, Rubén Dario; Pflock, Stephan; Schmidt, Cordula; Schönamsgruber, Jörg; Backes, Susanne; Hirsch, Andreas; Guldi, Dirk Michael (RSC Advances, 2012)
In this work, we have realized nickel oxide (NiO) electrodes that serve as photocathodes in p-type dye-sensitized solar cells (p-DSSCs) sensitized by dendronized perylenediimides (PDIs). To this end, two different approaches in terms of preparing NiO nanoparticle pastes were pursued to fabricate mesoporous electrodes on conductive fluorine doped tin oxide (FTO) glass substrates. Firstly, commercially available NiO nanoparticles were dispersed in a mixture of ethanol and terpineol. Here, in order to obtain a mesoporous network two types of ethylcelluloses (EC), that is, EC 5-15 and 30-50 mPa s, were added in 1:1 weight ratios. Following the evaporation of ethanol, the resulting pastes were spread on FTOs by doctor blading and calcinated at different temperatures. Importantly, the calcination temperature evolved as a crucial aspect in developing efficient electrodes. Nevertheless, the visual appearance of these NiO electrodes prompts a fairly heterogeneous coverage. To circumvent the aforementioned problem, a second approach en route to homogenous electrodes was investigated. In that particular case, commercial NiO nanoparticles were mixed with a mixture of EC 5-15 and 30-50 mPa s at a 1:1 weight ratio, with triacetin as a plasticizer in ethanol. In doing so, pastes containing 7 wt% EC, 3 wt% triacetin, and 3 to 20 wt% NiO nanoparticles were prepared. Most importantly, scanning electron microscopy (SEM) images corroborated the fact that the resulting electrodes revealed a dense coverage on FTOs. In addition, further characterizations ranging from UV/Vis transmission spectroscopy and conductivity measurements to Barrett-Joyner-Halenda (BJH) pore size and volume analysis were carried out. In the final step, the applicability of the new NiO photoelectrodes for p-DSSCs was successfully demonstrated by utilizing two types of PDIs, namely a symmetric 1 and a non-symmetric dendronized 2. Key aspects such as time dependence of dye uptake, hole lifetime and resistance features of the electrodes under operation conditions were investigated. © 2012 The Royal Society of Chemistry.

NOBF4-Functionalized Au-Fe3O4 Nanoheterodimers for Radiation Therapy: Synergy Effect Due to Simultaneous Reactive Oxygen and Nitrogen Species Formation - Klein, Stefanie; Harreiß, Christina; Menter, Christina; Hümmer, Julian; Distel, Luitpold; Meyer, Karsten; Hock, Rainer; Kryschi, Carola (ACS Applied Materials and Interfaces, 2018)
Snowman-shaped Au-Fe3O4 nanoheterodimers were synthesized by thermal decomposition of iron oleate on presynthesized Au nanoparticles. Subsequently performed ligand exchange with nitrosyl tetrafluoroborate provided water solubility and enabled X-ray-induced NO release. These Au-Fe3O4 nanoheterodimers combine high-Z material with catalytically active Fe3O4 surfaces and, moreover, plasmonic properties with superparamagnetic performance. We could establish synergetic interactions between X-radiation and both the Au and Fe3O4 surfaces, which resulted in the simultaneous production of the nitric oxide radical at the Fe3O4 surface and the superoxide radical at the Au surface. The surface-confined reaction between these radicals generated peroxynitrite. This highly reactive species may cause nitration of mitochondrial proteins and lipid peroxidation and induce DNA strand breaks. Therefore, high concentrations of peroxynitrite are expected to give rise to severe cellular energetic derangements and thereupon entail rapid cell death. As providing a common platform for X-ray-induced formation of the highly superoxide, and peroxynitrite, nitrosyl tetrafluoroborate functionalized Au-Fe3O4 nanosnowmen were shown to exhibit excellent performance as X-ray-enhancing agents in radiation therapy.
Keywords: Au-Fe3O4 nanoheterodimers; nitrosyl tetrafluoroborate coating; radiation therapy; reactive oxygen species; reactive nitrogen species

Noble-Metal-Free Photocatalytic Hydrogen Evolution Activity: The Impact of Ball Milling Anatase Nanopowders with TiH2 - Zhou, Xuemei; Liu, Ning; Schmidt, Jochen; Kahnt, Axel; Osvet, Andres; Romeis, Stefan; Zolnhofer, Eva; Marthala, Venkata; Guldi, Dirk Michael; Peukert, Wolfgang; Hartmann, Martin; Meyer, Karsten; et al. (Advanced Materials, 2016)
Ball milling TiO2 anatase together with TiH2 can create an effective photocatalyst. The process changes the lattice and electronic structure of anatase. Lattice deformation created by mechanical impact combined with hydride incorporation yield electronic gap-states close to the conduction band of anatase. These provide longer lifetimes of photogenerated charge carriers and lead to an intrinsic cocatalytic activation of anatase for H2 evolution.
Keywords: Anatase; Ball milling; Hydrogen evolution; Photocatalysis; Titanium hydride

Noncovalent functionalization of thiopyridyl porphyrins with ruthenium phthalocyanines - Lourenco, Leandro M. O.; Hausmann, Anita; Schubert, Christina; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael; Tome, Joao P. C. (ChemPlusChem, 2015)
Preconditions for the design of efficient organic solar-light-converting systems are strong absorptions across the visible region, the capacity to funnel excited state energy by intermolecular energy transfer, and alternative association processes in the photoinduced electron transfer. In this context, thiopyridyl porphyrins (PorSPy) and ruthenium phthalocyanines (RuPcs) proved to be versatile building blocks for the construction of novel supramolecular Por-Pc hybrid systems (PorSPy-RuPc) by axial coordination at ruthenium. The thiopyridyl groups placed at the bay region of the porphyrins coordinate the RuPc dye. A notable redistribution of the electron density in the new heterochromophore structures evidences the electron-donating/-accepting communication between the two dyes in the supramolecular hybrids. These structural hybrids were investigated physicochemically by means of their ground and excited state reactivities. Photophysical investigation by time-resolved transient absorption, mainly fluorescence and femtosecond spectroscopy, evidenced efficient intermolecular energy transfer from the photoexcited central porphyrin to the peripheral phthalocyanines in the supramolecular multichromophore ensembles. The findings may give impetus for the design of interesting materials for solar-light-converting systems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: donor-acceptor systems; phthalocyanines; porphyrins; ruthenium; supramolecular chemistry

Noncovalent Liquid Phase Functionalization of 2H-WS2with PDI: An Energy Conversion Platform with Long-Lived Charge Separation - Scharl, Tobias; Binder, Gerhard; Chen, Xin; Yokosawa, Tadahiro; Cadranel, Alejandro; Knirsch, Kathrin; Spiecker, Erdmann; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Transition metal dichalcogenides are attractive 2D materials in the context of solar energy conversion. Previous investigations have focused predominantly on the properties of these systems. The realization of noncovalent hybrids with, for example, complementary electroactive materials remains underexplored to this date for exfoliated WS2. In this contribution, we explore WS2 by means of exfoliation and integration together with visible light-absorbing and electron-accepting perylene diimides into versatile electron-donor acceptor hybrids. Important is the distinct electron-donating feature of WS2. Detailed spectroscopic investigations of WS2-PDI confirm the electron donor/acceptor nature of the hybrid and indicate that green light photoexcitation leads to the formation of long-lived WS2+-PDIcharge-separated states.
CRIS-Team Scopus Importer:2022-04-14

Non-Covalent Postfunctionalization of Dye Layers on TiO2 - A Tool for Enhancing Injection in Dye-Sensitized Solar Cells - Luchs, Tobias; Zieleniewska, Anna; Kunzmann, Andreas; Schol, Peter; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
We report on newly tailored dye layers, which were employed, on one hand, for covalent deposition and, on the other hand, for non-covalently post-functionalizing TiO2 nanoparticle films. Our functionalization concept enabled intermixing a stable covalent attachment of a first layer with a highly versatile and reversible hydrogen bonding through the Hamilton receptor-cyanuric acid binding motif as a second layer. Following this concept, we integrated step-by-step a first porphyrin layer and a second porphyrin/BODIPY layer. The individual building blocks and their corresponding combinations were probed with regard to their photophysical properties, and the most promising combinations were implemented in dye-sensitized solar cells (DSSCs). Relative to the first porphyrin layer adding the second porphyrin/BODIPY layers increased the overall DSSC efficiency by up to 43 %.
CRIS-Team WoS Importer:2021-03-12

Non-covalent versus covalent donor-acceptor systems based on near-infrared absorbing azulenocyanines and C 60 fullerene derivatives - Ince, Mine; Hausmann, Anita; Victoria Martinez-Diaz, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2012)
A novel supramolecular electron donor-acceptor hybrid (2·1) and an electron donor-acceptor conjugate (3), both exhibiting a remarkably shifted Q band in the NIR region of the solar spectrum, were prepared. Irradiation of the supramolecular ensemble 2·1 within the visible range leads to a nanosecond lived radical-ion pair state Zn-azulenocyanine -C . © 2012 The Royal Society of Chemistry.

Novel nanographene/porphyrin hybrids-preparation, characterization, and application in solar energy conversion schemes - Kießling, Daniel; Costa, Ruben Dario; Katsukis, Georgios; Malig, Jenny; Lodermeyer, Fabian; Feihl, Sebastian; Roth, Alexandra Marina; Wibmer, Leonie; Kehrer, Matthias; Volland, Michel; Wagner, Pawel; Wallace, Gordon G.; et al. (Chemical Science, 2013)
Four novel nanographene/porphyrin hybrids were prepared, characterized, and probed in solar energy conversion schemes. Exfoliation of graphite by means of immobilizing four different porphyrins onto the basal plane of graphene is accompanied by distinct electronic interactions in both the ground and the excited states. In the ground state, a strong loss in oscillator strength goes hand-in-hand with a notable broadening of the porphyrin transitions and, as such, attests to the shift of electron density from the electron donating porphyrins to nanographene. In the excited state, a nearly quantitative quenching of the porphyrin fluorescence is indicative of full charge transfer. The latter is corroborated by femtosecond transient absorption measurements, which reveal the generation of the one-electron oxidized radical cation of the porphyrins with absorption maxima at 490 and 625 nm in the visible region and conduction band electrons in nanographene with features at 890 and 1025 nm in the near infrared region. We have demonstrated the applicability of the new nanographene/porphyrin hybrids in, for example, solar cells. In this regard, the presence of flakes is crucial in terms of influencing the injection processes, preventing aggregation, and reducing recombination losses, which are commonly encountered in porphyrin-based DSSCs. © 2013 The Royal Society of Chemistry.

n- versus p-doping of graphite: what drives its wet-chemical exfoliation? - Wang, Bingzhe; Engelhardt, Verena; Roth, Alexandra Marina; Faust, Rdiger; Guldi, Dirk Michael (Nanoscale, 2017)
We have performed the syntheses of a novel pyrene-porphyrazine conjugate (ZnPzPy) and a reference porphyrazine (ZnPz) to promote the wet-chemical exfoliation of graphite based on the synergetic use of ultrasonication, centrifugation, and doping. ZnPzPy features, on one hand, a hydrophobic pyrene to anchor onto the basal plane of graphene, and, on the other hand, an amphoteric porphyrazine to either p- or n-dope graphene. To this end, we have characterized individual building blocks, that is, ZnPzPy and exfoliated graphite, and the resulting electron donor-acceptor nanohybrid, that is, ZnPzPy/graphene (ZnPzPy-G), by means of an arsenal of microscopic and spectroscopic techniques. From a full-fledged characterization we conclude that ZnPzPy facilitates the exfoliation of graphite affording suspensions featuring 9.5% of single- or few-layered ZnPzPy-G with a mean average size of 200 ± 140 nm. Importantly, a notable shift of charge density from graphene to ZnPzPy in the ground state of ZnPzPy-G corroborates the preference of exfoliated graphite to undergo p-doping rather than n-doping. As an immediate consequence, a full charge separation leads in the excited state to a 750 ± 150 ps lived charge separated state.
EAM Import::2019-03-12

One-pot solvothermal synthesis of magnetically separable rGO/MnFe2O4 hybrids as efficient photocatalysts for degradation of MB under visible light - Liu, Liping (Materials Chemistry and Physics, 2019)

One-Pot Synthesis and Excited-State Dynamics of Null Exciton-Coupled Diketopyrrolopyrroles Oligo-Grids - Bo, Yifan; Hou, Pengfei; Wan, Jun; Cao, Hongtao; Liu, Yuyu; Xie, Linghai; Guldi, Dirk Michael (Advanced Materials, 2023)
Exciton coupling in molecular aggregates plays a vital role in impacting and fine-tuning optoelectronic materials and their efficiencies in devices. A versatile platform to decipher aggregation-property relationships is built around multichromophoric architectures. Here, a series of cyclic diketopyrrolopyrrole (DPP) oligomers featuring nanoscale gridarene structures and rigid bifluorenyl spacers are designed and synthesized via one-pot Friedel–Crafts reaction. DPP dimer [2]Grid and trimer [3]Grid, which are cyclic rigid nanoarchitectures of rather different sizes, are further characterized via steady-state and time-resolved absorption and fluorescence spectroscopies. They exhibit monomer-like spectroscopic signatures in the steady-state measurements, from which null exciton couplings are derived. Moreover, in an apolar solvent, high fluorescence quantum yields and excited-state dynamics that resembled DPP monomer are gathered. In a polar solvent, the localized singlet excited state on a single DPP dissociates into the adjacent null coupling DPP with charge transfer characteristics. This pathway facilitates the evolution of the symmetry-broken charge-separated state (SB-CS). Notable is the fact that the SB-CS of [2]Grid is, on one hand, in equilibrium with the singlet excited state and promotes, on the other hand, the formation of the triplet excited state with a yield of 32% via charge recombination.
CRIS-Team Scopus Importer:2023-08-11
Keywords: diketopyrrolopyrroles; null-aggregates; rigidity of molecular structures; symmetry-breaking charge separation

On-off switch of charge-separated states of pyridine-vinylene-linked porphyrin-C-60 conjugates detected by EPR - Kirner, Sabrina; Arteaga, Danny; Henkel, Christian; Margrat, Johannes T.; Alegret, Nuria; Ohkubo, Kei; Insuasty, Braulio; Ortiz, Alejandro; Martin, Nazario; Echegoyen, Luis; Fukuzumi, Shunichi; Clark, Timothy; et al. (Chemical Science, 2015)
The design, synthesis, and electronic properties of a new series of D-pi-A conjugates consisting of free base (H2P) and zinc porphyrins (ZnP) as electron donors and a fullerene (C-60) as electron acceptor, in which the two electroactive entities are covalently linked through pyridine-vinylene spacers of different lengths, are described. Electronic interactions in the ground state were characterized by electrochemical and absorption measurements, which were further supported with theoretical calculations. Most importantly, charge-transfer bands were observed in the absorption spectra, indicating a strong push-pull behavior. In the excited states, electronic interactions were detected by selective photoexcitation under steady-state conditions, by time-resolved fluorescence investigations, and by pump probe experiments on the femto-, pico-, and nanosecond time scales. Porphyrin fluorescence is quenched for the different D-pi-A conjugates, from which we conclude that the deactivation mechanisms of the excited singlet states are based on photoinduced energy-and/or electron transfer processes between H2P/ZnP and C-60, mediated through the molecular spacers. The fluorescence intensity decreases and the fluorescence lifetimes shorten as the spacer length decreases and as the spacer substitution changes. With the help of transient absorption spectroscopy, the formation of charge-separated states involving oxidized H2P/ZnP and reduced C-60 was confirmed. Lifetimes of the corresponding charge-separated states, which ranged from similar to 400 picoseconds to 165 nanoseconds, depend on the spacer length, the spacer substitution, and the solvent polarity. Interestingly, D-pi-A conjugates containing the longest linkers did not necessarily exhibit the longest charge-separated state lifetimes. The distances between the electron donors and the acceptors were calculated by molecular modelling. The longest charge-separated state lifetime corresponded to the D-p-A conjugate with the longest electron donor-acceptor distance. Likewise, EPR measurements in frozen media revealed charge separated states in all the D-p-A conjugates investigated. A sharp peak with g values similar to 2.000 was assigned to reduced C-60, while a broader, less intense signal (g similar to 2.003) was assigned to oxidized H2P/ZnP. On-off switching of the formation and decay of the charge-separated states was detected by EPR at 77 K by repeatedly turning the irradiation source on and off.

On the mechanism of Zn4O-acetate precursors ripening to ZnO: How dimerization is promoted by hydroxide incorporation - Segets, Doris; Milek, Theodor; Kirschbaum, Rolf; von Gernler, Marc; Lübbert, Christian; Drewello, Thomas; Peukert, Wolfgang; Zahn, Dirk (Journal of Chemical Physics, 2015)
We report on a combined experimental and molecular modelling study on Zn4O ion clusters stabilized by acetate molecules (OAc). In particular, ab initio calculations of acetate substitution by hydroxide ions are compared with mass spectrometry data. Though quantum calculations in the gas phase indicate strong energetic preference, no experimental evidence of stable Zn4O(OAc)6−x(OH)x clusters in ethanolic solutions could be observed. This apparent contradiction is rationalized by identifying the supportive role of hydroxide ions for the association of (OAc− → OH− substituted) Zn4O(OAc)6 and Zn4O(OAc)5+ clusters. Mass spectrometry and quantum calculations hint at the stability of (Zn4O)2(OAc)12−x(OH)x dimers with x = 1, 2. Therein, the hydroxide ions establish salt-bridges that allow for the formation of additional Zn3 motifs with the OH above the triangle center—a structural motif close to that of the ZnO-crystal. The association of Zn4O(OAc)6 clusters is thus suggested to involve OAc− → OH− substitution as an activation step, quickly followed by dimerization and the subsequent agglomeration of oligomer
Keywords: mechanism; particle; rod; nano; ripening

On the photophysics of nanographenes-investigation of functionalized hexa-: Peri -hexabenzocoronenes as model systems - Haines, Philipp; Reger, David; Träg, Johannes; Strauss, Volker; Lungerich, Dominik; Zahn, Dirk; Jux, Norbert; Guldi, Dirk Michael (Nanoscale, 2021)
In this study, we report on hexa-peri-hexabenzocoronenes (HBCs) as representative models for nanographenes. To this end, we synthesized a family of functionalized HBCs and investigated the impact of the substituents on the π-extended systems of the HBCs. DFT and TD-DFT calculations suggested a charge transfer character, which intensified as the electron density withdrawing effects of the substituents (-M-effect) increased. Unambiguous corroboration of the charge transfer character in the case of NO2-substituents was realized via steady-state absorption and fluorescence experiments, which focused on the dependencies on the solvent polarity and temperature featuring. Going beyond HBCs with NO2-substituents, time-correlated single photon counting, and femtosecond and nanosecond transient absorption spectroscopy unveiled long-lived singlet and triplet excited states. As a complement, we performed electrochemical and spectroelectrochemical measurements. These measurements were carried out to shed light onto the nature of the functionalized HBCs as electron acceptors and/or donors, on the one hand, and their corresponding spectroscopic signatures, on the other hand. All of the aforementioned information enabled intermolecular charge separation assays with, for example, suitable electron acceptors by steady-state and time-resolved spectroscopy. This journal is
CRIS-Team Scopus Importer:2021-02-05

Optical gap and fundamental gap of oligoynes and carbyne - Zirzlmeier, Johannes; Schrettl, Stephen; Brauer, Jan C.; Contal, Emmanuel; Vannay, Laurent; Brémond, Éric; Jahnke, Eike; Guldi, Dirk Michael; Corminboeuf, Clémence; Tykwinski, Rik R.; Frauenrath, Holger (Nature Communications, 2020)
The optoelectronic properties of various carbon allotropes and nanomaterials have been well established, while the purely sp-hybridized carbyne remains synthetically inaccessible. Its properties have therefore frequently been extrapolated from those of defined oligomers. Most analyses have, however, focused on the main optical transitions in UV-Vis spectroscopy, neglecting the frequently observed weaker optical bands at significantly lower energies. Here, we report a systematic photophysical analysis as well as computations on two homologous series of oligoynes that allow us to elucidate the nature of these weaker transitions and the intrinsic photophysical properties of oligoynes. Based on these results, we reassess the estimates for both the optical and fundamental gap of carbyne to below 1.6 eV, significantly lower than previously suggested by experimental studies of oligoynes.
CRIS-Team Scopus Importer:2020-10-02

Optical processes in carbon nanocolloids - Ragazzon, Giulio; Cadranel, Alejandro; Ushakova, Elena V.; Wang, Yichun; Guldi, Dirk Michael; Rogach, Andrey L.; Kotov, Nicholas A.; Prato, Maurizio (Chem, 2021)
Light is the original source of most energy on Earth, allowing us to see and live. It is also central to many technological processes. Therefore, innovative nanomaterials that can absorb, generate, or further exploit light are of utmost importance, having the potential to become pervasive in our lives. This is the case for carbon nanocolloids, which are ubiquitous, biocompatible, and inexpensive, which are the three important prerequisites for their broader application in different fields of technology. Yet, despite intense research for a number of years, a unifying picture describing the excited-state properties of these nanocolloids is lacking. It is possibly the time when this approach should be reversed, embracing the inherent diversity of excited states in carbon-based particles, which enable us to focus on engineering their optical properties based on their structural variability. A deeper understanding of the molecular features of carbon nanocolloids is emerging as one of the key factors, which will allow unlocking excited-state processes appearing out of reach, unfolding the full potential of optical processes in this potent family of nanomaterials.
CRIS-Team Scopus Importer:2021-03-19
Keywords: carbon dots; carbon nanocolloids; carbon nanoparticles; charge transfer; energy transfer; fluorescence; SDG7: Affordable and clean energy; SDG9: Industry; innovation; and infrastructure

Optimizing CuO p-type dye-sensitized solar cells by using a comprehensive electrochemical impedance spectroscopic study - Langmar, Oliver; Ganivet, Carolina R.; De La Torre, Gema; Torres, Tomas; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
We introduce a novel and comprehensive approach for the evaluation and interpretation of electrochemical impedance spectroscopy (EIS) measurements in p-type DSSCs. In detail, we correlate both the device performance and EIS figures-of-merit of a series of devices in which, the calcination temperature, film thickness, and electrolyte concentration have been systematically modified. This new approach enables the separation of the different processes across the dye/semiconductor/electrolyte interface, namely the unfavorable charge recombination and the favorable electron injection/regeneration processes. In addition, studies on non-sensitized CuO and NiO electrodes provide insights into their affinity towards a reaction with the electrolyte - CuO is far less reactive towards the polyiodide species. Overall, this work underlines the superior features of CuO with respect to NiO for p-DSSCs and demonstrates a comprehensive optimization of the CuO-based DSSCs with respect to the device architecture by the aid of EIS analysis.
EAM Import::2019-03-08

Optimizing electronic synergy of atomically dispersed dual-metal Ni–N4 and Fe–N4 sites with adjacent Fe nanoclusters for high-efficiency oxygen electrocatalysis - Liu, Liping (Energy and Environmental Science, 2024)

Ordering aspects and intramolecular conformation of tetraphenylporphyrins on Ag(111) - Buchner, Florian; Kellner, Ina; Hieringer, Wolfgang; Görling, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2010)
A systematic scanning tunnelling microscopy study of the self-assembly, intramolecular conformation and supramolecular ordering of different tetraphenylporphyrins (xTPP) with or without a central metal atom (x = 2H, Fe, Co) on Ag(111) at room temperature is presented. The investigation covers a wide range, i.e. the adsorption behaviour from the low sub-monolayer up to the multilayer regime is described in detail and conclusively discussed in regard to molecule-molecule and molecule-substrate interactions. At monolayer coverage the molecules self-assemble in domains with a square unit cell caused by "T-type" intermolecular interactions, while the orientation of the domains along the symmetry axes is determined by adsorbate-substrate interactions. Interestingly for ordered monolayers domain boundaries always separate domains of different organizational chirality but same orientation of the square unit cell. This demonstrates that in the particular system chirality obviously restricts the long range order of the supramolecular TPP assemblies. In combination with DFT calculations it is also demonstrated that the previously reported intramolecular saddle shape deformation of TPPs upon adsorption is more pronounced for metallo-TPP than for 2HTPP. © 2010 the Owner Societies.

Organic functionalization of carbon nanotubes - Georgakilas, Vasilios; Kordatos, Konstantinos; Prato, Maurizio; Guldi, Dirk Michael; Holzinger, Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2002)
A very general and versatile method for functionalizing different types of carbon nanotubes is described, using the 1,3-dipolar cycloaddition of azomethine ylides. Approximately one organic group per 100 carbon atoms of the nanotube is introduced, to yield remakably soluble bundles of nanotubes, as seen in transmission electron micrographs. The solubilization of the nanotubes generates a novel, interesting class of materials, which combines the properties of the nanotubes and the organic moiety, thus offering new opportunities for applications in materials science, including the preparation of nanocomposites. Copyright © 2002 American Chemical Society.

Organic reactions in ionic liquids studied by in situ XPS - Niedermaier, Inga; Kolbeck, Claudia; Taccardi, Nicola; Schulz, Peter; Li, Jing; Drewello, Thomas; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (ChemPhysChem, 2012)
We demonstrate the application of in situ X-ray photoelectron spectroscopy (XPS) to monitor organic, liquid-phase reactions. By covalently attaching ionic head groups to the reacting organic molecules, their volatility can be reduced such that they withstand ultra high vacuum conditions. The applied method, which is new for the investigation of organic reactions, allows for following the fate of all elements present in the reaction mixtureexcept for hydrogenin a quantitative and oxidation-state-sensitive manner in one experiment. This concept is demonstrated for the alkylation of a tertiary amine attached to an imidazolium or phosphonium moiety by the anion 4-chlorobutylsulfonate ([ClC H SO ] ). In the course of the reaction, the covalently bound chlorine is converted to chloride and the amine to ammonium as reflected by the distinct shifts in the N 1s and Cl 2p binding energies. © 2012 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.

Organosulfur-based fullerene materials - Nakahodo, Tsukasa; Ishitsuka, Midori O.; Takano, Yuta; Tsuchiya, Takahiro; Akasaka, Takeshi; Herranz, M. Angeles; Martin, Nazario; Guldi, Dirk Michael; Nagase, Shigeru (Phosphorus Sulfur and Silicon and the Related Elements, 2011)
Chemical functionalizations of an endohedral metallofullerene, La @I-C, and an empty fullerene, C , are demonstrated using organosulfur compounds. A novel donor-acceptor system of La@I-C-exTTF (3) synthesized using the Prato reaction shows photo-induced intramolecular charge separation. On the other hand, the photoreaction of C with N-ptoluenesulfonyl sulfilimine affords N-tosyl-1,2-aziridinofullerene (5). The first reversible interconversion of 1,2-aziridinofullerene and 1,6-azafulleroid was found for mono-substituted fullerenes by thermal rearrangement of 5 to 6. S,S-Diphenylsulfilimines (7) with an electrondonating group on the N atom reacts with C to afford corresponding aziridinofullerenes (8-10) regioselectively. Copyright © Taylor & Francis Group, LLC.

Overpotentials and Faraday Efficiencies in CO2 Electrocatalysis-the Impact of 1-Ethyl-3-Methylimidazolium Trifluoromethanesulfonate - Neubauer, Sebastian; Krause, Ralf K.; Schmid, Bernhard; Guldi, Dirk Michael; Schmid, Guenter (Advanced Energy Materials, 2016)
The mixtures of room temperature ionic liquid 1-ethyl-3-methylimidazolium trifl uoromethanesulfonate ([EMIM]TFO) and water as electrolytes for reduction of CO2 to CO are reported. Linear sweep voltammetry shows overpotentials for CO2 reduction and the competing hydrogen evolution reaction (HER), both of which vary as a function of [EMIM]TFO concentration in the range from 4 × 10-3 M (0.006 mol%) to 4869 × 10-3 M (50 mol%). A steady lowering of overpotentials up to an optimum for 334 × 10-3 M is identifi ed. At 20 mol% and more of [EMIM]TFO, a signifi cant CO2 reduction plateau and inhibition of HER, which is limited by H2 O diffusion, is noted. Such a plateau in CO2 reduction correlates to high CO Faraday effi ciencies. In case of 50 mol% [EMIM]TFO, a broad plateau spanning over a potential range of 0.58 V evolves. At the same time, the overpotential for HER is increased by 1.20 V when compared to 334 × 10-3 M and, in turn, HER is largely inhibited. The Faraday effi ciencies for CO and H2 formation feature 95.6% ± 6.8% and 0.5% ± 0.3%, respectively, over a period of 3 h in a separator divided cell. Cathodic as well as anodic electrochemical stability of the electrolyte throughout this time period is corroborated in 1 H NMR spectroscopic measurements.
EAM Import::2019-03-08

Oxa[7]superhelicene: A pi-Extended Helical Chromophore Based on Hexa-peri-hexabenzocoronenes - Reger, David; Haines, Philipp; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2018)
A novel pi-extended "superhelicene" based on hexa-peri-hexabenzocoronenes (HBCs) has been synthesized by an efficient four-step synthetic procedure starting from diphenyl ether. Comprehensive structural analysis of the helicene was performed by NMR spectroscopy and mass spectrometry measurements together with X-ray analysis. Physicochemical analysis of the superhelicene and suitable HBC references revealed it had outstanding fluorescent features with quantum yields of over 80%.
Keywords: fluorescence; helical structures; photophysics; polycyclic aromatic hydrocarbons; pi-extension

Oxidative charge transfer of EMFs, biomedical applications of EMFs, and EMF-based nanomaterials and molecular materials - Lederer, Marcus; Rudolf, Marc; Wolf, Maximilian; Guldi, Dirk Michael; Zhao, Shasha; Lu, Xing; Feng, Lai (CRC Press, 2014)
Fullerenes have been under investigation in different fields of research for nearly 30 years. In September 1985, a group of scientists including Robert Curl, James Heath, Harry Kroto, Yuan Liu, Sean O’Brian, and Richard Smalley discovered fullerenes via mass spectrometry at Rice University in Houston, Texas [1]. This new class of carbon allotropes was termed buckminsterfullerenes because the geodesic domes designed by inventor and architect Buckminster Fuller provided a decisive clue about their structure (Figure 7.1) [2]. A decade later, namely, in 1996, Curl, Kroto, and Smalley were awarded with the Nobel Prize in chemistry for the discovery of fullerenes [1].
CRIS-Team Scopus Importer:2023-03-07

Oxidative Cyclodehydrogenation of Trinaphthylamine: Selective Formation of a Nitrogen-Centered Polycyclic pi-System Comprising 5-and 7-Membered Rings - Nebauer, Johannes; Neiß, Christian; Krug, Marcel; Vogel, Alexander; Fehn, Dominik; Ozaki, Shuhei; Rominger, Frank; Meyer, Karsten; Kamada, Kenji; Guldi, Dirk Michael; Görling, Andreas; Kivala, Milan (Angewandte Chemie International Edition, 2022)
We describe a new type of nitrogen-centered polycyclic scaffold comprising a unique combination of 5-, 6-, and 7-membered rings. The compound is accessible through an intramolecular oxidative cyclodehydrogenation of tri(1-naphthyl)amine. To the best of our knowledge this is the very first example of a direct 3-fold cyclization of a triarylamine under oxidative conditions. The unusual ring fusion motif is confirmed by X-ray crystallography and the impact of cyclization on the electronic and photophysical properties is investigated both experimentally and theoretically based on density-functional theory (DFT) calculations. The formation of the unexpected product is rationalized by detailed mechanistic studies on the DFT level. The results suggest the cyclization to occur under kinetic control via a dicationic mechanism.
CRIS-Team WoS Importer:2022-09-02

Oxidized silicon nanoparticles and iron oxide nanoparticles for radiation therapy - Klein, Stefanie; Kizaloglu, Melek; Dell'Acriprete, M. L.; Neuhuber, Winfried; Distel, Luitpold; Gonzales, M. C.; Kryschi, Carola (2016)
EVALuna2:33050

Oxidized silicon nanoparticles for radiosensitization of cancer and tissue cells - Klein, Stefanie; Dell'Arciprete, Maria L.; Wegmann, Marc; Distel, Luitpold; Neuhuber, Winfried; Gonzalez, Monica C.; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2013)
The applicability of ultrasmall uncapped and aminosilanized oxidized silicon nanoparticles (SiNPs and NH-SiNPs) as radiosensitizer was studied by internalizing these nanoparticles into human breast cancer (MCF-7) and mouse fibroblast cells (3T3) that were exposed to X-rays at a single dose of 3Gy. While SiNPs did not increase the production of reactive oxygen species (ROS) in X-ray treated cells, the NH-SiNPs significantly enhanced the ROS formation. This is due to the amino functionality as providing positive surface charges in aqueous environment. The NH-SiNPs were observed to penetrate into the mitochondrial membrane, wherein these nanoparticles provoked oxidative stress. The NH-SiNPs induced mitochondrial ROS production was confirmed by the determination of an increased malondialdehyde level as representing a gauge for the extent of membrane lipid peroxidation. X-ray exposure of NH-SiNPs incubated MCF-7 and 3T3 cells increased the ROS concentration for 180%, and 120%, respectively. Complementary cytotoxicity studies demonstrate that these silicon nanoparticles are more cytotoxic for MCF-7 than for 3T3 cells. © 2013 Elsevier Inc.

Oxyallyl Exposed: An Open-Shell Singlet with Picosecond Lifetimes in Solution but Persistent in Crystals of a Cyclobutanedione Precursor - Kuzmanich, Gregory; Spänig, Fabian; Tsai, Chao-Kuan; Um, Joann M.; Hoekstra, Ryan M.; Houk, K. N.; Guldi, Dirk Michael; Garcia-Garibay, Miguel A. (Journal of the American Chemical Society, 2011)
Photoinduced decarbonylation of 2,4-bis(spirocyclohexyl)-1,3- cyclobutanedione 1 in the crystalline solid state resulted in formation of a deep blue transient with λ = 550 nm and a half-life of 42 min at 298 K, identified as kinetically stabilized oxyallyl. Support for an open-shell singlet species was obtained by spectroscopic analysis and (4/4) CASSCF calculations with the 6-31+G(d) basis set and multireference MP2 corrections. The electronic spectrum of the singlet biradical, confirmed by femtosecond pump-probe studies in solution, was matched by coupled cluster calculations with single and double corrections. © 2011 American Chemical Society.

Pairing fullerenes and porphyrins: Supramolecular wires that exhibit charge transfer activity - Wessendorf, Florian; Grimm, Bruno; Guldi, Dirk Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A concept is elaborated of pairing electron donors and electron acceptors that share a common trait, wire-like features, as a powerful means to realize a new and versatile class of electron donor-acceptor nanohybrids. Important variables are fine-tuning (i) the complexation strength, (ii) the electron/energy transfer behavior, and (iii) the solubilities of the resulting architectures. In particular, a series of supramolecular porphyrin/fullerene hybrids assembled by the hydrogen bonding of Hamilton receptor/cyanuric acid motif has been realized. Putting the aforementioned variables into action, the association constants (K), as they were determined from H NMR and steady-state fluorescence assays, were successfully tweaked with values in the range of 10-10 M . In fact, our detailed studies corroborate that the latter reveal a dependence on the nature of the spacer, that is, p-phenylene-ethynylene, p-phenylene-vinylene, p-ethynylene, and fluorene, as well as on the length of the spacer. Complementary performed transient absorption studies confirm that electron transfer is indeed the modus operandi in our novel class of electron donor-acceptor nanohybrids, while energy transfer plays, if any, only a minor role. The accordingly formed electron transfer products, that is, one-electron oxidized porphyrins and one-electron reduced fullerenes, are long-lived with lifetimes that reach well into the time domain of tens of nanoseconds. Finally, we have used the distance dependence on electron transfer, charge separation and charge recombination, to determine for the first time a ß value (0.11) for hydrogen-bonding-mediated electron transfer. © 2010 American Chemical Society.

Palladium-Mediated Ethylation of the Imidazolium Cation Monitored In Operando on a Solid Catalyst with Ionic Liquid Layer - Bauer, Tanja; Hager, Veit; Williams, Marc; Laurin, Mathias; Döpper, Tibor; Görling, Andreas; Szesni, Normen; Wasserscheid, Peter; Haumann, Marco; Libuda, Jörg (ChemCatChem, 2017)
The ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate [EMIM][EtOSO] was supported on Pd-AlO to yield a solid catalyst with ionic liquid layer (SCILL) material. During the hydrogenation of ethene, it was found that ethene was incorporated into the imidazolium moiety in a reaction catalyzed by the palladium surface. The formation of 1,2-diethyl-3-methylimidazolium ethylsulfate was confirmed ex situ by means of NMR spectroscopy. Moreover, the reaction itself could be monitored in situ by diffuse reflection infrared Fourier transformation (DRIFT) spectroscopy. A reaction mechanism involving surface carbene species was proposed on the basis of the analytical data.
Keywords: carbenes; heterogeneous catalysis; ionic liquids; palladium; reaction mechanisms

Panchromatic light funneling through the synergy in hexabenzocoronene-(metallo)porphyrin-fullerene assemblies to realize the separation of charges - Wolf, Maximilian; Lungerich, Dominik; Bauroth, Stefan; Popp, Maximilian; Platzer, Benedikt; Clark, Timothy; Anderson, Harry L.; Jux, Norbert; Guldi, Dirk Michael (Chemical Science, 2020)
Here, we present a novel butadiyne-linked HBC-ethynyl-porphyrin dimer, which exhibits in the ground state strong absorption cross sections throughout the UV and visible ranges of the solar spectrum. In short, a unidirectional flow of excited state energy from the HBC termini to the (metallo)porphyrin focal points enables concentrating light at the latter. Control over excitonic interactions within, for example, the electron-donating porphyrin dimers was realized by complexation of bidentate ligands to set up panchromatic absorption that extends all the way into the near-infrared range. The bidentate binding motif was then exploited to create a supramolecular electron donor-acceptor assembly based on a HBC-ethynyl-porphyrin dimer and an electron accepting bis(aminoalkyl)-substituted fullerene. Of great relevance is the fact that charge separation from the photoexcited HBC-ethynyl-porphyrin dimer to the bis(aminoalkyl)-substituted fullerene is activated not only upon photoexciting the HBCs in the UV as well as the (metallo)porphyrins in the visible but also in the NIR. Implicit is the synergetic interplay of energy and charge transfer in a photosynthetic mimicking manner. The dimer and bis-HBC-ethynyl-porphyrin monomers, which serve as references, were probed by means of steady-state as well as time-resolved optical spectroscopies, including global target analyses of the time-resolved transient absorption data.
CRIS-Team Scopus Importer:2020-07-31

Panchromatic Light Harvesting and Stabilizing Charge-Separated States in Corrole-Phthalocyanine Conjugates through Coordinating a Subphthalocyanine - Berna, Beatrice Berionni; Platzer, Benedikt; Wolf, Maximilian; Lavarda, Giulia; Nardis, Sara; Galloni, Pierluca; Torres, Tomas; Guldi, Dirk Michael; Paolesse, Roberto (Chemistry - A European Journal, 2020)
Owing to the electron-donating and -accepting nature of corroles (Corr) and phthalocyanines (Pc), respectively, we designed and developed two novel covalently linked Corr-Pc conjugates. The synthetic route allows the preparation of the target conjugates in satisfying yields. Comprehensive steady-state absorption, fluorescence, and electrochemical assays enabled insights into energy and electron-transfer processes upon photoexcitation. Coordinating a pyridine-appended subphthalocyanine (SubPc) to the Pc of the conjugate sets up the ways and means to realize the first example of an array composed by three different porphyrinoids, which drives a cascade of energy and charge-transfer processes. Importantly, the SubPc assists in stabilizing the charge-separated state, that is, one-electron oxidized Corr and the one electron-reduced Pc, upon photoexcitation by means of a reductive charge transfer to the SubPc. To the best of our knowledge, this is the first case of an intramolecular oxidation of a Corr within electron-donor-acceptor conjugates by means of just photoexcitation. Moreover, the combination of Corr, Pc, and SubPc guarantees panchromatic absorption across the visible range of the solar spectrum, with the SubPc covering the green gap" that usually affects porphyrinoids.
CRIS-Team WoS Importer:2020-10-09

Panchromatic light harvesting in single wall carbon nanotube hybrids - Immobilization of porphyrin-phthalocyanine conjugates - Bartelmeß, Jürgen; Soares, Ana R. M.; Victoria Martinez-Diaz, M.; Neves, Maria G. P. M. S.; Tome, Augusto C.; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael (Chemical Communications, 2011)
We report on immobilizing H /Zn-porphyrin-Zn-phthalocyanine conjugates onto single wall carbon nanotubes and by using the excellent stability of the resulting suspensions we were able to demonstrate for the first time the sequence of energy transfer-electron transfer in SWNT donor-acceptor conjugates. © 2011 The Royal Society of Chemistry.

Parallel (face-to-face) versus perpendicular (edge-to-face) alignment of electron donors and acceptors in fullerence porphyrin dyads: The importance of orientation in electron transfer [2] - Guldi, Dirk Michael; Luo, Chuping; Prato, Maurizio; Troisi, Alessandro; Zerbetto, Francesco; Scheloske, Michael; Dietel, Elke; Bauer, Walter; Hirsch, Andreas (Journal of the American Chemical Society, 2001)

Parallel versus Twisted Pentacenes: Conformational Impact on Singlet Fission - Papadopoulos, Ilias; Reddy, S. Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Thiel, Dominik; Thoss, Michael; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Physical Chemistry Letters, 2022)
We placed two pentacene chromophores at the termini of a diacetylene linker to investigate the impact of excitation wavelength, conformational flexibility, and vibronic coupling on singlet fission. Photoexcitation of the low-energy absorption results in a superposed mixture of states, which transform on an ultrafast time-scale into a spin-correlated and vibronically coupled/hot delocalized triplet pair 1(T1T1)deloc. Regardless of temperature, the lifetime for 1(T1T1)deloc is less than 2 ps. In contrast, photoexcitation of the high-energy absorption results in the formation of 1(T1T1)deloc lasting 1.0 ps, which then decays at room temperature within 4 ps via triplet-triplet annihilation. Lowering the temperature enables 1(T1T1)deloc to delocalize and vibronically decouple, in turn affording 1(T1T1)loc. In addition, our results suggest that the quasi-free rotation at the diacetylene spacer may lead to twisted conformations with very low SF quantum yields, highlighting the need of controlling this structural aspect in the design of new singlet fission active molecules.
CRIS-Team Scopus Importer:2023-03-07

P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.

p-Doping of graphene in hybrid materials with 3,10-diazapicenium dications - Roth, Alexandra Marina; Schaub, Tobias; Meinhardt, Ute; Thiel, Dominik; Storch, Jan; Cirkva, Vladimir; Jakubik, Pavel; Guldi, Dirk Michael; Kivala, Milan (Chemical Science, 2017)
N,N′-Didodecyl-substituted 3,10-diazapicenium salts featuring bromide and hexafluorophosphate counterions have been designed as novel dopants to realize individualized graphene sheets in a series of cutting edge experiments and to intrinsically stabilize them via p-doping. Importantly, electrochemical studies revealed two consecutive irreversible one-electron reductions of the N,N′-didodecyl-substituted 3,10-diazapicenium salts to yield the corresponding radical cation and neutral quinoidal species. Formation of both species was accompanied by characteristic changes in the absorption spectra. The 3,10-diazapicenium bromide was found to be a potent dopant to produce hybrid materials with exfoliated graphene. Microscopy based on AFM and TEM imaging and spectroscopy based on Raman probing corroborated that, upon drying, the hybrid material consists of few layer (5–8 layers) turbostratic graphene sheets that are p-doped. Our findings identify the newly synthesized N,N′-dialkylated 3,10-diazapicenium salts as highly promising candidates for the fabrication of functional graphene materials with tailored properties.
EAM Import::2019-03-08

Pentacene Appended to a TEMPO Stable Free Radical: The Effect of Magnetic Exchange Coupling on Photoexcited Pentacene - Chernick, Erin; Casillas, Ruben; Zirzlmeier, Johannes; Gardner, Daniel M.; Gruber, Marco; Kropp, Henning; Meyer, Karsten; Wasielewski, Michael R.; Guldi, Dirk Michael; Tykwinski, Rik (Journal of the American Chemical Society, 2015)
Understanding the fundamental spin dynamics of photoexcited pentacene derivatives is important in order to maximize their potential for optoelectronic applications. Herein, we report on the synthesis of two pentacene derivatives that are functionalized with the [(2,2,6,6-tetramethylpiperidin-1-yl)oxy] (TEMPO) stable free radical. The presence of TEMPO does not quench the pentacene singlet excited state, but does quench the photoexcited triplet excited state as a function of TEMPO-to-pentacene distance. Time-resolved electron paramagnetic resonance experiments confirm that triplet quenching is accompanied by electron spin polarization transfer from the pentacene excited state to the TEMPO doublet state in the weak coupling regime.
EAM Import::2019-03-08

Pentacene Dimers as a Critical Tool for the Investigation of Intramolecular Singlet Fission - Hetzer, Constantin; Guldi, Dirk Michael; Tykwinski, Rik R. (Chemistry - A European Journal, 2018)
Singlet fission (SF) involves the spontaneous splitting of a photoexcited singlet state into a pair of triplets, and it holds great promise toward the realization of more efficient solar cells. Although the process of SF has been known since the 1960s, debate regarding the underlying mechanism continues to this day, especially for molecular materials. A number of different chromophores have been synthesized and studied in order to better understand the process of SF. These previous reports have established that pentacene and its derivatives are especially well-suited for the study of SF, since the energetic requirement E(S1)≥2E(T1) is fulfilled rendering the process exothermic and unidirectional. Dimeric pentacene derivatives, in which individual pentacene chromophores are tethered by a “spacer”, have emerged as the system of choice toward exploring the mechanism of intramolecular singlet fission (iSF). The dimeric structure, and in particular the spacer, allows for controlling and tuning the distance, geometric relationship, and electronic coupling between the two pentacene moieties. This Minireview describes recent advances using pentacene dimers for the investigation of iSF.
CRIS-Team Scopus Importer:2022-04-14
Keywords: acene synthesis; pentacene; singlet fission; solar energy; ultrafast spectroscopy

Pentacenes: A Molecular Ruler for Singlet Fission - Basel, Bettina; Papadopoulos, Ilias; Thiel, Dominik; Casillas, Ruben; Zirzlmeier, Johannes; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Trends in Chemistry, 2019)
Surpassing the Shockley–Queisser limit, which places an upper bound on solar conversion efficiency for a single p–n junction solar cell at slightly more than 30%, is one of the grand challenges in the field of solar-energy research. Singlet fission (SF)in molecular acenes, the molecular analog of multiple exciton generation (MEG), has the potential to initiate a game-changing advance in solar-energy conversion. SF allows singlet-excited states (S 1 )to be down-converted into twice as many triplet-excited states (T 1 ).
CRIS-Team Scopus Importer:2019-05-14
Keywords: interfacial electron transfer; pentacenes; singlet fission; solar energy; time-resolved spectroscopy; triplet

Perspectives on electrochemical insertion of lithium in carbon nanotubes - Sgobba, Vito; Guldi, Dirk Michael (Electrochemical Society Interface, 2010)
Carbon nanotubes (CNTs) are emerging materials with high potential in several disciplines, such as electrochemical insertion of Lithium ion batteries is discussed. Lithium ion batteries are the main power source in today's portable electronic devices. The formation of the new SWNT/lithium systems was complementary monitored by in situ galvanostatic charge-discharge, cyclic voltammetry, X-ray diffraction, as well as resistivity measurements. This has shaped the scientific community's view on technological advances in the emerging fields of energy storage devices focusing on Li-ion secondary batteries, supercapacitors, hydrogen storage. It also unveils the impact on contemporary advances and innovations in, for example, electrochemical doping of the Fermi level of CNT for photonic and nanoelectronic applications.

Perylene-Monoimides: Singlet Fission Down-Conversion Competes with Up-Conversion by Geminate Triplet-Triplet Recombination - Papadopoulos, Ilias; Gutiérrez-Moreno, David; McCosker, Patrick Michael; Casillas, Ruben; Keller, Paul A.; Sastre-Santos, Ángela; Clark, Timothy; Fernández-Lázaro, Fernando; Guldi, Dirk Michael (Journal of Physical Chemistry A, 2020)
Triplet-excited-state energies of perylene-monoimides (PMIs) lie in the range 1.12 eV ± 2 meV when compared to singlet-excited-state energies of about 2.39 eV ± 2 meV; therefore, the corresponding naphthalene-linked PMI-Dimer was investigated as a novel singlet-fission (SF) material. Ultrafast transient absorption measurements demonstrated the (S1S0)-to-1(T1T1) transformation and the involvement of a mediating step in the overall 1(T1T1) formation. The intermediate is a charge-transfer state that links the initial (S1S0) with the final 1(T1T1), and imposes charge-transfer character on both, which are thus denoted (S1S0)CT and 1(T1T1)CT. At room temperature, the decorrelation and stability of 1(T1T1)CT is affected by the geminate triplet-triplet recombination (G-TTR) of the two triplets. Independent confirmation for G-TTR to afford up-converted (S1S0)UC in fsTA and nsTA measurements with PMI-Dimer, came from probing PMI-Monomer (T1)s in triplet-triplet annihilation up-conversion (TTA-UC). The G-TTR channel, active in the PMI-Dimer at room temperature, is suppressed by working at either low temperatures (∼140 K) or in polar solvents (benzonitrile): Both scenarios assist in stabilizing (T1T1)CT. As a consequence, the triplet quantum yields are 4.2% and 14.9% at room temperature and 140 K, respectively, in 2-methyltetrahydrofuran.
CRIS-Team Scopus Importer:2020-07-31

Phenothiazine-pyrene dyads: Photoinduced charge separation and structural relaxation in the CT state - Acar, Nursel; Kurzawa, Jana; Schneider, Siegfried; Clark, Timothy; et al. (Journal of Physical Chemistry A, 2003)
Electron donor-acceptor systems with phenothiazine linked directly to pyrene exhibit a dual emission in moderately and very polar solvents. Steady state and time-resolved fluorescence spectroscopy provide evidence that the "blue" and "red" emission bands originate from different species. Fluorescence excitation spectra show a similar appearance when the emission is monitored either in the red or blue spectral range, but they are slightly shifted against each other. This suggests that different isomers exist with a distinctly different photophysical behavior. Semiempirical (AM1/CI) molecular orbital calculations with a continuum solvent treatment have been used to establish the geometry of the two nearly isoenergetic stereoisomers and to calculate the properties of their excited Franck-Condon states. Geometry optimization of various excited states provides evidence for different internal relaxation coordinates for the phenothiazine-localized S-1 state and the charge transfer state S-6, on one hand, and the pyrene-localized S-2 (S-3) state, on the other hand. The relaxed geometries in the excited states of both isomers represent mirror images with identical properties. The different photophysical behavior of the two isomers is most likely caused by the different potential energy curves, or more precisely speaking, by different location and/or heights of the barrier along the reaction coordinates from the locally excited to the geometry-relaxed CT states.

Photoacid-macroion assemblies: how photo-excitation switches the size of nano-objects - Zika, Alexander; Agarwal, Mohit; Zika, Wiebke; Guldi, Dirk Michael; Schweins, Ralf; Gröhn, Franziska (Nanoscale, 2023)
Electrostatic self-assembly of photoacids with oppositely charged macroions yields supramolecular nano-objects in aqueous solutions, whose size is controlled through light irradiation. Nano-assemblies are formed due to electrostatic attractions and mutual hydrogen bonding of the photoacids. Irradiation with UV light leads to the deprotonation of the photoacid and, consequently, a change in particle size. Overall, the hydrodynamic radii of the well-defined photoacid-macroion nano-objects lie between 130 and 370 nm. For a set of photoacids, we determine the acidity constants in the ground and excited state, discuss the sizes of photoacid-macroion nano-objects (by dynamic and static light scattering), their composition and the particle shapes (by small-angle neutron scattering), and relate their charge characteristics to size, structure and shape. We investigate the association thermodynamics and relate nanoscale structures to thermodynamics and, in turn, thermodynamics to molecular features, particularly the ionization energy of the photoacid hydroxyl group proton. Structure-directing effects completely differ from those for previously investigated systems, with hydrogen bonding and entropic effects playing a major role herein. This combined approach allows developing a comprehensive understanding of assembly formation and photo-response, anchored in molecular parameters (pKa, ionization energy, substituent group location), charge characteristics, and the association enthalpy and entropy. This fundamental understanding again paves the way for tailoring application solutions with novel photoresponsive materials.
CRIS-Team Scopus Importer:2023-12-29

Photoactive preorganized subphthalocyanine-based molecular tweezers for selective complexation of fullerenes - Zango, Germán; Krug, Marcel; Krishna, Swathi; Mariñas, Víctor; Clark, Timothy; Martinez-Diaz, M. Victoria; Guldi, Dirk Michael; Torres, Tomás (Chemical Science, 2020)
The development of new chromophoric receptors capable of binding curved carbon nanostructures is central to the quest for improved fullerene-based organic photovoltaics. We herein report the synthesis and characterization of a subphthalocyanine-based multicomponent ensemble consisting of two electron-rich SubPc-monomers rigidly attached to the convex surface of an electron-poor SubPc-dimer. Such a unique configuration, especially in terms of the two SubPc-monomers, together with the overall stiffness of the linker, endows the multicomponent system with a well-defined tweezer-like topology to efficiently embrace a fullerene in its inner cavity. The formation of a 1 : 1 complex was demonstrated in a variety of titration studies with either C60 or C70. In solution, the underlying association constants were of the order of 105 M-1. Detailed physicochemical experiments revealed a complex scenario of energy- and electron-transfer processes upon photoexcitation in the absence and presence of fullerenes. The close proximity of the fullerenes to the electron-rich SubPcs enables a charge shift from the initially formed reduced SubPc-dimer to either C60 to C70.
CRIS-Team Scopus Importer:2020-04-17

Photochem—A New Multidisciplinary Open Access Journal for Photochemistry - Guldi, Dirk Michael (Photochem, 2021)
CRIS-Team Scopus Importer:2024-12-16

Photoinduced charge transfer in porphyrin-cobaloxime and corrole-cobaloxime hybrids - Peuntinger, Katrin; Lazarides, Theodore; Dafnomili, Dimitra; Charalambidis, Georgios; Landrou, Georgios; Kahnt, Axel; Sabatini, Randy Pat; Mccamant, David W.; Gryko, Daniel T.; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Journal of Physical Chemistry C, 2013)
We report on the synthesis of hybrid molecules consisting of a porphyrin or corrole chromophore axially coordinated to a [Co(dmgH) (Cl)] (dmg = dimethylglyoxime) unit via a pyridine group as potential hydrogen forming entities in HO/THF medium. Photophysical, electrochemical, and pulse radiolysis studies on the hybrids and/or their separate components show that selective excitation of the porphyrin or corrole chromophore in its first singlet excited state leads to fast charge separation due to chromophore to cobalt electron transfer. However, this charge separation is followed by even faster charge recombination thereby preventing the accumulation of a reduced cobalt species which would lead to hydrogen production. It is important, nevertheless, that addition of a sacrificial electron donor slows the charge recombination down. In light of the latter it comes as hardly surprising that the photocatalysis experiments in the presence of a sacrificial electron donor (i.e., triethylamine) show modest rates of hydrogen production. © 2012 American Chemical Society.

Photoinduced electron transfer in a meso-linked Zn(II)porphyrin-Zn(II) phthalocyanine/C60-pyridyl supramolecular system - Urbani, Maxence; Osati, Samira; Kuhri, Susanne; Guldi, Dirk Michael; Torres, Tomas (Journal of Porphyrins and Phthalocyanines, 2013)
A non-covalent supramolecular complex combining porphyrin (Por), phthalocyanine (Pc) and fullerene [C], was obtained through zinc metal-pyridine coordination between a covalently meso-linked heterodimer ZnPor-ZnPc (4) and a N-pyridylfulleropyrrolidine derivative (5). The complexation was studied in toluene by absorption and fluorescence binding studies, and evidenced that the coordination of the N-pyridylfulleropyrrolidine (5) occurs preferentially through the zinc ion center of ZnPc (log K > 6.0) rather than ZnPor (log K = 5.23). Steady-state and time-resolved spectroscopies evidenced that upon selective excitation of either the Por, or the Pc moiety in [(ZnPor-ZnPc)∪C], the singlet excited state of Pc was generated efficiently in both cases (either from singlet-singlet energy transfer from Por* to Pc, or directly after selective excitation of the Pc moiety). Next, an electron transfer occurred from the Pc* to the C to generate the charge-separated specie [(ZnPor-ZnPc )∪C]. Finally, the back electron transfer afforded the Pc triplet excited state rather than the ground state. The introduction of a covalent meso-linkage between Por and Pc in the heterodimer 4 and in the supramolecular assembly 4∪5 induces appreciable differences toward the photo-induced processes and the binding constants in comparison with other β-covalently linked analogue systems. © 2013 World Scientific Publishing Company.

Photoinduced Electron Transfer in a Zinc Phthalocyanine–Fullerene Conjugate Connected by a Long Flexible Spacer - Lederer, Marcus; Ince, Mine; Victoria Martinez-Diaz, M.; Torres, Tomas; Guldi, Dirk Michael (ChemPlusChem, 2016)
A hexadodecyl-substituted zinc phthalocyanine covalently linked through a flexible spacer to a fullerene—ZnPc−C60—has been investigated regarding electron transfer from the photoexcited, electron-donating ZnPc to the electron-accepting C60. While ground-state interactions between electron donor and acceptor within ZnPc−C60 could not be detected via steady-state absorption spectroscopy, clear proof for excited-state interactions came from steady-state fluorescence spectroscopy. To this end, the fluorescence in ZnPc−C60 is strongly quenched with quantum yields in THF as low as 0.05. Insight into excited-state electron-transfer deactivation within ZnPc−C60 came from time-resolved femtosecond transient absorption spectroscopy. For example, upon exclusive excitation of the phthalocyanine within the ZnPc−C60 conjugate, a set of transients evolve featuring, on the one hand, the signature of the one-electron oxidized ZnPc radical cation and, on the other hand, of the one-electron reduced C60 radical anion. The analysis of the corresponding dynamics in chlorobenzene resulted in lifetimes for charge-separation and charge-recombination of 7.4 ps and 2.2 ns, respectively.
CRIS-Team Scopus Importer:2023-03-07
Keywords: fullerenes; liquid crystals; photoinduced charge transfer; phthalocyanines

Photoinduced electron transfer in multicomponent arrays of a π-stacked fullerene porphyrin dyad and diazabicyclooctane or a fulleropyrrolidine ligand - Guldi, Dirk Michael; Luo, Chuping; Da Ros, T.; Prato, Maurizio; Dietel, Elke; Hirsch, Andreas (Chemical Communications, 2000)
The kinetics of photoinduced electron transfer in new multicomponent arrays of a π-stacked fullerene porphyrin dyad and diazabicyclooctane or a fulleropyrrolidine ligand have been determined and depend on the molecular architecture.

Photoinduced Electron Transfer in Multicomponent Fullerene-Porphyrin Arrays - Luo, Chuping; Guldi, Dirk Michael; Da Ros, T.; Prato, Maurizio; Dietel, Elke; Hirsch, Andreas (Fullerenes for the New Millenium, 2001)

Photoinduced Intervalence Charge Transfers: Spectroscopic Tools to Study Fundamental Phenomena and Applications - Ramirez-Wierzbicki, Ivana; Cotic, Agustina; Cadranel, Alejandro (ChemPhysChem, 2022)
The exploitation of excited state chemistry for solar energy conversion or photocatalysis has been continuously increasing, and the needs of a transition to a sustainable human development indicate this trend will continue. In this scenario, the study of mixed valence systems in the excited state offers a unique opportunity to explore excited state electron transfer reactivity, and, in a broader sense, excited state chemistry. This Concept article analyzes recent contributions in the field of photoinduced mixed valence systems, i. e. those where the mixed valence core is absent in the ground state but created upon light absorption. The focus is on the utilization of photoinduced intervalence charge transfer bands, detected via transient absorption spectroscopy, as key tools to study fundamental phenomena like donor/acceptor inversion, hole delocalization, coexistence of excited states and excited state nature, together with applications in molecular electronics.
CRIS-Team Scopus Importer:2022-08-12
Keywords: donor-acceptor interactions; excited-state dynamics; photoinduced intervalence charge transfer; photoinduced mixed valence; transient absorption spectroscopy

Photon- and Charge-Management in Advanced Energy Materials: Combining 0D, 1D, and 2D Nanocarbons as well as Bulk Semiconductors with Organic Chromophores - Cadranel, Alejandro; Haines, Philipp; Kaur, Ramandeep; Menon, Arjun; Münich, Peter Wilhelm; Schol, Peter; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
In this contribution, seminal works in the area of photon- and charge-management are highlighted with focus on covalent electron donor-acceptor conjugates built around porphyrins (Ps), on one hand, and 0D, 1D, and 2D nanocarbons, on the other hand. Photons in these conjugates are managed by Ps, while 0D, 1D, and 2D nanocarbons serve as the active component, which enable managing charges. With a few leading examples, it can be explored much beyond the simple photon- and charge-management characterization and emphasize photovoltaics and photocatalysis to convert and store energy. This contribution concludes by highlighting recent progress in mixing and matching the unique charge-management features of nanocarbons in the design of multidimensional nanocarbons.
CRIS-Team Scopus Importer:2020-12-11
Keywords: charge management; nanocarbons; photon management; solar-energy conversion

Photophysical characterization of a ruthenium-based tetrameric pentacene complex - Hou, Yuxuan; Papadopoulos, Ilias; Ferguson, Michael J.; Jux, Norbert; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2023)
The synthesis of a ruthenium(II) tetramer (Ru(Lpc)4Cl2) bearing pyridyl pentacene-based ligands and its corresponding model complex lacking pentacene moieties (Ru(Lref)4Cl2) is presented. The formation of these tetramers is corroborated by 1H, 13C NMR, and IR spectroscopies, as well as X-ray crystallography and mass spectrometry. Photophysical properties of the tetramers are probed by steady-state and time-resolved transient absorption spectroscopy. Steady-state absorption and fluorescence assays suggest weak ground-state interactions between the pentacene moieties of Ru(Lpc)4Cl2 and sizeable metal-to-ligand interactions, which are ruthenium-to-pentacene based. Time-resolved transient absorption measurements reveal an ultrafast singlet-to-triplet transition that occurs on the femtosecond timescale and that yields vibrationally hot and solvent unrelaxed triplet excited states. After relaxation, these triplet excited states deactivate back to the ground state in less than 3 μs. These observations lead us to conclude that intersystem crossing outperforms photophysical processes such as singlet fission.
CRIS-Team Scopus Importer:2023-05-26
Keywords: excited state dynamics; intersystem crossing; pentacene; ruthenium complex; singlet fission

Photophysical, electrochemical, and mesomorphic properties of a liquid-crystalline [60]fullerene-peralkylated ferrocene dyad - Campidelli, Stephane; Severac, Marjorie; Scanu, David; Deschenaux, Robert; Vazquez, Ester; Milic, Dragana; Prato, Maurizio; Carano, Maurizio; Marcaccio, Massimo; Paolucci, Francesco; Rahman, Aminur; Guldi, Dirk Michael (Journal of Materials Chemistry, 2008)
Two fullerene-peralkylated ferrocene derivatives were synthesized: (1) a liquid-crystalline dyad (compound 1) was obtained by introduction of nonamethyl ferrocene into a liquid-crystalline fullerene derivative and (2) a reference compound (compound 2) was synthesized by attachment of nonamethyl ferrocene to a fulleropyrrolidine. The liquid-crystalline dyad displayed an enantiotropic smectic A phase from 57 to 155 °C. Oxidation and reduction processes were investigated by cyclic voltammetry, and were in agreement with the electrochemical characteristics of the redox-active units (peralkylated ferrocene, fullerene, dendrimer). Photoinduced electron transfer from ferrocene derivative to fullerene was identified. © The Royal Society of Chemistry.

Photophysics and transient nonlinear optical response of donor-[60]fullerene hybrids - Aloukos, Panagiotis; Iliopoulos, Konstantinos; Couris, Stelios; Guldi, Dirk Michael; Sooambar, Chloe; Mateo-Alonso, Aurelio; Nagaswaran, Praveen Ganesh; Bonifazi, Davide; Prato, Maurizio (Journal of Materials Chemistry, 2011)
The photophysical properties of some recently synthesized donor-[60]fullerene hybrids, porphyrinyl- and ferrocenyl-[60]fullerene dyads, are studied by means of absorption, fluorescence and femtosecond transient absorption spectroscopy. The formation of charge transfer states is experimentally confirmed, while it is shown that an efficient photoinduced intra-molecular electron-transfer process takes place between the donors (i.e. porphyrin, ferrocene) and the acceptor (i.e. [60]fullerene). In addition, the transient nonlinear optical response of these [60]fullerene dyads is investigated under visible nanosecond laser excitation. Both dyads were found to exhibit significantly enhanced second hyperpolarizability (γ) compared to that of unfunctionalized [60]fullerene, while the refractive part of their nonlinearity dominated their nonlinear optical response in contrast to what has been observed for pristine fullerene and other functionalized fullerenes. Moreover, their optical limiting action is investigated both experimentally and by means of a five-level model. The results are discussed and compared with other literature reports. © 2011 The Royal Society of Chemistry.

Photoreactions of Sc3N@C80 with Disilirane, Silirane, and Digermirane: A Photochemical Method to Separate Ih and D5h Isomers - Kako, Masahiro; Miyabe, Kyosuke; Fukazawa, Shinpei; Kanzawa, Shinji; Yasui, Masanori; Yamada, Michio; Maeda, Yutaka; Slanina, Zdeněk; Uhlík, Filip; Adamowicz, Ludwik; Papadopoulos, Ilias; Guldi, Dirk Michael; et al. (Photochem, 2022)
Under photoirradiation, Sc3N@Ih-C80 reacted readily with disilirane 1, silirane 4, and digermirane 7 to afford the corresponding 1:1 adducts, whereas Sc3N@D5h-C80 was recovered without producing those adducts. Based on these results, we described a novel method for the exclusive separation of Ih and D5h isomers of Sc3N@C80. The method includes three procedures: selective derivatization of Sc3N@Ih-C80 using 1, 4, and 7, facile HPLC separation of pristine Sc3N@D5h-C80 and Sc3N@Ih-C80 derivatives, and thermolysis of Sc3N@Ih-C80 derivatives to collect pristine Sc3N@Ih-C80. In addition, laser flash photolysis experiments were conducted to elucidate the reaction mechanism. Decay of the transient absorption of 3Sc3N@Ih-C80* was observed to be enhanced in the presence of 1, indicating the quenching process. When Sc3N@D5h-C80 was used, the transient absorption was much less intensive. Therefore, the quenching of 3Sc3N@D5h-C80* by 1 could not be confirmed. Furthermore, we applied time-dependent density functional theory (TD-DFT) calculations of the photoexcited states of Sc3N@C80 to obtain insights into the reaction mechanism.
CRIS-Team Scopus Importer:2024-12-16
Keywords: density functional theory; digermirane; disilirane; metallofullerene; photophysics; Sc; silirane

Phthalocyanine-corannulene conjugates: Synthesis, complexation studies with a pyridyl-functionalized C 6 0 fullerene, and photophysical properties - Suanzes, Juan A.; Chaurasia, Sumit; Krick Calderon, Rafael; Guldi, Dirk Michael; Bottari, Giovanni; Torres, Tomás (Journal of Porphyrins and Phthalocyanines, 2019)
We report here the synthesis and characterization of some novel Zn(II)phthalocyanine (Pc)-corannulene conjugates and their complexation ability towards a pyridyl-functionalized C60 fullerene through metal-ligand supramolecular interactions. Steady-state and time-resolved photophysical studies carried out on these electron donor-acceptor (D-A) Zn(II)Pc-corannulene/C60 ensembles indicate the formation of photogenerated charge-separated species. Interestingly, a stabilization of the photoinduced charge-separated state is observed in the case of the D-A supramolecular complexes comprising the corannulene-substituted Zn(II)Pcs when compared to their non-corannulene functionalized Zn(II)Pc analogues. We rationalize this stabilizing effect of the charge-separated state exerted by the corannulene as a result of the increased π-extension and augmented hydrophobicity of the Zn(II)Pc core by the covalently-linked polyaromatic hydrocarbon (PAH) fragment.
CRIS-Team Scopus Importer:2019-11-05
Keywords: C 6 0 fullerene; corannulene; electron donor-acceptor systems; electron transfer; metal-ligand interactions; phthalocyanine

Phthalocyanine-Perylenediimide Cart Wheels - Fernandez-Ariza, Javier; Krick Calderon, Rafael; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2016)
The electronic features of Zn(II) and Ru(II) phthalocyanines (Pcs) have been modulated by direct peripheral attachment of up to eight ferrocenes. The presence of peripheral ferrocenes noticeably impacts the electronic properties of the corresponding ZnPc and RuPc complexes 7, 12 and 9, 15, respectively - a notion that is supported by optical spectroscopy with bathochromic shifts of up to 8-10 nm per ferrocene unit. Cyclic voltammetry and optical spectroscopy reveal long-distance (10-11 bonds) electronic interaction between ferrocene units. The ZnPc and RuPc complexes have been integrated into a series of orthogonal, supramolecular bis(phthalocyanine)-perylenediimide electron donor-acceptor conjugates, 2a,b and 3a,b. In these cart-wheel-shaped arrays, coordination of ditopic perylenediimide 16, containing two pyridyl substituents at its imido positions, enabled selective interactions with the metal centers of phthalocyanines 7, 12, 9, and 15. The presence of ferrocenes in, for example, Zn complexes 2a and 3a triggers a fast energy transfer from the excited-state PDI to ZnPc. In the RuPc-PDI conjugates, substitution with ferrocenes produces a slight acceleration of the charge separation upon photoexcitation of the PDI chromophore. However, charge recombination is accelerated by 2 orders of magnitude in ferrocene-containing conjugates when compared to that in the analogous tert-butyl-substituted array 1b.
CRIS-Team Scopus Importer:2023-03-07

Phthalocyanine-pyrene conjugates: A powerful approach toward carbon nanotube solar cells - Bartelmeß, Jürgen; Ballesteros, Beatriz; De La Torre, Gema; Kießling, Daniel; Campidelli, Stephane; Prato, Maurizio; Torres, Tomas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2010)
In the present work, a new family of pyrene (Py)-substituted phthalocyanines (Pcs), i.e., ZnPc-Py and H Pc-Py, were designed, synthesized, and probed in light of their spectroscopic properties as well as their interactions with single-wall carbon nanotubes (SWNTs). The pyrene units provide the means for non-covalent functionalization of SWNTs via π-π interactions. Such a versatile approach ensures that the electronic properties of SWNTs are not impacted by the chemical modification of the carbon skeleton. The characterization of ZnPc-Py/SWNT and H Pc-Py/SWNT has been performed in suspension and in thin films by means of different spectroscopic and photoelectrochemical techniques. Transient absorption experiments reveal photoinduced electron transfer between the photoactive components. ZnPc-Py/SWNT and H Pc-Py/SWNT have been integrated into photoactive electrodes, revealing stable and reproducible photocurrents with monochromatic internal photoconversion efficiency values for H Pc-Py/SWNT as large as 15 and 23% without and with an applied bias of +0.1 V. © 2010 American Chemical Society.

Ping-Pong Energy Transfer in Covalently Linked Porphyrin-MoS2 Architectures - Canton-Vitoria, Ruben; Scharl, Tobias; Stergiou, Anastasios; Cadranel, Alejandro; Arenal, Raul; Guldi, Dirk Michael; Tagmatarchis, Nikos (Angewandte Chemie International Edition, 2020)
Molybdenum disulfide nanosheets covalently modified with porphyrin were prepared and fully characterized. Neither the porphyrin absorption nor its fluorescence was notably affected by covalent linkage to MoS2. The use of transient absorption spectroscopy showed that a complex ping-pong energy-transfer mechanism, namely from the porphyrin to MoS2 and back to the porphyrin, operated. This study reveals the potential of transition-metal dichalcogenides in photosensitization processes.
CRIS-Team WoS Importer:2020-02-07

Polyhydrogenated Graphene: Excited State Dynamics in Photo- and Electroactive Two-Dimensional Domains - Strauß, Volker; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2015)
Understanding the phenomenon of intense photoluminescence in carbon materials such as hydrogenated graphene, graphene nanoribbons, and so forth is at the forefront of investigations. In this study, six different types of hydrogenated graphene (phG) produced from different starting materials were fully characterized in terms of structure and optical spectroscopy. Comprehensive photoluminescence lifetime analyses of phGs were conducted by combining time-correlated single-photon counting with steady-state fluorescence spectroscopy and femtosecond transient absorption spectroscopy. The conclusion drawn from these assays is that graphene islands with diameters in the range from 1.1 to 1.75 nm reveal band gap photoluminescence between 450 and 800 nm. As a complement, phGs were implemented in hybrids with water-soluble electron accepting perylenediimides (PDIs). By virtue of mutual π-stacking and charge transfer interactions with graphene islands, PDIs assisted in stabilizing aqueous dispersion of phG. Implicit in these ground state interactions is the formation of 300 ps lived charge separated states once photoexcited.

Polyoxometalate W18O56XO6 clusters with embedded redox-active main-group templates as localized inner-cluster radicals - Vila-Nadal, Laia; Peuntinger, Katrin; Busche, Christoph; Yan, Jun; Lüders, Daniela; Long, De-Liang; Poblet, Josep M.; Guldi, Dirk Michael; Cronin, Leroy (Angewandte Chemie International Edition, 2013)
Non-mixed-valent reduced polyoxometalates, namely WO XO Dawson-like clusters (X=I or Te ) with a localized redox active template have been synthesized and redox properties compared with the pure tungsten control (that is, X=W ). Upon one-electron reduction, the electron localizes on the main-group element, giving I or Te, respectively. These clusters have potential as a new type of electron-transfer reagent. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Porphyrin Antennas on Carbon Nanodots: Excited State Energy and Electron Transduction - Arcudi, Francesca; Strauß, Volker; Dordevic, Luka; Cadranel, Alejandro; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2017)
We report the synthesis and electron donor-acceptor features of a novel nanohybrid, in which the light-harvesting and electron-donating properties of a meso-tetraarylporphyrin (TArP) are combined with the electron-accepting features of nitrogen-doped carbon nanodots (NCNDs). In particular, in an ultrafast process (>1012 s-1), visible-light excitation transforms the strongly quenched porphyrin singlet excited states into short-lived (225 ps) charge-separated states. On the other hand, ultraviolet light excitation triggers a non-resolvable transduction of singlet excited state energy from the NCNDs to the porphyrins, followed by the same charge separation observed upon visible light excitation.
EAM Import::2019-03-08

Porphyrin Donor and Tunable Push-Pull Acceptor ConjugatesExperimental Investigation of Marcus Theory - Reekie, Tristan A.; Sekita, Michael; Urner, Lorenz M.; Bauroth, Stefan; Ruhlmann, Laurent; Gisselbrecht, Jean-Paul; Boudon, Corinne; Trapp, Nils; Clark, Timothy; Guldi, Dirk Michael; Diederich, Francois (Chemistry - A European Journal, 2017)
We report on a series of electron donor-acceptor conjugates incorporating a Zn-II-porphyrin-based electron donor and a variety of non-conjugated rigid linkers connecting to push-pull chromophores as electron acceptors. The electron acceptors comprize multicyanobutadienes or extended tetracyanoquinodimethane analogues with first reduction potentials ranging from -1.67 to -0.23V vs. Fc(+)/Fc in CH2Cl2, which are accessible through a final-step cycloaddition-retroelectrocyclization (CA-RE) reaction. Characterization of the conjugates includes electrochemistry, spectroelectrochemistry, DFT calculations, and photophysical measurements in a range of solvents. The collected data allows for the construction of multiple Marcus curves that consider electron-acceptor strength, linker length, and solvent, with data points extending well into the inverted region. The enhancement of electron-vibration couplings, resulting from the rigid spacers and, in particular, multicyano-groups in the conformationally highly fixed push-pull acceptor chromophores affects the charge-recombination kinetics in the inverted region drastically.
Keywords: donor-acceptor systems; electron transfer; Marcus theory; photochemistry; porphyrinoids

Porphyrin-phthalocyanine/pyridylfullerene supramolecular assemblies - Pereira, Ana M. V. M.; Hausmann, Anita; Tome, Joao P. C.; Trukhina, Olga; Urbani, Maxence; Neves, Maria G. P. M. S.; Cavaleiro, Jose A. S.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2012)
The synthesis and photophysical properties of several porphyrin (P)-phthalocyanine (Pc) conjugates (P-Pc; 1-3) are described, in which the phthalocyanines are directly linked to the β-pyrrolic position of a meso-tetraphenylporphyrin. Photoinduced energy- and electron-transfer processes were studied through the preparation of H P-ZnPc, ZnP-ZnPc, and PdP-ZnPc conjugates, and their assembly through metal coordination with two different pyridylfulleropyrrolidines (4 and 5). The resulting electron-donor-acceptor hybrids, which were formed by axial coordination of compounds 4 and 5 with the corresponding phthalocyanines, mimicked the fundamental processes of photosynthesis; that is, light harvesting, the transduction of excited-state energy, and unidirectional electron transfer. In particular, photophysical studies confirmed that intramolecular energy-transfer resulted from the S excited state as well as from the S excited state of the porphyrins to the energetically lower-lying phthalocyanines, followed by an intramolecular charge-transfer to yield P-Pc ·C . This unique sequence of processes opens the way for solar-energy-conversion processes. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Porphyrins as Multifunctional Interconnects in Networks of ZnO Nanoparticles and their Application in Dye-Sensitized Solar Cells - Düring, Jasmin; Kunzmann, Andreas; Killian, Manuela; Costa, Ruben Dario; Guldi, Dirk Michael; Gröhn, Franziska (Chemphotochem, 2018)
ZnO nanoparticles of 2.6 to 4.0 nm in size were interconnected by meso-tetra(4-carboxyphenyl)porphyrin (TCPP) for the realization of novel ZnO–TCPP networks, reaching lateral dimensions ranging from 50 to 800 nm. The resulting ZnO–TCPP networks were probed by dynamic light-scattering experiments, transmission electron microscopy, and spectroscopy, and were also tested as photoactive top layers in TiO2 and ZnO dye-sensitized solar cells (DSSCs). Control over these ZnO–TCPP networks on top of the semiconductor electrodes enables efficiency increases of 10 % and 46 % for TiO2- and ZnO-based photoelectrodes, respectively. In other words, effects, such as reducing the electron recombination and increasing the electron lifetime, document the benefits of using tailored functional hybrid systems in DSSCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: dye-sensitized solar cells; electron transfer; hybrid assemblies; porphyrins; semiconductor nanoparticles

Potassium Poly(Heptazine Imide): Transition Metal-Free Solid-State Triplet Sensitizer in Cascade Energy Transfer and [3+2]-cycloadditions - Savateev, Aleksandr; Tarakina, Nadezda V.; Strauss, Volker; Hussain, Tanveer; ten Brummelhuis, Katharina; Sánchez Vadillo, José Manuel; Markushyna, Yevheniia; Mazzanti, Stefano; Tyutyunnik, Alexander P.; Walczak, Ralf; Oschatz, Martin; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2020)
Polymeric carbon nitride materials have been used in numerous light-to-energy conversion applications ranging from photocatalysis to optoelectronics. For a new application and modelling, we first refined the crystal structure of potassium poly(heptazine imide) (K-PHI)—a benchmark carbon nitride material in photocatalysis—by means of X-ray powder diffraction and transmission electron microscopy. Using the crystal structure of K-PHI, periodic DFT calculations were performed to calculate the density-of-states (DOS) and localize intra band states (IBS). IBS were found to be responsible for the enhanced K-PHI absorption in the near IR region, to serve as electron traps, and to be useful in energy transfer reactions. Once excited with visible light, carbon nitrides, in addition to the direct recombination, can also undergo singlet–triplet intersystem crossing. We utilized the K-PHI centered triplet excited states to trigger a cascade of energy transfer reactions and, in turn, to sensitize, for example, singlet oxygen (1O2) as a starting point to synthesis up to 25 different N-rich heterocycles.
CRIS-Team Scopus Importer:2020-06-16
Keywords: carbon nitrides; organic photocatalysis; potassium poly(heptazine imide); singlet oxygen; solid-state sensitizer

Powering reductive charge shift reactions - Linking fullerenes of different electron acceptor strength to secure an energy gradient - Villegas, Carmen; Luis Delgado, Juan; Bouit, Pierre-Antoine; Grimm, Bruno; Seitz, Wolfgang; Martin, Nazario; Guldi, Dirk Michael (Chemical Science, 2011)
We report here on one of the rare cases that realizes a reductive charge shift from a primary electron acceptor (C ) to a secondary electron acceptor (C ) in a ZnP-C -C conjugate. Initially, charge separation evolves from an excited state electron donor (ZnP). By far the most far reaching benefit from such a reductive pathway is a marked slow down of the energy wasting charge recombination when compared to the ZnP-C conjugate (i.e., picoseconds versus nanoseconds). © The Royal Society of Chemistry 2011.

p-Phenyleneethynylene molecular wires: influence of structure on photoinduced electron-transfer properties. - Wielopolski, Mateusz; Atienza, Carmen; Clark, Timothy; Guldi, Dirk Michael; Martín, Nazario (Chemistry - A European Journal, 2008)
A series of donor-acceptor arrays (exTTF-oPPE-C ) containing π-conjugated oligo(phenyleneethynylene) wires (oPPE) of different length between π-extended tetrathiafulvalene (exTTF) as electron donor and fullerene (C ) as electron acceptor has been prepared by following a convergent synthesis. The key reaction in these approaches is the bromo-iodo selectivity of the Hagihara-Sonogashira reaction and the deprotecting of acetylenes with different silyl groups to afford the corresponding donor-acceptor conjugates in moderate yields. The electronic interactions between the three electroactive species were determined by using UV-visible spectroscopy and cyclic voltammetry. Our studies clearly confirm that, although the C units are connected to the exTTF donor through π-conjugated oPPE frameworks, no significant electronic interactions are observed in the ground state. Theoretical calculations predict how a simple exchange from C=C double bonds (i.e., oligo(p-phenylenevinylene) to C≡C triple bonds (i.e., oPPE) in the electron donor-acceptor conjugates considerably alters long-range electron transfer. Photoexcitation of exTTF-oPPE-C leads to the following features: a transient photoproduct with maxima at 660 and 1000 nm, which are unambiguously attributed to the photolytically generated radical-ion-pair state, [exTTF -oPPE- C ]. Both charge-separation and charge-recombination processes give rise to a molecular-wire behaviour of the oPPE moiety with an attenuation factor (β) of (0.2 ±0.05) Å . © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Precise control of intramolecular charge-transport: The interplay of distance and conformational effects - Schubert, Christina; Wielopolski, Mateusz; Mewes, Lars-Hendrik; De Miguel Rojas, Gustavo; Van Der Pol, Cornelia; Moss, Kathryn C.; Bryce, Martin; Moser, Jacques E.; Guldi, Dirk Michael; Clark, Timothy (Chemistry - A European Journal, 2013)
A new series of donor-bridge-acceptor (D-B-A) compounds consisting of π-conjugated oligofluorene (oFL) bridges between a ferrocene (Fc) electron-donor and a fullerene (C) electron-acceptor have been synthesized. In addition to varying the length of the bridge (i.e., mono- and bi-fluorene derivatives), four different ways of linking ferrocene to the bridge have been examined. The Fc moiety is linked to oFL: 1) directly without any spacer, 2) by an ethynyl linkage, 3) by a vinylene linkage, and 4) by a p-phenylene unit. The electronic interactions between the electroactive species have been characterized by cyclic voltammetry, absorption, fluorescence, and transient absorption spectroscopy in combination with quantum chemical calculations. The calculations reveal exceptionally close energy-matching between the Fc and the oFL units, which results in strong electronic-coupling. Hence, intramolecular charge-transfer may easily occur upon exciting either the oFLs or Fcs. Photoexcitation of Fc-oFL-C conjugates results in transient radical-ion-pair states. The mode of linkage of the Fc and FL bridge has a profound effect on the photophysical properties. Whereas intramolecular charge-separation is found to occur rather independently of the distance, the linker between Fc and oFL acts (at least in oFL) as a bottleneck and significantly impacts the intramolecular charge-separation rates, resulting in beta values between β 0.08 and 0.19 Å. In contrast, charge recombination depends strongly on the electron-donor-acceptor distance, but not at all on the linker. A value of β (0.35±0.01 Å) was found for all the systems studied. Oligofluorenes prove, therefore, to be excellent bridges for probing how small structural variations affect charge transport in D-B-A systems. Finely tuned transfer: Chemical modification of the oligo-fluorene linkers between Fc and C units enables fine-tuning of photoinduced charge-transfer processes in new donor-bridge-acceptor conjugates (see illustration). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Preface - JSS Focus Issue on Porphyrins, Phthalocyanines, and Supramolecular Assemblies in Honor of Karl M. Kadish - D'Souza, Francis; Guldi, Dirk Michael; Paolesse, Roberto; Torres, Tomas; Rajeshwar, Krishnan (ECS Journal of Solid State Science and Technology, 2020)
CRIS-Team Scopus Importer:2020-10-23

Pre-Planarized Triphenylamine-Based Linear Mixed-Valence Charge-Transfer Systems - Krug, Marcel; Fröhlich, Nina; Fehn, Dominik; Vogel, Alexander; Rominger, Frank; Meyer, Karsten; Clark, Timothy; Kivala, Milan; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2021)
Three linear dimers with two redox-active planarized triphenylamines were synthesized and their structures verified by X-ray crystallography. Their radical cations, which exhibit electron self-exchange between the two redox centers, are of great interest. This process was thoroughly investigated by means of electron paramagnetic resonance spectroscopy, absorption spectroscopy, and (time-dependent) density functional theory calculations. A comparison of the key parameters of electron transfer with non-planarized nitrogen-centered building blocks emphasizes the impact of using redox centers with low internal reorganization energies. However, the distance-dependence attenuation factor of the super-exchange mechanisms remains similar.
CRIS-Team WoS Importer:2021-02-26

Probability distributions in quadrupole ion traps - Neugebauer, Thomas; Drewello, Thomas (International Journal of Mass Spectrometry, 2021)
The solution to Mathieu's equation was modified and combined to only one single sine function. In this form, the cumulative probability functions for a fixed RF-phase can be determined as arcsine distributions. The probability of a normalized position u/umax or normalized velocity u˙/u˙max is relative to 1/1−(u/umax)2, u˙/u˙max respectively. This corrects reference descriptions present in the literature, which stated the probability to be proportional to 1−(u/umax)2. Resulting probability plots show that ions that are heavy on the relative mass scale of quadrupole ion traps, are more likely to be found close to the maximum of their oscillation amplitude. Light ions are more likely to be found at the center of their oscillation. The velocity distributions show that the likeliest velocity converges for low q-values to the mean-square velocity but splits into two likely velocity regions with increasing q-value. It is further emphasized, that these distributions describe the probability of a single ion and in order to describe the behavior of an ensemble of ions, it is inevitably needed to define a distribution of oscillation amplitudes umax.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Hill's equation; Mathieu's equation; Phase-space ellipses; Probability distributions; Quadrupole ion trap; twiss parameters

Probing Charge Management across the π-Systems of Nanographenes in Regioisomeric Electron Donor-Acceptor Architectures - Hölzel, Helen; Haines, Philipp; Kaur, Ramandeep; Lungerich, Dominik; Jux, Norbert; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)
Inspired by light-induced processes in nature to mimic the primary events in the photosynthetic reaction centers, novel functional materials combine electron donors and acceptors, i.e., (metallo)porphyrins (ZnP) and fullerenes (C60), respectively, with emerging materials, i.e., nanographenes. We utilized hexa-peri-hexabenzocoronene (HBC) due to its versatility regarding functionalization and physicochemical properties, to construct three regioisomeric ZnP-HBC-C60 conjugates, which foster geometrical diversity by arranging ZnP and C60 in ortho-, meta-, and para-positions to each other. The corresponding hexaarylbenzene (HAB) motifs, with an interrupted π-system, were also prepared. Transient absorption measurements disclosed the fast population of charge transfer as well as singlet and triplet charge-separated states. With the help of density functional theory (DFT) calculations, we further conceive the communication across the HBCs and HABs. This work reveals the impact of both the geometrical arrangement with respect to through-space versus through-bond interactions and the structural rigidity/flexibility on the charge management across the different π-systems.
CRIS-Team Scopus Importer:2022-06-10

Probing charge transfer in benzodifuran-C60 dumbbell-type electron donor-acceptor conjugates: Ground- and excited-state assays - Li, Hui; Schubert, Christina; Dral, Pavlo; Costa, Ruben Dario; La Rosa, Andrea; Thüring, Jürg; Liu, Shi-Xia; Yi, Chenyi; Filippone, Salvatore; Martín, Nazario; Decurtins, Silvio; Clark, Timothy; et al. (ChemPhysChem, 2013)
Rigid electron donor-acceptor conjugates (1-3) that combine π-extended benzodifurans as electron donors and C molecules as electron acceptors with different linkers have been synthesized and investigated with respect to intramolecular charge-transfer events. Electrochemistry, fluorescence, and transient absorption measurements revealed tunable and structure-dependent charge-transfer processes in the ground and excited states. Our experimental findings are underpinned by density-functional theory calculations. Dumbbell arrays: A benzodifuran (BDF) donor is for the first time fused to two C molecules by different linkers to form triads 1-3 (see figure). Their redox behavior, absorption, fluorescence emission, and photoinduced intramolecular charge-transfer events have been investigated experimentally and theoretically. The lifetime of the resulting charge-separated state varies distinctly with the polarity of the solvents and the distance between the BDF and C units. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Probing Supramolecular Interactions between a Crown Ether Appended Zinc Phthalocyanine and an Ammonium Group Appended to a C60 Derivative - Lederer, Marcus; Hahn, Uwe; Strub, Jean-Marc; Cianferani, Sarah; Van Dorsselaer, Alain; Nierengarten, Jean-Francois; Torres, Tomas; Guldi, Dirk Michael (Chemistry - A European Journal, 2016)
Self-assembly driven by crown ether complexation of zinc phthalocyanines equipped with one 18-crown-6 moiety and fullerenes bearing an ammonium head group afforded a novel donor-acceptor hybrid. In reference experiments, fullerenes containing a Boc-protected amine functionality have been probed. The circumvention of zinc phthalocyanine aggregation is important for the self-assembly, which required the addition of pyridine. From absorption and fluorescence titration assays, which provided sound and unambiguous evidence for mutual interactions between the electron donor and the electron acceptor within the hybrids, association constants in the order of 8.0×105 m-1 have been derived. The aforementioned is based on 1:1 stoichiometries, which have been independently confirmed by Job's plot measurements. In the excited state, which has been examined by transient absorption experiments, intermolecular charge separation evolves from the photoexcited zinc phthalocyanine to the fullerene subunit and leads to short-lived charge-separated states. Interestingly, photoexcitation of zinc phthalocyanine dimers/aggregates can also be followed by an intermolecular charge separation between vicinal phthalocyanines. These multicomponent supramolecular ensembles have also been shown by in-depth electrospray ionization mass spectrometry (ESI-MS) studies, giving rise to the formation and detection of a variety of non-covalently linked species.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charge transfer; crown ethers; donor-acceptor systems; fullerenes; mass spectrometry; phthalocyanines

Production of small binary carbon clusters by laser ablation of thin films of derivatised fullerenes - Wallis, Darren; Vasil’ev, Yu; Clipston, Nigel; Lohbach, Anatolii; Hirsch, Andreas; Boltalina, Olga V.; Lenz, Christof; Drewello, Thomas (International Journal of Mass Spectrometry, 2003)
The distribution of small carbon clusters derived by laser ablation (laser desorption/ionization) of thin films of derivatised fullerenes has been studied. The production of positive and negative ions has been monitored by time-of-flight (ToF) mass spectrometry. The materials under investigation included the [60]fullerene (C ), hydrogenated and deuterated [60]fullerenes (C X where X=H and D), fluorinated [60]fullerenes (C F where x=46 and 48) and the aza[60]fullerene dimer ((C N) ). Following laser ablation using a nitrogen laser, the efficient formation of small, negatively charged carbon clusters has been observed, while the corresponding positively charged clusters were not formed. Derivatised fullerenes display the co-formation of small binary carbon clusters of the type C X , where n shows odd/even alternation depending on X which represents the heteroatom initially linked to or networked with the fullerene cage. Although binary carbon clusters C X were formed where X=H, D and N, the ablation of fluorofullerene targets would not lead to the formation of C F clusters under the applied conditions, as confirmed by ablation experiments with chloro/fluoroalky-polymers. The formation of the binary carbon clusters has been also studied by laser fluence-dependent production of C D ions from C D , and by the production of C P ions using a composite C /P target. Possible pathways leading to small binary carbon clusters are addressed. © 2003 Elsevier B.V. All rights reserved.

Production of well dispersible single walled carbon nanotubes via a "floating catalyst"-method - Toni, Franziska; Xing, Haichen; Walter, Johannes; Strauß, Volker; Nacken, Thomas; Damm, Cornelia; Wirth, Karl-Ernst; Guldi, Dirk Michael; Peukert, Wolfgang (Chemical Engineering Science, 2015)
In this paper, we present a unique process chain for the production of single-walled carbon nanotubes (SWCNT) and document the relationship between the process parameters in gas phase production, the dispersibility of SWCNTs in aqueous solutions of sodium cholate and their properties. SWCNTs were prepared by a "floating catalyst" method using a solution of ferrocene in ethanol as precursor. Production rates in the range from 5 to 20. mg/h were achieved by using an optimized riser reactor design, which enables reduction of undesired wall-sticking of the catalyst particles and SWCNTs. Products featuring iron catalyst contents less than 30. wt% were obtained for low precursor concentrations in combination with short residence time in the reactor. Transmission electron microscopy (TEM) and statistical Raman analyses of the products reveal that the SWCNTs exhibit a diameter distribution ranging from 0.5 to 2.0. nm. Processing conditions, including precursor concentration, residence time, etc. were found to have only a slight impact on the mean geometric SWCNT diameter. Sonication based post-processing of the as-prepared SWCNTs in aqueous solutions of sodium cholate leads to an effective individualization of SWCNTs as proven by atomic force microscopy (AFM), 3D fluorescence spectroscopy, and by multi-wavelength analytical ultracentrifugation (AUC). Overall, the dispersibility of the non-purified SWCNTs in a 2. wt% aqueous solution of sodium cholate increases as the ferrocene partial pressure is decreased and, in turn, the catalyst concentration is reduced in the gas phase. Statistical Raman spectroscopy performed with the SWCNTs reveals that more than 75% of the produced carbon species are SWCNTs and that about 2/3 are semiconducting.
Keywords: Analytical ultracentrifugation and Raman spectroscopy; CNTs; Dispersion; Floating catalyst

Progress on solution processed Si-nanoparticle solar cells towards new generation photovoltaics - Makhdoom, Muhammad Atif; Kryschi, Carola (Optik, 2024)
Cost-effective, clean and safe solar energy production is envisaged to solve or at least mitigate climate change problems originated from the current carbon-based power sources addressing both environmental concerns as well as energy needs. Liquid-phase processing of thin films from nanoparticles – as not requiring high temperatures and vacuum – is the optimal strategy towards cost-effective, light weight, flexible and large-area devices. Silicon nanoparticles are in particular important owing to the abundance, chemical stability and low toxicity of this material. This contribution is aimed to highlight the research progresses on free-standing silicon nanoparticles (≤ 50 nm); synthesis, modification and processing towards photovoltaic applications.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Free-standing silicon nanoparticles; Functionalization; Hydrosilylation; Photovoltaic; Thin films

Promising fast energy transfer system via an easy synthesis: Bodipy-porphyrin dyads connected via a cyanuric chloride bridge, their synthesis, and electrochemical and photophysical investigations - Lazarides, Theodore; Charalambidis, Georgios; Vuillamy, Alexandra; Reglier, Marius; Klontzas, Emmanuel; Froudakis, Georgios; Kuhri, Susanne; Guldi, Dirk Michael; Coutsolelos, Athanassios G. (Inorganic Chemistry, 2011)
The boron dipyrrin (Bodipy) chromophore was combined with either a free-base or a Zn porphyrin moiety (H P and ZnP respectively), via an easy synthesis involving a cyanuric chloride bridging unit, yielding dyads Bodipy-H P (4) and Bodipy-ZnP (5). The photophysical properties of Bodipy-H P (4) and Bodipy-ZnP (5) were investigated by UV-Vis absorption and emission spectroscopy, cyclic voltammetry, and femtosecond transient absorption spectroscopy. The comparison of the absorption spectra and cyclic voltammograms of dyads Bodipy-H P (4) and Bodipy-ZnP (5) with those of their model compounds Bodipy, H P, and ZnP shows that the spectroscopic and electrochemical properties of the constituent chromophores are essentially retained in the dyads indicating negligible interaction between them in the ground state. In addition, luminescence and transient absorption experiments show that excitation of the Bodipy unit in Bodipy-H P (4) and Bodipy-ZnP (5) into its first singlet excited state results in rapid Bodipy to porphyrin energy transfer-k = 2.9 ×10 s and k = 2.2 ×10 s for Bodipy-H P (4) and Bodipy-ZnP (5), respectively-generating the first porphyrin-based singlet excited state. The porphyrin-based singlet excited states give rise to fluorescence or undergo intersystem crossing to the corresponding triplet excited states. The title complexes could also be used as precursors for further substitution on the third chlorine atom on the cyanuric acid moiety. © 2011 American Chemical Society.

Protonation-induced changes in the photophysical properties of a phthalocyanine and a covalently-linked, phthalocyanine-C60 fullerene dyad - Bottari, Giovanni; Kahnt, Axel; Guldi, Dirk Michael; Torres, Tomas (ECS Journal of Solid State Science and Technology, 2013)
The effect of the protonation on the photophysical properties (i.e., ground state and excited state properties) of Zn(II)phthalocyanine (Zn(II)Pc) 2 and covalently-linked, electron donor-acceptor Zn(II)Pc-C 1 have been investigated. On one hand, important changes in the absorption features of these two systems have been seen upon addition of trifluoroacetic acid due to protonation of some meso nitrogens of the Pc moiety. On the other hand, significant changes in the lifetime of the singlet excited states - in the case of 1 and 2 - and of the charge-separated state - in the case of 1 - were also observed. We reckon that this study, unprecedented in term of the study of the time-resolved excited state features of a protonated Pc-C conjugate, will contribute in terms of shedding light toward a better understanding of photoinduced processes in Pc-based systems. © 2013 The Electrochemical Society.

Pt-Fe3O4, Pd-Fe3O4, and Au-Fe3O4Nanoheterodimers and Their Efficacy as Radiosensitizers in Cancer Therapy - Klein, Stefanie; Otto, Julia; Harreiß, Christina; Distel, Luitpold; Leistner, Angelika; Neuhuber, Winfried; Spiecker, Erdmann; Kryschi, Carola (ACS Applied Bio Materials, 2021)
The X-radiation enhancing effect of caffeic acid-functionalized Au-Fe3O4, Pt-Fe3O4, and Pd-Fe3O4 nanoheterodimers (NHDs) on 2D and 3D breast tumor (MCF-7) and healthy breast epithelial (MCF-10A) cells was comprehensively examined by performing cell viability, reactive oxygen species (ROS) detection, enzyme activity, and clonogenic assays. Intracellular NHDs were observed to cause DNA fragmentation and to enhance superoxide and hydroxyl radical formation in MCF-7 cells when exposed to a single dose of 1 Gy. MCF-7-derived multicellular tumor spheroids (MCF-7 MCTS) and MCF-10A-derived multicellular spheroids (MCF-10A MCS) were incubated with the NHDs and irradiated with five daily doses of 2 Gy. The Au-Fe3O4 and Pt-Fe3O4 NHD-loaded MCF-7 MCTS significantly decreased in volume after being exposed to fractionated irradiation, whereas intracellular Au-Fe3O4 and Pt-Fe3O4 NHDs promoted the growth of the irradiated MCF-10A MCS. Moreover, Au-Fe3O4 and Pt-Fe3O4 NHDs were shown to impede ROS formation and inhibit DNA strand breakage in the noncancerous MCF-10A cells. On the other hand, the Pd-Fe3O4 NHDs boosted X-radiation-induced damage of MCF-10 A cells, which was ascribed to impairment of the ROS scavenging enzyme activities. In summary, caffeic acid-functionalized Au-Fe3O4 and Pt-Fe3O4 NHDs performed as excellent X-radiation enhancing agents in breast tumor cells, while they protect healthy breast epithelial cells against X-radiation.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Au-Fe; caffeic acid; MCF-10A; MCF-7; multicellular tumor spheroids; Pd-Fe; Pt-Fe; radiotherapy

Purification and structural elucidation of carbon dots by column chromatography - Hinterberger, Vanessa; Damm, Cornelia; Haines, Philipp; Guldi, Dirk Michael; Peukert, Wolfgang (Nanoscale, 2019)
Carbon dots (CDs) are an astonishing class of fluorescent materials with many applications in bioimaging, drug delivery, photovoltaics and photocatalysis due to their outstanding luminescence properties and low toxicity. However, the internal CD structure of bottom-up synthesized CDs is still the subject of considerable debate. Unambiguous analysis of the internal CD composition is hampered by the fact that reaction products usually contain mixtures of several CD fractions as well as molecular intermediate and side products. Therefore, purification and careful separation of the various CD fractions is vital for structural analysis and isolation of pure CDs possessing optimized optical properties. In this study, CD solutions were synthesized from citric acid and cysteine via a one-pot hydrothermal synthesis. A simple column chromatography unit was used to systematically study the influence of the molar precursor ratios and synthesis conditions (temperature, reaction time) on the CD solution composition. By investigating the structural and optical properties of the chromatographically separated fractions, three different fluorescent species could be identified. Freely floating molecular fluorophores left the column first, followed by highly fluorescent CDs with fluorophores bound to the carbon core, finally followed by low-fluorescent carbon particles without fluorophores. We demonstrate that the CD solution composition and the internal structure of the individual fluorescent components can be clarified via chromatographic separation. This information can be further applied to isolate pure CDs with optimized optical properties.
CRIS-Team Scopus Importer:2019-05-09

Putting a positive spin on molecular bridges - Guldi, Dirk Michael (Angewandte Chemie International Edition, 2010)
Getting the message across: Insight into electronic coupling beween electron donors and acceptors connected by molecular bridges (see example) has been achieved by measuring the magnitude of the spin-spin exchange interactions. A kinetic analysis of the magnetic field effects showed that charge transfer in highly π-conjugated bridges is a function of the spin-selective charge-recombination pathways. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Quadrupolar Cyclopenta[hi]aceanthrylene-Based Electron Donor-Acceptor-Donor Conjugates: Charge Transfer versus Charge Separation - Schierl, Christoph; Alex, Wiebke; Mateo, Luis M.; Ballesteros, Beatriz; Shimizu, Daiki; Osuka, Atsuhiro; Torres, Tomas; Guldi, Dirk Michael; Bottari, Giovanni (Angewandte Chemie International Edition, 2019)
Cyclopenta[hi]aceanthrylenes (CPAs) have been functionalized at two of the peripheral positions with electronically inert trimethylsilylethynyl (1), as well as with electron-donating 4-ethynyl-N,N-dimethylaniline (2), ethynyl ZnIIphthalocyanine (3), and ethynyl ZnIIporphyrin (4) units. Consistent with X-ray crystal structures of 2 and 4, analyses of absorption and fluorescence of 2–4 point to strong electronic communication between the CPA and the peripheral units, affording quadrupolar electron donor-acceptor-donor charge-transfer conjugates. By virtue of their quadrupolar/dipolar charge-transfer characters in the excited state, 2–4 exhibit fluoro-solvatochromism. Transient absorption spectroscopy confirmed delocalized quadrupolar ground states and formation of weakly solvent stabilized quadrupolar singlet excited states. The latter transform into strongly stabilized dipolar excited states before deactivating to the ground state in 2 and give rise to a fully charge separated state in 3 and 4.
CRIS-Team Scopus Importer:2019-09-24
Keywords: absorption; charge transfer; fluorescence; hydrocarbons; porphyrinoids

Quantitative transduction of excited-state energy in fluorophore- heterofullerene conjugates - Hauke, Frank; Hirsch, Andreas; Atalick, Stefan; Guldi, Dirk Michael; Hauke, Frank (European Journal of Organic Chemistry, 2005)
A novel series of fluorophore-heterofullerene conjugates 10-14 - the fluorophores range from benzene, naphthalene, phenanthrene, and fluorene to pyrene - was synthesized. NMR spectroscopy and quantum mechanical calculations demonstrate that the flexibility of the acetyl-group linker opens the way for conformations with π-π stacking interactions between the chromophores. This leads to favorable electronic communication between the two subsystems and is reflected in a series of ground- and excited-state assays ranging from fluorescence to fast transient absorption measure ments. It was found that a common deactivation process of the photoexcited fluorophores takes place, namely, a quantitative transduction of singlet excited state, yielding the heterofullerene singlet excited state. This reaction pathway leads to the long-lived and highly reactive fullerene triplet state, which forms, in a reaction with molecular oxygen, a cytotoxic oxygen species (i.e. singlet oxygen). © Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005.

Quantum-dot-sensitized solar cells: Understanding linker molecules through theory and experiment - Margraf, Johannes; Ruland, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We have investigated the role of linker molecules in quantum-dot-sensitized solar cells (QDSSCs) using density-functional theory (DFT) and experiments. Linkers not only govern the number of attached QDs but also influence charge separation, recombination, and transport. Understanding their behavior is therefore not straightforward. DFT calculations show that mercaptopropionic acid (MPA) and cysteine (Cys) exhibit characteristic binding configurations on TiO2 surfaces. This information is used to optimize the cell assembly process, yielding Cys-based cells that significantly outperform MPA cells, and reach power conversion efficiencies (PCE) as high as 2.7% under AM 1.5 illumination. Importantly, the structural information from theory also helps understand the cause for this improved performance.

Quaternized Pyridyloxy Phthalocyanines Render Aqueous Electron-Donor Carbon Nanotubes as Unprecedented Supramolecular Materials for Energy Conversion - Anaya-Plaza, Eduardo; Moreno-Oliva, Maria; Kunzmann, Andreas; Romero-Nieto, Carlos; Costa, Ruben Dario; De La Escosura, Andres; Guldi, Dirk Michael; Torres, Tomas (Advanced Functional Materials, 2015)
Exploring new properties in known materials, sometimes even achieving behaviors opposite to those traditionally encountered, is a fundamental aspect of innovation in materials science. In the ﬁeld of energy conversion, for example, the development of water-processed organic solar cells provides environmentally friendlier materials, which contribute to reduce health risks. Herein, a novel approach is described to produce water-soluble electron-donor single wall carbon nanotube (SWCNT) hybrids based on the noncovalent immobilization of quaternized pyridyloxy zinc phthalocyanines (ZnPc) with a varying number of pyridyl substituents. Moreover, the excellent electron-accepting ability of the latter ZnPcs is reported. The introduction of tert-butylphenyl groups at the pyridines enables for the ﬁrst time a complete characterization. The electron-acceptor nature of the ZnPcs enables switching the role of SWCNTs within the resulting supramolecular hybrids. Finally, a proof-of-concept demonstration of the SWCNT/ZnPc hybrids' capacity for energy conversion is presented, paving their way to possible use as active layer material in solar cells processed entirely from aqueous solutions.
EAM Import::2019-03-13

Rates and energetics of intramolecular electron transfer processes in conjugated metallofullerenes - Schubert, Christina; Rudolf, Marc; Guldi, Dirk Michael; Takano, Yuta; Mizorogi, Naomi; Angeles Herranz, M.; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2013)
In this paper, we report on the design, redox potentials, excited state energies and radical ion pair state energies in electron donor-acceptor conjugates comprising the electron-donating π-extended tetrathiafulvalene and several electron-accepting fullerenes. To this end, we contrast an empty fullerene, that is, C, with two endohedral metallofullerenes, that is, open-shell La@C and closed-shell La@C, in terms of charge separation and charge recombination dynamics. © 2013 The Author(s) Published by the Royal Society. All rights reserved.

Rationalizing Fabrication and Design Toward Highly Efficient and Stable Blue Light-Emitting Electrochemical Cells Based on NHC Copper(I) Complexes - Weber, Michael; Fresta, Elisa; Elie, Margaux; Miehlich, Matthias; Renaud, Jean-Luc; Meyer, Karsten; Gaillard, Sylvain; Costa, Ruben Dario (Advanced Functional Materials, 2018)
Recently, the use of a new family of electroluminescent copper(I) complexes—i.e., the archetypal [Cu(IPr)(3-Medpa)][PF6] complex; IPr: 1,3-bis-(2,6-di-iso-propylphenyl)imidazole-2-ylidene; 3-Medpa: 2,2′-bis-(3-methylpyridyl)amine—has led to blue light-emitting electrochemical cells (LECs) featuring luminances of 20 cd m−2, stabilities of 4 mJ, and efficiencies of 0.17 cd A−1. Herein, this study rationalizes how to enhance these figures-of-merit optimizing both device fabrication and design. On one hand, a comprehensive spectroscopic and electrochemical study reveals the degradation of this novel emitter in common solvents used for LEC fabrication, as well as the impact on the photoluminescence features of thin-films. On the other hand, spectro-electrochemical and electrochemical impedance spectroscopy assays suggest that the device performance is strongly limited by the irreversible formation of oxidized species that mainly act as carrier trappers and luminance quenchers. Based on all of the aforementioned, device optimization was realized using ionic additives and a hole transporter either as a host–guest or as a multilayered architecture approach to decouple hole/electron injection. The latter significantly enhances the LEC performance, reaching luminances of 160 cd m−2, stabilities of 32.7 mJ, and efficiencies of 1.2 cd A−1. Overall, this work highlights the need of optimizing both device fabrication and design toward highly efficient and stable LECs based on cationic copper(I) complexes.
CRIS-Team Scopus Importer:2020-09-14
Keywords: blue electroluminescence; copper(I) complexes; light-emitting electrochemical cells; multi-layered device design; redox stability

Reaction of water-soluble fullerenes with O2 - and other reactive radical species - Kahnt, Axel; Guldi, Dirk Michael; Brettreich, Michael; Hartnagel, Uwe; Hirsch, Andreas (Journal of Materials Chemistry, 2010)
In this work we focused on the reaction of water-soluble fullerene derivatives with various organic (i.e., methyl radical and t-butyl radical) and inorganic (i.e., superoxide radical and azide radical) radicals to mimic their superoxide dismutase (SOD) activity. Importantly, with the help of time-resolved pulse radiolysis and steady-state gamma radiolysis measurements all of the assays were conducted in aqueous solutions. Our fully-fledged spectroscopic and kinetic investigations leave no doubt about a diffusion-controlled addition mechanism (10 M s) by which superoxide radical reacts with fullerenes to yield (C-O) . Notable is that the formations of (C-CH), (C-(CH)(CH)COH), and (C -N) are much slower and proceed with activation-controlled rate constants less than 10 M s. The major deactivation path of (C-O ) is a pH dependent protonation (10 M s). Despite lacking unambiguous evidence for the formation of C - via a direct impact or an indirect dissociation mechanism - (C-O) is still redoxactive. The latter has been confirmed by an activation-controlled reduction (10 M s) of a series of p-benzoquinones that display different electron affinities. In other words, (C -O) - but not C - is likely to emerge as a key intermediate in the SOD activity of fullerenes. Its slow protonation is beneficial toward an efficient dismutation to form H O. © 2010 The Royal Society of Chemistry.

Reactivity of a metastable cobalt(III) trisulfide complex: Multiple C-H functionalization of p-xylene and disulfides to afford photofunctional cobalt complexes - Maruyama, Masashi; König, Matthias; Guldi, Dirk Michael; Nakamura, Eiichi; Matsuo, Yutaka (Angewandte Chemie International Edition, 2013)
Unprecedented reactivity of a metastable cobalt trisulfide complex has been observed, and several direct C-S bond formation reactions by C-H functionalization were developed. These reactions produced a series of photofunctional motifs of sulfur-rich cobalt complexes (see picture). The measured photophysical properties of these complexes suggest promising molecular designs for photocurrent generating materials. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Recent advances in multifunctional nanocarbons used in dye-sensitized solar cells - Costa Riquelme, Rubén Dario; Lodermeyer, Fabian; Casillas Pacheco, Ruben; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
Throughout recent years the implementation of nanocarbons into dye-sensitized solar cells (DSSC) has resulted in important breakthroughs. The most relevant of them in this context are (i) the enhancement of charge transport and charge collection in nanocarbon-doped electrodes, (ii) the introduction of nanocarbon interlayers that simultaneously reduce the charge recombination and increase the charge collection efficiency, (iii) the use of nanocarbon-based, iodine-free, solid-state electrolytes featuring excellent diffusion coefficients and catalytic efficiencies, (iv) the use of novel nanocarbon-based hybrid dyes, and (v) the use of nanocarbons towards platinum-free counter electrodes. The first four aforementioned aspects are thoroughly described in this review. This journal is © the Partner Organisations 2014.

Recognition of C60 by tetra- and tri-quinoxaline cavitands - Ballistreri, Francesco P.; Brancatelli, Giovanna; Demitri, Nicola; Geremia, Silvano; Guldi, Dirk Michael; Melchionna, Michele; Pappalardo, Andrea; Prato, Maurizio; Tomaselli, Gaetano A.; Sfrazzetto, Giuseppe Trusso (Supramolecular Chemistry, 2016)
Molecular recognition of C60 fullerene by two cavitands, bearing four and three quinoxaline walls, is reported here. Fluorescence titrations show the recognition ability of the receptors with high binding constant values. The formation of a stable 1:1 supramolecular complex was also confirmed by DOSY, EI-MS and X-ray analysis. The crystal structure analysis of tetraquinoxaline cavitand and C60 shows a crystal packing, where C60 molecules are intercalated between bilayers of cavitand molecules, on the ideal fourfold symmetry axis of the receptor, and are arranged in a zigzag motif.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Cavitand; crystal structure; fullerene; molecular recognition

Red edge effect and chromoselective photocatalysis with amorphous covalent triazine-based frameworks - Zou, Yajun; Abednatanzi, Sara; Derakhshandeh, Parviz Gohari; Mazzanti, Stefano; Schüßlbauer, Christoph; Cruz, Daniel; Van Der Voort, Pascal; Shi, Jian-Wen; Antonietti, Markus; Guldi, Dirk Michael; Savateev, Aleksandr (Nature Communications, 2022)
Chromoselective photocatalysis offers an intriguing opportunity to enable a specific reaction pathway out of a potentially possible multiplicity for a given substrate by using a sensitizer that converts the energy of incident photon into the redox potential of the corresponding magnitude. Several sensitizers possessing different discrete redox potentials (high/low) upon excitation with photons of specific wavelength (short/long) have been reported. Herein, we report design of molecular structures of two-dimensional amorphous covalent triazine-based frameworks (CTFs) possessing intraband states close to the valence band with strong red edge effect (REE). REE enables generation of a continuum of excited sites characterized by their own redox potentials, with the magnitude proportional to the wavelength of incident photons. Separation of charge carriers in such materials depends strongly on the wavelength of incident light and is the primary parameter that defines efficacy of the materials in photocatalytic bromination of electron rich aromatic compounds. In dual Ni-photocatalysis, excitation of electrons from the intraband states to the conduction band of the CTF with 625 nm photons enables selective formation of C‒N cross-coupling products from arylhalides and pyrrolidine, while an undesirable dehalogenation process is completely suppressed.
CRIS-Team Scopus Importer:2022-05-06

Redox Behavior of a Dinuclear Ruthenium(II) Complex Bearing an Uncommon Bridging Ligand: Insights from High-Pressure Electrochemistry - Dürr, Maximilian; Klein, Johannes; Kahnt, Axel; Becker, Sabine; Puchta, Ralph; Sarkar, Biprajit; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2017)

Regio-, Stereo-, and Atropselective Synthesis of C60Fullerene Bisadducts by Supramolecular-Directed Functionalization - Bottari, Giovanni; Trukhina, Olga; Kahnt, Axel; Frunzi, Michael; Murata, Yasujiro; Rodriguez-Fortea, Antonio; Poblet, Josep M.; Guldi, Dirk Michael; Torres, Tomas (Angewandte Chemie International Edition, 2016)
The regio- and stereocontrolled synthesis of fullerene bisadducts is a topic of increasing interest in fullerene chemistry and a key point for the full exploitation of these derivatives in materials science. In this context, while the tether-directed remote functionalization strategy offers a valid approach to this synthetic challenge, no examples of such control have yet been reported using nontethered species. Presented here is a conceptually novel, supramolecular-directed functionalization approach in which noncovalent interactions between untethered residues have been used, for the first time, to amplify (>2800-fold) the regio-, stereo-, and atropselective formation of a C60fullerene bisadduct racemate from a complex mixture of 130 bisadducts. Remarkably, both enantiomers, which present a sterically demanding cis-1 C60addition pattern, represent the first examples of fullerene derivatives which combine central, axial, and helical chirality.
CRIS-Team Scopus Importer:2023-03-07
Keywords: atropisomerism; cycloaddition; fullerenes; phthalocyanines; supramolecular chemistry

Resonance-Enhanced Charge Delocalization in Carbazole-Oligoyne-Oxadiazole Conjugates - Zieleniewska, Anna; Zhao, Xiaotao; Bauroth, Stefan; Wang, Changsheng; Batsanov, Andrei S.; Krick Calderon, Christina; Kahnt, Axel; Clark, Timothy; Bryce, Martin R.; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
There are notably few literature reports of electron donor-acceptor oligoynes, even though they offer unique opportunities for studying charge transport through "all-carbon" molecular bridges. In this context, the current study focuses on a series of carbazole-(C≡C)n-2,5-diphenyl-1,3,4-oxadiazoles (n = 1-4) as conjugated π-systems in general and explores their photophysical properties in particular. Contrary to the behavior of typical electron donor-acceptor systems, for these oligoynes, the rates of charge recombination after photoexcitation increase with increasing electron donor-acceptor distance. To elucidate this unusual performance, we conducted detailed photophysical and time-dependent density functional theory investigations. Significant delocalization of the molecular orbitals along the bridge indicates that the bridging states come into resonance with either the electron donor or acceptor, thereby accelerating the charge transfer. Moreover, the calculated bond lengths reveal a reduction in bond-length alternation upon photoexcitation, indicating significant cumulenic character of the bridge in the excited state. In short, strong vibronic coupling between the electron-donating N-arylcarbazoles and the electron-accepting 1,3,4-oxadiazoles accelerates the charge recombination as the oligoyne becomes longer.
CRIS-Team Scopus Importer:2020-11-13

Reversible Charge Transfer with Single-Walled Carbon Nanotubes Upon Harvesting the Low Energy Part of the Solar Spectrum - Menon, Arjun; Slominskii, Yuri L.; Joseph, Jan; Dimitriev, Oleg P.; Guldi, Dirk Michael (Small, 2020)
Here, the ability of a novel near-infrared dye to noncovalently self-assemble onto the surface of single-walled carbon nanotubes (SWCNTs) driven by charge-transfer interactions is demonstrated. Steady-state, Raman, and transient absorption spectroscopies corroborate the electron donating character of the near-infrared dye when combined with SWCNTs, in the form of fluorescence quenching of the excited state of the dye, n-doping of SWCNTs, and reversible charge transfer, respectively. Formation of the one-electron oxidized dye as a result of interactions with SWCNTs is supported by spectroelectrochemical measurements. The ultrafast electronic process in the near-infrared dye, once immobilized onto SWCNTs, starts with the formation of excited states, which decay to the ground state via the intermediate population of a fully charge-separated state, with characteristic time constants for the charge separation of 1.5 ps and charge recombination of 25 ps, as derived from the multiwavelength global analysis. Of great relevance is the fact that charge-transfer occurs from the hot excited state of the near-infrared dye to SWCNTs.
CRIS-Team WoS Importer:2020-02-18

Reversible gating of singlet fission by tuning the role of a charge-transfer state - Bo, Yifan; Hou, Yuxuan; Lavergne, Dominic A.X.; Clark, Timothy; Ferguson, Michael J.; Tykwinski, Rik R.; Guldi, Dirk Michael (Nature Communications, 2025)
Stimulus-responsive triplet excited states and multiexcitonic logic gates have garnered increasing interest. Singlet fission is an efficient multiple exciton generation process, in which one singlet converts into two triplets. Singlet fission is, however, rarely reported to be switchable by external stimuli. Here we design a meta-diethynylphenylene-linked tetracene dimer featuring pyridyl endgroups that function as an acid/base-responsive switch, enabling the reversible modulation of singlet fission. In its neutral form, the interchromophore charge-transfer state facilitates singlet fission and promotes the formation of a correlated triplet-pair state. Upon treatment with acid, protonation of the pyridyl nitrogens generates a more strongly electron-accepting pyridinium, leading to an intra-chromophore charge-transfer state, which inhibits singlet fission. Finally, an IMPLICATION logic gate is constructed by using acid and base as inputs and monitoring the formation of triplet excited states based on singlet fission.
CRIS-Team Scopus Importer:2025-04-11

Reversible vapochromic response of polymer films doped with a highly emissive molecular rotor - Minei, Pierpaolo; König, Matthias; Battisti, Antonella; Ahmad, Muzaffer; Barone, Vincenzo; Torres, Tomas; Guldi, Dirk Michael; Brancato, Giuseppe; Bottari, Giovanni; Pucci, Andrea (Journal of Materials Chemistry C, 2014)
We report on a new vapochromic system suitable for sensing volatile organic compounds (VOCs) based on polymer films doped with 4-(diphenylamino)phthalonitrile (DPAP), a fluorescent molecular rotor sensitive to both solvent polarity and viscosity. Poly(methyl methacrylate) (PMMA) and polycarbonate (PC) films containing small amounts of DPAP (≤0.1 wt%) were prepared and exposed to saturated atmospheres of different VOCs. DPAP/PMMA films show a good and reversible vapochromism when exposed to VOCs with high polarity index and favourable interaction with polymer matrices such as THF, CHCl3, and acetonitrile. Analogously, DPAP/PC films exposed to polar and highly polymer-interacting solvents, that is, toluene, THF, and CHCl3, show a gradual decrease and red-shift of the emission. In contrast to DPAP/PMMA films, an unexpected increase and further red-shift of fluorescence are observed at longer exposure times as a consequence of an irreversible, solvent-induced crystallization process of PC. The vapochromism of DPAP-doped films is rationalized on the basis of alterations of the rotor intramolecular motion and polarity effects stemming from the environment, which, in concert, influence the deactivation pathways of the DPAP intramolecular charge transfer state. Overall, the present results support the use of DPAP-enriched plastic films as a new chromogenic material suitable for the detection of VOCs.
CRIS-Team Scopus Importer:2023-03-07

Review - Single-Walled Carbon Nanohorn-Based Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (ECS Journal of Solid State Science and Technology, 2017)
Efforts in the broad field of dye-sensitized solar cells (DSSC) are governed by four key challenges: i) the development of photoelectrodes with high charge injection yields and charge collection efficiencies, ii) the development of low-cost buffer layers, which effectively reduce the back reaction of electrons from the transparent conductive oxide (TCO) to the electrolyte, iii) the design of platinum-free counter electrodes (CE), which feature good electrolyte regeneration yields, and iv) the implementation of (quasi) solid-state and iodine-free electrolytes featuring excellent ionic diffusion and conductivity. The introduction of nanocarbons into each component of DSSCs has emerged as a promising strategy to tackle all the aforementioned challenges. Leading examples of nanocarbons are graphene, carbon black (CB), multi-walled carbon nanotubes (MWCNT), and single-walled carbon nanotubes (SWCNT). Here, we focus on single-walled carbon nanohorns (SWCNH), which were successfully integrated into each of the aforementioned parts of DSSCs.
EAM Import::2019-03-13

Rigid, Branched Porphyrin Antennas: Control over Cascades of Unidirectional Energy Funneling and Charge Transfer - Wolf, Maximilian; Herrmann, Astrid; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2017)

Ring-ribbon transition and parallel alignment in SWNT films on polyelectrolytes - Guldi, Dirk Michael; Mamedov, A. A.; Crisp, Todd; Kotov, N. A.; Hirsch, Andreas; Prato, Maurizio (Journal of Physical Chemistry B, 2004)
A simple and reliable method of permanent organization of SWNTs into morphologically different films is described. Under standard adsorption conditions, SWNTs form films from randomly intersecting nanotubes. It was found that virtually perfect rings from single SWNTs also form spontaneously in these films. Adsorption in laminar flow produces SWNT ribbons with parallel alignment of the nanotubes. Further increase of the flow rate detaches SWNT from the surface.

Ruthenoarenes versus phenol derivatives as axial linkers for subporphyrazine dimers and trimers - Caballero, Esmeralda; Nieto, Carlos Romero; Strauß, Volker; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Sessler, Jonathan L.; Torres, Tomas (Chemistry - A European Journal, 2014)
The subporphyrazine (SubPz) dimer diboron(III) [μ-1',4'-benzenediolato][bis-(1,2,6,7,11,12-hexapropylsubporphyrazinato)] (2) and trimer triboron(III)[μ-1',3',5'-benzenetriolato][tris-(1,2,6,7,11,12-hexapropylsubporphyrazinato)] (4), consisting of SubPz units assembled through their axial positions by hydroquinone- and phloroglucinol-linkers, respectively, have been prepared. Selective ruthenium-π-coordination to the linking aromatic rings afforded SubPz arrays 8 and 9, respectively. These latter systems displayed different degrees of electronic communication between the macrocycles relative to 2 and 4 as inferred from analyses of the ground- and excited-state features. For instance, as revealed by time-resolved pump probe transient absorption spectroscopy, the excited singlet states of dimer 2 and trimer 4 undergo rather rapid deactivation. In contrast, the presence of a ruthenoarene linker, as in 8 and 9, serves to increase the SubPz singlet excited state lifetimes; these now reach values similar to those seen in the case of monomeric SubPz compounds that either do or do not contain ruthenoarene subunits (i.e., 7 and 6, respectively). These findings are ascribed to the redox active nature of the hydroquinone and phloroglucinol linkers in 2 and 4 and a change in the electronics that results from organometallic functionalization. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Salt Cluster Attachment to Crown Ether Decorated Phthalocyanines in the Gas Phase - Kellner, Ina; Hahn, Uwe; Torres, Tomás; Drewello, Thomas (Journal of Physical Chemistry A, 2018)
Crown ether decorated phthalocyanines were designed to form rigidly eclipsed aggregates with metal ions being sandwiched between the molecules. We studied tetra-[18]crown-6 ether functionalized zinc phthalocyanine (ZnPcTetCr) in the presence of excess NaCl by electrospray ionization mass spectrometry. ZnPcTetCr was found to form aggregates in the gas phase to which several neutral NaCl molecules are attached. Collision-induced dissociation experiments revealed that the ions observed in the positive- and negative-ion modes possess remarkably different structures. Their fragmentation behavior indicates that the sodium ions providing the charge of the positively charged aggregates are strongly bound inside the crown ether moieties, while the neutral salt units are less strongly attached. However, in the negatively charged ions, none of the sodium ions is embedded in the crown ether moieties, and the NaCl molecules were found to be attached as one large, weakly bound cluster.
Created from Fastlane, Scopus look-up

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up

Screening interactions of zinc phthalocyanine-PPV oligomers with single wall carbon nanotubes - A comparative study - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
In this paper, the ability to disperse single wall carbon nanotubes (SWNT) of several different-nature poly(p-phenylene vinylene) (PPV) oligomers having pendant zinc phthalocyanines (ZnPc) has been investigated. Based on the quenching of the ZnPc and SWNT fluorescence in the supramolecular assemblies, it has been shown that parameters such as p/n-type character of the oligomer, size and the distance between the ZnPc moiety and the conjugated backbone play an important role in the strength of the interactions. Important results suggest that n-type oligomers as well as certain flexibility in the phthalocyanine arrangement are breakthroughs for immobilizing SWNT in THF, affording stable and homogeneous suspensions. Transient absorption measurements confirm that upon photoexcitation the photoexcited ZnPc triggers an intraensemble charge transfer to yield oxidized ZnPc and reduced SWNT. © 2011 The Royal Society of Chemistry.

Screening Nanographene-Mediated Inter(Porphyrin) Communication to Optimize Inter(Porphyrin–Fullerene) Forces - Haines, Philipp; Kaur, Ramandeep; Martin, Max; Minameyer, Martin; Frühwald, Stefan; Bönisch, Simon; Lungerich, Dominik; Hampel, Frank; Görling, Andreas; Drewello, Thomas; Jux, Norbert; Guldi, Dirk Michael (Advanced Energy Materials, 2021)
Multifunctional molecular materials comprising porphyrins and fullerenes have served as perfect prototypes to study key aspects of natural photosynthesis starting at light harvesting and energy transfer processes all the way to charge separation, charge shift, and charge recombination. Herein, hexa-peri-hexabenzocoronenes (HBCs) are explored, decorated with one, two, and six porphyrins at their peripheral positions, within the context of replicating key steps of photosynthesis. The major focus of the investigations is to screen inter(porphyrin) communications across the HBC platform as a function of the substitution pattern and to optimize the intermolecular forces with fullerenes. To this end, the ground- and excited-state features are investigated in the absence of C60 and C70 by employing an arsenal of spectroscopic methods. Further insights into inter(porphyrin) communications come from time-dependent density-functional theory (TDDFT) calculations. In the presence of C60 and C70, X-ray crystallography, steady-state and time-resolved spectroscopy, and mass spectrometry corroborate exceptionally strong inter(porphyrin–fullerene) interactions in the solid, liquid, and gas phases. The experiments are backed-up with DFT calculations of the geometrically optimized and energetically stable complex configuration.
CRIS-Team Scopus Importer:2021-03-26
Keywords: charge separation; crystal structure; fullerene; hexabenzocoronene; porphyrin; transient absorption

Screening Supramolecular Interactions between Carbon Nanodots and Porphyrins - Cadranel, Alejandro; Strauß, Volker; Margraf, Johannes; Winterfeld, Kim; Vogl, Christoph; Dordevic, Luka; Arcudi, Francesca; Hölzel, Helen; Jux, Norbert; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
We present an in-depth investigation regarding the electron-accepting nature of pressure-synthesized carbon nanodots (pCNDs) in combination with porphyrins as excited-state electron donors. To this end, electrostatic attractions involving negative charges, which are present on the pCND surface, are essential to govern the hybrid assembly, on one hand, and charge separation, on the other hand.
CRIS-Team Scopus Importer:2022-04-14

Scrutinizing the chemical nature and photophysics of an expanded hemiporphyrazine: The special case of [30]trithia-2,3,5,10,12,13,15,20,22,23,25, 30-dodecaazahexaphyrin - Trukhina, Olga N.; Rodriguez-Morgade, M. Salome; Wolfrum, Silke; Caballero, Esmeralda; Snejko, Natalia; Danilova, Elena A.; Gutierrez-Puebla, Enrique; Islyaikin, Mikhail K.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
Thirty π-electron-expanded hemiporphyrazines 1a-c have been prepared by crossover condensation reaction of 2,5-diamino-1,3,4-thiadiazole and the corresponding phthalonitrile (3) or diiminoisoindoline (4) derivatives. The expanded azaporphyrin hexamers have been unequivocally characterized by means of spectroscopic, crystallographic, and electrochemical techniques. Weak intramolecular hydrogen bonding imposes a planar conformation to macrocycles. However, the overall electronic delocalization is low, and the nature of the resulting [30]heteroannulene is nonaromatic, as confirmed by NMR studies, XR diffraction analysis, and calculation of the NICS(0) value. Studies on a wide range of physicochemical features including ground, excited, reduced, and oxidized states provide evidence for the wide applicability of these 30 π-electron-expanded hemiporphyrazines in processes involving electron transfer. A key asset of our work is the systematic development of spectroscopic and kinetic markers for the formation and decay of all of the aforementioned species. Thirty π-electron-expanded hemiporphyrazines evolve as broadly absorbing light harvesters with excited state energies of around 2.3 eV that are susceptible to facile one-electron reduction and one-electron oxidation reactions. © 2010 American Chemical Society.

Selective synthesis of Co8S15 cluster in bowl-shaped template of the pentaaryl[60]fullerene ligand - Maruyama, Masashi; Imoto, Kenta; König, Matthias; Guldi, Dirk Michael; Ohkoshi, Shin-Ichi; Nakamura, Eiichi; Matsuo, Yutaka (Journal of the American Chemical Society, 2013)
A cobalt-sulfur cluster CoS with molecular formula of (CAr)-CoSBu-(CAr) (Ar = 4- BuCH) was selectively synthesized from a pentaaryl[60]fullerene cobalt trisulfide complex, (η-C Ar)CoS. The bowl-shaped steric templating fullerene ligand, as well as the metastable cobalt trisulfide moiety, played important roles in the exclusive cluster formation. X-ray crystallography, as well as electrochemical, time-resolved photophysical, and magnetic, measurements revealed a mixed-valence cluster with six cobalt(III) and two high-spin cobalt(II) centers showing reversible redox behavior and photoinduced charge separation. © 2013 American Chemical Society.

Self-assembling depsipeptide dendrimers and dendritic fullerenes with new cis- and trans-symmetric Hamilton receptor functionalized zn-porphyrins: Synthesis, photophysical properties and cooperativity phenomena - Maurer, Katja; Grimm, Bruno; Wessendorf, Florian; Hartnagel, Kristine; Guldi, Dirk Michael; Hirsch, Andreas (European Journal of Organic Chemistry, 2010)
Two novel supramolecular building blocks, namely cis- and trans-symmetric zinc-porphyrins bearing Hamilton receptors as their focal points (10 and 15), were self-assembled with (i) first-, second- and third-generation depsipeptide cyanurates (21-23); (ii) second-generation dendrofullerene (24), and (iii) cyanuric acid substituted fullerene (20), and probed in a series of photophysical investigations. Importantly, an overall 1:2 stoichiometry was confirmed with binding con-stants Kn, and Hill coefficients nH that indicate remarkable cooperativities. As a general feature, stronger binding evolves from the trans-symmetric porphyrin isomer, although the increased steric demand of the depsipeptide ligands means that the binding constants decrease with each generation. The self-assembly of 10 or 15 with 20 affords novel electron donor-acceptor hybrids that reveal, upon excitation, intra-hybrid charge-transfer events. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Self-assembly, host-guest chemistry, and photophysical properties of subphthalocyanine-based metallosupramolecular capsules - Sanchez-Molina, Irene; Grimm, Bruno; Krick Calderon, Rafael; Claessens, Christian G.; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2013)
Four new subphthalocyanine-based capsules have been synthesized and characterized. These supramolecular systems have been successfully employed for the encapsulation of fullerenes and probed by a wide range of characterization methods, including NMR, UV-vis and fluorescence spectroscopy, electrospray ionization mass spectrometry, and electrochemistry. Furthermore, the binding constants of the host guest complexes were estimated. Finally, the photophysical properties revealed that the subphthalocyanines undergo a transduction of singlet excited-state energy to the fullerene inside the cavity upon photoexcitation. © 2013 American Chemical Society.

Self-association and electron transfer in donor-acceptor dyads connected by meta-substituted oligomers - Molina-Ontoria, Agustin; Fernandez, Gustavo; Wielopolski, Mateusz; Atienza, Carmen; Sanchez, Luis; Gouloumis, Andreas; Clark, Timothy; Martin, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2009)
The synthesis of a new series of electron donor-acceptor conjugates (5, 10, 13, and 16) in which the electron acceptor - C - and the electron donor - π-extended tetrathiafulvalene (exTTF) - are bridged by means of m-phenyleneethynylene spacers of variable length is reported. The unexpected self-association of these hybrids was first detected to occur in the gas phase by means of MALDI-TOF spectrometry and subsequently corroborated in solution by utilizing concentration-dependent and variable-temperature H NMR experiments. Furthermore, the ability of these new conjugates to form wirelike structures upon deposition onto a mica surface has been demonstrated by AFM spectroscopy. In light of their photoactivity and redoxactivity, 5, 10, 13, and 16 were probed in concentration-dependent photophysical experiments. Importantly, absorption and fluorescence revealed subtle dissimilarities for the association constants, that is, a dependence on the length of the m-phenylene spacers. The binding strength is in 5 greatly reduced when compared with those in 10, 13, and 16. Not only that, the spacer length also plays a decisive role in governing excited-state interactions in the corresponding electron donor-acceptor conjugates (5, 10, 13, and 16). To this end, 5, in which the photo- and electroactive constituents are bridged by just one aromatic ring, displayssexclusively and independent of the concentration (10 to 10 M) - efficient intramolecular electron transfer events on the basis of a "through-bond" mechanism. On the contrary, the lack of conjugation throughout the bridges in 10 (two m-phenyleneethynylene rings), 13 (three m-phenyleneethynylene rings), and 16 (four m-phenyleneethynylene rings) favors at low concentration (10 M) "through space" intramolecular electron transfer events. These are, however, quite ineffective and, in turn, lead to excited-state deactivations that are at high concentrations (10 M) dominated by intracomplex electron transfer events, namely, between exTTF of one molecule and C of another molecule, and that stabilize the resulting radical ion pair state with lifetimes reaching 4.0 μs. © 2009 American Chemical Society.

Self-ordering electron donor-acceptor nanohybrids based on single-walled carbon nanotubes across different scales - Brunetti, Fulvio G.; Nieto, Carlos Romero; Lopez-Andarias, Javier; Atienza, Carmen; Luis Lopez, Juan; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2013)
From nano- to macroscale: The immobilization of photo- and redox-active 9,10-di(1,3-dithiol-2-ylidene)-9,10-dihydroanthracene-based dipeptide 1 onto SWCNTs resulted in a high order of self-alignment among 1/SWCNTs (see picture). The assembly of the 1/SWCNTs is the key for stabilizing long-lived charge-separated states that are formed upon photoexcitation of the SWCNTs. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Self-organisation in photoactive fullerene porphyrin based donor-acceptor ensembles - Guldi, Dirk Michael; Luo, Chuping; Swartz, Angela; Scheloske, Michael; Hirsch, Andreas (Chemical Communications, 2001)
Complexation of ZnP-C-ZnP triads with diazabicyclooctane (DABCO) leads to rigid assemblies that display considerably prolonged charge-separated states.

Semiconducting Supramolecular Organic Frameworks Assembled from a Near-Infrared Fluorescent Macrocyclic Probe and Fullerenes - Kaur, Ramandeep; Sen, Sajal; Larsen, Mads Christian; Tavares, Luciana; Kjelstrup-Hansen, Jakob; Ishida, Masatoshi; Zieleniewska, Anna; Lynch, Vincent M.; Bahring, Steffen; Guldi, Dirk Michael; Sessler, Jonathan L.; Jana, Atanu (Journal of the American Chemical Society, 2020)
We report here a new extended tetrathiafulvalene (exTTF)-porphyrin scaffold, 2, that acts as a ball-and-socket receptor for C60 and C70. Supramolecular interactions between 2 and these fullerenes serve to stabilize 3D supramolecular organic frameworks (SOFs) in the solid state formally comprising peapod-like linear assemblies. The SOFs prepared via self-assembly in this way act as "tunable functional materials", wherein the complementary geometry of the components and the choice of fullerene play crucial roles in defining the conductance properties. The highest electrical conductivity (σ = 1.3 × 10-8 S cm-1 at 298 K) was observed in the case of the C70-based SOF. In contrast, low conductivity was seen for the SOF based on pristine 2 (σ = 5.9 × 10-11 S cm-1 at 298 K). The conductivity seen for the C70-based SOF approaches that seen for other TTF-and fullerene-based supramolecular materials despite the fact that the present systems are metal-free and constructed entirely from neutral building blocks. Transient absorption spectroscopic measurements corroborated the formation of charge-transfer states (i.e., 2δ+/C60δ- and 2δ+/C70δ-, respectively) rather than fully charge separated states (i.e., 2•+/C60•- and 2•+/C70•-, respectively) both in solution (toluene and benzonitrile) and in the solid state at 298 K. Such findings are considered consistent with an ability to transfer charges effectively over long distances within the present SOFs, rather than, for example, the formation of energetically trapped ionic species.
CRIS-Team Scopus Importer:2020-07-24

Sensitized Singlet Fission in Rigidly Linked Axial and Peripheral Pentacene-Subphthalocyanine Conjugates - Gotfredsen, Henrik; Thiel, Dominik; Greißel, Phillip; Chen, Lan; Krug, Marcel; Papadopoulos, Ilias; Ferguson, Michael J.; Nielsen, Mogens Brøndsted; Torres, Tomas; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Journal of the American Chemical Society, 2023)
The goal of harnessing the theoretical potential of singlet fission (SF), a process in which one singlet excited state is split into two triplet excited states, has become a central challenge in solar energy research. Covalently linked dimers provide crucial models for understanding the role of chromophore arrangement and coupling in SF. Sensitizers can be integrated into these systems to expand the absorption bandwidth through which SF can be accessed. Here, we define the role of the sensitizer-chromophore geometry in a sensitized SF model system. To this end, two conjugates have been synthesized consisting of a pentacene dimer (SF motif) connected via a rigid alkynyl bridge to a subphthalocyanine (the sensitizer motif) in either an axial or a peripheral arrangement. Steady-state and time-resolved photophysical measurements are used to confirm that both conjugates operate as per design, displaying near unity energy transfer efficiencies and high triplet quantum yields from SF. Decisively, energy transfer between the subphthalocyanine and pentacene dimer occurs ca. 26 times faster in the peripheral conjugate, even though the two chromophores are ca. 3 angstrom farther apart than in the axial conjugate. Following a theoretical evaluation of the dipolar coupling, Vdip2, and the orientation factor, kappa 2, of both the axial (Vdip2 = 140 cm-2; kappa 2 = 0.08) and the peripheral (Vdip2 = 724 cm-2; kappa 2 = 1.46) arrangements, we establish that this rate acceleration is due to a more favorable (nearly co-planar) relative orientation of the transition dipole moments of the subphthalocyanine and pentacenes in the peripheral constellation.
CRIS-Team WoS Importer:2023-05-19

Sequential Cleavage of Lignin Systems by Nitrogen Monoxide and Hydrazine - Hofmann, Laura; Hofmann, Dagmar; Prusko, Lea; Altmann, Lisa-Marie; Heinrich, Markus (dvanced Synthesis & Catalysis, 2020)
The cleavage of representative lignin systems has been achieved in a metal-free two-step sequence first employing nitrogen monoxide for oxidation followed by hydrazine for reductive C−O bond scission. In combining nitrogen monoxide and lignin, the newly developed valorization strategy shows the particular feature of starting from two waste materials, and it further exploits the attractive conditions of a Wolff-Kishner reduction for C−O bond cleavage for the first time. (Figure presented.).
CRIS-Team Scopus Importer:2020-03-31
Keywords: Depolymerization; Hydrazine; Lignin; Nitrogen oxides; Pyrazole

Shape-Controlled Solution-Epitaxial Perovskite Micro-Crystal Lasers Rivaling Vapor Deposited Ones - Afify, Hany A.; Rehm, Viktor; Barabash, Anastasia; These, Albert; Zhang, Jiyun; Osvet, Andres; Schüßlbauer, Christoph; Thiel, Dominik; Ullrich, Tobias; Dierner, Martin; Przybilla, Thomas; Will, Johannes; et al. (Advanced Functional Materials, 2022)
Epitaxial growth methods usually need dedicated equipment, high energy consumption to maintain pure vacuum conditions and evaporation of source materials, and elevated substrate temperatures. Solution epitaxial growth requires nothing of that but is rarely used because the achieved microstructures are of low quality, not homogeneous, and finally exhibit worse performances in devices. Here, an antisolvent-vapor-assisted-crystallization of metal-halide-perovskites as a method overcoming these disadvantages is demonstrated. The methylammonium lead tribromide exhibits van-der-Waals type of epitaxial growth on mica substrates, resulting in micro-crystallites whose shape can be controlled to be either triangular micro-prism or micro-cuboid. These micro-crystallites act as optical resonators supporting various optical modes and lasing is achieved under optical excitation with low thresholds and record high environmental stability. Selecting suitable resonators from a large variety of sizes allows control of mode spacing and finally mono-mode operation, considered to be an important feature of semiconductor laser devices. The achieved results are essentially competitive to those obtained by vapor phase epitaxial microstructures, highlighting that epitaxy of high-quality optoelectronic device structures is feasible by minimum technological efforts and energy consumption, which are of increasing importance considering issues such as global warming and the current energy crisis.
Created from Fastlane, WoS look-up

Shedding light on the effective fluorophore structure of high fluorescence quantum yield carbon nanodots - Wang, Wenshuo; Wang, Bingzhe; Embrechts, Heidemarie; Damm, Cornelia; Cadranel, Alejandro; Strauß, Volker; Distaso, Monica; Hinterberger, Vanessa; Guldi, Dirk Michael; Peukert, Wolfgang (RSC Advances, 2017)
Carbon nanodots (CD) have great potential for imaging and sensing applications, due to their unique luminescence properties in combination with their low toxicity. Although CDs are currently the subject of intensive research activity, the exact structure of their effective fluorophore species has to be clarified because it can depend on the starting materials and reaction conditions. Most importantly, the limited photostability of some CDs presents an impediment to the much-needed breakthroughs required in the field. In this work, the photobleaching of CDs synthesized hydrothermally from citric acid and urea undervarious conditions is studied in detail. By visualizing changes in the absorption and fluorescence properties of CDs over time upon exposure to UV-light by means of in situ spectroscopic probes, we demonstrate a trade-off between high initial quantum yield and photostability. We found that the CDs consist of low-molecular weight fluorophores bound to extgreekp-conjugated domains (carbon core). In the case of CDs synthesized at higher reaction temperatures and/or for longer reaction times, lower initial quantum yields and higher photostability originate from partial conversion of the low-molecular weight fluorophores to extgreekp-conjugated domains during synthesis. Thus, the remaining surface bound fluorophores are bound to larger extgreekp-conjugated domains, which, in turn, enable dissipation of absorbed UV-energy and protection against photochemical damage. Reference experiments were performed with citrazinic acid – a pyridone-based structure – using ultrafast time-resolved spectroscopy, steady-state spectroscopy, and theoretical DFT simulations. We conclude that pyridone-like structures are most likely responsible for both the high quantum yields and the photobleaching of CDs.

Shell-by-Shell functionalized nanoparticles as radiosensitizers and radioprotectors in radiation therapy of cancer cells and tumor spheroids - Wedler, Vincent; Stiegler, Lisa; Gandziarowski, Teresa; Walter, Johannes; Peukert, Wolfgang; Distel, Luitpold; Hirsch, Andreas; Klein, Stefanie (Colloids and Surfaces B: Biointerfaces, 2025)
Shell-by-Shell (SbS)-functionalized NPs can be tailor-made by combining a metal oxide NP core of choice with any desired phosphonic acids and amphiphiles as 1st or 2nd ligand shell building blocks. The complementary composition of such highly hierarchical structures makes them interesting candidates for various biomedical applications, as certain active ingredients can be incorporated into the structure. Here, we used TiO2 and CoFe2O4 NPs as drug delivery tools and coated them with a hexadecylphosphonic acid and with hexadecyl ammonium phenolates (caffeate, p-coumarate, ferulate), that possess anticancer as well as antioxidant properties. These architectures were then incubated in 2D and 3D cell cultures of non-tumorigenic and tumorigenic breast cells and irradiated to study their anticancer effect. It was found that both, the functionalized TiO2 and CoFe2O4 NPs acted as strong protective agents in non-tumorigenic spheroids. In contrast, the functionalized CoFe2O4 NPs induce a higher damage in irradiated tumor spheroids compared to the functionalized TiO2 NPs. CoFe3O4 NPs act additionally as radiosensitizing agents to the tumor spheroids. The radio-enhancement of the CoFe2O4 NPs is due to the generation of highly toxic hydroxyl radicals during X-ray irradiation. The irradiation exposed the CoFe2O4 surface, releasing the anticancer drugs into the cytoplasm and making the surface Co2+ ions accessible. These surface ions catalyze the FENTON reaction. This combination of radiosensitizer and anticancer drug delivery proved to be a very effective nanotherapeutic in 2D and 3D cell cultures of breast cancer cells.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Amphiphiles; CoFe; Phenolic acids; Radioprotectors; Radiosensitizers; Shell-by-Shell functionalization; TiO

Silver cation tagged on 5,7,12,14-tetraphenyl-6,13-diazapentacene and its dihydro-form - Kinzelmann, Marina; Oschwald, Johannes; Elsen, Holger; Warmbrunn, Vera; Hauschild, Miriam; Harder, Sjoerd; Kivala, Milan; Drewello, Thomas (Physical Chemistry Chemical Physics, 2023)
The attachment of silver(i) cations to 5,7,12,14-tetraphenyl-6,13-diazapentacene and its reduced dihydro-form has been studied by electrospray ionization mass spectrometry (ESI-MS). The structure elucidation of the Ag+ complexes has been accomplished in gas-phase collision experiments in conjunction with density functional theory (DFT) calculations. The oxidized form provides a favourable cavity for the Ag+ ion, leading to the [1 : 1] complex with the highest resilience towards dissociation and severely hindering the attainment of a second molecular ligand. When the nitrogen is hydrogenated in the reduced dihydro-form, the cavity is partly blocked. This leads to a less strongly bound [1 : 1] complex ion but facilitates the attachment of a second molecular ligand to the Ag+. The resulting complex is the most stable among the [2 : 1] complexes. DFT calculations provide valuable insight into the geometries of the complex ions. Adding silver(i) to the reduced dihydro-form for cationization also induces its oxidation in solution. The oxidative dehydrogenation reaction, for which a mechanism is proposed, proceeds by first order kinetics and is markedly accelerated by day light.
CRIS-Team Scopus Importer:2023-06-23

Singlet Fission - Tykwinski, Rik R.; Guldi, Dirk Michael (Chemphotochem, 2021)
CRIS-Team WoS Importer:2021-04-09

Singlet Fission for Photovoltaics with 130 % Injection Efficiency - Kunzmann, Andreas; Gruber, Marco; Casillas Pacheco, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2018)
A novel pentacene dimer (P2) and a structurally analogous monomer (P1) were synthesized for use in n-type dye-sensitized solar cells. In P2, the triplet excited states formed by the rapid, spin-allowed process singlet fission were expected to enable carrier multiplication in comparison to the slow, spin-forbidden intersystem crossing seen in P1. A meta-positioning of the two pentacenes and the carboxylate anchor were chosen in P2 to balance the intramolecular dynamics of singlet fission and electron injection. Electron injection from energetically low-lying triplet excited states of pentacene units necessitated the intrinsic and extrinsic lowering of the Fermi level of the semiconductor. Indium-zinc oxide in the presence of Li+ was found to be the optimum choice for the photoelectrodes. Efficient electron injection from the triplet excited states of P1 and P2 was found, with a carrier multiplication of nearly 130 %.
Keywords: pentacene sensitizers; singlet fission; dye-sensitized solar cells; transient absorption spectroscopy

Singlet Fission in Carbene-Derived Diradicaloids - Ullrich, Tobias; Pinter, Piermaria; Messelberger, Julian; Haines, Philipp; Kaur, Ramandeep; Hansmann, Max M.; Munz, Dominik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2020)
Herein, we present a new class of singlet fission (SF) materials based on diradicaloids of carbene scaffolds, namely cyclic (alkyl)(amino)carbenes (CAACs). Our modular approach allows the tuning of two key SF criteria: the steric factor and the diradical character. In turn, we modified the energy landscapes of excited states in a systematic manner to accommodate the needs for SF. We report the first example of intermolecular SF in solution by dimer self-assembly at cryogenic temperatures.
CRIS-Team WoS Importer:2020-04-07

Singlet Fission in Combinatorial Diketopyrrolopyrrole-Rylene Supramolecular Films - Levine, Andrew M.; Schierl, Christoph; Basel, Bettina; Ahmed, Mehroz; Camargo, Braden A.; Guldi, Dirk Michael; Braunschweig, Adam B. (Journal of Physical Chemistry C, 2019)
Two diketopyrrolopyrroles (DPPs) and three rylenes (NDI, dPyr PDI, and dEO PDI) were combined to form six hierarchical superstructures that assemble as a result of orthogonal H-bonding and π···π stacking. The individual components and the DPP-NDI as well as DPP-PDI pairs were cast into films, and their superstructures were interrogated by electron microscopy and advanced spectroscopy. All six superstructures feature different geometries, causing subtle changes in the solid-state packing of the DPPs. Changes in inter-DPP stacking that are scaffolded by the adjacent rylenes have a subtle impact on both the excited-state dynamics and on activating new pathways such as singlet fission (SF). Our studies demonstrate the unique benefits of combinatorial supramolecular assembly in exploring the impact of structure on advanced light management in the form of SF to afford triplet quantum yields, which are as high as 65% for a correlated pair of triplets and 15% for an uncorrelated pair of triplets.
CRIS-Team Scopus Importer:2019-08-13

Singlet fission in combinatorial diketopyrrolopyrrole-rylene supramolecular films - Levine, Andrew; Schierl, Christoph; Basel, Bettina; Ahmed, Mehroz; Camargo, Braden; Guldi, Dirk Michael; Braunschweig, Adam (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-27

Singlet Fission in Enantiomerically Pure Pentacene Dimers - Papadopoulos, Ilias; Gao, Yueze; Hetzer, Constantin; Tykwinski, Rik R.; Guldi, Dirk Michael (Chemphotochem, 2020)
Singlet fission (SF), that is, producing two triplet excited states (T-1+T-1) from a single singlet excited state (S1S0), has the potential to surpass the thermodynamic Shockley-Queisser limit for solar cells of 33 %. Of great relevance for singlet fission is the (S1S0)-to-(1)(T1T1) transformation as it is the key step in driving the efficiency of SF. In the current study, we focus on the control over intramolecular interactions in enantiomerically pure platinum linked pentacene dimers, (S,S)- and (R,R)-cis-Pt. Despite the internal heavy-atom effect stemming from the presence of the Pt-centered linkers, (S,S)- and (R,R)-cis-Pt undergo quantitative and solvent dependent formation of (1)(T1T1). Implicit is an enantiomer-independent SF mediation by means of a virtual CT intermediate in a superexchange mechanism. With the help of steady-state and time-resolved spectroscopic techniques, a kinetic model is developed to describe the entire deactivation pathway following photoexcitation of (S,S)- and (R,R)-cis-Pt.
CRIS-Team WoS Importer:2020-05-02

Singlet fission in pentacene dimers - Zirzlmeier, Johannes; Lehnherr, Dan; Brana Coto, Pedro; Chernick, Erin; Casillas, Ruben; Basel, Bettina; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Singlet fission (SF) has the potential to supersede the traditional solar energy conversion scheme by means of boosting the photon-to-current conversion efficiencies beyond the 30% Shockley-Queisser limit. Here, we show unambiguous and compelling evidence for unprecedented intramolecular SF within regioisomeric pentacene dimers in room-temperature solutions, with observed triplet quantum yields reaching as high as 156 ± 5%. Whereas previous studies have shown that the collision of a photoexcited chromophore with a ground-state chromophore can give rise to SF, here we demonstrate that the proximity and sufficient coupling through bond or space in pentacene dimers is enough to induce intramolecular SF where two triplets are generated on one molecule.

Singlet Fission in Pyrene-Fused Azaacene Dimers - Mora-Fuentes, Juan P.; Papadopoulos, Ilias; Thiel, Dominik; Alvarez-Boto, Roberto; Cortizo-Lacalle, Diego; Clark, Timothy; Melle-Franco, Manuel; Guldi, Dirk Michael; Mateo-Alonso, Aurelio (Angewandte Chemie International Edition, 2019)
Singlet fission has emerged as a promising strategy to avoid the loss of extra energy through thermalization in solar cells. A family of dimers consisting of nitrogen-doped pyrene-fused acenes that undergo singlet fission with triplet quantum yields as high as 125 % are presented. They provide new perspectives for nitrogenated polycyclic aromatic hydrocarbons and for the design of new materials for singlet fission.
CRIS-Team WoS Importer:2019-12-10

Singlet fission in self-assembled PDI nanocrystals - Schierl, Christoph; Niazov-Elkan, Angelica; Shimon, Linda J. W.; Feldman, Yishay; Rybtchinski, Boris; Guldi, Dirk Michael (Nanoscale, 2018)
Upon photoexcitation, self-assembled PDI nanocrystals (S1S0) in the form of rods of 70 nm width and 1 μm length are subject to a symmetry breaking charge separation (SBCS) as the first step in the singlet fission (SF) sequence. Hereby, the correlated pair of triplet excited states 1(T1T1) is formed with a quantum yield of 122%. Decoherence and triplet diffusion within the nanocrystals affords a long-lived, uncorrelated pair of triplet excited states (T1 + T1) with a quantum yield of 24%.
CRIS-Team Scopus Importer:2022-04-14

Singulettspaltung für Photovoltaikanwendungen mit Injektionseffizienzen von bis zu 130 % - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie, 2018)

Size-Dependent Local Ordering in Melanin Aggregates and Its Implication on Optical Properties - Träg, Johannes; Duchstein, Patrick; Hennemann, Matthias; Clark, Timothy; Guldi, Dirk Michael; Zahn, Dirk (Journal of Physical Chemistry A, 2019)
We present atomic scale models of differently sized eumelanin nanoaggregates from molecular dynamics simulations combined with a simulated annealing procedure. The analysis reveals the formation of secondary structures due to π-stacking on one hand, but on the other hand a broad distribution of stack geometries in terms of stack size, horizontal displacement angles, and relative torsion angles. The displacement angle distribution, which is a measure of the occurrence of zigzag and linear stacking motives, respectively, strongly depends on the aggregate size - and is hence controlled by the interplay of surface and bulk energy terms. Semiempirical spectra calculations of small stacks (up to five protomolecules) reveal a strong dependence on the precise stack structure and allow for a direct structure-property correlation. The observed spectral shifts result in an overall spectral broadening and, hence, further support the geometric disorder model, which complements the chemical disorder model in the interpretation of eumelanin's monotonically increasing broad-band absorption.
CRIS-Team Scopus Importer:2019-10-29

Smart Shell-by-Shell Nanoparticles with Tunable Perylene Fluorescence in the Organic Interlayer - Stiegler, Lisa; Klein, Stefanie; Kryschi, Carola; Neuhuber, Winfried; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A new series of shell-by-shell (SbS)-functionalized Al2O3 nanoparticles (NPs) containing a perylene core in the organic interlayer as a fluorescence marker is introduced. Initially, the NPs were functionalized with both, a fluorescent perylene phosphonic acid derivative, together with the lipophilic hexadecylphosphonic acid or the fluorophilic (1 H,1 H,2 H,2H-perfluorodecyl)phosphonic acid. The lipophilic first-shell functionalized NPs were further implemented with amphiphiles built of aliphatic chains and polar head-groups. However, the fluorophilic NPs were combined with amphiphiles consisting of fluorocarbon tails and polar head-groups. Depending on the nature of the combined phosphonic acids and the amphiphiles, tuning of the perylene fluorescence can be accomplished due variations of supramolecular organization with the shell interface. Because the SbS-functionalized NPs dispose excellent dispersibility in water and in biological media, two sorts of NPs with different surface properties were tested with respect to biological fluorescent imaging applications. Depending on the agglomeration of the NPs, the cellular uptake differs. The uptake of larger agglomerates is facilitated by endocytosis, whereas individualized NPs cross directly the cellular membrane. Also, the larger agglomerates were preferentially incorporated by all tested cells.
CRIS-Team Scopus Importer:2020-12-11
Keywords: amphiphiles; fluorescent imaging; hydro-; lipo-; fluoro-philic/phobic; perylene chromophore; shell-by-shell (SbS)-functionalization

Solar Energy Storage: Competition between Delocalized Charge Transfer and Localized Excited States in the Norbornadiene to Quadricyclane Photoisomerization - Alex, Wiebke; Lorenz, Patrick; Henkel, Christian; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2021)
We describe for the first time the full reaction coordinate regarding the photoisomerization of red-absorbing norbornadienes (NBDs) to quadricyclanes (QCs). Our studies go beyond steady-state investigations by using an arsenal of time-resolved techniques. Importantly, the red absorption of NBDs is made possible by a different charge-transfer character; adjusting its strength enables control over the photoreversibility of the rearrangement. In the case of strong charge-transfer character (a weakly electron-withdrawing ester and a strongly electron-donating dimethylaniline), photoirradiation with visible light into the delocalized charge-transfer absorption of NBD affords QC reversibly. In stark contrast, UV photoirradiation into the NBD localized excited state leads to a photoinduced degradation and cannot be back-isomerized to NBD under any circumstances. If the charge-transfer character is weak (a weakly electron-withdrawing ester and a weakly electron-donating phenyl), reversibility is seen independently of the photoirradiation light.
CRIS-Team WoS Importer:2022-01-14

Solar Energy Storage: Competition between Delocalized Charge Transfer and Localized Excited States in the Norbornadiene to Quadricyclane Photoisomerization - Alex, Wiebke; Lorenz, Patrick; Henkel, Christian; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2022)

Solution and solid-state interactions in a supramolecular ruthenium photosensitizer-polyoxometalate aggregate - Heußner, Kirsten; Peuntinger, Katrin; Rockstroh, Nils; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Rau, Sven; Streb, Carsten (Chemical Communications, 2011)
The intermolecular interactions between a ruthenium-based photosensitizer ([Ru(tbbpy)(biH)]) and a molecular metal oxide ([β-MoO]) are investigated in solution and in the solid state. The supramolecular interactions were studied using H-NMR, UV-Vis and emission spectroscopy, ESI mass spectrometry and single-crystal X-ray diffraction. The formation of supramolecular aggregates was observed both in the crystal lattice and in solution. In addition, it is shown that aggregation in solution can be controlled by the competitive formation of ion pairs. © 2011 The Royal Society of Chemistry.

Solution-based intramolecular singlet fission in cross-conjugated pentacene dimers - Zirzlmeier, Johannes; Casillas, Ruben; Reddy, Rajagopala; Coto, Pedro B.; Lehnherr, Dan; Chernick, Erin; Papadopoulos, Ilias; Thoss, Michael; Tykwinski, Rik; Guldi, Dirk Michael (Nanoscale, 2016)
We show unambiguous and compelling evidence by means of pump-probe experiments, which are complemented by calculations using ab initio multireference perturbation theory, for intramolecular singlet fission (SF) within two synthetically tailored pentacene dimers with cross-conjugation, namely XC1 and XC2. The two pentacene dimers differ in terms of electronic interactions as evidenced by perturbation of the ground state absorption spectra stemming from stronger through-bond contributions in XC1 as confirmed by theory. Multiwavelength analysis, on one hand, and global analysis, on the other hand, confirm that the rapid singlet excited state decay and triplet excited state growth relate to SF. SF rate constants and quantum yields increase with solvent polarity. For example, XC2 reveals triplet quantum yields and rate constants as high as 162 ± 10% and (0.7 ± 0.1) × 1012 s-1, respectively, in room temperature solutions.
EAM Import::2019-03-13

Solution behavior of iron(iii) and iron(ii) porphyrins in DMSO and reaction with superoxide. Effect of neighboring positive charge on thermodynamics, kinetics and nature of iron-(su)peroxo product - Dürr, Katharina L.; Tröppner, Oliver; Olah, J.; Li, Jing; Zahl, Achim; Drewello, Thomas; Jux, Norbert; Harvey, Jeremy N.; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2012)

Solvent-Dependent Singlet Fission in Diketopyrrolopyrrole Dimers: A Mediating Charge Transfer versus a Trapping Symmetry-Breaking Charge Separation - Papadopoulos, Ilias; Álvaro-Martins, Maria João; Molina, Desiré; McCosker, Patrick Michael; Keller, Paul A.; Clark, Timothy; Sastre-Santos, Ángela; Guldi, Dirk Michael (Advanced Energy Materials, 2020)
Three diketopyrrolopyrrole (DPP) dimers, linked via different dithienylphenylene spacers, ortho-DPP (o-DPP), meta-DPP (m-DPP), and para-DPP (p-DPP), are synthesized, characterized, and probed in light of intramolecular singlet fission (i-SF). Importantly, the corresponding DPP reference (DPP-Ref) singlet and triplet excited state energies of 2.22 and 1.04 eV, respectively, suggest that i-SF is thermodynamically feasible. The investigations focus on the impact of the relative positioning of the DPPs, and give compelling evidence that solvent polarity and/or spatial overlap govern i-SF dynamics and efficiencies. Polar solvents make the involvement of an intermediate charge transfer (CT) state possible, followed by the population of 1(T1T1) and subsequently (T1 + T1), while spatial overlap drives the mutual interactions between the DPPs. In o-DPP, the correct balance between polar solvents and spatial overlap leads to the highest triplet quantum yield (TQY) of 40%. Notable is the superimposition of CT and triplet excited states, preventing an accurate TQY determination. For m-DPP, poorer spatial overlap correlates with weaker CT character and manifests in a TQY of 11%. Strong CT character acts as a trap and prevents i-SF, as found with p-DPP. The DPP separation is decisive, enabling a symmetry-breaking charge-separated state rather than CT formation, shutting down the formation 1(T1T1).
CRIS-Team Scopus Importer:2020-10-09
Keywords: charge transfer states; diketopyrrolopyrrole dimers; intramolecular singlet fission

Spectroscopic and electrochemical characterization of heteropoly acids for their optimized application in selective biomass oxidation to formic acid - Albert, Jakob; Lüders, Daniela; Bösmann, Andreas; Guldi, Dirk Michael; Wasserscheid, Peter (Green Chemistry, 2014)
Different Keggin-type polyoxometalates have been synthesized and characterized in order to identify optimized homogeneous catalysts for the selective oxidation of biomass to formic acid (FA) using oxygen as an oxidant and p-toluenesulfonic acid as an additive. Applying the optimized polyoxometalate catalyst system H[PVMoO ] (HPA-5), a total FA-yield (with respect to carbon in the biogenic feedstock) of 60% for glucose within 8 h reaction time and 28% for cellulose within 24 h reaction time could be achieved. The transformation is characterized by its mild reaction temperature, its excellent selectivity to FA in the liquid product phase and its applicability to a very wide range of biogenic raw materials including non-edible biopolymers and complex biogenic mixtures. © 2014 The Royal Society of Chemistry.

Spectroscopic studies on inclusion properties of fullerenocalix[4]arene conjugates with metal ions - Luo, Chuping; Guldi, Dirk Michael; Soi, Antonio; Hirsch, Andreas (Journal of Physical Chemistry A, 2005)
Metal-chelating properties - in the ground and excited states - of fullerenocalix[4]arenes containing two malonamide substituents at the upper rim and four alkyl ester chains at the lower rim have been studied by means of steady-state absorption, fluorescence spectroscopy, and time-resolved transient absorption spectra. In particular, the influence that Ag enforces on the fullerene electronic spectra is due to direct interactions between Ag and the surface of C . The effects stemming from Na , Mg , and Ba , on the other hand, are indirect and are introduced through chelating the metal ions to the calix[4]arene moiety. They strongly depend on the molecular structure of the fullerenocalix[4]arenes. No spectroscopic evidence was obtained for any influence caused by Mn , although the malonamide groups provide good chelating ability even for this transition metal ion. © 2005 American Chemical Society.

Stabilisation of emissive charge-separated states in π-stacked donor-acceptor ensembles - Guldi, Dirk Michael; Scheloske, Michael; Hirsch, Andreas (Photosynthesis Research, 2006)
π-Stacking of an electron donor and acceptor minimises reorganisation energy and stabilises charge-separated state. © Springer 2006.

Stability of [10-12]cycloparaphenylene complexes with pristine fullerenes C76, 78, 84 and endohedral metallofullerenes M3N@C78, 80 - Freiberger, Markus; Stasyuk, Olga A.; Perez-Ojeda Rodriguez, Maria Eugenia; Echegoyen, Luis; Sola, Miquel; Drewello, Thomas (Nanoscale, 2024)
[n]Cycloparaphenylenes ([n]CPPs) are strained macrocycles, comprising only sp2-hybridized carbon atoms. In recent years, [n]CPPs have become of great research interest in the field of supramolecular chemistry since their special structure enables the formation of novel host–guest complexes. In this work, we investigate the gas-phase chemistry of noncovalent complexes of [10–12]CPP with the pristine fullerenes C76/78/84 and the endohedral metallofullerenes (EMFs) Sc3N@D3h-C78, Sc3N@D5h-C80 and M3N@Ih-C80 (M = Sc, Y, Lu, Gd). The [1 : 1] complexes with [10–12]CPP are detected as radical cations. The stability and charge distributions of these complexes are studied using energy-resolved collision-induced dissociation (ER-CID). Our results assess the size complementarity, the influence of fullerene symmetry and size as well as the role of the metal size inside the EMF on the binding affinity and complex stability. Two main trends in complex stability have been found: First, [10–12]CPP form more stable complexes with EMFs than with pristine fullerenes and second, all complexes of EMFs with the C80 skeleton show similar stability despite the different metal clusters encapsulated. Another major finding is the fact that [11]CPP is generally the most suitable host for fullerenes with a C76/78/80/84 skeleton. Considering the charge distributions, we observe the existence of two different fragmentation channels for complexes with EMFs where the radical cation is either located at the CPP or at the EMF: (1) [n]CPP+˙ + EMF and (2) [n]CPP + EMF+˙. This behavior allows a clear distinction of the cage isomers ([11]CPP⊃Sc3N@Ih-C80)+˙ and ([11]CPP⊃Sc3N@D5h-C80)+˙ in the MS2 experiment. The experimental results are accompanied by density functional theory (DFT) calculations of ionization potentials (IPs) and fragmentation energies. The computational results fully confirm the measured order of complex stabilities and explain the prevalence of EMF or CPP signals in the spectra by the trend in ionization potential

Stability of Odd- Versus Even-Electron Gas-Phase (Quasi)Molecular Ions Derived from Pyridine-Substituted N-Heterotriangulenes - Hitzenberger, Jakob; Dral, Pavlo O.; Meinhardt, Ute; Clark, Timothy; Thiel, Walter; Kivala, Milan; Drewello, Thomas (ChemPlusChem, 2017)
Electrospray ionisation of N-heterotriangulenes (i.e., dimethyl-methylene-bridged triphenylamines) with up to three pyridyl groups at their periphery, produces the true radical cation ([M](+center dot)) and the protonated molecule ([M+H](+)) simultaneously. These ions are studied as model systems to illustrate the stability alternation of odd-versus even-electron ions in energy-dependent collision-induced dissociation (CID) experiments. All ions show the same fragmentation pattern, the consecutive loss of three methyl radicals ((CH3)-C-center dot) from the dimethylmethylene bridges of the central triangulene core. [M](+center dot) ions dissociate at much lower collision energies than their [M+H](+) counterparts. The radical cation forms a singlet fragment with an extended aromatic system that is energetically favoured. Ab initio and density functional theory calculations support this interpretation and allow the assignment of the electronic structure of the fragment ions. Consecutive collision-induced dissociations provide a better match with theory when studied with an ion trap, rather than a linear quadrupole. This is attributed to the resonant nature of the excitation of intermediate ions.
Keywords: ab initio calculations; collision-induced dissociation; density functional calculations; electrospray ionisation; mass spectrometry; N-heterotriangulenes

Stabilizing ion and radical ion pair states in a paramagnetic endohedral metallofullerene/π-extended tetrathiafulvalene conjugate - Takano, Yuta; Obuchi, Shota; Mizorogi, Naomi; Garcia, Raul; Angeles Herranz, M.; Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Martin, Nazario; Nagase, Shigeru; Akasaka, Takeshi (Journal of the American Chemical Society, 2012)
Electron donor-acceptor conjugates of paramagnetic endohedral metallofullerenes and π-extended tetrathiafulvalene (exTTF) were synthesized, characterized, and probed with respect to intramolecular electron transfer involving paramagnetic fullerenes. UV-vis-NIR absorption spectroscopy complemented by electrochemical measurements attested to weak electronic interactions between the electron donor, exTTF, and the electron acceptor, La@C , in the ground state. In the excited state, photoexcitation powers a fast intramolecular electron transfer to yield an ion and radical ion pair state consisting of one-electron-reduced La@C and of one-electron-oxidized exTTF. © 2012 American Chemical Society.

Stable electron donor-acceptor nanohybrids by interfacing n-type TCAQ with p-type single-walled carbon nanotubes - Romero, Carlos; Garcia, Raul; Angeles Herranz, Maria; Rodriguez-Perez, Laura; Sanchez-Navarro, Macarena; Rojo, Javier; Martin, Nazario; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2013)
Tuning the electronics of nanotubes: Electron-accepting 11,11,12,12-tetracyano-9,10-anthraquinodimethane (TCAQ) nanotweezers endowed with a carboxylic acid-containing dendrimeric moiety form exceptionally stable n-/p-type dispersions with single-walled carbon nanotubes (SWCNTs) in water. Upon photoexcitation, the nanohybrids undergo a less common electron transfer from the SWCNTs to the TCAQ nanotweezers (see picture). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Stable radical anions inside fullerene cages: Formation of reversible electron transfer systems - Tsuchiya, Takahiro; Wielopolski, Mateusz; Sakuma, Noriko; Mizorogi, Naomi; Akasaka, Takeshi; Kato, Tatsuhisa; Guldi, Dirk Michael; Nagase, Shigeru (Journal of the American Chemical Society, 2011)
The complexation behavior of La @C dimetallofullerenes with organic donor molecules (D) in solution has been investigated. It has been shown that La @C and D form 1:1 complexes as a result of electron transfer interactions in the ground state. The equilibrium between La @C /D and [La @C ] /[D] in solution is readily controlled by changing the temperature and solvent. © 2011 American Chemical Society.

Star-shaped magnesium tetraethynylporphyrin bearing four peripheral electron-accepting diketopyrrolopyrrole functionalities for organic solar cells - Wang, Huan; Yue, Qihui; Nakagawa, Takafumi; Zieleniewska, Anna; Okada, Hiroshi; Ogumi, Keisuke; Ueno, Hiroshi; Guldi, Dirk Michael; Zhu, Xiaozhang; Matsuo, Yutaka (Journal of Materials Chemistry A, 2019)
Magnesium tetraethynylporphyrins bearing four electron-deficient diketopyrrolopyrrole (DPP; Mg-TEP-DPP4) units were synthesized by Sonogashira coupling, and their optical and electrochemical properties were investigated. The energy levels were effectively tuned by DPP with or without electron-withdrawing end-caps. Importantly, all the Mg-TEP-DPP4 molecules have broad absorption bands across the visible and near-infrared regions. The time-dependent excited state features of Mg-TEP-DPP4 and their kinetics were investigated by femtosecond transient absorption spectroscopy in combination with multiwavelength and global/target analyses of time-resolved spectra. Importantly, the charge-separated state was demonstrated to undergo recombination within 253 ps in benzonitrile. Bulk heterojunction organic solar cells fabricated with Mg-TEP-DPP4:PC61BM exhibited a power conversion efficiency of 7.40% after solvent vapor annealing, which enabled balanced charge carrier transport, reduced charge recombination, and favorable charge separation and collection.
CRIS-Team WoS Importer:2019-03-15

Step-by-step self-assembled hybrids that feature control over energy and charge transfer - Grimm, Bruno; Schornbaum, Julia; Jasch, Hannelore; Trukhina, Olga; Wessendorf, Florian; Hirsch, Andreas; Torres, Tomas; Guldi, Dirk Michael (Proceedings of the National Academy of Sciences of the United States of America, 2012)
In the current work, we have documented the use of two complementary supramolecular motifs, namely multipoint hydrogen bonding and metal complexation, as a means to control the step-by- step assembly of a panchromatically absorbing and highly versatile solar energy conversion system. On one hand, two different perylenediimides (1a/1b) have been integrated together with a metalloporphyrin (2) by means of the Hamilton receptor/cyanuric acid hydrogen bonding motif into energy transduction systems 1a•2 or 1b•2. Steady-state and time-resolved measurements corroborated that upon selective photoexcitation of the perylenediimides (1a/1b), an energy transfer evolved from the singlet excited state of the perylenediimides (1a/1b) to that of the metalloporphyrin (2). On the other hand, fullerene (3) and metalloporphyrin (2) form the electron donor-acceptor system 2•3 via axial complexation. Photophysical measurements confirm that an electron transfer prevails from the singlet excited state of 2 to the elec-tron- accepting 3. The correspondingly formed radical ion pair state decays with a lifetime of 1.0 ± 0.1 ns. As a complement to the aforementioned, the energy transduction features of 1a•2 were combined with the electron donor-acceptor characteristics of 2•3 to afford 1a•2•3. To this end, time-resolved measurements reveal that the initially occurring energy-transfer interaction (53 ± 3 ps) between 1a/1b and 2 is followed by an electron transfer (12 ± 1 ps) from 2 to 3. From multiwavelength analyses, the lifetime of the radical ion pair state in 1a•2•3 - as a product of a cascade of light-induced energy and electron transfer - was derived as 3.8 ± 0.2 ns.

Strong Electronic Communication in Linearly Elongated Rylenes Featuring Tunable Bridges - Dobeneck, Michaela; Kaur, Ramandeep; Platzer, Benedikt; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A modified synthetic pathway towards perylene-perylene dimers and a facile purification method to obtain the regioisomerically pure syn- and anti-isomers are reported. In addition, a novel perylene-naphthalene heterodimer with 30 conjugated π-electron pairs was designed and synthesized on the basis of a previously described precursor and the resulting regioisomers were separated from each other. Thereby, the opto-electronic properties of the linearly elongated chromophores could be investigated regarding the differences in length of their aromatic system and the configuration of the isomers. Further tuning of their energy gaps was realized via protonation and methylation of the dibenzimidazole-bridging unit. Extraordinary red-shifts of the absorption maxima of 62 nm for the methylated and 92 nm for the protonated perylene-perylene anti-isomer could be achieved. Moreover, the maxima for the syn-isomer could be shifted bathochromically by 87 and 113 nm, respectively.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Chromophores; Dyes/Pigments; Methylation; Perylene; π Conjugation

Strong electronic coupling and electron transfer in a Ce2@: I h-C80-H2P electron donor acceptor conjugate - Rudolf, Marc; Feng, Lai; Slanina, Zdenek; Wang, Weiwei; Nagase, Shigeru; Akasaka, Takeshi; Guldi, Dirk Michael (Nanoscale, 2016)
A newly designed electron donor-acceptor conjugate, namely Ce2@Ih-C80-H2P consisting of an endohedral dimetallofullerene Ce2@Ih-C80 and a free-base prophyrin (H2P), has been synthesized and systematically investigated. Basic characterization by means of NMR spectroscopy, steady-state absorption spectroscopy, and electrochemistry points to a folded configuration with sizeable interactions between Ce2@Ih-C80 and H2P. Complementary DFT optimization also results in the same conclusions. Time-resolved absorption spectroscopic investigations corroborate the formation of the (Ce2)-@Ih-C80-(H2P)+ radical ion pair state in non-polar as well as polar media. Overall, the modus operandi is an ultrafast through-space electron transfer enabled by the folded configuration in the ground and excited state.
CRIS-Team Scopus Importer:2023-03-07

Structural and Electronic Impacts of the Axial Substitution at the Phosphorus Center of C(sp3)-Bridged P-Heterotriangulenes - Harrer, Siegfried; Schühle, Johannes D.R.; Neiß, Christian; Günthert, Marina; Mittmann, Lena; Reule, Andrea; Leitner, Jonas; Rominger, Frank; Görling, Andreas; Kivala, Milan (European Journal of Organic Chemistry, 2024)
The structural and electronic properties of the dimethylmethylene-bridged P-heterotriangulene have been systematically modulated by functionalization of its phosphorus center. The optoelectronic properties of the obtained derivatives in solution were characterized by UV/Vis absorption and emission spectroscopy, cyclic voltammetry and 31P NMR spectroscopy. The solid state structures were analyzed by X-ray crystallography. The experimental results were corroborated by density functional theory calculations which revealed the crucial influence of the axial substitution on the bowl-shaped geometry of the phosphorus-centered polycyclic scaffold, which is proportional to the s-character of the P−X bond. The advantage of the bowl-shaped P-heterotriangulene scaffold was demonstrated by successful co-crystallization with fullerene C60.
CRIS-Team Scopus Importer:2024-05-10
Keywords: bowl-shaped; bridged triarylphosphines; density functional theory calculations; phosphorus heterocycles; X-ray crystallography

Structural properties of ruthenium biimidazole complexes determining the stability of their supramolecular aggregates - Rockstroh, Nils; Peuntinger, Katrin; Görls, Helmar; Guldi, Dirk Michael; Heinemann, Frank Wilhelm; Schäfer, Bernhard; Rau, Sven (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
The results of a detailed investigation of the influence of substituents in a variety of ruthenium biimidazole-type complexes [Ru(R-bpy)2(Ŕ-bi(bz) imH)] (R = H, Bu; Ŕ = H, Me; bi(bz)imH = 2,2-bi(benz)imidazole) on selected structural and photophysical properties is reported. The photo-physical properties are only marginally influenced by the substituents at the bipyridine and the bi-imidazole core. All complexes show intense absorptions in the visible range of the spectrum with maxima around 475 nm, and emission from the formed excited state occurs at wavelengths between 650 and 670 nm. The comparison of structural properties determined by X-ray analysis within a series of related complexes shows that the Ru-N bond lengths to the coordinated bipyridines are not significantly influenced by the substituents, but slight differences in the Ru-N bond lengths to the biimidazole-type ligands can be detected. The reactions between ruthenium complexes containing different biimidazole-type ligands with the sulfate dianion, however, show a strong correlation between the substituents at the biimidazole core and the solubility of the product. The bibenzimidazole-containing complexes precipitate from aqueous solution whereas the ruthenium complex containing unsubstituted biimidazole stays in solution. The solid-state structure of one example of the sulfate-containing products (2b) shows that strong hydrogen bonds between the secondary amine function of the bibenzimidazole and the oxygen functionalities of the sulfate contribute to this unexpected behavior. © 2010 Verlag der Zeitschrift für Naturforschung, Tubingen.

Studies on an iron(iii)-peroxo porphyrin. Iron(iii)-peroxo or iron(ii)-superoxo? - Dürr, Katharina L.; Olah, Julianna; Davydov, Roman; Kleimann, Michael; Li, Jing; Lang, Nina; Puchta, Ralph; Hübner, Eike; Drewello, Thomas; Harvey, Jeremy N.; Jux, Norbert; Ivanovic-Burmazovic, Ivana (Dalton Transactions, 2010)
We demonstrate that a one electron reduced product of the heme iron dioxygen adduct exists in solution not only as the commonly accepted iron(iii)-peroxo species, but coexists with its isomeric iron(ii)-superoxo form. This unusual reduced metal-superoxide adduct [M(ii)-O] is recently reported as a reactive intermediate in the case of non-heme extradiol dioxygenases and could also be generated by cryoreduction of a heme Fe-O adduct. The existence of iron(ii)-superoxo species in solution is consistent with IR, EPR, mass and Mössbauer spectra. The equilibrium between heme iron(iii)-peroxo and iron(ii)-superoxo forms is supported by density functional theory and explains our previous finding that upon release of coordinated (su)peroxide a corresponding iron(ii) complex remains. These results shed new light on the nature of heme iron(iii)-peroxo species that are key intermediates in the metalloenzyme-catalyzed dioxygen and hydrogen peroxide activation. © 2010 The Royal Society of Chemistry.

Subphthalocyanine-polymethine cyanine conjugate: An all organic panchromatic light harvester that reveals charge transfer - Nieto, Carlos Romero; Guilleme, Julia; Villegas, Carmen; Luis Delgado, Juan; Gonzalez-Rodriguez, David; Martin, Nazario; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
The synthesis and photophysical characterization of a subphthalocyanine- polymethine cyanine panchromatic light harvester is described. The new conjugate shows the extraordinary absorption features of both constituents and reveals electron transfer that evolves from both constituents. © 2011 The Royal Society of Chemistry.

Subphthalocyanines Axially Substituted with a Tetracyanobuta-1,3-diene-Aniline Moiety: Synthesis, Structure, and Physicochemical Properties - Winterfeld, Kim; Lavarda, Giulia; Guilleme, Julia; Sekita, Michael; Guldi, Dirk Michael; Torres, Tomas; Bottari, Giovanni (Journal of the American Chemical Society, 2017)
A 1,1,4,4-tetracyanobuta-1,3-diene (TCBD)-aniline moiety has been introduced, for the first time, at the axial position of two subphthalocyanines (SubPcs) peripherally substituted with hydrogen (H12SubPc) or fluorine atoms (F12SubPc). Single-crystal X-ray analysis of both SubPc-TCBD-aniline systems showed that each conjugate is a racemic mixture of two atropisomers resulting from the almost orthogonal geometry adopted by the axial TCBD unit, which were separated by chiral high-performance liquid chromatography. Remarkably, the single-crystal X-ray structure of one atropisomer of each SubPc-TCBD-aniline conjugate has been solved, allowing to unambiguously assign the atropisomers’ absolute configuration, something, to the best of our knowledge, unprecedented in TCBD-based conjugates. Moreover, the physicochemical properties of both SubPc-TCBD-aniline racemates have been investigated using a wide range of electrochemical as well as steady-state and time-resolved spectroscopic techniques. Each of the two SubPc-TCBD-aniline conjugates presents a unique photophysical feature never observed before in SubPc chemistry. As a matter of fact, H12SubPc-TCBD-aniline showed significant ground-state charge transfer interactions between the H12SubPc macrocycle and the electron-withdrawing TCBD unit directly attached at its axial position. In contrast, F12SubPc-TCBD-aniline gave rise to an intense, broad emission, which red shifts upon increasing the solvent polarity and stems from an excited complex (i.e., an exciplex). Such an exciplex emission, which has also no precedent in TCBD chemistry, results from intramolecular interactions in the excited state between the electron-rich aniline and the F12SubPc π-surface, two molecular fragments kept in spatial proximity by the “unique” three-dimensional geometry adopted by the F12SubPc-TCBD-aniline. Complementary transient absorption studies were carried out on both SubPc-TCBD-aniline derivatives, showing the occurrence, in both cases, of photoinduced charge separation and corroborating the formation of the aforementioned intramolecular exciplex in terms of a radical ion pair stabilized through-space.
CRIS-Team Scopus Importer:2022-04-14

Subphthalocyanine-tetracyanobuta-1,3-diene-aniline conjugates: Stereoisomerism and photophysical properties - Winterfeld, Kim; Lavarda, Giulia; Guilleme, Julia; Guldi, Dirk Michael; Torres, Tomas; Bottari, Giovanni (Chemical Science, 2019)
Two subphthalocyanines (SubPcs) decorated at their peripheral (SubPc 1) or peripheral and axial (SubPc 2) positions with tetracyanobuta-1,3-diene (TCBD)-aniline moieties have been prepared as novel electron donor-acceptor (D-A) conjugates. In 1 and 2, the multiple functionalization of C3-symmetric SubPcs by TCBD moieties, each of them having a chiral axis, results in the formation of several stereoisomers. Variable temperature 1H-NMR studies in chlorinated solvents suggest that these latter species, which are detected at low temperatures, rapidly interconvert-on the NMR timescale-into each other at room temperature. Beside their unique structural and stereochemical features, 1 and 2 present interesting physicochemical properties. Steady-state absorption and fluorescence, as well as electrochemical studies on 1 and 2 clearly point to an important degree of electronic communication between the SubPc, the TCBD and the aniline subunits. Moreover, in both derivatives, photoexcitation of the SubPc moiety yields charge transfer products involving the electron-rich SubPc moiety and the electron-withdrawing TCBD fragment. Interestingly, such polarized excited state species evolve in 1 and 2 in different ways. While in the former compound, it directly decays to the ground state, the fourth axial TCBD moiety in 2 leads to the formation of an intermediate fully charge separated state prior to the ground state deactivation.
CRIS-Team Scopus Importer:2019-12-31

Substituting TiCl4-Carbon Nanohorn Interfaces for Dye-Sensitized Solar Cells - Casillas Pacheco, Ruben; Lodermeyer, Fabian; Costa, Ruben Dario; Prato, Maurizio; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
An easy-to-implement strategy to introduce carbon nanohorns as interlayers in the photoelectrode of a dye-sensitized solar cell without affecting its overall performance is presented. This provides a clean, easy, and ecofriendly alternative to achieve highly efficient cells.

Substituting TiCl4-carbon nanohorn interfaces for dye-sensitized solar cells - Casillas, Ruben; et al. (Advanced Energy Materials, 2014)
Keywords: carbon nanohorns; carbon allotropes; nanocarbon-based interfaces; dye-sensitized solar cells

Sulfur rich electron donors-formation of singlet versus triplet radical ion pair states featuring different lifetimes in the same conjugate - Saha, Avishek; Chen, Muqing; Lederer, Marcus; Kahnt, Axel; Lu, Xing; Guldi, Dirk Michael (Chemical Science, 2017)
An unprecedented family of novel electron-donor acceptor conjugates based on fullerenes as electron acceptors, on one hand, and triphenyl amines as electron donors, on the other hand, have been synthesized and characterized in a variety of solvents using steady state absorption/emission as well as transient absorption spectroscopy. These are unprecedented in terms of their outcome of radical ion pair formation, that is, the singlet versus triplet excited state. This was corroborated by femto/nanosecond pump probe experiments and by molecular orbital calculations. Not only has the donor strength of the triphenylamines been systematically altered by appending one or two sulfur rich dithiafulvenes, but the presence of the latter changed the nature of the radical ion pair state. Importantly, depending on the excitation wavelength, that is, either where the fullerenes or where the triphenylamines absorb, short-lived or long-lived radical ion pair states, respectively, are formed. The short-lived component with a lifetime as short as 6 ps has singlet character and stems from a fullerene singlet excited state precursor. In contrast, the long-lived component has a lifetime of up to 130 ns in THF, has triplet character, and evolves from a triplet excited state precursor. Key in forming more than three orders of magnitude longer lived radical ion pair states is the presence of sulfur atoms, which enhance spin-orbit coupling and, in turn, intersystem crossing. Independent confirmation for the singlet versus triplet character came from temperature dependent measurements with a focus on the radical ion pair state lifetimes. Here, activation barriers of 2.4 and 10.0 kJ mol-1 for the singlet and triplet radical ion pair state, respectively, were established.
CRIS-Team Scopus Importer:2022-04-14

Superhelicenes in the gas phase: experimental and computational evidence of stable radical cation dimers - Kinzelmann, Marina; Reger, David; Warmbrunn, Vera; Lungerich, Dominik; Jux, Norbert; Drewello, Thomas (Chemical Communications, 2023)
Electrospray-ionization mass spectrometry (ESI-MS) readily produces stable radical cation pi-dimers of the superhelicenes. Energy-resolved collision experiments reveal the dissociation of the dicationic dimer into two singly charged superhelicenes. DFT calculations indicate that open-shell dications composed of two radical cations are thermochemically more attractive than the closed-shell dimer formed by a doubly charged and a neutral superhelicene.
CRIS-Team WoS Importer:2023-05-12

Superparamagnetic iron oxide nanoparticles as novel x-ray enhancer for low-dose radiation therapy - Klein, Stefanie; Sommer, Anja; Distel, Luitpold; Hazemann, Jean-Louis; Kroener, Wolfgang; Neuhuber, Winfried; Müller, Paul; Proux, Olivier; Kryschi, Carola (Journal of Physical Chemistry B, 2014)
Superparamagnetic iron oxide nanoparticles (SPIONs) with a mixed phase composition (γ-FeO)(Fe O)and sizes between 9 and 20 nm were synthesized via coprecipitation and were either left uncoated or subsequently surface-stabilized with citrate or malate anions. The sizes, morphology, surface chemistry, and magnetic properties of the nanoparticles were characterized using transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, and superconducting quantum interference device measurements, respectively. Cellular uptake and intracellular distribution in normal tissue and tumor cells were verified by TEM images. X-ray-induced changes of the oxidation state and site geometries of surface iron ions of uncoated and citrate-coated SPIONs were explored by collecting Fe K-edge X-ray absorption spectroscopy data. The potential applicability of citrate- and malate-coated SPIONs as an X-ray enhancer for radiation cancer therapy was substantiated by their drastic enhancement of the concentration of reactive oxygen species (ROS) in X-ray irradiated tumor cells. © 2014 American Chemical Society.

Superparamagnetic iron oxide nanoparticles as radiosensitizer via enhanced reactive oxygen species formation - Klein, Stefanie; Sommer, Anja; Distel, Luitpold; Neuhuber, Winfried; Kryschi, Carola (Biochemical and Biophysical Research Communications, 2012)
Internalization of citrate-coated and uncoated superparamagnetic iron oxide nanoparticles by human breast cancer (MCF-7) cells was verified by transmission electron microscopy imaging. Cytotoxicity studies employing metabolic and trypan blue assays manifested their excellent biocompatibility. The production of reactive oxygen species in iron oxide nanoparticle loaded MCF-7 cells was explained to originate from both, the release of iron ions and their catalytically active surfaces. Both initiate the Fenton and Haber-Weiss reaction. Additional oxidative stress caused by X-ray irradiation of MCF-7 cells was attributed to the increase of catalytically active iron oxide nanoparticle surfaces. © 2012 Elsevier Inc.

Supramolecular assembly of a quasi-linear heterofullerene-porphyrin dyad - Hauke, Frank; Swartz, Angela; Guldi, Dirk Michael; Hirsch, Andreas; Hauke, Frank (Journal of Materials Chemistry, 2002)
A novel supramolecular dyad (Zn-ttbpp-pyridine-CN) - with a quasi-linear geometry - involving a heterofullerene acceptor and a zinc tetrakis(p-tert-butylphenyl)porphyrin (Zn-ttbpp) donor was assembled via axial coordination. Depending on the solvent either photoinduced singlet-singlet energy transfer or electron transfer was observed. The latter process takes place in o-dichlorobenzene as solvent and leads to the corresponding charge-separated state, that is, the π-radical anion of CN and the π-radical cation of Zn-ttbpp.

Supramolecular assembly of multicomponent photoactive systems via cooperatively coupled equilibria - Garcia-Iglesias, Miguel; Peuntinger, Katrin; Kahnt, Axel; Krausmann, Jan; Vazquez, Purificacion; Gonzalez-Rodriguez, David; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2013)
Here, we show that the synergistic interplay between two binding equilibria, acting at different sites of a (Zn)phthalocyanine-amidine molecule (Pc1), enables the dissociation of the photoinactive phthalocyanine dimer (Pc1) into a three-component system, in which a sequence of light harvesting, charge separation, and charge shift is successfully proven. The aforementioned dimer is assembled by dual amidine-Zn(II) coordination between neighboring Pc1 molecules and gives rise to high association constants (K ≈ 10 M). Such extraordinary stability hampers the individual binding of either carboxylic acid ligands through the amidine group or pyridine-type ligands through the Zn(II) metal atom to (Pc1). However, the combined addition of both ligands, which cooperatively bind to different sites of Pc1 through distinct noncovalent interactions, efficiently shifts the overall equilibrium toward a photoactive tricomponent species. In particular, when a fullerene-carboxylic acid (C A) and either a dimethylamino-pyridine (DMAP) or a phenothiazine-pyridine ligand (PTZP) are simultaneously present, the photoactivity is turned on and evidence is given for an electron transfer from photoexcited Pc1 to the electron-accepting CA that affords the DMAP-Pc1-CA or PTZP-Pc1 -CA radical ion pair states. Only in the latter case does a cascade of photoinduced electron transfer processes afford the PTZP-Pc1-CA radical ion pair state. The latter is formed via a thermodynamically driven charge shift evolving from PTZP-Pc1- CA and exhibits lifetimes that are notably longer than those of DMAP-Pc1-CA. © 2013 American Chemical Society.

Supramolecular complexation of C60 and C70 by helical nanographene incorporating N-heterotriangulene and hexabenzocoronene subunits - Kinzelmann, Marina; Fröhlich, Nina; Gnannt, Frederik; Borstelmann, Jan; Frühwald, Stefan; Oleszak, Christoph; Jux, Norbert; Görling, Andreas; Kivala, Milan; Drewello, Thomas (RSC Advances, 2025)
Supramolecular host–guest complexes are studied in the gas-phase evaluating a new host molecule for fullerenes (C60 and C70). The new host molecule is a double N-heterotriangulene-[5]helicene (NTH), consisting of two N-heterotriangulene (N-HTA) blades embedded into a hexabenzocoronene-like backbone with helically curved topology. Host–guest complexes of [1:1]+c/2+, [1:2]+c/2+, [2:1]2+ and [2:3]2+ stoichiometry and charge state are formed by electrospray ionization-mass spectrometry (ESI-MS). Ion formation occurs through electrochemical oxidation of the N-HTA moieties. Energy-resolved collision-induced dissociation (ER-CID) experiments reveal the noncovalent binding of the fullerenes to the NTH molecule and provide an order of stability for the complexes. Density-functional theory (DFT) calculations establish the lowest energy geometries of the complexes.
CRIS-Team Scopus Importer:2025-02-14

Supramolecular Fullerene Tetramers Concocted with Porphyrin Boxes Enable Efficient Charge Separation and Delocalization - Yu, Xiujun; Wang, Bingzhe; Kim, Younghoon; Park, Jiyong; Ghosh, Samrat; Dhara, Barun; Mukhopadhyay, Rahul Dev; Koo, Jaehyoung; Kim, Ikjin; Kim, Seungha; Hwang, In Chul; Seki, Shu; et al. (Journal of the American Chemical Society, 2020)
Herein, we report a novel porphyrin/fullerene supramolecular cocrystal using a shape-persistent zinc-metalated porphyrin box (Zn-PB) and C60/C70. An unprecedented arrangement of a tightly packed square-planar core of four C60 or C70 surrounded by six cube-shaped Zn-PBs was observed. This unique packing promotes strong charge transfer (CT) interactions between the two components in the ground state and formation of charge-separated states with very long lifetimes in the excited state and enables unusually high photoconductivity. Quantum chemical calculations show that these features are enabled by delocalized orbitals that promote the CT, on one hand, and that are spatially separated from each other, on the other hand. This work may open a new avenue to design novel electron donor/acceptor architectures for artificial photosynthesis.
CRIS-Team Scopus Importer:2020-07-31

Supramolecular One-Dimensional n/p-Nanofibers - Insuasty, Alberto; Atienza, Carmen; Luis Lopez, Juan; Marco-Martinez, Juan; Casado, Santiago; Saha, Avishek; Guldi, Dirk Michael; Martin, Nazario (Scientific Reports, 2015)
Currently, there is a broad interest in the control over creating ordered electroactive nanostructures, in which electron donors and acceptors are organized at similar length scales. In this article, a simple and efficient procedure is reported en-route towards the construction of 1D arrays of crystalline pristine C 60 and phenyl-C 61-butyric acid methyl ester (PCBM) coated onto supramolecular fibers based on exTTF-pentapeptides. The resulting n/p-nanohybrids have been fully characterized by a variety of spectroscopic (FTIR, UV-Vis, circular dichroism, Raman and transient absorption), microscopic (AFM, TEM, and SEM), and powder diffraction (X-ray) techniques. Our experimental findings document the tendency of electroactive exTTF-fibers to induce the crystallization of C 60 and PCBM, on one hand, and to afford 1D n/p-nanohybrids, on the other hand. Furthermore, photogenerated radical ion pairs, formed upon visible light irradiation of the n/p-nanohybrids, feature lifetimes on the range of 0.9-1.2ns.
CRIS-Team Scopus Importer:2023-03-07

Supramolecular Recognition of Cytidine Phosphate in Nucleotides and RNA Sequences - Morozov, Boris; Oshchepkov, Aleksandr S.; Klemt, Insa; Agafontsev, Aleksandr; Krishna, Swathi; Hampel, Frank; Xu, Honggui; Mokhir, Andriy; Guldi, Dirk Michael; Kataev, Evgeny (JACS Au, 2022)
Supramolecular recognition of nucleotides would enable manipulating crucial biochemical pathways like transcription and translation directly and with high precision. Therefore, it offers great promise in medicinal applications, not least in treating cancer or viral infections. This work presents a universal supramolecular approach to target nucleoside phosphates in nucleotides and RNA. The artificial active site in new receptors simultaneously realizes several binding and sensing mechanisms: encapsulation of a nucleobase via dispersion and hydrogen bonding interactions, recognition of the phosphate residue, and a self-reporting feature─“turn-on” fluorescence. Key to the high selectivity is the conscious separation of phosphate- and nucleobase-binding sites by introducing specific spacers in the receptor structure. We have tuned the spacers to achieve high binding affinity and selectivity for cytidine 5′ triphosphate coupled to a record 60-fold fluorescence enhancement. The resulting structures are also the first functional models of poly(rC)-binding protein coordinating specifically to C-rich RNA oligomers, e.g., the 5′-AUCCC(C/U) sequence present in poliovirus type 1 and the human transcriptome. The receptors bind to RNA in human ovarian cells A2780, causing strong cytotoxicity at 800 nM. The performance, self-reporting property, and tunability of our approach open up a promising and unique avenue for sequence-specific RNA binding in cells by using low-molecular-weight artificial receptors.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cytosine; encapsulation; fluorescence sensing; nucleotide recognition; synthetic receptors

Supramolecular Recognition within a Nanosized “Buckytrap” That Exhibits Substantial Photoconductivity - Sen, Sajal; Ishiwari, Fumitaka; Kaur, Ramandeep; Ishida, Masatoshi; Ray, Debmalya; Kikuchi, Koichi; Mori, Takehiko; Bähring, Steffen; Lynch, Vincent M.; Saeki, Akinori; Guldi, Dirk Michael; Sessler, Jonathan L.; et al. (Journal of the American Chemical Society, 2023)
We report here a nanosized “buckytrap”, 1, constructed from two bis-zinc(II) expanded-TTF (exTTF) porphyrin subunits. Two forms, 1a and 1b, differing in the axial ligands, H2O vs tetrahydrofuran (THF), were isolated and characterized. Discrete host-guest inclusion complexes are formed upon treatment with fullerenes as inferred from a single-crystal X-ray structural analyses of 1a with C70. The fullerene is found to be encapsulated within the inner pseudohexagonal cavity of 1a. In contrast, the corresponding free-base derivative (2) was found to form infinite ball-and-socket type supramolecular organic frameworks (3D-SOFs) with fullerenes, (2•C60)n or (2•C70)n. This difference is ascribed to the fact that in 1a and 1b the axial positions are blocked by a H2O or THF ligand. Emission spectroscopic studies supported a 1:1 host-guest binding stoichiometry, allowing association constants of (2.0 ± 0.5) × 104 M-1 and (4.3 ± 0.9) × 104 M-1 to be calculated for C60 and C70, respectively. Flash-photolysis time-resolved microwave conductivity (FP-TRMC) studies of solid films of the Zn-complex 1a revealed that the intrinsic charge carrier transport, i.e., pseudo-photoconductivity (ϕ∑μ), increases upon fullerene inclusion (e.g., ϕ∑μ = 1.53 × 10-4 cm2 V-1 s-1 for C60⊂(1a)2 and ϕ∑μ = 1.45 × 10-4 cm2 V-1 s-1 for C70⊂(1a)2 vs ϕ∑μ = 2.49 × 10-5 cm2 V-1 s-1 for 1a) at 298 K. These findings provide support for the notion that controlling the nature of self-assembly supramolecular constructs formed from exTTF-porphyrin dimers through metalation or choice of fullerene can be used to regulate key functional features, including photoconductivity.
CRIS-Team Scopus Importer:2023-02-03

Surface functionalization and electronic interactions of ZnO nanorods with a porphyrin derivative - Klaumünzer, Martin; Kahnt, Axel; Burger, Alexandra; Mackovic, Mirza; Muenzel, Corinna; Srikantharajah, Rubitha; Spiecker, Erdmann; Hirsch, Andreas; Peukert, Wolfgang; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2014)
To optimize electron transfer and optoelectronic properties in nanoparticulate thin films for electronics we show the surface functionalization of ZnO nanorods by means of replacing surface active 2-[2-(2-methoxyethoxy) ethoxy]acetic acid (TODA) by a redoxactive organic component, that is, 5,10,15,20-(phenoxyacetat)-porphyrin bearing four carboxylic acids as possible ZnO anchors. Microscopy-transmission electron microscopy-And spectroscopy-optical spectroscopy-verifies the successful and homogenous integration of the porphyrin onto the surface of ZnO nanorods, a process that is facilitated by the four anchoring groups. Photophysical investigations based on emission and absorption spectroscopy prompt to distinct electronic interactions between ZnO nanorods and the porphyrins. Consequently, we performed further photophysical studies flanked by pulse radiolysis assays to corroborate the nature of the electronic interactions. © 2014 American Chemical Society.

Surface functionalization of ZnO nanorods with C60 derivatives carrying phosphonic acid functionalities - Voigt, Michael; Klaumünzer, Martin; Ebel, Alexander; Werner, Fabian; Yang, Guang; Marczak, Renata; Spiecker, Erdmann; Guldi, Dirk Michael; Hirsch, Andreas; Peukert, Wolfgang (Journal of Physical Chemistry C, 2011)
ZnO with its wide band gap (3.37 eV) emerged as a promising semiconductor material for applications in the fields of printable and flexible electronics such as field effect transistors, etc. The fact that contacts at particle/particle interfaces exert a limiting impact on device performances motivates research on aligning the electronic levels at particle/particle interfaces. To this end, we focus in the present study on the surface functionalization of ZnO nanorods by a series of C derivatives. The latter share in common (i) a phosphonic acid as an anchor to ZnO, (ii) an alkyl chain as a flexible spacer, and (iii) a C as the headgroup. To shed light onto the electronic interactions between ZnO and C, we vary the alkyl chain length from n = 3 to n = 18. HRTEM and EELS prove the successful surface functionalization. Fundamental to this work are steady state absorption and photoluminescence measurements, which confirm the presence of appreciable electronic couplings between ZnO nanorods and C. Especially the photoluminescence measurements are important since they provide strong support for the dependence between spacer length and strength of electronic communication. In particular, a blue-shift of the ZnO free exciton emission band amounting to as much as 50 meV is observed with a decrease in spacer length. Furthermore, time-resolved absorption measurements corroborate ultrafast charge injection - facilitated by strong coupling - from the photoexcited ZnO nanorods to C. © 2011 American Chemical Society.
Keywords: Functionalization; Oxides; Reaction products; Organophosphorus compounds; Nanorods

Surface modification of TiO2 nanosheets with fullerene and zinc-phthalocyanine for enhanced photocatalytic reduction under solar-light irradiation - Liu, Liping (Science China Materials, 2020)

Symmetry-Breaking Charge-Transfer Chromophore Interactions Supported by Carbon Nanodots - Cacioppo, Michele; Scharl, Tobias; Dordevic, Luka; Cadranel, Alejandro; Arcudi, Francesca; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2020)
Carbon dots (CDs) and their derivatives are useful platforms for studying electron-donor/acceptor interactions and dynamics therein. Herein, we couple amorphous CDs with phthalocyanines (Pcs) that act as electron donors with a large extended pi-surface and intense absorption across the visible range of the solar spectrum. Investigations of the intercomponent interactions by means of steady-state and pump-probe transient absorption spectroscopy reveal symmetry-breaking charge transfer/separation and recombination dynamics within pairs of phthalocyanines. The CDs facilitate the electronic interactions between the phthalocyanines. Thus, our findings suggest that CDs could be used to support electronic couplings in multichromophoric systems and further increase their applicability in organic electronics, photonics, and artificial photosynthesis.
CRIS-Team WoS Importer:2020-05-29

Synergie von elektrostatischen und π-π-Wechselwirkungen für die Verwirklichung von künstlichen photosynthetischen Modellsystemen auf Nano-Ebene - Anaya-Plaza, Eduardo; Joseph, Jan; Bauroth, Stefan; Wagner, Maximilian; Dolle, Christian; Sekita, Michael; Gröhn, Franziska; Spiecker, Erdmann; Clark, Timothy; de la Escosura, Andrés; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie, 2020)
CRIS-Team Scopus Importer:2020-09-11

Synergy of Catechol-Functionalized Zinc Oxide Nanorods and Porphyrins in Layer-by-Layer Assemblies - Burger, Alexandra; Kunzmann, Andreas; Costa, Ruben Dario; Srikantharajah, Rubitha; Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Catechol-functionalized, positively charged ZnO nanorods (NRs) and anionic porphyrins were integrated into layer-by-layer (LbL) assemblies. In general, this study focuses on the impact that different porphyrins, varying in size and number of negative charges, exert on the LbL architecture in terms of morphology and spectroscopy. In particular, through a combination of analytical methods, including UV/Vis spectroscopy, SEM, and profilometry, valuable insights into LbL assembly formation were gathered. A key feature was the surface coverage in the resulting films. Denser films and surface coverages were realized when highly negatively charged and sterically demanding porphyrins were employed. As a complement to basic characterization, the LbL assembled films were used to fabricate proof-of-concept solar cells.
Keywords: porphyrins; solar energy conversion; layer-by-layer assemblies; layered compounds; thin films; ZnO nanorods

Synergy of Electrostatic and π–π Interactions in the Realization of Nanoscale Artificial Photosynthetic Model Systems - Anaya-Plaza, Eduardo; Joseph, Jan; Bauroth, Stefan; Wagner, Maximilian; Dolle, Christian; Sekita, Michael; Gröhn, Franziska; Spiecker, Erdmann; Clark, Timothy; de la Escosura, Andrés; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie International Edition, 2020)
In the scientific race to build up photoactive electron donor-acceptor systems with increasing efficiencies, little is known about the interplay of their building blocks when integrated into supramolecular nanoscale arrays, particularly in aqueous environments. Here, we describe an aqueous donor-acceptor ensemble whose emergence as a nanoscale material renders it remarkably stable and efficient. We have focused on a tetracationic zinc phthalocyanine (ZnPc) featuring pyrenes, which shows an unprecedented mode of aggregation, driven by subtle cooperation between electrostatic and π–π interactions. Our studies demonstrate monocrystalline growth in solution and a symmetry-breaking intermolecular charge transfer between adjacent ZnPcs upon photoexcitation. Immobilizing a negatively charged fullerene (C60) as electron acceptor onto the monocrystalline ZnPc assemblies was found to enhance the overall stability, and to suppress the energy-wasting charge recombination found in the absence of C60. Overall, the resulting artificial photosynthetic model system exhibits a high degree of preorganization, which facilitates efficient charge separation and subsequent charge transport.
CRIS-Team Scopus Importer:2020-09-11
Keywords: artificial photosynthesis; fullerenes; nanoscale self-assembly; phthalocyanines

Synergy of light harvesting and energy transfer as well as short-range charge shift reactions in multicomponent conjugates - Fazio, Ettore; Winterfeld, Kim; Lopez-Perez, Ana; Torres, Tomas; Guldi, Dirk Michael; De La Torre, Gema (Nanoscale, 2018)
We report herein on the design, the synthesis, and the characterization of a panchromatic, charge stabilizing electron donor-acceptor conjugate: (BBPA)3-ZnPor-ZnPc-SubPc 1. Each component, that is, bis(biphenyl)phenylamine (BBPA), Zn(ii) porphyrin (ZnPor), Zn(ii) phthalocyanine ZnPc, and subphthalocyanine (SubPc), has been carefully chosen and modified to enable a cascade of energy and charge transfer processes. On one hand, ZnPor, has been functionalized with three electron-donating BBPA as primary and secondary electron donors and to stabilize the final charge-separated state, and, on the other hand, a perfluorinated SubPc has been selected as ultimate electron acceptor. In addition, the ZnPc unit contains several trifluoromethylphenyl moieties to match its energy levels to those of the other components. In fact, irradiation of the heteroarray 1 triggers a cascade of light harvesting across the entire visible range, unidirectional energy transfer, exergonic charge separating, and short-range charge shifting to afford in 14% quantum yield a (BBPA)3 +-ZnPor-ZnPc-SubPc- charge-separated state. The lifetime of the latter reaches well into the range of tens of nanoseconds.
CRIS-Team Scopus Importer:2022-04-14

Synthesis and aggregation properties of polycationic perylenetetracarboxylic acid diimides - Schönamsgruber, Jörg; Schade, Boris; Kirschbaum, Rolf; Li, Jing; Bauer, Walter; Boettcher, Christoph; Drewello, Thomas; Hirsch, Andreas (European Journal of Organic Chemistry, 2012)
The synthesis and structural characterization of a first family of dendronized polycationic perylenetetracarboxylic acid diimides (PDIs) 7, 8, and 10 is reported. They were obtained by amide coupling reactions of pyridinium salt head groups with terminal carboxylic groups of Newkome-dendron-type functionalized PDIs. Resulting pyridinium-terminated PDIs 7, 8, and 10 are highly water-soluble, independent of the pH value. This is due to 6, 18, and 9 permanent positive charges, respectively. PDIs 7 containing the smaller first-generation dendrons exhibit a pronounced aggregation behavior in water. This was studied by absorption and fluorescence spectroscopy, by pulsed-gradient spin-echo (PGSE, DOSY) NMR measurements, and by cryo-transmission electron microscopy (cryo-TEM). The counterparts containing the bulkier second-generation dendrons hamper aggregation, and as a consequence intermolecular π-π stacking interactions between the perylene cores is suppressed. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Synthesis and C 60Binding of Aza[10]CPP and N -Methylaza[10]CPP - Schwer, Fabian; Zank, Simon; Freiberger, Markus; Kaur, Ramandeep; Frühwald, Stefan; Robertson, Craig C.; Görling, Andreas; Drewello, Thomas; Guldi, Dirk Michael; Von Delius, Max (Organic Materials, 2022)
Within the growing family of strained carbon nanohoops and nanobelts, [10]CPP arguably offers the best compromise between synthetic accessibility and strong binding affinity for C60. In this work, we report the synthesis of two nitrogen-containing analogues of [10]CPP and we systematically compare the structure, optoelectronic properties and C60 binding affinities of this small set of structurally similar macrocycles. While Aza[10]CPP outcompetes the parent compound by approximately one order of magnitude with respect to C60 binding, we found that the reverse was true for the methylaza analogue. Transient absorption studies showed that photo-induced electron transfer occurred readily from [10]CPP and its aza-analogue to an encapsulated C60 guest. Formation of a charge-separated complex was not observed however for the N-methylated derivative. These insights will prove useful for further applications of strained nanohoops in supramolecular chemistry and organic electronics.
CRIS-Team Scopus Importer:2024-12-16
Keywords: curved π-systems; fullerenes; host-guest chemistry; nitrogen doping; photo-induced electron transfer

Synthesis and Characterization of a Trisheteroleptic Ru-II-Based Molecular Switch - Monczak, Katharina; Peuntinger, Katrin; Sorsche, Dieter; Heinemann, Frank Wilhelm; Guldi, Dirk Michael; Rau, Sven (Chemistry - A European Journal, 2014)
The synthesis of a trisheteroleptic ruthenium complex [Ru(tb)(dppz)(tmbiH(2))][PF6](2) (tb = 4,4'-di-tert-butyl-2,2'-bipyridine, dppz = dipyrido[3,2-a:2',3'-c]phenazin, tmbiH(2) = 5,6,5',6'-tetramethyl-2,2'-bibenzimidazole) is described. In addition, the structural characterisation by means of 1D, 2D H-1 NMR spectroscopy, and mass spectrometry, along with determination of the solid-state structure of the important precursor Ru(tb)(dppz) Cl-2, supports the proposed octahedral coordination geometry. The capability of tmbiH(2) to form hydrogen bonds is corroborated by the solid-state structure. The photochemical characteristics of this complex can be described as a combination of the "light switch" effects, which are either attributed to the dppz or to the tmbiH(2) ligand. To illustrate the molecule's double switchable features, steady-state absorption and emission measurements were performed, which include the determination of the quantum yield and the pK(a) values of the acidic protons of the tmbiH(2) ligand. Notably, the emission lifetimes are sensitive to the solvents used. This phenomenon is due to a proton-coupled deactivation of the excited metal-to-ligand charge transfer (MLCT) state of the complex.
Keywords: bibenzimidazole; light switch effect; molecular switch; pH dependency; trisheteroleptic Ru-II complex

Synthesis and characterization of boron azadipyrromethene single-wall carbon nanotube electron donor-acceptor conjugates - Flavin, Kevin; Lawrence, Katherine; Bartelmeß, Jürgen; Tasior, Mariusz; Navio, Cristina; Bittencourt, Carla; O'Shea, Donal F.; Guldi, Dirk Michael; Giordani, Silvia (Acs Nano, 2011)
The preparation of a novel donor-acceptor material, consisting of a red/near-infrared (NIR) absorbing boron azadipyrromethene donor covalently attached to a highly functionalized single-wall carbon nanotube (SWNT) acceptor, which bears great potential in the field of organic photovoltaics, has been demonstrated. Both purification and covalent functionalization of SWNTs have been demonstrated using a number of complementary characterization techniques, including atomic force microscopy, Raman, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared, and NIR-photoluminescence spectroscopy, and a functionalization density of approximately 1 donor molecule per 100 SWNT atoms has been estimated by XPS. The redox behavior of the fluorophore has been investigated by electrochemistry and spectroelectrochemistry as well as by pulse radiolysis. The donor-acceptor properties of the material have been characterized by means of various spectroscopic techniques, such as UV-vis NIR absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy, and time-resolved transient absorption spectroscopy. Charge transfer from the photoexcited donor to the SWNT acceptor has been confirmed with a radical ion pair state lifetime of about 1.2 ns. © 2011 American Chemical Society.

Synthesis and characterization of novel "clicked" dimers of unsymmetrically substituted tetraphenylporphyrins - Malig, Jenny; Strauß, Volker; Grönninger, Philipp; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2011)
Herein, we present a novel and facile approach to porphyrin tweezer scaffolds through copper catalyzed azide alkyne cycloaddition (CuAAC). To this end, asymmetric structures arise that are highly versatile precursors for the molecular design of multi-functional porphyrin systems. The synthesis and characterization by means of photophysical and electrochemical methods and first results on the formation of dye-sensitized solar cells (DSSC) are described. © 2011 World Scientific Publishing Company.

Synthesis and characterization of zinc oxide nanoparticles for dye-sensitized solar cells - Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas; Werner, Fabian; Gnichwitz, Jan-Frederik; Marczak, Renata (2008 AIChE Annual Meeting, AIChE 100, 2008)
Stable ZnO nanoparticles suitable for further derivatization of their surface were synthesized in the liquid phase from homogeneous ethanolic solutions of the precursors, lithium hydroxide and zinc acetate. The particle growth was monitored by in situ absorption spectroscopy and dynamic light scattering (DLS). It was found that the growth of the particles was governed by temperature as well as the presence of the reaction by-product lithium acetate during the ripening process. In particular, the reaction could be almost completely arrested by removal of this by-product. The "washing" consisted of repeated precipitation of the ZnO particles by addition of alkanes such as heptane, removal of the supernatant, and redispersion in ethanol. The ZnO nanoparticles, before and after "washing", were characterized by absorption spectroscopy, DLS, thermogravimetric analysis (TGA), X-ray powder diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). The functionalization of the ZnO nanoparticles with photoactive organic compounds, i.e., 5-(N-(3,4-dihydroxyphenethyl)-2-phenoxyacetamide)-10, 15, 20-(p-tert-butyl-triphenyl)-porphyrinato-zinc and 5-(3,4-dihydroxy-N- phenylbenzamide)-10,15,20-tris(4-tertbutylphenyl)-porphyrinato-zinc, was examined. Mesoporous films of the ZnO nanoparticles suitable for use as electrodes in dye-sensitized solar cells (DSSCs) were prepared by the doctor blade technique. Following sintering the films were sensitized by the dye molecules mentioned above. The morphology of the films was characterized by using scanning electron microscopy (SEM). The current generated during photoelectrochemical measurements of these films was ascribed to an efficient photoinduced electron transfer from the photoexcited porphyrin to the ZnO moiety.
Keywords: functionalization; ZnO; nanoparticle; growth; light; scattering; solar; call

Synthesis and charge-transfer chemistry of La2@I h-C80/Sc3N@Ih-C80-zinc porphyrin conjugates: Impact of endohedral cluster - Feng, Lai; Radhakrishnan, Shankara Gayathri; Mizorogi, Naomi; Slanina, Zdenek; Nikawa, Hidefumi; Tsuchiya, Takahiro; Akasaka, Takeshi; Nagase, Shigeru; Martin, Nazario; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Two stable electron donor-acceptor conjugates, that is, 3 and 5b, employing La@I-C and ScN@I -C, on one hand, and zinc tetraphenylporphyrin, on the other hand, have been prepared via [1 + 2] cycloaddition reactions of a diazo precursor. Combined studies of crystallography and NMR suggest a common (6,6)-open addition pattern of 3 and 5b. Still, subtly different conformations, that is, a restricted and a comparatively more flexible topography, emerge for 3 and 5b, respectively. In line with this aforementioned difference are the electrochemical assays, which imply appreciably stronger I-C /ZnP interactions in 3 when compared to those in 5b. Density functional calculations reveal significant attractions between the two entities of these conjugates, as well as their separately localized HOMOs and LUMOs. The geometrical conformations and LUMO distributions of 3 and 5b, at our applied computational level, are slightly varied with their different endohedral clusters. The clusters also exert different impact on the excited state reactivity of the conjugates. For example, 3 undergoes, upon photoexcitation, a fast charge separation process and yields a radical ion pair, whose nature, namely, (La@C)-(ZnP) ) versus (La@C)- (ZnP)), varies with solvent polarity. 5b, on the other hand, afforded the same (ScN@C)-(ZnP) ) radical ion pair regardless of the solvent. © 2011 American Chemical Society.

Synthesis and Electrochemical and Photophysical Characterization of New 4,4-Conjugated 2,2-Bipyridines that are End-Capped with Cyanoacrylic Acid/Ester Groups - Fingerhut, Anja; Wu, Yanlin; Kahnt, Axel; Bachmann, Julien; Tsogoeva, Svetlana (Chemistry-An Asian Journal, 2016)
Two new functionalized 4,4-disubstituted 2,2-bipyridines that were end-capped with cyanoacrylic acid or cyanoacrylic acid ester anchoring groups, which might allow their efficient functionalization on TiO2 or other metal-oxide semiconductor surfaces, have been synthesized and characterized by electrochemical, photophysical, and spectroscopic measurements. The electrochemical and photophysical properties of these 4,4-disubstituted 2,2-bipyridines with extended systems, in particular their LUMO energies, make them promising candidates to build up inorganic-organic hybrid photosensitizers for the sensitization of metal-oxide semiconductors (e.g., TiO2 nanoparticles and/or nanotubes).
Keywords: adsorption; bipyridines; conjugation; fluorescence; photosensitizers

Synthesis and excited state processes of arrays containing amine-rich carbon dots and unsymmetrical rylene diimides - Đorđević, Luka; Haines, Philipp; Cacioppo, Michele; Arcudi, Francesca; Scharl, Tobias; Cadranel, Alejandro; Guldi, Dirk Michael; Prato, Maurizio (Materials Chemistry Frontiers, 2020)
Combining carbon dots (CDs) with π-extended chromophores is an attractive way to study the electronic and energy processes of the former as a key step to many applications, including photosensing, photocatalysis, or photosensitization. CDs, in conjugation with chromophores, can have value in preparing donor-acceptor hybrids, and can also be used as scaffolds to support electronic communication between dyes. In this work, we conjugate two different rylene diimides, naphthalene and perylene diimides (NDI and PDI, respectively), with amorphous nitrogen-doped carbon dots. We take advantage of the imidization reaction between the amine-rich surface of the carbon dots and the monimide monoanhydride precursors of NDIs and PDIs, under microwave assisted conditions. The resulting (nano)hybrids were characterized also by spectroscopic methods. In particular, time-resolved spectroscopy for the multichromophoric array, consisting of CDs and both rylene diimides, allowed us to elucidate the complex inter-chromophoric interactions taking place in the excited state.
CRIS-Team Scopus Importer:2020-12-11

Synthesis and Optical Features of Axially and Peripherally Substituted Subporphyrins. A Paradigmatic Example of Charge Transfer versus Exciplex States - Winterfeld, Kim; Lavarda, Giulia; Yoshida, Kota; Bayerlein, Maximilian J.; Kise, Koki; Tanaka, Takayuki; Osuka, Atsuhiro; Guldi, Dirk Michael; Torres, Tomas; Bottari, Giovanni (Journal of the American Chemical Society, 2020)
We report here the synthesis of two novel subporphyrins (SubPs), in which the macrocycle has been functionalized at its meso (1) or axial (2) position with tetracyanobuta-1,3-diene (TCBD)-aniline. In-depth spectroscopic, spectrometric, and electrochemical analyses were carried out with both of them, whose molecular structures were determined by single-crystal X-ray diffraction studies. In the case of 2, its Ra and Sa enantiomers were separable by chiral HPLC and presented a fairly good configurational stability at room temperature, which enabled determining the activation parameters for the thermally induced racemization. Conversely, the enantiomers' separation was unfeasible for 1 due to the conformational and/or configurational dynamics of the TCBD-aniline, a structural "flexibility" that could be drastically reduced at low temperatures. The physicochemical impact of placing the TCBD-aniline at either the axial or peripheral positions of SubPs is also rather significant. The HOMO-LUMO gap is reduced by as much as 0.35 eV in SubP-(TCBD-aniline)meso 1 (1.77 eV) and, in turn, enables an emissive charge-transfer (CT) state in virtually all environments. It is only in polar environments, where it links a local excitation with an indirect charge separation. In contrast, a much larger HOMO-LUMO gap of 2.12 eV in SubP-(TCBD-aniline)axial 2 disables an emissive CT state and enforces either an exciplex deactivation in apolar environments or a direct charge separation in polar environments.
CRIS-Team Scopus Importer:2020-05-26

Synthesis and photoinduced electron-transfer properties of phthalocyanine-[60]fullerene conjugates. - Quintiliani, M.; Kahnt, Axel; Wölfle, Thorsten; Hieringer, Wolfgang; Vázquez, P.; Görling, Andreas; Guldi, Dirk Michael; Torres, T. (Chemistry - A European Journal, 2008)
A series of three novel ZnPc-C conjugates (Pc = phthalocyanine) 1a-c bearing different spacers (single, double, and triple bond) between the two electroactive moieties was synthesized and compared to that of ZnPc-C conjugate 2, in which the two electroactive moieties are linked directly. The synthetic strategy - towards the preparation of 1a-c - involved palladium-catalyzed cross-coupling reactions over a monoiodophthalocyanine precursor 4 to introduce the corresponding spacer, and subsequent dipolar cycloaddition reaction to C . Detailed photophysical investigations of 1a-c and 2 prompted an intramolecular electron transfer that evolves from the photoexcited ZnPc to the electron-accepting C . In particular, with the help of femtosecond laser photolysis charge separation was indeed confirmed as the major deactivation channel. Complementary time-dependent density functional calculations supported the spectral assignment, namely, the spectral identity of the ZnPc radical cation and the C radical anion as seen in the differential absorption spectra. The lifetimes of the correspondingly formed radical ion-pair states depend markedly on the solvent polarity: they increase as polarity decreases. Similarly, although to a lesser extent, the nature of the linker impacts the lifetime of the radical ion-pair states. In general, the lifetimes of these states tend to be shortest in the system that lacks any spacer at all (2), whereas the longest lifetimes were found in the system that carries the triple-bond spacer (1a). © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Synthesis and Photoinduced Electron-Transfer Reactions in a La2@Ih-C80–Phenoxazine Conjugate - Akasaka, Takeshi; Nakata, Akira; Rudolf, Marc; Wang, Wei-Wei; Yamada, Michio; Suzuki, Mitsuaki; Maeda, Yutaka; Aoyama, Ryo; Tsuchiya, Takahiro; Nagase, Shigeru; Guldi, Dirk Michael (ChemPlusChem, 2017)
A newly designed electron donor–acceptor conjugate consisting of an endohedral dimetallofullerene (La2@Ih-C80) and phenoxazine (POZ) was successfully synthesized under Prato conditions. Our results document that the 1,3-dipolar cycloaddition took place across the [5,6] junction to afford exclusively the corresponding [5,6] cycloadduct. The structure of the conjugate was characterized by means of NMR spectroscopy, absorption spectroscopy, and electrochemical studies. Computational calculations suggest that the electron density of the highest occupied molecular orbital (HOMO) is distributed on the POZ moiety, whereas that of the lowest unoccupied molecular orbital (LUMO) is located at the endohedral La atoms, leading to efficient separation of the HOMO and LUMO in the conjugate. Time-resolved absorption spectroscopic investigations and spectroelectrochemical measurements corroborate the formation of the energetically low-lying (La2@Ih-C80).−–(POZ).+ radical-ion-pair state by means of ultrafast through-space electron transfer.
CRIS-Team Scopus Importer:2022-04-14
Keywords: donor–acceptor systems; electrochemistry; electron transfer; fullerenes; photochemistry

Synthesis and photophysical properties of a hydrogen-bonded phthalocyanine-perylenediimide assembly - Seitz, Wolfgang; Jimenez, Angel J.; Carbonell, Esther; Grimm, Bruno; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2010)
A supramolecular phthalocyanine-perylenediimide donor-acceptor array has been assembled by using a melamine/perylenediimide motif. Photoexcitation of the perylenediimide component affords transduction of singlet excited state energy to the energetically lower lying phthalocyanine. © 2010 The Royal Society of Chemistry.

Synthesis and Photophysical Properties of a Sc3N@ C80‐Corrole Electron Donor–Acceptor Conjugate - Liu, Bin; Fang, Hongyun; Li, Xiaofang; Cai, Wenting; Bao, Lipiao; Rudolf, Marc; Plass, Fabian; Fan, Louzhen; Lu, Xing; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
Embedding endohdedral metallofullerenes (EMFs) into electron donor–acceptor systems is still a challenging task owing to their limited quantities and their still largely unexplored chemical properties. In this study, we have performed a 1,3-dipolar cycloaddition reaction of a corrole-based precursor with Sc3N@C80 to regioselectively form a [5,6]-adduct (1). The successful attachment of the corrole moiety was confirmed by mass spectrometry. In the electronic ground state, absorption spectra suggest sizeable electronic communications between the electron acceptor and the electron donor. Moreover, the addition pattern occurring at a [5,6]-bond junction is firmly proven by NMR spectroscopy and electrochemical investigations performed with 1. In the electronically excited state, which is probed in photophysical assays with 1, a fast electron-transfer yields the radical ion pair state consisting of the one-electron-reduced Sc3N@C80 and of the one-electron-oxidized corrole upon its exclusive photoexcitation. As such, our results shed new light on the practical work utilizing EMFs as building blocks in photovoltaics.<br
Keywords: corroles; donor–acceptor systems; fullerenes; metallocycles; photophysics

Synthesis and photophysical properties of fullerene-phthalocyanine- porphyrin triads and pentads - Enes, Roger F.; Cid, Juan-Jose; Hausmann, Anita; Trukhina, Olga; Gouloumis, Andreas; Vazquez, Purificacion; Cavaleiro, Jose A. S.; Tome, Augusto C.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2012)
The synthesis and photophysical properties of several fullerene- phthalocyanine-porphyrin triads (1-3) and pentads (4-6) are described. The three photoactive moieties were covalently connected in an one-step synthesis through 1,3-dipolar cycloaddition to C of the corresponding azomethine ylides generated in situ by condensation reaction of a substituted N-porphyrinylmethylglycine derivative and an appropriated formyl phthalocyanine or a diformyl phthalocyanine derivative, respectively. ZnP-C -ZnPc (3), (ZnP) -ZnPc-(C ) (6), and (H P) -ZnPc-(C ) (5) give rise upon excitation of their ZnP or H P components to a sequence of energy and charge-transfer reactions with, however, fundamentally different outcomes. With (ZnP) -ZnPc-(C ) (6) the major pathway is an highly exothermic charge transfer to afford (ZnP)(ZnP )-ZnPc- (C )(C ). The lower singlet excited state energy of H P (i.e., ca. 0.2 eV) and likewise its more anodic oxidation (i.e., ca. 0.2 V) renders the direct charge transfer in (H P) -ZnPc-(C ) (5) not competitive. Instead, a transduction of singlet excited state energy prevails to form the ZnPc singlet excited state. This triggers then an intramolecular charge transfer reaction to form exclusively (H P) -ZnPc -(C )(C ). A similar sequence is found for ZnP-C -ZnPc (3). Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Synthesis and photophysical properties of new catenated electron donor-acceptor materials with magnesium and free base porphyrins as donors and C60 as the acceptor - Kirner, Sabrina; Guldi, Dirk Michael; Megiatto, Jackson D.; Schuster, David I. (Nanoscale, 2015)
A new series of nanoscale electron donor-acceptor systems with [2]catenane architectures has been synthesized, incorporating magnesium porphyrin (MgP) or free base porphyrin (H2P) as electron donor and C60 as electron acceptor, surrounding a central tetrahedral Cu(i)-1,10-phenanthroline (phen) complex. Model catenated compounds incorporating only one or none of these photoactive moieties were also prepared. The synthesis involved the use of Sauvage's metal template protocol in combination with the 1,3-dipolar cycloaddition of azides and alkynes ("click chemistry"), as in other recent reports from our laboratories. Ground state electron interactions between the individual constituents was probed using electrochemistry and UV-vis absorption spectroscopy, while events occurring following photoexcitation in tetrahydrofuran (under both aerobic and anaerobic conditions) at various wavelengths were followed by means of time-resolved transient absorption and emission spectroscopies on the femtosecond and nanosecond time scales, respectively, complemented by measurements of quantum yields for generation of singlet oxygen. From similar studies with model catenates containing one or neither of the chromophores, the events following photoexcitation could be elucidated. The results were compared with those previously reported for analogous catenates based on zinc porphyrin (ZnP). It was determined that a series of energy transfer (EnT) and electron transfer (ET) processes take place in the present catenates, ultimately generating long-distance charge separated (CS) states involving oxidized porphyrin and reduced C60 moieties, with lifetimes ranging from 400 to 1060 nanoseconds. Shorter lived short-distance CS states possessing oxidized copper complexes and reduced C60, with lifetimes ranging from 15 to 60 ns, were formed en route to the long-distance CS states. The dynamics of the ET processes were analyzed in terms of their thermodynamic driving forces. It was clear that intramolecular back ET was occurring in the inverted region of the Marcus parabola correlating rates and driving forces for electron transfer processes. In addition, evidence for triplet excited states as a product of either incomplete ET or back ET was found. The differences in behavior of the three catenates upon photoexcitation are analyzed in terms of the energy levels of the various intermediate states and the driving forces for EnT and ET processes.
CRIS-Team Scopus Importer:2023-03-07

Synthesis and Photo/Radiation Chemical Characterization of a New Redox-Stable Pyridine-Triazole Ligand - Al-Romema, Abdulaziz; Plass, Fabian; Nizovtsev, Alexey; Kahnt, Axel; Tsogoeva, Svetlana (ChemPhysChem, 2024)
Photocatalysis using transition-metal complexes is widely considered the future of effective and affordable clean-air technology. In particular, redox-stable, easily accessible ligands are decisive. Here, we report a straightforward and facile synthesis of a new highly stable 2,6-bis(triazolyl)pyridine ligand, containing a nitrile moiety as a masked anchoring group, using copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click reaction. The reported structure mimics the binding motif of uneasy to synthesize ligands. Pulse radiolysis under oxidizing and reducing conditions provided evidence for the high stability of the formed radical cation and radical anion 2,6-di(1,2,3-triazol-1-yl)-pyridine compound, thus indicating the feasibility of utilizing this as a ligand for redox active metal complexes and the sensitization of metal-oxide semiconductors (e. g., TiO2 nanoparticles or nanotubes).
CRIS-Team Scopus Importer:2024-08-02
Keywords: click chemistry; laser photolysis; pulse radiolysis; pyridine-triazole; redox-stable ligand

Synthesis and physico-chemical properties of porphycenes - Brenner, Wolfgang; Malig, Jenny; Oelsner, Christian; Guldi, Dirk Michael; Jux, Norbert (Journal of Porphyrins and Phthalocyanines, 2012)
A new and improved synthesis for porphycenes is presented. In particular, treating pyrroles with iodine monochloride results in quantitative yields and easier work up. This key step was employed for the synthesis of different 2,7,12,17-substituted porphycenes (TPrPc, TPPc, TtBPPc). The synthetic part of this project is followed by a global analysis of the physico-chemical properties of three exemplary porphycenes, including absorption, emission, and electrochemistry. In-situ UV-vis/nIR spectroelectrochemistry was used to determine the spectral signatures of the radical anion and cation species. Temperature-dependent fluorescence lifetimes were determined under air as well as under inert atmosphere. © 2012 World Scientific Publishing Company.

Synthesis and Properties of Acridine and Acridinium Dye Functionalized Bis(terpyridine) Ruthenium(II) Complexes - Eberhard, Jens; Peuntinger, Katrin; Froehlich, Roland; Guldi, Dirk Michael; Mattay, Jochen (European Journal of Organic Chemistry, 2018)
We present first principle studies on the rational design of an acridine/N-methylacridinium dye (Acr/MeAcr+) substituted terpyridine ligand to investigate if these chromophores can act as triplet-energy storage units in bis(terpyridine) ruthenium(II) complexes. We studied the influence of the dye form (Acr/MeAcr+) as well as the interconnecting linker unit (none, 4-phenyl, or 5-thien-2-yl) and investigated these aspects by steady-state/time-resolved spectroscopy, cyclic voltammetry, X-ray structure analysis, and DFT calculations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dyes/Pigments; Electronic structure; Energy transfer; Functional organic materials; Ligand design; Ruthenium

Synthesis, characterization, and photoinduced energy and electron transfer in a supramolecular tetrakis (ruthenium(II) phthalocyanine) perylenediimide pentad - Jimenez, Angel J.; Grimm, Bruno; Gunderson, Victoria L.; Vagnini, Michael T.; Krick Calderon, Sandra; Salome Rodriguez-Morgade, M.; Wasielewski, Michael R.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Metal coordination was probed as a versatile approach for designing a novel electron donor/acceptor hybrid [PDIpy Ru(CO)Pc ] (1), in which four pyridines placed at the bay region of a perylenediimides (PDIpy ) coordinate with four ruthenium phthalocyanine units [Ru(CO)Pc]. This structural motif was expected to promote strong electronic coupling between the electron donors and the electron acceptor, a hypothesis that was confirmed in a full-fledged physicochemical investigation focusing on the ground and excited state reactivities. As far as the ground state is concerned, absorption and electrochemical assays indeed reveal a notable redistribution of electron density, that is, from the electron-donating [Ru(CO)Pc] to the electron-accepting PDIpy . The most important thing to note in this context is that both the [Ru(CO)Pc] oxidation and the PDIpy reduction are rendered more difficult in 1 than in the individual building blocks. Likewise, in the excited state, strong electronic communication is the inception for a rapid charge-transfer process in photoexcited 1. Regardless of exciting [Ru(CO)Pc] or PDIpy , spectral characteristics of the [RuPc] radical cation (broad absorptive features from 425 to 600 nm with a maximum at 575 nm, as well as a band centered at 725 nm) and of the PDI radical anion (780 nm maximum) emerge. The correspondingly formed radical ion pair state lasts for up to several hundred picoseconds in toluene, for example. On the other hand, employing more polar solvents, such as dichloromethane, destabilizes the radical ion pair state. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Synthesis, characterization and photophysical properties of a melamine-mediated hydrogen-bound phthalocyanine-perylenediimide assembly - Jimenez, Angel J.; Krick Calderon, Rafael; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
The synthesis and supramolecular organization of a phthalocyanine 3 functionalized with a melamine moiety is described. 3 self-assembles in solution to form dimeric species-driven by double hydrogen-bonding between the aromatic amine functionality that is directly attached to the phthalocyanine ring and the melamine pyridinic nitrogens. In the presence of perylenediimide 2, endowed with a complementary tritopic functionality, electron donor-acceptor assembly Pc-PDI (3)·2 is spontaneously formed. (3)· 2 consists of two phthalocyanines of type 3 and a perylenediimide 2, connected via triple hydrogen bonding between the melamine and the complementary unsubstituted imido functions. Electronic interactions between 2 and 3 in (3)·2 give rise, upon selective photoexcitation of 2, to an intramolecular electron transfer, affording a several nanosecond lived PDI /HPc species, while photoexcitation of 3 is only followed by an ordinary intersystem crossing. © 2013 The Royal Society of Chemistry.

Synthesis, Cyclic Voltammetry and Photophysical Properties of a Bridged o-Phenylenediamine C-60 Dyad. - Diekers, Michael; Hirsch, Andreas; Luo, Chuping; Guldi, Dirk Michael; Bauer, Klaus Andreas; Nickel, Ulrich (Organic Letters, 2000)
The synthesis, complete spectroscopic characterization, cyclic voltammetry, and photophysical measurements of a new o-phenylenediamine-C dyad are described. By using a tether strategy, only a single regioisomer was obtained. Cyclic voltammetry measurements indicate that the two electroactive groups do not interact in their singlet ground states. Photophysical investigations reveal a rapid photoinduced electron transfer between the singlet excited state of the fullerene acceptor and the o-phenylenediamine donor, yielding a charge-separated radical pair.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.ppc25.synthe

Synthesis of stable and surface functionalized nanoparticles in an amphiphilic block copolymer melt - Klaumünzer, Martin; Distaso, Monica; Hübner, Jakob; Kryschi, Carola; Peukert, Wolfgang; Wolfrum, Christian (Technical Proceedings of the 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
We report on an ultrafast and simple one pot synthesis of noble metal nanoparticles and semiconducting metaloxide nanoparticles with aminoblockcopolymer O,O'-Bis (2-aminopropyl) polypropylene glycol- block-polyethylene glycol- block- polypropylene glycols. No additional organic or anorganic solvents are used during synthesis. For demonstrating the universal application of the amino block copolymer for multiple nanoparticle formation we present exemplary syntheses and their characterizations for the following precursor metal compounds: HAuCl, AgNO and Zn(Ac) .
Keywords: synthesis; particle; functionalization

Synthesis of thieno-bridged porphyrins: Changing the antiaromatic contribution by the direction of the thiophene ring - Mitsushige, Yusuke; Yamaguchi, Shigeru; Lee, Byung Sun; Sung, Young Mo; Kuhri, Susanne; Schierl, Christoph; Guldi, Dirk Michael; Kim, Dongho; Matsuo, Yutaka (Journal of the American Chemical Society, 2012)
Two types of thieno-bridged porphyrins were synthesized by incorporating a thiophene group across their meso and β positions with different directions of the thiophene ring to investigate the aromaticity of these porphyrins with extended π-systems. The 2,3-thieno-bridged porphyrin showed a larger antiaromatic contribution than did the 3,4-thieno-bridged porphyrin. In the former, the antiaromatic contribution is based on a 20-π-electron conjugated circuit. The two thieno-bridged porphyrins were characterized by calculations of nucleus-independent chemical shift and anisotropy of the induced current density as well as by X-ray crystallography, NMR spectroscopy, UV-vis-NIR absorption spectroscopy, electrochemical studies, time-resolved excited-state analysis, and two-photon absorption cross section measurements. Chemical derivatization of the 2,3-thieno-bridged porphyrin was also demonstrated. © 2012 American Chemical Society.

Synthesis, photophysical properties, and excited state dynamics of a platinum complex of tetracene imide disulfide - Nakagawa, Takafumi; Suzuki, Tsuyoshi; König, Matthias; Guldi, Dirk Michael; Matsuo, Yutaka (Chemical Communications, 2013)
A platinum complex containing a tetracene dicarboxylic imide disulfide (TIDS) was synthesized and structurally characterized by X-ray analysis. Steady-state absorption and emission spectroscopy for Pt-TIDS revealed its extended π-conjugated structure. Excited state studies characterized its triplet state with a lifetime of 0.18-0.28 μs. © 2013 The Royal Society of Chemistry.

Synthesis, physicochemical properties and theoretical calculations of a subphthalocyanine peripherally substituted by multiple anthryl-ethynyl-aniline moieties - Fernandez-Vera, Oscar; Bo, Yifan; Luo, Yusen; Labella, Jorge; Guldi, Dirk Michael; Torres, Tomás; Bottari, Giovanni (Journal of Porphyrins and Phthalocyanines, 2023)
We report here the synthesis of a novel C3-subphthalocyanine (SubPc)-based electron donor-acceptor conjugate (1) in which the macrocycle has been functionalized at its peripheral positions with three anthryl-ethynyl-N,N-dimethylaniline groups. The latter moiety, besides conferring increased stability and solubility to the resulting system, substantially broadens its absorption capability. In-depth spectroscopic, spectrometric, and electrochemical analyses as well as theoretical calculations carried out on 1 suggest a moderate ground state intramolecular interaction between the macrocycle and the orthogonally-arranged anthryl-ethynyl-N,N-dimethylaniline moieties. Interestingly, such electronic communication significantly increases in the excited state in a process strongly depending on the polarity of the solvent. On the one hand, in toluene, upon photoexcitation of the anthryl-ethynyl-aniline, the formation of a 1*(SubPc) state is observed which decays into a 3*(SubPc) manifold before deactivating to the ground state. On the other hand, increasing the polarity of the solvent to tetrahydrofuran and benzonitrile, significantly modifies the fate of the photoexcited state. In this new scenario, the 1*(SubPc) state, formed directly upon 550 nm light stimulation or by 1*(anthryl-ethynyl-aniline) sensitization upon 405 nm excitation, transforms into a charge transfer (SubPc)d–-anthryl-ethynyl-anilined+ state which further evolves into a fully charge-separated (SubPc)•−-anthryl-ethynyl-aniline•+ species before deactivating to the ground state.
CRIS-Team Scopus Importer:2023-12-22
Keywords: aniline; anthryl moiety; panchromaticity; photophysics; subphthalocyanine

Synthetic Strategies for the Selective Functionalization of Carbon Nanodots Allow Optically Communicating Suprastructures - Bartolomei, Beatrice; Sbacchi, Maria; Rosso, Cristian; Günay-Gürer, Ayse; Zdrazil, Lukas; Cadranel, Alejandro; Kralj, Slavko; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2024)
The surface of Carbon Nanodots (CNDs) stands as a rich chemical platform, able to regulate the interactions between particles and external species. Performing selective functionalization of these nanoscale entities is of practical importance, however, it still represents a considerable challenge. In this work, we exploited the organic chemistry toolbox to install target functionalities on the CND surface, while monitoring the chemical changes on the material's outer shell through nuclear magnetic resonance spectroscopy. Following this, we investigated the use of click chemistry to covalently connect CNDs of different nature en-route towards covalent suprastructures with unprecedent molecular control. The different photophysical properties of the connected particles allowed their optical communication in the excited state. This work paves the way for the development of selective and addressable CND building blocks which can act as modular nanoscale synthons that mirror the long-established reactivity of molecular organic synthesis.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Carbon Nanodots; Click Chemistry; Nanotechnology; Particle Network; Self-Assembly

Systematic variation of cyanobuta-1,3-dienes and expanded tetracyanoquinodimethane analogues as electron acceptors in photoactive, rigid porphyrin conjugates - Urner, Lorenz M.; Sekita, Michael; Trapp, Nils; Schweizer, W. Bernd; Woerle, Michael; Gisselbrecht, Jean-Paul; Boudon, Corinne; Guldi, Dirk Michael; Diederich, Francois (European Journal of Organic Chemistry, 2015)
We report on a homologous series of nine electron donor-acceptor systems featuring push-pull chromophores as electron acceptors, which are accessible by a cycloaddition-retroelectrocyclization (CA-RE) reaction. The conjugates comprise a ZnII porphyrin as electron donor, which is connected through either a rigid phenylene-ethynylene-phenylene (PEP)-bicyclo[2.2.2]octane or a PEP-trans-decahydroquinoline spacer to different anilino-substituted multicyanobutadienes or extended tetracyanoquinodimethane analogues with first reduction potentials ranging from-1.78 to-0.58 V vs. Fc+/Fc. Characterization of the conjugates includes X-ray crystallography, electrochemistry, DFT calculations, and fluorescence spectroscopy. The extent of ZnII porphyrin fluorescence quenching correlates with the strength of the electron acceptor. Overall, we demonstrate the synthetic feasibility of rationally modulating the acceptor strength by means of the CA-RE reaction in geometrically well-defined electron donor-acceptor conjugates.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Donor-acceptor systems; Electron transfer; Energy conversion; Photochemistry; Porphyrinoids

Taming C60 fullerene: Tuning intramolecular photoinduced electron transfer process with subphthalocyanines - Rudolf, Marc; Trukhina, Olga; Perles, Josefina; Feng, Lai; Akasaka, Takeshi; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2015)
Two subphthalocyanine-C60 conjugates have been prepared by means of the 1,3-dipolar cycloaddition reaction of (perfluoro) or hexa(pentylsulfonyl) electron deficient subphthalocyanines to C60. Comprehensive assays regarding the electronic features-in the ground and excited state-of the resulting conjugates revealed energy and electron transfer processes upon photoexcitation. Most important is the unambiguous evidence-in terms of time-resolved spectroscopy-of an ultrafast oxidative electron transfer evolving from C60 to the photoexcited subphthalocyanines. This is, to the best of our knowledge, the first case of an intramolecular oxidation of C60 within electron donor-acceptor conjugates by means of only photoexcitation.
CRIS-Team Scopus Importer:2023-03-07

Tandem mass spectrometry of π-expanded triphenylamine and N-heterotriangulene scaffolds: Radical cation versus silver(I) adduct - Kinzelmann, Marina; Fröhlich, Nina; Vogel, Alexander; Kivala, Milan; Drewello, Thomas (Journal of Mass Spectrometry, 2024)
Triphenylamine (TPA) and N-heterotriangulene (N-HTA) scaffolds with up to three oligophenyl extensions are investigated by electrospray ionization (tandem) mass spectrometry (ESI-[MS/]MS). Due to their low oxidation potentials, all molecules readily form radical cations in the electrospray process. The energy-resolved collision-induced dissociation behaviour of the molecular ions is contrasted to that of the silver(I) adducts. Complexation with Ag(I) leads to the expected [1:1] and [2:1] complexes (MAg+ and M2Ag+); however, even [1:2] complexes (MAg22+) can be detected for molecules with two and three large π-expansions to allow stabilization of two charges. The TPA scaffolds decompose only at high collision energies through the loss of peripheral tert-butyl groups. A general mechanism for this is proposed commencing with a methyl loss and followed by the release of isobutene and butyl radical moieties. The N-HTA-based scaffolds are considerably less stable and molecular ions fragment at low collision energies. This is caused by the facile loss of methyl radicals from the dimethylmethylene-bridged triangulene core. In contrast, complexation with Ag+ leads to a dramatic stabilization. Most interestingly, dissociation eventually proceeds via the loss of neutral AgCH3, which is indicative of strong bidentate, tweezer-like bonding of Ag+ to the molecules.
CRIS-Team Scopus Importer:2024-08-23
Keywords: CH; energy-resolved collision-induced dissociation; radical cation; silver(I) adduct; π-extended triphenylamine and N-heterotriangulene

Tartaric acid-derived chiral carbon nanodots for catalytic enantioselective ring-opening reactions of styrene oxide - Zhao, Xinyi; Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Zhang, Zhipeng; Liu, Qi; Drewello, Thomas; Guldi, Dirk Michael; Chen, Xiaoqing (Chemical Communications, 2024)
Chiral carbon nanodots (CNDs) were fabricated through the hydrothermal processing of sulfanilic acid and chiral tartaric acid, exhibiting outstanding catalytic performance for the chiral catalysis of the ring-opening reaction. Furthermore, the catalytic mechanism was proposed to understand the link between the chiral structure and the performance of the catalyst.
CRIS-Team Scopus Importer:2024-09-27

Template-Dependent Photochemical Reactivity of Molecular Metal Oxides - Tucher, Johannes; Peuntinger, Katrin; Margraf, Johannes; Clark, Timothy; Guldi, Dirk Michael; Streb, Carsten (Chemistry - A European Journal, 2015)
A combined experimental and theoretical study shows that the photooxidative activity of two isostructural metal oxide clusters depends on their internal templates. To this end, two halide-templated bismuth vanadium oxide clusters [X(Bi(dmso)(3))(2)V12O33](-) (X=Cl-, Br-) are reported and fully characterized. The two clusters show similar absorption features and illustrate that bismuth incorporation results in increased visible-light absorption. Significantly higher photooxidative activity is observed for the bromide-templated cluster compared with the chloride-templated one. Detailed photophysical assays and complementary DFT calculations suggest that the more efficient triplet excited state formation in the Br–containing cluster is the decisive step in the photocatalysis and is due to the heavy-atom effect of the bromide. This concept can therefore open new pathways towards the optimization of photocatalytic activity in metal oxide clusters.
Keywords: density functional calculations; metal oxide; polyoxometalate; self-assembly; template

Testing electron transfer within molecular associates built around anionic C60 and C70 dendrofullerenes and a cationic zinc porphyrin - Sarova, Ginka; Hartnagel, Uwe; Balbinot, Domenico; Sali, Sevda; Jux, Norbert; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2008)
Mono- and bis-functionalized C and C fullerene derivatives (DF, 1-10) that carry one or two oligoanionic dendritic termini in their malonate addends and an oligocationic octapyridinium zinc porphyrin salt (ZnP) were found to self-assemble in buffered aqueous solution to yield a novel series of 1:1 and/or 1:2 electron transfer hybrid associates. Remarkably high association constants-typically on the order of 10 M - were derived that corroborate stable complex formations. A combination of electrostatic and charge-transfer interactions that are operative between the electron-accepting DF and the electron-donating ZnP is considered to contribute to the uniquely high complex stability. First insight into intracomplex excited state interactions came from steady-state and time-resolved fluorescence quenching experiments that were performed with the molecular ZnP/DF hybrid as_sociates. Excited state quenching processes are, for example, evident in form of a bi-exponential fluorescence decay of ZnP - corresponding to a distribution of associated and non-associated ZnP. Unambiguous evidence for an intracomplex electron transfer quenching, namely, formation of ZnP/C and ZnP/C radical ion pairs, was gathered in time-resolved transient absorption measurements. Lifetimes of these radical ion-pairs range from nanoseconds to a few microseconds. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Tetracene Dimers: A Platform for Intramolecular Down- and Up-conversion - Bo, Yifan; Hou, Yuxuan; Thiel, Dominik; Weiß, René; Clark, Timothy; Ferguson, Michael J.; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of the American Chemical Society, 2023)
Photon energy conversion can be accomplished in many different ways, including the two opposing manners, down-conversion (i.e., singlet fission, SF) and up-conversion (i.e., triplet-triplet annihilation up-conversion, TTA-UC). Both processes have the potential to help overcome the detailed balance limit of single-junction solar cells. Tetracene, in which the energies of the lowest singlet excited state and twice the triplet excited state are comparable, exhibits both down- and up-conversion. Here, we have designed meta-diethynylphenylene- and 1,3-diethynyladamantyl-linked tetracene dimers, which feature different electronic coupling, to characterize the interplay between intramolecular SF (intra-SF) and intramolecular TTA-UC (intra-TTA-UC) via steady-state and time-resolved absorption and fluorescence spectroscopy. Furthermore, we have used Pd-phthalocyanine as a sensitizer to enable intra-TTA-UC in the two dimers via indirect photoexcitation in the near-infrared part of the solar spectrum. The work is rounded off by temperature-dependent measurements, which outline key aspects of how thermal effects impact intra-SF and intra-TTA-UC in different dimers.
CRIS-Team Scopus Importer:2023-10-06

Tetrathiafulvalene-based nanotweezers-noncovalent binding of carbon nanotubes in aqueous media with charge transfer implications - Romero, Carlos; Garcia, Raul; Herranz, M. Angeles; Ehli, Christian; Ruppert, Michaela; Hirsch, Andreas; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2012)
Electron donor-acceptor hybrids based on single wall carbon nanotubes (SWCNT) are one of the most promising functional structures that are currently developed in the emerging areas of energy conversion schemes and molecular electronics. As a suitable electron donor, π-extended tetrathiafulvalene (exTTF) stands out owing to its recognition of SWCNT through π-π stacking and electron donor-acceptor interactions. Herein, we explore the shape and electronic complementarity between different types of carbon nanotubes (CNT) and a tweezers-shaped molecule endowed with two exTTFs in water. The efficient electronic communication between semiconducting SWCNT/multiwall carbon nanotubes (MWCNT), on one hand, and the water-soluble exTTF nanotweezers 8, on the other hand, has been demonstrated in the ground and excited state by using steady-state as well as time-resolved spectroscopies, which were further complemented by microscopy. Importantly, appreciable electronic communication results in the electronic ground state having a shift of electron density, that is, from exTTFs to CNT, and in the electronic excited state having a full separation of electron density, that is oxidized exTTF and reduced CNT. Lifetimes in the range of several hundred picoseconds, which were observed for the corresponding electron transfer products upon light irradiation, tend to be appreciably longer in MWCNT/8 than in SWCNT/8. © 2012 American Chemical Society.

The Cascade Reactions of Indigo with Propargyl Substrates for Heterocyclic and Photophysical Diversity - Mccosker, Patrick M.; Butler, Nicholas M.; Shakoori, Alireza; Volland, Michel; Perry, Matthew J.; Mullen, Jesse W.; Willis, Anthony C.; Clark, Timothy; Bremner, John B.; Guldi, Dirk Michael; Keller, Paul A. (Chemistry - A European Journal, 2021)
The synthesis of structurally diverse heterocycles for chemical space exploration was achieved via the cascade reactions of indigo with propargylic electrophiles. New pyrazinodiindolodione, naphthyridinedione, azepinodiindolone, oxazinoindolone and pyrrolodione products were prepared in one pot reactions by varying the leaving group (-Cl, -Br, -OMs, -OTs) or propargyl terminal functionality (-H, -Me, -Ph, -Ar). Mechanistic and density functional theory studies revealed that the unsaturated propargyl moiety can behave as an electrophile when aromatic terminal substitutions are made, and therefore competes with leaving group substitution for new outcomes. Selected products from the cascade reactions were investigated for their absorption and fluorescence properties, including transient absorption spectroscopy. This revealed polarity dependent excited state relaxation pathways, fluorescence, and triplet formation, thus highlighting these reactions as a means to access diverse functional materials rapidly.
CRIS-Team WoS Importer:2021-03-05

The Chemistry of Energy Conversion and Storage - Cho, Jaephil; Dai, Liming; Guldi, Dirk Michael (Chemistry - An Asian Journal, 2016)
CRIS-Team Scopus Importer:2023-03-07

The dissociation behaviour of a singly and doubly charged (cationised) aza-crown ether/metalloporphyrin-conjugate: Metal-induced reactivity and Coulomb explosions Dedication: In memory of Prof. Detlef Schröder. - Li, Jing; Dürr, Katharina L.; von Gernler, Marc; Jux, Norbert; Ivanovic-Burmazovic, Ivana; Drewello, Thomas (International Journal of Mass Spectrometry, 2013)
Fe(III) and Mn(III) complexes of an aza-crown ether/porphyrin conjugate, 5-N-(4-aza-18-crown-6)methyl-5,10,15 ,20-tetra-tert-butyl-5-methyl-5,10,15,20- tetraphenylporphyrin, with Cl and Br as respective counter ions, are studied by electrospray ionisation (ESI)-mass spectrometry (MS). Fragmentation pathways are established by MS and MS collision-induced dissociation (CID) experiments performed with a quadrupole ion trap (QIT) and energy-dependent CID is studied with a quadrupole/time-of-flight (q-ToF) instrument. Singly charged ions are produced by selective protonation, sodiation or potassiation of the crown ether moiety, and dications possess one additional charge on the halide-released porphyrin metal cation. Singly charged parent ions undergo a two-step decay. Firstly, an "ion pair" is lost, composed of the cationic charge carrier of the crown ether and the anionic counter ion at the porphyrin. Secondly, the intact crown ether is released. The threshold of this process is dependent on the nature of the central porphyrin metal, with Fe(III) dramatically facilitating the reaction. The dications undergo two different Coulomb explosions: crown/porphyrin-fission and cation loss from the crown ether, the ratio of which is dependent on the affinity of the cation to the crown ether. © 2013 Elsevier B.V. All rights reserved.

The Effect of PCBM Dimerization on the Performance of Bulk Heterojunction Solar Cells - Distler, Andreas; Sauermann, Tobias; Egelhaaf, Hans-Joachim; Rodman, Sheila; Waller, Dave; Cheon, Kap-Soo; Lee, Mike; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
Increasing the lifetime of polymer based organic solar cells is still a major challenge. Here, the photostability of bulk heterojunction solar cells based on the polymer poly[4,4'-bis(2-ethylhexyl)dithieno[3,2-b:2',3'-d]silole)-2,6-diyl-alt-[2,5-bis(3-tetradecylthiophen-2-yl)thiazole[5,4-d]thiazole)-1,8-diyl] (PDTSTzTz) and the fullerene [6,6]-phenyl-C-butyric acid methyl ester (PCBM) under inert atmosphere is investigated. Correlation of electrical measurements on complete devices and UV-vis absorption measurements as well as high-performance liquid chromatography (HPLC) analysis on the active materials reveals that photodimerization of PCBM is responsible for the observed degradation. Simulation of the electrical device parameters shows that this dimerization results in a significant reduction of the charge carrier mobility. Both the dimerization and the associated device performance loss turn out to be reversible upon annealing. BisPCBM, the bis-substituted analog of PCBM, is shown to be resistant towards light exposure, which in turn enables the manufacture of photostable PDTSTzTz:bisPCBM solar cells. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei

The effects of post-processing on the surface and the optical properties of copper indium sulfide quantum dots - Akdas, Tugce; Distaso, Monica; Kuhri, Susanne; Winter, Benjamin; Birajdar, Balaji; Spiecker, Erdmann; Guldi, Dirk Michael; Peukert, Wolfgang (Advances in Colloid and Interface Science, 2015)
In the current contribution we report on investigations regarding the surface of CuInS2 quantum dots and on different strategies to control the amount of surface ligands in a post-processing step. In particular, the reactivity of the organic components, that is, 1-dodecanthiol and 1-octadecene as ligand and solvent, respectively, during nanocrystal formation was studied. A new method to remove residuals from the reaction mixture and to detach excess organics from the surface of the nanocrystals is reported. Our new method, which is based on the utilization of acids, is compared with standard purification procedures by means of thermogravimetric analysis (TGA) with particular focus on its efficiency to remove organics. As a complement, the surface chemistry is analyzed by nuclear magnetic resonance spectroscopy (NMR) to shed light on the nature of the organic components still present after purification. Further analysis of the product by inductively coupled plasma optical emission spectroscopy (ICP-OES) is performed to verify the influence of the new purification method on surface composition and properties. Moreover, steady state and time resolved spectroscopies give insights into excitonic behavior as well as recombination processes. Finally, the new method is optimized for the purification of CuInS2-ZnS nanocrystals, which show enhanced optical properties.

The Electronic Structure of Amorphous Carbon Nanodots - Margraf, Johannes; Strauß, Volker; Guldi, Dirk Michael; Clark, Timothy (Journal of Physical Chemistry B, 2015)
We have studied hydrogen-passivated amorphous carbon nanostructures with semiempirical molecular orbital theory in order to provide an understanding of the factors that affect their electronic properties. Amorphous structures were first constructed using periodic calculations in a melt/quench protocol. Pure periodic amorphous carbon structures and their counterparts doped with nitrogen and/or oxygen feature large electronic band gaps. Surprisingly, descriptors such as the elemental composition and the number of sp3-atoms only influence the electronic structure weakly. Instead, the exact topology of the sp2-network in terms of effective conjugation defines the band gap. Amorphous carbon nanodots of different structures and sizes were cut out of the periodic structures. Our calculations predict the occurrence of localized electronic surface states, which give rise to interesting effects such as amphoteric reactivity and predicted optical band gaps in the near-UV/visible range. Optical and electronic gaps display a dependence on particle size similar to that of inorganic colloidal quantum dots.

The energy-transfer-enabled biocompatible disulfide–ene reaction - Teders, Michael; Henkel, Christian; Anhaeuser, Lea; Strieth-Kalthoff, Felix; Gomez-Suarez, Adrian; Kleinmans, Roman; Kahnt, Axel; Rentmeister, Andrea; Guldi, Dirk Michael; Glorius, Frank (Nature chemistry, 2018)
Sulfur-containing molecules participate in many essential biological processes. Of utmost importance is the methylthioether moiety, present in the proteinogenic amino acid methionine and installed in tRNA by radical-S-adenosylmethionine methylthiotransferases. Although the thiol–ene reaction for carbon–sulfur bond formation has found widespread applications in materials or medicinal science, a biocompatible chemo- and regioselective hydrothiolation of unactivated alkenes and alkynes remains elusive. Here, we describe the design of a general chemoselective anti-Markovnikov hydroalkyl/aryl thiolation of alkenes and alkynes—also allowing the biologically important hydromethylthiolation—by triplet–triplet energy transfer activation of disulfides. This fast disulfide–ene reaction shows extraordinary functional group tolerance and biocompatibility. Transient absorption spectroscopy was used to study the sensitization process in detail. The hereby gained mechanistic insights were successfully employed for optimization of the catalytic system. This photosensitized transformation should stimulate bioimaging applications and carbon–sulfur bond-forming late-stage functionalization chemistry, especially in the context of metabolic labelling.
CRIS-Team Scopus Importer:2022-04-14

The Excited-State Creutz–Taube Ion - Pieslinger, German E.; Ramírez-Wierzbicki, Ivana; Cadranel, Alejandro (Angewandte Chemie International Edition, 2022)
The excited-state version of the Creutz–Taube ion was prepared via visible light excitation of [(NH3)5RuII(μ-pz)RuII(NH3)5]4+. The resulting excited state is a mixed valence RuIII–δ(μ-pz⋅−)RuII+δ transient species, which was characterized using femtosecond transient absorption spectroscopy with vis-NIR detection. Very intense photoinduced intervalence charge transfers were observed at 7500 cm−1, revealing an excited-state electronic coupling element HDA=3750 cm−1. DFT calculations confirm a strongly delocalized excited state. A notable consequence of strong electron delocalization is the nanosecond excited state lifetime, which was exploited in a proof-of-concept intermolecular electron transfer. The excited-state Creutz–Taube ion is established as a reference, and demonstrates that electron delocalization in the excited state can be leveraged for artificial photosynthesis or other photocatalytic schemes based on electron transfer chemistry.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Electron Transfer; Electronic Coupling; Excited States; Intervalence; Mixed Valence

The first fullerene-heterofullerene dyad - Hauke, Frank; Herranz, María Ángeles; Echegoyen, Luis; Guldi, Dirk Michael; Hirsch, Andreas; Atalick, Stefan; Hauke, Frank (Chemical Communications, 2004)
The highly regioselective attack of a C malonate containing a terminal acetyl function to the heterofullerene cage CN leads to the formation of the first fullerene-heterofullerene dyad, representing a new scaffold for directional energy transduction.

The Impact of Aggregation of Quaterthiophenes on the Excited State Dynamics - Ghosh, Srijon; Jana, Bikash; Ghosh, Arnab; Guldi, Dirk Michael; Patra, Amitava (Journal of Physical Chemistry Letters, 2021)
Oligothiophenes and their aggregates play a dominant role in optoelectronic and light-harvesting applications. Here, we controlled the degree of aggregation of 2,2':5',2″:5'',2‴-quaterthiophene (QTH) to shed light on the impact of the aggregation on the excited state dynamics. QTH aggregation realized the control over the Intersystem Crossing (ISC) rates and, in turn, the formation of triplet excited states via the simple addition of water to QTH solutions in THF. From global target analysis, the time scale was 345.5 ps for ISC for QTHs in THF, but it was 2.33 ns in the case of QTH solutions featuring 70% water. Notably, the excitonic coupling between closely packed QTHs occurred predominantly in the aggregates formed in the presence of large water concentrations. Relaxation dynamics of the resulting QTH-aggregates differed substantially from QTH solutions at lower water content. For example, QTH-aggregates lacked any triplet excited states, and the unusual emission occurs from lower excitonic states from these predominantly H-aggregates.
CRIS-Team Scopus Importer:2021-04-19

The Impact of Aggregation on the Photophysics of Spiro-Bridged Heterotriangulenes - Krug, Marcel; Wagner, Maximilian; Schaub, Tobias A.; Zhang, Wen-Shan; Schüßlbauer, Christoph; Ascherl, Johannes D. R.; Münich, Peter Wilhelm; Schroeder, Rasmus R.; Gröhn, Franziska; Dral, Pavlo O.; Barbatti, Mario; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2020)
We report on the impact of the central heteroatom on structural, electronic, and spectroscopic properties of a series of spirofluorene-bridged heterotriangulenes and provide a detailed study on their aggregates. The in-depth analysis of their molecular structure by NMR spectroscopy and X-ray crystallography was further complemented by density functional theory calculations. With the aid of extensive photophysical analysis the complex fluorescence spectra were deconvoluted showing contributions from the peripheral fluorenes and the heteroaromatic cores. Beyond the molecular scale, we examined the aggregation behavior of these heterotriangulenes in THF/H2O mixtures and analyzed the aggregates by static and dynamic light scattering. The excited-state interactions within the aggregates were found to be similar to those found in the solid state. A plethora of morphologies and superstructures were observed by scanning electron microscopy of drop-casted dispersions.
CRIS-Team WoS Importer:2020-07-24

The Influence of Alkali Metal Cation Size on the Formation and Dissociation of Crown Ether Fullerene Dimers in Electrospray Mass Spectrometry - Kellner, Ina; von Gernler, Marc; Tzirakis, Manolis D.; Orfanopoulos, Michael; Drewello, Thomas (Journal of Physical Chemistry C, 2016)
Created from Fastlane, Scopus look-up

The mechanical bond on carbon nanotubes: Diameter-selective functionalization and effects on physical properties - Martinez-Perinan, Emiliano; De Juan, Alberto; Pouillon, Yann; Schierl, Christoph; Strauß, Volker; Martin, Nazario; Rubio, Angel; Guldi, Dirk Michael; Lorenzo, Encarnacion; Perez, Emilio M. (Nanoscale, 2016)
We describe the functionalization of SWNTs enriched in (6,5) chirality with electron donating macrocycles to yield rotaxane-type mechanically interlocked carbon nanotubes (MINTs). Investigations by means of electron microscopy and control experiments corroborated the interlocked nature of the MINTs. A comprehensive characterization of the MINTs through UV-vis-NIR, Raman, fluorescence, transient absorption spectroscopy, cyclic voltammetry, and chronoamperometry was carried out. Analyses of the spectroscopic data reveal that the MINT-forming reaction proceeds with diameter selectivity, favoring functionalization of (6,5) SWNTs rather than larger (7,6) SWNTs. In the ground state, we found a lack of significant charge-transfer interactions between the electron donor exTTF and the SWNTs. Upon photoexcitation, efficient charge-transfer between the electron donating exTTF macrocycles and SWNTs was demonstrated. As a complement, we established significantly different charge-transfer rate constants and diffusion coefficients for MINTs and the supramolecular models, which confirms the fundamentally different type of interactions between exTTF and SWNTs in the presence or absence of the mechanical bond. Molecular mechanics and DFT calculations support the experimental findings.
CRIS-Team Scopus Importer:2023-03-07

Theoretical and experimental insights into the surface chemistry of semiconductor quantum dots - Margraf, Johannes; Ruland Palaia, Andres; Sgobba, Vito; Guldi, Dirk Michael; Clark, Timothy (Langmuir, 2013)
We present a series of non-stoichiometric cadmium sulfide quantum-dot (QD) models. Using density functional theory (DFT) and semi-empirical molecular orbital (MO) calculations, we explore the ligand binding and exchange chemistry of these models. Their surface morphology allows for these processes to be rationalized on the atomic scale. This is corroborated by ultraviolet-visible (UV-vis), infrared (IR), and inductively coupled plasma-optical emission spectroscopy (ICP-OES). © 2013 American Chemical Society.

The redox chemistry of copper tetraphenylporphyrin revisited - Saphier, Magal; Yifrah, Tova; Zilbermann, Israel; Saphier, Oshra; Shames, Alexander I.; Froumin, Natalya; Meyerstein, Dan; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2012)
Mixing Cu(II)Cl with free base tetraphenylporphyrin ((H (TPP)) in dry deaerated 1,2-dichloroethane surprisingly yields a mixture of Cu(II)(TPP) and Cu(III)(TPP). The later is long-lived in the absence of water and slowly decomposes within days to yield Cu(II)(TPP). Furthermore, in the presence of air, a slightly different Cu porphyrin species forms, presumably, Cu(III)(TPP) , in which the Q-band is subject to a 10 nm red shift. The new Cu(III)(TPP) and Cu(III)(TPP) differ in terms of absorption, fluorescence, electron paramagnetic resonance (EPR), and X-ray photoemission spectroscopy (XPS) when compared to the well-characterized Cu(II)(TPP), Cu(II)(TPP) , and Cu(II)(TPP) species. © 2012 World Scientific Publishing Company.

The Role of Light Irradiation and Dendrimer Generation in Directing Electrostatic Self-Assembly - Agarwal, Mohit; Zika, Alexander; Yücel, Müge; Schweins, Ralf; Kohlbrecher, Joachim; Gröhn, Franziska (Polymers, 2025)
pH-responsive polyamidoamine (PAMAM) dendrimers are used as well-defined building blocks to design light-switchable nano-assemblies in solution. The complex interplay between the photoresponsive di-anionic azo dye Acid Yellow 38 (AY38) and the cationic PAMAM dendrimers of different generations is presented in this study. Electrostatic self-assembly involving secondary dipole–dipole interactions provides well-defined assemblies within a broad size range (10 nm–1 μm) with various shapes. The size and shape of these assemblies were determined using dynamic and static light scattering (DLS/SLS) and small-angle neutron scattering (SANS); ζ-potential measurements were performed to elucidate the charge characteristics, revealing the effective surface charge density of the nano-objects as an important parameter in the size and shape control. UV–vis spectroscopy and isothermal titration calorimetry (ITC) were employed to investigate the interaction on a molecular level and from a thermodynamic point of view. The results show that the amount of isomerized cis dye depends on the dendrimer generation because of a photoprotective effect through electrostatics for lower generations and through dipole–dipole interactions for higher generations; as the cis dye and trans dye bind with different strength, the amount of cis dye then again encodes the charge density and thereby the particle size and shape.
CRIS-Team Scopus Importer:2025-01-31
Keywords: azo dye; dendrimer; electrostatic self-assembly; light irradiation; photoresponsive; switchability

The Soft Nanodots as Fluorescent Probes for Cell Imaging: Analysis of Cell and Spheroid Penetration Behavior of Single Chain Polymer Dots - Yücel, Müge; Onbas, Rabia; Arslan Yildiz, Ahu; Yildiz, Umit Hakan (Macromolecular Bioscience, 2024)
This study describes the formation, size control, and penetration behavior of polymer nanodots (Pdots) consisting of single or few chain polythiophene-based conjugated polyelectrolytes (CPEs) via nanophase separation between good solvent and poor solvent of CPE. Though the chain singularity may be associated with dilution nanophase separation suggests that molecules of a good solvent create a thermodynamically driven solvation layer surrounding the CPEs and thereby separating the single chains even in their poor solvents. This statement is therefore corroborated with emission intensity/lifetime, particle size, and scattering intensity of polyelectrolyte in good and poor solvents. Regarding the augmented features, Pdots are implemented into cell imaging studies to understand the nuclear penetration and to differentiate the invasive characteristics of breast cancer cells. The python based red, green, blue (RGB) color analysis depicts that Pdots have more nuclear penetration ability in triple negative breast cancer cells due to the different nuclear morphology in shape and composition and Pdots have penetrated cell membrane as well as extracellular matrix in spheroid models. The current Pdot protocol and its utilization in cancer cell imaging are holding great promise for gene/drug delivery to target cancer cells by explicitly achieving the very first priority of nuclear intake.
CRIS-Team Scopus Importer:2024-01-19
Keywords: conjugated polyelectrolyte; image analysis; nanophase separation; polymer dots; triple negative breast cancer

The Transfer Dehydrogenation Method Enables a Family of High Crystalline Benzimidazole-linked Cu (II)-phthalocyanine-based Covalent Organic Frameworks Films - Liu, Liping (Angewandte Chemie International Edition, 2024)

Thin membranes versus bulk substrates: Investigation of proximity effects in focused electron beam-induced processing - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Kunzmann, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physics D-Applied Physics, 2012)
The resolution of focused electron beam induced processing techniques is limited by electron scattering processes. General wisdom holds that using a membrane, this can be effectively improved due to a cutoff of the electron interaction volume and thus diminished proximity effects. Recently, we demonstrated that in contrast to the expectation, proximity effects can be indeed larger on a 200nm silicon nitride membrane than on the respective bulk substrate, due to charging-induced surface activation. Herein, we expand these investigations on proximity effects in electron beam-induced surface activation to other substrates and to electron beam-induced deposition followed by autocatalytic growth. © 2012 IOP Publishing Ltd.

Threefold exTTF-based Buckycatcher - Radhakrishnan, Shankara Gayathri; Guldi, Dirk Michael; Perez, Emilio M.; Perez, Iria; Bietti, Massimo; Martin, Nazario (Journal of Coordination Chemistry, 2010)
Charge-transfer complex formation by a tuning-fork shaped π-extended tetrathiafulvalene-based molecule, which acts as molecular catcher for C in a variety of solvents upon photoexcitation, has been explored. An increase in 2-[9-(1, 3-dithiol-2-ylidene)anthracen-10(9H)-ylidene]-1, 3-dithiole unit creates an easy-chair like conformation accommodating C60, which leads to a binding constant and lifetime of radical ion pair state of 2.23 × 10 (mol L ) and 4.8 ps in ortho-dichlorobenzene. © 2010 Taylor & Francis.

Th-symmetrical hexakisadducts of C60 with a densely packed π-donor shell can act as energy- or electron-transducing systems - Diekers, Michael; Luo, Chuping; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2002)
For the first time several T-symmetrical hexakisadducts of C bearing up to six electro- and photoactive o-phenylene diamine or 9,10-dialkoxyanthracene moieties were synthesized and subjected to photoinduced electron/energy-transfer studies. Both donors form a densely packed π-donor shell surrounding the fullerene core. In these novel core-shell ensembles (7 and 19), either an efficient energy transfer from the dialkoxyanthracene periphery, or an electron transfer from the o-phenylene diamine periphery transduces the flow of excited-state energy or electrons, respectively, to the fullerene moiety, which resides in the central core. Due to the relatively high reduction potential of the fullerene core, which is anodically shifted by ≈0.7 V, compared with that of pristine C, the outcome of these intramolecular reactions depends mainly on the donor ability of the peripheral system. Interestingly, the charge-separated state in the o-phenylene diamine heptad (7; τ = 2380 ns in benzonitrile) is stabilized by a factor of 20 relative to the corresponding o-phenylene diamine dyad (6; τ = 120 ns in benzonitrile), an effect that points unequivocally to the optimized storage of charges in this highly functionalized fullerene ensemble.

Time-Resolved Exploration of a photoCORM Ru(bpy) - Levin, Natalia; Marcolongo, Juan Pablo; Cadranel, Alejandro; Slep, Leonardo Daniel (Inorganic Chemistry)
The carbon monoxide (CO)-photoreleasing molecule [Ru(Me3[9]aneN3)(bpy)(CO)]2+ (RuCO2+ bpy = 2,2′-bipyridine) was prepared and structurally characterized. The photochemical behavior was studied in unprecedented detail for this type of system, using a combination of steady-state and ultrafast transient absorption experiments, which unveiled that 3MLCT and 3dd excited states participate in the decay cascade of photoexcited RuCO2+. Theoretical calculations yield a consistent picture, providing details of the electronic structure of the transient species involved. Our results suggest that the photorelease of CO involves excited states of different electronic nature that are populated sequentially and in parallel. This complex scenario strengthens the idea that the rational design of a good photoCORM is a difficult task to carry out solely using the tools provided by chemical intuition: it is necessary to control by design factors that favor the population of specific photoactive electronic states with respect to those that are not.
CRIS-Team Scopus Importer:2020-09-18

Topological and conformational effects on electron transfer dynamics in porphyrin-[60]fullerene interlocked systems - Megiatto, Jackson D.; Schuster, David I.; De Miguel Rojas, Gustavo; Wolfrum, Silke; Guldi, Dirk Michael (Chemistry of Materials, 2012)
The effect of molecular topology and conformation on the dynamics of photoinduced electron transfer (ET) processes has been studied in interlocked electron donor-acceptor systems, specifically rotaxanes with zinc(II)-tetraphenylporphyrin (ZnP) as the electron donor and [60]fullerene (C ) as the electron acceptor. Formation or cleavage of coordinative bonds was used to induce major topological and conformational changes in the interlocked architecture. In the first approach, the tweezer-like structure created by the two ZnP stopper groups on the thread was used as a recognition site for complexation of 1,4-diazabicyclo[2.2.2]octane (DABCO), which creates a bridge between the two ZnP moieties of the rotaxane, generating a catenane structure. The photoinduced processes in the DABCO-complexed (ZnP) -[2]catenate-C system were compared with those of the (ZnP) -rotaxane-C precursor and the previously reported ZnP-[2]catenate-C . Steady-state emission and transient absorption studies showed that a similar multistep ET pathway emerged for rotaxanes and catenanes upon photoexcitation at various wavelengths, ultimately resulting in a long-lived ZnP /C charge-separated radical pair (CSRP) state. However, the decay kinetics of the CSRP states clearly reflect the topological differences between the rotaxane, the catenate, and DABCO-complexed-catenate architectures. The lifetime of the long-distance ZnP -[Cu(I)phen ] -C CSRP state is more than four times longer in 3 (1.03 μs) than in 1 (0.24 μs) and approaches that in catenate 2 (1.1 μs). The results clearly showed that creation of a catenane from a rotaxane topology inhibits the charge recombination process. In a second approach, when the Cu(I) ion used as the template to assemble the (ZnP) -[Cu(I) phen ] -C rotaxane was removed, it was evident that a major structural change had occurred. since charge separation between the chromophores was no longer observed upon photoexcitation in nonpolar as well as in polar solvents. Only ZnP and C triplet excited states were observed upon laser excitation of the Cu-free rotaxane. These results highlight the critical importance of the central Cu(I) ion for long-range ET processes in these nanoscale interlocked electron donor-acceptor systems. © 2012 American Chemical Society.

Toward combining graphene and QDs: Assembling CdTe QDs to exfoliated graphite and nanographene in water - Katsukis, Georgios; Malig, Jenny; Schulz-Drost, Christian; Leubner, Susanne; Jux, Norbert; Guldi, Dirk Michael (Acs Nano, 2012)
Herein, we report for the first time on a full-fledged investigation of water-soluble CdTe quantum dots (QD) that are immobilized onto exfoliated graphite (EG) and/or nanographene (NG). Particular emphasis was placed on a top-down preparation of stable aqueous dispersions-starting from natural graphite rather than graphene oxide-while preserving the intrinsic properties of graphene. To this end, we circumvented the harsh conditions commonly employed for the pre-exfoliation (i.e., Hummers method). First, a hydrophobic- hydrophobic/π-π stacking motif was tested between EG and pyrene, to which QDs are covalently attached (QD-pyrene). Second, we employed the combination of hydrophobic-hydrophobic/π-π stacking and electrostatic interactions to build up hierarchical structures composed of NG, positively charged pyrene (pyrene ), and negatively charged QDs. The novel nanohybrids-QD- pyrene/EG and QD/pyrene /NG-were characterized with specific emphasis on electron-transfer chemistry. In fact, both assays provide kinetic and spectroscopic evidence that support electron transfer dynamics that vary, however, between EG and NG as a reflection of the different degree of graphite exfoliation. © 2012 American Chemical Society.

Toward multifunctional wet chemically functionalized graphene - Integration of oligomeric, molecular, and particulate building blocks that reveal photoactivity and redox activity - Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Accounts of Chemical Research, 2013)
Many technological applications indispensable in our daily lives rely on carbon. By altering the periodic binding motifs in networks of sp, sp, and sp-hybridized carbon atoms, researchers have produced a wide palette of carbon allotropes. Over the past two decades, the physicochemical properties of low-dimensional nanocarbons, including fullerenes (0D), carbon nanotubes (1D), and, most recently, graphene (2D), have been explored systematically.An entire area of research has focused on the chemistry of 1D nanocarbons, particularly single-wall carbon nanotubes. These structures exhibit unique electronic, mechanical, and optical properties. These properties are, however, only discernible for single-wall carbon nanotubes that are debundled, individualized, and stabilized, often in solution. Most prominently, they are small band gap, p-type semiconductors or metals with conductances that reach ballistic dimensions. These structures can have poor solubility in many media, and large bundles can originate from attractive interactions such as π-π stacking and London dispersion forces. Therefore, both covalent and noncovalent modifications of single-wall carbon nanotubes have emerged as powerful approaches to overcome some of these problems. Noncovalent functionalization is especially useful in improving the solubility without altering the electronic structure.We expect that many of the strategies that have recently been exploited and established in the context of 1D nanocarbons can be applied to the chemistry of 2D nanocarbons, especially graphene. Two-dimensional nanocarbons are currently attracting extensive attention due to their striking mechanical, optical, and electrical features. Nanocarbons that are a single atom thick are gapless semiconductors and exhibit electron mobilities reaching values of up to 15000 cm V s at room temperature. Researchers have made rapid progress in the covalent and/or noncovalent functionalization of graphene with photoactive and or redox active building blocks.In this Account, we summarize our work on the integration of photoactive and/or redox active building blocks, including oligomers, molecules, and particulates, onto graphenoid materials to yield multifunctional electron donor-acceptor conjugates and hybrids. Intriguingly, we produce graphene in the form of single-layer, bilayer, and multilayer graphene through the exfoliation of graphite by surface active agents. The exfoliation occurs through π-π, hydrophobic, van der Waals, electrostatic, and charge transfer interactions, and the surface active agents also serve as versatile anchor groups. We studied the electronic interactions in terms of photoactivity and/or redox activity in depth by steady-state and time-resolved spectroscopy. Finally, we present examples of proof-of-principle solar energy conversion devices. © 2012 American Chemical Society.

Towards enhancing light harvesting - Subphthalocyanines as electron acceptors - Nieto, Carlos Romero; Medina, Anais; Molina-Ontoria, Agustin; Claessens, Christian G.; Echegoyen, Luis; Martin, Nazario; Torres, Tomas; Guldi, Dirk Michael (Chemical Communications, 2012)
One carbon atom is too many. Two subphthalocyanine-extended TTF electron donor-acceptor conjugates were synthesized and characterized. Their photophysical properties prompt the remarkable impact that one extra carbon between the two constitutents exerts on photoinduced processes, that is, charge recombination dynamics in the normal versus inverted region. © The Royal Society of Chemistry 2012.

Towards tunable graphene/phthalocyanine-PPV hybrid systems - Malig, Jenny; Jux, Norbert; Kießling, Daniel; Cid, Juan-Jose; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2011)
Exfoliation of graphite was achieved using a zinc phthalocyanine oligomer that is also an electron donor. The resulting functionalized graphene material was investigated by Raman and electron spectroscopy and was trialed in a photoelectrochemical cell. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Towards understanding the competition of electron and energy transfer in “molecular” nanographenes on the example of hexa-peri-hexabenzocoronene - Beneventi, Giovanni Mariano; Krug, Marcel; Reger, David; Jux, Norbert; Guldi, Dirk Michael (Journal of Photochemistry and Photobiology C-Photochemistry Reviews, 2023)
Bottom-up strategies have allowed the synthesis of “molecular” nanographenes with full control over size, shape and functionality. In recent years, the progress on wet chemical approaches, oxidative cyclodehydrogenation amongst all, has been the foundation to the synthesis of an impressive number of soluble and well-defined molecular nanographenes. The level of control over nanographene syntheses has allowed a fine-tuning of the photophysical and electrochemical properties and, in turn, has a compelling potential in the field of material science. In this regard, understanding and harnessing the competition between electron transfer and energy transfer in nanographenic systems is of utmost importance. However, a comprehensive structure-property relationship remains still an open aspect. In the present review we describe a large variety of hexa-peri-hexabenzocoronene (HBC)-based nanographenes obtained through wet chemical strategies and linked – either covalently or non-covalently – to porphyrins, rylenes, fullerenes, etc. Particular attention was placed on the optical, electrochemical and excited-state properties.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Electron transfer; Energy transfer; Hexa-peri-hexabenzocoronene; Nanographene; Polycyclic aromatic hydrocarbons

trans-2 addition pattern to power charge transfer in dendronized metalloporphyrin C60 conjugates - Spänig, Fabian; Ruppert, Michaela; Dannhäuser, Jörg; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2009)
Coordinating different transition metalssmanganese(III), iron(III), nickel(II), and copper(II) - by a dendronized porphyrin afforded a new family of redox-active metalloporphyrins to which C was attached as a ground-state electron acceptor. Such a strategy introduced an additional center of redoxactivity, that is, a change of the oxidation state of the metal. Cyclic voltammetry and absorption/fluorescence measurements provided support for mutual interactions between the redox-active constituents in the ground state. In particular, slightly anodic shifted reduction potentials/cathodic shifted oxidation potentials and the occurrence of new charge transfer features in the 700-900 nm range prompt to sizable electronic coupling in the range of 300 cm. Photophysical meansssteady-state/time-resolved fluorescence and transient absorption measurementssshed light on the excited-state interactions. To this end, we have added pulse radiolytic investigations to characterize the radical cation (i.e., metalloporphyrins) and radical anion (i.e., fullerene) characteristics. π-π stacking of the excited state electron donor and the electron acceptor is key to overcome the intrinsically fast deactivation of the excited states in these metalloporphyrins and to power an exothermic charge transfer. The lifetimes of the rapidly and efficiently generated radical ion pair states, which range from 15 to >3000 ps, revealed several important trends. First, they were found to depend on the solvent polarity. Second, the nature of the transition metal plays a similarly decisive role. It is important that the product of charge recombination, namely tripmultiplet excited states versus ground state, had a great impact. Finally, a correlation between the charge transfer rate (i.e., charge separation and charge recombination) and the free energy change for the underlying reaction reveals a parabolic dependence with parameters of the reorganization energy (0.84 eV) and electronic coupling (70 cm) closely resembling that seen for the zinc(II) and free base analogues. © 2009 American Chemical Society.

Transduction of excited state energy between covalently linked porphyrins and phthalocyanines - Hausmann, Anita; Soares, Ana R. M.; Victoria Martinez-Diaz, M.; Neves, Maria G. P. M. S.; Tome, Augusto C.; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael (Photochemical & Photobiological Sciences, 2010)
Complementary experiments, that is, femtosecond up-conversion fluorescence, conventional fluorescence lifetime measurements, and transient absorption measurements, imply efficient porphyrin-to-phthalocyanine energy transfer phenomena in NH-connected porphyrin/phthalocyanine conjugates. © 2010 The Royal Society of Chemistry and Owner Societies.

Transient absorption spectroscopy studies on polythiophene-fullerene bulk heterojunction organic blend films sensitized with a low-bandgap polymer - Löslein, Heiko; Ameri, Tayebeh; Matt, Gebhard; Koppe, Markus; Egelhaaf, Hans J.; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Brabec, Christoph (Macromolecular Rapid Communications, 2013)
Recently, the concept of near-infrared sensitization is successfully employed to increase the light harvesting in large-bandgap polymer-based solar cells. To gain deeper insights into the operation mechanism of ternary organic solar cells, a comprehensive understanding of charge transfer-charge transport in ternary blends is a necessity. Herein, P3HT:PCPDTBT:PCBM ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the P3HT:PCPDTBT:PCBM 0.9:0.1:1 blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Polythiophene-fullerene bulk heterojunction ternary blend films are investigated by transient absorption spectroscopy. Hole transfer from PCPDTBT-positive polarons to P3HT in the blend film can be visualized. This process evolves within 140 ps and is discussed with respect to the proposed charge-generation mechanisms. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Transmission electron microscopy and time resolved optical spectroscopy study of the electronic and structural interactions of ZnO nanorods with bovine serum albumin - Klaumünzer, Martin; Weichsel, Ulrike; Mackovic, Mirza; Spiecker, Erdmann; Peukert, Wolfgang; Kryschi, Carola; Spiecker, Erdmann; Mackovic, Mirza (Journal of Physical Chemistry B, 2013)
The adsorption behavior and electronic interactions of bovine serum albumin (BSA) with ZnO nanorod surfaces were investigated using high-resolution transmission electron microscopy as well as stationary and time-resolved optical spectroscopy techniques. Transmission electron microscopy shows that ZnO nanorod surfaces are surrounded by a homogeneous amorphous BSA film with thicknesses between ∼2.5 and 5.0 nm. The electronic structure and adsorption geometry of BSA were examined using high-angle annular dark field scanning transmission electron microscopy combined with electron energy loss spectroscopy. The adsorption process was observed to result into an unfolded conformation of BSA becoming predominantly bound in the side-on orientation at the ZnO surface. This adsorption mode of the BSA molecules allows for a strong interaction with surface states of the ZnO nanorods. This is obvious from its efficient quenching of the defect-center photoluminescence of ZnO. Complementary information of electronic interactions across the ZnO nanorod interface was obtained from femtosecond transient absorption spectroscopy experiments. The rise dynamics of the measured transients revealed altered hole trapping dynamics and, thus, indicated to heterogeneous charge transfer as emerging from adsorbed BSA molecules to defect centers of the ZnO interface. © 2013 American Chemical Society.

Trapping fullerenes with jellyfish-like subphthalocyanines - Sanchez-Molina, Irene; Claessens, C. G.; Grimm, Bruno; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
Six electronically different concave-shaped subphthalocyanines (SubPcs) have been prepared for testing the structural factors governing fullerenes encapsulation. Thus, the supramolecular interaction of SubPcs with C and C fullerenes in solution has been studied by Job's plot and titration experiments, which yielded quantitative information on both the stoichiometry and strength of the complexes in toluene solution. The importance of the electronic nature of the SubPc was demonstrated, as it influences not only the stability of the complex, but also its stoichiometry. Alkyl chains incorporated in hexaalkylthio-substituted SubPcs seem to in some way cooperate in the binding process and influence its kinetics. In the resulting 2:1 complexes, the large absorption cross section of SubPcs throughout the visible part of the spectrum is the beginning of an unidirectional energy transfer to funnel the excited state energy from the periphery (i.e., two SubPcs) to the core (i.e., C and C). © 2013 The Royal Society of Chemistry.

Trapping intermediate MLCT states in low-symmetry Ru(bpy) - Cadranel, Alejandro; Oviedo, Paola S.; Pieslinger, German E.; Yamazaki, Shiori; Kleiman, Valeria D.; Baraldo, Luis M.; Guldi, Dirk Michael (Chemical Science)
The picosecond excited state dynamics of [Ru(tpm)(bpy)(NCS)]+ (RubNCS+) and [Ru(tpm)(bpy)(CN)]+ (RubCN+) (tpm = tris(1-pyrazolyl)methane, bpy = 2,2′-bipyridine) have been analyzed by means of transient absorption measurements and spectroelectrochemistry. Emissive 3MLCTs with (GS)HOMO(h+)-(GS)LUMO(e-) configurations are the lowest triplet excited states regardless of whether 387 or 505 nm photoexcitation is used. 387 nm photoexcitation yields, after a few picoseconds, the emissive 3MLCTs. In contrast, 505 nm photoexcitation populates an intermediate excited state that we assign as a 3MLCT state, in which the hole sits in a metal-centered orbital of different symmetry, prior to its conversion to the emissive 3MLCTs. The disparities in terms of electronic configuration between the intermediate and the emissive 3MLCTs have two important consequences. On one hand, both states feature very different fingerprint absorptions in transient absorption measurements. On the other hand, the reconfiguration is impeded by a kinetic barrier. As such, the conversion is followed spectroscopically and kinetically on the 300 ps timescale.
CRIS-Team Scopus Importer:2022-04-14

Tri- and hexaferrocenyl-substituted subphthalocyanines in the quest for the optimum electron donor-acceptor distances - Fernandez-Ariza, Javier; Krick Calderon, Rafael; Perles, Josefina; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2017)
Three and six ferrocenyl subunits have been attached to the periphery of subphthalocyanines (SubPcs). Unlike axially coordinated ferrocenes, peripherally-bonded ferrocenes have an impact on the electronic features of SubPcs, which show a 44 to 70 nm red-shift of their Q-bands. The unusually deep and narrow ferrocenyl-SubPc is able to host C60, giving rise to atypical SubPc•C60 cocrystallates, through a combination of concave-convex and convex-convex π-π interactions.
CRIS-Team Scopus Importer:2022-04-14

Triazole bridges as versatile linkers in electron donor-acceptor conjugates - De Miguel Rojas, Gustavo; Wielopolski, Mateusz; Schuster, David I.; Fazio, Michael A.; Lee, Olivia P.; Haley, Christopher K.; Ortiz, Angy L.; Echegoyen, Luis; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Aromatic triazoles have been frequently used as π-conjugated linkers in intramolecular electron transfer processes. To gain a deeper understanding of the electron-mediating function of triazoles, we have synthesized a family of new triazole-based electron donor-acceptor conjugates. We have connected zinc(II)porphyrins and fullerenes through a central triazole moiety-(ZnP-Tri-C )-each with a single change in their connection through the linker. An extensive photophysical and computational investigation reveals that the electron transfer dynamics-charge separation and charge recombination-in the different ZnP-Tri-C conjugates reflect a significant influence of the connectivity at the triazole linker. Except for the m4m-ZnP-Tri-C 17, the conjugates exhibit through-bond photoinduced electron transfer with varying rate constants. Since the through-bond distance is nearly the same for all the synthesized ZnP-Tri-C conjugates, the variation in charge separation and charge recombination dynamics is mainly associated with the electronic properties of the conjugates, including orbital energies, electron affinity, and the energies of the excited states. The changes of the electronic couplings are, in turn, a consequence of the different connectivity patterns at the triazole moieties. © 2011 American Chemical Society.

Tunable Macrocyclic Polyparaphenylene Nanolassos via Copper-Free Click Chemistry - Schaub, Tobias A.; Zieleniewska, Anna; Kaur, Ramandeep; Minameyer, Martin; Yang, Wudi; Schüßlbauer, Christoph; Zhang, Lina; Freiberger, Markus; Zakharov, Lev N.; Drewello, Thomas; Dral, Pavlo O.; Guldi, Dirk Michael; et al. (Chemistry - A European Journal, 2023)
Deriving diverse compound libraries from a single substrate in high yields remains to be a challenge in cycloparaphenylene chemistry. In here, a strategy for the late-stage functionalization of shape-persistent alkyne-containing cycloparaphenylene has been explored using readily available azides. The copper-free [3+2]azide-alkyne cycloaddition provided high yields (>90 %) in a single reaction step. Systematic variation of the azides from electron-rich to -deficient shines light on how peripheral substitution influences the characteristics of the resulting adducts. We find that among the most affected properties are the molecular shape, the oxidation potential, excited-state features, and affinities towards different fullerenes. Joint experimental and theoretical results are presented including calculations with the state-of-the-art, artificial intelligence-enhanced quantum mechanical method 1 (AIQM1).
CRIS-Team Scopus Importer:2023-05-05
Keywords: artificial intelligence-enhanced quantum mechanical method; click reactions; excited state dynamics; fullerene complexation; strained macrocycles

Tuning and optimizing the intrinsic interactions between phthalocyaninebased PPV oligomers and single-wall carbon nanotubes toward n-type/p-type - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2011)
In this work we have developed a strategy to immobilize functional groups such as ZnPc onto the surface of SWNT without, however, the needs of covalent functionalization, using substituted PPVoligomers (1-4) with different electronic character. The complementary use of a series of microscopies and spectroscopies is central, especially to gather a comprehensive picture of the mutual interactions. Importantly, only 1, bearing electron-withdrawing CN substituents, interacts tightly with SWNT affording stable and finely dispersed SWNT suspensions. 2-4, on the other hand, fail to disperse SWNT in THF following our newly developed protocol. A likely rationale is the p-type character of PPVoligomers 2-4, which imposes repelling forces relative to p-type SWNT, while placing CN groups yields n-type PPV-oligomer 1 and, in turn, strengthens the π-π interactions with SWNT. Photoexcitation of SWNT/1 hybrids generates a metastable radical ion pair state, namely oxidized ZnPc and reduced SWNT. Quite remarkable is the ratio of charge separation to charge recombination, namely nearly 3 orders of magnitude, which is encouraging to fabricate photovoltaic cells that are based, for example, on different nanocarbons. © The Royal Society of Chemistry 2011.

Tuning Charge Transfer Energetics in Reaction Center Mimics via Th-Functionalization of Fullerenes - Guldi, Dirk Michael; Ohkubo, Kei; Hauke, Frank; Hauke, Frank; Hirsch, Andreas; Spänig, Fabian; Fukuzumi, Shunichi; Kovács, Christian (Journal of the American Chemical Society, 2009)
We have introduced an approach of mono- and hexakis-adducts of C-60 involving a T-h-symmetrical addition pattern, where up to 12 ferrocene or 10 ferrocene and one porphyrin units are linked flexibly to C-60 with the objective to systematically raise the energy of the radical ion pair state. A detailed electrochemical and photophysical investigation has shed light onto charge transfer events that depend largely on (i) the functionalization pattern of C-60, (ii) the donor strength of the donor, (iii) the excited-state energy of the predominant chromophore, and (iv) the solvent polarity. Considering (i)-(iv), the presence of the porphyrins is key to providing sufficient driving forces for affording spatially separated radical ion pair states. An ideal scenario, that is, testing ZnP-C-60-(Fc)(10) (19) in benzonitrile and DMF, allows storing nearly 1.7 eV in a nanosecond lived radical ion pair state. In this context, the flexible linkage, powering a through space charge transfer, prevents, however, stabilization of the radical ion pair state beyond nanoseconds.

Tuning conversion efficiency in metallo endohedral fullerene-based organic photovoltaic devices - Ross, Russel B.; Cardona, Claudia M.; Swain, Francis B.; Guldi, Dirk Michael; Sankaranarayanan, Shankara Gayathri; Van Keuren, Edward; Holloway, Brian C.; Drees, Martin (Advanced Functional Materials, 2009)
Here the influence that l-(3-hexoxycarbonyl)propyl-l-phenyl-[6,6]-Lu N@C, LuN@C-PCBH, a novel acceptor material, has on active layer morphology and the performance of organic photovoltaic (OPV) devices using this material is reported. Polymer/fullerene blend films with poly(3-hexylthiophene), P3HT, donor material and Lu N@C-PCBH acceptor material are studied using absorption spectroscopy, grazing incident X-ray diffraction and photocurrent spectra of photovoltaic devices. Due to a smaller molecular orbital offset the OPV devices built with LuN@C-PCBH display increased open circuit voltage over empty cage fullerene acceptors. The photovoltaic performance of these metallo endohedral fullerene blend films is found to be highly impacted by the fullerene loading. The results indicate that the optimized blend ratio in a P3HT matrix differs from a molecular equivalent of an optimized P3HT/ [6,6]-phenyl-C-butyric methyl ester, C-PCBM, active layer, and this is related to the physical differences of the C fullerene. The influence that active layer annealing has on the OPV performance is further evaluated. Through properly matching the film processing and the donor/acceptor ratio, devices with power conversion efficiency greater than 4% are demonstrated. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Tuning electron donor-acceptor hybrids by alkali metal complexation - Lederer, Marcus; Hahn, Uwe; Fernandez-Ariza, Javier; Trukhina, Olga; Salome Rodriguez-Morgade, M.; Dammann, Claudia; Drewello, Thomas; Torres, Tomas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
A zinc phthalocyanine endowed with four [18]-crown-6 moieties, ZnPcTeCr, has been prepared and self-assembled with either pyridyl-functionalized perylenebisimides (PDI-Py) or fullerenes (C60-Py) to afford a set of novel electron donor-acceptor hybrids. In the case of ZnPcTeCr, aggregation has been circumvented by the addition of potassium or rubidium ions to lead to the formation of monomers and cofacial dimers, respectively. From fluorescence titration experiments, which gave rise to mutual interactions between the electron donors and the acceptors in the excited state, the association constants of the respective ZnPcTeCr monomers and/or dimers with the corresponding electron acceptors were derived. Complementary transient-absorption experiments not only corroborated photoinduced electron transfer from ZnPcTeCr to either PDI-Py or C60-Py within the electron donor-acceptor hybrids, but also the unexpected photoinduced electron transfer within ZnPcTeCr dimers. In the electron donor-acceptor hybrids, the charge-separated-state lifetimes were elucidated to be close to 337 ps and 3.4 ns for the two PDI-Pys, whereas the longest lifetime for the photoactive system that contains C60-Py was calculated to be approximately 5.1 ns.
CRIS-Team Scopus Importer:2023-03-07
Keywords: alkali metals; charge transfer; crown ethers; donor-acceptor systems; fullerenes; perylenbisimides; phthalocyanines

Tuning electron transfer in supramolecular nano-architectures made of fullerenes and porphyrins - Wang, Bingzhe; Bauroth, Stefan; Saha, Avishek; Chen, Muqing; Clark, Timothy; Lu, Xing; Guldi, Dirk Michael (Nanoscale, 2019)
The current work focuses on self-assembled nano-architectures in which metal-ligand coordination between a zinc tetraphenyl-porphyrin (ZnP) and a zinc tetrakis(4-((1,3-dithiol-2-ylidene)methyl)phenyl)-porphyrin (ZnP-TDP), as electron donors, and functionalized fullerenes (C60) featuring different conjugated pyridine substituents as electron acceptors have been designed and investigated. Stoichiometric ratios and binding constants were derived from absorption and fluorescence measurements. Important insight into the free-energy change of charge separation and recombination was obtained from differential pulse voltammetry studies. Compelling evidence for energy transfer, charge separation and recombination was obtained from femtosecond and nanosecond transient-absorption measurements in a wide temperature range. Intramolecular energy transfer is found to take place from TDP to ZnP followed by intramolecular charge transfer from ZnP to C60. Semiempirical and density-functional theory calculations were used to help understand the excited-state deactivation mechanisms.
CRIS-Team Scopus Importer:2019-06-21

Tuning electron transfer through p-phenyleneethynylene molecular wires - Atienza, Carmen; Martín, Nazario; Wielopolski, Mateusz; Haworth, Naomi; Clark, Timothy; Guldi, Dirk Michael (Chemical Communications, 2006)
Weak wire-like behavior - with a damping factor (β) of 0.2 ± 0.05 Å - has been found in a series of C -wire- exTTF systems (i.e., p-phenyleneethynylene): these results contrast with previous observations involving p-phenylenevinylene systems. © The Royal Society of Chemistry 2006.

Tuning Interactions to Control Molecular Down Conversion in [2.2]Paracyclophane Bridged Oligo-Tetracenes - Rapp, Mario R.; Weiß, René; Wollny, Anna-Sophie; Guldi, Dirk Michael; Bettinger, Holger F. (Advanced Functional Materials, 2024)
In tetracene, the energies of the lowest singlet excited state and twice that of the lowest triplet excited state are similar, allowing both down-conversion (i.e., singlet fission, SF) and up-conversion (i.e., triplet-triplet annihilation up-conversion, TTA-UC) processes. Through-space and through-bond contributions to the inter-tetracene coupling in purposefully designed oligomers play a crucial role in determining which of the two processes dominates. In this work, the focus is exclusively on SF in newly synthesized oligo-tetracenes linked by conjugated [2.2]paracyclophane (PCP) building blocks. By choosing different PCP substitution patterns and by varying the degree of substitution the inter-tetracene couplings are addressed. An independent variable is connecting the tetracences to the PCP at different positions to alter the through-bond and through-space coupling of the resulting oligo-tetracenes. The novel oligo-tetracenes are investigated by means of steady-state and time-resolved absorption and fluorescence spectroscopies with respect to the initial events of SF, that is, the transformation of a singlet excited state into a correlated triplet pair state. Briefly, through-space couplings are profoundly weaker than through-bond couplings that enable the correlated triplet pair state formation. If interactions are through-space, correlated triplet pair state formation is turned off, while it is turned on if through-bond interactions are operative.
CRIS-Team Scopus Importer:2024-03-15
Keywords: acenes; cyclophanes; excited states; oligomers; photophysics; singlet fission

Tuning intramolecular electron and energy transfer processes in novel conjugates of La2@C80 and electron accepting subphthalocyanines - Feng, Lai; Rudolf, Marc; Trukhina, Olga; Slanina, Zdenek; Uhlik, Filip; Lu, Xing; Torres, Tomas; Guldi, Dirk Michael; Akasaka, Takeshi (Chemical Communications, 2015)
A series of two conjugates with La2@C80 and subphthalocyanine (SubPc) have been prepared and characterized by means of cyclic voltammetry, absorption, fluorescence, and femtosecond resolved transient absorption spectroscopy. The strong electron-donating character of La2@C80 is essential to power an intramolecular electron-transfer in the La2@C80-SubPc conjugates upon photoexcitation. This journal is
CRIS-Team Scopus Importer:2023-03-07

Tuning Intramolecular Förster Resonance Energy Transfer and Activating Intramolecular Singlet Fission - Lavarda, Giulia; Zirzlmeier, Johannes; Gruber, Marco; Rami, Parisa R.; Tykwinski, Rik; Torres, Tomas; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2018)
The synergy of panchromatic absorption throughout most of the visible range of the solar spectrum and intramolecular singlet fission (SF) has been realized in a series of conjugates featuring different light-harvesting subphthalocyanines (SubPcs) and an energy accepting pentacene dimer (Pnc2). At the focal point was a modular SubPc approach, which was based on decorating the SubPc core with different peripheral substituents to tailor and fine-tune their optical properties. Transient absorption measurements assisted in corroborating that the SubPcs act as energy-transfer antennas by means of unidirectional and quantitative intramolecular Förster resonance energy transfer (FRET) to the Pnc2, where an intramolecular SF affords triplet quantum yields reaching unity.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Förster resonance energy transfer; intramolecular singlet fission; photochemistry; transient absorption spectroscopy

Tuning of photocatalytic activity by creating a tridentate coordination sphere for palladium - Pfeffer, M. G.; Zedler, L.; Kupfer, Stephan; Paul, M.; Schwalbe, M.; Peuntinger, Katrin; Guldi, Dirk Michael; Guthmuller, J.; Popp, Jürgen; Gräfe, Stefanie; Dietzek, B.; Rau, S. (Dalton Transactions, 2014)
The synthesis and characterisation of an asymmetric potential bridging ligand bmptpphz (bmptpphz = 2,17-bis(4-methoxyphenyl)tetrapyrido[3,2-a:2′, 3′-c:3′′,2′′-h:2′′′, 3′′′-j] phenazine) is presented. This ligand contains a 1,10-phenanthroline (phen) and a 2,9-disubstituted phen sphere and possesses a strong absorbance in the visible. Facile coordination of the phen sphere to a Ru(tbbpy)2 core leads to Ru(bmptpphz) ([(tbbpy) 2Ru(bmptpphz)](PF6)2; tbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine). UV-vis, emission, resonance Raman and theoretical investigations show that this complex possesses all properties associated with a Ru(tpphz) ([(tbbpy)2Ru(tpphz)](PF 6)2; tpphz = tetrapyrido[3,2-a:2′,3′-c: 3′′,2′′-h:2′′′,3′′′- j] phenazine) moiety and that the ligand based absorbances in the vis-part also populate an MLCT like state. The coordination of a Pd-core in the new 2,9-disubstituted phen sphere is possible, leading to a cyclometallation. The tridentate complexation leads to changes in the UV-vis and emission behaviour. Furthermore, the stability of the Pd-coordination is significantly enhanced if compared to the unsubstituted Ru(tpphz). Ru(bmptpphz)PdCl proved to be an active photocatalyst for H2 evolution, albeit with lower activity than the mother compound Ru(tpphz)PdCl2. This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-07

Tuning pentacene based dye-sensitized solar cells - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Tykwinski, Rik; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2018)

Tuning the Absorption, Fluorescence, Intramolecular Charge Transfer, and Intersystem Crossing in Spiro[fluorene]acridinone - Bo, Yifan; Zhang, He; Li, Yue; Reva, Yana; Xie, Linghai; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
In this work, we prepared a series of electron donor-acceptor systems based on spiro[fluorene-9,7’-dibenzo[c,h]acridine]-5’-one (SFDBAO). Our SFDBAOs consist of orthogonally positioned fluorenes and aromatic ketones. By fine-tuning the substitution of electron-donating pyrenes, the complex interplay among different excited-state decay channels and the overall impact of solvents on these decay channels were uncovered. Placing pyrene, for example, at the aromatic ketones resulted in a profound solvatochromism in the form of a bright charge-transfer (CT) emission spanning from yellow to red-NIR. In contrast, a dark non-emissive CT was noted upon pyrene substitution at the fluorenes. In apolar solvents, efficient triplet-excited state generation was observed for all SFDBAOs. Either charge transfer was concluded to mediate the intersystem crossing (ISC) in the case of pyrene substitution or the El-Sayed rule was applicable when lacking pyrene substitution as in the case of SFABAO. In polar solvents, charge separation is the sole decay upon pyrene substitution. Moreover, competition between ISC and CT lowered the triplet-excited state generation in SFDBAO.
CRIS-Team Scopus Importer:2024-03-22
Keywords: charge transfer; intersystem crossing; ketones; spiro-conjugation; triplet sensitizers

Tuning the Carbon Nanotube Selectivity: Optimizing Reduction Potentials and Distortion Angles in Perylenediimides - Münich, Peter Wilhelm; Schierl, Christoph; Dirian, Konstantin; Volland, Michel; Bauroth, Stefan; Wibmer, Leonie; Syrgiannis, Zois; Clark, Timothy; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2018)
Different water-soluble perylenediimides (PDIs) have been used to individualize and stabilize single-walled carbon nanotubes (SWCNTs) in aqueous media. A key feature of the PDIs is that they can be substituted at the bay positions via the addition of two and/or four bromines. This enables control over structural and electronic PDI characteristics, which prompted us to conduct comparative assays with focus on SWCNTs' chirality and charge transfer. Electrochemical, microscopic, and spectroscopic experiments were used to investigate the SWCNT chiral selectivity of PDIs, on the one hand, and charge-transfer reactions between SWCNTs and PDIs, on the other hand.

Tuning the Electron Acceptor in Phthalocyanine-Based Electron Donor-Acceptor Conjugates - Sekita, Michael; Jimenez, Angel J.; Luisa Marcos, M.; Caballero, Esmeralda; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2015)
Zinc phthalocyanines (ZnPc) have been attached to the peri-position of a perylenemonoimide (PMI) and a perylenemonoanhydride (PMA), affording electron donor-acceptor conjugates 1 and 2, respectively. In addition, a perylene-monoimide-monoanhydride (PMIMA) has been connected to a ZnPc through its imido position to yield the ZnPc-PMIMA conjugate 10. The three conjugates have been studied for photoinduced electron transfer. For ZnPc-PMIMA 10, electron transfer occurs upon both ZnPc and PMIMA excitation, giving rise to a long-lived (340 ps) charge-separated state. For ZnPc-PMI 1 and ZnPc-PMA 2, stabilization of the radical ion pair states by using polar media is necessary. In THF, photoexcitation of either ZnPc or PMI/PMA produces charge-separated states with lifetimes of 375 and 163 ps, respectively.
CRIS-Team Scopus Importer:2023-03-07
Keywords: anhydrides; electron transfer; imides; perylene; phthalocyanine

Tuning the ground-state and excited-state interchromophore interactions in porphyrin-fullerene π-stacks - Chukharev, Vladimir; Tkachenko, Nikolai; Efimov, Alexander; Guldi, Dirk Michael; Hirsch, Andreas; Scheloske, Michael; Lemmetyinen, Helge (Journal of Physical Chemistry B, 2004)
Recently synthesized porphyrin-fullerene dyads with two separate linkers form a nearly symmetric complex with π-stack sandwich-like structure. The interchromophore interactions of such complexes can be fine-tuned by varying the linker lengths, which opens an opportunity to control physical and chemical properties of the dyads. Absorption spectroscopy emerged as a convenient means to register the interchromophore interactions: the spectra of the chromophores ground-state absorptions show appreciable perturbations and, more importantly, an additional absorption feature is discernible in the near-infrared region. Similarly, the emission spectra have a character typical for intramolecular exciplex. These new spectral features (i.e., absorption and emission) were attributed to a new electronic state, namely, an intramolecular preformed exciplex, featuring a common molecular orbital with a partial charge transfer (CT) character. From the mechanistic point of view, it is important that the preformed exciplex preceded the actual nonemitting charge separated (CS) state. The quantitative analysis of the CT absorption and the exciplex emission bands within the framework of the Marcus electron transfer (ET) theory allowed us to estimate the energy of the exciplex, ΔG°, the solvent or outer-sphere reorganization energy, λ the internal reorganization energy, λ , the energy of the vibrational mode, E , and the electronic coupling matrix element, V. Variation in the linker lengths shows that mainly the electronic coupling is affected by this structural modification, leaving the other parameters essentially unchanged. The strongest coupling, V = 450 cm (0.056 eV), was observed for the dioxyethyl type of linkers, whereas in the shorter, oxymethyl type, and longer, dioxypropyl type, dyads the couplings were much weaker (190 and 270 cm , respectively). Photodynamics of the dyads was studied in the femto-and picosecond time domains, using the emission up-conversion and absorption pump-probe techniques.

Tuning the reorganization energy of electron transfer in supramolecular ensembles - metalloporphyrin, oligophenylenevinylenes, and fullerene - and the impact on electron transfer kinetics - Stangel, Christina; Schubert, Christina; Kuhri, Susanne; Rotas, Georgios; Margraf, Johannes; Regulska, Elzbieta; Clark, Timothy; Torres, Tomas; Tagmatarchis, Nikos; Coutsolelos, Athanassios G.; Guldi, Dirk Michael (Nanoscale, 2015)
Oligo(p-phenylenevinylene) (oPPV) wires of various lengths featuring pyridyls at one terminal and C-60 moieties at the other, have been used as molecular building blocks in combination with porphyrins to construct a novel class of electron donor-acceptor architectures. These architectures, which are based on non-covalent, directional interactions between the zinc centers of the porphyrins and the pyridyls, have been characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. Complementary physico-chemical assays focused on the interactions between electron donors and acceptors in the ground and excited states. No appreciable electron interactions were noted in the ground state, which was being probed by electrochemistry, absorption spectroscopy, etc.; the electron acceptors are sufficiently decoupled from the electron donors. In the excited state, a different picture evolved. In particular, steady-state and time-resolved fluorescence and transient absorption measurements revealed substantial electron donor-acceptor interactions. These led, upon photoexcitation of the porphyrins, to tunable intramolecular electron-transfer processes, that is, the oxidation of porphyrin and the reduction of C-60. In this regard, the largest impact stems from a rather strong distance dependence of the total reorganization energy in stark contrast to the distance independence seen for covalently linked conjugates.

Tuning the stability of graphene layers by phthalocyanine-based oppv oligomers towards photo- and redoxactive materials - Brinkhaus, Linda; Katsukis, Georgios; Malig, Jenny; Costa, Ruben Dario; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Small, 2013)
In contrast to pristine zinc phthalocyanine (1), zinc phthalocyanine based oPPV-oligomers (2-4) of different chain lengths interact tightly and reversibly with graphite, affording stable and finely dispersed suspensions of mono- to few-layer graphene - nanographene (NG) - that are photoactive. The p-type character of the oPPV backbones and the increasing length of the oPPV backbones facilitate the overall π-π interactions with the graphene layers. In NG/2, NG/3, and NG/4 hybrids, strong electronic coupling between the individual components gives rise to charge transfer from the photoexcited zinc phthalocyanines to NG to form hundreds of picoseconds lived charge transfer states. The resulting features, namely photo- and redoxactivity, serve as incentives to construct and to test novel solar cells. Solar cells made out of NG/4 feature stable and repeatable photocurrent generation during several 'on-off' cycles of illumination with monochromatic IPCE values of around 1%. Photoactive graphene hybrids: p-type oligo-para-phenylene vinylene zinc phthalocyanine oligomers exfoliate graphite, interact electronically with wet-chemically exfoliated graphite via charge transfer, and produce photocurrent upon illumination. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Two-Photon Absorption in Pentacene Dimers: The Importance of the Spacer Using Upconversion as an Indirect Route to Singlet Fission - Garoni, Eleonora; Zirzlmeier, Johannes; Basel, Bettina; Hetzer, Constantin; Kamada, Kenji; Guldi, Dirk Michael; Tykwinski, Rik (Journal of the American Chemical Society, 2017)
In this proof of concept study, we show that intramolecular singlet fission (iSF) can be initiated from a singlet excited state accessed by two-photon absorption, rather than through a traditional route of direct one-photon excitation (OPE). Thus, iSF in pentacene dimers 2 and 3 is enabled through NIR irradiation at 775 nm, a wavelength where neither dimer exhibits linear absorption of light. The adamantyl and meta-phenylene spacers 2 and 3, respectively, are designed to feature superimposable geometries, which establishes that the electronic coupling between the two pentacenes is the significant structural feature that dictates iSF efficiency.
CRIS-Team Scopus Importer:2022-04-14

Two Rings Around One Ball: Stability and Charge Localization of [1 : 1] and [2 : 1] Complex Ions of [10]CPP and C60/70[*] - Freiberger, Markus; Minameyer, Martin; Solymosi, Iris; Frühwald, Stefan; Krug, Marcel; Xu, Youzhi; Hirsch, Andreas; Clark, Timothy; Guldi, Dirk Michael; von Delius, Max; Amsharov, Konstantin; Görling, Andreas; et al. (Chemistry - A European Journal, 2022)
We investigate the gas-phase chemistry of noncovalent complexes of [10]cycloparaphenylene ([10]CPP) with C60 and C70 by means of atmospheric pressure photoionization and electrospray ionization mass spectrometry. The literature-known [1 : 1] complexes, namely [10]CPP⊃C60 and [10]CPP⊃C70, are observed as radical cations and anions. Their stability and charge distribution are studied using energy-resolved collision-induced dissociation (ER-CID). These measurements reveal that complexes with a C70 core exhibit a greater stability and, on the other hand, that the radical cations are more stable than the respective radical anions. Regarding the charge distribution, in anionic complexes charges are exclusively located on C60 or C70, while the charges reside on [10]CPP in the case of cationic complexes. [2 : 1] complexes of the ([10]CPP2⊃C60/70)+⋅/−⋅ type are observed for the first time as isolated solitary gas-phase species. Here, C60-based [2 : 1] complexes are less stable than the respective C70 analogues. By virtue of the high stability of cationic [1 : 1] complexes, [2 : 1] complexes show a strongly reduced stability of the radical cations. DFT analyses of the minimum geometries as well as molecular dynamics calculations support the experimental data. Furthermore, our novel gas-phase [2 : 1] complexes are also found in 1,2-dichlorobenzene. Insights into the thermodynamic parameters of the binding process as well as the species distribution are derived from isothermal titration calorimetry (ITC) measurements.
CRIS-Team Scopus Importer:2023-03-07
Keywords: cycloparaphenylenes; fullerenes; host-guest systems; polycyclic aromatic hydrocarbons; supramolecular chemistry

Two similar near-infrared (IR) absorbing benzannulated AZA-bodipy dyes as near-ir sensitizers for ternary solar cells - Min, Jie; Ameri, Tayebeh; Gresser, Roland; Lorenz-Rothe, Melanie; Baran, Derya; Troeger, Anna; Sgobba, Vito; Leo, Karl; Riede, Moritz; Guldi, Dirk Michael; Brabec, Christoph (ACS Applied Materials and Interfaces, 2013)
Ternary composite inverted organic solar cells based on poly(3-hexylthiophen-2,5-diyl) (P3HT) and phenyl-C-butyric acid methyl ester (PCBM) blended with two different near-infrared absorbing benzannulated aza-BODIPY dyes, difluoro-bora-bis-(1-phenyl-indoyl)-azamethine (1) or difluoro-bora-bis-(1-(5-methylthiophen)-indoyl)-azamethine (2), were constructed and characterized. The amount of these two aza-BODIPY dyes, within the P3HT and PCBM matrix, was systematically varied, and the characteristics of the respective devices were recorded. Although the addition of both aza-BODIPY dyes enhanced the absorption of the blends, only the addition of 1 improved the overall power conversion efficiency (PCE) in the near-infrared (IR) region. The present work paves the way for the integration of near-infrared absorbing aza-BODIPY derivatives as sensitizers in ternary composite solar cells. © 2013 American Chemical Society.

Ultrafast Charge Transfer between Light Absorber and Co3O4 Water Oxidation Catalyst across Molecular Wires Embedded in Silica Membrane - Edri, Eran; Cooper, Jason K.; Sharp, Ian D.; Guldi, Dirk Michael; Frei, Heinz (Journal of the American Chemical Society, 2017)
The mechanism of visible light-induced hole transfer from a molecular light absorber, in the form of a free-base porphyrin, coupled to a Co3O4 nanoparticle catalyst for water oxidation by a molecular wire (p-oligo(phenylenevinylene) featuring three aryl units) is investigated by transient absorption spectroscopy. The wires are covalently anchored on the Co3O4 surface and embedded in a dense, yet ultrathin (2 nm), silica layer that separates light absorber and catalyst. The porphyrin is electrostatically adsorbed on the silica surface, and aqueous colloidal solutions of the core-shell particles are used for transient optical measurements. Pulsed optical excitation of the porphyrin results in rapid injection of the photogenerated hole onto the molecular wire and concurrent formation of reduced light absorber in less than 1 picosecond (ps). Ultrafast charge separation was monitored by transient absorption of the wire radical cation, which is given by bands in the 500 to 600 nm region and at 1130 nm, while formation of reduced porphyrin was characterized by absorption at 700 nm. Forward transfer of the hole to Co3O4 catalyst proceeds in 255 ± 23 ps. Ultrafast transfer of positive charge from the molecular assembly to a metal oxide nanoparticle catalyst for water oxidation is unprecedented. Holes on Co3O4 recombined with electrons of the reduced sensitizer with biphasic kinetics on a much longer time scale of ten to several hundred nanoseconds. The unusually efficient hole transfer coupling of a molecular light absorber with an Earth-abundant metal oxide catalyst by silica-embedded p-oligo(phenylenevinylene) offers an approach for integrated artificial photosystems featuring product separation on the nanoscale.
EAM Import::2019-03-13

Ultrafast excitation energy transfer in vinylpyridine terminated silicon quantum dots - Sommer, Anja; Cimpean, Carla Ramona; Kunz, Michael; Oelsner, Christian; Kupka, Hans J.; Kryschi, Carola (Journal of Physical Chemistry C, 2011)
Water-soluble 2- and 4-vinylpyridine terminated silicon quantum dots (SiQDs) with sizes between 2 and 3 nm were obtained by HF etching of oxidized SiQDs and subsequently passivating with vinylpyridine ligands via thermal hydrosilylation. The functionalized SiQDs emit photoluminescence in the blue-green spectrum with quantum yields around 30%. The photoluminescence is ascribed to radiative recombination of excitons confined to the SiQD core. Indication of efficient electronic interactions between excited ligand states and SiQD conduction band states has been achieved by real-time monitoring excitation relaxation dynamics on the subpicosecond time scale using time-resolved laser spectroscopy techniques. The observed ultrafast excitation relaxation dynamics involving decay and rise dynamics faster than 1 ps were ascribed to electronic excitation energy transfer from an initially photoexcited ligand state to SiQD conduction band states. These results were analyzed by performing a state population analysis on the basis of electron exchange interactions. © 2011 American Chemical Society.

Ultrafast exciton dynamics after Soret- or Q-band excitation of a directly β,β′-linked bisporphyrin - Kullmann, Martin; Hipke, Arthur; Nuernberger, Patrick; Bruhn, Torsten; Goetz, Daniel C. G.; Sekita, Michael; Guldi, Dirk Michael; Bringmann, Gerhard; Brixner, Tobias (Physical Chemistry Chemical Physics, 2012)
We report on a comprehensive transient absorption study with β,β′-linked bis[tetraphenylporphyrinato-zinc(ii)] and its corresponding monomer, covering the ultrafast dynamics from femtoseconds up to several microseconds. By exciting these porphyrins either to their first (S ) or second (S ) electronically excited states and by probing the subsequent dynamics, a multitude of reaction pathways have been identified. In the spectral region associated with the ground-state recovery of the bisporphyrin, transient absorption changes occur within the first few picoseconds, which are ascribable to excitonic interaction both in the S (fs time-domain) and in the S (ps time-domain) state. This is substantiated by complementary experiments with the monomeric porphyrin, in which the S state exhibits a longer lifetime. In contrast to the picosecond dynamics the bisporphyrin and the monomer behave similarly on the nanosecond time-scale, that is nearly all excited molecules eventually reach a long-lived triplet excited state. © 2012 the Owner Societies.

Ultrafast exciton relaxation dynamics in silicon quantum dots - Cimpean, Carla Ramona; Groenewegen, Vincent; Kuntermann, Volker; Sommer, Anja; Kryschi, Carola (Laser & Photonics Reviews, 2009)
The photoluminescence properties of silicon quantum dots may be tailored by surface states via efficient coupling to resonant bulk states. Therefore various wet-chemistry procedures were developed to fabricate silicon quantum dots with adjustable sizes and surface properties. While the energy gap of the Si core is tuned by the size, resonant electronic surface states may be attained by varying the structure and chemical composition of the grafting. The strength of electronic couplings between surface and bulk states determines the timescale of both photo-induced electron transfer from excited surface states to conduction band states and capture of conduction band electrons by surface states. Whereas the origin of photoluminescence and therewith the quantum dot size distribution may be elucidated by stationary luminescence spectroscopy, ultrafast optical spectroscopy techniques, for instance the femtosecond transient absorption spectroscopy, allow to monitor photo-induced electron transfer between surface and bulk states and carrier trapping on the subpicosecond timescale. © 2009 by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Silicon quantum dots; photoluminescence; thermal hydrosilylation; femtosecond spectroscopy; photo-induced electron transfe

Ultrafast photoinduced processes in subphthalocyanine electron donor-acceptor conjugates linked by a single B-N bond∥ - Nieto, Carlos Romero; Guilleme, Julia; Fernandez-Ariza, Javier; Salome Rodriguez-Morgade, M.; Gonzalez-Rodriguez, David; Torres, Tomas; Guldi, Dirk Michael (Organic Letters, 2012)
We have prepared two different subphthalocyanine conjugates by linking these macrocycles either to an electron-accepting perylene diimide or to an electron-donating phenothiazine through a single B-N covalent bond. The short spacing between the two active building blocks results in ultrafast photoinduced electron-transfer reactions. © 2012 American Chemical Society.

Ultrasound-induced transformation of fluorescent organic nanoparticles from a molecular rotor into rhomboidal nanocrystals with enhanced emission - König, Matthias; Torres, Tomas; Barone, Vincenzo; Brancato, Giuseppe; Guldi, Dirk Michael; Bottari, Giovanni (Chemical Communications, 2014)
Fluorescent organic nanoparticles (FONs) based on aggregation-induced emission (AIE) are receiving increasing attention owing to their simple preparation, enhanced optical properties, and a wide range of applications. Therefore, finding simple methods to tune the structural and emissive properties of FONs is highly desirable. In this context, we discuss the preparation of highly emissive, amorphous AIE spherical nanoparticles based on a structurally-simple molecular rotor and their sonochemical transformation into rhomboidal nanocrystals. Interestingly, the ultrasound-induced modification of the morphology is accompanied by a remarkable enhancement in the stability and emission of the resulting nanocrystals. Detailed characterization of both spherical and rhomboidal nanoparticles was carried out by means of several microscopic, crystallographic, and spectroscopic techniques as well as quantum mechanical calculations. In a nutshell, this work provides a unique example of the ultrasound-induced switching of morphology, stability, and emission in FONs. © 2014 Partner Organisations.
CRIS-Team Scopus Importer:2023-03-07

Ultrastrong Materials, Nanostructured - Kotov, N. A.; Mamedov, A. A.; Guldi, Dirk Michael; Tang, Z.; Prato, Maurizio; Wicksted, J.; Hirsch, Andreas (Dekker Encyclopedia of Nanoscience and Nanotechnology (3rd Edition), 2014)

Unconventional Photocatalysis in Conductive Polymers: Reversible Modulation of PEDOT:PSS Conductivity by Long-Lived Poly(Heptazine Imide) Radicals - Savateev, Aleksandr; Markushyna, Yevheniia; Schüßlbauer, Christoph; Ullrich, Tobias; Guldi, Dirk Michael; Antonietti, Markus (Angewandte Chemie International Edition, 2021)
In photocatalysis, small organic molecules are converted into desired products using light responsive materials, electromagnetic radiation, and electron mediators. Substitution of low molecular weight reagents with redox active functional materials may increase the utility of photocatalysis beyond organic synthesis and environmental applications. Guided by the general principles of photocatalysis, we design hybrid nanocomposites composed of n-type semiconducting potassium poly(heptazine imide) (K-PHI), and p-type conducting poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as the redox active substrate. Electrical conductivity of the hybrid nanocomposite, possessing optimal K-PHI content, is reversibly modulated combining a series of external stimuli ranging from visible light under inert conditions and to dark conditions under an O-2 atmosphere. Using a conductive polymer as the redox active substrate allows study of the photocatalytic processes mediated by semiconducting photocatalysts through electrical conductivity measurements.
CRIS-Team WoS Importer:2021-03-19

Unconventional singlet fission materials - Ullrich, Tobias; Munz, Dominik; Guldi, Dirk Michael (Chemical Society Reviews, 2021)
Singlet fission (SF) is a photophysical downconversion pathway, in which a singlet excitation transforms into two triplet excited states. As such, it constitutes an exciton multiplication generation process, which is currently at the focal point for future integration into solar energy conversion devices. Beyond this, various other exciting applications were proposed, including quantum cryptography or organic light emitting diodes. Also, the mechanistic understanding evolved rapidly during the last year. Unfortunately, the number of suitable SF-chromophores is still limited. This is per se problematic, considering the wide range of envisaged applicability. With that in mind, we emphasize uncommon SF-scaffolds and outline requirements as well as strategies to expand the chromophore pool of SF-materials. This journal is
CRIS-Team Scopus Importer:2021-04-02

Understanding and Controlling Short- A nd Long-Range Electron/Charge-Transfer Processes in Electron Donor-Acceptor Conjugates - Kaur, Ramandeep; Possanza, Fabio; Limosani, Francesca; Bauroth, Stefan; Zanoni, Robertino; Clark, Timothy; Arrigoni, Giorgio; Tagliatesta, Pietro; Guldi, Dirk Michael (Journal of the American Chemical Society, 2020)
We probed a series of multicomponent electron donor2-donor1-acceptor1 conjugates both experimentally and computationally. The conjugates are based on the light harvester and primary electron-donor zinc-porphyrin (ZnP, donor1) to whose β positions a secondary electron-donor ferrocene (Fc, donor2) and the primary electron-acceptor C60-fullerene (C60, acceptor1) are attached. Linking all of them via p-phenylene-acetylene/acetylene bridges of different lengths to gain full control over shuttling electrons and holes between C60, ZnP, and Fc is novel. Different charge-separation, charge-transfer, and charge-recombination routes have been demonstrated, both by transient absorption spectroscopy measurements on the femto, pico-, nano-, and microsecond time scales and by multiwavelength and target analyses. The molecular wire-like nature of the p-phenylene-acetylene bridges as a function of C60-ZnP and ZnP-Fc distances is decisive in the context of generating distant and long-lived C60 â¢--ZnP-Fcâ¢+ charge-separated states. For the first time, we confirm the presence of two adjacent charge-transfer states, a C60-ZnPâ¢--Fcâ¢+ intermediate in addition to C60 â¢--ZnPâ¢+-Fc, en route to the distant C60 â¢--ZnP-Fcâ¢+ charge-separated state. Our studies demonstrate how the interplay of changes in the reorganization energy and the damping factor of the molecular bridges, in addition to variation in the solvent polarity, affect the outcome of the charge-transfer and corresponding rate constants. The different regions of the Marcus parabola are highly relevant in this matter: The charge recombination of, for example, the adjacent C60 â¢--ZnPâ¢+-Fc charge-separated state is located in the inverted region, while that of the distant C60 â¢--ZnP-Fcâ¢+ charge-separated state lies in the normal region. Here, the larger reorganization energy of Fc relative to ZnP makes the difference.
CRIS-Team Scopus Importer:2020-05-08

Understanding the Role of Surface Charge in Cellular Uptake and X‑ray-Induced ROS Enhancing of Au−Fe3O4 Nanoheterodimers - Klein, Stefanie; Stiegler, Lisa; Harreiß, Christina; Distel, Luitpold; Neuhuber, Winfried; Spiecker, Erdmann; Hirsch, Andreas; Kryschi, Carola (ACS Applied Bio Materials, 2018)
Au−Fe3O4 nanoheterodimers were obtained by thermally decomposing iron oleate on presynthesized gold nanoparticles. Water solubility as well as surface charges were achieved by encapsulating the initially hydrophobic Au−Fe3O4 nanoheterodimers in a self-assembled bilayer shell formed either by 1-octadecylpyridinium, providing positive surface charges, or by 4-dodecylbenzenesulfonate, yielding a negatively charged surface. The surface charge and surface architecture were shown to control both the cellular entry and the intracellular trafficking of the Au−Fe3O4 nanoheterodimers. The positively charged (1-octylpyridinium-terminated) Au−Fe3O4 nanoheterodimers were internalized by both breast cancer cells (MCF-7) and epithelial cells (MCF-10 A), wherein they were electrostatically bound at the negatively charged membranes of the cell organelles and, in particular, adsorbed onto the mitochondrial membrane. The treatment of MCF-7 and MCF-10 cells with a fractional X-radiation dose of 1 Gy resulted into a large increase of superoxide production, which arose from the Au−Fe3O4 nanoheterodimer-induced mitochondrial depolarization. In contrast, the negatively charged (4-dodecylbenzenesulfonateterminated) Au−Fe3O4 nanoheterodimers preferentially invaded the cancerous MCF-7 cells by direct permeation. X-ray treatment of MCF-7 cells, loaded with anionic Au−Fe3O4 nanoheterodimers, yielded the increase of both hydroxyl radical and cytoplasmic superoxide formation. The X-radiation-induced activation of the Fe3O4 surfaces, consisting of Fe2+ and Fe3+ cations, triggered the catalysis of the hydroxyl radical production, whereas superoxide formation presumably occurred through X-rayinduced photoelectron emission near the Au surface. Since hydroxyl radicals are highly cytotoxic and the negatively charged Au−Fe3O4 NHDs spare the healthy MCF-10A cells, these Au−Fe3O4 nanoheterodimers exhibit a higher potential for radiation therapy than the positively charged Au−Fe3O4 nanoheterodimers. Encouraging results from the clonogenic cell survival assay and DMF calculations corroborate the excellent performance of the anionic Au−Fe3O4 nanoheterodimers as an X-ray dosage enhance
Keywords: Au−Fe3O4 nanoheterodimers; self-assembled bilayer; surface charge; reactive oxygen species; radiation therapy

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy

Unexpected change in charge transfer behavior in a cobalt(II) porphyrin-fullerene conjugate that stabilizes radical ion pair states - Sutton, Liam; Scheloske, Michael; Pirner, Kristina; Hirsch, Andreas; Guldi, Dirk Michael; Gisselbrecht, Jean-Paul (Journal of the American Chemical Society, 2004)
Two cobalt(II) porphyrin-C malonate-linked conjugates, the mono-connected Co1 and the bis-connected trans-2 isomer Co3, have been synthesized for the first time either by direct cyclopropanation with the precursor malonate Co4 or by metalation of the bisadduct H3. For the investigation of the interaction between the porphyrin donor and fullerene acceptor within these dyads, electrochemical and photophysical investigations have been carried out. Compared to Zn3 and trans-2 bisadduct 7, the first reduction of the fullerene moiety within Co3 becomes easier (40 mV in dichloromethane and 20 mV in benzonitrile), indicating significant interactions between the π-system of the fullerene and the d-orbitals of the central Co atom. Compared to the Co complexes 9, Co4, and Co1, the first oxidation of Co3 is considerably shifted to more positive potentials, if benzonitrile instead of dichloromethane is used as solvent. At the same time, the oxidation is no longer centered on the Co(II) center but on the porphyrin macrocycle, as corroborated by spectroelectrochemistry. A similar solvent dependence was observed in transient absorption spectroscopic measurements. In toluene, benzonitrile and anisole photoinduced electron transfer within Co3 leads to the formation of a charge-separated state Co(II)P-C with a lifetime of 560 ± 20 ns in benzonitrile, whereas in other solvents such as THF, nitrobenzene, ortho-diclorobenzene, and tert-butylbenzene the formation of a Co(III)P-C as transient was detected, which is, however, short-lived (860 ± 40 ps in THF) and exhibits charge recombination dynamics that are in the Marcus inverted region. Particularly important is the fact that the electronic coupling (V) in Co(III)P-C is 18 cm substantially smaller than the V value of 313 cm in ZnP-C60.

Unified model for singlet fission within a non-conjugated covalent pentacene dimer - Basel, Bettina; Zirzlmeier, Johannes; Hetzer, Constantin; Phelan, Brian T.; Krzyaniak, Matthew D.; Seelam, Rajagopala Reddy; Brana Coto, Pedro; Horwitz, Noah E.; Young, Ryan M.; White, Fraser J.; Hampel, Frank; Clark, Timothy; et al. (Nature Communications, 2017)
When molecular dimers, crystalline films or molecular aggregates absorb a photon to produce a singlet exciton, spin-allowed singlet fission may produce two triplet excitons that can be used to generate two electron-hole pairs, leading to a predicted similar to 50% enhancement in maximum solar cell performance. The singlet fission mechanism is still not well understood. Here we report on the use of time-resolved optical and electron paramagnetic resonance spectroscopy to probe singlet fission in a pentacene dimer linked by a non-conjugated spacer. We observe the key intermediates in the singlet fission process, including the formation and decay of a quintet state that precedes formation of the pentacene triplet excitons. Using these combined data, we develop a single kinetic model that describes the data over seven temporal orders of magnitude both at room and cryogenic temperatures.

Unique multiphthalocyanine coordination systems: vibrationally hot excited states and charge transfer states that power high energy triplet charge separated states - Joseph, Jan; Lourenco, Leandro M. O.; Tome, Joao P. C.; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2022)
Controlling the molecular architecture of well-organized organic building blocks and linking their functionalities with the impact of solar-light converting systems constitutes a grand challenge in materials science. Strong absorption cross-sections across the visible range of the solar spectrum as well as a finely balanced energy- and redox-gradient are all important features that pave the way for either funneling excited state energy or transducing charges. In light of this, we used thiopyridyl-phthalocyanines (PcSPy) and ruthenium (tert-butyl)-phthalocyanines (RuPc) as versatile building blocks and demonstrated the realization of a family of multi-functional PcSPy-RuPc 1-4 by means of axial coordination. Sizeable electronic couplings between the electron donors and acceptors in PcSPy-RuPc 1-4 govern ground-state as well as excited-state reactivity. Time-resolved techniques, in general, and fluorescence and transient absorption spectroscopy, in particular, helped to corroborate a rapid charge separation next to a slow charge recombination. Key to these charge transfer characteristics are higher lying, vibrationally hot states of the singlet excited states in parallel with a charge transfer state and the presence of several heavy atom effects that are provided by ruthenium and sulfur. As such, our advanced investigations confirm that rapid charge separation evolves from both higher lying, vibrationally hot states as well as from a charge transfer state, populating charge separated states, whose energies exceed those of the singlet excited states. Charge recombination involves triplet rather than singlet charge separated states, which delays the charge recombination by one order of magnitude.
CRIS-Team WoS Importer:2022-09-16

Unraveling the Charge-Carrier Dynamics from the Femtosecond to the Microsecond Time Scale in Double-Cable Polymer-Based Single-Component Organic Solar Cells - He, Yakun; Wang, Bingzhe; Lüer, Larry; Feng, Guitao; Osvet, Andres; Heumüller, Thomas; Liu, Chao; Li, Weiwei; Guldi, Dirk Michael; Li, Ning; Brabec, Christoph (Advanced Energy Materials, 2021)
Single-component organic solar cells (SCOSCs) have witnessed great improvement during the last few years with the champion efficiency jumping from the previous 2-3% to currently 6-11% for the representative material classes. However, the photophysics in many of these materials has not been sufficiently investigated, lacking essential information regarding charge-carrier dynamics as a function of microstructure, which is highly demanded for a better understanding and potential guidance for further improvements. In this work, for the first time, the charge-carrier dynamics of a representative double-cable polymer, which achieves efficiencies of over 6% as an active layer in SCOSCs, is investigated across seven orders of magnitude in time scale, from fs-ps charge generation to ns-mu s charge recombination processes. Specific emphasis is placed on understanding the impact of thermal post-treatment on the charge dissociation and recombination dynamics. Annealing the photoactive layer at 230 degrees C results in the highest photovoltaic performance because of efficient charge generation in parallel to suppressed recombination. This work intends to present a complete picture of the charge-carrier dynamics in SCOSCs using the representative double-cable polymer PBDBPBI-Cl.
CRIS-Team WoS Importer:2021-12-31

Unraveling the peculiar modus operandi of a new class of solvatochromic fluorescent molecular rotors by spectroscopic and quantum mechanical methods - König, Matthias; Bottari, Giovanni; Brancato, Giuseppe; Barone, Vincenzo; Guldi, Dirk Michael; Torres, Tomas (Chemical Science, 2013)
A prototype for a new class of fluorescent molecular rotors (FMRs), namely 4-(diphenylamino)phthalonitrile (DPAP), was synthesized and its sensitivity towards solvent polarity and viscosity probed using photophysical and computational methods. DPAP is characterized by a pronounced fluorosolvatochromism in polarity-dependent absorption, emission and fluorescent lifetime experiments. At the same time, a strong viscosity response is observed, especially in polar and protic solvents. Quantum mechanical calculations assisted in interpreting the unusual solvent sensitivity of DPAP in terms of its high flexibility, giving rise to solvent-independent, barrier-free rotations. As a matter of fact, the modus operandi in DPAP contrasts that of traditional FMRs involving twisted intramolecular charge transfer (TICT) states. The influence of this unusual flexible character on excitation and emission energies was studied using computational methods upon considering twisting of the molecule in solvents of different polarity. Furthermore, a detailed characterization of the excited state profile was attained using time resolved spectroscopy techniques. In particular, a contrasting deactivation pattern of the intramolecular charge transfer (ICT) state was observed in low and high polar media. Moreover, in low and medium polar solvents strong emission is accompanied by triplet excited state formation, while in high polar and protic solvents the ICT state is highly stabilized and decays primarily non-radiatively. Notably, a viscosity increase in the latter solvents hampers rotations leading to a strong emission enhancement. This latter behavior, coupled to a remarkable solvatochromic character, makes DPAP a promising probe for biological and environmental sensing and imaging applications. © 2013 The Royal Society of Chemistry.

Unusually high energy barriers for internal conversion in a Ru(bpy) - Cotic, Agustina; Veys, Koen; Escudero, Daniel; Cadranel, Alejandro (Physical Chemistry Chemical Physics)
Internal conversion (IC) coupled to vibrational relaxation (VR) in molecular chromophores is a source of major energy losses in natural and artificial solar-to-chemical energy conversion schemes. The development of anti-Kasha chromophores, where dissipative IC channels are blocked, is a promising strategy to boost energy conversion efficiencies. In this contribution, we demonstrate the presence of an unusually high kinetic barrier for IC in [Ru(tpm)(bpy)(NCS)](+) (RuNCS), where tpm is tris(1-pyrazolyl)methane and bpy is 2,2 '-bipyridine, by means of an arsenal of temperature-dependent spectroscopic methods including nanosecond and femtosecond transient absorption spectroscopies. These studies are complemented with theoretical investigations, that provide a detailed atomistic description of the dissipation process, including the electronic structures of the excited states involved. The observed IC is mainly a hole reconfiguration within the octahedral t(2g) set of the Ru ion, with contributions from a Ru to NCS charge transfer. Thus, in a Marcus picture, inner and outer reorganizations contribute to the observed barrier. The results presented here show that wavefunction symmetry within a molecular chromophore can be exploited to inhibit dissipative IC. Finally, guidelines for the design of anti-Kasha chromophores that prevent dissipation in energy conversion schemes, based on minimum energy conical intersection calculations, are provided.
CRIS-Team WoS Importer:2022-10-21

Unveiling the nature of supramolecular crown ether-C60 interactions - Moreira, Luis; Calbo, Joaquin; Krick Calderon, Rafael; Santos, Jose; Illescas, Beatriz M.; Arago, Juan; Nierengarten, Jean-Francois; Guldi, Dirk Michael; Orti, Enrique; Martin, Nazario (Chemical Science, 2015)
A series of exTTF-(crown ether)2 receptors, designed to host C60, has been prepared. The size of the crown ether and the nature of the heteroatoms have been systematically changed to fine tune the association constants. Electrochemical measurements and transient absorption spectroscopy assisted in corroborating charge transfer in the ground state and in the excited state, leading to the formation of radical ion pairs featuring lifetimes in the range from 12 to 21 ps. To rationalize the nature of the exTTF-(crown ether)2·C60 stabilizing interactions, theoretical calculations have been carried out, suggesting a synergetic interplay of donor-acceptor, π-π, n-π and CH⋯π interactions, which is the basis for the affinity of our novel receptors towards C60.
CRIS-Team Scopus Importer:2023-03-07

Use of alkylated, amphiphilic zinc porphyrins to disperse individualized SWCNTs - Münich, Peter Wilhelm; Wagner, Pawel; Officer, David L.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2018)
A series of zinc porphyrins, namely ZnPa and ZnPb, which exist predominantly as aggregates, are utilized in a top-down preparation of individualized and stabilized single wall carbon nanotubes (SWCNTs). Sizable interactions in the ground state of the corresponding SWCNT/ZnPa and SWCNT/ZnPb electron donor-acceptor systems lead to charge transfer in the excited state. The product includes the simultaneous reduction of the electron-accepting SWCNTs and the oxidation of the electron-donating ZnPa and ZnPb.
CRIS-Team Scopus Importer:2022-04-14
Keywords: porphyrin; single wall carbon nanotube; spectroscopy

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.

Utilization of Sc3N@C80 in long-range charge transfer reactions - Wolfrum, Silke; Pinzon, Julio R.; Molina-Ontoria, Agustin; Gouloumis, Andreas; Martin, Nazario; Echegoyen, Luis; Guldi, Dirk Michael (Chemical Communications, 2011)
Electron accepting Sc N@C promotes long-range charge transfer events evolving from photoexcited metalloporphyrins to afford radical ion pair states with lifetimes in the range of μs. © 2011 The Royal Society of Chemistry.

Varying the Interpentacene Electronic Coupling to Tune Singlet Fission - Papadopoulos, Ilias; Zirzlmeier, Johannes; Hetzer, Constantin; Bae, Youn J.; Krzyaniak, Matthew D.; Wasielewski, Michael R.; Clark, Timothy; Tykwinski, Rik; Guldi, Dirk Michael (Journal of the American Chemical Society, 2019)
We have designed and used four different spacers, denoted A-D, to connect two pentacenes and to probe the impact of intramolecular forces on the modulation of pentacene-pentacene interactions and, in turn, on the key steps in singlet fission (SF), that is, the 1 (S 1 S 0 )-to- 1 (T 1 T 1 ) as well as 1 (T 1 T 1 )-to- 5 (T 1 T 1 ) transitions by means of transient absorption and electron paramagnetic resonance measurements. In terms of the 1 (S 1 S 0 )-to- 1 (T 1 T 1 ) transition, a superexchange mechanism, that is, coupling to a higher-lying CT state to generate a virtual intermediate, enables rapid SF in A-D. Sizeable electronic coupling in A and B opens, on one hand, an additional pathway, that is, the population of a real intermediate, and changes, on the other hand, the mechanism to that of hopping. In turn, A and B feature much higher 1 (T 1 T 1 ) quantum yields than C and D, with a maximum value of 162% for A. In terms of the 1 (T 1 T 1 )-to- 5 (T 1 T 1 ) transition, the sizable electronic coupling in A and B is counterproductive, and C and D give rise to higher 5 (T 1 T 1 )-to-(T 1 + T 1 ) quantum yields than A and B, with a maximum value of 85% for D.
CRIS-Team Scopus Importer:2019-05-02

VIBRATIONS OF HYDROGEN-BONDS IN HYDROGENDISULFITO AND HYDROGENSULFITO COMPLEXES - Breitinger, Dietrich; Breiter, Roman; Raidel, Maria; Bauer, Gerhard; Tomkinson, John (Journal of Molecular Structure, 1992)
Compounds K3[MX2(SO3)2H/D] (M = Pd, Pt; X = Cl, Br) with very short intramolecular hydrogen bonds O..H/D..O (bond lengths R(O....O) < 240 pm) were studied with IR, Raman, and, partly, inelastic neutron scattering spectrometries at ambient and low temperatures. On this experimental basis, the hydrogen-bond vibrations in the unusual sequence delta(OHO) > gamma(OHO) > nu(as)(OHO) are assigned to bands around 1500, 950, and 750 cm-1, respectively; the latter shows a complex structure (IR spectrum) and abnormal isotope shift with nu(H)/nu(D) close to 1. These vibrations are not strictly localized, but couple with modes of the SO3 ligands. Slow rocking modes of the SO3 ligands involving protons occur around 350 and 250 cm-1. In contrast, the vibrations of the medium-strong intermolecular hydrogen bonds in [RU(SO3H/D)2(NH/D3)4] (R(O....O) 268.9 pm) behave normally with nu(as)(OHO) 2950, delta(OHO) 1240, and gamma(OHO) 700 cm-1/100 K, all with isotope shift ratios near 1.35.

Vinyl spacers - Tuning electron transfer through fluorene-based molecular wires - Wielopolski, Mateusz; Santos, José; Illescas, Beatriz M.; Ortiz, Alejandro; Insuasty, Braulio; Bauer, Thilo; Clark, Timothy; Guldi, Dirk Michael; Martín, Nazario (Energy and Environmental Science, 2011)
Rigid and soluble electron donor-acceptor conjugates (3 and 11) that combine π-extended tetrathiafulvalene (exTTF) as an electron donor and C as an electron acceptor have been synthesized using oligo-vinylfluorene (oFV) linkers to connect the electroactive entities. Fluorescence and transient absorption measurements confirm that light-induced excitation induces charge-transfer reactions over distances of 28 in THF. The incorporation of vinylene spacers into oligofluorene molecular wires has been shown both experimentally and theoretically to improve the charge-transfer features significantly to give a β value of 0.075 ± 0.001 . Enhanced π-conjugation caused by higher orbital overlap is responsible for this trend. © 2011 The Royal Society of Chemistry.

Water exchange reactivity and stability of cobalt polyoxometalates under catalytically relevant pH conditions: Insight into water oxidation catalysis - Lieb, Dominik; Zahl, Achim; Wilson, Elizabeth Frances; Streb, Carsten; Nye, Leanne; Meyer, Karsten; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2011)
Water exchange on a molecular, purely inorganic cobalt-based water oxidation catalyst, [Co (H O) (α-P W O ) ] (1), in the catalytically relevant pH region (pH 6-10) is studied using O-NMR spectroscopy and ultrahigh-resolution electrospray ionization mass spectrometry. The results are compared with those of the inactive [Co (H O) Si W O ] (2), which is stable in the same pH region. The results obtained provide mechanistic details of the elementary reaction step related to the water oxidation on homogeneous metal oxide catalysts under catalytically relevant conditions. It is shown that the structural integrity of 1 and 2 is maintained, no deprotonation of the aqua ligands on the Co(II) centers occurs, and the water exchange does not undergo any mechanistic changeover at the catalytic pH conditions. We have demonstrated that the water exchange process is influenced by the cluster environment surrounding the water binding sites and is fast enough to not be rate-limiting for the water oxidation catalysis. © 2011 American Chemical Society.

Water solubility, antioxidant activity and cytochrome C binding of four families of exohedral adducts of C60 and C70 - Witte, Patrick; Beuerle, Florian; Hartnagel, Uwe; Lebovitz, Russel; Savouchkina, Anastasia; Sali, Sevda; Guldi, Dirk Michael; Chronakis, Nikos; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2007)
Over the past decade, surface-modified, water soluble fullerenes have been shown by many different investigators to exhibit strong antioxidant activity against reactive oxygen species (ROS) in vitro and to protect cells and tissues from oxidative injury and cell death in vivo. Nevertheless, progress in developing fullerenes as bona fide drug candidates has been hampered by three development issues: 1) lack of methods for scalable synthesis; 2) inability to produce highly purified, single-species regioisomers compatible with pharmaceutical applications; and 3) inadequate understanding of structure-function relationships with respect to various surface modifications (e.g., anionic versus cationic versus charge-neutral polarity). To address these challenges, we have designed and synthesized more than a dozen novel water soluble fullerenes that can be purified as single isomers and which we believe can be manufactured to scale at reasonable cost. These compounds differ in addition pattern, lipophilicity and number and type of charge and were examined for their water solubility, antioxidant activity against superoxide anions and binding of cytochrome C. Our results indicate that dendritic water soluble fullerene[60] monoadducts exhibit the highest degree of antioxidant activity against superoxide anions in vitro as compared with trismalonate-derived anionic fullerenes as well as cationic fullerenes of similar overall structure. Among the higher adducts, anionic derivatives have a higher antioxidant activity than comparable cationic compounds. To achieve sufficient water solubility without the aid of a surfactant or co-solvent at least three charges on the addends are required. Significantly, anionic in contrast to cationic fullerene adducts bind with high affinity to cytochrome C. © The Royal Society of Chemistry.

Wave-Function Symmetry Control of Electron-Transfer Pathways within a Charge-Transfer Chromophore - Aramburu-Trošelj, Bruno M.; Ramírez-Wierzbicki, Ivana; Scarcasale, Franco; Oviedo, Paola S.; Baraldo, Luis M.; Cadranel, Alejandro (Journal of Physical Chemistry Letters, 2020)
Despite a diverse manifold of excited states available, it is generally accepted that the photoinduced reactivity of charge-transfer chromophores involves only the lowest-energy excited state. Shining a visible-light laser pulse on an aqueous solution of the chromophore-quencher [Ru(tpy)(bpy)(μNC)OsIII(CN)5]- assembly (tpy = 2,2';6,2''-terpyridine and bpy = 2,2'-bipyridine), we prepared a mixture of two charge-transfer excited states with different wave-function symmetry. We were able to follow, in real time, how these states undergo separate electron-transfer reaction pathways. As a consequence, their lifetimes differ in 3 orders of magnitude. Implicit are energy barriers high enough to prevent internal conversion within early excited-state populations, shaping isolated electron-transfer channels in the excited-state potential energy surface. This is relevant not only for supramolecular donor/acceptor chemistry with restricted donor/acceptor relative orientations. These energy barriers provide a means to avoid chemical potential dissipation upon light absorption in any molecular energy conversion scheme, and our observations invite to explore wave-function symmetry-based strategies to engineer these barriers.
CRIS-Team Scopus Importer:2020-10-23

Well-separated water-soluble carbon dots via gradient chromatography - Michaud, Vanessa; Pracht, Jonas; Schilfarth, Fabian; Damm, Cornelia; Platzer, Benedikt; Haines, Philipp; Harreiß, Christina; Guldi, Dirk Michael; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2021)
Carbon dots (CDs) are strongly fluorescent advanced materials that are promising for applications in bio-imaging, sensors or luminescent displays. One of the most-widely used class of CDs is synthesized via an aqueous, bottom-up technique starting from citric acid (CA) and an amino-precursor. Very high fluorescence quantum yields (QY) are reported for the resulting CDs. The as-synthesized raw suspensions, however, are crude mixtures of many components: bare carbon cores, carbon cores functionalized with fluorophores, freely floating molecular fluorophores, and several other by-products. In this study, we synthesized CDs from CA and amino acid cysteine (Cys) hydrothermally and demonstrate a complete separation of all components by means of two step gradient chromatography. In the first step, the separation was carried out on a normal-pressure preparative silica-gel column to get sufficient amounts of material to investigate structure and optical properties of the collected fractions. This preparative gradient elution method enabled us to separate moderately-fluorescent CDs from freely floating molecular fluorophores, polymeric fluorophores and CDs with built-in fluorophores. Here, we evidenced that amorphous CDs co-exist with crystalline CDs in one and the same suspension and showed that the amount of crystalline CDs increases with the synthesis temperature. In the second step, we turned to high performance liquid chromatography (HPLC) to further improve and optimize the efficiency of purification and automate it. Via HPLC, we were able to well-separate of up to six components. Within this work, we laid the foundation for CD purification with the highest possible purity for aqueous, bottom-up synthesized CDs and quantified the true quantum yield of CDs.
Keywords: Graphene quantum dots; Photoluminescence mechanism; Polymer dots; Citric-acid; Nanodots; Fluorescence; Yield; Nitrogen; Light; Reduction

Wet chemistry of graphene - Malig, Jenny; Englert, Jan; Hirsch, Andreas; Guldi, Dirk Michael (Electrochemical Society Interface, 2011)
A variety of sophisticated approaches have been established to obtain stable dispersions of graphene. The use of graphite as starting material for the top-down preparation of graphene offers a cost-efficient and environmentally-friendly alternative to low-dimensional nanocarbon. When in van der Waals contact, graphene sheets are subjected to very efficient π-π stacking interactions, minimizing the surface energy. An alternative approach to stabilize graphene sheets in solution is ultrasonic treatment in organic solvents. The use of amphiphilic π-systems increases the driving force and renders the exfoliation process more dominant in terms of monolayer graphene. Functionalization is certainly a crucial step not only for stabilizing the graphene sheets, but also for harvesting the material's full potential by tuning electron-donor and electron acceptor systems in solution-based processes.

Where's the spin? A DFT study of mixed-valence cyanide-bridged ruthenium polypyridines - Pieslinger, German E.; Cadranel, Alejandro; Baraldo, Luis M. (Journal of the Brazilian Chemical Society, 2020)
This article discusses the use of density functional theory (DFT) calculations in classifying and characterizing bimetallic ruthenium mixed-valence systems in terms of their electronic localization/ delocalization degree. A standard B3LYP/LanL2DZ methodology including integral equation formalism-polarizable continuum model (IEF-PCM) solvent model is evaluated for a set of 16 non-symmetric mixed-valence cyanide-bridged ruthenium polypyridines. This procedure reproduces well the features of the observed electronic and vibrational spectra, with better agreement for the more delocalized systems, and therefore provides an appropriate description of the electronic structures. Computed spin densities support class II or class III Robin-Day assignments and allow to quantify the electronic delocalization degree. The applied methodology yields good results due to the nature of the systems explored, which display a strong electronic coupling promoted by the cyanide-bridge and a lack of strong specific solvation effects. This procedure is not only useful in the study of ground state mixed-valence systems, but also provides a powerful insight into photoinduced mixed-valence excited states of related complexes.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Cyanide-bridge; DFT calculations; Electron transfer; Ruthenium polypyridines

White Light-Emitting Electrochemical Cells Based on Deep-Red Cu(I) Complexes - Fresta, Elisa; Weber, Michael; Fernandez-Cestau, Julio; Costa, Ruben Dario (Advanced Optical Materials, 2019)
The synthesis and characterization, as well as photoluminescent and electrochemical features of a series of ionic copper(I) complexes-, i.e., [Cu((NN)-N-<^>)((PP)-P-<^>)](+), where (NN)-N-<^> is 4,4 '-diethylester-2,2 '-biquinoline (dcbq) and (PP)-P-<^> is bis-triphenylphosphine, bis[2-(diphenylphosphino)phenyl)ether] (POP), or 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene (Xantphos)-are reported along with their application to achieve both deep-red and white light-emitting electrochemical cells (LECs). In short, the first deep-red Cu(I)-based LECs featuring high irradiances (approximate to 100 mu W cm(-2)) and excellent color stability (x/y CIE color coordinates of 0.66/0.32) over days are reported. This is achieved by comparing the electroluminescent behavior of this series of complexes with respect to the irradiance and stability, as well as the impact of introducing supporting electrolytes on the device performance. This is rationalized using spectroscopic and electrochemical studies. Finally, the first white-emitting LEC is manufactured with red-emitting copper(I) complexes, achieving x/y CIE color coordinates of 0.31/0.32 and a high color rendering index of 92.
CRIS-Team WoS Importer:2019-10-04

X-Ray Crystallography of Tetracycline, Doxycycline and Sancycline - Heinemann, Frank Wilhelm; Leypold, Clemens; Roman, Cyprian R.; Schmitt, Matthias O.; Schneider, Siegfried (Journal of Chemical Crystallography, 2013)
Although the packing of the three title compounds in the respective crystals is different, the geometries of the molecular framework are nearly the same as the one shown for the sancycline cation. A comparison of experimentally determined bond lengths with calculated Wiberg-Bond orders provides evidence that only one tautomer is present in the crystal..
Keywords: Molecular and crystal structures; Tetracycline; Doxycycline; Sancycline; Wiberg-bond order

X-ray dose-enhancing impact of functionalized Au-Fe3O4nanoheterodimers on MCF-7 and A549 multicellular tumor spheroids - Klein, Stefanie; Distel, Luitpold; Neuhuber, Winfried (ACS Applied Bio Materials, 2021)
The efficiency of nanoparticle-enhanced radiotherapy was studied by loading MCF-7 and A549 multicellular tumor spheroids (MCTSs) with caffeic acid- and nitrosoniumfunctionalized Au-Fe3O4 nanoheterodimers (Au-Fe3O4 NHDs). Transmission electron microscope images of MCTS crosssectional sections visualized the invasion and distribution of the nitrosonium- and caffeic acid-functionalized Au-Fe3O4 NHDs (NO- and CA-NHDs) in the A549 and MCF-7 MCTSs, whereas the iron content of the MCTSs were quantified using the ferrozine assay. The synergistic impact of intracellular NO- and CA-NHDs and X-ray irradiation on the growth dynamics of the A549 and MCF-7 MCTSs was surveyed by monitoring their temporal evolution under a light microscope over a period of 14 days. The emergence of hypoxia during the spheroid growth was followed by detecting the lactate efflux of MCTSs without and with NO- and CA-NHDs. The performance of the NO- and CA-NHDs as X-ray dose-enhancing agents in the A549 and MCF-7 MCTSs was clarified by performing clonogenic cell survival assays and determining the respective dose-modifying factors for X-ray doses of 0, 2, 4, and 6 Gy. The NO- and CA-NHDs were shown to perform as potent X-ray dose-enhancing agents in A549 and MCF-7 MCTSs. Moreover, the CA-NHDs boosted their radio-sensitizing efficacy by inhibiting the lactate efflux as impairing metabolic reprogramming. A synergistic effect on the MCTS destruction was observed for the combination of both NHDs since the surfactants differ in their antitumor effect.
CRIS-Team Scopus Importer:2021-04-16
Keywords: A549 cells; Au-Fe; MCF-7 cells; Multicellular tumor spheroids; X-ray dose enhancement

ZnO superstructures via oriented aggregation initiated in a block copolymer melt - Klaumünzer, Martin; Distaso, Monica; Hübner, Jakob; Mackovic, Mirza; Spiecker, Erdmann; Kryschi, Carola; Peukert, Wolfgang (Crystengcomm, 2014)
A fast and simple one pot synthesis of ZnO nano- and microparticles initiated and driven by an amino block copolymer O,O′-bis(2-aminopropyl) polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol (Jeffamine®) is reported. The specific building mechanism of ZnO mesocrystals is investigated in detail using electron microscopy and diffraction methods. Mesocrystals with a complex superstructure are formed as a result of a consecutive and oriented multiple stage aggregation process: first a 0D → 1D aggregation process is observed, then a 1D → 3D aggregation process occurs in which secondary particles form cones and multiple cone symmetries. Dots, rods, cones, and multiple cones have been isolated within a time resolved study which clearly supports the growth model. To control the morphology of the product particles, the influence of relevant synthesis parameters including stirring and sonication of the intermediate were investigated. Extensive surface characterization of the resulting mesocrystals is presented using infrared and photoluminescence spectroscopies as well as thermogravimetric analysis. Even after multiple washing steps, the particles exhibit a Jeffamine® coated surface that allows for easy dispersion in both polar and nonpolar solvents. The obtained mesocrystals efficiently scatter in the whole range of visible light. © 2014 The Royal Society of Chemistry.

Zwitterionic clusters with dianion core produced by electrospray ionisation of Brønsted acidic ionic liquids - Li, Jing; Nye, Leanne; Schulz, Peter; Wasserscheid, Peter; Ivanovic-Burmazovic, Ivana; Drewello, Thomas; Wei, Wei (Physical Chemistry Chemical Physics, 2012)
New Brønsted acidic ionic liquids (BAILs) are prepared by treating zwitterions, which are composed of an imidazolium cation and a sulfonate anion, with an alkanedisulfonic acid. Acidification of the zwitterions produces the cation and deprotonation of the alkanedisulfonic acid forms the anion of the new BAILs. Direct laser desorption/ionisation (LDI), matrix-assisted LDI (MALDI) and electrospray ionisation (ESI) are employed to transfer ions into the gas-phase for detection by mass spectrometry and for dissociation studies by tandem mass spectrometry. The components of the BAILs are confirmed by LDI and MALDI by the detection of the respective cation and anion and by ESI by the observation of the cation and the dianion. A prominent feature of ESI is the formation of aggregates (cluster ions). Positively charged cluster ions are formally composed of multiple zwitterions plus one additional proton. In the negative-ion mode the clusters also incorporate the zwitterions which are, however, linked with the alkanedisulfonate dianion. In collision-induced dissociations (CID), the cationic aggregates show the evaporation of zwitterions until the protonated zwitterion is reached. Similarly, the cluster dianions release zwitterions until the free alkane disulfonate dianion is reached. However, the 1:1 adduct of dianion and zwitterion also displays proton transfer and Coulomb explosion into the mono-protonated disulfonic mono-anion and an imidazole-based carbene with sulfonate mono-anion. © 2012 the Owner Societies.

π-Stacking attraction vs. electrostatic repulsion: competing supramolecular interactions in a tpphz-bridged Ru(II)/Au(III) complex. - Sorsche, Dieter; Schaub, Markus; Heinemann, Frank Wilhelm; Habermehl, Johannes; Kuhri, Susanne; Guldi, Dirk Michael; Guthmuller, Julien; Rau, Sven (Dalton Transactions, 2016)
The synthesis and characterization of a mixed metal ruthenium(ii)/gold(iii) complex bridged by tetrapyridophenazine (tpphz) are described. It is isostructural and isoelectronic to the well-known photocatalysts with palladium(ii) or platinum(ii). Concentration dependent (1)H-NMR spectroscopy and XRD studies show that the electrostatic repulsion between the gold(iii) moieties exceeds the attractive π-stacking interaction. Theoretical calculations based on the new structural data confirm an increased positive charge on the bridging ligand as well as significantly altered orbital symmetry as compared to the previously investigated palladium(ii) complex. This is the first example of a tpphz ruthenium(ii) complex where π-stacking is completely inhibited. The detailed investigation of the solid-state structure showed for the first time in bimetallic tpphz bridged complexes no significant torsion within the bridging ligand itself. Although catalytic performance for proton reduction by gold(iii) is naturally not observed, its photochemical decomposition in colloidal gold particles could be shown by TEM and DLS.